Adolescent with painful vesicular otitis and vertigo. - Conversano, Ester; Cozzi, Giorgio; Poropat, Federico; Di Mascio, Alberto; Salis, Simona; Grasso, Domenico Leonardo; Barbi, Egidio (Arch Dis Child Educ Pract Ed, 2019)

Causes of Treatment Failure in Children With Inflammatory Bowel Disease Treated With Infliximab: A Pharmacokinetic Study. - Naviglio, Samuele; Lacorte, Doriana; Lucafò, Marianna; Cifù, Adriana; Favretto, Diego; Cuzzoni, Eva; Silvestri, Tania; Pozzi Mucelli, Martina; Radillo, Oriano; Decorti, Giuliana; Fabris, Martina; Bramuzzo, Matteo; et al. (J Pediatr Gastroenterol Nutr, 2019)
OBJECTIVES: Anti-tumor necrosis factor antibodies have led to a revolution in the treatment of inflammatory bowel diseases (IBD); however, a sizable proportion of patients does not respond to therapy. There is increasing evidence suggesting that treatment failure may be classified as mechanistic (pharmacodynamic), pharmacokinetic, or immune-mediated. Data regarding the contribution of these factors in children with IBD treated with infliximab (IFX) are still incomplete. The aim was to assess the causes of treatment failure in a prospective cohort of pediatric patients treated with IFX. METHODS: This observational study considered 49 pediatric (median age 14.4) IBD patients (34 Crohn disease, 15 ulcerative colitis) treated with IFX. Serum samples were collected at 6, 14, 22 and 54 weeks, before IFX infusions. IFX and anti-infliximab antibodies (AIA) were measured using enzyme linked immunosorbent assays. Disease activity was determined by Pediatric Crohn's Disease Activity Index or Pediatric Ulcerative Colitis Activity Index. RESULTS: Clinical remission, defined as a clinical score <10, was obtained by 76.3% of patients at week 14 and by 73.9% at week 54. Median trough IFX concentration was higher at all time points in patients achieving sustained clinical remission. IFX levels during maintenance correlated also with C-reactive protein, albumin, and fecal calprotectin. After multivariate analysis, IFX concentration at week 14 >3.11 μg/mL emerged as the strongest predictor of sustained clinical remission. AIA concentrations were correlated inversely with IFX concentrations and directly with adverse reactions. CONCLUSIONS: Most cases of therapeutic failure were associated with low serum drug levels. IFX trough levels at the end of induction are associated with sustained long-term response.

Cervico-vaginal secretion cytokine profile: A non-invasive approach to study the endometrial receptivity in IVF cycles. - Zanotta, Nunzia; Monasta, Lorenzo; Skerk, Kristina; Luppi, Stefania; Martinelli, Monica; Ricci, Giuseppe; Comar, Manola (Am J Reprod Immunol, 2019)
PROBLEM: Cytokines have a significant role in the process of embryo implantation, trophoblast growth, and differentiation by modulating the immune and endocrine system. The aim of this study was to investigate the profile of a large set of cytokines in the cervico-vaginal washing of women undergoing IVF, to explore the association of these proteins with a good receptive endometrium. METHOD OF STUDY: A cohort of 155 women scheduled for IVF cycle was recruited. All patients were asymptomatic for genitourinary infections and had been screened for chlamydia, mycoplasma, and other bacterial infections. All IVF subjects were treated according to standard clinical and laboratory protocols. A panel of 48 immune factors was analyzed on cervico-vaginal washing, using magnetic bead-based multiplex immunoassays (Bio-Plex, BIO-RAD Laboratories, Milano, Italy). RESULTS: A total of 99 patients reached embryo transfer, of which 31 had a clinical pregnancy. A pattern of four pro-inflammatory immune molecules, IL-12p40, IFN-a, MIF, and MCP3 (P < 0.001), was found significantly up-regulated in the cervico-vaginal fluid of women with clinical pregnancy. A significantly increased expression of IL-9, Gro , and SDF-1 (P < 0.05) was observed in the presence of endometriosis, while high levels of IL-13 and L-15 were associated with ovulatory infertility factor (P < 0.05). CONCLUSION: In this pilot study, we demonstrated that the expression of specific cytokines in the cervico-vaginal washing on the day of oocyte retrieval might have a positive correlation with the potential clinical pregnancy. Therefore, cervico-vaginal secretion cytokine profiling might be a new, non-invasive approach to study the endometrial receptivity in IVF management.

Changing Epidemiology of Liver Involvement in Children With Celiac Disease. - Benelli, Elisa; Naviglio, Samuele; De Leo, Luigina; Stera, Giacomo; Giangreco, Manuela; Ronfani, Luca; Villanacci, Vincenzo; Martelossi, Stefano; Ventura, Alessandro; Not, Tarcisio (J Pediatr Gastroenterol Nutr, 2019)
OBJECTIVES: Available data indicate that liver involvement is present in a significant proportion of children with celiac disease (CD) at the diagnosis (elevated transaminases 15%-57%, autoimmune liver disease 1%-2%). We sought to evaluate prevalence, clinical course, and risk factors for liver involvement in a large cohort of children with CD. METHODS: Children (age 0-18 years) diagnosed with CD from March 2010 to April 2016 were enrolled. Liver involvement was considered to be present when alanine transaminase (ALT) levels were >40 U/L (hypertransaminasemia [HTS]). Patients with HTS were re-evaluated after at least 12 months of a gluten-free diet. RESULTS: CD was diagnosed in 806 patients during the study period; of these, ALT levels were available for 700 patients (86.9%), and were elevated in 27 (3.9%, HTS group); median ALT and aspartate transaminase levels in the HTS group were 57 U/L (interquartile range 49-80 U/L) and 67 U/L (interquartile range 53-85 U/L), respectively. Younger age, malabsorption symptoms, and low hemoglobin or ferritin were significantly more common in the HTS group at univariate analysis. At multivariate analysis, only age ≤4.27 years correlated with risk of liver involvement (odds ratio 3.73; 95% confidence interval: 1.61-8.66). When retested on a gluten-free diet, all but 3 patients normalized ALT levels; of these, 1 was diagnosed with sclerosing cholangitis. CONCLUSIONS: Liver involvement in celiac children is now less frequent than previously reported, possibly due to changing CD epidemiology. Younger age is the only risk factor. Associated autoimmune liver disease is rare.

An evaluation of the Movement ABC-2 Test for use in Italy: A comparison of data from Italy and the UK. - Zoia, Stefania; Biancotto, Marina; Guicciardi, Marco; Lecis, Romina; Lucidi, Fabio; Pelamatti, Giovanna M; Carrozzi, Marco; Skabar, Aldo; Sugden, David A; Barnett, Anna L; Henderson, Sheila E (Res Dev Disabil, 2019)
BACKGROUND: The standardized test within the Movement Assessment Battery for Children-2nd edition (MABC-2) is used worldwide to assess motor problems in children. Ideally, any country using a test developed in another country should produce national norms to ensure that it functions effectively in the new context. AIM: The first objective of this study was to explore the differences in motor performance between Italian and British children. The second was to examine the structural validity of the test for the Italian sample. METHOD: A total of 718 Italian (IT) and 765 British (UK) children, aged 3-10 years, were individually tested on the age-appropriate items of the MABC-2 Test. RESULTS: Developmental trends emerged on every task and differences between IT and UK children were obtained on 11 of 27 task comparisons. Interactions between age and country indicated that differences were not consistently in favor of one culture. Confirmatory factor analysis generally supported the proposed structure of the MABC-2 Test. CONCLUSION: Although the differences between the IT and the UK children were relatively few, those that did emerge emphasize the need for population specific norms and suggest that cultural diversity in motor experiences should be considered when evaluating motor abilities in children.

First urinary tract infections in children: the role of the risk factors proposed by the Italian recommendations. - Alberici, I; La Manna, A; Pennesi, M; Starc, M; Scozzola, F; Nicolini, G; Toffolo, A; Marra, G; Chimenz, R; Sica, F; Maringhini, S; Monasta, L; et al. (Acta Paediatr, 2019)
AIM: In 2009, the Italian society for paediatric nephrology suggested the need for cystography, following a first febrile urinary tract infection (UTI), only in children at high risk for dilating vesicoureteral reflux or in the event of a second infection. The aim of this study was to evaluate the adequacy of the risk factors proposed by the Italian guidelines. METHODS: Children aged 2-36 months, managed by 10 Italian hospitals between 2009 and 2013, with a first febrile UTI were retrospectively evaluated. RESULTS: Four hundred and fourteen children were included: 51% female, mean age eight months. Escherichia coli was responsible of 84% UTIs. 269 children (65%) presented at least one risk factor, thus were further investigated: 44% had a reflux. The presence of a pathogen other than E. coli significantly predicted high-grade reflux, both in the univariate (Odd Ratio 2.52, 95% Confidence Interval 1.32-4.81, p < 0.005) and multivariate analysis (OR 2.74, 95% CI: 1.39-5.41, p: 0.003). 26/145 children (18%) with no risk factors experienced a second UTI, which prompted the execution of cystography, showing a dilating reflux in 11. CONCLUSION: Among the risk factors proposed by the Italian guidelines, only the presence of a pathogen other than E. coli significantly predicted reflux. Cystography can be postponed in children with no risk factors.

Four-miRNA Signature to Identify Asbestos-Related Lung Malignancies. - Santarelli, Lory; Gaetani, Simona; Monaco, Federica; Bracci, Massimo; Valentino, Matteo; Amati, Monica; Rubini, Corrado; Sabbatini, Armando; Pasquini, Ernesto; Zanotta, Nunzia; Comar, Manola; Neuzil, Jiri; et al. (Cancer Epidemiol Biomarkers Prev, 2019)
BACKGROUND: Altered miRNA expression is an early event upon exposure to occupational/environmental carcinogens; thus, identification of a novel asbestos-related profile of miRNAs able to distinguish asbestos-induced cancer from cancer with different etiology can be useful for diagnosis. We therefore performed a study to identify miRNAs associated with asbestos-induced malignancies. METHODS: Four groups of patients were included in the study, including patients with asbestos-related (NSCLC) and asbestos-unrelated non-small cell lung cancer (NSCLC) or with malignant pleural mesothelioma (MPM), and disease-free subjects (CTRL). The selected miRNAs were evaluated in asbestos-exposed population. RESULTS: Four serum miRNAs, that is miR-126, miR-205, miR-222, and miR-520g, were found to be implicated in asbestos-related malignant diseases. Notably, increased expression of miR-126 and miR-222 were found in asbestos-exposed subjects, and both miRNAs are involved in major pathways linked to cancer development. Epigenetic changes and cancer-stroma cross-talk could induce repression of miR-126 to facilitate tumor formation, angiogenesis, and invasion. CONCLUSIONS: This study indicates that miRNAs are potentially involved in asbestos-related malignancies, and their expression outlines mechanism(s) whereby miRNAs may be involved in an asbestos-induced pathogenesis. IMPACT: The discovery of a miRNA panel for asbestos-related malignancies would impact on occupational compensation and may be utilized for screening asbestos-exposed populations.

Gadolinium tissue deposition in the periodontal ligament of mice with reduced renal function exposed to Gd-based contrast agents. - Delfino, Riccarda; Biasotto, Matteo; Candido, Riccardo; Altissimo, Matteo; Stebel, Marco; Salomè, Murielle; van Elteren, Johannes T; Vogel Mikuš, Katarina; Zennaro, Cristina; Šala, Martin; Addobbati, Riccardo; Tromba, Giuliana; et al. (Toxicol Lett, 2019)
Gadolinium deposition in tissue is linked to nephrogenic systemic fibrosis (NSF): a rare disorder occurring in patients with severe chronic kidney disease and associated with administration of Gd-based contrast agents (GBCAs) for Magnetic Resonance Imaging (MRI). It is suggested that the GBCAs prolonged permanence in blood in these patients may result in a Gd precipitation in peripheral or central organs, where it initiates a fibrotic process. In this study we investigated new sites of retention/precipitation of Gd in a mouse model of renal disease (5/6 nephrectomy) receiving two doses (closely after each other) of a linear GBCA. Two commercial GBCAs (Omniscan® and Magnevist®) were administered at doses slightly higher than those used in clinical practice (0.7 mmol/kg body weight, each). The animals were sacrificed one month after the last administration and the explanted organs (kidney, liver, femur, dorsal skin, teeth) were analysed by X-ray fluorescence (XRF) at two synchrotron facilities. The XRF analysis with a millimetre-sized beam at the SYRMEP beamline (Elettra, Italy) produced no detectable levels of Gd in the examined tissues, with the notable exception of the incisors of the nephrectomised mice. The XRF analyses at sub-micron resolution performed at ID21 (ESRF, France) allowed to clearly localize Gd in the periodontal ligaments of teeth both from Omniscan® and Magnevist® treated nephrectomised mice. The latter results were further confirmed by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). The study prompts that prolonged permanence of GBCAs in blood may result in Gd retention in this particular muscular tissue, opening possibilities for diagnostic applications at this level when investigating Gd-related toxicities.
Keywords: Animals; Contrast Media; Disease Models, Animal; Dose-Response Relationship, Drug; Female; Gadolinium; Gadolinium DTPA; Magnetic Resonance Imaging; Mice; Nephrogenic Fibrosing Dermopathy; Periodontal Ligament; Renal Insufficiency; Tissue Distribution

Idiopathic neutropenia of infancy: Data from the Italian Neutropenia Registry. - Farruggia, Piero; Fioredda, Francesca; Puccio, Giuseppe; Onofrillo, Daniela; Russo, Giovanna; Barone, Angelica; Bonanomi, Sonia; Boscarol, Gianluca; Finocchi, Andrea; Ghilardi, Roberta; Giordano, Paola; Ladogana, Saverio; et al. (Am J Hematol, 2019)
Autoimmune neutropenia of infancy (AIN) is characterized by low risk of severe infection, tendency to spontaneously resolve and typically onset at ≤4-5 years of age; it is due to auto-antibodies whose detection is often difficult. In case of negativity of 4 antineutrophils autoantibody tests, after having excluded ethnic, postinfection, drug induced, or congenital neutropenia, according to the Italian guidelines the patients will be defined as affected by "idiopathic neutropenia" (IN). We describe the characteristics of 85 IN patients enrolled in the Italian neutropenia registry: they were compared with 336 children affected by AIN. The 2 groups were clinically very similar and the main differences were detection age (later in IN), length of disease (longer in IN) and, among recovered patients, age of spontaneous recovery: the median age at resolution was 2.13 years in AINs and 3.03 years in INs (P = .00002). At bivariate analysis among AIN patients earlier detection age (P = .00013), male sex (P = .000748), absence of leucopenia (P = .0045), and absence of monocytosis (P = .0419) were significantly associated with earlier recovery; in the IN group only detection age (P = .013) and absence of monocytosis (P = .0333) were significant. At multivariate analysis detection age and absence of monocytosis were independently significant (P = 6.7e-05 and 4.4e-03, respectively) in the AIN group, whereas in the IN group only detection age stayed significant (P = .013).

Loss-of-function mutations in cause a new form of inherited thrombocytopenia. - Marconi, Caterina; Di Buduo, Christian A; LeVine, Kellie; Barozzi, Serena; Faleschini, Michela; Bozzi, Valeria; Palombo, Flavia; McKinstry, Spencer; Lassandro, Giuseppe; Giordano, Paola; Noris, Patrizia; Balduini, Carlo L; et al. (Blood, 2019)
Inherited thrombocytopenias (ITs) are a heterogeneous group of disorders characterized by low platelet count that may result in bleeding tendency. Despite progress being made in defining the genetic causes of ITs, nearly 50% of patients with familial thrombocytopenia are affected with forms of unknown origin. Here, through exome sequencing of 2 siblings with autosomal-recessive thrombocytopenia, we identified biallelic loss-of-function variants in This gene encodes for a receptor-like PTP, PTPRJ (or CD148), which is expressed abundantly in platelets and megakaryocytes. Consistent with the predicted effects of the variants, both probands have an almost complete loss of PTPRJ at the messenger RNA and protein levels. To investigate the pathogenic role of PTPRJ deficiency in hematopoiesis in vivo, we carried out CRISPR/Cas9-mediated ablation of (the ortholog of human ) in zebrafish, which induced a significantly decreased number of CD41 thrombocytes in vivo. Moreover, megakaryocytes of our patients showed impaired maturation and profound defects in SDF1-driven migration and formation of proplatelets in vitro. Silencing of in a human megakaryocytic cell line reproduced the functional defects observed in patients' megakaryocytes. The disorder caused by mutations presented as a nonsyndromic thrombocytopenia characterized by spontaneous bleeding, small-sized platelets, and impaired platelet responses to the GPVI agonists collagen and convulxin. These platelet functional defects could be attributed to reduced activation of Src family kinases. Taken together, our data identify a new form of IT and highlight a hitherto unknown fundamental role for PTPRJ in platelet biogenesis.

Management of endometrial, ovarian and cervical cancer in the elderly: current approach to a challenging condition. - Vitale, Salvatore Giovanni; Capriglione, Stella; Zito, Gabriella; Lopez, Salvatore; Gulino, Ferdinando Antonio; Di Guardo, Federica; Vitagliano, Amerigo; Noventa, Marco; La Rosa, Valentina Lucia; Sapia, Fabrizio; Valenti, Gaetano; Rapisarda, Agnese Maria Chiara; et al. (Arch Gynecol Obstet, 2019)
PURPOSE: Gynaecological cancer management in older people represents a current challenge. Therefore, in the present paper, we aimed to gather all the evidence reported in the literature concerning gynecological cancers in the elderly, illustrating the state of art and the future perspectives. METHODS: We searched MEDLINE (PubMed), EMBASE, Cochrane Central Register of Controlled Trials, IBECS, BIOSIS, Web of Science, SCOPUS and Grey literature (Google Scholar; British Library) from January 1952 to May 2017, using the terms "ovarian cancer", "endometrial cancer", "cervical cancer", "gynecological cancers" combined with 'elderly', 'cancer', 'clinical trial' and 'geriatric assessment'. RESULTS: The search identified 81 citations, of which 65 were potentially relevant after initial evaluation and met the criteria for inclusion and were analyzed. We divided all included studies into three different issue: "Endometrial cancer", "Ovarian cancer" and "Cervical cancer". CONCLUSIONS: The present literature review shows that, in spite of the higher burden of comorbidities, elderly patients can also benefit from standard treatment to manage their gynecological cancers. It is important to overcome the common habit of undertreating the elderly patients because they are more fragile and with a lower life expectancy than their younger counterpart. Further trials with elderly women are warranted.

Menstruation-related disseminated intravascular coagulation in an adenomyosis patient: case report and review of the literature. - Cernogoraz, Alice; Schiraldi, Luigi; Bonazza, Deborah; Ricci, Giuseppe (Gynecol Endocrinol, 2019)
Disseminated intravascular coagulation (DIC) is a high mortality coagulopathy that leads to simultaneous thrombotic and bleeding problems. It occurs as a complication in different disease as malignancies, obstetrical catastrophes, bacterial sepsis and traumas. We report on an extremely rare case of acute DIC in a patient with misdiagnosed adenomyosis and massive methrorragia which led to acute kidney failure. The patient was successfully treated with hysterectomy and blood product transfusions; however, a slight reduction of renal function persisted. We were able to confirm the cause-consequence link between adenomyosis and consumptive DIC since we saw the thrombi in the adenomyotic uterus from early hysterectomy specimen. Moreover, this is the first case, for the best of our knowledge, in which systemic consequences persist in an adenomyosis patient who developed a DIC. Early diagnose and treatment of acute DIC is essential for patient's survival and to prevent severe complications: adenomyosis should be kept in mind as a possible cause of DIC when a patient shows up with massive bleeding.

MYH9-Related Thrombocytopenia: Four Novel Variants Affecting the Tail Domain of the Non-Muscle Myosin Heavy Chain IIA Associated with a Mild Clinical Evolution of the Disorder. - Zaninetti, Carlo; De Rocco, Daniela; Giangregorio, Tania; Bozzi, Valeria; Demeter, Judit; Leoni, Pietro; Noris, Patrizia; Ryhänen, Samppa; Barozzi, Serena; Pecci, Alessandro; Savoia, Anna (Hamostaseologie, 2019)
-related disease (-RD) is an autosomal-dominant thrombocytopenia caused by mutations in the gene for non-muscle myosin heavy chain IIA (NMMHC-IIA). Patients present congenital macrothrombocytopenia and inclusions of NMMHC-IIA in leukocytes, and have a variable risk of developing kidney damage, sensorineural deafness, presenile cataracts and/or liver enzymes abnormalities. The spectrum of mutations found in -RD patients is limited and the incidence and severity of the non-congenital features are predicted by the causative variant. In particular, different alterations of the C-terminal tail domain of NMMHC-IIA associate with remarkably different disease evolution. We report four novel mutations affecting the tail domain of NMMHC-IIA and responsible for -RD in four families. Two variants cause amino acid substitutions in the coiled-coil region of NMMHC-IIA, while the other two are a splicing variant and a single nucleotide deletion both resulting in frameshift alterations of the short non-helical tailpiece. Characterization of phenotypes of affected individuals shows that all of these novel variants are associated with a mild clinical evolution of the disease.

Prevalence and phenotype of the c.1529C>T SPG7 variant in adult-onset cerebellar ataxia in Italy. - Mancini, C; Giorgio, E; Rubegni, A; Pradotto, L; Bagnoli, S; Rubino, E; Prontera, P; Cavalieri, S; Di Gregorio, E; Ferrero, M; Pozzi, E; Riberi, E; et al. (Eur J Neurol, 2019)
BACKGROUND AND PURPOSE: Hereditary ataxias are heterogeneous groups of neurodegenerative disorders, characterized by cerebellar syndromes associated with dysarthria, oculomotor and corticospinal signs, neuropathy and cognitive impairment. Recent reports have suggested mutations in the SPG7 gene, causing the most common form of autosomal recessive spastic paraplegia (MIM#607259), as a main cause of ataxias. The majority of described patients were homozygotes or compound heterozygotes for the c.1529C>T (p.Ala510Val) change. We screened a cohort of 895 Italian patients with ataxia for p.Ala510Val in order to define the prevalence and genotype-phenotype correlation of this variant. METHODS: We set up a rapid assay for c.1529C>T using restriction enzyme analysis after polymerase chain reaction amplification. We confirmed the diagnosis with Sanger sequencing. RESULTS: We identified eight homozygotes and 13 compound heterozygotes, including two novel variants affecting splicing. Mutated patients showed a pure cerebellar ataxia at onset, evolving in mild spastic ataxia (alternatively) associated with dysarthria (~80% of patients), urinary urgency (~30%) and pyramidal signs (~70%). Comparing homozygotes and compound heterozygotes, we noted a difference in age at onset and Scale for the Assessment and Rating of Ataxia score between the two groups, supporting an earlier and more severe phenotype in compound heterozygotes versus homozygotes. CONCLUSIONS: The SPG7 c.1529C>T (p.Ala510Val) mutants accounted for 2.3% of cerebellar ataxia cases in Italy, suggesting that this variant should be considered as a priority test in the presence of late-onset pure ataxia. Moreover, the heterozygous/homozygous genotype appeared to predict the onset of clinical manifestation and disease progression.

When Long-Lasting Food Selectivity Leads to an Unusual Genetic Diagnosis: A Case Report. - Da Lozzo, Prisca; Magnolato, Andrea; Del Rizzo, Irene; Sirchia, Fabio; Bruno, Irene; Barbi, Egidio (J Adolesc Health, 2019)
Hereditary fructose intolerance is an autosomal recessive disorder of fructose metabolism caused by catalytic deficiency of aldolase B enzyme [1]. The disease is typically expressed when fructose- and sucrose-containing foods are first introduced in the diet; acute manifestations include nausea, vomiting, abdominal distress, and symptomatic hypoglycemia [1,2]. Chronic fructose ingestion eventually leads to poor feeding, growth retardation and gradual liver and/or renal failure [3,4]. Some patients may remain undiagnosed until adulthood because of a self-protective avoidance of sweet tasting food that prevents the development of acute toxicity from fructose containing food; however, these subjects may suffer intermittent symptoms throughout life, leading to potentially serious misdiagnosis [4]. We report the case of a patient with unrecognized hereditary fructose intolerance in which chronic gastrointestinal complaints, low body weight, and unexplained food avoidance were addressed as manifestations of an eating disorder during adolescence.

Activation of hepatic stem cells compartment during hepatocarcinogenesis in a HBsAg HBV-transgenic mouse model. - Anfuso, Beatrice; El-Khobar, Korri E; Ie, Susan I; Avellini, Claudio; Radillo, Oriano; Raseni, Alan; Tiribelli, Claudio; Sukowati, Caecilia H C (Sci Rep, 2018)
Chronic infection of Hepatitis B Virus (HBV) is one of the highest risk factors of hepatocellular carcinoma (HCC). The accumulation of HBV surface antigen (HBsAg) into hepatocytes induces inflammation and oxidative stress, impairing their replicative ability and allowing the activation of the hepatic stem cells (SC) compartment. This study aimed to understand the involvement of SC during hepatocarcinogenesis in HBsAg-related liver damage, from early injury until HCC. HBsAg-transgenic (TG) and wild type (WT) mouse were followed at several stages of the liver damage: inflammation, early hepatocytes damage, dysplasia, and HCC. Serum transaminases, liver histology, and diagnostic data were collected. The expressions of SC and cancer stem cells (CSC) markers was analyzed by RT-qPCR, immunohistochemistry and Western blot. Starting from 3 months, TG animals showed a progressive liver damage characterized by transaminases increase. The up-regulations of SCs markers Cd34 and Sca-1 started from the beginning of the inflammatory stage while progressive increase of Krt19 and Sox9 and CSCs markers Epcam and Cd133 from early hepatic injury. The expressions of Cd133, Cd34, and Afp were significantly higher in HCC compared to paired non-HCC tissue, in contrast to Epcam and Krt19. Western blot and IHC confirmed the positivity of Cd34 and Cd133 in small cells subpopulation.

ACTN1 mutations lead to a benign form of platelet macrocytosis not always associated with thrombocytopenia. - Faleschini, Michela; Melazzini, Federica; Marconi, Caterina; Giangregorio, Tania; Pippucci, Tommaso; Cigalini, Elena; Pecci, Alessandro; Bottega, Roberta; Ramenghi, Ugo; Siitonen, Timo; Seri, Marco; Pastore, Annalisa; et al. (Br J Haematol, 2018)
The inherited thrombocytopenias (IT) are a heterogeneous group of diseases resulting from mutations in more than 30 different genes. Among them, ACTN1-related thrombocytopenia (ACTN1-RT; Online Mendelian Inheritance in Man: 615193) is one of the most recently identified forms. It has been described as a mild autosomal dominant macrothrombocytopenia caused by mutations in ACTN1, a gene encoding for one of the two non-muscle isoforms of α-actinin. We recently identified seven new unrelated families with ACTN1-RT caused by different mutations. Two of them are novel missense variants (p.Trp128Cys and p.Pro233Leu), whose pathogenic role has been confirmed by in vitro studies. Together with the 10 families we have previously described, our cohort of ACTN1-RT now consists of 49 individuals carrying ACTN1 mutations. This is the largest case series ever collected and enabled a critical evaluation of the clinical aspects of the disease. We concluded that ACTN1-RT is the fourth most frequent form of IT worldwide and it is characterized by platelet macrocytosis in all affected subjects and mild thrombocytopenia in less than 80% of cases. The risk of bleeding, either spontaneous or upon haemostatic challenge, is negligible and there are no other associated defects, either congenital or acquired. Therefore, ACTN1-RT is a benign form of IT, whose diagnosis provides affected individuals and their families with a good prognosis.

Acute small bowel obstruction in a child with a strict raw vegan diet. - Amoroso, Stefano; Scarpa, Maria-Grazia; Poropat, Federico; Giorgi, Rita; Murru, Flora Maria; Barbi, Egidio (Arch Dis Child, 2018)

Adenomyomatosis of the Gallbladder as a Cause of Recurrent Abdominal Pain. - Agrusti, Anna; Gregori, Massimo; Salviato, Tiziana; Codrich, Daniela; Barbi, Egidio (J Pediatr, 2018)
Keywords: Abdominal Pain; Adenomyoma; Adolescent; Biopsy, Needle; Cholecystectomy; Diagnosis, Differential; Female; Gallbladder; Gallbladder Neoplasms; Humans; Immunohistochemistry; Recurrence; Risk Assessment; Severity of Illness Index; Ultrasonography, Doppler

Anti-transglutaminase 6 Antibody Development in Children With Celiac Disease Correlates With Duration of Gluten Exposure. - De Leo, Luigina; Aeschlimann, Daniel; Hadjivassiliou, Marios; Aeschlimann, Pascale; Salce, Nicola; Vatta, Serena; Ziberna, Fabiana; Cozzi, Giorgio; Martelossi, Stefano; Ventura, Alessandro; Not, Tarcisio (J Pediatr Gastroenterol Nutr, 2018)
OBJECTIVES: Antibodies against transglutaminase 6 (anti-TG6) have been implicated in neurological manifestations in adult patients with genetic gluten intolerance, and it is unclear whether autoimmunity to TG6 develops following prolonged gluten exposure. We measured the anti-TG6 in children with celiac disease (CD) at the diagnosis time to establish a correlation between these autoantibodies and the duration of gluten exposure. We investigated a correlation between anti-TG6 and the presence of neurological disorders. METHODS: Anti-TG6 (IgA/IgG) were measured by ELISA in sera of children with biopsy-proven CD and of children experiencing gastrointestinal disorders. CD patients positive for anti-TG6 were retested after 2 years of gluten-free diet (GFD). RESULTS: We analyzed the sera of 274 CD children and of 121 controls. Anti-TG6 were detected in 68/274 (25%) CD patients and in 19/121 (16%) controls, with significant difference between the 2 groups (P = 0.04). None of the CD patients and of the controls testing positive for anti-TG6 were experiencing neurological disorders. Eleven of 18 (61%) CD patients with other autoimmune diseases were positive for anti-TG6. In CD patients, a significant correlation between the gluten exposure before the CD diagnosis and anti-TG6 concentration was found (P = 0.006 for IgA; P < 0.0001 for IgG). After GFD anti-TG6 concentrations were significantly reduced (P < 0.001). No significant correlation was observed between anti-TG6 and anti-TG2 serum concentrations. CONCLUSIONS: Anti-TG6 are more prevalent in children with untreated CD in the absence of overt neurological disorders. The synthesis of the anti-TG6 is related to a longer exposure to gluten before the CD diagnosis, and the autoimmunity against TG6 is gluten dependent and disappeared during GFD.

Are aortic coarctation and rheumatoid arthritis different models of aortic stiffness? Data from an echocardiographic study. - Faganello, Giorgio; Cioffi, Giovanni; Rossini, Maurizio; Ognibeni, Federica; Giollo, Alessandro; Fisicaro, Maurizio; Russo, Giulia; Di Nora, Concetta; Doimo, Sara; Tarantini, Luigi; Mazzone, Carmine; Cherubini, Antonella; et al. (Cardiovasc Ultrasound, 2018)
BACKGROUND: Patients who underwent a successful repair of the aortic coarctation (CoA) show high risk for cardiovascular (CV) events. Mechanical and structural abnormalities in the ascending aorta (Ao) might have a role in the prognosis of CoA patients. We analyzed the elastic properties of Ao measured as aortic stiffness index (AoSI) in CoA patients in the long-term period and we compared AoSI with a cohort of 38 patients with rheumatoid arthritis (RA) and 38 non-RA matched controls. METHODS: Data from 19 CoA patients were analyzed 28 ± 13 years after surgery. Abnormally high AoSI was diagnosed if AoSI > 6.07% (95th percentile of the AoSI detected in our reference healthy population). AoSI was assessed at the level of the aortic root by two-dimensional guided M-mode evaluation. RESULTS: CoA patients showed more than two-fold higher AoSI compared to RA and controls (9.8 ± 12.6 vs 4.8 ± 2.5% and 3.1 ± 2.0%, respectively; all p < 0.05 and in 5 of 19 patients with CoA (26%) AoSI was exceptionally high. The 5 patients with abnormally high AoSI were older with higher BP, LV mass and prevalence of LV diastolic dysfunction. Multiple linear regression analysis revealed that AoSI was independently related to the presence of LV hypertrophy and higher LV relative wall thickness. CONCLUSIONS: CoA patients have higher AoSI levels than RA patients and non-RA matched controls. AoSI levels are abnormally high in a small sub-group of CoA patients who show a very high-risk clinical profile for adverse CV events.
Keywords: Aorta; Aortic Coarctation; Arthritis, Rheumatoid; Humans; Prognosis; Vascular Stiffness

Cell-autonomous and cell non-autonomous downregulation of tumor suppressor DAB2IP by microRNA-149-3p promotes aggressiveness of cancer cells. - Bellazzo, Arianna; Di Minin, Giulio; Valentino, Elena; Sicari, Daria; Torre, Denis; Marchionni, Luigi; Serpi, Federica; Stadler, Michael B; Taverna, Daniela; Zuccolotto, Gaia; Montagner, Isabella Monia; Rosato, Antonio; et al. (Cell Death Differ, 2018)
The tumor suppressor DAB2IP contributes to modulate the network of information established between cancer cells and tumor microenvironment. Epigenetic and post-transcriptional inactivation of this protein is commonly observed in multiple human malignancies, and can potentially favor progression of tumors driven by a variety of genetic mutations. Performing a high-throughput screening of a large collection of human microRNA mimics, we identified miR-149-3p as a negative post-transcriptional modulator of DAB2IP. By efficiently downregulating DAB2IP, this miRNA enhances cancer cell motility and invasiveness, facilitating activation of NF-kB signaling and promoting expression of pro-inflammatory and pro-angiogenic factors. In addition, we found that miR-149-3p secreted by prostate cancer cells induces DAB2IP downregulation in recipient vascular endothelial cells, stimulating their proliferation and motility, thus potentially remodeling the tumor microenvironment. Finally, we found that inhibition of endogenous miR-149-3p restores DAB2IP activity and efficiently reduces tumor growth and dissemination of malignant cells. These observations suggest that miR-149-3p can promote cancer progression via coordinated inhibition of DAB2IP in tumor cells and in stromal cells.

Cerebrospinal Fluid Cytokine Expression Profile in Multiple Sclerosis and Chronic Inflammatory Demyelinating Polyneuropathy. - Bonin, Serena; Zanotta, Nunzia; Sartori, Arianna; Bratina, Alessio; Manganotti, Paolo; Trevisan, Giusto; Comar, Manola (Immunol Invest, 2018)
BACKGROUND: Cerebrospinal fluid (CSF) analysis in patients with particular neurologic disorders is a powerful tool to evaluate specific central nervous system inflammatory markers for diagnostic needs, because CSF represents the specific immune micro-environment to the central nervous system. METHODS: CSF samples from 49 patients with multiple sclerosis (MS), chronic inflammatory demyelinating polyneuropathy (CIDP), and non-inflammatory neurologic disorders (NIND) as controls were submitted to protein expression profiles of 47 inflammatory biomarkers by multiplex Luminex bead assay to investigate possible differences in the inflammatory process for MS and CIDP. RESULTS: Our results showed differences in CSF cytokine levels in MS and CIDP; in particular, IL12 (p40) was significantly highly expressed in MS in comparison with CIDP and NIND, while SDF-1α and SCGF-β were significantly highly expressed in CIDP cohort when compared to MS and NIND. IL-9, IL-13, and IL-17 had higher expression levels in NIND if compared with the other groups. CONCLUSIONS: Our study showed that, despite some common pathogenic mechanisms, central and peripheral nervous system demyelinating diseases, such as MS and CIDP, differ in some specific inflammatory soluble proteins in CSF, underlining differences in the immune response involved in those autoimmune diseases.
Keywords: Adult; Aged; Biomarkers; Central Nervous System; Diagnosis, Differential; Female; Hematopoietic Cell Growth Factors; Humans; Interleukin-12; Lectins, C-Type; Male; Middle Aged; Multiple Sclerosis; Peripheral Nervous System; Polyradiculoneuropathy, Chronic Inflammatory Demyelinating; Proteins

Cervical-length measurement in mid-gestation to predict spontaneous preterm birth in asymptomatic triplet pregnancy. - Fichera, A; Pagani, G; Stagnati, V; Cascella, S; Faiola, S; Gaini, C; Lanna, M; Pasquini, L; Raffaelli, R; Stampalija, T; Tommasini, A; Prefumo, F (Ultrasound Obstet Gynecol, 2018)
OBJECTIVE: To assess the predictive value of sonographic cervical-length (CL) measurement in mid-gestation for spontaneous preterm birth (PTB) in asymptomatic triplet pregnancy. METHODS: This was a retrospective study of asymptomatic triplet pregnancies followed at five Italian tertiary referral centers, between 2002 and 2015. CL was measured transvaginally between 18 and 24 weeks' gestation. Pregnancies with medically indicated PTB were excluded. Demographic and pregnancy characteristics of pregnancies complicated by PTB were analyzed and the distributions of CL measurements in these patients were calculated. Logistic regression analysis was performed to assess the association between CL and PTB, adjusted for confounders. Performance of CL measurement in prediction of PTB < 28, < 30 and < 32 weeks of gestation was assessed. RESULTS: A total of 120 triplet pregnancies were included in the final analysis. Median CL was 35 (interquartile range (IQR), 29-40) mm measured at a median gestational age of 20 + 2 (IQR, 20 + 0 to 23 + 4) weeks. Overall, 23 (19.2%), 17 (14.2%) and eight (6.7%) patients had a CL < 25, < 20 and < 15 mm, respectively. Spontaneous PTB < 32 weeks occurred in 41 (34.2%) cases, < 30 weeks in 23 (19.2%) and < 28 weeks in 12 (10%) cases. CL < 15 mm was significantly more frequent in the group of patients who delivered < 28 (P = 0.03) and < 30 (P = 0.01) weeks' gestation, compared with those who delivered after 28 and after 30 weeks, respectively, while CL < 20 mm was more common in triplet pregnancies with delivery < 32 weeks compared with those delivered ≥ 32 weeks (P = 0.03). Logistic regression analysis was possible only for PTB < 32 weeks due to the small number of cases that delivered < 30 and < 28 weeks. After adjustment for confounders, CL was not significantly associated with PTB < 32 weeks (adjusted odds ratio, 0.97; 95% CI, 0.94-1.01). CL measurement had an area under the receiver-operating characteristics curve of 0.41 (95% CI, 0.20-0.62), 0.41 (95% CI, 0.26-0.56) and 0.42 (95% CI, 0.31-0.54) for the prediction of spontaneous PTB < 28, < 30 and < 32 weeks, respectively. CONCLUSION: CL assessed in mid-gestation is a poor predictor of PTB < 28, < 30 and < 32 weeks' gestation in asymptomatic triplet pregnancy. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cervical Length Measurement; Female; Gestational Age; Humans; Infant, Newborn; Logistic Models; Predictive Value of Tests; Pregnancy; Pregnancy, Triplet; Premature Birth; Retrospective Studies

Characterization of multi-locus imprinting disturbances and underlying genetic defects in patients with chromosome 11p15.5 related imprinting disorders. - Fontana, L; Bedeschi, M F; Maitz, S; Cereda, A; Faré, C; Motta, S; Seresini, A; D'Ursi, P; Orro, A; Pecile, V; Calvello, M; Selicorni, A; et al. (Epigenetics, 2018)
The identification of multilocus imprinting disturbances (MLID) appears fundamental to uncover molecular pathways underlying imprinting disorders (IDs) and to complete clinical diagnosis of patients. However, MLID genetic associated mechanisms remain largely unknown. To characterize MLID in Beckwith-Wiedemann (BWS) and Silver-Russell (SRS) syndromes, we profiled by MassARRAY the methylation of 12 imprinted differentially methylated regions (iDMRs) in 21 BWS and 7 SRS patients with chromosome 11p15.5 epimutations. MLID was identified in 50% of BWS and 29% of SRS patients as a maternal hypomethylation syndrome. By next-generation sequencing, we searched for putative MLID-causative mutations in genes involved in methylation establishment/maintenance and found two novel missense mutations possibly causative of MLID: one in NLRP2, affecting ADP binding and protein activity, and one in ZFP42, likely leading to loss of DNA binding specificity. Both variants were paternally inherited. In silico protein modelling allowed to define the functional effect of these mutations. We found that MLID is very frequent in BWS/SRS. In addition, since MLID-BWS patients in our cohort show a peculiar pattern of BWS-associated clinical signs, MLID test could be important for a comprehensive clinical assessment. Finally, we highlighted the possible involvement of ZFP42 variants in MLID development and confirmed NLRP2 as causative locus in BWS-MLID.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Beckwith-Wiedemann Syndrome; Child; Child, Preschool; Chromosomes, Human, Pair 15; DNA Methylation; Female; Genomic Imprinting; Humans; Infant; Kruppel-Like Transcription Factors; Male; Mutation, Missense; Silver-Russell Syndrome; Young Adult

Cooking influence in tolerance acquisition in egg-induced acute food protein enterocolitis syndrome. - Miceli Sopo, S; Romano, A; Bersani, G; Fantacci, C; Badina, L; Longo, G; Monti, G; Viola, S; Tripodi, S; Barilaro, G; Iacono, I D; Caffarelli, C; et al. (Allergol Immunopathol (Madr), 2018)
BACKGROUND: Few studies on the age of resolution of Food Protein Induced Enterocolitis Syndrome (FPIES) induced by solid foods are available. In particular, for FPIES induced by egg, the mean age of tolerance acquisition reported in the literature ranges from 42 to 63 months. OBJECTIVE: We have assessed whether the age of tolerance acquisition in acute egg FPIES varies depending on whether the egg is cooked or raw. METHODS: We conducted a retrospective and multicentric study of children with diagnosis of acute egg FPIES seen in 10 Italian allergy units between July 2003 and October 2017. The collected data regarded sex, presence of other allergic diseases, age of onset of symptoms, kind and severity of symptoms, cooking technique of the ingested egg, outcome of the allergy test, age of tolerance acquisition. RESULTS: Sixty-one children with acute egg FPIES were enrolled, 34 (56%) males and 27 (44%) females. Tolerance to cooked egg has been demonstrated by 47/61 (77%) children at a mean age of 30.2 months. For 32 of them, tolerance to raw egg has been demonstrated at a mean age of 43.9 months. No episodes of severe adverse reaction after baked egg ingestion have been recorded. CONCLUSIONS: It is possible to perform an OFC with baked egg, to verify the possible acquisition of tolerance, at about 30 months of life in children with acute egg FPIES.

Cx26 partial loss causes accelerated presbycusis by redox imbalance and dysregulation of Nfr2 pathway. - Fetoni, Anna Rita; Zorzi, Veronica; Paciello, Fabiola; Ziraldo, Gaia; Peres, Chiara; Raspa, Marcello; Scavizzi, Ferdinando; Salvatore, Anna Maria; Crispino, Giulia; Tognola, Gabriella; Gentile, Giulia; Spampinato, Antonio Gianmaria; et al. (Redox Biol, 2018)
Mutations in GJB2, the gene that encodes connexin 26 (Cx26), are the most common cause of sensorineural hearing impairment. The truncating variant 35delG, which determines a complete loss of Cx26 protein function, is the prevalent GJB2 mutation in several populations. Here, we generated and analyzed Gjb2 mice as a model of heterozygous human carriers of 35delG. Compared to control mice, auditory brainstem responses (ABRs) and distortion product otoacoustic emissions (DPOAEs) worsened over time more rapidly in Gjb2 mice, indicating they were affected by accelerated age-related hearing loss (ARHL), or presbycusis. We linked causally the auditory phenotype of Gjb2 mice to apoptosis and oxidative damage in the cochlear duct, reduced release of glutathione from connexin hemichannels, decreased nutrient delivery to the sensory epithelium via cochlear gap junctions and deregulated expression of genes that are under transcriptional control of the nuclear factor erythroid 2-related factor 2 (Nrf2), a pivotal regulator of tolerance to redox stress. Moreover, a statistically significant genome-wide association with two genes (PRKCE and TGFB1) related to the Nrf2 pathway (p-value < 4 × 10) was detected in a very large cohort of 4091 individuals, originating from Europe, Caucasus and Central Asia, with hearing phenotype (including 1076 presbycusis patients and 1290 healthy matched controls). We conclude that (i) elements of the Nrf2 pathway are essential for hearing maintenance and (ii) their dysfunction may play an important role in the etiopathogenesis of human presbycusis.
Keywords: Animals; Apoptosis; Connexin 26; Female; Gene Deletion; Male; Mice; Mice, Inbred C57BL; NF-E2-Related Factor 2; Oxidation-Reduction; Presbycusis; Signal Transduction

Cytokine profiles of women with vulvodynia: Identification of a panel of pro-inflammatory molecular targets. - Zanotta, Nunzia; Campisciano, Giuseppina; Scrimin, Federica; Blendi, Ura; Marcuzzi, Annalisa; Vincenti, Ezio; Crovella, Sergio; Comar, Manola (Eur J Obstet Gynecol Reprod Biol, 2018)
OBJECTIVE: The vulvar pain syndrome (VPS) is a multifactorial disease severely influencing the lifestyle of affected women. Among possible etiological factors, local injury, peripheral and/or central sensitization of the nervous system, and a chronic inflammatory status have been positively associated with the development of VPS. The identification of a constitutive altered local inflammatory profile in VPS women may represent an important point in the characterization of patients' phenotype as a useful marker influencing the vulvar micro-environment. The aim of this study was to investigative the possible role of the local cytokines production in women with VPS in comparison to healthy women. STUDY DESIGN: In this study were collected vaginal swabs from 57 healthy women (HC) who never suffered from VPS and from 30 patients diagnosed with vulvodynia (VPS) by at least 3 years and currently symptomatic. All patients included in this study showed the absence of Sexually Transmitted (STD) diseases and Reproductive Tract Infection. Real-time PCR was performed to assess the genomic sequences of ST pathogens. The Luminex Bio-Plex platform was used for the analysis of a panel of 48 immune factors. RESULTS: Eleven molecules, specifically involved in the pro-inflammatory pathway were significantly modulated in VPS patients in comparison to healthy women, suggesting a persistent inflammatory process. CONCLUSIONS: Therefore, these inflammatory factors could be possible biological markers involved in this disease. Nevertheless, other studies are needed to consider this specific immune profile as a valid marker of the vulvodynia.
Keywords: Adult; Aged; Cytokines; Female; Humans; Inflammation; Middle Aged; Vaginal Smears; Vulva; Vulvodynia; Women's Health

De novo unbalanced translocations have a complex history/aetiology. - Bonaglia, Maria Clara; Kurtas, Nehir Edibe; Errichiello, Edoardo; Bertuzzo, Sara; Beri, Silvana; Mehrjouy, Mana M; Provenzano, Aldesia; Vergani, Debora; Pecile, Vanna; Novara, Francesca; Reho, Paolo; Di Giacomo, Marilena Carmela; et al. (Hum Genet, 2018)
We investigated 52 cases of de novo unbalanced translocations, consisting in a terminally deleted or inverted-duplicated deleted (inv-dup del) 46th chromosome to which the distal portion of another chromosome or its opposite end was transposed. Array CGH, whole-genome sequencing, qPCR, FISH, and trio genotyping were applied. A biparental origin of the deletion and duplication was detected in 6 cases, whereas in 46, both imbalances have the same parental origin. Moreover, the duplicated region was of maternal origin in more than half of the cases, with 25% of them showing two maternal and one paternal haplotype. In all these cases, maternal age was increased. These findings indicate that the primary driver for the occurrence of the de novo unbalanced translocations is a maternal meiotic non-disjunction, followed by partial trisomy rescue of the supernumerary chromosome present in the trisomic zygote. In contrast, asymmetric breakage of a dicentric chromosome, originated either at the meiosis or postzygotically, in which the two resulting chromosomes, one being deleted and the other one inv-dup del, are repaired by telomere capture, appears at the basis of all inv-dup del translocations. Notably, this mechanism also fits with the origin of some simple translocations in which the duplicated region was of paternal origin. In all cases, the signature at the translocation junctions was that of non-homologous end joining (NHEJ) rather than non-allelic homologous recombination (NAHR). Our data imply that there is no risk of recurrence in the following pregnancies for any of the de novo unbalanced translocations we discuss here.
Keywords: DNA End-Joining Repair; Female; Humans; Male; Meiosis; Recombinational DNA Repair; Translocation, Genetic

DEFB1 polymorphisms and HIV-1 mother-to-child transmission in Zambian population. - Zupin, Luisa; Polesello, Vania; Segat, Ludovica; Kamada, Anselmo Jiro; Kuhn, Louise; Crovella, Sergio (J Matern Fetal Neonatal Med, 2018)
INTRODUCTION: Human Beta Defensin-1 (hBD-1) is a component of the innate immune system, the first line of defence against pathogens, already reported as involved in the susceptibility to HIV-1 infection and HIV-1 mother-to-child transmission (MTCT) in different populations. We investigated the role of DEFB1 gene (encoding for hBD-1) functional polymorphisms in the susceptibility to HIV-1 MTCT in a population from Zambia. METHODS: Four selected polymorphisms within DEFB1 gene, three at the 5' untranslated region (UTR), namely -52G > A (rs1799946), -44C > G (rs1800972) and -20G > A (rs11362) and one in the 3'UTR, c.*87A > G (rs1800972), were genotyped in 101 HIV-1 positive mothers (26 transmitters -27% and 75 not transmitters -73%) and 331 infants born to HIV-1 infected mothers (85 HIV-1 positive -26% and 246 exposed but not infected -74%). RESULTS: DEFB1 c.*87-A allele was more frequent among HIV- children with respect to HIV+ (with intrauterine MTCT). Concerning DEFB1 haplotypes, GCGA haplotype resulted more represented in HIV- than HIV+ infants and DEFB1 ACGG haplotype presented increased frequency in HIV- children respect to HIV+ (with intra-partum MTCT) (p = .02, p = .002 and p = .006, respectively). CONCLUSIONS: DEFB1 polymorphisms were significantly associated with decreased risk of HIV-1 infection acquisition in the studied Zambian population suggesting that they may play a role in HIV-1 MTCT.

Does the Application of Heat Gel Pack After Eutectic Mixture of Local Anesthetic Cream Improve Venipuncture or Intravenous Cannulation Success Rate in Children? A Randomized Control Trial. - Schreiber, Silvana; Cozzi, Giorgio; Patti, Giuseppa; Taddio, Andrea; Montico, Marcella; Pierobon, Chiara; Barbi, Egidio (Pediatr Emerg Care, 2018)
OBJECTIVE: Needle-related procedures are the most common sources of pain for children in the hospital setting. The most used topical anesthetic, eutectic mixture of local anesthetic (EMLA) cream, may cause transient vasoconstriction. It has been postulated that this vasoconstriction may decrease vein visualization. The application of heat gel pack after removal of EMLA cream in the site of venipuncture counteracts the vasoconstriction, improving vein visualization. We assessed using a prospective randomized controlled trial whether the application of heat gel pack increases the needle procedure success rate. The primary study outcome was procedural success rate at the first attempt. METHODS: The study enrolled 400 children, 200 of whom applied heat gel pack after removing EMLA (treatment group) and 200 did not (control group). Procedural success rate at the first attempt, vein perception before procedure, procedural pain, and adverse events were recorded in both groups. RESULTS: Eighty-eight percent of the procedures were successful at the first attempt in the treatment group and 89% in the control group (P = 0.876). Vein perception was not significantly different in the 2 groups (P = 0.081). Pain score after the procedure was similar in the 2 groups. CONCLUSIONS: This study shows that the application of heat gel pack after removal of EMLA cream does not improve venipuncture or intravenous cannulation success rate.
Keywords: Anesthetics, Local; Child; Child, Preschool; Female; Hot Temperature; Humans; Lidocaine; Lidocaine, Prilocaine Drug Combination; Male; Pain; Pain Management; Phlebotomy; Prilocaine; Prospective Studies

Dysregulated chaperones associated with cell proliferation and negative apoptosis regulation in the uterine leiomyoma. - Ura, Blendi; Scrimin, Federica; Arrigoni, Giorgio; Aloisio, Michelangelo; Monasta, Lorenzo; Ricci, Giuseppe (Oncol Lett, 2018)
Uterine leiomyomas are benign smooth muscle cell tumors that originate from the myometrium. In this study we focus on dysregulated chaperones associated with cell proliferation and apoptosis. Paired tissue samples of 15 leiomyomas and adjacent myometria were obtained and analyzed by two-dimensional gel electrophoresis (2-DE). Mass spectrometry was used for protein identification and western blotting for 2-DE data validation. The values of 6 chaperones were found to be significantly different in the leiomyoma when compared with the myometrium. A total of 4 proteins were upregulated in the leiomyoma and 2 proteins were downregulated. Calreticulin and 78 kDa glucose-regulated protein were further validated by western blotting because the first is considered a marker of cell proliferation, while the second protects against apoptotic cell death. In addition, we also validated the two downregulated proteins heat shock protein β-1 and heat shock 70 kDa protein 1A. Our study shows the existence of a dysregulation of chaperone proteins associated with leiomyoma development. Functional studies are needed to ascertain the role of these chaperones in the leiomyoma. This may be crucial for the further development of specific inhibitors against the activity of these proteins in order to block the growth of the leiomyoma.

Efficacy and Safety of Adalimumab in Pediatric Ulcerative Colitis: A Real-life Experience from the SIGENP-IBD Registry. - Aloi, Marina; Bramuzzo, Matteo; Arrigo, Serena; Romano, Claudio; D'Arcangelo, Giulia; Lacorte, Doriana; Gatti, Simona; Illiceto, Maria T; Zucconi, Francesca; Dilillo, Dario; Zuin, Giovanna; Knafelz, Daniela; et al. (J Pediatr Gastroenterol Nutr, 2018)
OBJECTIVES: The aim of this study was to evaluate the effectiveness and safety of adalimumab (ADA) in children with ulcerative colitis (UC) previously treated with infliximab (IFX). METHODS: Retrospective study including children with UC from a national registry who received ADA therapy. The primary endpoint was the rate of corticosteroid-free remission at week 52. Secondary outcomes were the rate of sustained clinical remission, primary nonresponse, and loss of response at weeks 12, 30, and 52 and rate of mucosal healing and side effects at week 52. RESULTS: Thirty-two children received ADA (median age 10 ± 4 years). Median disease duration before ADA therapy was 27 months. All patients received previous IFX (43% intolerant, 50% nonresponders [37.5% primary, 42.5% secondary nonresponders], 6.7% positive anti-IFX antibodies). Fifty-two weeks after ADA initiation, 13 patients (41%) were in corticosteroid-free remission. Mucosal healing occurred in 9 patients (28%) at 52 weeks. The cumulative probability of a clinical relapse-free course was 69%, 59%, and 53% at 12, 30, and 52 weeks, respectively. Ten patients (31%) had a primary failure and 5 (15%) a loss of response to ADA. No significant differences in efficacy were reported between not-responders and intolerant to IFX (P = 1.0). Overall, 19 patient (59%) maintained ADA during 52-week follow-up. Seven patients (22%) experienced an adverse event, no serious side effects were observed and none resulted in ADA discontinuation. CONCLUSIONS: Based on our data, ADA seems to be effective in children with UC, allowing to recover a significant percentage of patients intolerant or not-responding to IFX. The safety profile was good.

Endocrine and psychological aspects of sexual dysfunction in Klinefelter patients. - Ferlin, A; Selice, R; Angelini, S; Di Grazia, M; Caretta, N; Cavalieri, F; Di Mambro, A; Foresta, C (Andrology, 2018)
Klinefelter syndrome is a frequent cause of hypogonadism, but despite hundreds of publications on different aspects of Klinefelter syndrome, only a few studies dealt with sexual dysfunction. In particular, testosterone is critical for various aspects of sexual response, but its role on sexuality in Klinefelter syndrome patients is debatable and no studies have evaluated the efficacy of testosterone treatment on sexual dysfunction in these subjects. Furthermore, the impact of psychological and relational aspects on sexual function of Klinefelter syndrome subjects is poorly defined. In this study, we aimed to determine the presence and type of sexual dysfunctions in Klinefelter syndrome subjects; to correlate them with testosterone levels and psychosexological and relational domains; and to evaluate the effects of testosterone therapy. We studied 62 non-mosaic naïve Klinefelter syndrome patients and 60 age-matched controls by means of medical history, psychosexological history, 15-item International Index of Erectile Function questionnaire, endocrine assessment, and dynamic penile color Doppler ultrasound. Twenty-five hypogonadal Klinefelter syndrome patients were studied after 6 months of testosterone replacement therapy. Klinefelter syndrome subjects have reduced 15-item International Index of Erectile Function scores regarding sexual desire, intercourse satisfaction, and overall satisfaction with respect to controls, and these aspects were significantly associated with testosterone levels. Klinefelter syndrome subjects had also higher prevalence of erectile dysfunction, but no relation with testosterone levels was evident. A high prevalence of a range of psychological disturbances was present in Klinefelter syndrome subjects with erectile dysfunction with respect to those without erectile dysfunction. No statistical difference in the prevalence of premature and delayed ejaculation was observed between Klinefelter syndrome and control subjects. Testosterone replacement therapy improved sexual desire, intercourse satisfaction, and overall satisfaction scores, but had no effect on erectile function. Penile color Doppler ultrasound was normal in all subjects. This study shows that sexual dysfunction in Klinefelter syndrome is multifactorial and related only in part to hypogonadism and largely to psychological disturbances. Evaluation and therapy of sexual dysfunction should include a combined andrological and psychosexological approach.

Exome-chip meta-analysis identifies novel loci associated with cardiac conduction, including ADAMTS6. - Prins, Bram P; Mead, Timothy J; Brody, Jennifer A; Sveinbjornsson, Gardar; Ntalla, Ioanna; Bihlmeyer, Nathan A; van den Berg, Marten; Bork-Jensen, Jette; Cappellani, Stefania; Van Duijvenboden, Stefan; Klena, Nikolai T; Gabriel, George C; et al. (Genome Biol, 2018)
BACKGROUND: Genome-wide association studies conducted on QRS duration, an electrocardiographic measurement associated with heart failure and sudden cardiac death, have led to novel biological insights into cardiac function. However, the variants identified fall predominantly in non-coding regions and their underlying mechanisms remain unclear. RESULTS: Here, we identify putative functional coding variation associated with changes in the QRS interval duration by combining Illumina HumanExome BeadChip genotype data from 77,898 participants of European ancestry and 7695 of African descent in our discovery cohort, followed by replication in 111,874 individuals of European ancestry from the UK Biobank and deCODE cohorts. We identify ten novel loci, seven within coding regions, including ADAMTS6, significantly associated with QRS duration in gene-based analyses. ADAMTS6 encodes a secreted metalloprotease of currently unknown function. In vitro validation analysis shows that the QRS-associated variants lead to impaired ADAMTS6 secretion and loss-of function analysis in mice demonstrates a previously unappreciated role for ADAMTS6 in connexin 43 gap junction expression, which is essential for myocardial conduction. CONCLUSIONS: Our approach identifies novel coding and non-coding variants underlying ventricular depolarization and provides a possible mechanism for the ADAMTS6-associated conduction changes.
Keywords: ADAMTS Proteins; African Continental Ancestry Group; Animals; Connexin 43; Electrocardiography; European Continental Ancestry Group; Exome; Female; Gene Expression; Gene Expression Profiling; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Humans; Male; Mice; Middle Aged; Myocardium; Open Reading Frames; Polymorphism, Single Nucleotide; Whole Exome Sequencing

Fecal Calprotectin to Detect Inflammatory Bowel Disease in Juvenile Idiopathic Arthritis. - Ferrara, Giovanna; Pastore, Serena; Sancin, Lara; Torelli, Lucio; Radillo, Oriano; Bramuzzo, Matteo; Bibalo, Chiara; Tommasini, Alberto; Ventura, Alessandro; Taddio, Andrea (J Rheumatol, 2018)
OBJECTIVE: This study aimed to test fecal calprotectin (FC) as a screening tool to identify inflammatory bowel disease (IBD) among patients with juvenile idiopathic arthritis (JIA). METHODS: FC level < 100 g/kg was considered normal. Patients with 2 consecutive FC dosage ≥ 100 g/kg underwent endoscopic evaluation. RESULTS: There were 113 patients with JIA enrolled. FC was raised in 7 patients out of 113. All patients had IBD. In 3/7 patients, high FC levels were the only sign consistent with IBD. CONCLUSION: FC is a useful, economical, and noninvasive diagnostic tool to identify JIA patients with underlying IBD.

Flares After Withdrawal of Biologic Therapies in Juvenile Idiopathic Arthritis: Clinical and Laboratory Correlates of Remission Duration. - Simonini, Gabriele; Ferrara, Giovanna; Pontikaki, Irene; Scoccimarro, Erika; Giani, Teresa; Taddio, Andrea; Meroni, Pier Luigi; Cimaz, Rolando (Arthritis Care Res (Hoboken), 2018)
OBJECTIVE: To assess the time in remission after discontinuing biologic therapy in patients with juvenile idiopathic arthritis (JIA). METHODS: We enrolled 135 patients followed in 3 tertiary-care centers. The primary outcome was to assess, once remission was achieved, the time in remission up to the first flare after discontinuing treatment. Mann-Whitney U test, Wilcoxon's signed rank test for paired samples, chi-square tests, and Fisher's exact test were used to compare data. Pearson's and Spearman's correlation tests were used to determine correlation coefficients for different variables. To identify predictors of outcome, Cox regression model and Kaplan-Meier curves were constructed, each one at the mean of entered covariates. RESULTS: The majority of enrolled patients flared after stopping treatment with biologics (102 of 135, 75.6%) after a median followup time in remission off therapy of 6 months (range 3-109 months). A higher probability of maintaining remission after discontinuing treatment was present in systemic-onset disease compared to the rest of the JIA patients (Mantel-Cox χ = 8.31, P < 0.004). In analysis limited to children with JIA with polyarticular and oligoarticular disease, patients who received biologics >2 years after achieving remission had a higher probability of maintaining such remission off therapy (mean ± SD 18.64 ± 3.3 months versus 11.51 ± 2.7 months [P < 0.009]; Mantel-Cox χ = 9.06, P < 0.002). No other clinical variable was significantly associated with a long-lasting remission. CONCLUSION: Children with oligoarticular and polyarticular JIA who stop treatment before 2 years from remission have a higher chance of relapsing after biologic withdrawal.

Fractional CO laser for genitourinary syndrome of menopause in breast cancer survivors: clinical, immunological, and microbiological aspects. - Becorpi, Angelamaria; Campisciano, Giuseppina; Zanotta, Nunzia; Tredici, Zelinda; Guaschino, Secondo; Petraglia, Felice; Pieralli, Annalisa; Sisti, Giovanni; De Seta, Francesco; Comar, Manola (Lasers Med Sci, 2018)
The composition of vaginal microbiome in menopause and cancer survivor women changes dramatically leading to genitourinary syndrome of menopause (GSM) in up to 70% of patients. Recent reports suggest that laser therapy may be valuable as a not hormonal therapeutic modality. The aim of the present study was to evaluate the effects of fractional CO laser treatment on the vaginal secretory pathway of a large panel of immune mediators, usually implicated in tissue remodeling and inflammation, and on microbiome composition in postmenopausal breast cancer survivors. The Ion Torrent PGM platform and the Luminex Bio-Plex platform were used for microbiome and immune factor analysis. The significant reduction of clinical symptoms and the non-significant changes in vaginal microbiome support the efficacy and safety of laser treatment. Moreover, the high remodeling status in vaginal epithelium is demonstrated by the significant changes in inflammatory and modulatory cytokine patterns. Laser therapy can be used for the treatment of GSM symptoms and does not show any adverse effects. However, further studies will be needed to clarify its long-term efficacy and other effects.
Keywords: Breast Neoplasms; Cancer Survivors; Cytokines; Dyspareunia; Female; Humans; Lasers, Gas; Menopause; Microbiota; Middle Aged; Prospective Studies; Syndrome; Vagina; Vaginal Diseases

Gene discovery and polygenic prediction from a genome-wide association study of educational attainment in 1.1 million individuals. - Lee, James J; Wedow, Robbee; Okbay, Aysu; Kong, Edward; Maghzian, Omeed; Zacher, Meghan; Nguyen-Viet, Tuan Anh; Bowers, Peter; Sidorenko, Julia; Karlsson Linnér, Richard; Fontana, Mark Alan; Kundu, Tushar; et al. (Nat Genet, 2018)
Here we conducted a large-scale genetic association analysis of educational attainment in a sample of approximately 1.1 million individuals and identify 1,271 independent genome-wide-significant SNPs. For the SNPs taken together, we found evidence of heterogeneous effects across environments. The SNPs implicate genes involved in brain-development processes and neuron-to-neuron communication. In a separate analysis of the X chromosome, we identify 10 independent genome-wide-significant SNPs and estimate a SNP heritability of around 0.3% in both men and women, consistent with partial dosage compensation. A joint (multi-phenotype) analysis of educational attainment and three related cognitive phenotypes generates polygenic scores that explain 11-13% of the variance in educational attainment and 7-10% of the variance in cognitive performance. This prediction accuracy substantially increases the utility of polygenic scores as tools in research.

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

A genetic variant of NLRP1 gene is associated with asbestos body burden in patients with malignant pleural mesothelioma. - Crovella, S; Moura, R R; Cappellani, S; Celsi, F; Trevisan, E; Schneider, M; Brollo, A; Nicastro, E M; Vita, F; Finotto, L; Zabucchi, G; Borelli, V (J Toxicol Environ Health A, 2018)
The presence of asbestos bodies (ABs) in lung parenchyma is considered a histopathologic hallmark of past exposure to asbestos fibers, of which there was a population of longer fibers. The mechanisms underlying AB formation are complex, involving inflammatory responses and iron (Fe) metabolism. Thus, the responsiveness to AB formation is variable, with some individuals appearing to be poor AB formers. The aim of this study was to disclose the possible role of genetic variants of genes encoding inflammasome and iron metabolism proteins in the ability to form ABs in a population of 81 individuals from North East Italy, who died after having developed malignant pleural mesothelioma (MPM). This study included 86 genetic variants distributed in 10 genes involved in Fe metabolism and 7 genetic variants in two genes encoding for inflammasome molecules. Genotypes/haplotypes were compared according to the number of lung ABs. Data showed that the NLRP1 rs12150220 missense variant (H155L) was significantly correlated with numbers of ABs in MPM patients. Specifically, a low number of ABs was detected in individuals carrying the NLRP1 rs12150220 A/T genotype. Our findings suggest that the NLRP1 inflammasome might contribute in the development of lung ABs. It is postulated that the NLRP1 missense variant may be considered as one of the possible host genetic factors contributing to individual variability in coating efficiency, which needs to be taken when assessing occupational exposure to asbestos.

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide association meta-analysis highlights light-induced signaling as a driver for refractive error. - Tedja, Milly S; Wojciechowski, Robert; Hysi, Pirro G; Eriksson, Nicholas; Furlotte, Nicholas A; Verhoeven, Virginie J M; Iglesias, Adriana I; Meester-Smoor, Magda A; Tompson, Stuart W; Fan, Qiao; Khawaja, Anthony P; Cheng, Ching-Yu; et al. (Nat Genet, 2018)
Refractive errors, including myopia, are the most frequent eye disorders worldwide and an increasingly common cause of blindness. This genome-wide association meta-analysis in 160,420 participants and replication in 95,505 participants increased the number of established independent signals from 37 to 161 and showed high genetic correlation between Europeans and Asians (>0.78). Expression experiments and comprehensive in silico analyses identified retinal cell physiology and light processing as prominent mechanisms, and also identified functional contributions to refractive-error development in all cell types of the neurosensory retina, retinal pigment epithelium, vascular endothelium and extracellular matrix. Newly identified genes implicate novel mechanisms such as rod-and-cone bipolar synaptic neurotransmission, anterior-segment morphology and angiogenesis. Thirty-one loci resided in or near regions transcribing small RNAs, thus suggesting a role for post-transcriptional regulation. Our results support the notion that refractive errors are caused by a light-dependent retina-to-sclera signaling cascade and delineate potential pathobiological molecular drivers.

Genome-wide association meta-analysis of individuals of European ancestry identifies new loci explaining a substantial fraction of hair color variation and heritability. - Hysi, Pirro G; Valdes, Ana M; Liu, Fan; Furlotte, Nicholas A; Evans, David M; Bataille, Veronique; Visconti, Alessia; Hemani, Gibran; McMahon, George; Ring, Susan M; Smith, George Davey; Duffy, David L; et al. (Nat Genet, 2018)
Hair color is one of the most recognizable visual traits in European populations and is under strong genetic control. Here we report the results of a genome-wide association study meta-analysis of almost 300,000 participants of European descent. We identified 123 autosomal and one X-chromosome loci significantly associated with hair color; all but 13 are novel. Collectively, single-nucleotide polymorphisms associated with hair color within these loci explain 34.6% of red hair, 24.8% of blond hair, and 26.1% of black hair heritability in the study populations. These results confirm the polygenic nature of complex phenotypes and improve our understanding of melanin pigment metabolism in humans.

A genome-wide association study of corneal astigmatism: The CREAM Consortium. - Shah, Rupal L; Li, Qing; Zhao, Wanting; Tedja, Milly S; Tideman, J Willem L; Khawaja, Anthony P; Fan, Qiao; Yazar, Seyhan; Williams, Katie M; Verhoeven, Virginie J M; Xie, Jing; Wang, Ya Xing; et al. (Mol Vis, 2018)
Purpose: To identify genes and genetic markers associated with corneal astigmatism. Methods: A meta-analysis of genome-wide association studies (GWASs) of corneal astigmatism undertaken for 14 European ancestry (n=22,250) and 8 Asian ancestry (n=9,120) cohorts was performed by the Consortium for Refractive Error and Myopia. Cases were defined as having >0.75 diopters of corneal astigmatism. Subsequent gene-based and gene-set analyses of the meta-analyzed results of European ancestry cohorts were performed using VEGAS2 and MAGMA software. Additionally, estimates of single nucleotide polymorphism (SNP)-based heritability for corneal and refractive astigmatism and the spherical equivalent were calculated for Europeans using LD score regression. Results: The meta-analysis of all cohorts identified a genome-wide significant locus near the platelet-derived growth factor receptor alpha () gene: top SNP: rs7673984, odds ratio=1.12 (95% CI:1.08-1.16), p=5.55×10. No other genome-wide significant loci were identified in the combined analysis or European/Asian ancestry-specific analyses. Gene-based analysis identified three novel candidate genes for corneal astigmatism in Europeans-claudin-7 (), acid phosphatase 2, lysosomal (), and TNF alpha-induced protein 8 like 3 (). Conclusions: In addition to replicating a previously identified genome-wide significant locus for corneal astigmatism near the gene, gene-based analysis identified three novel candidate genes, , , and , that warrant further investigation to understand their role in the pathogenesis of corneal astigmatism. The much lower number of genetic variants and genes demonstrating an association with corneal astigmatism compared to published spherical equivalent GWAS analyses suggest a greater influence of rare genetic variants, non-additive genetic effects, or environmental factors in the development of astigmatism.
Keywords: Acid Phosphatase; Asian Continental Ancestry Group; Astigmatism; Claudins; Cohort Studies; Cornea; Corneal Diseases; European Continental Ancestry Group; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Odds Ratio; Polymorphism, Single Nucleotide; Receptor, Platelet-Derived Growth Factor alpha; Software

Girl With Chest Pain. - Scarpa, Maria-Grazia; Rabach, Ingrid; Canuto, Arianna; Sanabor, Daniela; Barbi, Egidio; Schleef, Jurgen (Ann Emerg Med, 2018)

A Girl with Delayed Puberty and Bumpy Lips. - Andrade, Stefanny; Sirchia, Fabio; Faleschini, Elena; Barbi, Egidio (J Pediatr, 2018)
Keywords: Adolescent; Exons; Female; Genes, Dominant; Humans; Lip; Multiple Endocrine Neoplasia Type 2b; Neoplasm Metastasis; Puberty, Delayed; Thyroid Neoplasms; Thyroidectomy; Tongue

Gut microbiota characterisation in obese patients before and after bariatric surgery. - Campisciano, G; Palmisano, S; Cason, C; Giuricin, M; Silvestri, M; Guerra, M; Macor, D; De Manzini, N; Crocé, L S; Comar, M (Benef Microbes, 2018)
Intestinal microbiota analysis of obese patients after bariatric surgery showed that Proteobacteria decreased after laparoscopic sleeve gastrectomy (SG), while it increased after laparoscopic gastric bypass (LGB). Comparing to normal weight (NW) patients, obese patients that were selected for SG showed an almost equal amount of Firmicutes and Bacteroidetes and the ratio was not affected by the surgery. Obese patients before LGB showed a predominance of Bacteroidetes, whose amount regained a relative abundance similar to NW patients after surgery. Obese patients before LGB showed the predominance of Bacteroides, which decreased after surgery in favour of Prevotella, a bacterium associated with a healthy diet. The bacteria detected at the highest percentages belonged to biofilm forming species. In conclusion, in this study, we found that the characterization of the gut microbial communities and the modality of mucosal colonisation have a central role as markers for the clinical management of obesity and promote the maintenance of good health and the weight loss.
Keywords: Adult; Bariatric Surgery; Gastrointestinal Microbiome; Humans; Laparoscopy; Microbiota; Middle Aged; Obesity; Young Adult

High-Throughput Sequencing of microRNAs in Glucocorticoid Sensitive Paediatric Inflammatory Bowel Disease Patients. - De Iudicibus, Sara; Lucafò, Marianna; Vitulo, Nicola; Martelossi, Stefano; Zimbello, Rosanna; De Pascale, Fabio; Forcato, Claudio; Naviglio, Samuele; Di Silvestre, Alessia; Gerdol, Marco; Stocco, Gabriele; Valle, Giorgio; et al. (Int J Mol Sci, 2018)
The aim of this research was the identification of novel pharmacogenomic biomarkers for better understanding the complex gene regulation mechanisms underpinning glucocorticoid (GC) action in paediatric inflammatory bowel disease (IBD). This goal was achieved by evaluating high-throughput microRNA (miRNA) profiles during GC treatment, integrated with the assessment of expression changes in GC receptor (GR) heterocomplex genes. Furthermore, we tested the hypothesis that differentially expressed miRNAs could be directly regulated by GCs through investigating the presence of GC responsive elements (GREs) in their gene promoters. Ten IBD paediatric patients responding to GCs were enrolled. Peripheral blood was obtained at diagnosis (T0) and after four weeks of steroid treatment (T4). MicroRNA profiles were analyzed using next generation sequencing, and selected significantly differentially expressed miRNAs were validated by quantitative reverse transcription-polymerase chain reaction. In detail, 18 miRNAs were differentially expressed from T0 to T4, 16 of which were upregulated and 2 of which were downregulated. Out of these, three miRNAs (miR-144, miR-142, and miR-96) could putatively recognize the 3’UTR of the GR gene and three miRNAs (miR-363, miR-96, miR-142) contained GREs sequences, thereby potentially enabling direct regulation by the GR. In conclusion, we identified miRNAs differently expressed during GC treatment and miRNAs which could be directly regulated by GCs in blood cells of young IBD patients. These results could represent a first step towards their translation as pharmacogenomic biomarkers.
Keywords: Adolescent; Biomarkers; Child; Female; Gene Expression Regulation; Glucocorticoids; High-Throughput Nucleotide Sequencing; Humans; Inflammatory Bowel Diseases; Male; MicroRNAs; Receptors, Glucocorticoid; Transcriptome

How to predict response to anti-tumour necrosis factor agents in inflammatory bowel disease. - Naviglio, Samuele; Giuffrida, Paolo; Stocco, Gabriele; Lenti, Marco Vincenzo; Ventura, Alessandro; Corazza, Gino Roberto; Di Sabatino, Antonio (Expert Rev Gastroenterol Hepatol, 2018)
INTRODUCTION: Anti-tumor necrosis factor (TNF) agents have changed the therapeutic approach to inflammatory bowel disease (IBD). However, a considerable proportion of patients either do not primarily respond or lose response to treatment. Despite the long-standing experience in the use of these drugs, still there is the need of identifying the possible predictors of efficacy. Areas covered: We critically review the current knowledge on predictors of response to anti-TNF therapy - both those available in clinical practice and those still under investigation. Multiple factors are involved in treatment success, including disease phenotype and severity, adherence to medications, and pharmacogenomic, pharmacokinetic, and immunologic factors. Literature search was conducted in PubMed using keywords 'inflammatory bowel disease,' 'Crohn's disease,' and 'ulcerative colitis,' matched with 'antitumor necrosis factor,' 'biologic therapy,' 'clinical response,' 'predictors,' and 'efficacy,' Relevant articles were selected for review. Expert commentary: While the role of several factors in clinical practice is clearly established, other investigational markers have been proposed, mostly in small studies, yet for many of them little external validation exists. Therapeutic drug monitoring is emerging as a pivotal strategy to guide decisions in clinical practice. In the near future, novel markers could improve our ability to direct treatment and personalize therapy.
Keywords: Antibodies, Monoclonal; Biological Therapy; Gastrointestinal Agents; Humans; Inflammatory Bowel Diseases; Patient Selection; Prognosis; Treatment Outcome; Tumor Necrosis Factor-alpha

Hypomorphic FANCA mutations correlate with mild mitochondrial and clinical phenotype in Fanconi anemia. - Bottega, Roberta; Nicchia, Elena; Cappelli, Enrico; Ravera, Silvia; De Rocco, Daniela; Faleschini, Michela; Corsolini, Fabio; Pierri, Filomena; Calvillo, Michaela; Russo, Giovanna; Casazza, Gabriella; Ramenghi, Ugo; et al. (Haematologica, 2018)
Fanconi anemia is a rare disease characterized by congenital malformations, aplastic anemia, and predisposition to cancer. Despite the consolidated role of the Fanconi anemia proteins in DNA repair, their involvement in mitochondrial function is emerging. The purpose of this work was to assess whether the mitochondrial phenotype, independent of genomic integrity, could correlate with patient phenotype. We evaluated mitochondrial and clinical features of 11 affected individuals homozygous or compound heterozygous for p.His913Pro and p.Arg951Gln/Trp, the two residues of FANCA that are more frequently affected in our cohort of patients. Although p.His913Pro and p.Arg951Gln proteins are stably expressed in cytoplasm, they are unable to migrate in the nucleus, preventing cells from repairing DNA. In these cells, the electron transfer between respiring complex I-III is reduced and the ATP/AMP ratio is impaired with defective ATP production and AMP accumulation. These activities are intermediate between those observed in wild-type and FANCA-/- cells, suggesting that the variants at residues His913 and Arg951 are hypomorphic mutations. Consistent with these findings, the clinical phenotype of most of the patients carrying these mutations is mild. These data further support the recent finding that the Fanconi anemia proteins play a role in mitochondria, and open up possibilities for genotype/phenotype studies based on novel mitochondrial criteria.

Imaging and therapy of ovarian cancer: clinical application of nanoparticles and future perspectives. - Di Lorenzo, Giovanni; Ricci, Giuseppe; Severini, Giovanni Maria; Romano, Federico; Biffi, Stefania (Theranostics, 2018)
Despite significant advances in cancer diagnostics and treatment, ovarian cancers (OC) continue to kill more than 150,000 women every year worldwide. Due to the relatively asymptomatic nature and the advanced stage of the disease at the time of diagnosis, OC is the most lethal gynecologic malignancy. The current treatment for advanced OC relies on the synergistic effect of combining surgical cytoreduction and chemotherapy; however, beside the fact that chemotherapy resistance is a major challenge in OC management, new imaging strategies are needed to target microscopic lesions and improve both cytoreductive surgery and patient outcomes. In this context, nanostructured probes are emerging as a new class of medical tool that can simultaneously provide imaging contrast, target tumor cells, and carry a wide range of medicines resulting in better diagnosis and therapeutic precision. Herein we summarize several exemplary efforts in nanomedicine for addressing unmet clinical needs.

Influence of polymerization time on properties of dual-curing cements in combination with high translucency monolithic zirconia. - Alovisi, Mario; Scotti, Nicola; Comba, Allegra; Manzon, Elena; Farina, Elena; Pasqualini, Damiano; Michelotto Tempesta, Riccardo; Breschi, Lorenzo; Cadenaro, Milena (J Prosthodont Res, 2018)
PURPOSE: The aim of this in vitro study was to assess conversion degree (DC), micro-hardness (MH) and bond strength of two dual-curing resin cements employed under translucent monolithic zirconia irradiated with different time protocols. METHODS: 84 square shaped samples of 1mm thickness were prepared from high translucency zirconia blocks and divided into two groups (n=24) according to the cement employed: (1) Rely-X Ultimate; (2) Panavia SA. Each group was further divided into 3 subgroups (n=8) according to the irradiation time: (a) no light; (b) 20s; (c) 120s. Light curing was performed 60s after the sample was placed on the diamond support of a FT-IR spectrophotometer with a high power multiLED lamp. Final DC% were calculated after 10min. After 24h, Vickers Test on the cement layer was performed. The same protocol was used to lute composite cylinders in order to evaluate microshear bond-strength test. ANOVA and Bonferroni tests were performed to find differences between MH and bond-strength to zirconia, while for DC% the Scheirer-Ray-Hare two-way test was used. RESULTS: The two cements reached higher DC% in subgroup (b) and (c). As concern MH, statistics showed an increase in curing time was able to improve MH significantly. Bond-strength was not affected by irradiation time only for Panavia SA. CONCLUSIONS: The first null hypothesis has to be rejected since DC% and MH of the dual-cements tested were influenced by the curing time. The second null hypothesis is partially rejected since the bond strength was influenced by the curing time only for Rely-X Ultimate.
Keywords: Composite Resins; Dental Bonding; Dental Cements; Hardness; Lansoprazole; Materials Testing; Polymerization; Resins, Synthetic; Spectrophotometry; Time Factors; Zirconium

Interstitial Fluid in Gynecologic Tumors and Its Possible Application in the Clinical Practice. - Ura, Blendi; Di Lorenzo, Giovanni; Romano, Federico; Monasta, Lorenzo; Mirenda, Giuseppe; Scrimin, Federica; Ricci, Giuseppe (Int J Mol Sci, 2018)
Gynecologic cancers are an important cause of worldwide mortality. The interstitium consists of solid and fluid phases, situated between the blood vessels and cells. The interstitial fluid (IF), or fluid phase, is an extracellular fluid bathing and surrounding the tissue cells. The TIF (tumor interstitial fluid) is a dynamic fluid rich in lipids, proteins and enzyme-derived substances. The molecules found in the IF may be associated with pathological changes in tissues leading to cancer growth and metastatization. Proteomic techniques have allowed an extensive study of the composition of the TIF as a source of biomarkers for gynecologic cancers. In our review, we analyze the composition of the TIF, its formation process, the sampling methods, the consequences of its accumulation and the proteomic analyses performed, that make TIF valuable for monitoring different types of cancers.
Keywords: Biomarkers, Tumor; Biophysical Phenomena; Extracellular Fluid; Female; Genital Neoplasms, Female; Humans; Practice Patterns, Physicians'; Tumor Microenvironment

Iron-related toxicity of single-walled carbon nanotubes and crocidolite fibres in human mesothelial cells investigated by Synchrotron XRF microscopy. - Cammisuli, Francesca; Giordani, Silvia; Gianoncelli, Alessandra; Rizzardi, Clara; Radillo, Lucia; Zweyer, Marina; Da Ros, Tatiana; Salomè, Murielle; Melato, Mauro; Pascolo, Lorella (Sci Rep, 2018)
Carbon nanotubes (CNTs) are promising products in industry and medicine, but there are several human health concerns since their fibrous structure resembles asbestos. The presence of transition metals, mainly iron, in the fibres seems also implicated in the pathogenetic mechanisms. To unravel the role of iron at mesothelial level, we compared the chemical changes induced in MeT-5A cells by the exposure to asbestos (crocidolite) or CNTs at different content of iron impurities (raw-SWCNTs, purified- and highly purified-SWCNTs). We applied synchrotron-based X-Ray Fluorescence (XRF) microscopy and soft X-ray imaging (absorption and phase contrast images) to monitor chemical and morphological changes of the exposed cells. In parallel, we performed a ferritin assay. X-ray microscopy imaging and XRF well localize the crocidolite fibres interacting with cells, as well as the damage-related morphological changes. Differently, CNTs presence could be only partially evinced by low energy XRF through carbon distribution and sometimes iron co-localisation. Compared to controls, the cells treated with raw-SWCNTs and crocidolite fibres showed a severe alteration of iron distribution and content, with concomitant stimulation of ferritin production. Interestingly, highly purified nanotubes did not altered iron metabolism. The data provide new insights for possible CNTs effects at mesothelial/pleural level in humans.
Keywords: Asbestos, Crocidolite; Cell Line; Epithelial Cells; Humans; Iron; Microscopy, Fluorescence; Nanotubes, Carbon

Joint Data Analysis in Nutritional Epidemiology: Identification of Observational Studies and Minimal Requirements. - Pinart, Mariona; Nimptsch, Katharina; Bouwman, Jildau; Dragsted, Lars O; Yang, Chen; De Cock, Nathalie; Lachat, Carl; Perozzi, Giuditta; Canali, Raffaella; Lombardo, Rosario; D'Archivio, Massimo; Guillaume, Michèle; et al. (J Nutr, 2018)
Background: Joint data analysis from multiple nutrition studies may improve the ability to answer complex questions regarding the role of nutritional status and diet in health and disease. Objective: The objective was to identify nutritional observational studies from partners participating in the European Nutritional Phenotype Assessment and Data Sharing Initiative (ENPADASI) Consortium, as well as minimal requirements for joint data analysis. Methods: A predefined template containing information on study design, exposure measurements (dietary intake, alcohol and tobacco consumption, physical activity, sedentary behavior, anthropometric measures, and sociodemographic and health status), main health-related outcomes, and laboratory measurements (traditional and omics biomarkers) was developed and circulated to those European research groups participating in the ENPADASI under the strategic research area of "diet-related chronic diseases." Information about raw data disposition and metadata sharing was requested. A set of minimal requirements was abstracted from the gathered information. Results: Studies (12 cohort, 12 cross-sectional, and 2 case-control) were identified. Two studies recruited children only and the rest recruited adults. All studies included dietary intake data. Twenty studies collected blood samples. Data on traditional biomarkers were available for 20 studies, of which 17 measured lipoproteins, glucose, and insulin and 13 measured inflammatory biomarkers. Metabolomics, proteomics, and genomics or transcriptomics data were available in 5, 3, and 12 studies, respectively. Although the study authors were willing to share metadata, most refused, were hesitant, or had legal or ethical issues related to sharing raw data. Forty-one descriptors of minimal requirements for the study data were identified to facilitate data integration. Conclusions: Combining study data sets will enable sufficiently powered, refined investigations to increase the knowledge and understanding of the relation between food, nutrition, and human health. Furthermore, the minimal requirements for study data may encourage more efficient secondary usage of existing data and provide sufficient information for researchers to draft future multicenter research proposals in nutrition.
Keywords: Adult; Biomarkers; Blood Glucose; Case-Control Studies; Child; Chronic Disease; Cohort Studies; Cross-Sectional Studies; Diet; Epidemiology; Europe; Genomics; Health Status; Humans; Inflammation; Insulin; Life Style; Lipoproteins; Longitudinal Studies; Metabolomics; Nutritional Status; Observational Studies as Topic; Statistics as Topic

A Large-Scale Multi-ancestry Genome-wide Study Accounting for Smoking Behavior Identifies Multiple Significant Loci for Blood Pressure. - Sung, Yun J; Winkler, Thomas W; de Las Fuentes, Lisa; Bentley, Amy R; Brown, Michael R; Kraja, Aldi T; Schwander, Karen; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Lu, Yingchang; Cheng, Ching-Yu; et al. (Am J Hum Genet, 2018)
Genome-wide association analysis advanced understanding of blood pressure (BP), a major risk factor for vascular conditions such as coronary heart disease and stroke. Accounting for smoking behavior may help identify BP loci and extend our knowledge of its genetic architecture. We performed genome-wide association meta-analyses of systolic and diastolic BP incorporating gene-smoking interactions in 610,091 individuals. Stage 1 analysis examined ∼18.8 million SNPs and small insertion/deletion variants in 129,913 individuals from four ancestries (European, African, Asian, and Hispanic) with follow-up analysis of promising variants in 480,178 additional individuals from five ancestries. We identified 15 loci that were genome-wide significant (p < 5 × 10) in stage 1 and formally replicated in stage 2. A combined stage 1 and 2 meta-analysis identified 66 additional genome-wide significant loci (13, 35, and 18 loci in European, African, and trans-ancestry, respectively). A total of 56 known BP loci were also identified by our results (p < 5 × 10). Of the newly identified loci, ten showed significant interaction with smoking status, but none of them were replicated in stage 2. Several loci were identified in African ancestry, highlighting the importance of genetic studies in diverse populations. The identified loci show strong evidence for regulatory features and support shared pathophysiology with cardiometabolic and addiction traits. They also highlight a role in BP regulation for biological candidates such as modulators of vascular structure and function (CDKN1B, BCAR1-CFDP1, PXDN, EEA1), ciliopathies (SDCCAG8, RPGRIP1L), telomere maintenance (TNKS, PINX1, AKTIP), and central dopaminergic signaling (MSRA, EBF2).
Keywords: Blood Pressure; Cohort Studies; Continental Population Groups; Diastole; Epistasis, Genetic; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Smoking; Systole

Learning curve for the ultrasonographic diagnosis of deep endometriosis using a structured off-line training program. - Guerriero, Stefano; Pascual, M Angela; Ajossa, Silvia; Rodriguez, Ignacio; Zajicek, Michal; Rolla, Martino; Rams, Noelia Llop; Yulzari, Vered; Bardin, Ron; Buonomo, Francesca; Comparetto, Ornella; Perniciano, Maura; et al. (Ultrasound Obstet Gynecol, 2018)
OBJECTIVE: The aim of the present study was to assess the learning curves of trainees during a structured off-line/hands-on training program on the diagnosis of deep infiltrating endometriosis (DIE). METHODS: A two-week training program was conducted. One day was devoted to theoretical issues and guided off-line analysis of 10 volumes of three-dimensional (3D) ultrasound. During the following days, five sessions of real-time sonographic examinations were performed in a DIE referral center Ultrasound unit. In between sessions, the trainees analyzed four off-line sets, containing twenty-five 3D volumes each. At the end of each set, misinterpreted volumes were assessed with the trainer. One trainer and 4 trainees (all post-graduated Ob/Gyn with at least 5 years of experience in ultrasonography in Obstetrics and Gynecology but with no experience in DIE sonographic examinations) participated in the study. Presence or absence of DIE at surgery was considered as gold standard for the trainees. Trainee's results were evaluated by learning curve cumulative summation (LC-CUSUM) and the deviations of the level of trainees' performance at the control stage by CUSUM (standard CUSUM) for different locations of DIE. RESULTS: The trainees reached competence on average after 17 evaluations (range 21-14) for bladder locations, after 39 evaluations (range 60-30) for rectosigmoid locations, after 25 evaluations (range 34-14) for forniceal locations, after 44 evaluations (range 66-25) for utero-sacral locations (USL), after 21 evaluations (range 43-14) for rectovaginal septum (RVS) locations respectively, and kept the process under control with error levels of less than 4.5% until the end of the test. The overall accuracy for each trainee at the different locations ranged from 0.91 to 0.96 for bladder DIE, from 0.80 to 0.94 for recto-sigmoid DIE, from 0.90 to 0.94% for forniceal DIE, from 0.79 to 0.82 for utero-sacral ligaments DIE and from 0.89 to 0.97 for recto-vaginal septum DIE. CONCLUSIONS: The suggested two-weeks learning program based on a mix of off-line and live sessions is feasible and suggests a good performance in training for the diagnosis of DIE. This article is protected by copyright. All rights reserved.

Light element distribution in fresh and frozen-thawed human ovarian tissues: a preliminary study. - Pascolo, Lorella; Venturin, Irene; Gianoncelli, Alessandra; Bortul, Roberta; Zito, Gabriella; Giolo, Elena; Salomè, Murielle; Bedolla, Diana E; Altissimo, Matteo; Zweyer, Marina; Ricci, Giuseppe (Reprod Biomed Online, 2018)
RESEARCH QUESTION: Does synchrotron X-ray fluorescence (XRF) provide novel chemical information for the evaluation of human ovarian tissue cryopreservation protocols? DESIGN: Tissues from five patients undergoing laparoscopic surgery for benign gynaecological conditions were fixed for microscopic analysis either immediately or after cryopreservation. After fixation, fresh and slowly frozen samples were selected by light microscopy and transmission electron microscopy, and subsequently analysed with synchrotron XRF microscopy at different incident energies. RESULTS: The distributions of elements detected at 7.3 keV (S, P, K, Cl, Fe, and Os) and 1.5 keV (Na and Mg) were related to the changes revealed by light microscopy and transmission electron microscopy analyses. The light elements showed highly informative findings. The S distribution was found to be an indicator of extracellular component changes in the stromal tissues of the freeze-stored samples, further revealed by the transmission electron microscopy analyses. Low-quality follicles, frequent in the freeze-thawed tissues, showed a high Na level in the ooplasm. On the contrary, good-quality follicles were detected by a homogeneous Cl distribution. The occurrence of vacuolated follicles increased after cryopreservation, and the XRF analyses showed that the vacuolar structures contained mainly Cl and Na. CONCLUSIONS: The study demonstrates that elemental imaging techniques, particularly revealing the distribution of light elements, could be useful in establishing new cryopreservation protocols.
Keywords: Cryopreservation; Female; Humans; Microscopy, Electron, Transmission; Organ Preservation; Ovarian Follicle; Ovary

Long term outcome of eight patients with type 1 Leukocyte Adhesion Deficiency (LAD-1): Not only infections, but high risk of autoimmune complications. - De Rose, Domenico Umberto; Giliani, Silvia; Notarangelo, Lucia Dora; Lougaris, Vassilios; Lanfranchi, Arnalda; Moratto, Daniele; Martire, Baldassarre; Specchia, Fernando; Tommasini, Alberto; Plebani, Alessandro; Badolato, Raffaele (Clin Immunol, 2018)
Leukocyte Adhesion Deficiency type 1 (LAD-1) is a rare primary immunodeficiency due to mutations in the gene encoding for the common β-chain of the β2 integrin family (CD18). Herein, we describe clinical manifestations and long-term complications of eight LAD-1 patients. Four LAD-1 patients were treated with hematopoietic stem cell transplantation (HSCT), while the remaining four, including two with moderate LAD-1 deficiency, received continuous antibiotic prophylaxis. Untreated patients presented numerous infections and autoimmune manifestations. In particular, two of them developed renal and intestinal autoimmune diseases, despite the expression of Beta-2 integrin was partially conserved. Other two LAD-1 patients developed type 1 diabetes and autoimmune cytopenia after HSCT, suggesting that HSCT is effective for preventing infections in LAD-1, but does not prevent the risk of the autoimmune complications.

Meconium-stained amniotic fluid: a risk factor for postpartum hemorrhage. - Bouchè, Carlo; Wiesenfeld, Uri; Ronfani, Luca; Simeone, Roberto; Bogatti, Paolo; Skerk, Kristina; Ricci, Giuseppe (Ther Clin Risk Manag, 2018)
Background/aim: Clinical data with respect to the impact of meconium on the risk of maternal hemorrhage are scarce. Therefore, in this study, we aimed to determine whether meconium-stained amniotic fluid (MSAF) represents a risk factor for postpartum hemorrhage (PPH) after vaginal delivery in a large unselected population. Patients and methods: A retrospective cohort study evaluated 78,542 consecutive women who had a vaginal delivery between 24th and 44th weeks of gestation. The women who had undergone cesarean section were excluded to avoid possible bias. Postpartum blood loss was measured with graduated blood sack. Postpartum blood loss between 1,000 and 2,000 mL and >2,000 mL were classified as moderate and severe PPH, respectively. Results: A total of 74,144 patients were available for analysis. According to the color of amniotic fluid (AF), two groups of patients were identified: MSAF (n=10,997) and clear AF (n=63,147). The rates of severe and massive PPH were found to be significantly higher in the MSAF group than that of clear AF group (OR=1.3, 95% CI: 1.2-1.5, <0.001 and OR=2.5, 95% CI: 1.5-4.2, <0.001). Operative vaginal delivery rate was found to be higher in the MSAF group than that of clear AF group, but the difference was only borderline significant (OR=1.5, 95% CI: 1.0-2.2, =0.05). There were no significant differences between the MSAF and the clear AF groups with respect to episiotomies, second- or third-degree perineal tears, vaginal-perineal thrombus, cervical lacerations, vaginal births after cesarean section, twin deliveries, and placental retention rates. Conclusion: To the best of our knowledge, this is the first clinical study that has investigated the role of MSAF as a risk factor for PPH after vaginal delivery in an unselected population. Our results suggest that MSAF is significantly associated with higher risk of moderate and severe PPH than clear AF.

MKRN3 levels in girls with central precocious puberty and correlation with sexual hormone levels: a pilot study. - Grandone, Anna; Cirillo, Grazia; Sasso, Marcella; Capristo, Carlo; Tornese, Gianluca; Marzuillo, Pierluigi; Luongo, Caterina; Rosaria Umano, Giuseppina; Festa, Adalgisa; Coppola, Ruggero; Miraglia Del Giudice, Emanuele; Perrone, Laura (Endocrine, 2018)
PURPOSE: Recently, mutations of makorin RING-finger protein 3 (MKRN3) have been described in familial central precocious puberty. Serum levels of this protein decline before the pubertal onset in healthy girls and boys. The aim of the study is to investigate MKRN3 circulating levels in patients with central precocious puberty. METHODS: We performed an observational cross-sectional study. We enrolled 17 patients with central precocious puberty aged 7 years (range: 2-8 years) and breast development onset <8 years; 17 prepubertal control age-matched patients aged 6.3 years (2-8.2); and 10 pubertal stage-matched control patients aged 11.4 years (9-14). Serum values of MKRN3, gonadotropins, (17)estradiol and Anti-Müllerian Hormone were evaluated and the MKRN3 genotyped in central precocious puberty patients. RESULTS: No MKRN3 mutation was found among central precocious puberty patients. MKRN3 levels were lower in patients with central precocious puberty compared to prepubertal age-matched ones (p: 0.0004) and comparable to those matched for pubertal stage. MKRN3 levels were inversely correlated to Body Mass Index Standard Deviations (r:-0.35; p:0.02), Luteinizing Hormone (r:-0.35; p:0.03), FSH (r:-0.37; p:0.02), and (17)estradiol (r: -0.36; p:0.02). CONCLUSIONS: We showed that girls with central precocious puberty had lower peripheral levels of MKRN3 compared to age-matched pairs and that they negatively correlated to gonadotropins, estrogen, and BMI. Our findings support the MKRN3 involvement in central precocious puberty also in absence of deleterious mutations, although our sample size is small. In addition our data suggest the role of MKRN3 in the complex mechanism controlling puberty onset and its interaction with other factors affecting puberty such as nutrition.
Keywords: Adolescent; Adolescent Nutritional Physiological Phenomena; Anti-Mullerian Hormone; Case-Control Studies; Child; Child Nutritional Physiological Phenomena; Child, Preschool; Cross-Sectional Studies; Female; Follicle Stimulating Hormone; Gonadotropin-Releasing Hormone; Humans; Luteinizing Hormone; Pilot Projects; Puberty, Precocious; Ribonucleoproteins; Sexual Maturation

MKRN3 Levels in Girls with Central Precocious Puberty during GnRHa Treatment: A Longitudinal Study. - Grandone, Anna; Cirillo, Grazia; Sasso, Marcella; Tornese, Gianluca; Luongo, Caterina; Festa, Adalgisa; Marzuillo, Pierluigi; Miraglia Del Giudice, Emanuele (Horm Res Paediatr, 2018)
BACKGROUND: Recently, mutations of makorin RING finger protein 3 (MKRN3) have been identified in familial central precocious puberty (CPP). Serum levels of this protein decline before the pubertal onset in healthy girls and boys and are lower in patients with CPP compared to prepubertal matched pairs. The aim of our study was to investigate longitudinal changes in circulating MKRN3 levels in patients with CPP before and during GnRH analogs (GnRHa) treatment. METHODS: We performed a longitudinal prospective study. We enrolled 15 patients with CPP aged 7.2 years (range: 2-8) with age at breast development onset < 8 years and 12 control girls matched for the time from puberty onset (mean age 11.8 ± 1.2 years). Serum values of MKRN3, gonadotropins, and 17β-estradiol were evaluated before and during treatment with GnRHa (at 6 and 12 months). The MKRN3 gene was genotyped in CPP patients. In the girls from the control group, only basal levels were analyzed. RESULTS: No MKRN3 mutations were found among CPP patients. MKRN3 levels declined significantly from baseline to 6 months of GnRHa treatment (p = 0.0007) and from 6 to 12 months of treatment (p = 0.003); MKRN3 levels at 6 months were significantly lower than in the control girls (p < 0.0001). CONCLUSIONS: We showed that girls with CPP had a decline in peripheral levels of MKRN3 during GnRHa treatment. Our data suggest a suppression of MKRN3 by continuous pharmacological administration of GnRHa.
Keywords: Brain Diseases; Case-Control Studies; Child; Child, Preschool; Female; Follicle Stimulating Hormone; Genotype; Gonadotropin-Releasing Hormone; Humans; Longitudinal Studies; Luteinizing Hormone; Male; Puberty, Precocious; Ribonucleoproteins

MYH9: Structure, functions and role of non-muscle myosin IIA in human disease. - Pecci, Alessandro; Ma, Xuefei; Savoia, Anna; Adelstein, Robert S (Gene, 2018)
The MYH9 gene encodes the heavy chain of non-muscle myosin IIA, a widely expressed cytoplasmic myosin that participates in a variety of processes requiring the generation of intracellular chemomechanical force and translocation of the actin cytoskeleton. Non-muscle myosin IIA functions are regulated by phosphorylation of its 20 kDa light chain, of the heavy chain, and by interactions with other proteins. Variants of MYH9 cause an autosomal-dominant disorder, termed MYH9-related disease, and may be involved in other conditions, such as chronic kidney disease, non-syndromic deafness, and cancer. This review discusses the structure of the MYH9 gene and its protein, as well as the regulation and physiologic functions of non-muscle myosin IIA with particular reference to embryonic development. Moreover, the review focuses on current knowledge about the role of MYH9 variants in human disease.
Keywords: Animals; Cell Line; Deafness; Hearing Loss, Sensorineural; Humans; Mice; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Neoplasms; Nonmuscle Myosin Type IIA; Phosphorylation; Renal Insufficiency, Chronic; Thrombocytopenia

A new form of inherited thrombocytopenia due to monoallelic loss of function mutation in the thrombopoietin gene. - Noris, Patrizia; Marconi, Caterina; De Rocco, Daniela; Melazzini, Federica; Pippucci, Tommaso; Loffredo, Giuseppe; Giangregorio, Tania; Pecci, Alessandro; Seri, Marco; Savoia, Anna (Br J Haematol, 2018)

Non-invasive biomarkers of fetal brain development reflecting prenatal stress: An integrative multi-scale multi-species perspective on data collection and analysis. - Frasch, Martin G; Lobmaier, Silvia M; Stampalija, Tamara; Desplats, Paula; Pallarés, María Eugenia; Pastor, Verónica; Brocco, Marcela A; Wu, Hau-Tieng; Schulkin, Jay; Herry, Christophe L; Seely, Andrew J E; Metz, Gerlinde A S; et al. (Neurosci Biobehav Rev, 2018)
Prenatal stress (PS) impacts early postnatal behavioural and cognitive development. This process of 'fetal programming' is mediated by the effects of the prenatal experience on the developing hypothalamic-pituitary-adrenal (HPA) axis and autonomic nervous system (ANS). We derive a multi-scale multi-species approach to devising preclinical and clinical studies to identify early non-invasively available pre- and postnatal biomarkers of PS. The multiple scales include brain epigenome, metabolome, microbiome and the ANS activity gauged via an array of advanced non-invasively obtainable properties of fetal heart rate fluctuations. The proposed framework has the potential to reveal mechanistic links between maternal stress during pregnancy and changes across these physiological scales. Such biomarkers may hence be useful as early and non-invasive predictors of neurodevelopmental trajectories influenced by the PS as well as follow-up indicators of success of therapeutic interventions to correct such altered neurodevelopmental trajectories. PS studies must be conducted on multiple scales derived from concerted observations in multiple animal models and human cohorts performed in an interactive and iterative manner and deploying machine learning for data synthesis, identification and validation of the best non-invasive detection and follow-up biomarkers, a prerequisite for designing effective therapeutic interventions.

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alcohol Drinking; Blood Pressure; Cohort Studies; Continental Population Groups; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

Ocular Manifestations of Paediatric Inflammatory Bowel Disease: A Systematic Review and Meta-analysis. - Ottaviano, Giorgio; Salvatore, Silvia; Salvatoni, Alessandro; Martelossi, Stefano; Ventura, Alessandro; Naviglio, Samuele (J Crohns Colitis, 2018)
Background and Aims: Ocular extraintestinal manifestations [O-EIMs] are known complications of Crohn's disease [CD], ulcerative colitis [UC], and inflammatory bowel disease unclassified [IBD-U]. However, data on their prevalence in children are scarce and there are no clear recommendations on what follow-up should be offered. We aimed to review available data on O-EIMs in children. Methods: In January 2018, we performed a systematic review of published English literature using PubMed and EMBASE databases and disease-specific queries. Results: Fifteen studies [7467 patients] reported data on O-EIMs prevalence in children. Overall prevalence of O-EIMs was 0.62-1.82%. Uveitis was the most common O-EIM. Meta-analysis showed that children with CD are at increased risk of O-EIMs as compared with children with UC and IBD-U (odds ratio [OR] 2.70, 95% confidence interval [CI] 1.51-4.83). Five studies [357 patients] reported data on ophthalmological screening in asymptomatic children: mild asymptomatic uveitis was identified in a variable proportion of patients [1.06-23.1%], more frequently in male patients with CD and colonic involvement. No evidence of ocular complications from untreated uveitis was detected. A total of 23 case reports [24 patients] were identified. Conclusions: Data on O-EIMs in children are scarce. Prevalence of O-EIMs is lower than in adults but may be underestimated because of the possibility of asymptomatic uveitis; however, the long-term significance of this condition is unknown. Children with CD may be at increased risk of O-EIMs. No recommendations on routine ophthalmological examination can be made, but a low threshold for ophthalmological referral should be maintained. Larger studies in paediatric IBD populations are needed.
Keywords: Adolescent; Cataract; Child; Child, Preschool; Colitis, Ulcerative; Crohn Disease; Eye Diseases; Humans; Prevalence; Uveitis

Paediatric Home Artificial Nutrition in Italy: Report from 2016 Survey on Behalf of Artificial Nutrition Network of Italian Society for Gastroenterology, Hepatology and Nutrition (SIGENP). - Lezo, Antonella; Capriati, Teresa; Spagnuolo, Maria Immacolata; Lacitignola, Laura; Goreva, Irina; Di Leo, Grazia; Cecchi, Nicola; Gandullia, Paolo; Amarri, Sergio; Forchielli, Maria Luisa; Dipasquale, Valeria; Parma, Barbara; et al. (Nutrients, 2018)
Home Artificial Nutrition (HAN) is a safe and efficacious technique that insures children's reintegration into the family, society and school. Epidemiological data on paediatric HAN in Italy are not available. AIM: to detect the prevalence and incidence of Home Parenteral Nutrition (HPN) and Home Enteral Nutrition (HEN), either via tube or mouth, in Italy in 2016. MATERIALS AND METHODS: a specific form was sent to all registered SIGENP members and investigators of local HAN centres, inviting them to provide the requested centre's data and demographics, underlying diseases and HAN characteristics of the patients. RESULTS: we recorded 3403 Italian patients on HAN aged 0 to 19 years from 22 centres: 2277 HEN, 950 Oral Nutritional Supplements (ONS) and 179 HPN programs. The prevalence of HEN (205 pts/million inhabitants) and HPN (16 pts/million inhabitants) has dramatically increased in Italy in the last 9 years. Neurodisabling conditions were the first indication for HEN by tube or mouth while HPN is mainly requested in digestive disorders. CONCLUSIONS: HAN is a widespread and rapidly growing treatment in Italy, as well as in other European countries. Awareness of its extent and characteristics helps improving HAN service and patients' quality of life.
Keywords: Adolescent; Age Factors; Child; Child Nutritional Physiological Phenomena; Child, Preschool; Enteral Nutrition; Female; Health Care Surveys; Home Care Services; Humans; Infant; Infant, Newborn; Italy; Male; Nutritional Status; Parenteral Nutrition, Home; Pediatrics; Time Factors; Young Adult

Pharmacogenetics of treatments for inflammatory bowel disease. - Lucafò, Marianna; Franca, Raffaella; Selvestrel, Davide; Curci, Debora; Pugnetti, Letizia; Decorti, Giuliana; Stocco, Gabriele (Expert Opin Drug Metab Toxicol, 2018)
INTRODUCTION: Inflammatory bowel disease is a chronic inflammation of the gut whose pathogenesis is still unclear. Although no curative therapy is currently available, a number of drugs are used in induction and maintenance therapy; however, for most of these drugs, a high inter-individual variability in response is observed. Among the factors of this variability, genetics plays an important role. Areas covered: This review summarizes the results of pharmacogenetic studies, considering the most important drugs used and in particular aminosalycilates, glucocorticoids, thiopurines, monoclonal antibodies and thalidomide. Most studies used a candidate gene approach, even if significant breakthroughs have been obtained recently from applying genome-wide studies. When available, also investigations considering epigenetics and pharmacogenetic dosing guidelines have been included. Expert opinion: Only for thiopurines, genetic markers identified as predictors of efficacy or adverse events have allowed the development of dosing guidelines. For the other drugs, encouraging results are available and great expectations rely on the study of epigenetics and integration with pharmacokinetic information, especially useful for biologics. However, to improve therapy of IBD patients with these drugs, for implementation in the clinics of pharmacogenetics, informatic clinical decision support systems and training about pharmacogenetics of health providers are needed.
Keywords: Dose-Response Relationship, Drug; Epigenesis, Genetic; Gastrointestinal Agents; Genetic Markers; Genetic Predisposition to Disease; Humans; Inflammatory Bowel Diseases; Pharmacogenetics

Photobiomodulation at Multiple Wavelengths Differentially Modulates Oxidative Stress and . - Rupel, Katia; Zupin, Luisa; Colliva, Andrea; Kamada, Anselmo; Poropat, Augusto; Ottaviani, Giulia; Gobbo, Margherita; Fanfoni, Lidia; Gratton, Rossella; Santoro, Massimo; Di Lenarda, Roberto; Biasotto, Matteo; et al. (Oxid Med Cell Longev, 2018)
Photobiomodulation (PBM) is emerging as an effective strategy for the management of multiple inflammatory conditions, including oral mucositis (OM) in cancer patients who receive chemotherapy or radiotherapy. Still, the poor understanding of the mechanisms by which the light interacts with biological tissues and the heterogeneity of light sources and protocols employed worldwide significantly limits its applicability. Reactive oxygen species (ROS) are massively generated during the early phases of OM and play a major role in the pathogenesis of inflammation in general. Here, we report the results of a clinical and experimental study, aimed at evaluating the effect of laser light at different wavelengths on oxidative stress in oncologic patients suffering from OM and in two cell types abundantly present within the inflamed oral mucosa, neutrophil polymorphonuclear (PMN) granulocytes, and keratinocytes. In addition to standard ROS detection methods, we exploited a roGFP2-Orp1 genetically encoded sensor, allowing specific, quantitative, and dynamic imaging of redox events in living cells in response to oxidative stress and PBM. We found that the various wavelengths differentially modulate ROS production. In particular, the 660 nm laser light increases ROS production when applied either before or after an oxidative stimulus. In contrast, the 970 nm laser light exerted a moderate antioxidant activity both in the saliva of OM patients and in both cell types. The most marked reduction in the levels of ROS was detected in cells exposed either to the 800 nm laser light or to the combination of the three wavelengths. Overall, our study demonstrates that PBM exerts different effects on the redox state of both PMNs and keratinocytes depending on the used wavelength and prompts the validation of a multiwavelength protocol in the clinical settings.
Keywords: Adult; Aged; Aged, 80 and over; Female; Humans; Keratinocytes; Lasers, Semiconductor; Low-Level Light Therapy; Male; Middle Aged; Neutrophils; Oxidation-Reduction; Oxidative Stress; Stomatitis

Potential use of MCR-ALS for the identification of coeliac-related biochemical changes in hyperspectral Raman maps from pediatric intestinal biopsies. - Fornasaro, Stefano; Vicario, Annalisa; De Leo, Luigina; Bonifacio, Alois; Not, Tarcisio; Sergo, Valter (Integr Biol (Camb), 2018)
Raman hyperspectral imaging is an emerging practice in biological and biomedical research for label free analysis of tissues and cells. Using this method, both spatial distribution and spectral information of analyzed samples can be obtained. The current study reports the first Raman microspectroscopic characterisation of colon tissues from patients with Coeliac Disease (CD). The aim was to assess if Raman imaging coupled with hyperspectral multivariate image analysis is capable of detecting the alterations in the biochemical composition of intestinal tissues associated with CD. The analytical approach was based on a multi-step methodology: duodenal biopsies from healthy and coeliac patients were measured and processed with Multivariate Curve Resolution Alternating Least Squares (MCR-ALS). Based on the distribution maps and the pure spectra of the image constituents obtained from MCR-ALS, interesting biochemical differences between healthy and coeliac patients has been derived. Noticeably, a reduced distribution of complex lipids in the pericryptic space, and a different distribution and abundance of proteins rich in beta-sheet structures was found in CD patients. The output of the MCR-ALS analysis was then used as a starting point for two clustering algorithms (k-means clustering and hierarchical clustering methods). Both methods converged with similar results providing precise segmentation over multiple Raman images of studied tissues.

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity. - van Setten, Jessica; Brody, Jennifer A; Jamshidi, Yalda; Swenson, Brenton R; Butler, Anne M; Campbell, Harry; Del Greco, Fabiola M; Evans, Daniel S; Gibson, Quince; Gudbjartsson, Daniel F; Kerr, Kathleen F; Krijthe, Bouwe P; et al. (Nat Commun, 2018)
Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including heart block and atrial fibrillation. Variants in over half of the 44 loci were associated with atrial or blood transcript expression levels, or were in high linkage disequilibrium with missense variants. Six additional loci were identified either by meta-analysis of ~105,000 African and European-descent individuals and/or by pleiotropic analyses combining PR interval with heart rate, QRS interval, and atrial fibrillation. These findings implicate developmental pathways, and identify transcription factors, ion-channel genes, and cell-junction/cell-signaling proteins in atrio-ventricular conduction, identifying potential targets for drug development.
Keywords: Atrial Function; Atrioventricular Node; Electrocardiography; Electrophysiological Phenomena; Female; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Mutation, Missense; Risk Factors

Predictive value of the number of adverse reaction episodes for the IgE-mediated food allergy diagnosis. - Miceli Sopo, S; Gurnari, G; Monaco, S; Romano, A; Liotti, L; Cuomo, B; Dello Iacono, I; Badina, L; Longo, G; Calvani, M; Giannone, A; Calabrò, C; et al. (Allergol Immunopathol (Madr), 2018)
INTRODUCTION AND OBJECTIVES: The reproducibility of the adverse reaction increases the suggestiveness of a history of food allergy. However, the positive predictive value (PPV) of multiple adverse reaction episodes for the diagnosis of IgE-mediated food allergy is not known. This evaluation was the objective of our study. PATIENTS AND METHODS: We retrospectively studied 180 children with a history of non-anaphylactic adverse reactions after the ingestion of a food. All children had the prick test positive for the offending food and performed the oral food challenge (OFC) within 12 months after the last adverse reaction episode (ARE). We have evaluated whether increasing the number of ARE increased the probability that the OFC would be positive (failed). RESULTS: 93 patients (52%) presented one ARE, 49 (27%) presented two ARE, 24 (13%) presented three ARE, 14 (8%) patients presented≥four ARE. The OFC was positive in 94/180 (52%). The outcome of the OFC was found to be positively correlated with the number of ARE (OR=1.56; 95% CI=1.16-2.09; p=0.003). A PPV=100% was observed with a number of ARE≥five. CONCLUSIONS: The number of ARE is an important predictor of the diagnosis of food allergy, although less than we would have imagined. The number of ARE could be used to increase the predictability of the diagnostic tests currently in use, to define clinical prediction rules alternative to OFC and easy to use in clinical practice.

Pre-eclampsia affects procalcitonin production in placental tissue. - Agostinis, Chiara; Rami, Damiano; Zacchi, Paola; Bossi, Fleur; Stampalija, Tamara; Mangogna, Alessandro; Amadio, Leonardo; Vidergar, Romana; Vecchi Brumatti, Liza; Ricci, Giuseppe; Celeghini, Claudio; Radillo, Oriano; et al. (Am J Reprod Immunol, 2018)
PROBLEM: Procalcitonin (PCT) is the prohormone of calcitonin which is usually released from neuroendocrine cells of the thyroid gland (parafollicular) and the lungs (K cells). PCT is synthesized by almost all cell types and tissues, including monocytes and parenchymal tissue, upon LPS stimulation. To date, there is no evidence for PCT expression in the placenta both in physiological and pathological conditions. METHOD: Circulating and placental PCT levels were analysed in pre-eclamptic (PE) and control patients. Placental cells and macrophages (PBDM), stimulated with PE sera, were analysed for PCT expression. The effect of anti-TNF-α antibody was analysed. RESULTS: Higher PCT levels were detected in PE sera and in PE placentae compared to healthy women. PE trophoblasts showed increased PCT expression compared to those isolated from healthy placentae. PE sera induced an upregulation of PCT production in macrophages and placental cells. The treatment of PBDM with PE sera in the presence of anti-TNF-α completely abrogated the effect induced by pathologic sera. CONCLUSION: Trophoblast cells are the main producer of PCT in PE placentae. TNF-α, in association with other circulating factors present in PE sera, upregulates PCT production in macrophages and normal placental cells, thus contributing to the observed increased in circulating PCT in PE sera.
Keywords: Adult; Calcitonin; Cohort Studies; Female; Humans; Macrophages; Placenta; Pre-Eclampsia; Pregnancy; Trophoblasts; Tumor Necrosis Factor-alpha; Up-Regulation; Young Adult

Quality of care for children with acute malnutrition at health center level in Uganda: a cross sectional study in West Nile region during the refugee crisis. - Wanzira, Humphrey; Muyinda, Richard; Lochoro, Peter; Putoto, Giovanni; Segafredo, Giulia; Wamani, Henry; Lazzerini, Marzia (BMC Health Serv Res, 2018)
BACKGROUND: Arua district, in Uganda, hosts some of the largest refugee camps in the country. The estimated prevalence of moderate and severe acute malnutrition in children is higher than the national estimates (10.4 and 5.6% respectively, compared to 3.6 and 1.3%). This study aimed at assessing the quality of care provided to children with acute malnutrition at out-patient level in such a setting. METHODS: Six facilities with the highest number of children with malnutrition were selected. The main tool used was the National Nutrition Service Delivery Assessment Tool, assessing 10 key areas of service delivery and assigned a score as either poor, fair, good or excellent. Health outcomes, quality of case management and data quality were assessed from the health management information system and from the official nutrition registers. RESULTS: All facilities except two scored either poor or fair under all the 10 assessment areas. Overall, 33/60 (55%) areas scored as poor, 25/60 (41%) as fair, 2/60 (3.3%) as good, and none as excellent. Main gaps identified included: lack of trained staff; disorganised patient flow; poor case management; stock out of essential supplies including ready-to-use therapeutic foods; weak community linkage. A sample coverage of 45.4% (1020/2248) of total children admitted in the district during the 2016 financial year were included. The overall mean cure rate was 52.9% while the default rate was 38.3%. There was great heterogeneity across health facilities in health outcomes, quality of case management, and data quality. CONCLUSION: This study suggests that quality of care provided to children with malnutrition at health center level is substandard with unacceptable low cure rates. It is essential to identify effective approaches to enhance adherence to national guidelines, provision of essential nutritional commodities, regular monitoring of services and better linkage with the community through village health teams.
Keywords: Child Nutrition Disorders; Child, Preschool; Cross-Sectional Studies; Health Facilities; Humans; Nutrition Assessment; Nutritional Status; Prevalence; Quality of Health Care; Refugee Camps; Refugees; Uganda

Red Flags in Torticollis: A Historical Cohort Study. - Starc, Meta; Norbedo, Stefania; Tubaro, Martina; Ronfani, Luca; Bassanese, Giulia; Barbi, Egidio (Pediatr Emerg Care, 2018)
OBJECTIVE: This study aimed to assess the spectrum of pathologies responsible for torticollis in children presenting to the emergency department and to evaluate the associated symptoms to determine clinical red flags for hospitalization. METHODS: This was a historical retrospective cohort study. Medical records of children evaluated in our emergency department for torticollis from 2008 to 2013 were reviewed. RESULTS: Among 392 identified patients, 61% had postural torticollis,19.4% infection related, 16.3% traumatic, and 3.5% other. Twenty-five patients (6.4%) were hospitalized. Four variables were strongly and independently related to the severe outcome: fever, sore throat, headache, and age. CONCLUSIONS: The association of 2 or 3 of these 4 features carried a risk of 32% and 58%, respectively, of having a severe illness.
Keywords: Adolescent; Child; Child, Preschool; Cohort Studies; Emergency Service, Hospital; Female; Hospitalization; Humans; Male; Retrospective Studies; Torticollis

The Role of Oxidative Stress and Membrane Transport Systems during Endometriosis: A Fresh Look at a Busy Corner. - Vitale, Salvatore Giovanni; Capriglione, Stella; Peterlunger, Isabel; La Rosa, Valentina Lucia; Vitagliano, Amerigo; Noventa, Marco; Valenti, Gaetano; Sapia, Fabrizio; Angioli, Roberto; Lopez, Salvatore; Sarpietro, Giuseppe; Rossetti, Diego; et al. (Oxid Med Cell Longev, 2018)
Endometriosis is a condition characterized by the presence of endometrial tissue outside the uterine cavity, leading to a chronic inflammatory reaction. It is one of the most widespread gynecological diseases with a 10-15% prevalence in the general female population, rising up to 30-45% in patients with infertility. Although it was first described in 1860, its etiology and pathogenesis are still unclear. It is now accepted that inflammation plays a central role in the development and progression of endometriosis. In particular, it is marked by an inflammatory process associated with the overproduction of an array of inflammatory mediators such as prostaglandins, metalloproteinases, cytokines, and chemokines. In addition, the growth and adhesion of endometrial cells in the peritoneal cavity due to reactive oxygen species (ROS) and free radicals lead to disease onset, its ensuing symptoms-among which pain and infertility. The aim of our review is to evaluate the role of oxidative stress and ROS in the pathogenesis of endometriosis and the efficacy of antioxidant therapy in the treatment and mitigation of its symptoms.
Keywords: Endometriosis; Female; Humans; Oxidative Stress

Role of the Long Non-Coding RNA Growth Arrest-Specific 5 in Glucocorticoid Response in Children with Inflammatory Bowel Disease. - Lucafò, Marianna; Di Silvestre, Alessia; Romano, Maurizio; Avian, Alice; Antonelli, Roberta; Martelossi, Stefano; Naviglio, Samuele; Tommasini, Alberto; Stocco, Gabriele; Ventura, Alessandro; Decorti, Giuliana; De Iudicibus, Sara (Basic Clin Pharmacol Toxicol, 2018)
Glucocorticoids (GCs) are widely employed in inflammatory, autoimmune and neoplastic diseases, and, despite the introduction of novel therapies, remain the first-line treatment for inducing remission in inflammatory bowel disease (IBD). Given the high incidence of suboptimal response, associated with a significant number of side-effects, that are particularly severe in paediatric patients, the identification of subjects that are most likely to respond poorly to GCs is extremely important. Recent evidence suggests that the long non-coding RNA (lncRNA) GAS5 could be a potential marker of GC resistance. To address this issue, we evaluated the association between the lncRNA GAS5 and the efficacy of steroids, in terms of inhibition of proliferation, in two cell lines derived from colon and ovarian cancers, to confirm the sensitivity and specificity of these lncRNAs. These cells showed a different sensitivity to GCs and revealed differential expression of GAS5 after treatment. GAS5 was up-regulated in GC-resistant cells and accumulated more in the cytoplasm compared to the nucleus in response to the drug. The functions of GAS5 were assessed by silencing, and we found that GAS5 knock-down reduced the proliferation during GC treatment. Furthermore, for the first time, we measured GAS5 levels in 19 paediatric IBD patients at diagnosis and after the first cycle of GCs, and we demonstrated an up-regulation of the lncRNA in patients with unfavourable steroid response. Our preliminary results indicate that GAS5 could be considered a novel pharmacogenomic marker useful for the personalization of GC therapy.
Keywords: Biomarkers; Cell Line, Tumor; Cell Proliferation; Child; Drug Resistance; Female; Gene Knockdown Techniques; Glucocorticoids; Humans; Inflammatory Bowel Diseases; Male; Patient Selection; Pharmacogenomic Testing; Precision Medicine; RNA, Long Noncoding; RNA, Small Interfering; Treatment Outcome; Up-Regulation

Rothmund-Thomson Syndrome: Insights from New Patients on the Genetic Variability Underpinning Clinical Presentation and Cancer Outcome. - Colombo, Elisa A; Locatelli, Andrea; Cubells Sánchez, Laura; Romeo, Sara; Elcioglu, Nursel H; Maystadt, Isabelle; Esteve Martínez, Altea; Sironi, Alessandra; Fontana, Laura; Finelli, Palma; Gervasini, Cristina; Pecile, Vanna; et al. (Int J Mol Sci, 2018)
Biallelic mutations in gene, a caretaker of the genome, cause Rothmund-Thomson type-II syndrome (RTS-II) and confer increased cancer risk if they damage the helicase domain. We describe five families exemplifying clinical and allelic heterogeneity of RTS-II, and report the effect of pathogenic variants by predictions and transcripts analyses. Complete phenotype of patients #39 and #42 whose affected siblings developed osteosarcoma correlates with their c.[1048_1049del], c.[1878+32_1878+55del] and c.[1568G>C;1573delT], c.[3021_3022del] variants which damage the helicase domain. Literature survey highlights enrichment of these variants affecting the helicase domain in patients with cancer outcome raising the issue of strict oncological surveillance. Conversely, patients #29 and #19 have a mild phenotype and carry, respectively, the unreported homozygous c.3265G>T and c.3054A>G variants, both sparing the helicase domain. Finally, despite matching several criteria for RTS clinical diagnosis, patient #38 is heterozygous for c.2412_2414del; no pathogenic CNVs out of those evidenced by high-resolution CGH-array, emerged as contributors to her phenotype.
Keywords: Adolescent; Adult; Cell Line, Tumor; Child; Female; Homozygote; Humans; Male; Mutation; Pedigree; Phenotype; RecQ Helicases; Rothmund-Thomson Syndrome

Secondary prevention of early-onset sepsis: a less invasive Italian approach for managing neonates at risk. - Berardi, Alberto; Tzialla, Chryssoula; Travan, Laura; Bua, Jenny; Santori, Daniele; Azzalli, Milena; Spada, Caterina; Lucaccioni, Laura (Ital J Pediatr, 2018)
Strategies to prevent early-onset sepsis (EOS) have led to a substantial decline in many countries. However, one of the most controversial topics in neonatology is the management of asymptomatic full-term and late preterm neonates at risk for EOS, and guidelines lack substantial consensus regarding this issue. A strategy for managing neonates, entirely based on serial physical examinations, has been developed in two Italian regions. This strategy seems safe, while reducing laboratory tests and unnecessary antibiotics. In the current commentary we provide area-based data concerning the prevention of EOS in 2 northern Italian regions, and we detail the results of their strategy for managing healthy-appearing newborns at risk for EOS.

Serum Stem Cell Growth Factor Beta for the Prediction of Therapy Response in Hepatocellular Carcinoma. - Sukowati, Caecilia H C; Patti, Riccardo; Pascut, Devis; Ladju, Rusdina B; Tarchi, Paola; Zanotta, Nunzia; Comar, Manola; Tiribelli, Claudio; Crocè, Lory S (Biomed Res Int, 2018)
Introduction: Chronic inflammatory response is one of major contributors in the development of hepatocellular carcinoma (HCC). Inflammatory molecules, such as cytokines and growth factors in the circulation, can be useful in the diagnosis and prognosis of the patients. The stem cell growth factor beta (SCGF), a newly found protein, is a secreted sulfated glycoprotein and it functions as a growth factor for primitive hematopoietic progenitor cells. The level of SCGF had been reported to be elevated in several cancer types. However, there is very few or even no information on this protein in the study of HCC, even more in clinical studies. Methods: A multiplex immunoassay panel of 48 cytokines and growth factors were utilized to screen 68 sera from 29 HCC patients at pretreatment (T0), 1 month (T1), and 6 months (T6) after treatment by either radiofrequency ablation (RF) or transarterial chemoembolization (TACE). Treatment response was evaluated according to mRECIST criteria. Results: Immunoassay screening showed that the levels of IL-17, CTACK, TNF, IL-2R, IL-8, and SCGF were different in Complete Responders (CR) and Nonresponders (NR) groups. At T0 and T1, the SCGF level was significantly the highest in NR (23.8 and 40.7 ng/mL, respectively), followed by early recurrence (25.4 and 25.0 ng/mL), and CR (6.7 and 5.3 ng/mL), independently from HCV, stages, and treatment type. Low basal SCGF level was associated with longer disease-free survival compared to high SCGF. Conclusion: In this study, for the first time, we demonstrate that the high level of serum SCGF at pre- and posttreatment is associated with HCC nonresponsiveness.
Keywords: Aged; Carcinoma, Hepatocellular; Chemoembolization, Therapeutic; Female; Hematopoietic Cell Growth Factors; Humans; Liver Neoplasms; Male; Middle Aged; Neoplasm Recurrence, Local; Retrospective Studies; Stem Cells; Treatment Outcome

Total body irradiation and iron chelation treatment are associated with pancreatic injury following pediatric hematopoietic stem cell transplantation. - Maximova, Natalia; Gregori, Massimo; Simeone, Roberto; Sonzogni, Aurelio; Zanon, Davide; Boz, Giulia; D'Antiga, Lorenzo (Oncotarget, 2018)
Whereas many studies have addressed the risk of organ dysfunction following hematopoietic stem cell transplantation (HSCT), little is known about pancreatic susceptibility in this setting. We aimed to investigate the effect of iron overload (IO) and total body irradiation (TBI) on pancreatic function of children undergoing HSCT. We retrospectively evaluated children admitted between 2012-2016 fulfilling the following criteria: normal pancreatic iron concentration (PIC), regular pancreatic function before HSCT, availability of abdominal magnetic resonance imaging with gradient-recalled-echo sequences and a full set of biochemical markers of IO and pancreatic function performed before HSCT and at discharge. We divided the patients according to the use of TBI or myeloablative chemotherapy (MCHT) in the conditioning regimen. All patients with severe IO or moderate IO with a high risk of engraftment delay or transplantation-related complications underwent chelation therapy with deferoxamine (DFO) from the first day of conditioning to discharge. 63 patients had a HSCT in the study period, 13 did not fulfill the inclusion criteria; 50 (25 in each group) are included in the analysis, and did not show differences at baseline evaluation. At follow up testing the TBI group showed a significantly higher PIC (107,8±100,3 μmol/g vs 28,4±37,9 in MCHT group, p<0,0001). In the TBI group the patients who had DFO treatment had higher PIC (223,2±48,8 μmol/g vs 55,7±10,5 without DFO treatment, p<0,0001), and all patients having PIC >100 μmol/g at follow up had DFO-based chelation therapy, versus 26% of those with lower PIC (p<0,0001). The number of patients presenting exocrine pancreatic dysfunctions one month after transplantation was significantly higher in the TBI group (48% vs 4%; p<0.0001). The mean pancreatic volume reduction was significantly greater in the TBI group (39,1% vs 0,9% in the MCHT group; p<0,05), and was significantly worse on those who received DFO therapy. Based on our data, we suggest that TBI is detrimental for pancreatic functions, and speculate that DFO may contribute to the rapid pancreatic IO observed in these patients.

A transcriptomics study of hereditary angioedema attacks. - Castellano, Giuseppe; Divella, Chiara; Sallustio, Fabio; Montinaro, Vincenzo; Curci, Claudia; Zanichelli, Andrea; Bonanni, Erika; Suffritti, Chiara; Caccia, Sonia; Bossi, Fleur; Gallone, Anna; Schena, Francesco Paolo; et al. (J Allergy Clin Immunol, 2018)
BACKGROUND: Hereditary angioedema (HAE) caused by C1-inhibitor deficiency is a lifelong illness characterized by recurrent acute attacks of localized skin or mucosal edema. Activation of the kallikrein/bradykinin pathway at the endothelial cell level has a relevant pathogenetic role in acute HAE attacks. Moreover, other pathways are involved given the variable clinical expression of the disease in different patients. OBJECTIVE: We sought to explore the involvement of other putative genes in edema formation. METHODS: We performed a PBMC microarray gene expression analysis on RNA isolated from patients with HAE during an acute attack and compared them with the transcriptomic profile of the same patients in the remission phase. RESULTS: Gene expression analysis identified 23 genes significantly modulated during acute attacks that are involved primarily in the natural killer cell signaling and leukocyte extravasation signaling pathways. Gene set enrichment analysis showed a significant activation of relevant biological processes, such as response to external stimuli and protein processing (q < 0.05), suggesting involvement of PBMCs during acute HAE attacks. Upregulation of 2 genes, those encoding adrenomedullin and cellular receptor for urokinase plasminogen activator (uPAR), which occurs during an acute attack, was confirmed in PBMCs of 20 additional patients with HAE by using real-time PCR. Finally, in vitro studies demonstrated the involvement of uPAR in the generation of bradykinin and endothelial leakage. CONCLUSIONS: Our study demonstrates the increase in levels of adrenomedullin and uPAR in PBMCs during an acute HAE attack. Activation of these genes usually involved in regulation of vascular tone and in inflammatory response might have a pathogenic role by amplifying bradykinin production and edema formation in patients with HAE.

Vanishing Bile Ducts in the Long Term after Pediatric Hematopoietic Stem Cell Transplantation. - Maximova, Natalia; Sonzogni, Aurelio; Matarazzo, Lorenza; Ghirardi, Arianna; D'Antiga, Lorenzo (Biol Blood Marrow Transplant, 2018)
There are no structured studies on liver histology after hematopoietic stem cell transplantation (HSCT). We aimed to prospectively describe the clinicopathologic features of liver disease in the long term after HSCT in an observational, longitudinal study of liver histology in a consecutive cohort of children undergoing allogeneic HSCT. First liver biopsy was performed in presence of abnormal liver function tests and repeated per protocol thereafter. A previously reported semiquantitative score evaluating inflammation, cholestasis, and ductopenia (bile ducts-to-portal tracts ratio ≤ .5) was adopted. Graft-versus-host disease (GVHD) was diagnosed according to standard criteria. We evaluated 131 biopsies taken in 50 HSCTs performed in 47 children (mean age, 9.7 ± 5.2 years). Pre-HSCT chemotherapy was administered in 36 of 50 (72%). GVHD was diagnosed in 17 of 50 (34%). Over time the overall score decreased from a mean of 6 ± 2.7 to 3.25 ± .96 (P < .01), inflammation from 1.22 ± 1.19 to 1 ± 0 (not significant), and cholestasis from 3.9 ± 2.08 to 1.5 ± .58 (P < .01). Ductopenia, found in 113 of 131 biopsies (93%), worsened from .63 ± .35 to .16 ± .14 (P < .01). On multivariate analysis severe ductopenia (ratio ≤ .2) was associated with previous chemotherapy (P = .04), in particular with thiotepa, but not with history of GVHD. Vanishing bile duct syndrome after HSCT may be due to drug-induced liver disease. Longer follow-up will reveal whether these patients are prone to late liver-related morbidity and mortality.

What is known about deferasirox chelation therapy in pediatric HSCT recipients: two case reports of metabolic acidosis. - Fucile, Carmen; Mattioli, Francesca; Marini, Valeria; Gregori, Massimo; Sonzogni, Aurelio; Martelli, Antonietta; Maximova, Natalia (Ther Clin Risk Manag, 2018)
To date, in pediatric field, various hematological malignancies are increasingly treated with allogeneic hematopoietic stem cell transplantation (allo-HSCT). Iron overload and systemic siderosis often occur in this particular cohort of patients and are associated with poor prognosis. We describe herein the case of two allo-HSCT patients, on treatment with deferasirox; they showed histopathological elements compatible with venoocclusive disease or vanishing bile duct syndrome in ductopenic evolution before deferasirox started. The first patient developed drug-induced liver damage with metabolic acidosis and the second one a liver impairment with Fanconi syndrome. After withdrawing deferasirox treatment, both patients showed improvement. Measurements of drug plasma concentrations were performed by HPLC assay. The reduction and consequent disappearance of symptoms after the suspension of deferasirox substantiate its role in inducing hepatic damage, probably enabling the diagnosis of drug-induced liver damage. But the difficulties in diagnosing drug-related toxicity must be underlined, especially in compromised subjects. For these reasons, in patients requiring iron-chelating therapy, close and careful drug therapeutic monitoring is strongly recommended.

1000 Genomes-based meta-analysis identifies 10 novel loci for kidney function. - Gorski, Mathias; van der Most, Peter J; Teumer, Alexander; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Nolte, Ilja M; Cocca, Massimiliano; Taliun, Daniel; Gomez, Felicia; Li, Yong; Tayo, Bamidele; et al. (Sci Rep, 2017)
HapMap imputed genome-wide association studies (GWAS) have revealed >50 loci at which common variants with minor allele frequency >5% are associated with kidney function. GWAS using more complete reference sets for imputation, such as those from The 1000 Genomes project, promise to identify novel loci that have been missed by previous efforts. To investigate the value of such a more complete variant catalog, we conducted a GWAS meta-analysis of kidney function based on the estimated glomerular filtration rate (eGFR) in 110,517 European ancestry participants using 1000 Genomes imputed data. We identified 10 novel loci with p-value < 5 × 10 previously missed by HapMap-based GWAS. Six of these loci (HOXD8, ARL15, PIK3R1, EYA4, ASTN2, and EPB41L3) are tagged by common SNPs unique to the 1000 Genomes reference panel. Using pathway analysis, we identified 39 significant (FDR < 0.05) genes and 127 significantly (FDR < 0.05) enriched gene sets, which were missed by our previous analyses. Among those, the 10 identified novel genes are part of pathways of kidney development, carbohydrate metabolism, cardiac septum development and glucose metabolism. These results highlight the utility of re-imputing from denser reference panels, until whole-genome sequencing becomes feasible in large samples.
Keywords: Computational Biology; Gene Frequency; Genetic Loci; Genome, Human; Genome-Wide Association Study; Genotyping Techniques; Humans; Kidney; Polymorphism, Single Nucleotide

46,XY ovotesticular disorders of sex development: A therapeutic challenge. - Scarpa, Maria-Grazia; Grazia, Massimo Di; Tornese, Gianluca (Pediatr Rep, 2017)

ADA2 deficiency (DADA2) as an unrecognised cause of early onset polyarteritis nodosa and stroke: a multicentre national study. - Caorsi, Roberta; Penco, Federica; Grossi, Alice; Insalaco, Antonella; Omenetti, Alessia; Alessio, Maria; Conti, Giovanni; Marchetti, Federico; Picco, Paolo; Tommasini, Alberto; Martino, Silvana; Malattia, Clara; et al. (Ann Rheum Dis, 2017)
OBJECTIVES: To analyse the prevalence of mutations in patients diagnosed with early onset livedo reticularis and/or haemorrhagic/ischaemic strokes in the context of inflammation or polyarteritis nodosa (PAN). Forty-eight patients from 43 families were included in the study. METHODS: Direct sequencing of was performed by Sanger analysis. Adenosine deaminase 2 (ADA2) enzymatic activity was analysed in monocyte isolated from patients and healthy controls incubated with adenosine and with or without an ADA1 inhibitor. RESULTS: Biallelic homozygous or compound heterozygous mutations were detected in 15/48 patients. A heterozygous disease-associated mutation (p.G47V) was observed in two affected brothers. The mean age of onset of the genetically positive patients was 24 months (6 months to 7 years). Ten patients displayed one or more cerebral strokes during their disease course. Low immunoglobulin levels were detected in six patients. Thalidomide and anti-TNF (tumour necrosis factor) blockers were the most effective drugs. Patients without mutations had a later age at disease onset, a lower prevalence of neurological and skin manifestations; one of these patients displayed all the clinical features of adenosine deaminase 2deficiency (DADA2) and a defective enzymatic activity suggesting the presence of a missed mutation or a synthesis defect. CONCLUSIONS: DADA2 accounts for paediatric patients diagnosed with PAN-like disease and strokes and might explain an unrecognised condition in patients followed by adult rheumatologist. Timely diagnosis and treatment with anti-TNF agents are crucial for the prevention of severe complications of the disease. Functional assay to measure ADA2 activity should complement genetic testing in patients with non-confirming genotypes.
Keywords: Adenosine Deaminase; Adolescent; Age of Onset; Case-Control Studies; Child; Child, Preschool; DNA Mutational Analysis; Female; Heterozygote; Homozygote; Humans; Immunoglobulins; Immunosuppressive Agents; Infant; Intercellular Signaling Peptides and Proteins; Italy; Livedo Reticularis; Male; Pedigree; Polyarteritis Nodosa; Stroke; Thalidomide; Tumor Necrosis Factor-alpha; Young Adult

Amniocentesis and chorionic villus sampling in HIV-infected pregnant women: a multicentre case series. - Floridia, M; Masuelli, G; Meloni, A; Cetin, I; Tamburrini, E; Cavaliere, A F; Dalzero, S; Sansone, M; Alberico, S; Guerra, B; Spinillo, A; Chiadò Fiorio Tin, M; et al. (BJOG, 2017)
OBJECTIVES: To assess in pregnant women with HIV the rates of amniocentesis and chorionic villus sampling (CVS), and the outcomes associated with such procedures. DESIGN: Observational study. Data from the Italian National Program on Surveillance on Antiretroviral Treatment in Pregnancy were used. SETTING: University and hospital clinics. POPULATION: Pregnant women with HIV. METHODS: Temporal trends were analysed by analysis of variance and by the Chi-square test for trend. Quantitative variables were compared by Student's t-test and categorical data by the Chi-square test, with odds ratios and 95% confidence intervals calculated. MAIN OUTCOME MEASURES: Rate of invasive testing, intrauterine death, HIV transmission. RESULTS: Between 2001 and 2015, among 2065 pregnancies in women with HIV, 113 (5.5%) had invasive tests performed. The procedures were conducted under antiretroviral treatment in 99 cases (87.6%), with a significant increase over time in the proportion of tests performed under highly active antiretroviral therapy (HAART) (100% in 2011-2015). Three intrauterine deaths were observed (2.6%), and 14 pregnancies were terminated because of fetal anomalies. Among 96 live newborns, eight had no information available on HIV status. Among the remaining 88 cases with either amniocentesis (n = 75), CVS (n = 12), or both (n = 1), two HIV transmissions occurred (2.3%). No HIV transmission occurred among the women who were on HAART at the time of invasive testing, and none after 2005. CONCLUSIONS: The findings reinforce the assumption that invasive prenatal testing does not increase the risk of HIV vertical transmission among pregnant women under suppressive antiretroviral treatment. TWEETABLE ABSTRACT: No HIV transmission occurred among women who underwent amniocentesis or CVS under effective anti-HIV regimens.
Keywords: Adult; Amniocentesis; Analysis of Variance; Anti-Retroviral Agents; Chi-Square Distribution; Chorionic Villi Sampling; Female; Fetal Death; HIV Infections; Humans; Infectious Disease Transmission, Vertical; Odds Ratio; Pregnancy; Pregnancy Complications, Infectious

ANCA-associated vasculitis in childhood: recent advances. - Calatroni, Marta; Oliva, Elena; Gianfreda, Davide; Gregorini, Gina; Allinovi, Marco; Ramirez, Giuseppe A; Bozzolo, Enrica P; Monti, Sara; Bracaglia, Claudia; Marucci, Giulia; Bodria, Monica; Sinico, Renato A; et al. (Ital J Pediatr, 2017)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitides are rare systemic diseases that usually occur in adulthood. They comprise granulomatosis with polyangiitis (GPA, Wegener's), microscopic polyangiitis (MPA) and eosinophilic granulomatosis with polyangiitis (EGPA, Churg-Strauss syndrome). Their clinical presentation is often heterogeneous, with frequent involvement of the respiratory tract, the kidney, the skin and the joints. ANCA-associated vasculitis is rare in childhood but North-American and European cohort studies performed during the last decade have clarified their phenotype, patterns of renal involvement and their prognostic implications, and outcome. Herein, we review the main clinical and therapeutic aspects of childhood-onset ANCA-associated vasculitis, and provide preliminary data on demographic characteristics and organ manifestations of an Italian multicentre cohort.
Keywords: Age Distribution; Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis; Antibodies, Antineutrophil Cytoplasmic; Child; Child, Preschool; Churg-Strauss Syndrome; Female; Granulomatosis with Polyangiitis; Humans; Incidence; Male; Microscopic Polyangiitis; Rare Diseases; Risk Assessment; Severity of Illness Index; Sex Distribution; Survival Rate

and Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2017)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (: 111,666; : 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (, , and ; <3.7×10), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, (=5.4×10 by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of and -knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.
Keywords: Animals; Exome; Genetic Loci; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Protein Tyrosine Phosphatases; Proto-Oncogene Proteins; Son of Sevenless Proteins; Zebrafish

Association between thyroid hormones and TRAIL. - Bernardi, Stella; Bossi, Fleur; Toffoli, Barbara; Giudici, Fabiola; Bramante, Alessandra; Furlanis, Giulia; Stenner, Elisabetta; Secchiero, Paola; Zauli, Giorgio; Carretta, Renzo; Fabris, Bruno (Clin Biochem, 2017)
INTRODUCTION: Recent studies suggest that a circulating protein called TRAIL (TNF-related apoptosis-inducing ligand) might have a role in the regulation of body weight and metabolism. Interestingly, thyroid hormones seem to increase TRAIL tissue expression. This study aimed at evaluating whether overt thyroid disorders affected circulating TRAIL levels. METHODS: TRAIL circulating levels were measured in euthyroid, hyperthyroid, and hypothyroid patients before and after thyroid function normalization. Univariate and multivariate analyses were performed to evaluate the correlation between thyroid hormones and TRAIL. Then, the stimulatory effect of both triiodothyronine (T3) and thyroxine (T4) on TRAIL was evaluated in vitro on peripheral blood mononuclear cells. RESULTS: Circulating levels of TRAIL significantly increased in hyperthyroid and decreased in hypothyroid patients as compared to controls. Once thyroid function was restored, TRAIL levels normalized. There was an independent association between TRAIL and both fT3 and fT4. Consistent with these findings, T3 and T4 stimulated TRAIL release in vitro. CONCLUSION: Here we show that thyroid hormones are associated with TRAIL expression in vivo and stimulate TRAIL expression in vitro. Given the overlap between the metabolic effects of thyroid hormones and TRAIL, this work sheds light on the possibility that TRAIL might be one of the molecules mediating thyroid hormones peripheral effects.
Keywords: Aged; Female; Gene Expression Regulation; Humans; Hyperthyroidism; Hypothyroidism; Leukocytes, Mononuclear; Male; Middle Aged; Thyroxine; TNF-Related Apoptosis-Inducing Ligand; Triiodothyronine

Autoimmune neutropenia of childhood secondary to other autoimmune disorders: Data from the Italian neutropenia registry. - Farruggia, Piero; Puccio, Giuseppe; Fioredda, Francesca; Lanza, Tiziana; Porretti, Laura; Ramenghi, Ugo; Barone, Angelica; Bonanomi, Sonia; Finocchi, Andrea; Ghilardi, Roberta; Ladogana, Saverio; Marra, Nicoletta; et al. (Am J Hematol, 2017)
Keywords: Autoimmune Diseases; Child; Disease Susceptibility; Female; Humans; Immunoglobulins, Intravenous; Immunosuppressive Agents; Infant, Newborn; Infant, Premature; Infant, Premature, Diseases; Italy; Male; Neutropenia; Prevalence; Registries

Bipolar Disorder With Psychotic Features and Ocular Toxoplasmosis: A Possible Pathogenetic Role of the Parasite? - Del Grande, Claudia; Contini, Carlo; Schiavi, Elisa; Rutigliano, Grazia; Maritati, Martina; Seraceni, Silva; Pinto, Barbara; Dell'Osso, Liliana; Bruschi, Fabrizio (J Nerv Ment Dis, 2017)
Recent evidence suggests the involvement of Toxoplasma gondii infection in the emergence of psychotic and affective disorders. In this report, we describe the case of a young Brazilian woman affected by recurrent ocular toxoplasmosis and presenting with a manic episode with psychotic features in the context of a diagnosis of Bipolar Disorder (BD), type I. We observed a relationship between ocular manifestations and the clinical course of bipolar illness, confirmed by molecular analyses (nested-PCR), as well as by the high level of T. gondii specific IgG. This case report is the first showing the presence of circulating parasite DNA at the time of occurrence of psychiatric symptoms, thus providing further support for a possible role of the parasite in the pathogenesis of some cases of BD.
Keywords: Adult; Bipolar Disorder; Brazil; Female; Humans; Toxoplasmosis, Ocular; Young Adult

CCR5Δ32 and the genetic susceptibility to rheumatoid arthritis in admixed populations: a multicentre study. - Toson, Bruno; Dos Santos, Eduardo José; Adelino, José Eduardo; Sandrin-Garcia, Paula; Crovella, Sergio; Louzada-Júnior, Paulo; Oliveira, Renê Donizete Ribeiro; Pedroza, Larysse Santa Rosa Aquino; de Fátima Lobato Cunha Sauma, Maria; de Lima, Clayton Pereira Silva; Barbosa, Fabiola Brasil; Brenol, Claiton Viegas; et al. (Rheumatology (Oxford), 2017)
Keywords: Arthritis, Rheumatoid; Brazil; Case-Control Studies; Consanguinity; Gene Frequency; Genetic Predisposition to Disease; Humans; Polymorphism, Single Nucleotide; Receptors, CCR5

Cervical stitch (cerclage) for preventing preterm birth in singleton pregnancy. - Alfirevic, Zarko; Stampalija, Tamara; Medley, Nancy (Cochrane Database Syst Rev, 2017)
BACKGROUND: Cervical cerclage is a well-known surgical procedure carried out during pregnancy. It involves positioning of a suture (stitch) around the neck of the womb (cervix), aiming to give mechanical support to the cervix and thereby reduce risk of preterm birth. The effectiveness and safety of this procedure remains controversial. This is an update of a review last published in 2012. OBJECTIVES: To assess whether the use of cervical stitch in singleton pregnancy at high risk of pregnancy loss based on woman's history and/or ultrasound finding of 'short cervix' and/or physical exam improves subsequent obstetric care and fetal outcome. SEARCH METHODS: We searched Cochrane Pregnancy and Childbirth's Trials Register (30 June 2016) and reference lists of identified studies. SELECTION CRITERIA: We included all randomised trials of cervical suturing in singleton pregnancies. Cervical stitch was carried out when the pregnancy was considered to be of sufficiently high risk due to a woman's history, a finding of short cervix on ultrasound or other indication determined by physical exam. We included any study that compared cerclage with either no treatment or any alternative intervention. We planned to include cluster-randomised studies but not cross-over trials. We excluded quasi-randomised studies. We included studies reported in abstract form only. DATA COLLECTION AND ANALYSIS: Three review authors independently assessed trials for inclusion. Two review authors independently assessed risk of bias and extracted data. We resolved discrepancies by discussion. Data were checked for accuracy. The quality of the evidence was assessed using the GRADE approach. MAIN RESULTS: This updated review includes a total of 15 trials (3490 women); three trials were added for this update (152 women). Cerclage versus no cerclageOverall, cerclage probably leads to a reduced risk of perinatal death when compared with no cerclage, although the confidence interval (CI) crosses the line of no effect (RR 0.82, 95% CI 0.65 to 1.04; 10 studies, 2927 women; moderate quality evidence). Considering stillbirths and neonatal deaths separately reduced the numbers of events and sample size. Although the relative effect of cerclage is similar, estimates were less reliable with fewer data and assessed as of low quality (stillbirths RR 0.89, 95% CI 0.45 to 1.75; 5 studies, 1803 women; low quality evidence; neonatal deaths before discharge RR 0.85, 95% CI 0.53 to 1.39; 6 studies, 1714 women; low quality evidence). Serious neonatal morbidity was similar with and without cerclage (RR 0.80, 95% CI 0.55 to 1.18; 6 studies, 883 women; low-quality evidence). Pregnant women with and without cerclage were equally likely to have a baby discharged home healthy (RR 1.02, 95% CI 0.97 to 1.06; 4 studies, 657 women; moderate quality evidence).Pregnant women with cerclage were less likely to have preterm births compared to controls before 37, 34 (average RR 0.77, 95% CI 0.66 to 0.89; 9 studies, 2415 women; high quality evidence) and 28 completed weeks of gestation.Five subgroups based on clinical indication provided data for analysis (history-indicated; short cervix based on one-off ultrasound in high risk women; short cervix found by serial scans in high risk women; physical exam-indicated; and short cervix found on scan in low risk or mixed populations). There were too few trials in these clinical subgroups to make meaningful conclusions and no evidence of differential effects. Cerclage versus progesteroneTwo trials (129 women) compared cerclage to prevention with vaginal progesterone in high risk women with short cervix on ultrasound; these trials were too small to detect reliable, clinically important differences for any review outcome. One included trial compared cerclage with intramuscular progesterone (75 women) which lacked power to detect group differences. History indicated cerclage versus ultrasound indicated cerclageEvidence from two trials (344 women) was too limited to establish differences for clinically important outcomes. AUTHORS' CONCLUSIONS: Cervical cerclage reduces the risk of preterm birth in women at high-risk of preterm birth and probably reduces risk of perinatal deaths. There was no evidence of any differential effect of cerclage based on previous obstetric history or short cervix indications, but data were limited for all clinical groups. The question of whether cerclage is more or less effective than other preventative treatments, particularly vaginal progesterone, remains unanswered.
Keywords: Administration, Intravaginal; Cerclage, Cervical; Cesarean Section; Female; Humans; Injections, Intramuscular; Perinatal Death; Pregnancy; Premature Birth; Progesterone; Randomized Controlled Trials as Topic; Stillbirth; Suture Techniques

Child and Adolescent Health From 1990 to 2015: Findings From the Global Burden of Diseases, Injuries, and Risk Factors 2015 Study. - Kassebaum, Nicholas; Kyu, Hmwe Hmwe; Zoeckler, Leo; Olsen, Helen Elizabeth; Thomas, Katie; Pinho, Christine; Bhutta, Zulfiqar A; Dandona, Lalit; Ferrari, Alize; Ghiwot, Tsegaye Tewelde; Hay, Simon I; Kinfu, Yohannes; et al. (JAMA Pediatr, 2017)
Importance: Comprehensive and timely monitoring of disease burden in all age groups, including children and adolescents, is essential for improving population health. Objective: To quantify and describe levels and trends of mortality and nonfatal health outcomes among children and adolescents from 1990 to 2015 to provide a framework for policy discussion. Evidence Review: Cause-specific mortality and nonfatal health outcomes were analyzed for 195 countries and territories by age group, sex, and year from 1990 to 2015 using standardized approaches for data processing and statistical modeling, with subsequent analysis of the findings to describe levels and trends across geography and time among children and adolescents 19 years or younger. A composite indicator of income, education, and fertility was developed (Socio-demographic Index [SDI]) for each geographic unit and year, which evaluates the historical association between SDI and health loss. Findings: Global child and adolescent mortality decreased from 14.18 million (95% uncertainty interval [UI], 14.09 million to 14.28 million) deaths in 1990 to 7.26 million (95% UI, 7.14 million to 7.39 million) deaths in 2015, but progress has been unevenly distributed. Countries with a lower SDI had a larger proportion of mortality burden (75%) in 2015 than was the case in 1990 (61%). Most deaths in 2015 occurred in South Asia and sub-Saharan Africa. Global trends were driven by reductions in mortality owing to infectious, nutritional, and neonatal disorders, which in the aggregate led to a relative increase in the importance of noncommunicable diseases and injuries in explaining global disease burden. The absolute burden of disability in children and adolescents increased 4.3% (95% UI, 3.1%-5.6%) from 1990 to 2015, with much of the increase owing to population growth and improved survival for children and adolescents to older ages. Other than infectious conditions, many top causes of disability are associated with long-term sequelae of conditions present at birth (eg, neonatal disorders, congenital birth defects, and hemoglobinopathies) and complications of a variety of infections and nutritional deficiencies. Anemia, developmental intellectual disability, hearing loss, epilepsy, and vision loss are important contributors to childhood disability that can arise from multiple causes. Maternal and reproductive health remains a key cause of disease burden in adolescent females, especially in lower-SDI countries. In low-SDI countries, mortality is the primary driver of health loss for children and adolescents, whereas disability predominates in higher-SDI locations; the specific pattern of epidemiological transition varies across diseases and injuries. Conclusions and Relevance: Consistent international attention and investment have led to sustained improvements in causes of health loss among children and adolescents in many countries, although progress has been uneven. The persistence of infectious diseases in some countries, coupled with ongoing epidemiologic transition to injuries and noncommunicable diseases, require all countries to carefully evaluate and implement appropriate strategies to maximize the health of their children and adolescents and for the international community to carefully consider which elements of child and adolescent health should be monitored.
Keywords: Adolescent; Adolescent Health; Age Factors; Cause of Death; Child; Child Health; Child Mortality; Disabled Children; Female; Global Burden of Disease; Global Health; Humans; Male; Pregnancy; Pregnancy Complications; Risk Factors; Sex Factors; Wounds and Injuries

Circulating osteoprotegerin is associated with chronic kidney disease in hypertensive patients. - Bernardi, Stella; Toffoli, Barbara; Bossi, Fleur; Candido, Riccardo; Stenner, Elisabetta; Carretta, Renzo; Barbone, Fabio; Fabris, Bruno (BMC Nephrol, 2017)
BACKGROUND: Osteoprotegerin (OPG) is a glycoprotein that plays an important regulatory role in the skeletal, vascular, and immune system. It has been shown that OPG predicts chronic kidney disease (CKD) in diabetic patients. We hypothesized that OPG could be a risk marker of CKD development also in non-diabetic hypertensive patients. METHODS: A case-control study was carried out to measure circulating OPG levels in 42 hypertensive patients with CKD and in 141 hypertensive patients without CKD. A potential relationship between OPG and the presence of CKD was investigated and a receiver-operating characteristic (ROC) curve was designed thereafter to identify a cut-off value of OPG that best explained the presence of CKD. Secondly, to evaluate whether OPG increase could affect the kidney, 18 C57BL/6J mice were randomized to be treated with saline or recombinant OPG every 3 weeks for 12 weeks. RESULTS: Circulating OPG levels were significantly higher in hypertensive patients with CKD, and there was a significant inverse association between OPG and renal function, that was independent from other variables. ROC analysis showed that OPG levels had a high statistically predictive value on CKD in hypertensive patients, which was greater than that of hypertension. The OPG best cut-off value associated with CKD was 1109.19 ng/L. In the experimental study, OPG delivery significantly increased the gene expression of pro-inflammatory and pro-fibrotic mediators, as well as the glomerular nitrosylation of proteins. CONCLUSIONS: This study shows that OPG is associated with CKD in hypertensive patients, where it might have a higher predictive value than that of hypertension for CKD development. Secondly, we found that OPG delivery significantly increased the expression of molecular pathways involved in kidney damage. Further longitudinal studies are needed not only to evaluate whether OPG predicts CKD development but also to clarify whether OPG should be considered a risk factor for CKD.
Keywords: Aged; Animals; Biomarkers; Case-Control Studies; Female; Follow-Up Studies; Humans; Hypertension; Male; Mice; Mice, Inbred C57BL; Middle Aged; Osteoprotegerin; Random Allocation; Renal Insufficiency, Chronic

[Clinical and molecular study in a family with autosomal dominant hypohidrotic ectodermal dysplasia]. - Callea, Michele; Cammarata-Scalisi, Francisco; Willoughby, Colin E; Giglio, Sabrina R; Sani, Ilaria; Bargiacchi, Sara; Traficante, Giovanna; Bellacchio, Emanuele; Tadini, Gianluca; Yavuz, Izzet; Galeotti, Angela; Clarich, Gabriella (Arch Argent Pediatr, 2017)
Hypohidrotic ectodermal dysplasia (HED) is a rare disease characterized by deficiency in development of structure derived from the ectoderm and is caused by mutations in the genes EDA, EDAR, or EDARADD. Phenotypes caused by mutations in these three may exhibit similar clinical features, explained by a common signaling pathway. Mutations in EDA gene cause X linked HED, which is the most common form. Mutations in EDAR and EDARADD genes cause autosomal dominant and recessive form of HED. The most striking clinical findings in HED are hypodontia, hypotrichosis and hypohidrosis that can lead to episodes of hyperthermia. We report on clinical findings in a child with HED with autosomal dominant inheritance pattern with a heterozygous mutation c.1072C>T (p.Arg358X) in the EDAR gene. A review of the literature with regard to other cases presenting the same mutation has been carried out and discussed.
Keywords: Child, Preschool; Ectodermal Dysplasia 1, Anhidrotic; Edar Receptor; Humans; Male; Mutation; Pedigree

Common variants in CLDN14 are associated with differential excretion of magnesium over calcium in urine. - Corre, Tanguy; Olinger, Eric; Harris, Sarah E; Traglia, Michela; Ulivi, Sheila; Lenarduzzi, Stefania; Belge, Hendrica; Youhanna, Sonia; Tokonami, Natsuko; Bonny, Olivier; Houillier, Pascal; Polasek, Ozren; et al. (Pflugers Arch, 2017)
The nature and importance of genetic factors regulating the differential handling of Ca and Mg by the renal tubule in the general population are poorly defined. We conducted a genome-wide meta-analysis of urinary magnesium-to-calcium ratio to identify associated common genetic variants. We included 9320 adults of European descent from four genetic isolates and three urban cohorts. Urinary magnesium and calcium concentrations were measured centrally in spot urine, and each study conducted linear regression analysis of urinary magnesium-to-calcium ratio on ~2.5 million single-nucleotide polymorphisms (SNPs) using an additive model. We investigated, in mouse, the renal expression profile of the top candidate gene and its variation upon changes in dietary magnesium. The genome-wide analysis evidenced a top locus (rs172639, p = 1.7 × 10), encompassing CLDN14, the gene coding for claudin-14, that was genome-wide significant when using urinary magnesium-to-calcium ratio, but not either one taken separately. In mouse, claudin-14 is expressed in the distal nephron segments specifically handling magnesium, and its expression is regulated by chronic changes in dietary magnesium content. A genome-wide approach identified common variants in the CLDN14 gene exerting a robust influence on the differential excretion of Mg over Ca in urine. These data highlight the power of urinary electrolyte ratios to unravel genetic determinants of renal tubular function. Coupled with mouse experiments, these results support a major role for claudin-14, a gene associated with kidney stones, in the differential paracellular handling of divalent cations by the renal tubule.
Keywords: Animals; Calcium; Claudins; Humans; Kidney Tubules; Magnesium; Polymorphism, Single Nucleotide; Urine

Comparison of Efficacy and Safety of Caspofungin Versus Micafungin in Pediatric Allogeneic Stem Cell Transplant Recipients: A Retrospective Analysis. - Maximova, Natalia; Schillani, Giulia; Simeone, Roberto; Maestro, Alessandra; Zanon, Davide (Adv Ther, 2017)
INTRODUCTION: The high morbidity and mortality associated with invasive fungal infections (IFIs) provide the rationale for antifungal prophylaxis in immuno-compromised pediatric patients undergoing hematopoietic stem cell transplantation (HSCT). Caspofungin and micafungin are antifungal agents of interest for prophylaxis of IFIs because of their potency against Candida and minimal toxicity or interactions with other drugs. Few studies have demonstrated the safety and efficacy of such echinocandins as prophylaxis for IFIs in patients undergoing HSCT. METHODS: This retrospective cohort study compared caspofungin and micafungin for prevention of IFIs in 93 pediatric patients undergoing HSCT for oncological or non-oncological disease. The observation began with the first dose of antifungal agent and ended 3 months after transplantation. RESULTS: Patients in the micafungin group had a higher overall treatment success rate of 87.2 versus 84.8% in the caspofungin group, but the difference was not significant. There were no statistically significant differences in the incidence or type of proven/probable IFIs between the 2 groups. The low incidence of death did not differ statistically between the groups. Patients in the caspofungin group presented more frequently with fever, during and after neutropenia. In both groups, we observed an expected worsening of blood chemistry parameters. There were no adverse events definitely attributable to the two antifungal agents. CONCLUSION: These results demonstrate good efficacy and tolerability for caspofungin and micafungin. However, better results with respect to the incidence and resolution of fever in the micafungin group may suggest its use in preference to that of caspofungin.
Keywords: Adolescent; Antifungal Agents; Caspofungin; Child; Child, Preschool; Cohort Studies; Echinocandins; Female; Hematopoietic Stem Cell Transplantation; Humans; Infant; Infant, Newborn; Lipopeptides; Male; Micafungin; Mycoses; Neutropenia; Retrospective Studies

A complete duplication of X chromosome resulting in a tricentric isochromosome originated by centromere repositioning. - Villa, N; Conconi, D; Benussi, D Gambel; Tornese, G; Crosti, F; Sala, E; Dalprà, L; Pecile, V (Mol Cytogenet, 2017)
BACKGROUND: Neocentromeres are rare and considered chromosomal aberrations, because a non-centromeric region evolves in an active centromere by mutation. The literature reported several structural anomalies of X chromosome and they influence the female reproductive capacity or are associated to Turner syndrome in the presence of monosomy X cell line. CASE PRESENTATION: We report a case of chromosome X complex rearrangement found in a prenatal diagnosis. The fetal karyotype showed a mosaicism with a 45,X cell line and a 46 chromosomes second line with a big marker, instead of a sex chromosome. The marker morphology and fluorescence in situ hybridization (FISH) characterization allowed us to identify a tricentric X chromosome constituted by two complete X chromosome fused at the p arms telomere and an active neocentromere in the middle, at the union of the two Xp arms, where usually are the telomeric regions. FISH also showed the presence of a paracentric inversion of both Xp arms. Furthermore, fragility figures were found in 56% of metaphases from peripheral blood lymphocytes culture at birth: a shorter marker chromosome and an apparently acentric fragment frequently lost. CONCLUSIONS: At our knowledge, this is the first isochromosome of an entire non-acrocentric chromosome. The neocentromere is constituted by canonical sequences but localized in an unusual position and the original centromeres are inactivated. We speculated that marker chromosome was the result of a double rearrangement: firstly, a paracentric inversion which involved the Xp arm, shifting a part of the centromere at the p end and subsequently a duplication of the entire X chromosome, which gave rise to an isochromosome. It is possible to suppose that the first event could be a result of a non-allelic homologous recombination mediated by inverted low-copy repeats. As expected, our case shows a Turner phenotype with mild facial features and no major skeletal deformity, normal psychomotor development and a spontaneous development of puberty and menarche, although with irregular menses since the last follow-up.

Cubosomes for in vivo fluorescence lifetime imaging. - Biffi, Stefania; Andolfi, Laura; Caltagirone, Claudia; Garrovo, Chiara; Falchi, Angela M; Lippolis, Vito; Lorenzon, Andrea; Macor, Paolo; Meli, Valeria; Monduzzi, Maura; Obiols-Rabasa, Marc; Petrizza, Luca; et al. (Nanotechnology, 2017)
Herein we provided the first proof of principle for in vivo fluorescence optical imaging application using monoolein-based cubosomes in a healthy mouse animal model. This formulation, administered at a non-cytotoxic concentration, was capable of providing both exogenous contrast for NIR fluorescence imaging with very high efficiency and chemospecific information upon lifetime analysis. Time-resolved measurements of fluorescence after the intravenous injection of cubosomes revealed that the dye rapidly accumulated mainly in the liver, while lifetimes profiles obtained in vivo allowed for discriminating between free dye or dye embedded within the cubosome nanostructure after injection.
Keywords: Animals; Carbocyanines; Cell Survival; Drug Compounding; Erythrocytes; Female; Fluorescent Dyes; Glycerides; Humans; Injections, Intravenous; Liposomes; Liver; Mice; Mice, Inbred BALB C; Nanoparticles; NIH 3T3 Cells; Optical Imaging; Particle Size; Spectroscopy, Near-Infrared; Time-Lapse Imaging

CYP3A genes and the association between prenatal methylmercury exposure and neurodevelopment. - Llop, Sabrina; Tran, Van; Ballester, Ferran; Barbone, Fabio; Sofianou-Katsoulis, Aikaterini; Sunyer, Jordi; Engström, Karin; Alhamdow, Ayman; Love, Tanzy M; Watson, Gene E; Bustamante, Mariona; Murcia, Mario; et al. (Environ Int, 2017)
BACKGROUND: Results on the association between prenatal exposure to methylmercury (MeHg) and child neuropsychological development are heterogeneous. Underlying genetic differences across study populations could contribute to this varied response to MeHg. Studies in Drosophila have identified the cytochrome p450 3A (CYP3A) family as candidate MeHg susceptibility genes. OBJECTIVES: We evaluated whether genetic variation in CYP3A genes influences the association between prenatal exposure to MeHg and child neuropsychological development. METHODS: The study population included 2639 children from three birth cohort studies: two subcohorts in Seychelles (SCDS) (n=1160, 20 and 30months of age, studied during the years 2001-2012), two subcohorts from Spain (INMA) (n=625, 14months of age, 2003-2009), and two subcohorts from Italy and Greece (PHIME) (n=854, 18months of age, 2006-2011). Total mercury, as a surrogate of MeHg, was analyzed in maternal hair and/or cord blood samples. Neuropsychological development was evaluated using Bayley Scales of Infant Development (BSID). Three functional polymorphisms in the CYP3A family were analyzed: rs2257401 (CYP3A7), rs776746 (CYP3A5), and rs2740574 (CYP3A4). RESULTS: There was no association between CYP3A polymorphisms and cord mercury concentrations. The scores for the BSID mental scale improved with increasing cord blood mercury concentrations for carriers of the most active alleles (β[95% CI]:=2.9[1.53,4.27] for CYP3A7 rs2257401 GG+GC, 2.51[1.04,3.98] for CYP3A5 rs776746 AA+AG and 2.31[0.12,4.50] for CYP3A4 rs2740574 GG+AG). This association was near the null for CYP3A7 CC, CYP3A5 GG and CYP3A4 AA genotypes. The interaction between the CYP3A genes and total mercury was significant (p<0.05) in European cohorts only. CONCLUSIONS: Our results suggest that the polymorphisms in CYP3A genes may modify the response to dietary MeHg exposure during early life development.
Keywords: Adult; Child Development; Child, Preschool; Cohort Studies; Cytochrome P-450 CYP3A; Female; Fetal Blood; Genotype; Greece; Humans; Infant; Italy; Male; Mercury; Methylmercury Compounds; Neurodevelopmental Disorders; Neuropsychological Tests; Polymorphism, Genetic; Pregnancy; Prenatal Exposure Delayed Effects; Seychelles; Spain

DEFB1 polymorphisms and salivary hBD-1 concentration in Oral Lichen Planus patients and healthy subjects. - Polesello, Vania; Zupin, Luisa; Di Lenarda, Roberto; Biasotto, Matteo; Pozzato, Gabriele; Ottaviani, Giulia; Gobbo, Margherita; Crovella, Sergio; Segat, Ludovica (Arch Oral Biol, 2017)
OBJECTIVES: The aetiology of Oral Lichen Planus (OLP), a chronic inflammatory disease of oral mucosa, is not yet well understood. Since innate immunity may be hypothesized as involved in the susceptibility to OLP, we studied human beta defensin 1 (hBD-1) an antimicrobial peptide constitutively expressed in the saliva, looking at functional genetic variants possibly able to diminish hBD-1 production an consequently conferring major susceptibility to OLP. DESIGN: We analysed three DEFB1 polymorphisms at 5' UTR, -52G>A (rs1799946), -44C>G (rs1800972), -20G>A (rs11362) and two DEFB1 polymorphisms at 3'UTR, c*5G>A (rs1047031), c*87A>G (rs1800971), with the aim of correlating these genetic variants and hBD-1 salivary level in a group of OLP patients and in healthy subjects. We also evaluated hBD-1 salivary concentrations, using ELISA, in OLP and healthy controls. RESULTS: We compared hBD-1 concentrations in OLP and healthy subjects: hBD-1 concentration was significantly higher in OLP patients respect to control. When considering the correlation between DEFB1 polymorphisms genotypes and hBD-1 expression levels, significant results were obtained for SNPs -52G>A (p=0.03 both in OLP patients and healthy individuals) and -44C>G (p=0.02 in OLP patients). CONCLUSIONS: hBD-1 production was different between OLP and healthy subjects (not age-matched with OLP). DEFB1 gene polymorphisms, -52G>A and -44C>G, correlated with hBD-1 salivary concentrations.
Keywords: 5' Untranslated Regions; Adult; Aged; Aged, 80 and over; beta-Defensins; Female; Genetic Predisposition to Disease; Genotype; Humans; Lichen Planus, Oral; Male; Middle Aged; Polymorphism, Single Nucleotide; Saliva; Sequence Analysis, DNA

Defects in mitochondrial energetic function compels Fanconi Anaemia cells to glycolytic metabolism. - Cappelli, Enrico; Cuccarolo, Paola; Stroppiana, Giorgia; Miano, Maurizio; Bottega, Roberta; Cossu, Vanessa; Degan, Paolo; Ravera, Silvia (Biochim Biophys Acta Mol Basis Dis, 2017)
Energetic metabolism plays an essential role in the differentiation of haematopoietic stem cells (HSC). In Fanconi Anaemia (FA), DNA damage is accumulated during HSC differentiation, an event that is likely associated with bone marrow failure (BMF). One of the sources of the DNA damage is altered mitochondrial metabolism and an associated increment of oxidative stress. Recently, altered mitochondrial morphology and a deficit in the energetic activity in FA cells have been reported. Considering that mitochondria are the principal site of aerobic ATP production, we investigated FA metabolism in order to understand what pathways are able to compensate for this energy deficiency. In this work, we report that the impairment in mitochondrial oxidative phosphorylation (OXPHOS) in FA cells is countered by an increase in glycolytic flux. By contrast, glutaminolysis appears lower with respect to controls. Therefore, it is possible to conclude that in FA cells glycolysis represents the main pathway for producing energy, balancing the NADH/NAD ratio by the conversion of pyruvate to lactate. Finally, we show that a forced switch from glycolytic to OXPHOS metabolism increases FA cell oxidative stress. This could be the cause of the impoverishment in bone marrow HSC during exit from the homeostatic quiescent state. This is the first work that systematically explores FA energy metabolism, highlighting its flaws, and discusses the possible relationships between these defects and BMF.
Keywords: Cell Line; Fanconi Anemia; Glycolysis; Humans; Mitochondria; Oxidative Phosphorylation; Oxidative Stress

Describing Kawasaki shock syndrome: results from a retrospective study and literature review. - Taddio, Andrea; Rossi, Eleonora Dei; Monasta, Lorenzo; Pastore, Serena; Tommasini, Alberto; Lepore, Loredana; Bronzetti, Gabriele; Marrani, Edoardo; Mottolese, Biancamaria D'Agata; Simonini, Gabriele; Cimaz, Rolando; Ventura, Alessandro (Clin Rheumatol, 2017)
Kawasaki shock syndrome (KSS) is a rare manifestation of Kawasaki disease (KD) characterized by systolic hypotension or clinical signs of poor perfusion. The objectives of the study are to describe the main clinical presentation, echocardiographic, and laboratory findings, as well as the treatment options and clinical outcomes of KSS patients when compared with KD patients. This is a retrospective study. All children referred to two pediatric rheumatology units from January 1, 2012, to December 31, 2014, were enrolled. Patients were divided into patients with or without KSS. We compared the two groups according to the following variables: sex, age, type of KD (classic, with less frequent manifestations, or incomplete), clinical manifestations, cardiac involvement, laboratory findings, therapy administered, response to treatment, and outcome. Eighty-four patients with KD were enrolled. Of these, five (6 %) met the criteria for KSS. Patients with KSS had higher values of C-reactive protein (p = 0.005), lower hemoglobin levels (p = 0.003); more frequent hyponatremia (p = 0.004), hypoalbuminemia (p = 0.004), and coagulopathy (p = 0.003); and increase in cardiac troponins (p = 0.000). Among the KSS patients, three had a coronary artery involvement, but none developed a permanent aneurysm. Intravenous immunoglobulin resistance was more frequent in the KSS group, although not significantly so (3/5, 60 % vs. 23/79, 30 %, P = NS). None of the five cases was fatal, and all recovered without sequelae. KSS patients are more likely to have higher rates of cardiac involvement. However, most cardiovascular abnormalities resolved promptly with therapy.
Keywords: C-Reactive Protein; Child; Child, Preschool; Echocardiography; Female; Heart Failure; Hemoglobins; Humans; Immunoglobulins, Intravenous; Male; Mucocutaneous Lymph Node Syndrome; Retrospective Studies; Shock; Syndrome

Diagnosis and management of newly diagnosed childhood autoimmune haemolytic anaemia. Recommendations from the Red Cell Study Group of the Paediatric Haemato-Oncology Italian Association. - Ladogana, Saverio; Maruzzi, Matteo; Samperi, Piera; Perrotta, Silverio; Del Vecchio, Giovanni C; Notarangelo, Lucia D; Farruggia, Piero; Verzegnassi, Federico; Masera, Nicoletta; Saracco, Paola; Fasoli, Silvia; Miano, Maurizio; et al. (Blood Transfus, 2017)
Autoimmune haemolytic anaemia is an uncommon disorder to which paediatric haematology centres take a variety of diagnostic and therapeutic approaches. The Red Cell Working Group of the Italian Association of Paediatric Onco-haematology (Associazione Italiana di Ematologia ed Oncologia Pediatrica, AIEOP) developed this document in order to collate expert opinions on the management of newly diagnosed childhood autoimmune haemolytic anaemia.The diagnostic process includes the direct and indirect antiglobulin tests; recommendations are given regarding further diagnostic tests, specifically in the cases that the direct and indirect antiglobulin tests are negative. Clear-cut definitions of clinical response are stated. Specific recommendations for treatment include: dosage of steroid therapy and tapering modality for warm autoimmune haemolytic anaemia; the choice of rituximab as first-line therapy for the rare primary transfusion-dependent cold autoimmune haemolytic anaemia; the indications for supportive therapy; the need for switching to second-line therapy. Each statement is provided with a score expressing the level of appropriateness and the agreement among participants.
Keywords: Anemia, Hemolytic, Autoimmune; Blood Transfusion; Child; Coombs Test; Disease Management; Hematology; Humans; Immunoglobulin M; Italy; Pediatrics; Societies, Medical; Steroids

Early-life nutritional exposures and lifelong health: immediate and long-lasting impacts of probiotics, vitamin D, and breastfeeding. - Berti, Cristiana; Agostoni, Carlo; Davanzo, Riccardo; Hyppönen, Elina; Isolauri, Erika; Meltzer, Helle M; Steegers-Theunissen, Régine P M; Cetin, Irene (Nutr Rev, 2017)
Pregnancy and infancy comprise the most critical stages for conditioning an individual's health, with a number of implications for subsequent risks of morbidity, mortality, and reproductive health. Nutrition may influence both the overall pregnancy outcome and the growth trajectory and immune system of the fetus and infant, with short- and long-term effects on the health of the offspring. Within this context, leading experts at Expo Milano 2015 in Milan, Italy, discussed up-to-date knowledge while providing suggestions and challenges before, during, and after pregnancy. This narrative review summarizes the key issues raised by the experts concerning the interplay between the nutritional environment from conception to early infancy and the offspring's immediate and lifelong health, with a particular focus on epigenetic mechanisms, probiotics, vitamin D, and breastfeeding. Taken together, the findings strengthen the awareness that nutritional exposures occurring from preconception to the postnatal period may be strong determinants of the offspring's health and may provide supportive evidence for current nutritional recommendations and guidelines for pregnant women and infants. Critical topics to be addressed in future research and translated into recommendations of public health relevance are also highlighted.
Keywords: Breast Feeding; Diet; Female; Humans; Infant; Infant Nutritional Physiological Phenomena; Meta-Analysis as Topic; Nutritional Status; Pregnancy; Pregnancy Outcome; Probiotics; Vitamin D

Enrichment of low-frequency functional variants revealed by whole-genome sequencing of multiple isolated European populations. - Xue, Yali; Mezzavilla, Massimo; Haber, Marc; McCarthy, Shane; Chen, Yuan; Narasimhan, Vagheesh; Gilly, Arthur; Ayub, Qasim; Colonna, Vincenza; Southam, Lorraine; Finan, Christopher; Massaia, Andrea; et al. (Nat Commun, 2017)
The genetic features of isolated populations can boost power in complex-trait association studies, and an in-depth understanding of how their genetic variation has been shaped by their demographic history can help leverage these advantageous characteristics. Here, we perform a comprehensive investigation using 3,059 newly generated low-depth whole-genome sequences from eight European isolates and two matched general populations, together with published data from the 1000 Genomes Project and UK10K. Sequencing data give deeper and richer insights into population demography and genetic characteristics than genotype-chip data, distinguishing related populations more effectively and allowing their functional variants to be studied more fully. We demonstrate relaxation of purifying selection in the isolates, leading to enrichment of rare and low-frequency functional variants, using novel statistics, DVxy and SVxy. We also develop an isolation-index (Isx) that predicts the overall level of such key genetic characteristics and can thus help guide population choice in future complex-trait association studies.
Keywords: European Continental Ancestry Group; Gene Frequency; Genetic Variation; Genetics, Population; Genome, Human; Humans; Polymorphism, Single Nucleotide; Whole Genome Sequencing

Epratuzumab and Blinatumomab as Therapeutic Antibodies for Treatment of Pediatric Acute Lymphoblastic Leukemia: Current Status and Future Perspectives. - Franca, Raffaella; Favretto, Diego; Granzotto, Marilena; Decorti, Giuliana; Rabusin, Marco; Stocco, Gabriele (Curr Med Chem, 2017)
BACKGROUND: More than 85% of children affected by acute lymphoblastic leukemia (ALL) are successfully treated; however relapse remains a remarkable clinical concern, with 50-60% of relapsing patients facing a fatal outcome. Management of relapsed patients includes standardized intensive risk-adapted regimens based on conventional drugs, and hematopoietic stem cells transplantation for patients with unfavourable features. Biological drugs, in particular the monoclonal antibody epratuzumab and the bi-functional recombinant single chain peptide blinatumomab, have been recently recognized as novel potential agents to be integrated in salvage ALL therapy to further improve rescue outcome. METHODS: A systematic search of peer-reviewed scientific literature and clinical trials in public databases has been carried out. Both clinical and pre-clinical studies have been included to summarize recent evidence on epratuzumab and blinatumomab for salvage ALL therapy. RESULTS: Sixty-two papers and 25 clinical trials were included. Although not all patients responded properly to these agents, their use in relapsed and refractory pediatric ALL seems promising. CONCLUSION: Phase 3 studies have recently begun and more consistent results about epratuzumab and blinatumomab safety and efficacy in comparison to conventional therapies are expected in the next years. Epratuzumab seems safe in the dosing scheme proposed in ALL, but its efficacy over the conventional chemotherapy is still questionable. Blinatumomab has shown promising results in high risk cases such as elder adult patients and conclusive studies on pediatric ALL are needed. Patient inter-individual variability to these agents has not been investigated in depth, but this issue needs to be addressed, in particular for blinatumomab.
Keywords: Antibodies, Bispecific; Antibodies, Monoclonal; Antibodies, Monoclonal, Humanized; Antineoplastic Agents; Child; Clinical Trials as Topic; Half-Life; Humans; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Sialic Acid Binding Ig-like Lectin 2

Essure Permanent Birth Control, Effectiveness and Safety: An Italian 11-Year Survey. - Franchini, Mario; Zizolfi, Brunella; Coppola, Carmela; Bergamini, Valentino; Bonin, Cecilia; Borsellino, Giovanni; Busato, Enrico; Calabrese, Stefania; Calzolari, Stefano; Fantin, Gian Piero; Giarrè, Giovanna; Litta, Piero; et al. (J Minim Invasive Gynecol, 2017)
STUDY OBJECTIVE: To describe safety, tolerability, and effectiveness results through a minimum 2-year follow-up of patients who underwent permanent sterilization with the Essure insert. DESIGN: A retrospective multicenter study (Canadian Task Force classification II2). SETTING: Seven general hospitals and 4 clinical teaching centers in Italy. PATIENTS: A total of 1968 women, mean age 39.5 years (range, 23-48 years) who underwent office hysteroscopic sterilization using the Essure insert between April 1, 2003, and December 30, 2014. INTERVENTION: The women underwent office hysteroscopic bilateral Essure insert placement, with satisfactory device location and tube occlusion based on hysterosalpingography or hysterosalpingo-contrast sonography (HyCoSy). MEASUREMENTS AND MAIN RESULTS: Placement rate, successful bilateral tubal occlusion, perioperative adverse events, early postoperative (during the first 3 months of follow-up), and late complications were evaluated. Satisfactory insertion was accomplished in 97.2% of women and, in 4, perforation and 1 expulsion were detected during hysterosalpingography. Three unintended pregnancies occurred before the 3-month confirmation test. Two pregnancies were reported among women relying on the Essure inserts. Postprocedure pain was minimal and brief; in 9 women, pelvic pain became intractable, necessitating removal of the devices via laparoscopy. On telephone interviews, overall satisfaction was rated as "very satisfied" by the majority of women (97.6%), and no long-term adverse events were reported. CONCLUSION: The findings from this extended Italian survey further support the effectiveness, tolerability, and satisfaction of Essure hysteroscopic sterilization when motivated women are selected and well informed of the potential risks of the device. Moreover, the results do not demonstrate an increased incidence of complications and pregnancies associated with long-term Essure use. Patients with a known hypersensitivity to nickel may be less suitable candidates for the Essure insert.
Keywords: Adult; Fallopian Tubes; Female; Follow-Up Studies; Humans; Hypersensitivity; Hysterosalpingography; Hysteroscopy; Italy; Laparoscopy; Middle Aged; Nickel; Pain; Pregnancy; Pregnancy, Unplanned; Retrospective Studies; Sterilization, Reproductive; Sterilization, Tubal; Surveys and Questionnaires; Young Adult

Fetal and umbilical Doppler ultrasound in high-risk pregnancies. - Alfirevic, Zarko; Stampalija, Tamara; Dowswell, Therese (Cochrane Database Syst Rev, 2017)
BACKGROUND: Abnormal blood flow patterns in fetal circulation detected by Doppler ultrasound may indicate poor fetal prognosis. It is also possible that false positive Doppler ultrasound findings could lead to adverse outcomes from unnecessary interventions, including preterm delivery. OBJECTIVES: The objective of this review was to assess the effects of Doppler ultrasound used to assess fetal well-being in high-risk pregnancies on obstetric care and fetal outcomes. SEARCH METHODS: We updated the search of Cochrane Pregnancy and Childbirth's Trials Register on 31 March 2017 and checked reference lists of retrieved studies. SELECTION CRITERIA: Randomised and quasi-randomised controlled trials of Doppler ultrasound for the investigation of umbilical and fetal vessels waveforms in high-risk pregnancies compared with no Doppler ultrasound. Cluster-randomised trials were eligible for inclusion but none were identified. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed the studies for inclusion, assessed risk of bias and carried out data extraction. Data entry was checked. We assessed the quality of evidence using the GRADE approach. MAIN RESULTS: Nineteen trials involving 10,667 women were included. Risk of bias in trials was difficult to assess accurately due to incomplete reporting. None of the evidence relating to our main outcomes was graded as high quality. The quality of evidence was downgraded due to missing information on trial methods, imprecision in risk estimates and heterogeneity. Eighteen of these studies compared the use of Doppler ultrasound of the umbilical artery of the unborn baby with no Doppler or with cardiotocography (CTG). One more recent trial compared Doppler examination of other fetal blood vessels (ductus venosus) with computerised CTG.The use of Doppler ultrasound of the umbilical artery in high-risk pregnancy was associated with fewer perinatal deaths (risk ratio (RR) 0.71, 95% confidence interval (CI) 0.52 to 0.98, 16 studies, 10,225 babies, 1.2% versus 1.7 %, number needed to treat (NNT) = 203; 95% CI 103 to 4352, evidence graded moderate). The results for stillbirths were consistent with the overall rate of perinatal deaths, although there was no clear difference between groups for this outcome (RR 0.65, 95% CI 0.41 to 1.04; 15 studies, 9560 babies, evidence graded low). Where Doppler ultrasound was used, there were fewer inductions of labour (average RR 0.89, 95% CI 0.80 to 0.99, 10 studies, 5633 women, random-effects, evidence graded moderate) and fewer caesarean sections (RR 0.90, 95% CI 0.84 to 0.97, 14 studies, 7918 women, evidence graded moderate). There was no comparative long-term follow-up of babies exposed to Doppler ultrasound in pregnancy in women at increased risk of complications.No difference was found in operative vaginal births (RR 0.95, 95% CI 0.80 to 1.14, four studies, 2813 women), nor in Apgar scores less than seven at five minutes (RR 0.92, 95% CI 0.69 to 1.24, seven studies, 6321 babies, evidence graded low). Data for serious neonatal morbidity were not pooled due to high heterogeneity between the three studies that reported it (1098 babies) (evidence graded very low).The use of Doppler to evaluate early and late changes in ductus venosus in early fetal growth restriction was not associated with significant differences in any perinatal death after randomisation. However, there was an improvement in long-term neurological outcome in the cohort of babies in whom the trigger for delivery was either late changes in ductus venosus or abnormalities seen on computerised CTG. AUTHORS' CONCLUSIONS: Current evidence suggests that the use of Doppler ultrasound on the umbilical artery in high-risk pregnancies reduces the risk of perinatal deaths and may result in fewer obstetric interventions. The results should be interpreted with caution, as the evidence is not of high quality. Serial monitoring of Doppler changes in ductus venosus may be beneficial, but more studies of high quality with follow-up including neurological development are needed for evidence to be conclusive.
Keywords: Cardiotocography; Cesarean Section; Female; Fetal Monitoring; Humans; Labor, Induced; Perinatal Mortality; Pregnancy; Pregnancy, High-Risk; Randomized Controlled Trials as Topic; Stillbirth; Ultrasonography, Prenatal; Umbilical Arteries; Umbilical Cord

First-time success with needle procedures was higher with a warm lidocaine and tetracaine patch than an eutectic mixture of lidocaine and prilocaine cream. - Cozzi, Giorgio; Borrometi, Fabio; Benini, Franca; Neri, Elena; Rusalen, Francesca; Celentano, Loredana; Zanon, Davide; Schreiber, Silvana; Ronfani, Luca; Barbi, Egidio (Acta Paediatr, 2017)
AIM: More than 50% of children report apian during venepuncture or intravenous cannulation and using local anaesthetics before needle procedures can lead to different success rates. This study examined how many needle procedures were successful at the first attempt when children received either a warm lidocaine and tetracaine patch or an eutectic mixture of lidocaine and prilocaine (EMLA) cream. METHODS: We conducted this multicentre randomised controlled trial at three tertiary-level children's hospitals in Italy in 2015. Children aged three to 10 years were enrolled in an emergency department, paediatric day hospital and paediatric ward and randomly allocated to receive a warm lidocaine and tetracaine patch or EMLA cream. The primary outcome was the success rate at the first attempt. RESULTS: The analysis included 172 children who received a warm lidocaine and tetracaine patch and 167 who received an EMLA cream. The needle procedure was successful at the first attempt in 158 children (92.4%) who received the warm patch and in 142 children (85.0%) who received the cream (p = 0.03). The pain scores were similar in both groups. CONCLUSION: This study showed that the first-time needle procedure success was 7.4% higher in children receiving a warm lidocaine and tetracaine patch than EMLA cream.
Keywords: Anesthetics, Local; Catheterization, Peripheral; Child; Child, Preschool; Female; Hot Temperature; Humans; Lidocaine; Lidocaine, Prilocaine Drug Combination; Male; Pain; Phlebotomy; Prilocaine; Tetracaine

Genome-wide association analysis identifies novel blood pressure loci and offers biological insights into cardiovascular risk. - Warren, Helen R; Evangelou, Evangelos; Cabrera, Claudia P; Gao, He; Ren, Meixia; Mifsud, Borbala; Ntalla, Ioanna; Surendran, Praveen; Liu, Chunyu; Cook, James P; Kraja, Aldi T; Drenos, Fotios; et al. (Nat Genet, 2017)
Elevated blood pressure is the leading heritable risk factor for cardiovascular disease worldwide. We report genetic association of blood pressure (systolic, diastolic, pulse pressure) among UK Biobank participants of European ancestry with independent replication in other cohorts, and robust validation of 107 independent loci. We also identify new independent variants at 11 previously reported blood pressure loci. In combination with results from a range of in silico functional analyses and wet bench experiments, our findings highlight new biological pathways for blood pressure regulation enriched for genes expressed in vascular tissues and identify potential therapeutic targets for hypertension. Results from genetic risk score models raise the possibility of a precision medicine approach through early lifestyle intervention to offset the impact of blood pressure-raising genetic variants on future cardiovascular disease risk.
Keywords: Adult; Blood Pressure; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Genomic analyses identify hundreds of variants associated with age at menarche and support a role for puberty timing in cancer risk. - Day, Felix R; Thompson, Deborah J; Helgason, Hannes; Chasman, Daniel I; Finucane, Hilary; Sulem, Patrick; Ruth, Katherine S; Whalen, Sean; Sarkar, Abhishek K; Albrecht, Eva; Altmaier, Elisabeth; Amini, Marzyeh; et al. (Nat Genet, 2017)
The timing of puberty is a highly polygenic childhood trait that is epidemiologically associated with various adult diseases. Using 1000 Genomes Project-imputed genotype data in up to ∼370,000 women, we identify 389 independent signals (P < 5 × 10) for age at menarche, a milestone in female pubertal development. In Icelandic data, these signals explain ∼7.4% of the population variance in age at menarche, corresponding to ∼25% of the estimated heritability. We implicate ∼250 genes via coding variation or associated expression, demonstrating significant enrichment in neural tissues. Rare variants near the imprinted genes MKRN3 and DLK1 were identified, exhibiting large effects when paternally inherited. Mendelian randomization analyses suggest causal inverse associations, independent of body mass index (BMI), between puberty timing and risks for breast and endometrial cancers in women and prostate cancer in men. In aggregate, our findings highlight the complexity of the genetic regulation of puberty timing and support causal links with cancer susceptibility.
Keywords: Adolescent; Age Factors; Body Mass Index; Databases, Genetic; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomic Imprinting; Humans; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Neoplasms; Polymorphism, Single Nucleotide; Puberty; Quantitative Trait Loci; Ribonucleoproteins; Risk Factors

Gray platelet syndrome: Novel mutations of the NBEAL2 gene. - Bottega, Roberta; Nicchia, Elena; Alfano, Caterina; Glembotsky, Ana C; Pastore, Annalisa; Bertaggia-Calderara, Debora; Bisig, Bettina; Duchosal, Michel A; Arbesú, Guillermo; Alberio, Lorenzo; Heller, Paula G; Savoia, Anna (Am J Hematol, 2017)
Keywords: Adult; Alleles; Blood Proteins; Child; Female; Gene Expression; Gene Frequency; Genotype; Gray Platelet Syndrome; Humans; Male; Mutation; Phenotype; Platelet Aggregation; Platelet Count; Platelet Membrane Glycoproteins

Guidelines of the Italian Society of Videosurgery in Infancy for the minimally invasive treatment of the esophageal atresia. - Chiarenza, Salvatore Fabio; Conighi, Maria Luisa; Conforti, Andrea; Esposito, Ciro; Escolino, Maria; Beretta, Fabio; Cheli, Maurizio; Di Benedetto, Vincenzo; Scuderi, Maria Grazia; Casadio, Giovanni; Marzaro, Maurizio; Fascetti, Leon Francesco; et al. (Pediatr Med Chir, 2017)
Not available.
Keywords: Esophageal Atresia; Humans; Infant; Minimally Invasive Surgical Procedures; Video-Assisted Surgery

Guidelines of the Italian Society of Videosurgery in Infancy for the minimally invasive treatment of the ureteropelvic-junction obstruction. - Chiarenza, Salvatore Fabio; Bleve, Cosimo; Esposito, Ciro; Escolino, Maria; Beretta, Fabio; Cheli, Maurizio; Di Benedetto, Vincenzo; Scuderi, Maria Grazia; Casadio, Giovanni; Marzaro, Maurizio; Fascetti, Leon Francesco; Bagolan, Pietro; et al. (Pediatr Med Chir, 2017)
Not available.
Keywords: Humans; Infant; Kidney Pelvis; Minimally Invasive Surgical Procedures; Ureteral Obstruction; Video-Assisted Surgery

Histoproteomic Characterization of Localized Cutaneous Amyloidosis in X-Linked Reticulate Pigmentary Disorder. - L'Imperio, Vincenzo; Bruno, Irene; Rabach, Ingrid; Smith, Andrew; Chinello, Clizia; Stella, Martina; Magni, Fulvio; Pagni, Fabio (Skin Pharmacol Physiol, 2017)
Keywords: Amyloidosis; Genetic Diseases, X-Linked; Humans; Pigmentation Disorders; Proteomics; Skin Diseases

HLA-G regulatory polymorphisms are associated with susceptibility to HCV infection. - Catamo, E; Zupin, L; Freato, N; Polesello, V; Celsi, F; Crocè, S L; Masutti, F; Pozzato, G; Segat, L; Crovella, S (HLA, 2017)
BACKGROUND: Hepatitis C virus (HCV) is able to bypass the immune system modulating innate and adaptive immune response and blocking T helper 1 (Th1) cell production. Because the human leukocyte antigen (HLA)-G molecule has immunomodulatory properties inhibiting the function and production of natural killer and cytotoxic lymphocyte T cells, as well as promoting shift from Th1 toward Th2 response, we hypothesized its involvement in susceptibility to HCV infection. MATERIALS AND METHODS: Considering that HLA-G mRNA expression has been reported to be under genetic control, an association study was conducted analyzing 800 base pairs upstream the ATG at the 5'upstream regulator region (URR) and 850 base pairs from ATG to exon 3 and the 3'untranslated region (UTR) of HLA-G gene in Italian HCV-positive patients and uninfected controls. RESULTS: Four 5'URR polymorphisms (-725C>G>T, -509C>G, -400G>A and -398G>A), 7 polymorphisms at coding region (+15G>A, +36G>A, +243G>A, insC506, 531G>C, delA615 and 685G>A), the +644G>T polymorphism, and 1 haplotype (TTGTTCCIGAC) showed different frequency distributions between HCV patients and uninfected controls. CONCLUSION: The results from our study suggest a possible involvement of HLA-G in the risk modulation toward HCV infection.
Keywords: 3' Untranslated Regions; 5' Untranslated Regions; Adult; Aged; Aged, 80 and over; Alleles; Case-Control Studies; Exons; Female; Gene Expression; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Haplotypes; Hepacivirus; Hepatitis C; HLA-G Antigens; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk; Th1 Cells

How to monitor pregnancies complicated by fetal growth restriction and delivery before 32 weeks: post-hoc analysis of TRUFFLE study. - Ganzevoort, W; Mensing Van Charante, N; Thilaganathan, B; Prefumo, F; Arabin, B; Bilardo, C M; Brezinka, C; Derks, J B; Diemert, A; Duvekot, J J; Ferrazzi, E; Frusca, T; et al. (Ultrasound Obstet Gynecol, 2017)
OBJECTIVES: In the recent TRUFFLE study, it appeared that, in pregnancies complicated by fetal growth restriction (FGR) between 26 and 32 weeks' gestation, monitoring of the fetal ductus venosus (DV) waveform combined with computed cardiotocography (CTG) to determine timing of delivery increased the chance of infant survival without neurological impairment. However, concerns with the interpretation were raised, as DV monitoring appeared to be associated with a non-significant increase in fetal death, and some infants were delivered after 32 weeks, at which time the study protocol no longer applied. This secondary sensitivity analysis of the TRUFFLE study focuses on women who delivered before 32 completed weeks' gestation and analyzes in detail the cases of fetal death. METHODS: Monitoring data of 317 pregnancies with FGR that delivered before 32 weeks were analyzed, excluding those with absent outcome data or inevitable perinatal death. Women were allocated randomly to one of three groups of indication for delivery according to the following monitoring strategies: (1) reduced fetal heart rate short-term variation (STV) on CTG; (2) early changes in fetal DV waveform; and (3) late changes in fetal DV waveform. Primary outcome was 2-year survival without neurological impairment. The association of the last monitoring data before delivery and infant outcome was assessed by multivariable analysis. RESULTS: Two-year survival without neurological impairment occurred more often in the two DV groups (both 83%) than in the CTG-STV group (77%), however, the difference was not statistically significant (P = 0.21). Among the surviving infants in the DV groups, 93% were free of neurological impairment vs 85% of surviving infants in the CTG-STV group (P = 0.049). All fetal deaths (n = 7) occurred in the groups with DV monitoring. Of the monitoring parameters obtained shortly before fetal death in these seven cases, an abnormal CTG was observed in only one case. Multivariable regression analysis of factors at study entry demonstrated that a later gestational age, higher estimated fetal weight-to-50 percentile ratio and lower umbilical artery pulsatility index (PI)/fetal middle cerebral artery-PI ratio were significantly associated with normal outcome. Allocation to DV monitoring had a smaller effect on outcome, but remained in the model (P < 0.1). Abnormal fetal arterial Doppler before delivery was significantly associated with adverse outcome in the CTG-STV group. In contrast, abnormal DV flow was the only monitoring parameter associated with adverse outcome in the DV groups, while fetal arterial Doppler, STV below the cut-off used in the CTG-STV group and recurrent decelerations in fetal heart rate were not. CONCLUSIONS: In accordance with the findings of the TRUFFLE study on monitoring and intervention management of very preterm FGR, we found that the proportion of infants surviving without neuroimpairment was not significantly different when the decision for delivery was based on changes in DV waveform vs reduced STV on CTG. The uneven distribution of fetal deaths towards the DV groups was probably a chance effect, and neurological outcome was better among surviving children in these groups. Before 32 weeks, delaying delivery until abnormalities in DV-PI or STV and/or recurrent decelerations in fetal heat rate occur, as defined by the study protocol, is likely to be safe and possibly benefits long-term outcome. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cardiotocography; Central Nervous System Diseases; Child, Preschool; Female; Fetal Growth Retardation; Fetal Membranes, Premature Rupture; Gestational Age; Heart Rate, Fetal; Humans; Infant; Infant, Extremely Premature; Male; Middle Cerebral Artery; Pregnancy; Pulsatile Flow; Survival Analysis; Treatment Outcome; Ultrasonography, Prenatal; Uterine Artery

Identification of proteins with different abundance associated with cell migration and proliferation in leiomyoma interstitial fluid by proteomics. - Ura, Blendi; Scrimin, Federica; Franchin, Cinzia; Arrigoni, Giorgio; Licastro, Danilo; Monasta, Lorenzo; Ricci, Giuseppe (Oncol Lett, 2017)
Uterine leiomyoma is the most common female reproductive tract benign tumor. Little is known about protein composition and changes in the leiomyoma interstitial fluid (IF). The present study focused on changes in protein abundance in the IF of leiomyoma. Leiomyoma IFs and adjacent myometrial IFs were obtained and analyzed by two-dimensional electrophoresis (2-DE) coupled with mass spectrometry and western blotting for 2-DE data validation. A total of 25 unique proteins were observed to change significantly (P<0.05). Of these proteins with different abundance, 22 had not been previously identified in leiomyoma IF. analysis predicted that three of these proteins were secreted via classical mechanisms, while 22 were secreted via non-classical mechanisms. Ingenuity Pathway Analysis identified 17 proteins associated with cellular migration and proliferation. Among these, phosphoglycerate mutase 1 had not been previously associated with leiomyoma. The abundance of seven proteins was further validated by western blotting. A comparative proteomic approach identified a number of proteins associated with cellular migration and proliferation, with changes in abundance in IF likely to be involved in tumor development. Further studies will be required to investigate the role of these proteins in leiomyoma IF and their possible association with tumor development and growth.

Imported arboviral infections in Italy, July 2014-October 2015: a National Reference Laboratory report. - Fortuna, Claudia; Remoli, Maria Elena; Rizzo, Caterina; Benedetti, Eleonora; Fiorentini, Cristiano; Bella, Antonino; Argentini, Claudio; Farchi, Francesca; Castilletti, Concetta; Capobianchi, Maria Rosaria; Zammarchi, Lorenzo; Bartoloni, Alessandro; et al. (BMC Infect Dis, 2017)
BACKGROUND: Imported cases of infections due to Dengue (DENV) and Chikungunya (CHIKV) viruses and, more recently, Zika virus (ZIKV) are commonly reported among travelers returning from endemic regions. In areas where potentially competent vectors are present, the risk of autochthonous transmission of these vector-borne pathogens is relatively high. Laboratory surveillance is crucial to rapidly detect imported cases in order to reduce the risk of transmission. This study describes the laboratory activity performed by the National Reference Laboratory for Arboviruses (NRLA) at the Italian National Institute of Health in the period from July 2014 to October 2015. METHODS: Samples from 180 patients visited/hospitalized with a suspected DENV/CHIKV/ZIKV infection were sent to the NRLA from several Italian Hospitals and from Regional Reference Laboratories for Arboviruses, in agreement with the National Plan on human surveillance of vector-borne diseases. Both serological (ELISA IgM test and Plaque Reduction Neutralization Test-PRNT) and molecular assays (Real Time PCR tests, RT-PCR plus nested PCR and sequencing of positive samples) were performed. RESULTS: DENV infection was the most frequently diagnosed (80 confirmed/probable cases), and all four genotypes were detected. However, an increase in imported CHIKV cases (41 confirmed/probable cases) was observed, along with the detection of the first ZIKV cases (4 confirmed cases), as a consequence of the recent spread of both CHIKV and ZIKV in the Americas. CONCLUSIONS: Main diagnostic issues highlighted in our study are sensitivity limitations of molecular tests, and the importance of PRNT to confirm serological results for differential diagnosis of Arboviruses. The continuous evaluation of diagnostic strategy, and the implementation of laboratories networks involved in surveillance activities is essential to ensure correct diagnosis, and to improve the preparedness for a rapid and proper identification of viral threats.
Keywords: Chikungunya Fever; Chikungunya virus; Dengue; Dengue Virus; Disease Outbreaks; Female; Genotype; Humans; Italy; Male; Molecular Diagnostic Techniques; Population Surveillance; Public Health; Travel; Young Adult; Zika Virus; Zika Virus Infection

Improving the quality of hospital care for children by supportive supervision: a cluster randomized trial, Kyrgyzstan. - Lazzerini, Marzia; Shukurova, Venera; Davletbaeva, Marina; Monolbaev, Kubanychbek; Kulichenko, Tatiana; Akoev, Yuri; Bakradze, Maya; Margieva, Tea; Mityushino, Ilya; Namazova-Baranova, Leyla; Boronbayeva, Elnura; Kuttumuratova, Aigul; et al. (Bull World Health Organ, 2017)
OBJECTIVE: To determine whether periodic supportive supervision after a training course improved the quality of paediatric hospital care in Kyrgyzstan, where inappropriate care was common but in-hospital postnatal mortality was low. METHODS: In a cluster, randomized, parallel-group trial, 10 public hospitals were allocated to a 4-day World Health Organization (WHO) course on hospital care for children followed by periodic supportive supervision by paediatricians for 1 year, while 10 hospitals had no intervention. We assessed prospectively 10 key indicators of inappropriate paediatric case management, as indicated by WHO guidelines. The primary indicator was the combination of the three indicators: unnecessary hospitalization, increased iatrogenic risk and unnecessary painful procedures. An independent team evaluated the overall quality of care. FINDINGS: We prospectively reviewed the medical records of 4626 hospitalized children aged 2 to 60 months. In the intervention hospitals, the mean proportion of the primary indicator decreased from 46.9% (95% confidence interval, CI: 24.2 to 68.9) at baseline to 6.8% (95% CI: 1.1 to 12.1) at 1 year, but was unchanged in the control group (45.5%, 95% CI: 25.2 to 67.9, to 64.7%, 95% CI: 43.3 to 86.1). At 1 year, the risk ratio for the primary indicator in the intervention versus the control group was 0.09 (95% CI: 0.06 to 0.13). The proportions of the other nine indicators also decreased in the intervention group ( < 0.0001 for all). Overall quality of care improved significantly in intervention hospitals. CONCLUSION: Periodic supportive supervision for 1 year after a training course improved both adherence to WHO guidelines on hospital care for children and the overall quality of paediatric care.
Keywords: Child; Child Care; Cluster Analysis; Hospitalization; Hospitals, Public; Humans; Kyrgyzstan; Medical Audit; Pediatricians; Professional Role; Prospective Studies; Quality Improvement

Influence of vaginal lactoferrin administration on amniotic fluid cytokines and its role against inflammatory complications of pregnancy. - Maritati, Martina; Comar, Manola; Zanotta, Nunzia; Seraceni, Silva; Trentini, Alessandro; Corazza, Fabrizio; Vesce, Fortunato; Contini, Carlo (J Inflamm (Lond), 2017)
BACKGROUND: An altered amniotic cytokine profile has been reported in inflammatory pregnancy complications with a leading role for IL-6, a marker of the foetal systemic inflammatory response. Up to this date there is no exhaustive information neither on the foetal cytokine balance nor on the best method for its modulation. We aimed to evaluate the influence of vaginal lactoferrin administration on amniotic fluid concentration of 47 cytokines, chemokines and growth factors. METHODS: Sixty women undergoing genetic amniocentesis were enrolled in an open-label clinical trial. 300 mg of vaginal lactoferrin (Florence, Italy) were randomly administered to obtain 3 groups: A, 20 untreated patients; B and C (20 patients in each) respectively treated 4 and 12 h before amniocentesis. Cytokines, chemokines and growth factors concentrations were quantified by a magnetic bead Luminex multiplex immunoassays panel technology. Data analysis was performed with the software Stata (v. 13.1) and GraphPad Prism (v. 5). Group comparisons were performed using Kruskal-Wallis followed by Mann-Whitney U tests, with Bonferroni correction for multiple comparisons. A  < 0.05 was considered significant. RESULTS: Among the 47 tested mediators, 24 (51.06%) were influenced by lactoferrin. 11 (23.4%), showed a highly significant difference (p <0.001); among these IL-9, IL-15, IFN-γ, IP-10, TNF-α, IL-1α and MCP-3 underwent a down-regulation, while IL-17 and FGF-basic, G-CSF, GM-CSF an up-regulation. Difference between group C and both B and A was small for IL-15, IP-10, IL-1α, MCP-3, while it was negligible for IL-9, IFN-γ and TNF-α. IL-17 and the 3 growth factors were strongly enhanced in B and C groups. IL-17, FGF-basic and GM-CSF showed increasing concentrations in both B and C groups, while G-CSF resulted up-regulated only in group C. Significance was intermediate ( < 0.01) for the down regulated IL-2RA, IL-12p40 and IFNα2 (6.38%) while it was small for 10 mediators (21.27%) 7 of which (IL-2, IL-4, eotaxin, PDGF-BB, RANTES, IL-18 and MIF) down-regulated and 3 (MCP-1, IL-3, and SDF-1α) up-regulated. CONCLUSION: Lactoferrin down-regulates 17 pro-inflammatory amniotic mediators while up-regulating 7 anti-inflammatory amniotic mediators, 5 of which definitively belonging to an anti-inflammatory profile. These findings open to clinical investigation on its use against inflammatory complications of pregnancy.

ISL1 is a major susceptibility gene for classic bladder exstrophy and a regulator of urinary tract development. - Zhang, Rong; Knapp, Michael; Suzuki, Kentaro; Kajioka, Daiki; Schmidt, Johanna M; Winkler, Jonas; Yilmaz, Öznur; Pleschka, Michael; Cao, Jia; Kockum, Christina Clementson; Barker, Gillian; Holmdahl, Gundela; et al. (Sci Rep, 2017)
Previously genome-wide association methods in patients with classic bladder exstrophy (CBE) found association with ISL1, a master control gene expressed in pericloacal mesenchyme. This study sought to further explore the genetics in a larger set of patients following-up on the most promising genomic regions previously reported. Genotypes of 12 markers obtained from 268 CBE patients of Australian, British, German Italian, Spanish and Swedish origin and 1,354 ethnically matched controls and from 92 CBE case-parent trios from North America were analysed. Only marker rs6874700 at the ISL1 locus showed association (p = 2.22 × 10). A meta-analysis of rs6874700 of our previous and present study showed a p value of 9.2 × 10. Developmental biology models were used to clarify the location of ISL1 activity in the forming urinary tract. Genetic lineage analysis of Isl1-expressing cells by the lineage tracer mouse model showed Isl1-expressing cells in the urinary tract of mouse embryos at E10.5 and distributed in the bladder at E15.5. Expression of isl1 in zebrafish larvae staged 48 hpf was detected in a small region of the developing pronephros. Our study supports ISL1 as a major susceptibility gene for CBE and as a regulator of urinary tract development.
Keywords: Animals; Bladder Exstrophy; Embryo, Mammalian; Female; Gene Expression Regulation, Developmental; Genetic Predisposition to Disease; Humans; Larva; LIM-Homeodomain Proteins; Mesoderm; Mice; Organogenesis; Polymorphism, Single Nucleotide; Pronephros; Protein Isoforms; Transcription Factors; Urinary Tract; Zebrafish

Longitudinal Responses to Weighing and Bathing Procedures in Preterm Infants. - Bembich, Stefano; Fiani, Giulia; Strajn, Tamara; Sanesi, Cecilia; Demarini, Sergio; Sanson, Gianfranco (J Perinat Neonatal Nurs, 2017)
Knowledge of the effects of nursing-induced stress on short-term outcomes in preterm infants is limited. Effects of 2 standard nursing procedures-weighing and bathing-on autonomic and motor stability of preterm infants were studied during their hospitalization. Outcomes were evaluated during and after the procedures. Eleven preterm infants were observed between 32 and 35 weeks' postmenstrual age (PMA) (postnatal days range: 4-63). Neonatal responses were assessed according to the Synactive Theory of Development and nursing was performed taking into account Newborn Individualized Developmental Care and Assessment Program (NIDCAP) principles. Effects of the studied nursing procedures on infants' stability during and after their execution were evaluated by nonparametric statistics. During monitored procedures, stress responses in autonomic and motor systems were observed at all PMAs. However, after 32 weeks' PMA, preterm infants also showed an autonomic and motor stability recovery 5 minutes after procedure completion. Contrary to our hypothesis, preterm infants showed to be stressed by weighing and bathing procedures up to 35 weeks' PMA. However, if facilitated and supported after nursing conclusion by interventions such as swaddling and nesting, according to NIDCAP principles, they recovered autonomic and motor stability by 5 minutes after ending procedures.
Keywords: Baths; Body Weight; Female; Humans; Infant Behavior; Infant Care; Infant, Newborn; Infant, Premature; Male; Neonatal Nursing

Longitudinal study of computerized cardiotocography in early fetal growth restriction. - Wolf, H; Arabin, B; Lees, C C; Oepkes, D; Prefumo, F; Thilaganathan, B; Todros, T; Visser, G H A; Bilardo, C M; Derks, J B; Diemert, A; Duvekot, J J; et al. (Ultrasound Obstet Gynecol, 2017)
OBJECTIVES: To explore whether, in early fetal growth restriction (FGR), the longitudinal pattern of fetal heart rate (FHR) short-term variation (STV) can be used to identify imminent fetal distress and whether abnormalities of FHR recordings are associated with 2-year infant outcome. METHODS: The original TRUFFLE study assessed whether, in early FGR, delivery based on ductus venosus (DV) Doppler pulsatility index (PI), in combination with safety-net criteria of very low STV on cardiotocography (CTG) and/or recurrent FHR decelerations, could improve 2-year infant survival without neurological impairment in comparison with delivery based on CTG monitoring only. This was a secondary analysis of women who delivered before 32 weeks and had consecutive STV data recorded > 3 days before delivery and known infant outcome at 2 years of age. Women who received corticosteroids within 3 days of delivery were excluded. Individual regression line algorithms of all STV values, except the last one before delivery, were calculated. Life tables and Cox regression analysis were used to calculate the daily risk for low STV or very low STV and/or FHR decelerations (below DV group safety-net criteria) and to assess which parameters were associated with this risk. Furthermore, it was assessed whether STV pattern, last STV value or recurrent FHR decelerations were associated with 2-year infant outcome. RESULTS: One hundred and forty-nine women from the original TRUFFLE study met the inclusion criteria. Using the individual STV regression lines, prediction of a last STV below the cut-off used by the CTG monitoring group had sensitivity of 42% and specificity of 91%. For each day after study inclusion, the median risk for low STV (CTG group cut-off) was 4% (interquartile range (IQR), 2-7%) and for very low STV and/or recurrent FHR decelerations (below DV group safety-net criteria) was 5% (IQR, 4-7%). Measures of STV pattern, fetal Doppler (arterial or venous), birth-weight multiples of the median and gestational age did not usefully improve daily risk prediction. There was no association of STV regression coefficients, a low last STV and/or recurrent FHR decelerations with short- or long-term infant outcomes. CONCLUSION: The TRUFFLE study showed that a strategy of DV monitoring with safety-net criteria of very low STV and/or recurrent FHR decelerations for delivery indication could increase 2-year infant survival without neurological impairment. This post-hoc analysis demonstrates that, in early FGR, the daily risk of abnormal CTG, as defined by the DV group safety-net criteria, is 5%, and that prediction is not possible. This supports the rationale for CTG monitoring more often than daily in these high-risk fetuses. Low STV and/or recurrent FHR decelerations were not associated with adverse infant outcome and it appears safe to delay intervention until such abnormalities occur, as long as DV-PI is within normal range. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cardiotocography; Child, Preschool; Female; Fetal Growth Retardation; Fetal Heart; Heart Rate, Fetal; Humans; Infant; Infant, Newborn; Longitudinal Studies; Middle Cerebral Artery; Pregnancy; Pregnancy Outcome; Pulsatile Flow; Survival Analysis; Ultrasonography, Prenatal

Long-Term Survival After Hematopoietic Stem Cell Transplantation for Complete STAT1 Deficiency. - Naviglio, Samuele; Soncini, Elena; Vairo, Donatella; Lanfranchi, Arnalda; Badolato, Raffaele; Porta, Fulvio (J Clin Immunol, 2017)
PURPOSE: Complete signal transducer and activator of transcription 1 (STAT1) deficiency is a rare autosomal recessive condition characterized by impairment of intracellular signaling from both type I and type II interferons (IFN). Affected patients are prone to early severe mycobacterial and viral infections, which usually result in death before 18 months of age. We previously reported a patient affected by complete STAT1 deficiency who underwent hematopoietic stem cell transplantation (HSCT). Here, we describe the transplantation procedures and long-term outcomes. METHODS: The patient, who had suffered multiple life-threatening mycobacterial and viral infections in the first years of life, underwent HSCT at 4 years of age from a partially matched (HLA compatibility 8/10) unrelated donor after a myeloablative conditioning regimen consisting of busulfan, cyclophosphamide, and anti-thymocyte globulin. RESULTS: Hematological reconstitution was detected at d+15, with full donor engraftment demonstrated by molecular analysis of leukocytes. Several complications occurred in the post-transplantation phase, including acute graft versus host disease, posterior reversible encephalopathy, thrombotic thrombocytopenic purpura, bilateral keratoconjunctivitis with complete loss of vision, and chronic lower limb lymphedema. Analysis of STAT1 in CD3 cells at 90 and 120 days after HSCT by flow cytometry showed normal STAT1 phosphorylation levels in response to IFN-α. CONCLUSIONS: Notably, no severe infections occurred after discharge (day + 90) during a 9-year follow-up, suggesting that normal response to IFNs in hematopoietic cells is sufficient to provide protection in humans.
Keywords: Child, Preschool; Hematopoietic Stem Cell Transplantation; Humans; Immunologic Deficiency Syndromes; Male; STAT1 Transcription Factor; Treatment Outcome

MCM8 and MCM9 Nucleotide Variants in Women With Primary Ovarian Insufficiency. - Desai, Swapna; Wood-Trageser, Michelle; Matic, Jelena; Chipkin, Jaqueline; Jiang, Huaiyang; Bachelot, Anne; Dulon, Jerome; Sala, Cinzia; Barbieri, Caterina; Cocca, Massimiliano; Toniolo, Daniela; Touraine, Philippe; et al. (J Clin Endocrinol Metab, 2017)
Objective: To assess the frequency of variants, including biallelic pathogenic variants, in minichromosome maintenance 8 (MCM8) and minichromosome maintenance 9 (MCM9), other genes related to MCM8-MCM9, and DNA damage repair (DDR) pathway in participants with primary ovarian insufficiency (POI). Design: MCM8, MCM9, and genes encoding DDR proteins that have been implicated in reproductive aging were sequenced among POI participants. Setting: Academic research institution. Participants: All were diagnosed with POI prior to age 40 years and presented with elevated follicle-stimulating hormone levels. Interventions: None. Main Outcome Measures: We identified nucleotide variants in MCM8, MCM9, and genes thought to be involved in the DNA damage response pathway and/or implicated in reproductive aging. Results: MCM8 was sequenced in 155 POI participants, whereas MCM9 was sequenced in 151 participants. Three of 155 (2%) participants carried possibly damaging heterozygous variants in MCM8, whereas 7 of 151 (5%) individuals carried possibly damaging heterozygous variants in MCM9. One participant carried a novel homozygous variant, c.1651C>T, p.Gln551*, in MCM9, which is predicted to introduce a premature stop codon in exon 9. Biallelic damaging heterozygous variants in both MCM8 and MCM9 were identified in 1 participant. Of a total of 10 participants carrying damaging heterozygous variants in either MCM8 or MCM9, 2 individuals carried heterozygous damaging variants in genes associated with either MCM8 or MCM9 or the DDR pathway. Conclusions: We identified a significant number of potentially damaging and novel variants in MCM8 and MCM9 among participants with POI and examined multiallelic association with variants in DDR and MCM8-MCM9 interactome genes.
Keywords: Adult; Aging; DNA Damage; DNA Repair; Female; Humans; Minichromosome Maintenance Proteins; Primary Ovarian Insufficiency; Sequence Analysis, DNA

Metastatic neuroblastoma in infants: are survival rates excellent only within the stringent framework of clinical trials? - Di Cataldo, A; Agodi, A; Balaguer, J; Garaventa, A; Barchitta, M; Segura, V; Bianchi, M; Castel, V; Castellano, A; Cesaro, S; Couselo, J M; Cruz, O; et al. (Clin Transl Oncol, 2017)
INTRODUCTION: SIOPEN INES protocol yielded excellent 5-year survival rates for MYCN-non-amplified metastatic neuroblastoma. Patients deemed ineligible due to lack or delay of MYCN status or late registration were treated, but not included in the study. Our goal was to analyse survival at 10 years among the whole population. MATERIALS AND METHODS: Italian and Spanish metastatic INES patients' data are reported. SPSS 20.0 was used for statistical analysis. RESULTS: Among 98 infants, 27 had events and 19 died, while 79 were disease free. Five- and 10-year event-free survival (EFS) were 73 and 70 %, and overall survival (OS) was 81 and 74 %, respectively. MYCN status was significant for EFS, but not for OS in multivariate analysis. CONCLUSIONS: The survival rates of patients who complied with all the inclusion criteria for INES trials are higher compared to those that included also not registered patients. Five-year EFS and OS for INES 99.2 were 87.8 and 95.7 %, while our stage 4s population obtained 78 and 87 %. Concerning 99.3, 5-year EFS and OS were 86.7 and 95.6 %, while for stage 4 we registered 61 and 68 %. MYCN amplification had a strong impact on prognosis and therefore we consider it unacceptable that many patients were not studied for MYCN and probably inadequately treated. Ten-year survival rates were shown to decrease: EFS from 73 to 70 % and OS from 81 to 74 %, indicating a risk of late events, particularly in stage 4s. Population-based registries like European ENCCA WP 11-task 11 will possibly clarify these data.
Keywords: Biomarkers, Tumor; Child; Child, Preschool; Clinical Trials as Topic; Combined Modality Therapy; Female; Follow-Up Studies; Gene Amplification; Humans; Infant; Infant, Newborn; Male; N-Myc Proto-Oncogene Protein; Neoplasm Staging; Neuroblastoma; Prognosis; Survival Rate

Is middle cerebral artery Doppler related to neonatal and 2-year infant outcome in early fetal growth restriction? - Stampalija, Tamara; Arabin, Birgit; Wolf, Hans; Bilardo, Caterina M; Lees, Christoph (Am J Obstet Gynecol, 2017)
BACKGROUND: Reduced fetal middle cerebral artery Doppler impedance is associated with hypoxemia in fetal growth restriction. It remains unclear as to whether this finding could be useful in timing delivery, especially in the third trimester. In this regard there is a paucity of evidence from prospective studies. OBJECTIVES: The aim of this study was to determine whether there is an association between middle cerebral artery Doppler impedance and its ratio with the umbilical artery in relation to neonatal and 2 year infant outcome in early fetal growth restriction (26-31 weeks of gestation). Additionally we sought to explore which ratio is more informative for clinical use. STUDY DESIGN: This is a secondary analysis from the Trial of Randomized Umbilical and Fetal Flow in Europe, a prospective, multicenter, randomized management study on different antenatal monitoring strategies (ductus venosus Doppler changes and computerized cardiotocography short-term variation) in fetal growth restriction diagnosed between 26 and 31 weeks. We analyzed women with middle cerebral artery Doppler measurement at study entry and within 1 week before delivery and with complete postnatal follow-up (374 of 503). The primary outcome was survival without neurodevelopmental impairment at 2 years corrected for prematurity. Neonatal outcome was defined as survival until first discharge home without severe neonatal morbidity. Z-scores were calculated for middle cerebral artery pulsatility index and both umbilicocerebral and cerebroplacental ratios. Odds ratios of Doppler parameter Z-scores for neonatal and 2 year infant outcome were calculated by multivariable logistic regression analysis adjusted for gestational age and birthweight p50 ratio. RESULTS: Higher middle cerebral artery pulsatility index at inclusion but not within 1 week before delivery was associated with neonatal survival without severe morbidity (odds ratio, 1.24; 95% confidence interval, 1.02-1.52). Middle cerebral artery pulsatility index Z-score and umbilicocerebral ratio Z-score at inclusion were associated with 2 year survival with normal neurodevelopmental outcome (odds ratio, 1.33; 95% confidence interval, 1.03-1.72, and odds ratio, 0.88; 95% confidence interval, 0.78-0.99, respectively) as were gestation at delivery and birthweight p50 ratio (odds ratio, 1.41; 95% confidence interval, 1.20-1.66, and odds ratio, 1.86; 95% confidence interval, 1.33-2.60, respectively). When comparing cerebroplacental ratio against umbilicocerebral ratio, the incremental range of the cerebroplacental ratio tended toward zero, whereas the umbilicocerebral ratio tended toward infinity as the values became more abnormal. CONCLUSION: In a monitoring protocol based on ductus venosus and cardiotocography in early fetal growth restriction (26-31 weeks of gestation), the impact of middle cerebral artery Doppler and its ratios on outcome is modest and less marked than birthweight and delivery gestation. It is unlikely that middle cerebral artery Doppler and its ratios are informative in optimizing the timing of delivery in fetal growth restriction before 32 weeks of gestation. The umbilicocerebral ratio allows for a better differentiation in the abnormal range than the cerebroplacental ratio.
Keywords: Birth Weight; Child Development; Child, Preschool; Delivery, Obstetric; Female; Fetal Growth Retardation; Gestational Age; Humans; Middle Cerebral Artery; Pregnancy; Prospective Studies; Pulsatile Flow; Ultrasonography, Doppler; Ultrasonography, Prenatal; Umbilical Arteries

Multicentric Case-Control Study on Azathioprine Dose and Pharmacokinetics in Early-onset Pediatric Inflammatory Bowel Disease. - Stocco, Gabriele; Martelossi, Stefano; Arrigo, Serena; Barabino, Arrigo; Aloi, Marina; Martinelli, Massimo; Miele, Erasmo; Knafelz, Daniela; Romano, Claudio; Naviglio, Samuele; Favretto, Diego; Cuzzoni, Eva; et al. (Inflamm Bowel Dis, 2017)
BACKGROUND: Early-onset inflammatory bowel disease (IBD) is generally aggressive, with a high probability of complications and need of surgery. Despite the introduction of highly effective biological drugs, treatment with azathioprine continues to be important even for early-onset IBD; however, in these patients azathioprine response seems to be reduced. This study evaluated azathioprine doses, metabolite concentrations, and their associations with patients' age in children with IBD treated at 6 tertiary pediatric referral centers. METHODS: Azathioprine doses, metabolites, and clinical effects were assessed after at least 3 months of therapy in 17 early-onset (age < 6 yr, cases) and 51 nonearly-onset (aged > 12 and <18 yrs, controls) patients with IBD. Azathioprine dose was titrated on therapeutic efficacy (response and adverse effects). Azathioprine metabolites and thiopurine methyltransferase activity were determined by high-performance liquid chromatography with ultra violet-vis detection (HPLC-UV) methods. RESULTS: Frequency of patients in remission was similar among early-onset and control groups, respectively (82% and 84%, P value = 0.72). Early-onset patients required higher doses of azathioprine (median 2.7 versus 2.0 mg·kg·d, P value = 1.1 × 10). Different doses resulted in comparable azathioprine active thioguanine nucleotide metabolite concentrations (median 263 versus 366 pmol/8 × 10 erythrocytes, P value = 0.41) and methylmercaptopurine nucleotide concentrations (median 1455 versus 1532 pmol/8 × 10 erythrocytes, P value = 0.60). Lower ratios between thioguanine nucleotide metabolites and azathioprine doses were found in early-onset patients (median 98 versus 184 pmol/8 × 10 erythrocytes·mg·kg·d, P value = 0.017). Interestingly, early-onset patients presented also higher thiopurine methyltransferase activity (median 476 versus 350 nmol methylmercaptopurine/mg hemoglobin/h, P-value = 0.046). CONCLUSIONS: This study demonstrated that patients with early-onset IBD present increased inactivating azathioprine metabolism, likely because of elevated activity of the enzyme thiopurine methyltransferase.
Keywords: Adolescent; Age of Onset; Antimetabolites; Azathioprine; Case-Control Studies; Child; Child, Preschool; Chromatography, High Pressure Liquid; Dose-Response Relationship, Drug; Erythrocytes; Female; Guanine Nucleotides; Humans; Inflammatory Bowel Diseases; Male; Mercaptopurine; Methyltransferases; Thioguanine

Mutations of RUNX1 in families with inherited thrombocytopenia. - De Rocco, Daniela; Melazzini, Federica; Marconi, Caterina; Pecci, Alessandro; Bottega, Roberta; Gnan, Chiara; Palombo, Flavia; Giordano, Paola; Coccioli, Maria Susanna; Glembotsky, Ana C; Heller, Paula G; Seri, Marco; et al. (Am J Hematol, 2017)
Keywords: Adult; Blood Platelets; Cell Size; Child; Child, Preschool; Core Binding Factor Alpha 2 Subunit; Female; Frameshift Mutation; Genes, Dominant; Heterozygote; Humans; Introns; Leukemia, Myeloid, Acute; Male; Middle Aged; Mutation, Missense; Protein Domains; RNA Splice Sites; Sequence Deletion; Thrombocythemia, Essential; Thrombopoietin; Transcriptional Activation; Young Adult

MYH9 gene mutations associated with bleeding. - Savoia, Anna; De Rocco, Daniela; Pecci, Alessandro (Platelets, 2017)
Keywords: Asymptomatic Diseases; Blood Platelets; Cell Size; Chromosomes, Human, Pair 22; Exons; Gene Expression; Genetic Association Studies; Genotype; Hearing Loss, Sensorineural; Hemorrhage; Humans; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Phenotype; Platelet Count; Protein Domains; Severity of Illness Index; Thrombocytopenia

Neuroimaging Changes in Menkes Disease, Part 1. - Manara, R; D'Agata, L; Rocco, M C; Cusmai, R; Freri, E; Pinelli, L; Darra, F; Procopio, E; Mardari, R; Zanus, C; Di Rosa, G; Soddu, C; et al. (AJNR Am J Neuroradiol, 2017)
Menkes disease is a rare multisystem X-linked disorder of copper metabolism. Despite an early, severe, and progressive neurologic involvement, our knowledge of brain involvement remains unsatisfactory. The first part of this retrospective and review MR imaging study aims to define the frequency rate, timing, imaging features, and evolution of intracranial vascular and white matter changes. According to our analysis, striking but also poorly evolutive vascular abnormalities characterize the very early phases of disease. After the first months, myelination delay becomes evident, often in association with protean focal white matter lesions, some of which reveal an age-specific brain vulnerability. In later phases of the disease, concomitant progressive neurodegeneration might hinder the myelination progression. The currently enriched knowledge of neuroradiologic finding evolution provides valuable clues for early diagnosis, identifies possible MR imaging biomarkers of new treatment efficacy, and improves our comprehension of possible mechanisms of brain injury in Menkes disease.
Keywords: Brain; Disease Progression; Female; Humans; Magnetic Resonance Imaging; Male; Menkes Kinky Hair Syndrome; Neuroimaging; Retrospective Studies; White Matter

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near , , , , , and , and provide new replication evidence for a further 2 signals in and Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

Phenotypic expression of 19q13.32 microdeletions: Report of a new patient and review of the literature. - Travan, Laura; Naviglio, Samuele; De Cunto, Angela; Pellegrin, Andrea; Pecile, Vanna; Spinelli, Alessandro Mauro; Cappellani, Stefania; Faletra, Flavio (Am J Med Genet A, 2017)
The phenotypic manifestations of microdeletions in the 19q13.32 region are still poorly known. In this paper we report a patient who presented with hypotonia, developmental delay, facial dysmorphism, micrognathia, kyphoscoliosis, and buried penis. Chromosomal microarray revealed an interstitial 327 kb de novo microdeletion in the 19q13.32 region comprising eight genes (ARGHAP35, NPAS1, TMEM160, ZC3H4, SAE1, BBC3, MIR3190, and MIR3191). Previously reported cases of microdeletions in the 19q13.32 region were reviewed and compared to our patient, highlighting the common features of a possible 19q13.32 microdeletion syndrome.

Polymorphisms in key bone modulator cytokines genes influence bisphosphonates therapy in postmenopausal women. - Lima, C A D; Javorski, N R; Souza, A P O; Barbosa, A D; Valença, A P M C; Crovella, S; Souza, P R E; de Azevêdo Silva, J; Sandrin-Garcia, P (Inflammopharmacology, 2017)
Osteoporosis is a multifactorial and debilitating disease resulting from decreased bone mineral density (BMD) and loss of tissue microarchitecture. Ineffective therapies may lead to bone fractures and subsequent death. Single nucleotide polymorphisms (SNPs) in key immune regulator genes have been associated with therapeutic response to bisphosphonates, which are the first therapeutic line of choice for osteoporosis. However, cytokine pathways and their relation with therapeutic adhesion remain to be fully elucidated. Aimed at better understanding these processes, we investigated the response to bisphosphonate therapy in postmenopausal women and four SNPs in key proinflammatory cytokines genes: IL23R +2284 (C>A) (rs10889677), IL17A +672 (G>A) (rs7747909), IL12B +1188 (T>G) (rs3212227) and INF-γ -1616 (G>A) (rs2069705). A total of 69 patients treated with bisphosphonate were followed for a period of 1 up to 4 years, genotyped and compared according to their changes in bone mineral density (BMD) and level of biochemical markers during their treatment. The INF-γ -1616 G/G associated with increased BMD values in femoral neck (GG/AA, p = 0.016) and decreased BMD values in total hip (GG/GA, p = 0.019; GG/AA, p = 0.011). In relation to biochemical markers, INF-γ -1616 SNP associated with increased alkaline phosphatase (GG/AA; p < 0.0001) and parathyroid hormone levels (AA/GA; p = 0.017). Vitamin D values changes were related to IL17A +672 (GG/GA, p = 0.034) and to IL12B +1188 (TT/TG, p = 0.046) SNPs. Besides, significant differences in changes of calcium levels correlated with IL23R +2284 (CC/CA, p = 0.016) genotypes. Altogether, we suggest that these polymorphisms may play an important role for therapeutic decisions in osteoporosis treatment.
Keywords: Aged; Bone Density; Bone Remodeling; Cytokines; Diphosphonates; Female; Humans; Middle Aged; Osteoporosis, Postmenopausal; Polymorphism, Single Nucleotide; Postmenopause

Predictors of Relapse after Discontinuing Systemic Treatment in Childhood Autoimmune Chronic Uveitis. - Simonini, Gabriele; Bracaglia, Claudia; Cattalini, Marco; Taddio, Andrea; Brambilla, Alice; de Libero, Cinzia; Pires Marafon, Denise; Caputo, Roberto; Cimaz, Rolando (J Rheumatol, 2017)
OBJECTIVE: To identify clinical predictors of relapse in childhood autoimmune chronic uveitis after stopping systemic treatment. METHODS: A retrospective, multicenter, cohort study. RESULTS: Ninety-four children in remission, receiving no treatments and with at least a 6-month followup, were enrolled. A higher probability of maintaining remission after discontinuing treatment was shown in idiopathic compared with juvenile idiopathic arthritis uveitis (Mantel-Cox chi-square = 23.21) if inactivity had been obtained within 6 months from starting systemic treatment (Mantel-Cox chi-square = 24.17) and by antitumor necrosis factor-α treatment (Mantel-Cox chi-square = 6.43). CONCLUSION: Type of disease, time, and type of systemic therapy to achieve inactivity predict different duration of uveitis remission after treatment withdrawal.
Keywords: Adolescent; Antirheumatic Agents; Autoimmune Diseases; Child; Child, Preschool; Female; Humans; Male; Predictive Value of Tests; Recurrence; Retrospective Studies; Treatment Outcome; Uveitis; Withholding Treatment

Pregnant with HIV before age 25: data from a large national study in Italy, 2001-2016. - Floridia, M; Masuelli, G; Tamburrini, E; Cetin, I; Liuzzi, G; Martinelli, P; Guaraldi, G; Spinillo, A; Vimercati, A; Maso, G; Pinnetti, C; Frisina, V; et al. (Epidemiol Infect, 2017)
Young pregnant women with HIV may be at significant risk of unplanned pregnancy, lower treatment coverage, and other adverse pregnancy outcomes. In a large cohort of pregnant women with HIV in Italy, among 2979 pregnancies followed in 2001-2016, 9·0% were in women <25 years, with a significant increase over time (2001-2005: 7·0%; 2006-2010: 9·1%; 2011-2016: 12·2%, P < 0·001). Younger women had a lower rate of planned pregnancy (23·2% vs. 37·7%, odds ratio (OR) 0·50, 95% confidence interval (CI) 0·36-0·69), were more frequently diagnosed with HIV in pregnancy (46·5% vs. 20·9%, OR 3·29, 95% CI 2·54-4·25), and, if already diagnosed with HIV before pregnancy, were less frequently on antiretroviral treatment at conception (<25 years: 56·3%; ⩾25 years: 69·0%, OR 0·58, 95% CI 0·41-0·81). During pregnancy, treatment coverage was almost universal in both age groups (98·5% vs. 99·3%), with no differences in rate of HIV viral suppression at third trimester and adverse pregnancy outcomes. The data show that young women represent a growing proportion of pregnant women with HIV, and are significantly more likely to have unplanned pregnancy, undiagnosed HIV infection, and lower treatment coverage at conception. During pregnancy, antiretroviral treatment, HIV suppression, and pregnancy outcomes are similar compared with older women. Earlier intervention strategies may provide additional benefits in the quality of care for women with HIV.
Keywords: Adolescent; Cohort Studies; Female; HIV Infections; Humans; Italy; Odds Ratio; Pregnancy; Young Adult

A premenarcheal girl with urogenital bleeding. - Lora, Angela; Scrimin, Federica; Taddio, Andrea; Ventura, Alessandro; Barbi, Egidio (Arch Dis Child, 2017)

Preoperative Serum Human Epididymis Protein 4 Levels in Early Stage Endometrial Cancer: A Prospective Study. - Fanfani, Francesco; Restaino, Stefano; Cicogna, Stefania; Petrillo, Marco; Montico, Marcella; Perrone, Emanuele; Radillo, Oriano; De Leo, Rossella; Ceccarello, Matteo; Scambia, Giovanni; Ricci, Giuseppe (Int J Gynecol Cancer, 2017)
OBJECTIVE: The aim of the study was to evaluate the prognostic value of human epididymis protein 4 (HE4) and cancer antigen 125 markers with pathological prognostic factor to complete the preoperative clinical panel and help the treatment planning. METHODS: This prospective multicenter study was conducted in 2 gynecologic oncology centers between 2012 and 2014 (Institute for Maternal and Child Health IRCCS Burlo Garofolo in Trieste and Catholic University of the Sacred Heart in Rome, Italy). We enrolled 153 patients diagnosed with clinical early (International Federation of Gynecology and Obstetrics stages I-II) type I endometrial cancer. RESULTS: Human epididymis protein 4 levels seemed to be strictly related to age (P < 0.001) and menopausal status (P < 0.002). Compared with myometrial invasion (MI), the HE4 values were significantly higher in case of invasion of greater than 50% of the thickness: MI of greater than 50%, median of 94.85 pmol/L (38.3-820.8 pmol/L), versus MI of less than 50%, median of 65.65 pmol/L (25.1-360.2 pmol/L), (P < 0.001). The HE4 levels increase significantly with increasing tumor size: diameter of larger than 2 cm, median of 86.9 pmol/L (35.8-820.8 pmol/L), versus diameter of smaller than 2 cm, median of 52.2 pmol/L (33.3-146.8 pmol/L), (P < 0.001). In our population, HE4 did not correlate with the histological grade, endometrial cancer type I versus type II (P = 0.86), the lymphovascular infiltration (P = 0.12), and the cervical invasion (P = 0.6). We established a new variable, considering 3 high-risk tumor features: MI of greater than 50% and/or histological G3 and/or type II. Human epididymis protein 4 levels significantly increase in high-risk tumors (high risk HE4, 93.6 pmol/L vs low-medium risk, 65.5 pmol/L; P < 0.001). CONCLUSIONS: A preoperative HE4 evaluation could help stratify patients with deep invasion and/or metastatic disease and is correlated with other relevant prognostic factors to be considered to tailor an adequate surgical strategy.
Keywords: Adult; Aged; Aged, 80 and over; Biomarkers, Tumor; Endometrial Neoplasms; Female; Humans; Middle Aged; Neoplasm Staging; Preoperative Care; Prognosis; Prospective Studies; Proteins

Rare and low-frequency coding variants alter human adult height. - Marouli, Eirini; Graff, Mariaelisa; Medina-Gomez, Carolina; Lo, Ken Sin; Wood, Andrew R; Kjaer, Troels R; Fine, Rebecca S; Lu, Yingchang; Schurmann, Claudia; Highland, Heather M; Rüeger, Sina; Thorleifsson, Gudmar; et al. (Nature, 2017)
Height is a highly heritable, classic polygenic trait with approximately 700 common associated variants identified through genome-wide association studies so far. Here, we report 83 height-associated coding variants with lower minor-allele frequencies (in the range of 0.1-4.8%) and effects of up to 2 centimetres per allele (such as those in IHH, STC2, AR and CRISPLD2), greater than ten times the average effect of common variants. In functional follow-up studies, rare height-increasing alleles of STC2 (giving an increase of 1-2 centimetres per allele) compromised proteolytic inhibition of PAPP-A and increased cleavage of IGFBP-4 in vitro, resulting in higher bioavailability of insulin-like growth factors. These 83 height-associated variants overlap genes that are mutated in monogenic growth disorders and highlight new biological candidates (such as ADAMTS3, IL11RA and NOX4) and pathways (such as proteoglycan and glycosaminoglycan synthesis) involved in growth. Our results demonstrate that sufficiently large sample sizes can uncover rare and low-frequency variants of moderate-to-large effect associated with polygenic human phenotypes, and that these variants implicate relevant genes and pathways.
Keywords: ADAMTS Proteins; Adult; Alleles; Body Height; Cell Adhesion Molecules; Female; Gene Frequency; Genetic Variation; Genome, Human; Glycoproteins; Glycosaminoglycans; Hedgehog Proteins; Humans; Intercellular Signaling Peptides and Proteins; Interferon Regulatory Factors; Interleukin-11 Receptor alpha Subunit; Male; Multifactorial Inheritance; NADPH Oxidase 4; NADPH Oxidases; Phenotype; Pregnancy-Associated Plasma Protein-A; Procollagen N-Endopeptidase; Proteoglycans; Proteolysis; Receptors, Androgen; Somatomedins

Rate, correlates and outcomes of repeat pregnancy in HIV-infected women. - Floridia, M; Tamburrini, E; Masuelli, G; Martinelli, P; Spinillo, A; Liuzzi, G; Vimercati, A; Alberico, S; Maccabruni, A; Pinnetti, C; Frisina, V; Dalzero, S; et al. (HIV Med, 2017)
OBJECTIVES: The aim of the study was to assess the rate, determinants, and outcomes of repeat pregnancies in women with HIV infection. METHODS: Data from a national study of pregnant women with HIV infection were used. Main outcomes were preterm delivery, low birth weight, CD4 cell count and HIV plasma viral load. RESULTS: The rate of repeat pregnancy among 3007 women was 16.2%. Women with a repeat pregnancy were on average younger than those with a single pregnancy (median age 30 vs. 33 years, respectively), more recently diagnosed with HIV infection (median time since diagnosis 25 vs. 51 months, respectively), and more frequently of foreign origin [odds ratio (OR) 1.36; 95% confidence interval (CI) 1.10-1.68], diagnosed with HIV infection in the current pregnancy (OR: 1.69; 95% CI: 1.35-2.11), and at their first pregnancy (OR: 1.33; 95% CI: 1.06-1.66). In women with sequential pregnancies, compared with the first pregnancy, several outcomes showed a significant improvement in the second pregnancy, with a higher rate of antiretroviral treatment at conception (39.0 vs. 65.4%, respectively), better median maternal weight at the start of pregnancy (60 vs. 61 kg, respectively), a higher rate of end-of-pregnancy undetectable HIV RNA (60.7 vs. 71.6%, respectively), a higher median birth weight (2815 vs. 2885 g, respectively), lower rates of preterm delivery (23.0 vs. 17.7%, respectively) and of low birth weight (23.4 vs. 15.4%, respectively), and a higher median CD4 cell count (+47 cells/μL), with almost no clinical progression to Centers for Disease Control and Prevention stage C (CDC-C) HIV disease (0.3%). The second pregnancy was significantly more likely to end in voluntary termination than the first pregnancy (11.4 vs. 6.1%, respectively). CONCLUSIONS: Younger and foreign women were more likely to have a repeat pregnancy; in women with sequential pregnancies, the second pregnancy was characterized by a significant improvement in several outcomes, suggesting that women with HIV infection who desire multiple children may proceed safely and confidently with subsequent pregnancies.
Keywords: Adult; Anti-HIV Agents; CD4 Lymphocyte Count; Emigrants and Immigrants; Female; HIV Infections; HIV-1; Humans; Infant, Low Birth Weight; Pregnancy; Premature Birth; Viral Load

Shifts of subgingival bacterial population after nonsurgical and pharmacological therapy of localized aggressive periodontitis, followed for 1 year by Ion Torrent PGM platform. - Campisciano, Giuseppina; Toschetti, Annamaria; Comar, Manola; Taranto, Rosanna Di; Berton, Federico; Stacchi, Claudio (Eur J Dent, 2017)
The possibility of targeting the hypervariable region V3 of the 16S rRNA gene using Ion Torrent Personal Genome Machine (PGM) could provide a complete analysis of subgingival plaque samples, potentially able to identify microbiological species missed by culture-based methods. A 16-year-old female smoker patient, affected by localized aggressive periodontitis, underwent a full-mouth disinfection protocol and was inserted in a 3-month recall program. Microbiological samples were collected at baseline and at 30, 100, 365 days follow-up and analyzed by Ion Torrent PGM. , , , and were the most represented pathogens at baseline. Nonsurgical treatment and systemic antibiotics drastically lowered the anaerobic species, and their presence remained limited after 100 days, while a consistent recolonization by anaerobic bacteria was detected at 365 days. The patient showed a general improvement of periodontal conditions. Differently from polymerase chain reaction and other microarray techniques, Ion Torrent performs a quantitative analysis of the microbiota, irrespective of the searched species. An accurate definition of the shifts of the bacterial community might help periodontal researchers for a better understanding of the impact of different treatment approaches or in intercepting nonresponsive conditions.

Somatic symptom disorder was common in children and adolescents attending an emergency department complaining of pain. - Cozzi, Giorgio; Minute, Marta; Skabar, Aldo; Pirrone, Angela; Jaber, Mohamad; Neri, Elena; Montico, Marcella; Ventura, Alessandro; Barbi, Egidio (Acta Paediatr, 2017)
AIM: The aim of this study was to quantify the prevalence of somatic pain in a paediatric emergency department (ED). METHODS: We conducted a prospective observational study using patients admitted to the ED of an Italian children's hospital between December 2014 and February 2015. We enrolled children aged 7-17 who turned up at the ED complaining of pain. Patients and parents were asked to fill in a questionnaire to allow the analysis of the patients' medical history and provide contact details for follow-up. We divided the enrolled patients into four groups: post-traumatic pain, organic pain, functional pain and somatic pain. The questionnaire was used to define pain characteristics and to generate an impairment score. RESULTS: Of the 713 patients who met inclusion criteria, 306 (42.9%) were enrolled in the study. Of these, 135 (44.0%) suffered from post-traumatic pain, 104 (34.0%) from organic pain, 41 (13.4%) from functional pain and 26 (8.6%) from somatic pain. Somatic pain patients had endured pain longer, had missed more school days and had suffered severe functional impairment. CONCLUSION: This study highlighted that somatic pain was a significant contributor to paediatric emergency room visits and should be suspected and diagnosed in children reporting pain.
Keywords: Adolescent; Child; Emergency Service, Hospital; Female; Humans; Italy; Male; Medically Unexplained Symptoms; Pain; Prospective Studies

Subclinical alteration of the cervical-vaginal microbiome in women with idiopathic infertility. - Campisciano, Giuseppina; Florian, Fiorella; D'Eustacchio, Angela; Stanković, David; Ricci, Giuseppe; De Seta, Francesco; Comar, Manola (J Cell Physiol, 2017)
Biomarkers have a wide application in research and clinic, they help to choose the correct treatment for diseases. Recent studies, addressing the vaginal microbiome using next generation sequencing (NGS), reported the involvement of bacterial species in infertility. We compared the vaginal microbiome of idiopathic infertile women with that of healthy, including bacterial vaginosis affected women and non-idiopathic infertile women, to identify bacterial species suitable as biomarkers. Information on microorganisms was obtained from the V3-16S rDNA sequencing of cervical-vaginal fluids of 96 women using the Ion Torrent platform. Data were processed with QIIME and classified against the Vaginal 16S rDNA Reference Database. The analysis revealed a significant beta-diversity variation (p < 0.001) between the four groups included in the study. L. iners, L. crispatus, and L. gasseri distinguished idiopathic infertile women from the other groups. In these women, a microbial profile similar to that observed in bacterial vaginosis women has been detected. Our results suggest that the quantitative assessment and identification of specific microorganisms of the cervical-vaginal microflora could increase the accuracy of available tools for the diagnosis of infertility and improve the adoption of therapeutic protocols.
Keywords: Adult; Biodiversity; Cervix Uteri; Cohort Studies; Demography; Female; Humans; Infertility, Female; Microbiota; Species Specificity; Vagina; Vaginosis, Bacterial

Surgery for distal hypospadias: what about the catheter? - Scarpa, Maria-Grazia; Perin, Giordano; Di Grazia, Massimo; Codrich, Daniela; Pederiva, Federica; Guida, Edoardo; Lembo, Maria Antonietta; Giannotta, Antonio; Schleef, Jurgen (Pediatr Med Chir, 2017)
No agreed recommendations exist for timing of urethral stent removal, after distal hypospadias surgery. We compared our preliminary case series with outcomes from literature: 18/44 patients were treated with catheter and 26/44 without it. The surgical outcome was comparable in the two groups. After hypospadias surgery, the main advantage of the immediate postoperative catheter removal was the shorter hospital stay without negatively affecting the care and home management.
Keywords: Child; Child, Preschool; Device Removal; Humans; Hypospadias; Infant; Length of Stay; Male; Retrospective Studies; Stents; Treatment Outcome; Urinary Catheterization

Synthesis of Lipophilic Core-Shell FeO@SiO@Au Nanoparticles and Polymeric Entrapment into Nanomicelles: A Novel Nanosystem for in Vivo Active Targeting and Magnetic Resonance-Photoacoustic Dual Imaging. - Monaco, Ilaria; Arena, Francesca; Biffi, Stefania; Locatelli, Erica; Bortot, Barbara; La Cava, Francesca; Marini, Giada Maria; Severini, Giovanni Maria; Terreno, Enzo; Comes Franchini, Mauro (Bioconjug Chem, 2017)
In this work, iron/silica/gold core-shell nanoparticles (FeO@SiO@Au NPs) characterized by magnetic and optical properties have been synthesized to obtain a promising theranostic platform. To improve their biocompatibility, the obtained multilayer nanoparticles have been entrapped in polymeric micelles, decorated with folic acid moieties, and tested in vivo for photoacoustic and magnetic resonance imaging detection of ovarian cancer.
Keywords: Animals; Cell Proliferation; Female; Ferric Compounds; Folic Acid; Gold; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Magnetite Nanoparticles; Mice; Mice, Inbred BALB C; Mice, Nude; Micelles; Multimodal Imaging; Ovarian Neoplasms; Photoacoustic Techniques; Polymers; Silicon Dioxide; Tumor Cells, Cultured; Xenograft Model Antitumor Assays

Thrombogenesis in Thrombophilic Pregnancy: Evaluation of Low-Molecular-Weight Heparin Prophylaxis. - Simeone, Roberto; Giacomello, Roberta; Bruno, Germano; Parco, Sergio; Maximova, Natalia; Martinelli, Monica; Zito, Gabriella; Luppi, Stefania; Cervi, Gina; Ricci, Giuseppe (Acta Haematol, 2017)
The aim of this study is to investigate thrombogenesis and the hypercoagulable changes in pregnant women affected by thrombophilia who received low-molecular-weight heparin (LWMH) prophylaxis. We included 21 pregnant women affected by thrombophilia treated with LWMH and 20 nontreated normal pregnant women as the control group. The sample group of thrombophilic pregnant women included different conditions (factor V Leiden mutation, protein C deficiency, protein S deficiency, antiphospholipid antibodies syndrome, and combined defects). Three blood samples were collected during pregnancy (i.e., at 16, 20, and 24 weeks) and tested for activated partial thromboplastin time and prothrombin fragment F1 + 2 (F1 + 2); anti-FXa activity was tested only in treated thrombophilic pregnant women. F1 + 2 levels progressively increased during pregnancy in both study groups. However, the F1 + 2 increase in women exposed to heparin prophylaxis was significantly lower than that in normal pregnant women in all 3 measurements carried out during gestation (p < 0.05); a statistically significant inverse correlation between F1 + 2 levels and anti-Xa activity (R = -0.8575, p < 0.05) was observed in treated women during pregnancy. Our findings suggest that F1 + 2 in addition to anti-Xa measurement could be used to adjust LWMH prophylaxis, at least in high-risk pregnant women.
Keywords: Adult; Anticoagulants; Case-Control Studies; Factor Xa Inhibitors; Female; Heparin, Low-Molecular-Weight; Humans; Nadroparin; Partial Thromboplastin Time; Peptide Fragments; Pilot Projects; Pregnancy; Pregnancy Complications, Hematologic; Prothrombin; Thrombophilia; Thrombosis

Whole-Genome Sequencing Coupled to Imputation Discovers Genetic Signals for Anthropometric Traits. - Tachmazidou, Ioanna; Süveges, Dániel; Min, Josine L; Ritchie, Graham R S; Steinberg, Julia; Walter, Klaudia; Iotchkova, Valentina; Schwartzentruber, Jeremy; Huang, Jie; Memari, Yasin; McCarthy, Shane; Crawford, Andrew A; et al. (Am J Hum Genet, 2017)
Deep sequence-based imputation can enhance the discovery power of genome-wide association studies by assessing previously unexplored variation across the common- and low-frequency spectra. We applied a hybrid whole-genome sequencing (WGS) and deep imputation approach to examine the broader allelic architecture of 12 anthropometric traits associated with height, body mass, and fat distribution in up to 267,616 individuals. We report 106 genome-wide significant signals that have not been previously identified, including 9 low-frequency variants pointing to functional candidates. Of the 106 signals, 6 are in genomic regions that have not been implicated with related traits before, 28 are independent signals at previously reported regions, and 72 represent previously reported signals for a different anthropometric trait. 71% of signals reside within genes and fine mapping resolves 23 signals to one or two likely causal variants. We confirm genetic overlap between human monogenic and polygenic anthropometric traits and find signal enrichment in cis expression QTLs in relevant tissues. Our results highlight the potential of WGS strategies to enhance biologically relevant discoveries across the frequency spectrum.
Keywords: Anthropometry; Body Height; Cohort Studies; Databases, Genetic; DNA Methylation; Female; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Lipodystrophy; Male; Meta-Analysis as Topic; Obesity; Physical Chromosome Mapping; Quantitative Trait Loci; Sequence Analysis, DNA; Sex Characteristics; Syndrome; United Kingdom

Withdrawal Assessment Tool-1 Monitoring in PICU: A Multicenter Study on Iatrogenic Withdrawal Syndrome. - Amigoni, Angela; Mondardini, Maria Cristina; Vittadello, Ilaria; Zaglia, Federico; Rossetti, Emanuele; Vitale, Francesca; Ferrario, Stefania; Savron, Fabio; Coffaro, Giancarlo; Brugnaro, Luca; Amato, Roberta; Wolfler, Andrea; et al. (Pediatr Crit Care Med, 2017)
OBJECTIVES: Withdrawal syndrome is an adverse reaction of analgesic and sedative therapy, with a reported occurrence rate between 17% and 57% in critically ill children. Although some factors related to the development of withdrawal syndrome have been identified, there is weak evidence for the effectiveness of preventive and therapeutic strategies. The main aim of this study was to evaluate the frequency of withdrawal syndrome in Italian PICUs, using a validated instrument. We also analyzed differences in patient characteristics, analgesic and sedative treatment, and patients' outcome between patients with and without withdrawal syndrome. DESIGN: Observational multicenter prospective study. SETTING: Eight Italian PICUs belonging to the national PICU network Italian PICU network. PATIENTS: One hundred thirteen patients, less than 18 years old, mechanically ventilated and treated with analgesic and sedative therapy for five or more days. They were admitted in PICU from November 2012 to May 2014. INTERVENTIONS: Symptoms of withdrawal syndrome were monitored with Withdrawal Assessment Tool-1 scale. MEASUREMENTS AND MAIN RESULTS: The occurrence rate of withdrawal syndrome was 64.6%. The following variables were significantly different between the patients who developed withdrawal syndrome and those who did not: type, duration, and cumulative dose of analgesic therapy; duration and cumulative dose of sedative therapy; clinical team judgment about analgesia and sedation's difficulty; and duration of analgesic weaning, mechanical ventilation, and PICU stay. Multivariate logistic regression analysis revealed that patients receiving morphine as their primary analgesic were 83% less likely to develop withdrawal syndrome than those receiving fentanyl or remifentanil. CONCLUSIONS: Withdrawal syndrome was frequent in PICU patients, and patients with withdrawal syndrome had prolonged hospital treatment. We suggest adopting the lowest effective dose of analgesic and sedative drugs and frequent reevaluation of the need for continued use. Further studies are necessary to define common preventive and therapeutic strategies.
Keywords: Adolescent; Analgesics; Child; Child, Preschool; Critical Care; Female; Humans; Hypnotics and Sedatives; Iatrogenic Disease; Infant; Infant, Newborn; Intensive Care Units, Pediatric; Italy; Logistic Models; Male; Prospective Studies; Respiration, Artificial; Substance Withdrawal Syndrome

Abnormal expression of leiomyoma cytoskeletal proteins involved in cell migration. - Ura, Blendi; Scrimin, Federica; Arrigoni, Giorgio; Athanasakis, Emmanouil; Aloisio, Michelangelo; Monasta, Lorenzo; Ricci, Giuseppe (Oncol Rep, 2016)
Uterine leiomyomas are monoclonal tumors. Several factors are involved in the neoplastic transformation of the myometrium. In our study we focused on dysregulated cytoskeletal proteins in the leiomyoma as compared to the myometrium. Paired tissue samples of ten leiomyomas and adjacent myometria were obtained and analyzed by two‑dimensional gel electrophoresis (2-DE). Mass spectrometry was used for protein identification, and western blotting for 2-DE data validation. The values of ten cytoskeletal proteins were found to be significantly different: eight proteins were upregulated in the leiomyoma and two proteins were downregulated. Three of the upregulated proteins (myosin regulatory light polypeptide 9, four and a half LIM domains protein 1 and LIM and SH3 domain protein 1) are involved in cell migration, while downregulated protein transgelin is involved in replicative senescence. Myosin regulatory light polypeptide 9 (MYL9) was further validated by western blotting because it is considered to be a cell migration marker in several cancers and could play a key role in leiomyoma development. Our data demonstrate significant alterations in the expression of cytoskeletal proteins involved in leiomyoma growth. A better understanding of the involvement of cytoskeletal proteins in leiomyoma pathogenesis may contribute to the identification of new therapeutic targets and the development of new pharmacological approaches.

Acute myelitis as presenting symptom of HIV-HTLV-1 co-infection. - Cucca, A; Stragapede, L; Antonutti, L; Catalan, M; Caracciolo, I; Valentinotti, Romina; Granato, A; D'Agaro, P; Manganotti, P (J Neurovirol, 2016)
A 21-year-old woman presented with acute-onset spastic paraparesis. The MRI spinal scan revealed a contrast-enhanced T2 hyperintensity between C5-T2. The most common neurotropic pathogens were excluded by first level tests. Under suspicion of an acute immune-mediated myelitis, a corticosteroid therapy was administered. However, a seropositivity for both human immunodeficiency virus (HIV) type 1 and human T-lymphotropic virus (HTLV) subsequently emerged. An antiretroviral therapy was started while steroids discontinued. Patient's clinical conditions remained unchanged. HIV-HTLV-1 co-infection should be included in the differential diagnosis of any acute myelitis, even in patients with a preserved immune status and no risk factors.

Anti-ApoA-1 IgG serum levels predict worse poststroke outcomes. - Carbone, Federico; Satta, Nathalie; Montecucco, Fabrizio; Virzi, Julien; Burger, Fabienne; Roth, Aline; Roversi, Gloria; Tamborino, Carmine; Casetta, Ilaria; Seraceni, Silva; Trentini, Alessandro; Padroni, Marina; et al. (Eur J Clin Invest, 2016)
BACKGROUND: Autoantibodies to apolipoprotein A-1 (anti-ApoA-1 IgG) were shown to predict major adverse cardiovascular events and promote atherogenesis. However, their potential relationship with clinical disability and ischaemic lesion volume after acute ischaemic stroke (AIS) remains unexplored. MATERIALS AND METHODS: We included n = 76 patients admitted for AIS and we investigated whether baseline serum anti-ApoA-1 IgG levels could predict (i) AIS-induced clinical disability [assessed by the modified Rankin Scale (mRS)], and (ii) AIS-related ischaemic lesion volume [assessed by Computed Tomography (CT)]. We also evaluated the possible pro-apoptotic and pro-necrotic effects of anti-ApoA-1 IgG on human astrocytoma cell line (U251) using flow cytometry. RESULTS: High levels of anti-ApoA-1 IgG were retrieved in 15·8% (12/76) of patients. Increased baseline levels of anti-ApoA-1 IgG were independently correlated with worse mRS [β = 0·364; P = 0·002; adjusted odds ratio (OR): 1·05 (95% CI 1·01-1·09); P = 0·017] and CT-assessed ischaemic lesion volume [β = 0·333; P < 0·001; adjusted OR: 1·06 (95% CI 1·01-1·12); P = 0·048] at 3 months. No difference in baseline clinical, biochemical and radiological characteristics was observed between patients with high vs. low levels of anti-ApoA-1 IgG. Incubating human astrocytoma cells with anti-ApoA-1 IgG dose dependently induced necrosis and apoptosis of U251 cells in vitro. CONCLUSION: Anti-ApoA-1 IgG serum levels at AIS onset are associated with poorer clinical recovery and worse brain lesion volume 3 months after AIS. These observations could be partly explained by the deleterious effect of anti-ApoA-1 IgG on human brain cell survival in vitro and may have clinical implication in the prediction of poor outcome in AIS.

Association between p21 Ser31Arg polymorphism and the development of cervical lesion in women infected with high risk HPV. - Lima, Géssica; Santos, Erinaldo; Angelo, Hildson; Oliveira, Micheline; Heráclio, Sandra; Leite, Fernanda; de Melo, Celso; Crovella, Sergio; Maia, Maria; Souza, Paulo (Tumour Biol, 2016)
Infection by high-risk human papillomavirus (HR-HPV) and single nucleotide polymorphism (SNP) in genes involved in cell cycle control, as p21 and p27, are important factors in the development of different types of human cancers. This study aims at investigating whether both the p21 Ser31Arg and p27 V109G polymorphisms are associated with susceptibility to the development of cervical lesions in women HR-HPV positive. We analyzed 132 women HPV positive and with cervical lesions or CC and 154 healthy control (HPV negative and without cervical lesions). p21 Ser31Arg and p27 V109G polymorphisms were analyzed using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method and sequencing. The p21 31Arg allele was associated with susceptibility for the development of cervical lesions (P* = 0.0009), while p27 V109G polymorphism showed no significant differences for this association (P* = 0.89). However, the combined effect of the polymorphisms showed that the presence of the CC genotype (SNP p21 Ser31Arg) conferred protection for the development of cervical lesions (OR = 0.39). p21 Ser31Arg and p27 V109G polymorphisms were not associated with the grade of cervical lesions (CINI, CINII, and CINIII) or CC (P* > 0.05). The HR-HPV more frequent in this study were of 16 (57.6 %) and 18 (37.1 %) types; however, no association was observed when both polymorphisms and risk factors analyzed were compared (P* > 0.05). Our findings suggest a possible association between p21 Ser31tabArg polymorphism and susceptibility to the development of cervical lesions in women from Pernambuco. Brazil.

Candidate Soluble Immune Mediators in Young Women with High-Risk Human Papillomavirus Infection: High Expression of Chemokines Promoting Angiogenesis and Cell Proliferation. - Zanotta, Nunzia; Tornesello, Maria Lina; Annunziata, Clorinda; Stellato, Giovanni; Buonaguro, Franco Maria; Comar, Manola (PLoS One, 2016)
BACKGROUND: The causal interpretation of cervical immune response to Human Papillomavirus (HPV) infection is complex and poorly characterized mainly due to the delicate balance that exists between viral infection, increase of inflammatory cytokines and host risk factors. This study aims to explore the significance of cervical immune mediators associated to cell survival, angiogenesis and interaction with immune response, in predicting the risk to develop HPV-related intraepithelial lesions. METHODS: A panel of 48 cytokines and growth factors were explored in a selected cohort of 168 immunocompetent women including 88 diagnosed with low (LSIL) or high (HSIL) squamous intraepithelial lesions of the cervix and 80 with normal cervical cytology (NIL). HPV genotyping was performed by Linear Array HPV test and the soluble concentration of 48 immune molecules was analyzed using the Bio-Plex platform. RESULTS: The prevalence of single HR-HPV infection was 30% in NIL and 100% in LSIL and HSIL women. The expression of 13 cytokines, including interleukins IL-6, IL-3, IL-12p40, IL-12p70, IL-16, IL-18, LIF, of chemokines CCL7 (MCP-3), CXCL9 (MIG), CXCL12 (SDF-1α) and of the tropic factors VEGF, G-CSF, M-CSF were significantly associated with the presence of infection, with levels being higher in women with precancerous lesions compared to NIL HPV negative women. Only the growth factor GM-CSF was positively associated with the cytological abnormalities. CONCLUSIONS: The ability of HR-HPV to escape from innate immune recognition and to orchestrate the production of specific inflammatory and growth factors, involved in early inflammatory response and in the cell-proliferating phase of intraepithelial damage, was documented in women before the development of cervical lesions.
Keywords: Adult; Cell Survival; Cervix Uteri; Chemokines; Cohort Studies; Female; Humans; Neovascularization, Pathologic; Papillomaviridae; Papillomavirus Infections

Carbamazepine-induced thrombocytopenic purpura in a child: Insights from a genomic analysis. - Abate, Maria Valentina; Stocco, Gabriele; Devescovi, Raffaella; Carrozzi, Marco; Pierobon, Chiara; Valencic, Erica; Lucafò, Marianna; Di Silvestre, Alessia; d'Adamo, Pio; Tommasini, Alberto; Decorti, Giuliana; Ventura, Alessandro (Blood Cells Mol Dis, 2016)

A Case of Prenatal Neurocytoma Associated With ATR-16 Syndrome. - Quadrifoglio, Mariachiara; Faletra, Flavio; Bussani, Rossana; Pecile, Vanna; Zennaro, Floriana; Grasso, Alessandra; Zandonà, Lorenzo; Alberico, Salvatore; Stampalija, Tamara (J Ultrasound Med, 2016)

CCR2 and CCR5 genes polymorphisms in women with cervical lesions from Pernambuco, Northeast Region of Brazil: a case-control study. - Santos, Erinaldo Ubirajara Damasceno Dos; Lima, Géssica Dayane Cordeiro de; Oliveira, Micheline de Lucena; Heráclio, Sandra de Andrade; Silva, Hildson Dornelas Angelo da; Crovella, Sergio; Maia, Maria de Mascena Diniz; Souza, Paulo Roberto Eleutério de (Mem Inst Oswaldo Cruz, 2016)
Polymorphisms in chemokine receptors play an important role in the progression of cervical intraepithelial neoplasia (CIN) to cervical cancer (CC). Our study examined the association of CCR2-64I (rs1799864) andCCR5-Δ32 (rs333) polymorphisms with susceptibility to develop cervical lesion (CIN and CC) in a Brazilian population. The genotyping of 139 women with cervical lesions and 151 women without cervical lesions for the CCR2-64I and CCR5-Δ32 polymorphisms were performed using polymerase chain reaction-restriction fragment length polymorphism. The individuals carrying heterozygous or homozygous genotypes (GA+AA) for CCR2-64I polymorphisms seem to be at lower risk for cervical lesion [odds ratio (OR) = 0.37, p = 0.0008)]. The same was observed for the A allele (OR = 0.39, p = 0.0002), while no association was detected (p > 0.05) with CCR5-Δ32 polymorphism. Regarding the human papillomavirus (HPV) type, patients carrying the CCR2-64Ipolymorphism were protected against infection by HPV type 16 (OR = 0.35, p = 0.0184). In summary, our study showed a protective effect ofCCR2-64I rs1799864 polymorphism against the development of cervical lesions (CIN and CC) and in the susceptibility of HPV 16 infection.

CD209 promoter polymorphisms associate with HCV infection and pegylated-interferon plus ribavirin treatment response. - Zupin, Luisa; Polesello, Vania; Alberi, Giulia; Moratelli, Giulia; Crocè, Saveria Lory; Masutti, Flora; Pozzato, Gabriele; Crovella, Sergio; Segat, Ludovica (Mol Immunol, 2016)
Hepatitis C is a severe liver disease caused by hepatitis C virus that could persist in the host causing progression towards chronic disease in about 80% of the cases. Pegylated-interferon plus ribavirin was the gold standard therapy, however treatment's response was quite variable among individuals and different host/viral factors may play a role in disease outcome. The cluster of differentiation 209 (CD209 antigen) is a component of the innate immune system able to recognize HCV and consequently activating the immune response. We enrolled 203 Italian HCV infected patients and 220 healthy controls investigating if five promoter polymorphisms within CD209 gene (encoding for CD209 antigen) correlated with HCV infection susceptibility, spontaneous viral clearance and interferon treatment response. CD209 -939G>A and -871A>G polymorphisms associated with HCV infection susceptibility, while, CD209 -871A>G and -336A>G polymorphisms associated with response to treatment. In conclusion, CD209 polymorphisms could play a role in the susceptibility to HCV infection as well as interferon treatment response in our study population from North-East of Italy.

Circulating levels of TNF-related apoptosis inducing-ligand are decreased in patients with large adult-type granulosa cell tumors-implications for therapeutic potential. - Färkkilä, Anniina; Zauli, Giorgio; Haltia, Ulla-Maija; Pihlajoki, Marjut; Unkila-Kallio, Leila; Secchiero, Paola; Heikinheimo, Markku (Tumour Biol, 2016)
Targeted treatments are needed for advanced adult-type granulosa cell tumors (AGCTs). We set out to assess tumor tissue and circulating levels of TNF-related apoptosis-inducing ligand (TRAIL), a promising anti-cancer cytokine, in patients affected by AGCT. We analyzed tissue expression of TRAIL in 127 AGCTs using immunohistochemistry or RT-PCR. Soluble TRAIL was measured by means of ELISA from 141 AGCT patient serum samples, as well as the conditioned media of 15 AGCT patient-derived primary cell cultures, and the KGN cell line. Tissue and serum TRAIL levels were analyzed in relationship with clinical parameters, and serum estradiol, FSH, and LH levels. We found that AGCT samples expressed TRAIL mRNA and protein at levels comparable to normal granulosa cells. AGCT cells did not release soluble TRAIL. TRAIL protein levels were decreased in tumors over 10 cm in diameter (p = 0.04). Consistently, circulating TRAIL levels correlated negatively to tumor dimension (p = 0.01). Circulating TRAIL levels negatively associated with serum estradiol levels. In multiple regression analysis, tumor size was an independent factor contributing to the decreased levels of soluble TRAIL in AGCT patients. AGCTs associate with significantly decreased tumor tissue and serum TRAIL levels in patients with a large tumor mass. These findings encourage further study of agonistic TRAIL treatments in patients with advanced or recurrent AGCT.

Clinical and pathogenetic features of ETV6 related thrombocytopenia with predisposition to acute lymphoblastic leukemia. - Melazzini, Federica; Palombo, Flavia; Balduini, Alessandra; De Rocco, Daniela; Marconi, Caterina; Noris, Patrizia; Gnan, Chiara; Pippucci, Tommaso; Bozzi, Valeria; Faleschini, Michela; Barozzi, Serena; Doubek, Michael; et al. (Haematologica, 2016)
ETV6-related thrombocytopenia (ETV6-RT) is an autosomal dominant thrombocytopenia that has been recently identified in a few families and has been suspected to predispose to hematological malignancies. To gain further information on this disorder, we searched for ETV6 mutations in the 130 families with inherited thrombocytopenia of unknown origin from our cohort of 274 consecutive pedigrees with familial thrombocytopenia. We identified 20 ETV6-RT patients from 7 pedigrees. They have 5 different ETV6 variants, including three novel mutations affecting the highly conserved E26 transformation-specific domain. The relative frequency of ETV6-RT resulted 2.6% in the whole case series and 4.6% among the families with known forms of inherited thrombocytopenia. The degree of thrombocytopenia and bleeding tendency of ETV6-RT patients were mild, but 4 subjects developed B-cell acute lymphoblastic leukemia during childhood, resulting in a significantly increased incidence compared to the general population. Clinical and laboratory findings did not identify any peculiar defects that can be used to suspect this disorder by routine diagnostic workup. However, at variance with most inherited thrombocytopenias, platelet size was not enlarged. In vitro studies revealed that patients megakaryocytes have defective maturation and impaired proplatelet formation. Moreover, ETV6-RT platelets have reduced ability to spread on fibrinogen. Since also the dominant thrombocytopenias due to mutations in RUNX1 and ANKRD26 are characterized by normal platelet size and predispose to hematological malignancies, we suggest that mutation screening of ETV6, RUNX1 and ANKRD26 should be performed in all the subjects with autosomal dominant thrombocytopenia and normal platelet size.

Clinical Characteristics of Patients Carrying the Q703K Variant of the NLRP3 Gene: A 10-year Multicentric National Study. - Naselli, Aldo; Penco, Federica; Cantarini, Luca; Insalaco, Antonella; Alessio, Mariolina; Tommasini, Alberto; Maggio, Cristina; Obici, Laura; Gallizi, Romina; Cimmino, Marco; Signa, Sara; Lucherini, Orso Maria; et al. (J Rheumatol, 2016)
OBJECTIVE: The aim of our study was to analyze the clinical and functional effect of the p.Q703K (p. Q705K, c. 2107C>A) variant of the NLRP3 gene in a population of patients screened for suspected cryopyrin-associated periodic syndrome (CAPS). METHODS: Since 2002, 580 patients underwent molecular analysis for NLRP3. Data on clinical presentation, response to treatment, and longterm followup were collected using a uniform questionnaire. The pattern of cytokine secretion after lipopolysaccharide stimulation from isolated monocytes was analyzed in 3 patients carrying the p.Q703K variant and 1 patient with a chronic infantile neurologic, cutaneous, articular syndrome phenotype carrying both the p.M406I and p.Q703K, and compared with 7 patients with CAPS with sure pathogenic variants and 6 healthy controls. RESULTS: The p.Q703K variant was found in 57 screened patients with an overall allelic frequency of 5%. The frequency in normal controls was 5.5%. Clinical data at the moment of molecular analysis and at followup were available in 36 patients. Two patients displayed additional mutations of NLRP3. The mean followup was 2.5 years. Thirteen patients (39%) had a final diagnosis different from the original suspicion of CAPS. The remaining 21 patients displayed a mild phenotype mainly characterized by recurrent episodes of urticarial rash and arthralgia. Only 8 patients were treated with anti-interleukin (IL)-1 treatment, with a complete response in 5 patients. The pattern of secretion of IL-1β and other cytokines (IL-6 and IL-1 receptor antagonist) in patients did not display the aberrancies observed in patients with CAPS and was similar to that observed in healthy controls. CONCLUSION: The present study confirms the weak clinical and functional effect of the p.Q703K variant.

Clinical Spectrum of PRKAG2 Syndrome. - Porto, Andrea Giuseppe; Brun, Francesca; Severini, Giovanni Maria; Losurdo, Pasquale; Fabris, Enrico; Taylor, Matthew R G; Mestroni, Luisa; Sinagra, Gianfranco (Circ Arrhythm Electrophysiol, 2016)
Keywords: AMP-Activated Protein Kinases; DNA; Heart Conduction System; Humans; Mutation; Wolff-Parkinson-White Syndrome

CNV analysis in 169 patients with bladder exstrophy-epispadias complex. - von Lowtzow, Catharina; Hofmann, Andrea; Zhang, Rong; Marsch, Florian; Ebert, Anne-Karoline; Rösch, Wolfgang; Stein, Raimund; Boemers, Thomas M; Hirsch, Karin; Marcelis, Carlo; Feitz, Wouter F J; Brusco, Alfredo; et al. (BMC Med Genet, 2016)
BACKGROUND: The bladder exstrophy-epispadias complex (BEEC) represents the severe end of the congenital uro-rectal malformation spectrum. Initial studies have implicated rare copy number variations (CNVs), including recurrent duplications of chromosomal region 22q11.21, in BEEC etiology. METHODS: To detect further CNVs, array analysis was performed in 169 BEEC patients. Prior to inclusion, 22q11.21 duplications were excluded using multiplex ligation-dependent probe amplification. RESULTS: Following the application of stringent filter criteria, seven rare CNVs were identified: n = 4, not present in 1307 in-house controls; n = 3, frequency of <0.002 in controls. These CNVs ranged from 1 to 6.08 Mb in size. To identify smaller CNVs, relaxed filter criteria used in the detection of previously reported BEEC associated chromosomal regions were applied. This resulted in the identification of six additional rare CNVs: n = 4, not present in 1307 in-house controls; n = 2, frequency <0.0008 in controls. These CNVs ranged from 0.03-0.08 Mb in size. For 10 of these 13 CNVs, confirmation and segregation analyses were performed (5 of maternal origin; 5 of paternal origin). Interestingly, one female with classic bladder extrophy carried a 1.18 Mb duplication of 22q11.1, a chromosomal region that is associated with cat eye syndrome. CONCLUSIONS: A number of rare CNVs were identified in BEEC patients, and these represent candidates for further evaluation. Rare inherited CNVs may constitute modifiers of, or contributors to, multifactorial BEEC phenotypes.

Consensus Conference on Clinical Management of pediatric Atopic Dermatitis. - Galli, Elena; Neri, Iria; Ricci, Giampaolo; Baldo, Ermanno; Barone, Maurizio; Belloni Fortina, Anna; Bernardini, Roberto; Berti, Irene; Caffarelli, Carlo; Calamelli, Elisabetta; Capra, Lucetta; Carello, Rossella; et al. (Ital J Pediatr, 2016)
The Italian Consensus Conference on clinical management of atopic dermatitis in children reflects the best and most recent scientific evidence, with the aim to provide specialists with a useful tool for managing this common, but complex clinical condition. Thanks to the contribution of experts in the field and members of the Italian Society of Pediatric Allergology and Immunology (SIAIP) and the Italian Society of Pediatric Dermatology (SIDerP), this Consensus statement integrates the basic principles of the most recent guidelines for the management of atopic dermatitis to facilitate a practical approach to the disease. The therapeutical approach should be adapted to the clinical severity and requires a tailored strategy to ensure good compliance by children and their parents. In this Consensus, levels and models of intervention are also enriched by the Italian experience to facilitate a practical approach to the disease.

DEFB1 gene polymorphisms and tuberculosis in a Northeastern Brazilian population. - Celerino da Silva, Ronaldo; da Cruz, Heidi Lacerda Alves; Brandão, Lucas André Cavalcanti; Guimarães, Rafael Lima; Montenegro, Lilian Maria Lapa; Schindler, Haiana Charifker; Segat, Ludovica; Crovella, Sergio (Braz J Microbiol, 2016)
β-Defensin-1, an antimicrobial peptide encoded by the DEFB1 gene, is known to play an important role in lung mucosal immunity. In our association study we analyzed three DEFB1 functional polymorphisms -52G>A (rs1799946), -44C>G (rs1800972) and -20G>A (rs11362) in 92 tuberculosis patients and 286 healthy controls, both from Northeast Brazil: no association was found between the studied DEFB1 polymorphisms and the disease. However we cannot exclude that this lack of association could be due to the low number of subjects analyzed, as suggested by the low statistical power achieved for the three analyzed SNPs (values between 0.16 and 0.50).

DEFB1 polymorphisms and susceptibility to recurrent tonsillitis in Italian children. - Zupin, Luisa; Polesello, Vania; Grasso, Domenico Leonardo; Crovella, Sergio; Segat, Ludovica (Int J Pediatr Otorhinolaryngol, 2016)
INTRODUCTION: The tonsils are secondary lymphoid organs fundamental for immune system response against pathogens within the oral cavity. Tonsillitis refers to inflammation of the pharyngeal tonsils that may include the adenoids and the lingual tonsils and that can be acute, recurrent, and chronic. Viral or bacterial infections, as well as immunologic factors are the main trigger to tonsillitis and disease's chronicity: the host immune responses, especially the innate one, could play an important role in susceptibility to the disease. OBJECTIVES: The current study aims at investigating the role of functional polymorphisms in the 5'UTR (c.-52G>A, c.-44G>C and c.-20G>A) of DEFB1 gene, encoding for the antimicrobial peptide human beta-defensin 1, in the predisposition to recurrent tonsillitis in children from North Eastern Italy. RESULTS: No significant correlation was found between DEFB1 allele, genotype and haplotype frequencies and recurrent tonsillitis susceptibility with the exception of an increased risk to disease development in patients carrying DEFB1 rare haplotypes. CONCLUSION: Our results may suggest that DEFB1 polymorphisms alone may not influence pathology susceptibility, however they could possibly concur, together with other factors involved in the genetic control of innate immune system, in the predisposition towards recurrent tonsillitis.

Dyslipidemia, Diet, and Physical Exercise in Children on Treatment with Anti-Retroviral Medication in El Salvador: A Cross-Sectional Study. - Sonego, Michela; Sagrado, Maria José; Escobar, Gustavo; Lazzerini, Marzia; Rivas, Estefanie; Martín-Cañavate, Rocio; de López, Elsy Pérez; Ayala, Sandra; Castaneda, Luis; Aparicio, Pilar; Custodio, Estefanía (Pediatr Infect Dis J, 2016)
BACKGROUND: Dyslipidemias are common in HIV-infected children, especially if treated with protease-inhibitors, but there are few data on how to treat dyslipidemias in this population. We estimated the dislypidemia prevalence and its association with treatment, diet, and physical exercise in children on anti-retroviral treatment at the El Salvador reference center for pediatric HIV care (CENID). METHODS: Information was gathered regarding socio-demographic characteristics, treatment, diet, and physical activity of 173 children aged 5-18 years and receiving anti-retroviral therapy.Triglycerides, total cholesterol, low-density lipoprotein (LDL-C), high-density lipoprotein (HDL-C), viral load, and CD4 T-lymphocytes were measured. Abnormal concentrations were defined as triglycerides ≥130 mg/dl in 10- to 18-year-olds and ≥100 mg/dl in <10 year-olds; total cholesterol ≥200 mg/dl; LDL-C ≥130 mg/dl; and HDL-C ≤35 mg/dl.We adjusted four different multivariate models to assess the independent association of each type of dyslipidemia with protease-inhibitors, diet, and physical exercise. RESULTS: Of the 173 children, 83 (48%) had hypertriglyceridemia and 25 (14.5%) hypercholesterolemia. High LDL-C concentrations were observed in 17 children (9.8%) and low HDL-C in 38 (22%). Treatment with protease-inhibitors was significantly associated with hypertriglyceridemia (Prevalence Ratio (PR) 2.8; 95%CI 2.0-3.8) and hypercholesterolemia (PR 9.0; 95%CI 3.6-22.2).Higher adherence to a "high fat/sugar diet" was associated with hypercholesterolemia (PR 1.6; 95%CI 1.1-2.3) and high LDL-C (PR 1.7; 95%CI 1.0-2.9).Compared with those exercising <3 times/week, children exercising ≥7 times were less likely to have low HDL-C (PR=0.4; 95%CI 0.2-0.7). CONCLUSIONS: These results suggest that a healthy diet and exercise habits can contribute to controlling some aspects of the lipid profile in this population.

Effect of Early Versus Late Azathioprine Therapy in Pediatric Ulcerative Colitis. - Aloi, Marina; DʼArcangelo, Giulia; Bramuzzo, Matteo; Gasparetto, Marco; Martinelli, Massimo; Alvisi, Patrizia; Illiceto, Maria Teresa; Valenti, Simona; Distante, Manuela; Pellegrino, Salvatore; Gatti, Simona; Arrigo, Serena; et al. (Inflamm Bowel Dis, 2016)
BACKGROUND: We aimed at describing the efficacy of azathioprine (AZA) in pediatric ulcerative colitis, comparing the outcomes of early (0-6 months) versus late (6-24 months) initiation of therapy. METHODS: Children with ulcerative colitis treated with AZA within 24 months of diagnosis were included. Corticosteroid (CS)-free remission and mucosal healing (MH), assessed by endoscopy or fecal calprotectin, at 12 months were the primary outcomes. Patients were also compared for CS-free remission and MH, need for treatment escalation or surgery, number of hospitalizations, and adverse events during a 24-month follow-up. RESULTS: A total of 121 children entered the study (median age 10.5 ± 4.0 years, 59% girls). Seventy-six (63%) started AZA between 0 and 6 months (early group) and 45 (37%) started between 6 and 24 months (late group). Seventy-five percent and 53% of patients in the early and late group, respectively, received CS at the diagnosis (P = 0.01). CS-free remission at 1 year was achieved by 30 (50%) of the early and 23 (57%) of the late patients (P = 0.54). MH occurred in 37 (37%) patients at 1 year, with no difference between the 2 groups (33% early, 42% late; P = 0.56). No difference was found for the other outcomes. CONCLUSIONS: Introduction of AZA within 6 months of diagnosis seems not more effective than later treatment to achieve CS-free remission in pediatric ulcerative colitis. MH does not depend on the timing of AZA initiation; however, because of the incomplete comparability of the 2 groups at the diagnosis and the use of fecal calprotectin as a surrogate marker of MH, our results should be further confirmed by prospective studies.

Effectiveness of the Baby Friendly Community Initiative in Italy: a non-randomised controlled study. - Cattaneo, Adriano; Bettinelli, Maria Enrica; Chapin, Elise; Macaluso, Anna; Córdova do Espírito Santo, Lílian; Murante, Anna Maria; Montico, Marcella (BMJ Open, 2016)
OBJECTIVE: To assess the effectiveness of the Baby Friendly Community Initiative (BFCI) on exclusive breast feeding at 6 months. DESIGN: Controlled, non-randomised trial. SETTING: 18 Local Health Authorities in 9 regions of Italy. PARTICIPANTS: 5094 mother/infant dyads in 3 cohorts were followed up to 12 months after birth in 3 rounds of data collection: at baseline, after implementation of the intervention in the early intervention group and after implementation in the late intervention group. 689 (14%) dyads did not complete the study. INTERVENTION: Implementation of the 7 steps of the BFCI. MAIN OUTCOME MEASURES: The rate of exclusive breast feeding at 6 months was the primary outcome; breast feeding at discharge, 3 and 12 months was also measured. RESULTS: The crude rates of exclusive breast feeding at discharge, 3 and 6 months, and of any breast feeding at 6 and 12 months increased at each round of data collection after baseline in the early and late intervention groups. At the end of the project, 10% of infants were exclusively breast fed at 6 months and 38% were continuing to breast feed at 12 months. However, the comparison by adjusted rates and logistic regression failed to show statistically significant differences between groups and rounds of data collection in the intention-to-treat analysis, as well as when compliance with the intervention and training coverage was taken into account. CONCLUSIONS: The study failed to demonstrate an effect of the BFCI on the rates of breast feeding. This may be due, among other factors, to the time needed to observe an effect on breast feeding following this complex intervention.

Efficacy of ketamine in refractory convulsive status epilepticus in children: a protocol for a sequential design, multicentre, randomised, controlled, open-label, non-profit trial (KETASER01). - Rosati, Anna; Ilvento, Lucrezia; L'Erario, Manuela; De Masi, Salvatore; Biggeri, Annibale; Fabbro, Giancarlo; Bianchi, Roberto; Stoppa, Francesca; Fusco, Lucia; Pulitanò, Silvia; Battaglia, Domenica; Pettenazzo, Andrea; et al. (BMJ Open, 2016)
INTRODUCTION: Status epilepticus (SE) is a life-threatening neurological emergency. SE lasting longer than 120 min and not responding to first-line and second-line antiepileptic drugs is defined as 'refractory' (RCSE) and requires intensive care unit treatment. There is currently neither evidence nor consensus to guide either the optimal choice of therapy or treatment goals for RCSE, which is generally treated with coma induction using conventional anaesthetics (high dose midazolam, thiopental and/or propofol). Increasing evidence indicates that ketamine (KE), a strong N-methyl-d-aspartate glutamate receptor antagonist, may be effective in treating RCSE. We hypothesised that intravenous KE is more efficacious and safer than conventional anaesthetics in treating RCSE. METHODS AND ANALYSIS: A multicentre, randomised, controlled, open-label, non-profit, sequentially designed study will be conducted to assess the efficacy of KE compared with conventional anaesthetics in the treatment of RCSE in children. 10 Italian centres/hospitals are involved in enrolling 57 patients aged 1 month to 18 years with RCSE. Primary outcome is the resolution of SE up to 24 hours after withdrawal of therapy and is updated for each patient treated according to the sequential method. ETHICS AND DISSEMINATION: The study received ethical approval from the Tuscan Paediatric Ethics Committee (12/2015). The results of this study will be published in peer-reviewed journals and presented at international conferences. TRIAL REGISTRATION NUMBER: NCT02431663; Pre-results.

EPG5-related Vici syndrome: a paradigm of neurodevelopmental disorders with defective autophagy. - Byrne, Susan; Jansen, Lara; U-King-Im, Jean-Marie; Siddiqui, Ata; Lidov, Hart G W; Bodi, Istvan; Smith, Luke; Mein, Rachael; Cullup, Thomas; Dionisi-Vici, Carlo; Al-Gazali, Lihadh; Al-Owain, Mohammed; et al. (Brain, 2016)
Vici syndrome is a progressive neurodevelopmental multisystem disorder due to recessive mutations in the key autophagy gene EPG5. We report genetic, clinical, neuroradiological, and neuropathological features of 50 children from 30 families, as well as the neuronal phenotype of EPG5 knock-down in Drosophila melanogaster. We identified 39 different EPG5 mutations, most of them truncating and predicted to result in reduced EPG5 protein. Most mutations were private, but three recurrent mutations (p.Met2242Cysfs*5, p.Arg417*, and p.Gln336Arg) indicated possible founder effects. Presentation was mainly neonatal, with marked hypotonia and feeding difficulties. In addition to the five principal features (callosal agenesis, cataracts, hypopigmentation, cardiomyopathy, and immune dysfunction), we identified three equally consistent features (profound developmental delay, progressive microcephaly, and failure to thrive). The manifestation of all eight of these features has a specificity of 97%, and a sensitivity of 89% for the presence of an EPG5 mutation and will allow informed decisions about genetic testing. Clinical progression was relentless and many children died in infancy. Survival analysis demonstrated a median survival time of 24 months (95% confidence interval 0-49 months), with only a 10th of patients surviving to 5 years of age. Survival outcomes were significantly better in patients with compound heterozygous mutations (P = 0.046), as well as in patients with the recurrent p.Gln336Arg mutation. Acquired microcephaly and regression of skills in long-term survivors suggests a neurodegenerative component superimposed on the principal neurodevelopmental defect. Two-thirds of patients had a severe seizure disorder, placing EPG5 within the rapidly expanding group of genes associated with early-onset epileptic encephalopathies. Consistent neuroradiological features comprised structural abnormalities, in particular callosal agenesis and pontine hypoplasia, delayed myelination and, less frequently, thalamic signal intensity changes evolving over time. Typical muscle biopsy features included fibre size variability, central/internal nuclei, abnormal glycogen storage, presence of autophagic vacuoles and secondary mitochondrial abnormalities. Nerve biopsy performed in one case revealed subtotal absence of myelinated axons. Post-mortem examinations in three patients confirmed neurodevelopmental and neurodegenerative features and multisystem involvement. Finally, downregulation of epg5 (CG14299) in Drosophila resulted in autophagic abnormalities and progressive neurodegeneration. We conclude that EPG5-related Vici syndrome defines a novel group of neurodevelopmental disorders that should be considered in patients with suggestive features in whom mitochondrial, glycogen, or lysosomal storage disorders have been excluded. Neurological progression over time indicates an intriguing link between neurodevelopment and neurodegeneration, also supported by neurodegenerative features in epg5-deficient Drosophila, and recent implication of other autophagy regulators in late-onset neurodegenerative disease.
Keywords: Agenesis of Corpus Callosum; Animals; Autophagy; Cataract; Child, Preschool; Cross-Sectional Studies; Drosophila melanogaster; Female; Hippocampus; Humans; Male; Mutation; Neurodevelopmental Disorders; Proteins; Retrospective Studies

Evaluation of energy metabolism and calcium homeostasis in cells affected by Shwachman-Diamond syndrome. - Ravera, Silvia; Dufour, Carlo; Cesaro, Simone; Bottega, Roberta; Faleschini, Michela; Cuccarolo, Paola; Corsolini, Fabio; Usai, Cesare; Columbaro, Marta; Cipolli, Marco; Savoia, Anna; Degan, Paolo; et al. (Sci Rep, 2016)
Isomorphic mutation of the SBDS gene causes Shwachman-Diamond syndrome (SDS). SDS is a rare genetic bone marrow failure and cancer predisposition syndrome. SDS cells have ribosome biogenesis and their protein synthesis altered, which are two high-energy consuming cellular processes. The reported changes in reactive oxygen species production, endoplasmic reticulum stress response and reduced mitochondrial functionality suggest an energy production defect in SDS cells. In our work, we have demonstrated that SDS cells display a Complex IV activity impairment, which causes an oxidative phosphorylation metabolism defect, with a consequent decrease in ATP production. These data were confirmed by an increased glycolytic rate, which compensated for the energetic stress. Moreover, the signalling pathways involved in glycolysis activation also appeared more activated; i.e. we reported AMP-activated protein kinase hyper-phosphorylation. Notably, we also observed an increase in a mammalian target of rapamycin phosphorylation and high intracellular calcium concentration levels ([Ca(2+)]i), which probably represent new biochemical equilibrium modulation in SDS cells. Finally, the SDS cell response to leucine (Leu) was investigated, suggesting its possible use as a therapeutic adjuvant to be tested in clinical trials.

Evidence for three genetic loci involved in both anorexia nervosa risk and variation of body mass index. - Hinney, A; Kesselmeier, M; Jall, S; Volckmar, A-L; Föcker, M; Antel, J; Heid, I M; Winkler, T W; Grant, S F A; Guo, Y; Bergen, A W; Kaye, W; et al. (Mol Psychiatry, 2016)
The maintenance of normal body weight is disrupted in patients with anorexia nervosa (AN) for prolonged periods of time. Prior to the onset of AN, premorbid body mass index (BMI) spans the entire range from underweight to obese. After recovery, patients have reduced rates of overweight and obesity. As such, loci involved in body weight regulation may also be relevant for AN and vice versa. Our primary analysis comprised a cross-trait analysis of the 1000 single-nucleotide polymorphisms (SNPs) with the lowest P-values in a genome-wide association meta-analysis (GWAMA) of AN (GCAN) for evidence of association in the largest published GWAMA for BMI (GIANT). Subsequently we performed sex-stratified analyses for these 1000 SNPs. Functional ex vivo studies on four genes ensued. Lastly, a look-up of GWAMA-derived BMI-related loci was performed in the AN GWAMA. We detected significant associations (P-values <5 × 10(-5), Bonferroni-corrected P<0.05) for nine SNP alleles at three independent loci. Interestingly, all AN susceptibility alleles were consistently associated with increased BMI. None of the genes (chr. 10: CTBP2, chr. 19: CCNE1, chr. 2: CARF and NBEAL1; the latter is a region with high linkage disequilibrium) nearest to these SNPs has previously been associated with AN or obesity. Sex-stratified analyses revealed that the strongest BMI signal originated predominantly from females (chr. 10 rs1561589; Poverall: 2.47 × 10(-06)/Pfemales: 3.45 × 10(-07)/Pmales: 0.043). Functional ex vivo studies in mice revealed reduced hypothalamic expression of Ctbp2 and Nbeal1 after fasting. Hypothalamic expression of Ctbp2 was increased in diet-induced obese (DIO) mice as compared with age-matched lean controls. We observed no evidence for associations for the look-up of BMI-related loci in the AN GWAMA. A cross-trait analysis of AN and BMI loci revealed variants at three chromosomal loci with potential joint impact. The chromosome 10 locus is particularly promising given that the association with obesity was primarily driven by females. In addition, the detected altered hypothalamic expression patterns of Ctbp2 and Nbeal1 as a result of fasting and DIO implicate these genes in weight regulation.Molecular Psychiatry advance online publication, 17 May 2016; doi:10.1038/mp.2016.71.

Frequency of the CCR5-delta32 allele in Brazilian populations: A systematic literature review and meta-analysis. - Silva-Carvalho, Wlisses Henrique Veloso; De Moura, Ronald Rodrigues; Coelho, Antônio Victor Campos; Crovella, Sergio; Guimarães, Rafael Lima (Infect Genet Evol, 2016)
The CCR5 is a chemokine receptor widely expressed by several immune cells that are engaged in inflammatory responses. Some populations have individuals exhibiting a 32bp deletion in the CCR5 gene (CCR5-delta32) that produces a truncated non-functional protein not expressed on the cell surface. This polymorphism, known to be associated with susceptibility to infectious and inflammatory diseases, such as osteomyelitis, pre-eclampsia, systemic lupus erythematous, juvenile idiopathic arthritis, rheumatoid arthritis and HIV/AIDS, is more commonly found in European populations with average frequency of 10%. However, it is also possible to observe a significant frequency in other world populations, such as the Brazilian one. We performed a systematic review and meta-analysis of CCR5-delta32 genetic association studies in Brazilian populations throughout the country to estimate the frequency of this polymorphism. We also compared CCR5-delta32 frequencies across Brazilian regions. The systematic literature reviewed studies involving delta32 allele in Brazilian populations published from 1995 to 2015. Among the reviewed literature, 25 studies including 30 Brazilian populations distributed between the North, Northeast, South and Southeast regions were included in our meta-analysis. We observed an overall allelic frequency of 4% (95%-CI, 0.03-0.05), that was considered moderate and, notably, higher than some European populations, such as Cyprus (2.8%), Italy (3%) and Greece (2.4%). Regarding the regional frequency comparisons between North-Northeast (N-NE) and South-Southeast (S-SE) regions, we observed an allelic frequency of 3% (95%-CI, 0.02-0.04) and 4% (95%-CI, 0.03-0.05), respectively. The populations from S-SE regions had a slightly higher CCR5-delta32 frequency than N-NE regions (OR=1.41, p=0.002). Although there are several studies about the CCR5-delta32 polymorphism and its effect on the immune response of some infectious diseases, this report is the first meta-analysis study that provides a descriptive study of the distribution of CCR5-delta32 allele in Brazilian population.

Genetic associations at 53 loci highlight cell types and biological pathways relevant for kidney function. - Pattaro, Cristian; Teumer, Alexander; Gorski, Mathias; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Garnaas, Maija; Tin, Adrienne; Sorice, Rossella; Li, Yong; Taliun, Daniel; Olden, Matthias; et al. (Nat Commun, 2016)
Reduced glomerular filtration rate defines chronic kidney disease and is associated with cardiovascular and all-cause mortality. We conducted a meta-analysis of genome-wide association studies for estimated glomerular filtration rate (eGFR), combining data across 133,413 individuals with replication in up to 42,166 individuals. We identify 24 new and confirm 29 previously identified loci. Of these 53 loci, 19 associate with eGFR among individuals with diabetes. Using bioinformatics, we show that identified genes at eGFR loci are enriched for expression in kidney tissues and in pathways relevant for kidney development and transmembrane transporter activity, kidney structure, and regulation of glucose metabolism. Chromatin state mapping and DNase I hypersensitivity analyses across adult tissues demonstrate preferential mapping of associated variants to regulatory regions in kidney but not extra-renal tissues. These findings suggest that genetic determinants of eGFR are mediated largely through direct effects within the kidney and highlight important cell types and biological pathways.
Keywords: Gene Expression Regulation; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Renal Insufficiency, Chronic

Genome-wide association study identifies 74 loci associated with educational attainment. - Okbay, Aysu; Beauchamp, Jonathan P; Fontana, Mark Alan; Lee, James J; Pers, Tune H; Rietveld, Cornelius A; Turley, Patrick; Chen, Guo-Bo; Emilsson, Valur; Meddens, S Fleur W; Oskarsson, Sven; Pickrell, Joseph K; et al. (Nature, 2016)
Educational attainment is strongly influenced by social and other environmental factors, but genetic factors are estimated to account for at least 20% of the variation across individuals. Here we report the results of a genome-wide association study (GWAS) for educational attainment that extends our earlier discovery sample of 101,069 individuals to 293,723 individuals, and a replication study in an independent sample of 111,349 individuals from the UK Biobank. We identify 74 genome-wide significant loci associated with the number of years of schooling completed. Single-nucleotide polymorphisms associated with educational attainment are disproportionately found in genomic regions regulating gene expression in the fetal brain. Candidate genes are preferentially expressed in neural tissue, especially during the prenatal period, and enriched for biological pathways involved in neural development. Our findings demonstrate that, even for a behavioural phenotype that is mostly environmentally determined, a well-powered GWAS identifies replicable associated genetic variants that suggest biologically relevant pathways. Because educational attainment is measured in large numbers of individuals, it will continue to be useful as a proxy phenotype in efforts to characterize the genetic influences of related phenotypes, including cognition and neuropsychiatric diseases.
Keywords: Alzheimer Disease; Bipolar Disorder; Brain; Cognition; Computational Biology; Educational Status; Fetus; Gene Expression Regulation; Gene-Environment Interaction; Genome-Wide Association Study; Great Britain; Humans; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Schizophrenia

A Genome-Wide Association Study in isolated populations reveals new genes associated to common food likings. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; Amin, Najaf; Sala, Cinzia; Karssen, Lennart C; van Duijn, Cornelia; Toniolo, Daniela; Gasparini, Paolo (Rev Endocr Metab Disord, 2016)
Food preferences are the first factor driving food choice and thus nutrition. They involve numerous different senses such as taste and olfaction as well as various other factors such as personal experiences and hedonistic aspects. Although it is clear that several of these have a genetic basis, up to now studies have focused mostly on the effects of polymorphisms of taste receptor genes. Therefore, we have carried out one of the first large scale (4611 individuals) GWAS on food likings assessed for 20 specific food likings belonging to 4 different categories (vegetables, fatty, dairy and bitter). A two-step meta-analysis using three different isolated populations from Italy for the discovery step and two populations from The Netherlands and Central Asia for replication, revealed 15 independent genome-wide significant loci (p < 5 × 10(-8)) for 12 different foods. None of the identified genes coded for either taste or olfactory receptors suggesting that genetics impacts in determining food likings in a much broader way than simple differences in taste perception. These results represent a further step in uncovering the genes that underlie liking of common foods that in the end will greatly help understanding the genetics of human nutrition in general.

Hepatic Gadolinium Deposition and Reversibility after Contrast Agent-enhanced MR Imaging of Pediatric Hematopoietic Stem Cell Transplant Recipients. - Maximova, Natalia; Gregori, Massimo; Zennaro, Floriana; Sonzogni, Aurelio; Simeone, Roberto; Zanon, Davide (Radiology, 2016)
Purpose To determine if hepatic gadolinium deposition occurs in pediatric patients with iron overload but normal renal and hepatic function who undergo gadolinium-based contrast agent (GBCA)-enhanced magnetic resonance (MR) imaging. Materials and Methods Design and execution of this study was approved by the Ethical Committee of Institute for Research in Maternal and Child Health Burlo Garofolo of Trieste (reference no. 1105/2015). Because of the retrospective nature of the study, the requirement to obtain informed consent was waived. Twenty-one recipients of allogeneic hematopoietic stem cell transplants who underwent GBCA-enhanced MR imaging for suspected infection or relapse followed by liver biopsy comprised the study group. The number of GBCA-enhanced MR examinations and cumulative gadolinium dose for each patient was analyzed by comparing liver histologic analysis and iron and gadolinium liver concentration (GLC). Eight patients had siderosis and underwent chelation therapy. The study group was compared with four control patients who were never exposed to GBCA. Statistical analysis was performed with Spearman rank coefficient for correlation. Results All 21 patients had positive correlations between GLC and total GBCA dose (r = 0.4486; P < .05) and between GLC and liver iron concentration (r = 0.56; P < .05). Patients who underwent deferoxamine therapy had a significant reduction of GLC (from 0.64 μg/g ± 0.29 to 0.20 μg/g ± 0.17 [standard deviation]; P < .05). Conclusion In the presence of siderosis, a transmetallation mechanism may be set off between ferric ion and gadoterate meglumine. Deferoxamine appears capable of binding to gadolinium ion. Further studies of the safety of GBCAs in severe siderosis are needed. Chelation should be considered in patients with iron overload and a history of GBCA exposure. (©) RSNA, 2016.

HPV genotypes distribution in Chlamydia trachomatis co-infection in a large cohort of women from north-east Italy. - Seraceni, Silva; Campisciano, Giuseppina; Contini, Carlo; Comar, Manola (J Med Microbiol, 2016)
Human papillomavirus (HPV) and Chlamydia trachomatis are pathogens with oncogenic potential associated with persistent infections. Epidemiological data on C. trachomatis infection status, C. trachomatis/HPV co-infection and the relationship between HPV genotypes in Italian women are only preliminary. The aim of the present study was to characterize the relationship between HPV genotypes and C. trachomatis in an extending cohort of asymptomatic immunocompetent women from an area of north-east Italy. A retrospective study was conducted using Luminex technology on cervical swabs from asymptomatic immunocompetent women, comprising 921 attending the prevention centre for the Cervical Cancer Program and 6214 who had been referred to the Sexually Transmitted Infections Center, with clinical indications of HPV and C. trachomatis infections. A quantitative real-time PCR was performed to assess chronic C. trachomatis infection by heat-shock protein 60 (Hsp60) gene expression. The overall prevalence of the investigated pathogens was 39 % (359/921) for HPV and 4 % (251/6214) for C. trachomatis. The Hsp60 gene was detected in 57 % of the women infected with C. trachomatis. HPV co-infection was present in 58 % of C. trachomatis-infected women. A high prevalence of co-infection was found in women with chronic C. trachomatis infection (68 %, P = 0.0002), especially in women ≤ 25 years (72 %) where HPV multiple infections were found in 78 % (P = 0.022). HPV genotype distribution showed that uncommon low-risk genotypes were associated with C. trachomatis. These results indicate a high frequency of co-detection of multiple HPV genotypes in chronically infected young women and suggest that the expression of the C. trachomatis Hsp60 gene may favour HPV infection.

The Importance of Mortality Risk Assessment: Validation of the Pediatric Index of Mortality 3 Score. - Wolfler, Andrea; Osello, Raffaella; Gualino, Jenny; Calderini, Edoardo; Vigna, Gianluca; Santuz, Pierantonio; Amigoni, Angela; Savron, Fabio; Caramelli, Fabio; Rossetti, Emanuele; Cecchetti, Corrado; Corbari, Maurizio; et al. (Pediatr Crit Care Med, 2016)
OBJECTIVE: To evaluate the performance of the newest version of the Pediatric Index of Mortality 3 score and compare it with the Pediatric Index of Mortality 2 in a multicenter national cohort of children admitted to PICU. DESIGN: Retrospective, prospective cohort study. SETTING: Seventeen Italian PICUs. PATIENTS: All children 0 to 15 years old admitted in PICU from January 2010 to October 2014. INTERVENTIONS: None. MEASUREMENT AND MAIN RESULTS: Eleven thousand one hundred nine children were enrolled in the study. The mean Pediatric Index of Mortality 2 and 3 values of 4.9 and 3.9, respectively, differed significantly (p < 0.05). Overall mortality rate was 3.9%, and the standardized mortality ratio was 0.80 for Pediatric Index of Mortality 2 and 0.98 for Pediatric Index of Mortality 3 (p < 0.05). The area under the curve of the receiver operating characteristic curves was similar for Pediatric Index of Mortality 2 and Pediatric Index of Mortality 3. The Hosmer-Lemeshow test was not significant for Pediatric Index of Mortality 3 (p = 0.21) but was highly significant for Pediatric Index of Mortality 2 (p < 0.001), which overestimated death mainly in high-risk categories. CONCLUSIONS: Mortality indices require validation in each country where it is used. The new Pediatric Index of Mortality 3 score performed well in an Italian population. Both calibration and discrimination were appropriate, and the score more accurately predicted the mortality risk than Pediatric Index of Mortality 2.

In vitro sensitivity to methyl-prednisolone is associated with clinical response in pediatric idiopathic nephrotic syndrome. - Cuzzoni, E; De Iudicibus, S; Stocco, G; Favretto, D; Pelin, M; Messina, G; Ghio, L; Monti, E; Pasini, A; Montini, G; Decorti, G (Clin Pharmacol Ther, 2016)
The aim of this study was to evaluate the in vitro steroid sensitivity as a predictor of clinical response to glucocorticoids in childhood idiopathic nephrotic syndrome (INS). Seventy-four patients (median age 4.33, interquartile range [IQR] 2.82-7.23; 63.5% male) were enrolled in a prospective multicenter study: in vitro steroid inhibition of patients' peripheral blood mononuclear cell proliferation was evaluated by [methyl-(3) H] thymidine incorporation assay at disease onset (T0) and after 4 weeks (T4) of treatment. Steroid dependence was associated with increased in vitro sensitivity at T4 assessed both as drug concentration inducing 50% of inhibition (IC50 ; odds ratio [OR] = 0.48, 95% confidence interval [CI] = 0.24-0.85; P = 0.0094) and maximum inhibition at the highest drug concentration (Imax ; OR = 1.13, 95% CI = 1.02-1.31; P = 0.017). IC50 > 4.4 nM and Imax < 92% at T4 were good predictors for optimal clinical response. These results suggest that this test may be useful for predicting the response to glucocorticoid therapy in pediatric INS.

Innate and adaptive immunity in self-reported nonceliac gluten sensitivity versus celiac disease. - Di Sabatino, Antonio; Giuffrida, Paolo; Fornasa, Giulia; Salvatore, Chiara; Vanoli, Alessandro; Naviglio, Samuele; De Leo, Luigina; Pasini, Alessandra; De Amici, Mara; Alvisi, Costanza; Not, Tarcisio; Rescigno, Maria; et al. (Dig Liver Dis, 2016)
BACKGROUND: Immune mechanisms have been implicated in nonceliac gluten sensitivity (NCGS), a condition characterized by intestinal and/or extraintestinal symptoms caused by the ingestion of gluten in non-celiac/non-wheat allergic individuals. AIMS: We investigated innate and adaptive immunity in self-reported NCGS versus celiac disease (CD). METHODS: In the supernatants of ex vivo-cultured duodenal biopsies from 14 self-reported NCGS patients, 9 untreated and 10 treated CD patients, and 12 controls we detected innate cytokines - interleukin (IL)-15, tumor necrosis factor-α, IL-1β, IL-6, IL-12p70, IL-23, IL-27, IL-32α, thymic stromal lymphopoietin (TSLP), IFN-α-, adaptive cytokines - interferon (IFN)-γ, IL-17A, IL-4, IL-5, IL-10, IL-13-, chemokines - IL-8, CCL1, CCL2, CCL3, CCL4, CCL5, CXCL1, CXCL10-, granulocyte colony stimulating factor (G-CSF) and granulocyte-macrophage colony stimulating factor (GM-CSF). RESULTS: Mucosal innate and adaptive cytokines, chemokines and growth factors did not differ between self-reported NCGS, treated CD and controls. On the contrary, IL-6, IL-15, IL-27, IFN-α, IFN-γ, IL-17A, IL-23, G-CSF, GM-CSF, IL-8, CCL1 and CCL4 were significantly higher in untreated CD than in self-reported NCGS, treated CD and controls, while TSLP was significantly lower in untreated CD than in self-reported NCGS, treated CD and controls. CONCLUSION: In our hands, patients with self-reported NCGS showed no abnormalities of the mucosal immune response.

Iron signature in asbestos-induced malignant pleural mesothelioma: A population-based autopsy study. - Crovella, Sergio; Bianco, Anna Monica; Vuch, Joseph; Zupin, Luisa; Moura, Ronald Rodrigues; Trevisan, Elisa; Schneider, Manuela; Brollo, Alessandro; Nicastro, Enza Maria; Cosenzi, Alessandro; Zabucchi, Giuliano; Borelli, Violetta (J Toxicol Environ Health A, 2016)
Malignant pleural mesothelioma (MPM) is an aggressive cancer with poor prognosis. The development of MPM is frequently linked to inhalation of asbestos fibers. A genetic component of susceptibility to this disease is suggested by the observation that some individuals develop MPM following lower doses of asbestos exposure, whereas others exposed to higher quantities do not seem to be affected. This hypothesis is supported also by frequent reports of MPM familial clustering. Despite the widely recognized role of iron (Fe) in cellular asbestos-induced pulmonary toxicity, the role of the related gene polymorphisms in the etiology of MPM has apparently not been evaluated. Eighty-six single-nucleotide polymorphisms (SNPs) of 10 Fe-metabolism genes were examined by exploiting formalin-fixed paraffin-embedded postmortem samples from 77 patients who died due to MPM (designated AEM) and compared with 48 who were exposed to asbestos but from died in old age of cause other than asbestos (designated AENM). All subjects showed objective signs of asbestos exposure. Three SNPs, localized in the ferritin heavy polypeptide, transferrin, and hephaestin genes, whose frequencies were distributed differently in AEM and AENM populations, were identified. For ferritin and transferrin the C/C and the G/G genotypes, respectively, representing intronic polymorphisms, were significantly associated with protection against MPM and need to be considered as possible genetic markers of protection. Similarly, the C/C hephaestin SNP, a missense variation of this multicopper ferroxidase encoding gene, may be related, also functionally, with protection against MPM. In conclusion, it is proposed that three Fe metabolism-associated genes, significantly associated with protection against development of MPM, may serve as protective markers for this aggressive tumor.
Keywords: Adult; Aged; Asbestos; Autopsy; Case-Control Studies; Female; Ferritins; Gene Frequency; Genetic Markers; Humans; Iron; Lung Neoplasms; Male; Membrane Proteins; Mesothelioma; Middle Aged; Mutation, Missense; Polymorphism, Single Nucleotide; Transferrin; Young Adult

Isolation of the left innominate artery: a question of connection. - Gesuete, Valentina; Sanabor, Daniela; Benettoni, Alessandra; Bobbo, Marco; Ventura, Alessandro (J Cardiovasc Med (Hagerstown), 2016)

The Klinefelter syndrome is associated with high recurrence of copy number variations on the X chromosome with a potential role in the clinical phenotype. - Rocca, M S; Pecile, V; Cleva, L; Speltra, E; Selice, R; Di Mambro, A; Foresta, C; Ferlin, A (Andrology, 2016)
The Klinefelter syndrome (KS) is the most frequent sex chromosomal disorder in males, characterized by at least one supernumerary X chromosome (most frequent karyotype 47,XXY). This syndrome presents with a broad range of phenotypes. The common characteristics include small testes and infertility, but KS subjects are at increased risk of hypogonadism, cognitive dysfunction, obesity, diabetes, metabolic syndrome, osteoporosis, and autoimmune disorders, which are present in variable proportion. Although part of the clinical variability might be linked to a different degree of testicular function observed in KS patients, genetic mechanisms of the supernumerary X chromosome might contribute. Gene-dosage effects and parental origin of the supernumerary X chromosome have been suggested to this regard. No study has been performed analyzing the genetic constitution of the X chromosome in terms of copy number variations (CNVs) and their possible involvement in phenotype of KS. To this aim, we performed a SNP arrays analysis on 94 KS and 85 controls. We found that KS subjects have more frequently than controls X-linked CNVs (39/94, [41.5%] with respect to 12/42, [28.6%] of females, and 8/43, [18.6%] of males, p < 0.01). The number of X-linked CNVs in KS patients was 4.58 ± 1.92 CNVs/subject, significantly higher with respect to that found in control females (1.50 ± 1.29 CNVs/subject) and males (1.14 ± 0.37 CNVs/subject). Importantly, 94.4% X-linked CNVs in KS subjects were duplications, higher with respect to control males (50.0%, p < 0.001) and females (83.3%, p = 0.1). Half of the X-linked CNVs fell within regions encompassing genes and most of them (90%) included genes escaping X-inactivation in the regions of X-Y homology, particularly in the pseudoautosomal region 1 (PAR1) and Xq21.31. This study described for the first time the genetic properties of the X chromosome in KS and suggests that X-linked CNVs (especially duplications) might contribute to the clinical phenotype.

Lack of Evidence of Rotavirus-Dependent Molecular Mimicry as a Trigger of Celiac Disease. - Ziberna, Fabiana; De Lorenzo, Giuditta; Schiavon, Valentina; Arnoldi, Francesca; Quaglia, Sara; De Leo, Luigina; Vatta, Serena; Martelossi, Stefano; Burrone, Oscar R; Ventura, Alessandro; Not, Tarcisio (Clin Exp Immunol, 2016)
New data suggest the involvement of Rotavirus (RV) in triggering autoimmunity in celiac disease (CD) by molecular mimicry between the human-transglutaminase protein and the dodecapeptide (260-271 aa) of the RV protein VP7 (pVP7). To assess the role of RV in the onset of CD, we measured the anti-pVP7 antibodies in the sera of children with CD and of control groups. We analysed serum samples of 118 biopsy proven CD patients and 46 patients with potential-CD; 32 children with other gastrointestinal diseases; 107 no-CD children and 107 blood donors. By ELISA assay, we measured IgA-IgG antibodies against the synthetic peptides pVP7, the human transglutaminase-derived peptide (476-487 aa) which shows an homology with VP7 protein and a control peptide. The triple-layered RV particles (TLPs), containing the VP7 protein, and the double-layered RV-particles (DLPs), lacking the VP7 protein were also used as antigens in ELISA assay. Antibody reactivity to the RV-TLPs was positive in 22/118 (18%) CD patients and in both paediatric (17/107, 16%) and adult (29/107, 27%) control groups, without showing a statistically significant difference among them (p=0.6, p=0.1). Biopsy-proven CD patients as well as the adult control group demonstrated a high positive antibody reactivity against both pVP7 (34/118, 29% CD patients; 66/107, 62% adult controls) and control synthetic peptides (35/118, 30% CD patients; 56/107, 52% adult controls) suggesting a non-specific response against RV pVP7. We show that children with CD do not have higher immune reactivity to RV, thus questioning the molecular mimicry mechanism as a triggering factor of CD. This article is protected by copyright. All rights reserved.

Macrocephaly and palmoplantar pitting. - Rabach, Ingrid; Salis, Simona; Bruno, Irene; Ventura, Alessandro (Arch Dis Child, 2016)

MBL2 genetic polymorphisms and HIV-1 mother-to-child transmission in Zambia. - Zupin, Luisa; Polesello, Vania; Segat, Ludovica; Kuhn, Louise; Crovella, Sergio (Immunol Res, 2016)
Since antiretroviral drugs have been introduced to prevent mother-to-child transmission, the risk of HIV-1 infection in infants has decreased considerably worldwide. Nevertheless, many factors are involved in viral transmission and host susceptibility to infection. The immune system and its components, including mannose binding protein C (encoding by MBL2 gene), are already known to play an important role in this scenario. In the present study, 313 children and 98 of their mothers from Zambia were genotyped for the MBL2 promoter HL (rs11003125) and XY (rs7096206) polymorphisms and exon 1 D (rs5030737, at codon 52) B (rs1800450, at codon 54) and C (rs1800451, at codon 57) polymorphisms in order to investigate the potential role of these genetic variants in HIV-1 mother-to-child transmission. No statistical significant association was observed comparing transmitter and non-transmitter mothers and also confronting HIV-positive and HIV-negative children. The findings of the current study obtained on mother and children from Zambia evidence lack of association between MBL2 functional polymorphisms and HIV-1 mother-to-child transmission.

MBL2 Genetic Variants in HCV Infection Susceptibility, Spontaneous Viral Clearance and Pegylated Interferon Plus Ribavirin Treatment Response. - Zupin, L; Polesello, V; Alberi, G; Moratelli, G; Crocè, S L; Masutti, F; Pozzato, G; Crovella, S; Segat, L (Scand J Immunol, 2016)
Hepatitis C is disease that damages the liver, and it is caused by the hepatitis C virus (HCV). The pathology became chronic in about 80% of the cases due to virus persistence in the host organism. The standard of care consists of pegylated interferon plus ribavirin; however, the treatment response is very variable and different host/viral factors may concur in the disease outcome. The mannose-binding protein C (MBL) is a component of the innate immune system, able to recognize HCV and consecutively activating the immune response. MBL is encoded by MBL2 gene, and polymorphisms, two in the promoter region (H/L and X/Y) and three in exon 1 (at codon 52, 54 and 57), have been described as functionally influencing protein expression. In this work, 203 Italian HCV patients and 61 healthy controls were enrolled and genotyped for the five MBL2 polymorphisms mentioned above to investigate their role in HCV infection susceptibility, spontaneous viral clearance and treatment response. MBL2 polymorphisms were not associated with HCV infection susceptibility and with spontaneous viral clearance, while MBL2 O allele, O/O genotype, HYO haplotype and DP combined genotype (all correlated with low or deficient MBL expression) were associated with sustained virological response. Moreover, a meta-analysis to assess the role of MBL2 polymorphisms in HCV infection susceptibility was also performed: YA haplotype could be associated with protection towards HCV infection.

Molecular diagnosis of thrombocytopenia-absent radius syndrome using next-generation sequencing. - Nicchia, E; Giordano, P; Greco, C; De Rocco, D; Savoia, A (Int J Lab Hematol, 2016)
INTRODUCTION: Thrombocytopenia-absent radius (TAR) syndrome is a rare autosomal recessive disease. Patients are compound heterozygotes for a loss-of-function allele, which in most cases is a large genomic deletion on chromosome 1q21.1 containing the RBM8A gene, and a noncoding variant located in the 5'UTR (rs139428292) or intronic (rs201779890) regions of RBM8A. As the molecular genetic testing in TAR requires multiple techniques for detection of copy-number variations (CNV) and nucleotide substitutions, we tested whether a next-generation sequencing (NGS) approach could identify both alterations. METHODS: Two unrelated families were analyzed with Ion PGM sequencing using a target panel of genes responsible for different forms of inherited thrombocytopenia. A statistical quantitative evaluation of amplicon coverage was performed to detect CNV, in particular those on the RBM8A gene. RESULTS: All the probands were apparently homozygous for the rare allele inherited by the father at the rs139428292 locus, suggesting the presence of a deletion on the maternal chromosome. The statistical analysis confirmed the hemizygous condition of RBM8A. CONCLUSION: We concluded that NGS approaches could be used as a cost-effective method for molecular investigation of TAR as they could simultaneously detect CNV and point mutations.

Mortality and its risk factors in Malawian children admitted to hospital with clinical pneumonia, 2001-12: a retrospective observational study. - Lazzerini, Marzia; Seward, Nadine; Lufesi, Norman; Banda, Rosina; Sinyeka, Sophie; Masache, Gibson; Nambiar, Bejoy; Makwenda, Charles; Costello, Anthony; McCollum, Eric D; Colbourn, Tim (Lancet Glob Health, 2016)
BACKGROUND: Few studies have reported long-term data on mortality rates for children admitted to hospital with pneumonia in Africa. We examined trends in case fatality rates for all-cause clinical pneumonia and its risk factors in Malawian children between 2001 and 2012. METHODS: Individual patient data for children (<5 years) with clinical pneumonia who were admitted to hospitals participating in Malawi's Child Lung Health Programme between 2001 and 2012 were recorded prospectively on a standardised medical form. We analysed trends in pneumonia mortality and children's clinical characteristics, and we estimated the association of risk factors with case fatality for children younger than 2 months, 2-11 months of age, and 12-59 months of age using separate multivariable mixed effects logistic regression models. FINDINGS: Between November, 2012, and May, 2013, we retrospectively collected all available hard copies of yellow forms from 40 of 41 participating hospitals. We examined 113 154 pneumonia cases, 104 932 (92·7%) of whom had mortality data and 6903 of whom died, and calculated an overall case fatality rate of 6·6% (95% CI 6·4-6·7). The case fatality rate significantly decreased between 2001 (15·2% [13·4-17·1]) and 2012 (4·5% [4·1-4·9]; ptrend<0·0001). Univariable analyses indicated that the decrease in case fatality rate was consistent across most subgroups. In multivariable analyses, the risk factors significantly associated with increased odds of mortality were female sex, young age, very severe pneumonia, clinically suspected Pneumocystis jirovecii infection, moderate or severe underweight, severe acute malnutrition, disease duration of more than 21 days, and referral from a health centre. Increasing year between 2001 and 2012 and increasing age (in months) were associated with reduced odds of mortality. Fast breathing was associated with reduced odds of mortality in children 2-11 months of age. However, case fatality rate in 2012 remained high for children with very severe pneumonia (11·8%), severe undernutrition (15·4%), severe acute malnutrition (34·8%), and symptom duration of more than 21 days (9·0%). INTERPRETATION: Pneumonia mortality and its risk factors have steadily improved in the past decade in Malawi; however, mortality remains high in specific subgroups. Improvements in hospital care may have reduced case fatality rates though a lack of sufficient data on quality of care indicators and the potential of socioeconomic and other improvements outside the hospital precludes adequate assessment of why case-fatality rates fell. Results from this study emphasise the importance of effective national systems for data collection. Further work combining this with data on trends in the incidence of pneumonia in the community are needed to estimate trends in the overall risk of mortality from pneumonia in children in Malawi. FUNDING: Bill & Melinda Gates Foundation.

A multi-method approach to the molecular diagnosis of overt and borderline 11p15.5 defects underlying Silver-Russell and Beckwith-Wiedemann syndromes. - Russo, Silvia; Calzari, Luciano; Mussa, Alessandro; Mainini, Ester; Cassina, Matteo; Di Candia, Stefania; Clementi, Maurizio; Guzzetti, Sara; Tabano, Silvia; Miozzo, Monica; Sirchia, Silvia; Finelli, Palma; et al. (Clin Epigenetics, 2016)
BACKGROUND: Multiple (epi)genetic defects affecting the expression of the imprinted genes within the 11p15.5 chromosomal region underlie Silver-Russell (SRS) and Beckwith-Wiedemann (BWS) syndromes. The molecular diagnosis of these opposite growth disorders requires a multi-approach flowchart to disclose known primary and secondary (epi)genetic alterations; however, up to 20 and 30 % of clinically diagnosed BWS and SRS cases remain without molecular diagnosis. The complex structure of the 11p15 region with variable CpG methylation and low-rate mosaicism may account for missed diagnoses. Here, we demonstrate the relevance of complementary techniques for the assessment of different CpGs and the importance of testing multiple tissues to increase the SRS and BWS detection rate. RESULTS: Molecular testing of 147 and 450 clinically diagnosed SRS and BWS cases provided diagnosis in 34 SRS and 185 BWS patients, with 9 SRS and 21 BWS cases remaining undiagnosed and herein referred to as "borderline." A flowchart including complementary techniques and, when applicable, the analysis of buccal swabs, allowed confirmation of the molecular diagnosis in all borderline cases. Comparison of methylation levels by methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA) in borderline and control cases defined an interval of H19/IGF2:IG-DMR loss of methylation that was distinct between "easy to diagnose" and "borderline" cases, which were characterized by values ≤mean -3 standard deviations (SDs) compared to controls. Values ≥mean +1 SD at H19/IGF2: IG-DMR were assigned to borderline hypermethylated BWS cases and those ≤mean -2 SD at KCNQ1OT1: TSS-DMR to hypomethylated BWS cases; these were supported by quantitative pyrosequencing or Southern blot analysis. Six BWS cases suspected to carry mosaic paternal uniparental disomy of chromosome 11 were confirmed by SNP array, which detected mosaicism till 10 %. Regarding the clinical presentation, borderline SRS were representative of the syndromic phenotype, with exception of one patient, whereas BWS cases showed low frequency of the most common features except hemihyperplasia. CONCLUSIONS: A conclusive molecular diagnosis was reached in borderline methylation cases, increasing the detection rate by 6 % for SRS and 5 % for BWS cases. The introduction of complementary techniques and additional tissue analyses into routine diagnostic work-up should facilitate the identification of cases undiagnosed because of mosaicism, a distinctive feature of epigenetic disorders.
Keywords: Beckwith-Wiedemann Syndrome; Blotting, Southern; Child; Child, Preschool; Chromosomes, Human, Pair 11; CpG Islands; DNA Methylation; Epigenesis, Genetic; Female; Humans; Infant; Male; Mosaicism; Multiplex Polymerase Chain Reaction; Oligonucleotide Array Sequence Analysis; Silver-Russell Syndrome

Nonmuscle Myosin Heavy Chain IIA Mutation Predicts Severity and Progression of Sensorineural Hearing Loss in Patients With MYH9-Related Disease. - Verver, Eva J J; Topsakal, Vedat; Kunst, Henricus P M; Huygen, Patrick L M; Heller, Paula G; Pujol-Moix, Núria; Savoia, Anna; Benazzo, Marco; Fierro, Tiziana; Grolman, Wilko; Gresele, Paolo; Pecci, Alessandro (Ear Hear, 2016)
OBJECTIVES: MYH9-related disease (MYH9-RD) is an autosomal- dominant disorder deriving from mutations in MYH9, the gene for the nonmuscle myosin heavy chain (NMMHC)-IIA. MYH9-RD has a complex phenotype including congenital features, such as thrombocytopenia, and noncongenital manifestations, namely sensorineural hearing loss (SNHL), nephropathy, cataract, and liver abnormalities. The disease is caused by a limited number of mutations affecting different regions of the NMMHC-IIA protein. SNHL is the most frequent noncongenital manifestation of MYH9-RD. However, only scarce and anecdotal information is currently available about the clinical and audiometric features of SNHL of MYH9-RD subjects. The objective of this study was to investigate the severity and propensity for progression of SNHL in a large series of MYH9-RD patients in relation to the causative NMMHC-IIA mutations. DESIGN: This study included the consecutive patients diagnosed with MYH9-RD between July 2007 and March 2012 at four participating institutions. A total of 115 audiograms were analyzed from 63 patients belonging to 45 unrelated families with different NMMHC-IIA mutations. Cross-sectional analyses of audiograms were performed. Regression analysis was performed, and age-related typical audiograms (ARTAs) were derived to characterize the type of SNHL associated with different mutations. RESULTS: Severity of SNHL appeared to depend on the specific NMMHC-IIA mutation. Patients carrying substitutions at the residue R702 located in the short functional SH1 helix had the most severe degree of SNHL, whereas patients with the p.E1841K substitution in the coiled-coil region or mutations at the nonhelical tailpiece presented a mild degree of SNHL even at advanced age. The authors also disclosed the effects of different amino acid changes at the same residue: for instance, individuals with the p.R702C mutation had more severe SNHL than those with the p.R702H mutation, and the p.R1165L substitution was associated with a higher degree of hearing loss than the p.R1165C. In general, mild SNHL was associated with a fairly flat audiogram configuration, whereas severe SNHL correlated with downsloping configurations. ARTA plots showed that the most progressive type of SNHL was associated with the p.R702C, the p.R702H, and the p.R1165L substitutions, whereas the p.R1165C mutation correlated with a milder, nonprogressive type of SNHL than the p.R1165L. ARTA for the p.E1841K mutation demonstrated a mild degree of SNHL with only mild progression, whereas the ARTA for the mutations at the nonhelical tailpiece did not show any substantial progression. CONCLUSIONS: These data provide useful tools to predict the progression and the expected degree of severity of SNHL in individual MYH9-RD patients, which is especially relevant in young patients. Consequences in clinical practice are important not only for appropriate patient counseling but also for development of customized, genotype-driven clinical management. The authors recently reported that cochlear implantation has a good outcome in MYH9-RD patients; thus, stricter follow-up and earlier intervention are recommended for patients with unfavorable genotypes.

The one-step synthesis and surface functionalization of dumbbell-like gold-iron oxide nanoparticles: a chitosan-based nanotheranostic system. - Kostevsek, Nina; Locatelli, Erica; Garrovo, Chiara; Arena, Francesca; Monaco, Ilaria; Nikolov, Ivaylo Petrov; Sturm, Saso; Zuzek Rozman, Kristina; Lorusso, Vito; Giustetto, Pierangela; Bardini, Paola; Biffi, Stefania; et al. (Chem Commun (Camb), 2016)
The first one-step synthesis of dumbbell-like gold-iron oxide nanoparticles has been reported here. Surface functionalization with a biocompatible chitosan matrix allowed us to obtain a novel targetable diagnostic and therapeutic tool.

The prognostic value of biological markers in paediatric Hodgkin lymphoma. - Farruggia, Piero; Puccio, Giuseppe; Sala, Alessandra; Todesco, Alessandra; Buffardi, Salvatore; Garaventa, Alberto; Bottigliero, Gaetano; Bianchi, Maurizio; Zecca, Marco; Locatelli, Franco; Pession, Andrea; Pillon, Marta; et al. (Eur J Cancer, 2016)
BACKGROUND: Many biological and inflammatory markers have been proposed as having a prognostic value at diagnosis of Hodgkin lymphoma (HL), but very few have been validated in paediatric patients. We explored the significance of these markers in a large population of 769 affected children. PATIENTS AND METHODS: By using the database of patients enrolled in A.I.E.O.P. (Associazione Italiana di Emato-Oncologia Pediatrica) trial LH2004 for paediatric HL, we identified 769 consecutive patients treated with curative intent from 1st June 2004 to 1st April 2014 with ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine), or hybrid COPP/ABV (cyclophosphamide, vincristine, prednisone, procarbazine, doxorubicin, bleomycin and vinblastine) regimens. RESULTS: On multivariate analysis with categorical forms, the 5-year freedom from progression survival was significantly lower in patients with stage IV or elevated value of platelets, eosinophils and ferritin at diagnosis. Furthermore, stage IV and eosinophils seem to maintain their predictive value independently of interim (after IV cycles of chemotherapy) positron emission tomography. CONCLUSION: Using the combination of four simple markers such as stage IV and elevated levels of platelets, ferritin and eosinophils, it is possible to classify the patients into subgroups with very different outcomes.
Keywords: Adolescent; Age Factors; Antineoplastic Combined Chemotherapy Protocols; Biomarkers, Tumor; Blood Platelets; Child; Child, Preschool; Databases, Factual; Disease Progression; Disease-Free Survival; Eosinophils; Female; Ferritins; Hodgkin Disease; Humans; Infant; Infant, Newborn; Italy; Kaplan-Meier Estimate; Leukocyte Count; Male; Multivariate Analysis; Neoplasm Staging; Platelet Count; Predictive Value of Tests; Proportional Hazards Models; Retrospective Studies; Risk Factors; Time Factors; Treatment Outcome

Protective Role of BST2 Polymorphisms in Mother-to-Child Transmission of HIV-1 and Adult AIDS Progression. - Kamada, Anselmo J; Bianco, Anna M; Zupin, Luisa; Girardelli, Martina; Matte, Maria C C; Medeiros, Rúbia Marília de; Almeida, Sabrina Esteves de Matos; Rocha, Marineide M; Segat, Ludovica; Chies, José A B; Kuhn, Louise; Crovella, Sergio (J Acquir Immune Defic Syndr, 2016)
Bone marrow stromal cell antigen-2 (BST-2)/Tetherin is a restriction factor that prevents Human immunodeficiency virus type 1 (HIV-1) release from infected cells and mediates pro-inflammatory cytokine production. This study investigated the risk conferred by single nucleotide polymorphisms (rs919266, rs9192677, and rs9576) at BST-2 coding gene (BST2) in HIV-1 mother-to-child transmission and in disease progression. Initially, 101 HIV-1+ pregnant women and 331 neonates exposed to HIV-1 from Zambia were enrolled. Additional BST2 single nucleotide polymorphism analyses were performed in 2 cohorts with acquired immunodeficiency syndrome (AIDS) progression: an adult Brazilian cohort (37 rapid, 30 chronic and 21 long-term non-progressors) and an Italian pediatric cohort (21 rapid and 67 slow progressors). The rs9576A allele was nominally associated with protection during breastfeeding (P = 0.019) and individuals carrying rs919266 GA showed slower progression to AIDS (P = 0.033). Despite the influence of rs919266 and rs9576 on BST2 expression being still undetermined, a preventive role by BST2 polymorphisms was found during HIV-1 infection.

A Proteomic Approach for the Identification of Up-Regulated Proteins Involved in the Metabolic Process of the Leiomyoma. - Ura, Blendi; Scrimin, Federica; Arrigoni, Giorgio; Franchin, Cinzia; Monasta, Lorenzo; Ricci, Giuseppe (Int J Mol Sci, 2016)
Uterine leiomyoma is the most common benign smooth muscle cell tumor of the uterus. Proteomics is a powerful tool for the analysis of complex mixtures of proteins. In our study, we focused on proteins that were upregulated in the leiomyoma compared to the myometrium. Paired samples of eight leiomyomas and adjacent myometrium were obtained and submitted to two-dimensional gel electrophoresis (2-DE) and mass spectrometry for protein identification and to Western blotting for 2-DE data validation. The comparison between the patterns revealed 24 significantly upregulated (p < 0.05) protein spots, 12 of which were found to be associated with the metabolic processes of the leiomyoma and not with the normal myometrium. The overexpression of seven proteins involved in the metabolic processes of the leiomyoma was further validated by Western blotting and 2D Western blotting. Four of these proteins have never been associated with the leiomyoma before. The 2-DE approach coupled with mass spectrometry, which is among the methods of choice for comparative proteomic studies, identified a number of proteins overexpressed in the leiomyoma and involved in several biological processes, including metabolic processes. A better understanding of the mechanism underlying the overexpression of these proteins may be important for therapeutic purposes.

Recent advances in the use of Anti-TNFα therapy for the treatment of juvenile idiopathic arthritis. - Taddio, Andrea; Cattalini, Marco; Simonini, Gabriele; Cimaz, Rolando (Expert Rev Clin Immunol, 2016)
Juvenile Idiopathic Arthritis (JIA) encompasses a group of diseases of unknown etiology having in common arthritis in at least 1 joint that persists for 6 weeks and begins before 16 years of age, with other conditions excluded. With a prevalence of 1 per 1,000 children in the USA, JIA is the most common pediatric rheumatic illness and a major cause of acquired childhood disability. During the last 20 years, the advent of host immune response modifiers known as biologic agents, in particular the anti-TNFα agents (etanercept, infliximab, adalimumab), which directly inhibit the action of pro-inflammatory mediators, has revolutionized the treatment and the expected outcome of JIA. This article highlights treatment indications of anti-TNFα drugs and their more frequent side effects in JIA patients.

A reference panel of 64,976 haplotypes for genotype imputation. - McCarthy, Shane; Das, Sayantan; Kretzschmar, Warren; Delaneau, Olivier; Wood, Andrew R; Teumer, Alexander; Kang, Hyun Min; Fuchsberger, Christian; Danecek, Petr; Sharp, Kevin; Luo, Yang; Sidore, Carlo; et al. (Nat Genet, 2016)
We describe a reference panel of 64,976 human haplotypes at 39,235,157 SNPs constructed using whole-genome sequence data from 20 studies of predominantly European ancestry. Using this resource leads to accurate genotype imputation at minor allele frequencies as low as 0.1% and a large increase in the number of SNPs tested in association studies, and it can help to discover and refine causal loci. We describe remote server resources that allow researchers to carry out imputation and phasing consistently and efficiently.

Resistance (R) Genes: Applications and Prospects for Plant Biotechnology and Breeding. - Pandolfi, Valesca; Neto, José Ribamar Costa Ferreira; Silva, Manassés Daniel; Amorim, Lidiane Lindinalva Barbosa; Wanderley-Nogueira, Ana Carolina; de Oliveira Silva, Roberta Lane; Kido, Éderson Akio; Crovella, Sergio; Iseppon, Ana Maria Benko (Curr Protein Pept Sci, 2016)
The discovery of novel plant resistance (R) genes (including their homologs and analogs) opened interesting possibilities for controlling plant diseases caused by several pathogens. However, due to environmental pressure and high selection operated by pathogens, several crop plants have lost specificity, broad-spectrum or durability of resistance. On the other hand, the advances in plant genome sequencing and biotechnological approaches, combined with the increasing knowledge on R-genes have provided new insights on their applications for plant genetic breeding, allowing the identification and implementation of novel and efficient strategies that enhance or optimize their use for efficiently controlling plant diseases. The present review focuses on main perspectives of application of R-genes and its co-players for the acquisition of resistance to pathogens in cultivated plants, with emphasis on biotechnological inferences, including transgenesis, cisgenesis, directed mutagenesis and gene editing, with examples of success and challenges to be faced.

Role of inflammasome genetics in susceptibility to HPV infection and cervical cancer development. - Pontillo, A; Bricher, P; Leal, V N C; Lima, S; Souza, P R E; Crovella, S (J Med Virol, 2016)
PROBLEM: Only a small proportion of HPV+ women develop virus-associated lesions and cervical cancer, suggesting that other factors are involved in HPV+ keratinocyte transformation. Immune response plays an important role in clearing HPV infection, and host genetic variants resulting in defective immune response have been associated with virus persistence and/or cervical cancer. Considering that genetic variations in inflammasome genes were previously associated with viral infection and cancer development, the present study investigates selected single nucleotide polymorphisms (SNPs) in inflammasome genes as a possible risk factor for HPV infection susceptibility and/or for progression to cervical cancer. PATIENTS AND METHODS: 12 SNPs in seven inflammasome-related genes (NLRP1, NLRP3, NLRP6, CARD8, IL1B, IL18, TNFAIP3) were genotyped in a Brazilian HPV+ case/control cohort (n = 246/310). Multivariate analysis was performed in case/control as well as in HPV+ women stratified by the presence or severity of histologic lesion, HPV persistence, and type of virus. RESULTS: IL1B rs1143643 was associated with protection against HPV infection in case/control analysis. NLRP1 rs11651270 plays a protection role against HPV persistence and/or oncogenesis. NLRP3 rs10754558 and IL18 rs1834481 exert a beneficial role against HPV persistence. NLRP3 rs10754558 variant resulted significantly associated with a lower risk to be infected with a high-risk HPV. CONCLUSION: Our findings for the first time demonstrated that inflammasome genetics could affect HPV/host interaction in terms of virus susceptibility as well as of virus/persistence and cervical cancer progression. J. Med. Virol. 88:1646-1651, 2016. © 2016 Wiley Periodicals, Inc.

"Safety and utility of percutaneous liver biopsy in hematopoietic stem cell transplant pediatric recipients: a retrospective study". - Maximova, Natalia; Gregori, Massimo; Barbieri, Francesca; Pizzol, Antonio; Sonzogni, Aurelio (BMC Cancer, 2016)
BACKGROUND: Liver biopsies in pediatric hematopoietic stem cell transplantation (HSCT) patients are as and effective when performed at bedside in the Bone Marrow Transplant Unit (BMTU) than in the Day Surgery Unit (DSU), with better patient compliance and lower emotional distress for these children. METHODS: The study group consisted of 45 children who underwent allogeneic HSCT. We reviewed 68 liver biopsies performed between April 2006 and September 2015. 12 (17.6 %) biopsies were performed in the DSU and 56 (82.3 %) in the BMTU; nine (13.2 %) prior to HSCT and 59 (86.7 %) after HSCT. Pre-procedural behavioral status (subjective score) was evaluated by pediatric transplant physicians by filling in a questionnaire employing a three-point scale: "calm and cooperative", "agitated and non-cooperative" or "frightened and suffering". Objective score was obtained measuring patient's heart rate before the procedure and comparing it with mean heart rate. RESULTS: Patients who underwent the procedure at the BMTU experienced less emotional distress than those who underwent it in the DSU: 58.3 % of patients treated at the DSU were agitated as compared with 16.1 % of those treated at the BMTU (p < 0.01). Among the 59 biopsies performed after HSCT, 41 (69.5 %) were taken from symptomatic patients for a diagnostic purpose and 18 (30.5 %) in asymptomatic ones in order to rule out hepatic GVHD. Among these 18 procedures, GVHD was diagnosed in 16 (88.9 %) cases. Minor complications occurred in about 17 % of procedures (12 biopsies), at a rate of 25 % for the DSU location compared with 16 % for the BMTU location. Only two major complications were reported, one in the DSU and one in the BMTU. CONCLUSION: Liver biopsy performed at bedside in HSCT patients does not carry a higher risk of adverse events than the same procedure performed in the DSU and has lower emotional distress associated with better patient compliance, thus contributing significantly to a higher standard of care.

Somatic, hematologic phenotype, long-term outcome, and effect of hematopoietic stem cell transplantation. An analysis of 97 Fanconi anemia patients from the Italian national database on behalf of the Marrow Failure Study Group of the AIEOP (Italian Associ - Svahn, Johanna; Bagnasco, Francesca; Cappelli, Enrico; Onofrillo, Daniela; Caruso, Silvia; Corsolini, Fabio; De Rocco, Daniela; Savoia, Anna; Longoni, Daniela; Pillon, Marta; Marra, Nicoletta; Ramenghi, Ugo; et al. (Am J Hematol, 2016)
We analyzed 97 Fanconi anemia patients from a clinic/biological database for genotype, somatic, and hematologic phenotype, adverse hematological events, solid tumors, and treatment. Seventy-two patients belonged to complementation group A. Eighty percent of patients presented with mild/moderate somatic phenotype and most with cytopenia. No correlation was seen between somatic/hematologic phenotype and number of missense mutations of FANCA alleles. Over follow-up, 33% of patients improved or maintained mild/moderate cytopenia or normal blood count, whereas remaining worsened cytopenia. Eleven patients developed a hematological adverse event (MDS, AML, pathological cytogenetics) and three developed solid tumors. 10 years cumulative risk of death of the whole cohort was 25.6% with median follow-up 5.8 years. In patients eligible to hematopoietic stem cell transplantation because of moderate cytopenia, mortality was significantly higher in subjects transplanted from matched unrelated donor over nontransplanted subjects, whereas there was no significant difference between matched sibling donor transplants and nontransplanted patients. In patients eligible to transplant because of severe cytopenia and clonal disease, mortality risk was not significantly different in transplanted from matched unrelated versus matched sibling donor versus nontransplanted subjects. The decision to transplant should rely on various elements including, type of donor, HLA matching, patient comorbidities, impairment, and clonal evolution of hematopoiesis. Am. J. Hematol. 91:666-671, 2016. © 2016 Wiley Periodicals, Inc.

Thiopurine Biotransformation and Pharmacological Effects: Contribution of Oxidative Stress. - Pelin, Marco; De Iudicibus, Sara; Londero, Margherita; Spizzo, Riccardo; Dei Rossi, Sveva; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana; Stocco, Gabriele (Curr Drug Metab, 2016)
BACKGROUND: Thiopurine antimetabolites are important agents for the treatment of severe diseases, such as acute lymphoblastic leukemia and inflammatory bowel disease. Their pharmacological actions depend on biotransformation into active thioguanine-nucleotides; intracellular metabolism is mediated by enzymes of the salvage pathway of nucleotide synthesis and relies on polymorphic enzymes involved in thiopurines' catabolism such as thiopurine-S-methyl transferase. Given the enzymes involved in thiopurines' metabolism, it is reasonable to hypothesize that these drugs are able to induce significant oxidative stress conditions, possibly altering their pharmacological activity. METHODS: A systemic search of peer-reviewed scientific literature in bibliographic databases has been carried out. Both clinical and preclinical studies as well as mechanistic studies have been included to shed light on the role of oxidative stress in thiopurines' pharmacological effects. RESULTS: Sixty-nine papers were included in our review, allowing us to review the contribution of oxidative stress in the pharmacological action of thiopurines. Thiopurines are catabolized in the liver by xanthine oxidase, with potential production of reactive oxidative species and azathioprine is converted into mercaptopurine by a reaction with reduced glutathione, that, in some tissues, may be facilitated by glutathione- S-transferase (GST). A clear role of GSTM1 in modulating azathioprine cytotoxicity, with a close dependency on superoxide anion production, has been recently demonstrated. Interestingly, recent genome-wide association studies have shown that, for both azathioprine in inflammatory bowel disease and mercaptopurine in acute lymphoblastic leukemia, treatment effects on patients' white blood cells are related to variants of a gene, NUDT15, involved in biotransformation of oxidated nucleotides. CONCLUSIONS: Basing on previous evidences published in literature, oxidative stress may contribute to thiopurine effects in significant ways that, however, are still not completely elucidated.

Thromboprophilaxis in neurological conditions in pregnancy. A clinical dilemma or a methods dilemma? - Parco, Sergio; Vascotto, Fulvia; Simeone, Roberto (Minerva Ginecol, 2016)

Time for the 70°C water precautionary option in the home dilution of powdered infant formula. - Silano, Marco; Paganin, Paola; Davanzo, Riccardo (Ital J Pediatr, 2016)
Powdered infant formulas (PIF) are usually not sterile and may frequently be contaminated by several bacteria strains. Among them, Cronobacter species, previously known as Enterobacter sakazakii, is one of the most harmful, since it might be the causative agent of sepsis and meningitis in newborns and preterm infants during the first weeks of life. The mortality rate of these infections is up to 80 %. Therefore, some precautions are required in the home handling and dilution of PIF. Whereas there is wide consensus about the need that a PIF should be used immediately after being diluted or, if not, stored at < "5 °C", still recently the optimal temperature of the water used to dilute PIF is controversial among scientific societies and health agencies. The current knowledge is reviewed in this paper and provides sufficient evidence to cautiously advise the use of hot water at a temperature of "70 °C" in the dilution of PIF in order to prevent the Cronobacter sp. contamination and growth.

Time to optimise and enforce training in interpretation of intrapartum cardiotocograph. - Ugwumadu, A; Steer, P; Parer, B; Carbone, B; Vayssiere, C; Maso, G; Arulkumaran, S (BJOG, 2016)

Toward SERS-based point-of-care approaches for therapeutic drug monitoring: the case of methotrexate. - Fornasaro, Stefano; Marta, Silvia Dalla; Rabusin, Marco; Bonifacio, Alois; Sergo, Valter (Faraday Discuss, 2016)
To date, in spite of their toxicity, the plasmatic concentration of most chemotherapeutic drugs is difficult to monitor in oncological patients, because their quantitative determination is expensive and time consuming. This contribution reports a first attempt for the direct quantitative determination of a chemotherapeutic drug in human serum samples by means of Surface Enhanced Raman Spectroscopy (SERS). In this study, SERS substrates constituted by Au nanoparticles deposited on paper by a simple dipping method have been used for rapid (few minutes) analysis of diluted human serum spiked with different concentrations of methotrexate, MTX. The drug concentrations were chosen in a range designed to cover typical therapeutic plasmatic values (from nanomolar to millimolar) in oncological patients, and the pertinent calibration was obtained by Partial Least-Squares Regression (PLSR). Stability selection was employed to evaluate the capability of the PLSR model to accurately predict and extract spectral variations correlated to MTX concentration. Such a quantitative determination is crucial for frequent, and hence adherent, therapeutic drug monitoring, TDM, of chemiotherapic drugs, given their heavy side effects. Its low cost, rapid response and the possibility of obtaining spectra with simple and compact instruments, make SERS particularly apt for implementing effective TDM. The promising results obtained in the analytical validation indicate which steps are to be taken on the way toward a clinical validation with real samples from oncological patients, for MTX as well as for other chemotherapeutic drugs.

5-Aminoimidazole-4-carboxamide ribonucleotide-transformylase and inosine-triphosphate-pyrophosphatase genes variants predict remission rate during methotrexate therapy in patients with juvenile idiopathic arthritis. - Pastore, Serena; Stocco, Gabriele; Moressa, Valentina; Zandonà, Luigi; Favretto, Diego; Malusà, Noelia; Decorti, Giuliana; Lepore, Loredana; Ventura, Alessandro (Rheumatol Int, 2015)
For children with juvenile idiopathic arthritis (JIA) who fail to respond to methotrexate, the delay in identifying the optimal treatment at an early stage of disease can lead to long-term joint damage. Recent studies indicate that relevant variants to predict methotrexate response in JIA are those in 5-aminoimidazole-4-carboxamide ribonucleotide-transformylase (ATIC), inosine-triphosphate-pyrophosphatase (ITPA) and solute-liquid-carrier-19A1 genes. The purpose of the study was, therefore, to explore the role of these candidate genetic factors on methotrexate response in an Italian cohort of children with JIA. Clinical response to methotrexate was evaluated as clinical remission stable for a 6-month period, as ACRPed score and as change in Juvenile Arthritis Disease score. The most relevant SNPs for each gene considered were assayed on patients' DNA. ITPA activity was measured in patients' erythrocytes. Sixty-nine patients with JIA were analyzed: 52.2 % responded to therapy (ACRPed70 score), while 37.7 % reached clinical remission stable for 6 months. ATIC rs2372536 GG genotype was associated with improved clinical remission (adjusted p value = 0.0090). For ITPA, rs1127354 A variant was associated with reduced clinical remission: (adjusted p value = 0.028); this association was present even for patients with wild-type ITPA and low ITPA activity. These preliminary results indicate that genotyping of ATIC rs2372536 and ITPA rs1127354 variants or measuring ITPA activity could be useful to predict methotrexate response in children with JIA after validation by further prospective studies on a larger patient cohort.

Abnormal cytoplasmic extensions associated with active αIIbβ3 are probably the cause for macrothrombocytopenia in Glanzmann thrombasthenia-like syndrome. - Hauschner, Hagit; Mor-Cohen, Ronit; Messineo, Stefania; Mansour, Wissam; Seligsohn, Uri; Savoia, Anna; Rosenberg, Nurit (Blood Coagul Fibrinolysis, 2015)
Mutations in the ITGA2B or ITGB3 genes that encode for the αIIbβ3 platelet integrin usually cause Glanzmann thrombasthenia, a severe autosomal recessive bleeding disorder characterized by absence of platelet aggregation, but normal platelet number and size. Several rare mutations cause a Glanzmann-like syndrome which manifests macrothrombocytopenia and usually displays autosomal dominant inheritance. The exact mechanism causing Glanzmann-like syndrome is unknown. One typical example of Glanzmann-like mutations causes deletion of 40 amino acids (p.647-686) in the β3 β-tail domain (βTD_del) that was found in the heterozygous state in Italian and Japanese families. A second example is a missense mutation, C560R, located in the epidermal growth factor-like domain, found in the homozygous state in a French patient. Both mutations cause constitutive activation of αIIbβ3, but differ in their surface expression. In the current study, we generated cultured cells expressing β3-βTD_del or β3-C560R mutations along with wild-type αIIb, and examined the cells' ability to create tubulin-dependent protrusions compared to cells expressing wild-type αIIbβ3. Unlike cells expressing wild-type αIIbβ3, cells harboring each of the mutations exhibited abnormal cytoplasmic extensions on immobilized fibrinogen or Von Willebrand factor, which resembled extensions formed in megakaryocyte leading to proplatelets. Moreover, we showed that formation of abnormal extensions occurred also in wild-type αIIbβ3 cells when activated by activating antibody. These results suggest that the active conformation of αIIbβ3 can induce cytoskeletal rearrangements that lead to impaired proplatelet formation.
Keywords: Animals; Cell Line; Cricetinae; Cytoskeleton; DNA, Complementary; Fibrinogen; Genetic Vectors; Humans; Integrin alpha2; Integrin beta3; Megakaryocytes; Mesocricetus; Microtubules; Mutation, Missense; Platelet Glycoprotein GPIIb-IIIa Complex; Protein Conformation; Protein Interaction Mapping; Protein Structure, Tertiary; Recombinant Fusion Proteins; Sequence Deletion; Thrombasthenia; Tubulin; von Willebrand Factor

ACTN1-related thrombocytopenia: identification of novel families for phenotypic characterization. - Bottega, Roberta; Marconi, Caterina; Faleschini, Michela; Baj, Gabriele; Cagioni, Claudia; Pecci, Alessandro; Pippucci, Tommaso; Ramenghi, Ugo; Pardini, Simonetta; Ngu, Loretta; Baronci, Carlo; Kunishima, Shinji; et al. (Blood, 2015)
Inherited thrombocytopenias (ITs) are a heterogeneous group of syndromic and nonsyndromic diseases caused by mutations affecting different genes. Alterations of ACTN1, the gene encoding for α-actinin 1, have recently been identified in a few families as being responsible for a mild form of IT (ACTN1-related thrombocytopenia; ACTN1-RT). To better characterize this disease, we screened ACTN1 in 128 probands and found 10 (8 novel) missense heterozygous variants in 11 families. Combining bioinformatics, segregation, and functional studies, we demonstrated that all but 1 amino acid substitution had deleterious effects. The clinical and laboratory findings of 31 affected individuals confirmed that ACTN1-RT is a mild macrothrombocytopenia with low risk for bleeding. Low reticulated platelet counts and only slightly increased serum thrombopoietin levels indicated that the latest phases of megakaryopoiesis were affected. Given its relatively high frequency in our cohort (4.2%), ACTN1-RT has to be taken into consideration in the differential diagnosis of ITs.
Keywords: Actinin; Adolescent; Adult; Aged; Aged, 80 and over; Blood Platelets; Case-Control Studies; Child; Child, Preschool; Female; Gene Expression; Genotype; Heterozygote; Humans; Male; Middle Aged; Mutation, Missense; Pedigree; Phenotype; Platelet Count; Severity of Illness Index; Thrombocytopenia; Thrombopoiesis; Thrombopoietin

Advising Mothers on the Use of Medications during Breastfeeding: A Need for a Positive Attitude. - Davanzo, Riccardo; Bua, Jenny; De Cunto, Angela; Farina, Maria Luisa; De Ponti, Fabrizio; Clavenna, Antonio; Mandrella, Stefania; Sagone, Antonella; Clementi, Maurizio (J Hum Lact, 2015)
The use of medications by the nursing mother is a common reason for interrupting breastfeeding. Few drugs have been demonstrated to be absolutely contraindicated during breastfeeding. Excessive caution may lead health professionals to unnecessarily advise to interrupt breastfeeding, without assessing the latest evidence or considering the risk-benefit ratio of taking a medication versus terminating breastfeeding. To foster an appropriate approach toward the use of medications in breastfeeding women, the Italian Society of Perinatal Medicine created the following policy statement.

Altered germinal center reaction and abnormal B cell peripheral maturation in PI3KR1-mutated patients presenting with HIGM-like phenotype. - Lougaris, Vassilios; Faletra, Flavio; Lanzi, Gaetana; Vozzi, Diego; Marcuzzi, Annalisa; Valencic, Erica; Piscianz, Elisa; Bianco, AnnaMonica; Girardelli, Martina; Baronio, Manuela; Loganes, Claudia; Fasth, Anders; et al. (Clin Immunol, 2015)
Keywords: B-Lymphocytes; Child, Preschool; Female; Germinal Center; Humans; Hyper-IgM Immunodeficiency Syndrome; Infant; Male; Mutation; Phenotype; Phosphatidylinositol 3-Kinases; RNA Splice Sites; Sequence Analysis, DNA

Analgesia by cooling vibration during venipuncture in children with cognitive impairment. - Schreiber, Silvana; Cozzi, Giorgio; Rutigliano, Rosaria; Assandro, Paola; Tubaro, Martina; Cortellazzo Wiel, Luisa; Ronfani, Luca; Barbi, Egidio (Acta Paediatr, 2015)
AIM: Children with cognitive impairment experience pain more frequently than healthy children and are more likely to require venipuncture or intravenous cannulation for various procedures. They are frequently unable to report pain and often receive poor pain assessment and management. This study assessed the effectiveness of physical analgesia during vascular access in children with cognitive impairments. METHODS: We conducted a prospective randomised controlled study at a tertiary-level children's hospital in Italy from April to May 2015 to assess whether a cooling vibration device called Buzzy decreased pain during venipuncture and intravenous cannulation in children with cognitive impairment. None of the children had verbal skills and the main cognitive impairments were cerebral palsy, epileptic encephalopathy and genetic syndromes. RESULTS: We tested 70 children with a median age of nine years: 34 in the Buzzy group and 36 in the no-intervention group. Parents were trained in the use of the Noncommunicating Children's Pain Checklist - postoperative version scale, and they reported no or mild procedural pain in 32 cases (91.4%) in the Buzzy group and in 22 cases (61.1%) in the no-intervention group (p = 0.003). CONCLUSION: Cooling vibration analgesia during vascular access reduced pain in children with cognitive impairment.

The anti-leukemic activity of sodium dichloroacetate in p53mutated/null cells is mediated by a p53-independent ILF3/p21 pathway. - Agnoletto, Chiara; Brunelli, Laura; Melloni, Elisabetta; Pastorelli, Roberta; Casciano, Fabio; Rimondi, Erika; Rigolin, Gian Matteo; Cuneo, Antonio; Secchiero, Paola; Zauli, Giorgio (Oncotarget, 2015)
B-chronic lymphocytic leukemia (B-CLL) patients harboring p53 mutations are invariably refractory to therapies based on purine analogues and have limited treatment options and poor survival. Having recently demonstrated that the mitochondria-targeting small molecule sodium dichloroacetate (DCA) exhibits anti-leukemic activity in p53wild-type B-CLL cells, the aim of this study was to evaluate the effect of DCA in p53mutated B-CLL cells and in p53mutated/null leukemic cell lines. DCA exhibited comparable cytotoxicity in p53wild-type and p53mutated B-CLL patient cell cultures, as well as in p53mutated B leukemic cell lines (MAVER, MEC-1, MEC-2). At the molecular level, DCA promoted the transcriptional induction of p21 in all leukemic cell types investigated, including p53null HL-60. By using a proteomic approach, we demonstrated that DCA up-regulated the ILF3 transcription factor, which is a known regulator of p21 expression. The role of the ILF3/p21 axis in mediating the DCA anti-leukemic activity was underscored by knocking-down experiments. Indeed, transfection with ILF3 and p21 siRNAs significantly decreased both the DCA-induced p21 expression and the DCA-mediated cytotoxicity. Taken together, our results emphasize that DCA is a small molecule that merits further evaluation as a therapeutic agent also for p53mutated leukemic cells, by acting through the induction of a p53-independent pathway.

Applications of nanoparticles in cancer medicine and beyond: optical and multimodal in vivo imaging, tissue targeting and drug delivery. - Biffi, Stefania; Voltan, Rebecca; Rampazzo, Enrico; Prodi, Luca; Zauli, Giorgio; Secchiero, Paola (Expert Opin Drug Deliv, 2015)
INTRODUCTION: Nanotechnology has opened up the way to the engineering of new organized materials endowed with improved performances. In the past decade, engineered nanoparticles (NPs) have been progressively implemented by exploiting synthetic strategies that yield complex materials capable of performing functions with applications also in medicine. Indeed, in the field of 'nanomedicine' it has been explored the possibility to design multifunctional nanosystems, characterized by high analytical performances and stability, low toxicity and specificity towards a given cell target. Area covered: In this review article, we summarize the advances in the engineering of NPs for biomedical applications, from optical imaging (OI) to multimodal OI and targeted drug delivery. For this purpose, we will provide some examples of how investigations in nanomedicine can support preclinical and clinical research generating innovative diagnostic and therapeutic strategies in oncology. Expert opinion: The progressive breakthroughs in nanomedicine have supported the development of multifunctional and multimodal NPs. In particular, NPs are significantly impacting the diagnostic and therapeutic strategies since they allow the development of: NP-based OI probes containing more than one modality-specific contrast agent; surface functionalized NPs for specific 'molecular recognition'. Therefore, the design and characterization of innovative NP-based systems/devices have great applicative potential into the medical field.

Association Study between Cervical Lesions and Single or Multiple Vaccine-Target and Non-Vaccine Target Human Papillomavirus (HPV) Types in Women from Northeastern Brazil. - Chagas, Bárbara Simas; Comar, Manola; Gurgel, Ana Pavla Almeida Diniz; Paiva, Sérgio; Seraceni, Silva; de Freitas, Antonio Carlos; Crovella, Sergio (PLoS One, 2015)
We performed an association between high-grade squamous intraepithelial lesions (HSIL), low-grade squamous intraepithelial lesions (LSIL) and single or multiple vaccine-target as well as non-vaccine target Human papillomavirus (HPV) types. Using bead-based HPV genotyping, 594 gynecological samples were genotyped. An association between squamous intraepithelial lesion (SIL) and presence of HPV16, 18, 31, 58 and 56 types were calculated. The risk was estimated by using odds ratio (OR) and 95% of confidence intervals (CI). A total of 370 (62.3%) women were HPV positive. Among these, 157 (42.7%) presented a single HPV infection, and 212 (57.3%) were infected by more than one HPV type. HPV31 was the most prevalent genotype, regardless single and multiple HPV infections. Single infection with HPV31 was associated with LSIL (OR=2.32; 95%CI: 1.01 to 5.32; p=0.04); HPV31 was also associated with LSIL (OR=3.28; 95%CI: 1.74 to 6.19; p= 0.0002) and HSIL (OR=3.82; 95%CI: 2.10 to 6.97; p<0.001) in multiple HPV infections. Risk to harbor cervical lesions was observed in multiple HPV infections with regard to the HPV56 (OR=5.39; 95%CI: 2.44 to 11.90; p<0.001for LSIL; OR=5.37; 95%CI: 2.71 to 10.69; p<0.001) and HPV58 (OR=3.29; 95%CI: 1.34 to 8.09; p=0.0091 for LSIL; OR=3.55; 95%CI: 1.56 to 8.11; p=0.0026) genotypes. In addition, women coinfected with HPV16/31/56 types had 6 and 5-fold increased risk of HSIL (OR=6.46; 95%CI: 1.89 to 22.09; p=0.002) and LSIL (OR=5.22; 95%CI: 1.10 to 24.70; p=0.03), respectively. Multiple HPV infections without HPV16/18 has 2-fold increased risk of HSIL (OR=2.57; 95%CI: 1.41 to 4.70; p=0.002) and LSIL OR=2.03; 95%CI: 1.08 to 3.79; p=0.02). The results of this study suggest that single and multiple vaccine target as well as non-vaccine target HPV types are associated with LSIL and HSIL. These finding should be taken into consideration in the design of HPV vaccination strategies.

Bedside diagnosis of two major clinical phenotypes of hypertensive disorders of pregnancy. - Ferrazzi, E; Zullino, S; Stampalija, T; Vener, C; Cavoretto, P; Gervasi, M T; Vergani, P; Mecacci, F; Marozio, L; Oggè, G; Algeri, P; Ruffatti, A; et al. (Ultrasound Obstet Gynecol, 2015)
OBJECTIVE: We hypothesized that fetal abdominal circumference (AC) and Uterine Doppler Pulsatility Index (UtA-PI) could select two homogenous subgroups of women affected by hypertensive disorders of pregnancy (HDP), characterized by the coexistence of maternal hypertension with and without IUGR. METHODS: This is a multicentre study that studied cases affected by HDP in whom fetal AC and UtA-PI had been measured at admission to feto Maternal Medicine Units. Maternal characteristics, pregnancy complications and outcome were recorded. These data allowed us to model the characteristics of fetal growth in cases affected by HDP, and to design a composite index for risk factors of maternal metabolic syndrome (rfMMS) and composite index of severity for maternal organ and/or function damage (OFD). RESULTS: Measurements of fetal AC and UtA-PI allowed us to define a group of HDP with AGA fetuses (HDP-AGAf) diagnosed by normal fetal AC and a UtA-PI (#205), and a group of HDP with IUGR fetuses (HDP-IUGR) diagnosed by fetal AC <5(th) centile and UtA-PI >95(th) centile (#124). Curves fitted to birth-weight of the two groups were significantly different, and gestational age at admission for HDP, <34 or ≥34, had no effect on their models. When birth-weight was expressed as standard deviation score (SDS) of local reference charts, the average SDS (±standard error) corresponded to the 6(th) and 48(th) centile respectively. The risk of developing HDP-AGAf was significantly associated with risk factors for maternal metabolic syndrome (OR= 2.79;CI 1.57-4.97), independently of gestational age. The same risk factors yielded a non significant ORs of developing late onset HDP. Women with HDP-IUGR proved to be associated with the worst clinical outcomes. CONCLUSIONS: This study adds genuine new data based on simple prenatal bedside examinations, that might help to differentiate HDP with IUGR, from HDP with AGA fetuses, associated with different fetal growth patterns and different risk factors, not affected by gestational age at onset of the disease.

Brain sparing effect in growth-restricted fetuses is associated with decreased cardiac acceleration and deceleration capacities: a case-control study. - Stampalija, T; Casati, D; Monasta, L; Sassi, R; Rivolta, M W; Muggiasca, M L; Bauer, A; Ferrazzi, E (BJOG, 2015)
OBJECTIVE: Phase rectified signal averaging (PRSA) is a new method of fetal heart rate variability (fHRV) analysis that quantifies the average acceleration (AC) and deceleration capacity (DC) of the heart. The aim of this study was to evaluate AC and DC of fHR [recorded by trans-abdominal fetal electrocardiogram (ta-fECG)] in relation to Doppler velocimetry characteristics of intrauterine growth restriction (IUGR). DESIGN: Prospective case-control study. SETTING: Single third referral centre. POPULATION: IUGR (n = 66) between 25 and 40 gestational weeks and uncomplicated pregnancies (n = 79). METHODS: In IUGR the nearest ta-fECG monitoring to delivery was used for PRSA analysis and Doppler velocimetry parameters obtained within 48 hours. AC and DC were computed at s = T = 9. The relation was evaluated between either AC or DC and Doppler velocimetry parameters adjusting for gestational age at monitoring, as well as the association between either AC or DC and IUGR with or without brain sparing. RESULTS: In IUGRs there was a significant association between either AC and DC and middle cerebral artery pulsatility index (PI; P = 0.01; P = 0.005), but the same was not true for uterine or umbilical artery PI (P > 0.05). Both IUGR fetuses with and without brain sparing had lower AC and DC than controls, but this association was stronger for IUGRs with brain sparing. CONCLUSIONS: Our study observed for the first time that AC and DC at PRSA analysis are associated with middle cerebral artery PI, but not with uterine or umbilical artery PI, and that there is a significant decrease of AC and DC in association with brain sparing in IUGR fetuses from 25 weeks of gestation to term. TWEETABLE ABSTRACT: Brain sparing in IUGR fetuses is associated with decreased acceleration and deceleration capacities of the heart.

Cerebral oxygenation with different nasal continuous positive airway pressure levels in preterm infants. - Bembich, Stefano; Travan, Laura; Cont, Gabriele; Bua, Jenny; Strajn, Tamara; Demarini, Sergio (Arch Dis Child Fetal Neonatal Ed, 2015)
OBJECTIVES: This study evaluates the effect of varying nasal continuous positive airway pressure (NCPAP) level on cerebral blood flow (CBF) and oxygenation in preterm infants. METHODS: Oxy-haemoglobin (HbO2) and total haemoglobin (HbTot), as CBF estimates, and the ratio between HbO2 and HbTot (HbO2/HbTot), as cerebral oxygenation estimate, were assessed by near-infrared spectroscopy in 26 stable preterm newborns at a postmenstrual age between 26 and 33 weeks. Baseline HbO2, HbTot and HbO2/HbTot values were initially collected with NCPAP at 5 cm H2O and then compared with values obtained with NCPAP levels at both 3 and 8 cm H2O. RESULTS: Compared with 5 cm H2O, cerebral HbO2, HbTot and HbO2/HbTot remained unchanged both after increasing (to 8 cm H2O) and decreasing (to 3 cm H2O) the NCPAP level. This result was observed both in regional areas (24 sites) and in the overall monitored area (frontal and parietal cortex). Compared with 8 cm H2O, peripheral oxygen saturation significantly decreased at 3 cm H2O (p=0.021). Heart rate did not change. CONCLUSIONS: No differences in CBF and cerebral oxygenation were observed with NCPAP levels in the range 3-8 cm H2O despite a decrease in peripheral oxygenation with 3 cm H2O.
Keywords: Cerebrovascular Circulation; Continuous Positive Airway Pressure; Female; Hemoglobins; Humans; Infant, Newborn; Infant, Premature; Intensive Care, Neonatal; Male; Nasal Cavity; Oxygen; Oxygen Consumption; Oxyhemoglobins; Spectroscopy, Near-Infrared

Characterization of 14 novel deletions underlying Rubinstein-Taybi syndrome: an update of the CREBBP deletion repertoire. - Rusconi, Daniela; Negri, Gloria; Colapietro, Patrizia; Picinelli, Chiara; Milani, Donatella; Spena, Silvia; Magnani, Cinzia; Silengo, Margherita Cirillo; Sorasio, Lorena; Curtisova, Vaclava; Cavaliere, Maria Luigia; Prontera, Paolo; et al. (Hum Genet, 2015)
Rubinstein-Taybi syndrome (RSTS) is a rare, clinically heterogeneous disorder characterized by cognitive impairment and several multiple congenital anomalies. The syndrome is caused by almost private point mutations in the CREBBP (~55% of cases) and EP300 (~8%) genes. The CREBBP mutational spectrum is variegated and characterized by point mutations (30-50 %) and deletions (~10%). The latter are diverse in size and genomic position and remove either the whole CREBBP gene and its flanking regions or only an intragenic portion. Here, we report 14 novel CREBBP deletions ranging from single exons to the whole gene and flanking regions which were identified by applying complementary cytomolecular techniques: fluorescence in situ hybridization, multiplex ligation-dependent probe amplification and array comparative genome hybridization, to a large cohort of RSTS patients. Deletions involving CREBBP account for 23% of our detected CREBBP mutations, making an important contribution to the mutational spectrum. Genotype-phenotype correlations revealed that patients with CREBBP deletions extending beyond this gene did not always have a more severe phenotype than patients harboring CREBBP point mutations, suggesting that neighboring genes play only a limited role in the etiopathogenesis of CREBBP-centerd contiguous gene syndrome. Accordingly, the extent of the deletion is not predictive of the severity of the clinical phenotype.
Keywords: Adolescent; Adult; Base Sequence; Child; Child, Preschool; Cohort Studies; CREB-Binding Protein; Female; Humans; Infant; Infant, Newborn; Male; Middle Aged; Point Mutation; Rubinstein-Taybi Syndrome; Sequence Deletion

Clinical aspects of Fanconi anemia individuals with the same mutation of FANCF identified by next generation sequencing. - Nicchia, Elena; Benedicenti, Francesco; Rocco, Daniela De; Greco, Chiara; Bottega, Roberta; Inzana, Francesca; Faleschini, Michela; Bonin, Serena; Cappelli, Enrico; Mogni, Massimo; Stanzial, Franco; Svahn, Johanna; et al. (Birth Defects Res A Clin Mol Teratol, 2015)
BACKGROUND: Fanconi anemia (FA) is a rare genetic disease characterized by congenital malformations, aplastic anemia and increased risk of developing malignancies. FA is genetically heterogeneous as it is caused by at least 17 different genes. Among these, FANCA, FANCC, and FANCG account for approximately 85% of the patients whereas the remaining genes are mutated in only a small percentage of cases. For this reason, the molecular diagnostic process is complex and not always extended to all the FA genes, preventing the characterization of individuals belonging to rare groups. METHODS: The FA genes were analyzed using a next generation sequencing approach in two unrelated families. RESULTS: The analysis identified the same, c.484_485del, homozygous mutation of FANCF in both families. A careful examination of three electively aborted fetuses in one family and one affected girl in the other indicated an association of the FANCF loss-of-function mutation with a severe phenotype characterized by multiple malformations. CONCLUSION: The systematic use of next generation sequencing will allow the recognition of individuals from rare complementation groups, a better definition of their clinical phenotypes, and consequently, an appropriate genetic counseling. Birth Defects Research (Part A) 103:1003-1010, 2015. © 2015 Wiley Periodicals, Inc.

Combined circulating epigenetic markers to improve mesothelin performance in the diagnosis of malignant mesothelioma. - Santarelli, Lory; Staffolani, Sara; Strafella, Elisabetta; Nocchi, Linda; Manzella, Nicola; Grossi, Paola; Bracci, Massimo; Pignotti, Elettra; Alleva, Renata; Borghi, Battista; Pompili, Cecilia; Sabbatini, Armando; et al. (Lung Cancer, 2015)
OBJECTIVES: Malignant mesothelioma (MM) is a highly aggressive tumor with poor prognosis. A major challenge is the development and application of early and highly reliable diagnostic marker(s). Serum biomarkers, such as 'soluble mesothelin-related proteins' (SMRPs), is the most studied and frequently used in MM. However, the low sensitivity of SMRPs for early MM limits its value; therefore, additional biomarkers are required. In this study, two epigenetically regulated markers in MM (microRNA-126, miR-126, and methylated thrombomodulin promoter, Met-TM) were combined with SMRPs and evaluated as a potential strategy to detect MM at an early stage. MATERIALS AND METHODS: A total of 188 subjects, including 45 MM patients, 99 asbestos-exposed subjects, and 44 healthy controls were prospectively enrolled, serum samples collected, and serum levels of SMRPs, miR-126 and Met-TM evaluated. Logistic regression analysis was performed to evaluate the diagnostic value of the three biomarkers. Using this approach, the performance of the '3-biomarker classifier' was tested by calculating the overall probability score of the MM and control samples, respectively, and the ROC curve was generated. RESULTS AND CONCLUSION: The combination of the three biomarkers was the best predictor to differentiate MM patients from asbestos-exposed subjects and healthy controls. The accuracy and cancer specificity was confirmed in a second validation cohort and lung cancer population. We propose that the combination of the two epigenetic biomarkers with SMRPs as a diagnosis for early MM overcomes the limitations of using SMRPs alone.

Comment to Santos et al., "hyper-IgD and periodic fever syndrome: a new MVK mutation (p.R277G) associated with a severe phenotype". - Santos, Ruda de Luna Almeida; Crovella, Sergio; Celsi, Fulvio (Gene, 2015)
We performed molecular modeling analysis onto a novel mutation in the gene MVK, described by Santos et al., found to be causative of a severe form of Hyper-IgD/Mevalonate Kinase Deficiency. The mutation p.R277G, in our analysis, lowers the binding affinity for some enzyme's substrates. Interestingly, we found that p.R277G mutation inhibits binding of Isopentenyl Pyrophosphate (IPP) (binding free energy=0 kcal/mol), one of isoprenoids responsible for feedback-inhibition of MVK. IPP is known to be an activator of a specific class of T-cells and we can hypothesize that increased levels of this metabolite generate an aberrant immune system response. Indeed other experiments are needed to verify this hypothesis; however, this work demonstrates usefulness of molecular modeling in generating novel pathogenic hypothesis.
Keywords: Fever; Humans; Immunoglobulin D; Male; Mutation, Missense; Phosphotransferases (Alcohol Group Acceptor)

Comprehensive analysis of polymorphisms in the HLA-G 5' upstream regulatory and 3' untranslated regions in Brazilian patients with systemic lupus erythematosus. - Catamo, E; Addobbati, C; Segat, L; Sotero Fragoso, T; Tavares Dantas, A; de Ataíde Mariz, H; Ferreira da Rocha Junior, L; Branco PintoDuarte, A L; Coelho, A V C; de Moura, R R; Polesello, V; Crovella, S; et al. (Tissue Antigens, 2015)
This study aims to comprehensively analyze human leucocyte antigen (HLA)-G polymorphisms association with susceptibility to systemic lupus erythematosus (SLE) development and clinical manifestations. The HLA-G 5' upstream regulatory region (URR), 3' untranslated region (UTR) and a cytosine deletion at exon 3 (ΔC, HLA-G*0105N allele) were analyzed in 114 SLE patients and 128 healthy controls from North East Brazil. The +3003T>C (rs1707) C allele and the HG010101c extended HLA-G allele were significantly more frequent in SLE patients than healthy controls (+3003C allele frequency: 12% in SLE patients vs 6% in controls; odds ratio (OR), 2.10, 95% confidence interval (CI), 1.06-4.28, P = 0.026; HG010101c frequency: 11.8% in SLE patients and 6.3% in controls; OR, 2.14, 95% CI, 1.01-4.51, P = 0.046) and were associated with susceptibility for disease development. Other polymorphisms were associated with different clinical manifestations. Although HLA-G role in SLE disease is far from being elucidated yet, our association study results along with a systematic review and meta-analysis suggest that HLA-G might be able to slightly modulate the complex SLE phenotype (pooled OR, 1.14, 95% CI, 1.02-1.27, P = 0.021).

Design, Synthesis, and Biological Characterization of Novel Mitochondria Targeted Dichloroacetate-Loaded Compounds with Antileukemic Activity. - Trapella, Claudio; Voltan, Rebecca; Melloni, Elisabetta; Tisato, Veronica; Celeghini, Claudio; Bianco, Sara; Fantinati, Anna; Salvadori, Severo; Guerrini, Remo; Secchiero, Paola; Zauli, Giorgio (J Med Chem, 2015)
The mitochondrial kinase inhibitor dichloroacetate (DCA) has recently received attention in oncology due to its ability to target glycolysis. However, DCA molecule exhibits poor bioavailability and cellular uptake with limited ability to reach its target mitochondria. To overcome these biases, we have synthesized novel DCA-loaded compounds. The selection of the most promising therapeutic molecule was evaluated by combining in vitro assays, to test the antitumoral potential on leukemic cells, and a preliminary characterization of the molecule stability in vivo, in mice. Among the newly synthesized compounds, we have selected the multiple DCA-loaded compound 10, characterized by a tertiary amine scaffold, because it exhibited enhanced (>30-fold) in vitro antitumor activity with respect to DCA and increased in vivo stability. On the basis of these results, we believe that compound 10 should be considered for further preclinical evaluations for the treatment of cancers and/or other diseases characterized by altered metabolic origin.

Diagnostic criteria currently proposed for "ictal epileptic headache": Perspectives on strengths, weaknesses and pitfalls. - Parisi, Pasquale; Verrotti, Alberto; Costa, Paola; Striano, Pasquale; Zanus, Caterina; Carrozzi, Marco; Raucci, Umberto; Villa, Maria Pia; Belcastro, Vincenzo (Seizure, 2015)
PURPOSE: When we published the diagnostic criteria for "ictal epileptic headache" in 2012, we deliberately and consciously chose to adopt restrictive criteria that probably underestimate the phenomenon, rather than spread panic among patients and physicians who are reluctant to accept this entity. METHODS: Here we discuss four intriguing clinical cases to highlight why we believe, to this day, that it is necessary to follow these restrictive diagnostic criteria. CONCLUSIONS: EEG is not recommended as a routine examination for children diagnosed with headache, but it is mandatory and must be carried out promptly in cases of prolonged headache that does not respond to antimigraine drugs, if epilepsy is suspected or has been diagnosed previously. This is not a marginal or irrelevant question because possible isolated, non-motor, ictal manifestations should be taken into account before declaring that an epileptic patient is "seizure free" so as to ensure that any decision taken to suspend anticonvulsant therapy is safe.

Differential protein folding and chemical changes in lung tissues exposed to asbestos or particulates. - Pascolo, Lorella; Borelli, Violetta; Canzonieri, Vincenzo; Gianoncelli, Alessandra; Birarda, Giovanni; Bedolla, Diana E; Salomè, Murielle; Vaccari, Lisa; Calligaro, Carla; Cotte, Marine; Hesse, Bernhard; Luisi, Fernando; et al. (Sci Rep, 2015)
Environmental and occupational inhalants may induce a large number of pulmonary diseases, with asbestos exposure being the most risky. The mechanisms are clearly related to chemical composition and physical and surface properties of materials. A combination of X-ray fluorescence (μXRF) and Fourier Transform InfraRed (μFTIR) microscopy was used to chemically characterize and compare asbestos bodies versus environmental particulates (anthracosis) in lung tissues from asbestos exposed and control patients. μXRF analyses revealed heterogeneously aggregated particles in the anthracotic structures, containing mainly Si, K, Al and Fe. Both asbestos and particulates alter lung iron homeostasis, with a more marked effect in asbestos exposure. μFTIR analyses revealed abundant proteins on asbestos bodies but not on anthracotic particles. Most importantly, the analyses demonstrated that the asbestos coating proteins contain high levels of β-sheet structures. The occurrence of conformational changes in the proteic component of the asbestos coating provides new insights into long-term asbestos effects.

Directional dominance on stature and cognition in diverse human populations. - Joshi, Peter K; Esko, Tõnu; Mattsson, Hannele; Eklund, Niina; Gandin, Ilaria; Nutile, Teresa; Jackson, Anne U; Schurmann, Claudia; Smith, Albert V; Zhang, Weihua; Okada, Yukinori; Stančáková, Alena; et al. (Nature, 2015)
Homozygosity has long been associated with rare, often devastating, Mendelian disorders, and Darwin was one of the first to recognize that inbreeding reduces evolutionary fitness. However, the effect of the more distant parental relatedness that is common in modern human populations is less well understood. Genomic data now allow us to investigate the effects of homozygosity on traits of public health importance by observing contiguous homozygous segments (runs of homozygosity), which are inferred to be homozygous along their complete length. Given the low levels of genome-wide homozygosity prevalent in most human populations, information is required on very large numbers of people to provide sufficient power. Here we use runs of homozygosity to study 16 health-related quantitative traits in 354,224 individuals from 102 cohorts, and find statistically significant associations between summed runs of homozygosity and four complex traits: height, forced expiratory lung volume in one second, general cognitive ability and educational attainment (P < 1 × 10(-300), 2.1 × 10(-6), 2.5 × 10(-10) and 1.8 × 10(-10), respectively). In each case, increased homozygosity was associated with decreased trait value, equivalent to the offspring of first cousins being 1.2 cm shorter and having 10 months' less education. Similar effect sizes were found across four continental groups and populations with different degrees of genome-wide homozygosity, providing evidence that homozygosity, rather than confounding, directly contributes to phenotypic variance. Contrary to earlier reports in substantially smaller samples, no evidence was seen of an influence of genome-wide homozygosity on blood pressure and low density lipoprotein cholesterol, or ten other cardio-metabolic traits. Since directional dominance is predicted for traits under directional evolutionary selection, this study provides evidence that increased stature and cognitive function have been positively selected in human evolution, whereas many important risk factors for late-onset complex diseases may not have been.
Keywords: Biological Evolution; Blood Pressure; Body Height; Cholesterol, LDL; Cognition; Cohort Studies; Educational Status; Female; Forced Expiratory Volume; Genome, Human; Homozygote; Humans; Lung Volume Measurements; Male; Phenotype

Distribution of forensic marker allelic frequencies in Pernambuco, Northestern Brazil. - Santos, S M; Souza, C A; Rabelo, K C N; Souza, P R E; Moura, R R; Oliveira, T C; Crovella, S (Genet Mol Res, 2015)
Pernambuco is one of the 27 federal units of Brazil, ranking seventh in the number of inhabitants. We examined the allele frequencies of 13 short tandem repeat loci (CFS1PO, D3S1358, D5S818, D7S820, D8S1179, D13S317, D16S539, D18S51, D21S11, FGA, TH01, vWA, and TPOX), the minimum recommended by the Federal Bureau of Investigation and commonly used in forensic genetics laboratories in Brazil, in a sample of 609 unrelated individuals from all geographic regions of Pernambuco. The allele frequencies ranged from 5 to 47.2%. No significant differences for any loci analyzed were observed compared with other publications in other various regions of Brazil. Most of the markers observed were in Hardy-Weinberg equilibrium. The occurrence of the allele 47.2 (locus FGA) and alleles 35.1 and 39 (locus D21S11), also described in a single study of the Brazilian population, was observed. The other forensic parameters analyzed (matching probability, power of discrimination, polymorphic information content, paternity exclusion, complement factor I, observed heterozygosity, expected heterozygosity) indicated that the studied markers are very informative for human forensic identification purposes in the Pernambuco population.

Dysplastic bone marrow changes during maintenance therapy for acute leukemia. - Chinello, Matteo; Naviglio, Samuele; Shardlow, Alison; Severino, Alessandro; Ventura, Alessandro; Locasciulli, Anna (J Pediatr Hematol Oncol, 2015)
We describe the case of an 8-year-old girl with common precursor B-cell acute lymphoblastic leukemia who presented with severe pancytopenia during maintenance therapy with methotrexate and 6-mercaptopurine. The bone marrow smear showed moderate hypocellularity and trilinear dysplastic changes consistent with a diagnosis of drug toxicity, with no evidence of lymphoblasts. Flow cytometric immunophenotyping was negative for leukemic cells. Blood cell counts normalized after treatment with folinic acid. Maintenance therapy was gradually restarted and she remained well at follow-up visits. Myelotoxicity from methotrexate and 6-mercaptopurine may represent an unpredictable incident during an otherwise uneventful maintenance therapy, and may occur independently of other organ toxicities.
Keywords: 6-Mercaptopurine; Antineoplastic Combined Chemotherapy Protocols; Bone Marrow Diseases; Child; Disease Management; Female; Follow-Up Studies; Humans; Methotrexate; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Prognosis

Efficacy of intravenous immunoglobulin therapy in giant cell hepatitis with autoimmune hemolytic anemia: A multicenter study. - Marsalli, Giulia; Nastasio, Silvia; Sciveres, Marco; Calvo, Pier Luigi; Ramenghi, Ugo; Gatti, Simona; Albano, Veronica; Lega, Sara; Ventura, Alessandro; Maggiore, Giuseppe (Clin Res Hepatol Gastroenterol, 2015)
BACKGROUND AND OBJECTIVE: Giant cell hepatitis with autoimmune hemolytic anemia (GCH-AHA) is a rare disease of infancy, of possible autoimmune mechanism with poor prognosis due to its scarce response to immunosuppressive drugs. The aim of this retrospective multicenter study was to evaluate the efficacy and safety of intravenous immunoglobulin (IVIg) treatment in inducing and maintaining remission of the liver disease, in patients with GCH-AHA. METHODS: Seven children with GCH-AHA, four newly diagnosed, and three in relapse, being treated with different therapies, received one to three IVIg infusions (0.5 to 2g/kg) in association with other immunosuppressive drugs. Subsequently five of them received monthly sequential IVIg infusions (mean 13.4, range 7-24). RESULTS: IVIg infusions as first-line therapy associated with prednisone and other immunosuppressive drugs significantly (P=0.04) reduced the aminotransferase activity in all patients and normalized prothombin activity in the only patient with severe liver dysfunction. Sequential monthly IVIg infusions determined a steroid-sparing effect and allowed a complete or partial remission in all patients, although with temporary efficacy, since relapse of the hemolytic anemia and/or of liver disease occurred in all patients. IVIg infusions were associated with mild side effects in two patients. CONCLUSIONS: IVIg infusion can be safely and effectively administered in patients with severe GCH-AHA at diagnosis, or in case of relapse, in association with other immunosuppressive drugs. Repeated IVIg infusions may help maintain remission, however, due to their temporary efficacy, they should not be routinely employed.

Ficolin Gene Polymorphisms in Systemic Lupus Erythematosus and Rheumatoid Arthritis. - Addobbati, Catarina; De Azevêdo Silva, Jaqueline; A C Tavares, Nathália; Monticielo, Odirlei; M Xavier, Ricardo; T Brenol, João Carlos; Crovella, Sergio; B Chies, José Artur; Sandrin-Garcia, Paula (Ann Hum Genet, 2015)
Systemic lupus erythemathosus (SLE) and rheumatoid arthritis (RA) are complex autoimmune diseases characterized by an immune balance breakdown and by chronic inflammation. Several findings link SLE and RA development with the complement system and ficolin components have emerged as candidates for disease development. Since genetic association studies with ficolin genes in SLE and RA have not yet been conducted in a Brazilian population, the aim of this study was to determine whether polymorphisms of ficolin-1(FCN1) and ficolin-2 (FCN2) genes are associated with SLE and RA susceptibility as well as disease manifestation. Two SNPs within FCN1 (rs2989727 and 1071583) and three in FCN2 (rs17514136, rs3124954, and rs7851696) were studied in 208 SLE and184 RA patients as well as 264 healthy individuals in a Southeast Brazilian population. For SLE patients, the FCN2 rs17514136 SNP was associated with a more severe disease (SLICC) (p = 0.0067). Furthermore, an association between the occurrence of nephritis and the T/T genotype for FCN2 rs3124954 SNP (p = 0.047, OR = 3.17, 95%CI = 1.34-7.5) was observed. No association was observed between the studied polymorphisms and RA development. Thus, our data support involvement of the FCN2 gene in the SLE phenotype.

Food protein-induced enterocolitis syndrome caused by fish and/or shellfish in Italy. - Miceli Sopo, Stefano; Monaco, Serena; Badina, Laura; Barni, Simona; Longo, Giorgio; Novembre, Elio; Viola, Serena; Monti, Giovanna (Pediatr Allergy Immunol, 2015)
BACKGROUND: The study describes the demographic features, culprit foods, clinical features and outcomes for children presenting with acute fish and/or shellfish food protein-induced enterocolitis syndrome (FPIES) in four Italian paediatric allergy centres. METHODS: A retrospective/prospective study was undertaken. All children diagnosed with fish or shellfish FPIES were enrolled. The diagnosis of FPIES was based on Sicherer's or Miceli Sopo clinical criteria. Skin prick tests (SPT) were performed in all patients, at the time of diagnosis and prior to OFC. RESULTS: Seventy children were enrolled. Mean age at first episode was 14 months (range 6-46 months); mean age at diagnosis was 34 months (range 6-164 months). Sole and cod were the fish most commonly implicated. Fifty-seven of 70 (81%) children had FPIES exclusively to fish, 37 of 57 (65%) children had single-fish FPIES, 20 of 57 (35%) multiple-fish FPIES, nine of 70 (13%) presented adverse reactions exclusively to shellfish, and four of 70 (6%) presented adverse reactions to both fish and shellfish. Only four (5.7%) children presented episodes of acute FPIES with different foods (2 to cow's milk, 1 to egg, 1 to beef); in all cases, onset was prior to that of fish or shellfish FPIES. Fifteen of 70 (21%) children tolerated fish other than the offending fish. Twenty-four of 70 (34%) children achieved tolerance (age range 24-102 months). CONCLUSIONS: The chief peculiarities of acute fish and shellfish FPIES, compared to more frequent cow's milk or soy FPIES, are (i) later age of onset, (ii) longer persistence and (iii) possibility of tolerating fish other than the offending fish. Adverse reactions with shellfish are possible.

Functionalized synchrotron in-line phase-contrast computed tomography: a novel approach for simultaneous quantification of structural alterations and localization of barium-labelled alveolar macrophages within mouse lung samples. - Dullin, Christian; dal Monego, Simeone; Larsson, Emanuel; Mohammadi, Sara; Krenkel, Martin; Garrovo, Chiara; Biffi, Stefania; Lorenzon, Andrea; Markus, Andrea; Napp, Joanna; Salditt, Tim; Accardo, Agostino; et al. (J Synchrotron Radiat, 2015)
Functionalized computed tomography (CT) in combination with labelled cells is virtually non-existent due to the limited sensitivity of X-ray-absorption-based imaging, but would be highly desirable to realise cell tracking studies in entire organisms. In this study we applied in-line free propagation X-ray phase-contrast CT (XPCT) in an allergic asthma mouse model to assess structural changes as well as the biodistribution of barium-labelled macrophages in lung tissue. Alveolar macrophages that were barium-sulfate-loaded and fluorescent-labelled were instilled intratracheally into asthmatic and control mice. Mice were sacrificed after 24 h, lungs were kept in situ, inflated with air and scanned utilizing XPCT at the SYRMEP beamline (Elettra Synchrotron Light Source, Italy). Single-distance phase retrieval was used to generate data sets with ten times greater contrast-to-noise ratio than absorption-based CT (in our setup), thus allowing to depict and quantify structural hallmarks of asthmatic lungs such as reduced air volume, obstruction of airways and increased soft-tissue content. Furthermore, we found a higher concentration as well as a specific accumulation of the barium-labelled macrophages in asthmatic lung tissue. It is believe that XPCT will be beneficial in preclinical asthma research for both the assessment of therapeutic response as well as the analysis of the role of the recruitment of macrophages to inflammatory sites.
Keywords: Algorithms; Allergens; Animals; Asthma; Barium Sulfate; Cell Line, Transformed; Cell Movement; Contrast Media; Disease Models, Animal; Female; Image Processing, Computer-Assisted; Imaging, Three-Dimensional; Lung; Macrophages, Alveolar; Mice; Mice, Inbred BALB C; Microscopy, Fluorescence; Ovalbumin; Synchrotrons; Tomography, X-Ray Computed

Genetic determinants for methotrexate response in juvenile idiopathic arthritis. - Pastore, Serena; Stocco, Gabriele; Favretto, Diego; De Iudicibus, Sara; Taddio, Andrea; d'Adamo, Pio; Malusà, Noelia; Addobbati, Riccardo; Decorti, Giuliana; Lepore, Loredana; Ventura, Alessandro (Front Pharmacol, 2015)
Juvenile idiopathic arthritis (JIAs) is the most common chronic rheumatic disease of childhood and is an important cause of disability. The folic acid analog methotrexate is the first choice disease-modifying anti-rheumatic drug in this disease, however, 35-45% of patients fail to respond. Molecular elements, such as variants in genes of pharmacological relevance, influencing response to methotrexate in JIA, would be important to individualize treatment strategies. Several studies have evaluated the effects of candidate genetic variants in the complex pathway of genes involved in methotrexate pharmacodynamics and pharmacokinetics, however, results are still contrasting and no definitive genetic marker of methotrexate response useful for the clinician to tailor therapy of children with JIA has been identified. Recently, genome-wide approaches have been applied, identifying new potential biological processes involved in methotrexate response in JIA such as TGF-beta signaling and calcium channels. If these genomic results are properly validated and integrated with innovative analyses comprising deep sequencing, epigenetics, and pharmacokinetics, they will greatly contribute to personalize therapy with methotrexate in children with JIA.

Genetic profiling of autoinflammatory disorders in patients with periodic fever: a prospective study. - De Pieri, Carlo; Vuch, Josef; De Martino, Eleonora; Bianco, Anna M; Ronfani, Luca; Athanasakis, Emmanouil; Bortot, Barbara; Crovella, Sergio; Taddio, Andrea; Severini, Giovanni M; Tommasini, Alberto (Pediatr Rheumatol Online J, 2015)
BACKGROUND: Periodic fever syndromes (PFS) are an emerging group of autoinflammatory disorders. Clinical overlap exists and multiple genetic analyses may be needed to assist diagnosis. We evaluated the diagnostic value of a 5-gene sequencing panel (5GP) in patients with undiagnosed PFS. METHODS: Simultaneous double strand Sanger sequencing of MEFV, MVK, TNFRSF1A, NLRP3, NLRP12 genes was performed in 42 patients with unexplained PFS. Clinical features were correlated with genetic results. RESULTS: None of 42 patients analyzed displayed a causative genotype. However, single or multiple genetic variants of uncertain significance were detected in 24 subjects. Only in 5 subjects a definite diagnosis was made by taking into account both genetic and clinical data (2 TRAPS syndrome; 2 FMF; 1 FCAS). Statistical analysis showed that patients carrying genetic variants in one or more of the five selected genes displayed a significantly lower response to glucocorticoids compared with subjects who had completely negative genetic results. CONCLUSIONS: The sequencing of multiple genes is of little help in the diagnostics of PFS and can often lead to results of uncertain interpretation, thus the clinically driven sequencing of single genes should remain the recommended approach. However, the presence of single or multiple genetic variants of uncertain significance, even if not allowing any specific diagnosis, correlated with a poorer response to glucocorticoids, possibly indicating a multifactorial subgroup of PFS with differential response to pharmacological treatment.
Keywords: Adolescent; Carrier Proteins; Child; Cryopyrin-Associated Periodic Syndromes; Cytoskeletal Proteins; Familial Mediterranean Fever; Female; Fever; Gene Expression Profiling; Genotype; Hereditary Autoinflammatory Diseases; Humans; Intracellular Signaling Peptides and Proteins; Logistic Models; Male; Mutation; Phosphotransferases (Alcohol Group Acceptor); Prospective Studies; Receptors, Tumor Necrosis Factor, Type I; Syndrome

Genetic studies of body mass index yield new insights for obesity biology. - Locke, Adam E; Kahali, Bratati; Berndt, Sonja I; Justice, Anne E; Pers, Tune H; Day, Felix R; Powell, Corey; Vedantam, Sailaja; Buchkovich, Martin L; Yang, Jian; Croteau-Chonka, Damien C; Esko, Tõnu; et al. (Nature, 2015)
Obesity is heritable and predisposes to many diseases. To understand the genetic basis of obesity better, here we conduct a genome-wide association study and Metabochip meta-analysis of body mass index (BMI), a measure commonly used to define obesity and assess adiposity, in up to 339,224 individuals. This analysis identifies 97 BMI-associated loci (P < 5 × 10(-8)), 56 of which are novel. Five loci demonstrate clear evidence of several independent association signals, and many loci have significant effects on other metabolic phenotypes. The 97 loci account for ∼2.7% of BMI variation, and genome-wide estimates suggest that common variation accounts for >20% of BMI variation. Pathway analyses provide strong support for a role of the central nervous system in obesity susceptibility and implicate new genes and pathways, including those related to synaptic function, glutamate signalling, insulin secretion/action, energy metabolism, lipid biology and adipogenesis.
Keywords: Adipogenesis; Adiposity; Age Factors; Body Mass Index; Continental Population Groups; Energy Metabolism; Europe; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glutamic Acid; Humans; Insulin; Male; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Synapses

Genetic testing and genomic analysis: a debate on ethical, social and legal issues in the Arab world with a focus on Qatar. - El Shanti, Hatem; Chouchane, Lotfi; Badii, Ramin; Gallouzi, Imed Eddine; Gasparini, Paolo (J Transl Med, 2015)
In 2013 both Saudi Arabia and Qatar launched genome projects with the aim of providing information for better diagnosis, treatment and prevention of diseases and, ultimately to realize personalized medicine by sequencing hundred thousands samples. These population based genome activities raise a series of relevant ethical, legal and social issues general, related to the specific population structure as well as to the Islamic perspective on genomic analysis and genetic testing. To contribute to the debate, the Authors after reviewing the existing literature and taking advantage of their professional experience in the field and in the geographic area, discuss and provide their opinions. In particular, the Authors focus on the impact of consanguinity on population structure and disease frequency in the Arab world, on genetic testing and genomic analysis (i.e. technical aspects, impact, etc.) and on their regulations. A comparison between the Islamic perspective and the ethical, social and legal issues raised in other population contexts is also carried. In conclusion, this opinion article with an up-to-date contribution to the discussion on the relevance and impact of genomic analysis and genetic testing in the Arab world, might help in producing specific national guidelines on genetic testing and genomic analysis and help accelerate the implementation and roll out of genome projects in Muslim countries and more specifically in Qatar, and other countries of the Gulf.

Genome sequencing elucidates Sardinian genetic architecture and augments association analyses for lipid and blood inflammatory markers. - Sidore, Carlo; Busonero, Fabio; Maschio, Andrea; Porcu, Eleonora; Naitza, Silvia; Zoledziewska, Magdalena; Mulas, Antonella; Pistis, Giorgio; Steri, Maristella; Danjou, Fabrice; Kwong, Alan; Ortega Del Vecchyo, Vicente Diego; et al. (Nat Genet, 2015)
We report ∼17.6 million genetic variants from whole-genome sequencing of 2,120 Sardinians; 22% are absent from previous sequencing-based compilations and are enriched for predicted functional consequences. Furthermore, ∼76,000 variants common in our sample (frequency >5%) are rare elsewhere (<0.5% in the 1000 Genomes Project). We assessed the impact of these variants on circulating lipid levels and five inflammatory biomarkers. We observe 14 signals, including 2 major new loci, for lipid levels and 19 signals, including 2 new loci, for inflammatory markers. The new associations would have been missed in analyses based on 1000 Genomes Project data, underlining the advantages of large-scale sequencing in this founder population.

Genome-wide association analysis on five isolated populations identifies variants of the HLA-DOA gene associated with white wine liking. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; Amin, Najaf; Sala, Cinzia; Karssen, Lennart C; van Duijn, Cornelia M; Toniolo, Daniela; Gasparini, Paolo (Eur J Hum Genet, 2015)
Wine is the most popular alcoholic beverage around the world and because of its importance in society has been widely studied. Understanding what drives its flavor has been a quest for decades but much is still unknown and will be determined at least in part by individual taste preferences. Recently studies in the genetics of taste have uncovered the role of different genes in the determination of food preferences giving new insight on its physiology. In this context we have performed a genome-wide association study on red and white wine liking using three isolated populations collected in Italy, and replicated our results on two additional populations coming from the Netherland and Central Asia for a total of 3885 samples. We have found a significant association (P=2.1 × 10(-8)) between white wine liking and rs9276975:C>T a polymorphism in the HLA-DOA gene encoding a non-canonical MHC II molecule, which regulates other MHC II molecules. The same association was also found with red wine liking (P=8.3 × 10(-6)). Sex-separated analysis have also revealed that the effect of HLA-DOA is twice as large in women as compared to men suggesting an interaction between this polymorphism and gender. Our results are one of the first examples of genome-wide association between liking of a commonly consumed food and gene variants. Moreover, our results suggest a role of the MHC system in the determination of food preferences opening new insight in this field in general.

Genome-wide association analysis on normal hearing function identifies PCDH20 and SLC28A3 as candidates for hearing function and loss. - Vuckovic, Dragana; Dawson, Sally; Scheffer, Deborah I; Rantanen, Taina; Morgan, Anna; Di Stazio, Mariateresa; Vozzi, Diego; Nutile, Teresa; Concas, Maria P; Biino, Ginevra; Nolan, Lisa; Bahl, Aileen; et al. (Hum Mol Genet, 2015)
Hearing loss and individual differences in normal hearing both have a substantial genetic basis. Although many new genes contributing to deafness have been identified, very little is known about genes/variants modulating the normal range of hearing ability. To fill this gap, we performed a two-stage meta-analysis on hearing thresholds (tested at 0.25, 0.5, 1, 2, 4, 8 kHz) and on pure-tone averages (low-, medium- and high-frequency thresholds grouped) in several isolated populations from Italy and Central Asia (total N = 2636). Here, we detected two genome-wide significant loci close to PCDH20 and SLC28A3 (top hits: rs78043697, P = 4.71E-10 and rs7032430, P = 2.39E-09, respectively). For both loci, we sought replication in two independent cohorts: B58C from the UK (N = 5892) and FITSA from Finland (N = 270). Both loci were successfully replicated at a nominal level of significance (P < 0.05). In order to confirm our quantitative findings, we carried out RT-PCR and reported RNA-Seq data, which showed that both genes are expressed in mouse inner ear, especially in hair cells, further suggesting them as good candidates for modulatory genes in the auditory system. Sequencing data revealed no functional variants in the coding region of PCDH20 or SLC28A3, suggesting that variation in regulatory sequences may affect expression. Overall, these results contribute to a better understanding of the complex mechanisms underlying human hearing function.

Germline mutations in ETV6 are associated with thrombocytopenia, red cell macrocytosis and predisposition to lymphoblastic leukemia. - Noetzli, Leila; Lo, Richard W; Lee-Sherick, Alisa B; Callaghan, Michael; Noris, Patrizia; Savoia, Anna; Rajpurkar, Madhvi; Jones, Kenneth; Gowan, Katherine; Balduini, Carlo L; Pecci, Alessandro; Gnan, Chiara; et al. (Nat Genet, 2015)
Some familial platelet disorders are associated with predisposition to leukemia, myelodysplastic syndrome (MDS) or dyserythropoietic anemia. We identified a family with autosomal dominant thrombocytopenia, high erythrocyte mean corpuscular volume (MCV) and two occurrences of B cell-precursor acute lymphoblastic leukemia (ALL). Whole-exome sequencing identified a heterozygous single-nucleotide change in ETV6 (ets variant 6), c.641C>T, encoding a p.Pro214Leu substitution in the central domain, segregating with thrombocytopenia and elevated MCV. A screen of 23 families with similar phenotypes identified 2 with ETV6 mutations. One family also had a mutation encoding p.Pro214Leu and one individual with ALL. The other family had a c.1252A>G transition producing a p.Arg418Gly substitution in the DNA-binding domain, with alternative splicing and exon skipping. Functional characterization of these mutations showed aberrant cellular localization of mutant and endogenous ETV6, decreased transcriptional repression and altered megakaryocyte maturation. Our findings underscore a key role for ETV6 in platelet formation and leukemia predisposition.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Erythrocytes, Abnormal; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; Germ-Line Mutation; HEK293 Cells; Hematologic Diseases; Humans; Male; Mutation, Missense; Pedigree; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Proto-Oncogene Proteins c-ets; Repressor Proteins; Thrombocytopenia

The Global Burden of Cancer 2013. - Fitzmaurice, Christina; Dicker, Daniel; Pain, Amanda; Hamavid, Hannah; Moradi-Lakeh, Maziar; MacIntyre, Michael F; Allen, Christine; Hansen, Gillian; Woodbrook, Rachel; Wolfe, Charles; Hamadeh, Randah R; Moore, Ami; et al. (JAMA Oncol, 2015)
IMPORTANCE: Cancer is among the leading causes of death worldwide. Current estimates of cancer burden in individual countries and regions are necessary to inform local cancer control strategies. OBJECTIVE: To estimate mortality, incidence, years lived with disability (YLDs), years of life lost (YLLs), and disability-adjusted life-years (DALYs) for 28 cancers in 188 countries by sex from 1990 to 2013. EVIDENCE REVIEW: The general methodology of the Global Burden of Disease (GBD) 2013 study was used. Cancer registries were the source for cancer incidence data as well as mortality incidence (MI) ratios. Sources for cause of death data include vital registration system data, verbal autopsy studies, and other sources. The MI ratios were used to transform incidence data to mortality estimates and cause of death estimates to incidence estimates. Cancer prevalence was estimated using MI ratios as surrogates for survival data; YLDs were calculated by multiplying prevalence estimates with disability weights, which were derived from population-based surveys; YLLs were computed by multiplying the number of estimated cancer deaths at each age with a reference life expectancy; and DALYs were calculated as the sum of YLDs and YLLs. FINDINGS: In 2013 there were 14.9 million incident cancer cases, 8.2 million deaths, and 196.3 million DALYs. Prostate cancer was the leading cause for cancer incidence (1.4 million) for men and breast cancer for women (1.8 million). Tracheal, bronchus, and lung (TBL) cancer was the leading cause for cancer death in men and women, with 1.6 million deaths. For men, TBL cancer was the leading cause of DALYs (24.9 million). For women, breast cancer was the leading cause of DALYs (13.1 million). Age-standardized incidence rates (ASIRs) per 100 000 and age-standardized death rates (ASDRs) per 100 000 for both sexes in 2013 were higher in developing vs developed countries for stomach cancer (ASIR, 17 vs 14; ASDR, 15 vs 11), liver cancer (ASIR, 15 vs 7; ASDR, 16 vs 7), esophageal cancer (ASIR, 9 vs 4; ASDR, 9 vs 4), cervical cancer (ASIR, 8 vs 5; ASDR, 4 vs 2), lip and oral cavity cancer (ASIR, 7 vs 6; ASDR, 2 vs 2), and nasopharyngeal cancer (ASIR, 1.5 vs 0.4; ASDR, 1.2 vs 0.3). Between 1990 and 2013, ASIRs for all cancers combined (except nonmelanoma skin cancer and Kaposi sarcoma) increased by more than 10% in 113 countries and decreased by more than 10% in 12 of 188 countries. CONCLUSIONS AND RELEVANCE: Cancer poses a major threat to public health worldwide, and incidence rates have increased in most countries since 1990. The trend is a particular threat to developing nations with health systems that are ill-equipped to deal with complex and expensive cancer treatments. The annual update on the Global Burden of Cancer will provide all stakeholders with timely estimates to guide policy efforts in cancer prevention, screening, treatment, and palliation.

Global, regional, and national comparative risk assessment of 79 behavioural, environmental and occupational, and metabolic risks or clusters of risks in 188 countries, 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Forouzanfar, Mohammad H; Alexander, Lily; Anderson, H Ross; Bachman, Victoria F; Biryukov, Stan; Brauer, Michael; Burnett, Richard; Casey, Daniel; Coates, Matthew M; Cohen, Aaron; Delwiche, Kristen; Estep, Kara; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease, Injuries, and Risk Factor study 2013 (GBD 2013) is the first of a series of annual updates of the GBD. Risk factor quantification, particularly of modifiable risk factors, can help to identify emerging threats to population health and opportunities for prevention. The GBD 2013 provides a timely opportunity to update the comparative risk assessment with new data for exposure, relative risks, and evidence on the appropriate counterfactual risk distribution. METHODS: Attributable deaths, years of life lost, years lived with disability, and disability-adjusted life-years (DALYs) have been estimated for 79 risks or clusters of risks using the GBD 2010 methods. Risk-outcome pairs meeting explicit evidence criteria were assessed for 188 countries for the period 1990-2013 by age and sex using three inputs: risk exposure, relative risks, and the theoretical minimum risk exposure level (TMREL). Risks are organised into a hierarchy with blocks of behavioural, environmental and occupational, and metabolic risks at the first level of the hierarchy. The next level in the hierarchy includes nine clusters of related risks and two individual risks, with more detail provided at levels 3 and 4 of the hierarchy. Compared with GBD 2010, six new risk factors have been added: handwashing practices, occupational exposure to trichloroethylene, childhood wasting, childhood stunting, unsafe sex, and low glomerular filtration rate. For most risks, data for exposure were synthesised with a Bayesian meta-regression method, DisMod-MR 2.0, or spatial-temporal Gaussian process regression. Relative risks were based on meta-regressions of published cohort and intervention studies. Attributable burden for clusters of risks and all risks combined took into account evidence on the mediation of some risks such as high body-mass index (BMI) through other risks such as high systolic blood pressure and high cholesterol. FINDINGS: All risks combined account for 57·2% (95% uncertainty interval [UI] 55·8-58·5) of deaths and 41·6% (40·1-43·0) of DALYs. Risks quantified account for 87·9% (86·5-89·3) of cardiovascular disease DALYs, ranging to a low of 0% for neonatal disorders and neglected tropical diseases and malaria. In terms of global DALYs in 2013, six risks or clusters of risks each caused more than 5% of DALYs: dietary risks accounting for 11·3 million deaths and 241·4 million DALYs, high systolic blood pressure for 10·4 million deaths and 208·1 million DALYs, child and maternal malnutrition for 1·7 million deaths and 176·9 million DALYs, tobacco smoke for 6·1 million deaths and 143·5 million DALYs, air pollution for 5·5 million deaths and 141·5 million DALYs, and high BMI for 4·4 million deaths and 134·0 million DALYs. Risk factor patterns vary across regions and countries and with time. In sub-Saharan Africa, the leading risk factors are child and maternal malnutrition, unsafe sex, and unsafe water, sanitation, and handwashing. In women, in nearly all countries in the Americas, north Africa, and the Middle East, and in many other high-income countries, high BMI is the leading risk factor, with high systolic blood pressure as the leading risk in most of Central and Eastern Europe and south and east Asia. For men, high systolic blood pressure or tobacco use are the leading risks in nearly all high-income countries, in north Africa and the Middle East, Europe, and Asia. For men and women, unsafe sex is the leading risk in a corridor from Kenya to South Africa. INTERPRETATION: Behavioural, environmental and occupational, and metabolic risks can explain half of global mortality and more than one-third of global DALYs providing many opportunities for prevention. Of the larger risks, the attributable burden of high BMI has increased in the past 23 years. In view of the prominence of behavioural risk factors, behavioural and social science research on interventions for these risks should be strengthened. Many prevention and primary care policy options are available now to act on key risks. FUNDING: Bill & Melinda Gates Foundation.

Global, regional, and national disability-adjusted life years (DALYs) for 306 diseases and injuries and healthy life expectancy (HALE) for 188 countries, 1990-2013: quantifying the epidemiological transition. - Murray, Christopher J L; Barber, Ryan M; Foreman, Kyle J; Abbasoglu Ozgoren, Ayse; Abd-Allah, Foad; Abera, Semaw F; Aboyans, Victor; Abraham, Jerry P; Abubakar, Ibrahim; Abu-Raddad, Laith J; Abu-Rmeileh, Niveen M; Achoki, Tom; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease Study 2013 (GBD 2013) aims to bring together all available epidemiological data using a coherent measurement framework, standardised estimation methods, and transparent data sources to enable comparisons of health loss over time and across causes, age-sex groups, and countries. The GBD can be used to generate summary measures such as disability-adjusted life-years (DALYs) and healthy life expectancy (HALE) that make possible comparative assessments of broad epidemiological patterns across countries and time. These summary measures can also be used to quantify the component of variation in epidemiology that is related to sociodemographic development. METHODS: We used the published GBD 2013 data for age-specific mortality, years of life lost due to premature mortality (YLLs), and years lived with disability (YLDs) to calculate DALYs and HALE for 1990, 1995, 2000, 2005, 2010, and 2013 for 188 countries. We calculated HALE using the Sullivan method; 95% uncertainty intervals (UIs) represent uncertainty in age-specific death rates and YLDs per person for each country, age, sex, and year. We estimated DALYs for 306 causes for each country as the sum of YLLs and YLDs; 95% UIs represent uncertainty in YLL and YLD rates. We quantified patterns of the epidemiological transition with a composite indicator of sociodemographic status, which we constructed from income per person, average years of schooling after age 15 years, and the total fertility rate and mean age of the population. We applied hierarchical regression to DALY rates by cause across countries to decompose variance related to the sociodemographic status variable, country, and time. FINDINGS: Worldwide, from 1990 to 2013, life expectancy at birth rose by 6·2 years (95% UI 5·6-6·6), from 65·3 years (65·0-65·6) in 1990 to 71·5 years (71·0-71·9) in 2013, HALE at birth rose by 5·4 years (4·9-5·8), from 56·9 years (54·5-59·1) to 62·3 years (59·7-64·8), total DALYs fell by 3·6% (0·3-7·4), and age-standardised DALY rates per 100 000 people fell by 26·7% (24·6-29·1). For communicable, maternal, neonatal, and nutritional disorders, global DALY numbers, crude rates, and age-standardised rates have all declined between 1990 and 2013, whereas for non-communicable diseases, global DALYs have been increasing, DALY rates have remained nearly constant, and age-standardised DALY rates declined during the same period. From 2005 to 2013, the number of DALYs increased for most specific non-communicable diseases, including cardiovascular diseases and neoplasms, in addition to dengue, food-borne trematodes, and leishmaniasis; DALYs decreased for nearly all other causes. By 2013, the five leading causes of DALYs were ischaemic heart disease, lower respiratory infections, cerebrovascular disease, low back and neck pain, and road injuries. Sociodemographic status explained more than 50% of the variance between countries and over time for diarrhoea, lower respiratory infections, and other common infectious diseases; maternal disorders; neonatal disorders; nutritional deficiencies; other communicable, maternal, neonatal, and nutritional diseases; musculoskeletal disorders; and other non-communicable diseases. However, sociodemographic status explained less than 10% of the variance in DALY rates for cardiovascular diseases; chronic respiratory diseases; cirrhosis; diabetes, urogenital, blood, and endocrine diseases; unintentional injuries; and self-harm and interpersonal violence. Predictably, increased sociodemographic status was associated with a shift in burden from YLLs to YLDs, driven by declines in YLLs and increases in YLDs from musculoskeletal disorders, neurological disorders, and mental and substance use disorders. In most country-specific estimates, the increase in life expectancy was greater than that in HALE. Leading causes of DALYs are highly variable across countries. INTERPRETATION: Global health is improving. Population growth and ageing have driven up numbers of DALYs, but crude rates have remained relatively constant, showing that progress in health does not mean fewer demands on health systems. The notion of an epidemiological transition--in which increasing sociodemographic status brings structured change in disease burden--is useful, but there is tremendous variation in burden of disease that is not associated with sociodemographic status. This further underscores the need for country-specific assessments of DALYs and HALE to appropriately inform health policy decisions and attendant actions. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Aged; Chronic Disease; Communicable Diseases; Female; Global Health; Health Transition; Humans; Life Expectancy; Male; Middle Aged; Mortality, Premature; Quality-Adjusted Life Years; Socioeconomic Factors; Wounds and Injuries

Glucocorticoid pharmacogenetics in pediatric idiopathic nephrotic syndrome. - Cuzzoni, Eva; De Iudicibus, Sara; Franca, Raffaella; Stocco, Gabriele; Lucafò, Marianna; Pelin, Marco; Favretto, Diego; Pasini, Andrea; Montini, Giovanni; Decorti, Giuliana (Pharmacogenomics, 2015)
Idiopathic nephrotic syndrome represents the most common type of primary glomerular disease in children: glucocorticoids (GCs) are the first-line therapy, even if considerable interindividual differences in thepir efficacy and side effects have been reported. Immunosuppressive and anti-inflammatory effects of these drugs are mainly due to the GC-mediated transcription regulation of pro- and anti-inflammatory genes. This mechanism of action is the result of a complex multistep pathway that involves the glucocorticoid receptor and several other proteins, encoded by polymorphic genes. Aim of this review is to highlight the current knowledge on genetic variants that could affect GC response, particularly focusing on children with idiopathic nephrotic syndrome.

HLA-G and susceptibility to develop celiac disease. - Catamo, Eulalia; Zupin, Luisa; Segat, Ludovica; Celsi, Fulvio; Crovella, Sergio (Hum Immunol, 2015)
The Human Leukocyte Antigen-G has immunomodulatory function and its expression has been associated with several diseases. In our study we analyzed HLA-G polymorphisms in order to evaluate their possible association with susceptibility to celiac disease development. A total of 420 celiac patients and 509 controls were genotyped for HLA-G polymorphisms. We sequenced 800bp upstream the ATG codon (5' upstream regulatory region) and the whole 3' untranslated region of the HLA-G gene, whereas the ΔC deletion at exon 3 was detected by RFLP-PCR. Five polymorphisms (namely -477 C>G, -369 C>A, 14bp del/ins, 3187 A>G, 3196 C>G) and one haplotype (TCGGTACGAAITCCCGAG) were significantly more frequent in celiac patients than controls and associated with increased disease susceptibility. The 14bp I/I, 3187 G/G, 3196 G/G genotypes and TCGGTACGAAITCCCGAG haplotype, were still significantly associated with increased disease susceptibility (and in addition also the 3003 C/C genotype) when the analysis was restricted to patients and controls presenting the DQ2.5 or DQ8 HLA-DQ celiac disease risk haplotypes. Our findings indicate an association between HLA-G gene polymorphisms and susceptibility to celiac disease development, suggesting that HLA-G molecule is possibly involved in the pathogenesis of the disease.
Keywords: Adolescent; Adult; Alleles; Case-Control Studies; Celiac Disease; Child; Female; Gene Frequency; Genetic Predisposition to Disease; Haplotypes; HLA-DQ Antigens; HLA-G Antigens; Humans; Male; Middle Aged; Polymorphism, Genetic; Retrospective Studies

Hypoxaemia as a Mortality Risk Factor in Acute Lower Respiratory Infections in Children in Low and Middle-Income Countries: Systematic Review and Meta-Analysis. - Lazzerini, Marzia; Sonego, Michela; Pellegrin, Maria Chiara (PLoS One, 2015)
OBJECTIVE: To evaluate the association between hypoxaemia and mortality from acute lower respiratory infections (ALRI) in children in low- and middle-income countries (LMIC). DESIGN: Systematic review and meta-analysis. STUDY SELECTION: Observational studies reporting on the association between hypoxaemia and death from ALRI in children below five years in LMIC. DATA SOURCES: Medline, Embase, Global Health Library, Lilacs, and Web of Science to February 2015. RISK OF BIAS ASSESSMENT: Quality In Prognosis Studies tool with minor adaptations to assess the risk of bias; funnel plots and Egger's test to evaluate publication bias. RESULTS: Out of 11,627 papers retrieved, 18 studies from 13 countries on 20,224 children met the inclusion criteria. Twelve (66.6%) studies had either low or moderate risk of bias. Hypoxaemia defined as oxygen saturation rate (SpO2) <90% associated with significantly increased odds of death from ALRI (OR 5.47, 95% CI 3.93 to 7.63) in 12 studies on 13,936 children. An Sp02 <92% associated with a similar increased risk of mortality (OR 3.66, 95% CI 1.42 to 9.47) in 3 studies on 673 children. Sensitivity analyses (excluding studies with high risk of bias and using adjusted OR) and subgroup analyses (by: altitude, definition of ALRI, country income, HIV prevalence) did not affect results. Only one study was performed on children living at high altitude. CONCLUSIONS: The results of this review support the routine evaluation of SpO2 for identifying children with ALRI at increased risk of death. Both a Sp02 value of 92% and 90% equally identify children at increased risk of mortality. More research is needed on children living at high altitude. Policy makers in LMIC should aim at improving the regular use of pulse oximetry and the availability of oxygen in order to decrease mortality from ALRI.

Hysteroscopic chasing for endometrial cancer in a low-risk population: risks of overinvestigation. - Scrimin, Federica; Wiesenfeld, Uri; Galati, Emanuele F; Monasta, Lorenzo; Ricci, Giuseppe (Arch Gynecol Obstet, 2015)
PURPOSE: To evaluate the appropriateness of the indications for hysteroscopy done, in fertile and postmenopausal women, for the detection of endometrial cancer. METHODS: A retrospective analysis of 2673 consecutive women who underwent office hysteroscopy chasing for endometrial cancer between January 2012 and June 2014. According to their medical history only low-risk women entered the study. RESULTS: A total of 1070 patients entered the study. The main outcome measure was the appropriateness of the indications for hysteroscopy. Appropriateness was assessed on the basis of guidelines of scientific societies and histologic report. According to the algorithm developed for appropriateness, 44 % of procedures resulted in being inappropriate. In reproductive-aged women 57 % of hysteroscopies were inappropriate. In postmenopausal women inappropriate hysteroscopies were 45 %. In reproductive-aged women, the reasons for inappropriateness were: absence of abnormal uterine bleeding (AUB) or AUB without a trial of progestin therapy. In postmenopausal women, the reasons for inappropriateness were: ultrasound report of endometrial thickening or polyp without bleeding. CONCLUSIONS: Hysteroscopy is often recommended for inappropriate indications. More evidence is needed to identify the risks of overinvestigation, overdiagnosis, and related overtreatment and to better identify the threshold beyond which benefits are likely to outweigh harms.

Identification of a novel frameshift mutation in the EDAR gene causing autosomal dominant hypohidrotic ectodermal dysplasia. - Callea, M; Willoughby, C E; Nieminen, P; Di Stazio, M; Bellacchio, E; Giglio, S; Sani, I; Vinciguerra, A; Maglione, M; Tadini, G; Clarich, G (J Eur Acad Dermatol Venereol, 2015)

Impact of DEFB1 gene regulatory polymorphisms on hBD-1 salivary concentration. - Polesello, Vania; Zupin, Luisa; Di Lenarda, Roberto; Biasotto, Matteo; Ottaviani, Giulia; Gobbo, Margherita; Cecco, Luca; Alberi, Giulia; Pozzato, Gabriele; Crovella, Sergio; Segat, Ludovica (Arch Oral Biol, 2015)
OBJECTIVES: Human β-defensin 1 (hBD-1) is an antimicrobial peptide involved in epithelial defence of various tissues, also present in the saliva. Individual genetic variations within the DEFB1 gene, encoding for hBD-1, could influence gene expression and protein production. DESIGN: Three DEFB1 polymorphisms at 5' untranslated region (UTR), -52G > A (rs1799946), -44C > G (rs1800972) and -20G > A (rs11362), and two polymorphisms at DEFB1 3' UTR, c*5G > A (rs1047031) and c*87A > G (rs1800971), were analysed by direct sequencing and correlated with hDB-1 salivary concentration (tested with enzyme-linked immunosorbent assay (ELISA)) in 40 healthy subjects. RESULTS: Significant associations were found between individuals presenting different DEFB1 polymorphisms at positions -52 and -44 of the gene and hBD-1 salivary concentrations: -52 G/G carriers had higher levels of protein than G/A and A/A; -44C/G subjects showed a higher protein concentration than homozygous wild-type C/C. For the -20G > A, c*5G > A and c*87A > G polymorphisms, no statistically significant differences were found. Combined haplotype analysis confirmed the results obtained considering the single-nucleotide polymorphisms (SNPs) singularly. CONCLUSION: Polymorphisms in the DEFB1 gene influence hBD-1 production and, therefore, could modify the innate immune system responses and, consequently, the oral health.

Impaired immune response to Candida albicans in cells from Fanconi anemia patients. - Parodi, Alessia; Kalli, Francesca; Svahn, Johanna; Stroppiana, Giorgia; De Rocco, Daniela; Terranova, Paola; Dufour, Carlo; Fenoglio, Daniela; Cappelli, Enrico (Cytokine, 2015)
Fanconi anemia (FA) is a genetic disorder characterized by bone marrow failure and cancer predisposition. Several studies show alterations of the immunological status of FA patients including defects in peripheral blood lymphocyte subsets, serum immunoglobulin levels, and inflammatory cytokines. However scanty information is available on the response of FA cells to specific infectious antigens. In this work we examined the response of FA cells to different immunological stimuli and found a defective response of IL-1β, TNF-α and IL-17 to Candida albicans stimulation thus pointing to a potentially impaired response to fungal infections of FA patients.
Keywords: Adolescent; Candida albicans; CD8-Positive T-Lymphocytes; Cell Proliferation; Cells, Cultured; Child; Child, Preschool; Cytokines; Fanconi Anemia; Humans; Immunity; Infant; Young Adult

Improved imputation of low-frequency and rare variants using the UK10K haplotype reference panel. - Huang, Jie; Howie, Bryan; McCarthy, Shane; Memari, Yasin; Walter, Klaudia; Min, Josine L; Danecek, Petr; Malerba, Giovanni; Trabetti, Elisabetta; Zheng, Hou-Feng; Gambaro, Giovanni; Richards, J Brent; et al. (Nat Commun, 2015)
Imputing genotypes from reference panels created by whole-genome sequencing (WGS) provides a cost-effective strategy for augmenting the single-nucleotide polymorphism (SNP) content of genome-wide arrays. The UK10K Cohorts project has generated a data set of 3,781 whole genomes sequenced at low depth (average 7x), aiming to exhaustively characterize genetic variation down to 0.1% minor allele frequency in the British population. Here we demonstrate the value of this resource for improving imputation accuracy at rare and low-frequency variants in both a UK and an Italian population. We show that large increases in imputation accuracy can be achieved by re-phasing WGS reference panels after initial genotype calling. We also present a method for combining WGS panels to improve variant coverage and downstream imputation accuracy, which we illustrate by integrating 7,562 WGS haplotypes from the UK10K project with 2,184 haplotypes from the 1000 Genomes Project. Finally, we introduce a novel approximation that maintains speed without sacrificing imputation accuracy for rare variants.

Interleukin-18 gene promoter polymorphisms and celiac disease in Italian patients. - Zupin, Luisa; Catamo, Eulalia; Polesello, Vania; Crovella, Sergio; Segat, Ludovica (Mol Biol Rep, 2015)
Celiac disease (CD) is the most common food-sensitive enteropathy in genetically susceptible individuals. The major genetic risk factors known are specific human leukocyte antigen (HLA)-DQ haplotypes, but other genetic factors are supposed to be involved. Interleukin-18 (IL-18) is a pro-inflammatory cytokine that has an important role in the immune defense and it has the potential to influence inflammatory disorders. IL-18 is able to promote Th1 cell development and it is expressed in the mucosa of the small intestine in celiac patients. Given the IL-18 biological role, and since a few studies have previously suggested its involvement in CD, in order to investigate the role of IL18 gene in the susceptibility to CD we have performed a case-control study, analyzing two IL18 gene promoter polymorphisms, previously reported to impair the transcriptional activity of the gene, (-137G > C and -607C > A, rs187238 and rs1946518 respectively). A total of 556 CD Italian patients and 582 controls, further stratified for HLA class II (DQ) CD risk haplotypes were enrolled. The -607A > C A allele and A/A genotype, as well as the combination of this allele with the -137G allele in the AG haplotype, were associated with an increased risk towards CD development, in particular in HLA-DQ2.2 patients. Although the association was very moderate, our results indicate the possible involvement of IL18 gene in the susceptibility to CD, and for this reason we do think it should deserve further investigation.

Interleukin-18, interleukin-12B and interferon-γ gene polymorphisms in Brazilian patients with rheumatoid arthritis: a pilot study. - Angelo, H D; Gomes Silva, I I F; Oliveira, R D R; Louzada-Júnior, P; Donadi, E A; Crovella, S; Maia, M M D; de Souza, P R E; Sandrin-Garcia, P (Tissue Antigens, 2015)
Polymorphisms in interleukin (IL)-18, IL-12 and interferon (IFN)-γ genes are associated with different levels of cytokines expression and have been associated with rheumatoid arthritis (RA). IL-18 +105 A/C, IL-12B +1188 A/C and IFN-γ +874 T/A polymorphisms were analyzed by restriction fragment length polymorphism-polymerase chain reaction (PCR) and amplification refractory mutation system PCR from 90 RA patients and 186 healthy individuals. There were significant differences to IL-18 +105 A/C polymorphism between the RA and control groups (odds ratio = 3.77; P < 0.0001). Individual carriers of the variant allele C had a 3.77-fold increased risk of for RA (P = 0.0032). No association was observed for IL-12B and IFN-γ polymorphisms. Our finds suggest a possible role for IL-18 polymorphism in the RA susceptibility in studied population.

Intranasal adminsitration of oxytocin in postnatal depression: implications for psychodynamic psychotherapy from a randomized double-blind pilot study. - Clarici, Andrea; Pellizzoni, Sandra; Guaschino, Secondo; Alberico, Salvatore; Bembich, Stefano; Giuliani, Rosella; Short, Antonia; Guarino, Giuseppina; Panksepp, Jaak (Front Psychol, 2015)
Oxytocin is a neuropeptide that is active in the central nervous system and is generally considered to be involved in prosocial behaviors and feelings. In light of its documented positive effect on maternal behavior, we designed a study to ascertain whether oxytocin exerts any therapeutic effects on depressive symptoms in women affected by maternal postnatal depression. A group of 16 mothers were recruited in a randomized double-blind study: the women agreed to take part in a brief course of psychoanalytic psychotherapy (12 sessions, once a week) while also being administered, during the 12-weeks period, a daily dose of intranasal oxytocin (or a placebo). The pre-treatment evaluation also included a personality assessment of the major primary-process emotional command systems described by Panksepp () and a semi-quantitative assessment by the therapist of the mother's depressive symptoms and of her personality. No significant effect on depressive symptomatology was found following the administration of oxytocin (as compared to a placebo) during the period of psychotherapy. Nevertheless, a personality trait evaluation of the mothers, conducted in our overall sample group, showed a decrease in the narcissistic trait only within the group who took oxytocin. The depressive (dysphoric) trait was in fact significantly affected by psychotherapy (this effect was only present in the placebo group so it may reflect a positive placebo effect enhancing the favorable influence of psychotherapy on depressive symptoms) but not in the presence of oxytocin. Therefore, the neuropeptide would appear to play some role in the modulation of cerebral functions involved in the self-centered (narcissistic) dimension of the suffering that can occur with postnatal depression. Based on these results, there was support for our hypothesis that what is generally defined as postnatal depression may include disturbances of narcissistic affective balance, and oxytocin supplementation can counteract that type of affective disturbance. The resulting improvements in well-being, reflected in better self-centering in post-partuent mothers, may in turn facilitate better interpersonal acceptance of (and interactions with) the child and thereby, improved recognition of the child's needs.

Kinetic Profiles of Inflammatory Mediators in the Conjunctival Sac Fluid of Patients upon Photorefractive Keratectomy. - Tisato, Veronica; Perri, Paolo; Rimondi, Erika; Melloni, Elisabetta; Lamberti, Giuseppe; Milani, Daniela; Secchiero, Paola; Zauli, Giorgio (Mediators Inflamm, 2015)
Photorefractive keratectomy (PRK) represents a therapeutic option to remodel corneal stroma and to compensate refractive errors, which involves inflammatory and/or regenerative processes. In this context, the modulation of cytokines/chemokines in the conjunctival sac fluid and their role in the maintenance of the corneal microenvironment during the healing process upon refractive procedures has not been deeply investigated. In this study, serial samples of conjunctival sac fluid of patients (n = 25) undergoing PRK were harvested before and at different time points after surgery. The levels of 29 cytokines/chemokines/growth factors involved in inflammatory/immune processes were measured with a multiplex array system. The results have firstly highlighted the different pattern of cytokine expression between the microenvironment at the anterior surface of the eye and the systemic circulation. More importantly, the kinetic of modulation of cytokines/chemokines at the conjunctival level following PRK revealed that while the majority of cytokines/chemokines showed a significant decrease, MCP-1 emerged in light of its pronounced and significant increase soon after PRK and during the follow-up. This methodological approach has highlighted the role of MCP-1 in the healing process following PRK and has shown a potential for the identification of expression/modulation of soluble factors for biomarker profiling in ocular surface diseases.

Lactotransferrin gene functional polymorphisms do not influence susceptibility to human immunodeficiency virus-1 mother-to-child transmission in different ethnic groups. - Zupin, Luisa; Polesello, Vania; Coelho, Antônio Victor Campos; Boniotto, Michele; Arraes, Luiz Claudio; Segat, Ludovica; Crovella, Sergio (Mem Inst Oswaldo Cruz, 2015)
Lactotransferrin, also known as lactoferrin, is an iron binding glycoprotein that displays antiviral activity against many different infectious agents, including human immunodeficiency virus (HIV)-1. Lactotransferrin is present in the breast milk and in the female genitourinary mucosa and it has been hypothesised as a possible candidate to prevent mother-to-child HIV-1 transmission. To verify if two functional polymorphisms, Thr29Ala and Arg47Lys, in the lactotransferrin encoding gene (LTF) could affect HIV-1 infection and vertical transmission, a preliminary association study was performed in 238 HIV-1 positive and 99 HIV-1 negative children from Brazil, Italy, Africa and India. No statistically significant association for the Thr29Ala and Arg47Lys LTF polymorphisms and HIV-1 susceptibility in the studied populations was found. Additionally LTF polymorphisms frequencies were compared between the four different ethnic groups.
Keywords: Acquired Immunodeficiency Syndrome; Adolescent; Brazil; Child; Cohort Studies; Ethnic Groups; Female; Gene Frequency; Genetic Predisposition to Disease; Genotyping Techniques; HIV-1; Humans; India; Infant, Newborn; Infectious Disease Transmission, Vertical; Italy; Lactoferrin; Male; Polymorphism, Single Nucleotide; Real-Time Polymerase Chain Reaction; Retrospective Studies; Zimbabwe

Laparoscopic orchiopexy: short term outcomes. Experience of a single centre. - Pederiva, F; Guida, E; Codrich, D; Scarpa, M G; Olenik, D; Schleef, J (Minerva Pediatr, 2015)
BACKGROUND: Increased infertility and smaller volume accompany undescended testis. Timing of orchiopexy is still a matter of debate. We evaluated the growth of nonpalpable testes after laparoscopic orchiopexy according to age at surgery, intraoperative findings and type of procedure. METHODS: Forty-one boys undergoing laparoscopy for nonpalpable testes were retrospectively reviewed and divided into two groups, ≤ 18 months and > 18 months, according to their age at surgery. RESULTS: At follow-up, 14 testes in the younger group had normal size, while 3 atrophied either after single (2) or two stage procedure (1). Similarly, in older boys 11 testes grew normally, while 5 atrophied after both procedures. CONCLUSION: Most of the nonpalpable testes grew normally after laparoscopic orchiopexy and the postoperative volume seemed independent from the surgical strategy. Both techniques led to a few cases of testicular hypotrophy In our experience, the age at surgery did not affect the outcome in terms of testicular growth.

Large-scale genomic analyses link reproductive aging to hypothalamic signaling, breast cancer susceptibility and BRCA1-mediated DNA repair. - Day, Felix R; Ruth, Katherine S; Thompson, Deborah J; Lunetta, Kathryn L; Pervjakova, Natalia; Chasman, Daniel I; Stolk, Lisette; Finucane, Hilary K; Sulem, Patrick; Bulik-Sullivan, Brendan; Esko, Tõnu; Johnson, Andrew D; et al. (Nat Genet, 2015)
Menopause timing has a substantial impact on infertility and risk of disease, including breast cancer, but the underlying mechanisms are poorly understood. We report a dual strategy in ∼70,000 women to identify common and low-frequency protein-coding variation associated with age at natural menopause (ANM). We identified 44 regions with common variants, including two regions harboring additional rare missense alleles of large effect. We found enrichment of signals in or near genes involved in delayed puberty, highlighting the first molecular links between the onset and end of reproductive lifespan. Pathway analyses identified major association with DNA damage response (DDR) genes, including the first common coding variant in BRCA1 associated with any complex trait. Mendelian randomization analyses supported a causal effect of later ANM on breast cancer risk (∼6% increase in risk per year; P = 3 × 10(-14)), likely mediated by prolonged sex hormone exposure rather than DDR mechanisms.

Leptin/adiponectin ratio predicts poststroke neurological outcome. - Carbone, Federico; Burger, Fabienne; Roversi, Gloria; Tamborino, Carmine; Casetta, Ilaria; Seraceni, Silva; Trentini, Alessandro; Padroni, Marina; Bertolotto, Maria; Dallegri, Franco; Mach, François; Fainardi, Enrico; et al. (Eur J Clin Invest, 2015)
BACKGROUND AND AIMS: Different adipokines have been associated with atherosclerotic plaque rupture and cardiovascular events, such as acute ischaemic stroke (AIS). However, the potential role of these molecules in postischaemic brain injury remains largely unknown. METHODS AND METHODS: We performed a substudy analysis on nonobese patients with first atherothrombotic stroke (n = 35) from a recently published prospective cohort. Primary endpoint was to investigate the predictive value of serum leptin/adiponectin ratio on neurological recovery at 90 days after AIS. The secondary endpoint was the predictive value of serum adipokine levels of clinical and radiological outcomes at a shorter follow-up (at days 1 and 7 after AIS). The radiological evaluation included ischaemic lesion volume and haemorrhagic transformation (HT). The clinical examination was based on National Institutes of Health Stroke Scale (NIHSS) and modified Rankin Scale (mRS). RESULTS: At day 1 after AIS, serum leptin and leptin/adiponectin ratio were increased and inversely correlated with both radiological and clinical parameters at all follow-up time points. Once identified the best cut-off points by receiver operating characteristic (ROC) analysis, risk analysis showed that higher circulating leptin improved neurological recovery at day 90. In addition, leptin/adiponectin ratio maintained statistical significance after adjustment for age, gender and thrombolysis, also predicting the occurrence of HT in the first 7 days after AIS (adjusted OR 0·15 [95% CI 0·03-0·83); P = 0·030]). CONCLUSIONS: Higher leptin/adiponectin ratio at day 1 predicted better neurological outcomes in patients with atherothrombotic AIS and might be potentially useful as a prognostic biomarker of the disease.

Making the first days of life safer: preventing sudden unexpected postnatal collapse while promoting breastfeeding. - Davanzo, Riccardo; De Cunto, Angela; Paviotti, Giulia; Travan, Laura; Inglese, Stefania; Brovedani, Pierpaolo; Crocetta, Anna; Calligaris, Chiara; Corubolo, Elisa; Dussich, Valentina; Verardi, Giuseppa; Causin, Enrica; et al. (J Hum Lact, 2015)
Early and prolonged skin-to-skin contact (SSC) after birth between a mother and her newborn has been shown to generate beneficial effects on the mother-infant relationship and breastfeeding. Close mother-infant body contact immediately after birth positively enhances exclusive breastfeeding during the hospital stay, with a dose-response relationship. Skin-to-skin contact may ease the infant's transition to extra-uterine life and helps regulate the infant's body temperature and nursing behavior. However, reports of sudden unexpected postnatal collapse (SUPC) soon after birth, in healthy term neonates, in association with SSC, have raised concerns about the safety of this practice. Based on available evidence, we developed a surveillance protocol in the delivery room and postnatal ward of the Institute for Maternal and Child Health of Trieste (Italy). The aim of our protocol is (a) to promote safe mother and infant bonding and (b) to establish successful breastfeeding, without increasing the risk of SUPC. As there is no known effective intervention to prevent SUPC, our protocol has been conceived as a potential best practice.

Mature and immature teratoma: A report from the second Italian pediatric study. - Terenziani, Monica; D'Angelo, Paolo; Inserra, Alessandro; Boldrini, Renata; Bisogno, Gianni; Babbo, Gian Luca; Conte, Massimo; Dall' Igna, Patrizia; De Pasquale, Maria Debora; Indolfi, Paolo; Piva, Luigi; Riccipetitoni, Giovanna; et al. (Pediatr Blood Cancer, 2015)
BACKGROUND: Teratomas demonstrate a benign clinical behavior, however they may recur with malignant components or as teratoma, and in a small group of patients prognosis could be fatal. After the first Italian study, we collected cases of teratoma, alongside the protocol for malignant germ cell tumors. PROCEDURE: Patients with teratoma were collected from 2004 to 2014. Teratomas were classified according to the WHO classifications, as mature and immature. Patients with pathological aFP and/or bHCG, and those with a malignant germ cell component were not included. RESULTS: The study enrolled 219 patients (150 mature, 69 immature teratomas) with a median age at diagnosis of 42 months. The primary sites involved were: 118 gonadal and 101 extragonadal teratomas. Two females with ovarian teratoma had a positive family history. Complete and incomplete surgeries were performed in 85% and 9% of cases. Seventeen events occurred: six females had a second metachronous tumor (5 contralateral ovarian teratoma, 1 adrenal neuroblastoma) and 11 teratomas relapsed/progressed (3 mature, 8 immature teratomas). Two patients died, one of progressive immature teratoma and one of surgical complications. At a median follow up of 68 months, the event-free, relapse-free, and overall survival rates were 90.6%, 94.3%, 98.6%, respectively. CONCLUSIONS: Teratomas show a good prognosis, especially the mature ones: surgery and follow-up remain the standard approach. Incomplete surgery in immature teratoma is the group at greatest risk of relapse. Bilateral ovarian tumors are a possibility, and the rare family predisposition to ovarian mature teratoma warrants further analyses.
Keywords: Adolescent; Adult; Child; Child, Preschool; Female; Follow-Up Studies; Humans; Incidence; Infant; Infant, Newborn; Italy; Male; Neoplasm Grading; Neoplasm Recurrence, Local; Neoplasm Staging; Neoplasms, Second Primary; Neuroblastoma; Ovarian Neoplasms; Prognosis; Prospective Studies; Survival Rate; Teratoma; Testicular Neoplasms; Young Adult

MBL2 polymorphisms in women with atypical squamous cells of undetermined significance. - Zupin, Luisa; Polesello, Vania; Casalicchio, Giorgia; Freato, Nadia; Maestri, Iva; Comar, Manola; Crovella, Sergio; Segat, Ludovica (J Med Virol, 2015)
Infection with high risk Human papillomavirus (HPV) is the main known cause of cervical cancer. HPV induces different grades of lesions: among them, Atypical squamous cells of undetermined significance are abnormal lesions that could evolve in pre-cancer lesions or spontaneously regress. The mannose binding lectin (MBL) is an innate immunity serum protein also found in cervico-vaginal mucosa, whose expression is known to be affected by polymorphisms in exon 1 and promoter of the MBL2 gene. In the present study the possible association between MBL2 functional polymorphisms and susceptibility to develop atypical squamous cells of undetermined significance was investigated in a group of women from North-East of Italy, stratified for HPV infection status. The MBL2 D and O alleles and the deficient producer combined genotypes, responsible for low MBL production, were more represented among atypical squamous cells of undetermined significance positive women than healthy controls and the results were confirmed when only HPV negative samples were considered. These results suggest a possible involvement of MBL2 functional polymorphisms in atypical squamous cells of undetermined significance susceptibility.
Keywords: Adolescent; Adult; Atypical Squamous Cells of the Cervix; Female; Gene Frequency; Genetic Predisposition to Disease; Humans; Italy; Mannose-Binding Lectin; Polymorphism, Single Nucleotide; Young Adult

Metal accumulation in the renal cortex of a pediatric patient with sickle cell disease: a case report and review of the literature. - Maximova, Natalia; Zanon, Davide; Pascolo, Lorella; Zennaro, Floriana; Gregori, Massimo; Grosso, Daniele; Sonzogni, Aurelio (J Pediatr Hematol Oncol, 2015)
BACKGROUND: Sickle cell disease (SCD) is a well-known multisystem illness characterized by vascular injury due to vasoocclusion and hemolysis, as well as infectious complications and iron overload, all of which contribute to high morbidity and mortality rates among children. In these patients, some authors have previously described iron cortical deposition in the kidney. We here report the first case in the literature of a girl affected by SCD showing an anomalous metal and rare element retention in the renal cortex. CASE PRESENTATION: A 10-year-old white girl affected by SCD underwent a routine magnetic resonance imaging investigation that evidenced a reduced signal intensity in the renal cortex, compatible with hemosiderin precipitation. Histologic and elemental analyses of the hepatic and the renal biotic samples, performed with inductively coupled plasma mass spectrometry, revealed that concomitant with the high iron deposition, toxic and potentially carcinogenic elements such as nickel, magnesium, rubidium, and gadolinuim were anomalously retained particularly in the kidney. CONCLUSIONS: The finding of rare and toxic elements in the kidney of SCD patients might be linked to the development of specific neoplastic transformations already described in this patient cohort. To be confirmed, our speculations need to be demonstrated in large sampling of patients.
Keywords: Anemia, Sickle Cell; Child; Female; Humans; Kidney Cortex; Metals; Spectrophotometry, Atomic

Modulation of genetic associations with serum urate levels by body-mass-index in humans. - Huffman, Jennifer E; Albrecht, Eva; Teumer, Alexander; Mangino, Massimo; Kapur, Karen; Johnson, Toby; Kutalik, Zoltán; Pirastu, Nicola; Pistis, Giorgio; Lopez, Lorna M; Haller, Toomas; Salo, Perttu; et al. (PLoS One, 2015)
We tested for interactions between body mass index (BMI) and common genetic variants affecting serum urate levels, genome-wide, in up to 42569 participants. Both stratified genome-wide association (GWAS) analyses, in lean, overweight and obese individuals, and regression-type analyses in a non BMI-stratified overall sample were performed. The former did not uncover any novel locus with a major main effect, but supported modulation of effects for some known and potentially new urate loci. The latter highlighted a SNP at RBFOX3 reaching genome-wide significant level (effect size 0.014, 95% CI 0.008-0.02, Pinter= 2.6 x 10-8). Two top loci in interaction term analyses, RBFOX3 and ERO1LB-EDARADD, also displayed suggestive differences in main effect size between the lean and obese strata. All top ranking loci for urate effect differences between BMI categories were novel and most had small magnitude but opposite direction effects between strata. They include the locus RBMS1-TANK (men, Pdifflean-overweight= 4.7 x 10-8), a region that has been associated with several obesity related traits, and TSPYL5 (men, Pdifflean-overweight= 9.1 x 10-8), regulating adipocytes-produced estradiol. The top-ranking known urate loci was ABCG2, the strongest known gout risk locus, with an effect halved in obese compared to lean men (Pdifflean-obese= 2 x 10-4). Finally, pathway analysis suggested a role for N-glycan biosynthesis as a prominent urate-associated pathway in the lean stratum. These results illustrate a potentially powerful way to monitor changes occurring in obesogenic environment.

Molecular basis of inherited thrombocytopenias. - Savoia, A (Clin Genet, 2015)
Inherited thrombocytopenias (IT) are a heterogeneous group of diseases caused by at least 20 different genes. At present, these genes account for approximately 50% of cases, suggesting that novel genes have yet to be identified for a comprehensive understanding of platelet biogenesis defects. This review provides an update of ITs focusing on the molecular basis and potential pathogenic mechanisms affecting megakaryopoiesis and platelet production.

More than (Double) Bubble. - Ferrara, Giovanna; Stampalija, Tamara; Codrich, Daniela; Simionato, Cristina; Taddio, Andrea; Travan, Laura (J Pediatr, 2015)
Keywords: Amniotic Fluid; Duodenum; Female; Humans; Infant; Infant, Newborn; Polyhydramnios; Pregnancy; Pregnancy Trimester, Third; Prenatal Diagnosis; Ultrasonography, Prenatal

Multicohort analysis of the maternal age effect on recombination. - Martin, Hilary C; Christ, Ryan; Hussin, Julie G; O'Connell, Jared; Gordon, Scott; Mbarek, Hamdi; Hottenga, Jouke-Jan; McAloney, Kerrie; Willemsen, Gonnecke; Gasparini, Paolo; Pirastu, Nicola; Montgomery, Grant W; et al. (Nat Commun, 2015)
Several studies have reported that the number of crossovers increases with maternal age in humans, but others have found the opposite. Resolving the true effect has implications for understanding the maternal age effect on aneuploidies. Here, we revisit this question in the largest sample to date using single nucleotide polymorphism (SNP)-chip data, comprising over 6,000 meioses from nine cohorts. We develop and fit a hierarchical model to allow for differences between cohorts and between mothers. We estimate that over 10 years, the expected number of maternal crossovers increases by 2.1% (95% credible interval (0.98%, 3.3%)). Our results are not consistent with the larger positive and negative effects previously reported in smaller cohorts. We see heterogeneity between cohorts that is likely due to chance effects in smaller samples, or possibly to confounders, emphasizing that care should be taken when interpreting results from any specific cohort about the effect of maternal age on recombination.

MultiMeta: an R package for meta-analyzing multi-phenotype genome-wide association studies. - Vuckovic, D; Gasparini, P; Soranzo, N; Iotchkova, V (Bioinformatics, 2015)
UNLABELLED: As new methods for multivariate analysis of genome wide association studies become available, it is important to be able to combine results from different cohorts in a meta-analysis. The R package MultiMeta provides an implementation of the inverse-variance-based method for meta-analysis, generalized to an n-dimensional setting. AVAILABILITY AND IMPLEMENTATION: The R package MultiMeta can be downloaded from CRAN. CONTACT: dragana.vuckovic@burlo.trieste.it; vi1@sanger.ac.uk SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.

Music Training Increases Phonological Awareness and Reading Skills in Developmental Dyslexia: A Randomized Control Trial. - Flaugnacco, Elena; Lopez, Luisa; Terribili, Chiara; Montico, Marcella; Zoia, Stefania; Schön, Daniele (PLoS One, 2015)
There is some evidence for a role of music training in boosting phonological awareness, word segmentation, working memory, as well as reading abilities in children with typical development. Poor performance in tasks requiring temporal processing, rhythm perception and sensorimotor synchronization seems to be a crucial factor underlying dyslexia in children. Interestingly, children with dyslexia show deficits in temporal processing, both in language and in music. Within this framework, we test the hypothesis that music training, by improving temporal processing and rhythm abilities, improves phonological awareness and reading skills in children with dyslexia. The study is a prospective, multicenter, open randomized controlled trial, consisting of test, rehabilitation and re-test (ID NCT02316873). After rehabilitation, the music group (N = 24) performed better than the control group (N = 22) in tasks assessing rhythmic abilities, phonological awareness and reading skills. This is the first randomized control trial testing the effect of music training in enhancing phonological and reading abilities in children with dyslexia. The findings show that music training can modify reading and phonological abilities even when these skills are severely impaired. Through the enhancement of temporal processing and rhythmic skills, music might become an important tool in both remediation and early intervention programs.Trial Registration: ClinicalTrials.gov NCT02316873

Nasal irrigation with saline solution significantly improves oxygen saturation in infants with bronchiolitis. - Schreiber, Silvana; Ronfani, Luca; Ghirardo, Sergio; Minen, Federico; Taddio, Andrea; Jaber, Mohamad; Rizzello, Elisa; Barbi, Egidio (Acta Paediatr, 2015)
AIM: Published guidelines do not recommend nasal irrigation in bronchiolitis, but it is common practice in Italy, despite a lack of data on its benefits or adverse effects. This single-blind, multicentre, randomised controlled trial compared nasal irrigation using either isotonic 0.9% sodium chloride or hypertonic 3% sodium chloride with simple supportive care in infants with bronchiolitis. METHOD: We randomly assigned 133 Infants up one year of age, who were admitted to the emergency department with bronchiolitis and an oxygen saturation (SpO2) of between 88-94%, to the isotonic (n=47), hypertonic (n=44) or standard care (n=42) groups. Variations in SpO2 and the wheeze, air exchange, respiratory rate, muscle use (WARM) respiratory distress score were recorded at zero, five, 15, 20 and 50 minutes. RESULTS: Five minutes after the intervention, the median SpO2 value (95%) in the isotonic group was higher than both the hypertonic (94%) and the standard care (93%) groups. The differences between the isotonic and standard treatment groups were statistically significant at each time point, while the hypertonic group only reached significantly higher values after 50 minutes. However, the WARM score did not improve. CONCLUSION: A single nasal irrigation with saline solution significantly improved oxygen saturation in infants with bronchiolitis. This article is protected by copyright. All rights reserved.

A nationwide survey of PMM2-CDG in Italy: high frequency of a mild neurological variant associated with the L32R mutation. - Barone, Rita; Carrozzi, M; Parini, R; Battini, R; Martinelli, D; Elia, M; Spada, M; Lilliu, F; Ciana, G; Burlina, A; Leuzzi, V; Leoni, M; et al. (J Neurol, 2015)
PMM2-CDG (PMM2 gene mutations) is the most common congenital disorder of N-glycosylation. We conducted a nationwide survey to characterize the frequency, clinical features, glycosylation and genetic correlates in Italian patients with PMM2-CDG. Clinical information was obtained through a questionnaire filled in by the referral physicians including demographics, neurological and systemic features, neuroimaging data and genotype. Glycosylation analyses of serum transferrin were complemented by MALDI-Mass Spectrometry (MALDI-MS). Between 1996 and 2012, data on 37 Italian patients with PMM2-CDG were collected. All the patients with a severe phenotype were unable to walk unaided, 84 % had severe intellectual disability and 81 % microcephaly. Conversely, among 17 mildly affected patients 82 % had independent ambulation, 64 % had borderline to mild intellectual disability and 35 % microcephaly. Epilepsy and stroke-like events did not occur among patients with the mild phenotype. The rate and extent of systemic involvement were more pronounced in severely affected patients. The L32R misfolding mutation of the PMM2 gene occurred in 70 % of the patients with the mild phenotype and was associated with a less severe underglycosylation of serum Tf at MALDI-MS analyses. Despite their different disease severity, all patients had progressive (olivo)ponto-cerebellar atrophy that was the hallmark clinical feature for the diagnosis. A mild neurological phenotype of PMM2-CDG marked by preserved ambulatory ability and autonomy and associated with L32R mutation is particularly frequent in Italy. PMM2-CDG should be considered in patients with even mild developmental disability and/or unexplained progressive cerebellar atrophy.

New genetic loci link adipose and insulin biology to body fat distribution. - Shungin, Dmitry; Winkler, Thomas W; Croteau-Chonka, Damien C; Ferreira, Teresa; Locke, Adam E; Mägi, Reedik; Strawbridge, Rona J; Pers, Tune H; Fischer, Krista; Justice, Anne E; Workalemahu, Tsegaselassie; Wu, Joseph M W; et al. (Nature, 2015)
Body fat distribution is a heritable trait and a well-established predictor of adverse metabolic outcomes, independent of overall adiposity. To increase our understanding of the genetic basis of body fat distribution and its molecular links to cardiometabolic traits, here we conduct genome-wide association meta-analyses of traits related to waist and hip circumferences in up to 224,459 individuals. We identify 49 loci (33 new) associated with waist-to-hip ratio adjusted for body mass index (BMI), and an additional 19 loci newly associated with related waist and hip circumference measures (P < 5 × 10(-8)). In total, 20 of the 49 waist-to-hip ratio adjusted for BMI loci show significant sexual dimorphism, 19 of which display a stronger effect in women. The identified loci were enriched for genes expressed in adipose tissue and for putative regulatory elements in adipocytes. Pathway analyses implicated adipogenesis, angiogenesis, transcriptional regulation and insulin resistance as processes affecting fat distribution, providing insight into potential pathophysiological mechanisms.
Keywords: Adipocytes; Adipogenesis; Adipose Tissue; Age Factors; Body Fat Distribution; Body Mass Index; Continental Population Groups; Epigenesis, Genetic; Europe; Female; Genome, Human; Genome-Wide Association Study; Humans; Insulin; Insulin Resistance; Male; Models, Biological; Neovascularization, Physiologic; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Sex Characteristics; Transcription, Genetic; Waist-Hip Ratio

New lenses to look at preeclampsia. - Zullino, Sara; Di Martino, Daniela; Stampalija, Tamara; Ferrazzi, Enrico (Gynecol Endocrinol, 2015)

Normal saline flushes performed once daily maintain peripheral intravenous catheter patency: a randomised controlled trial. - Schreiber, Silvana; Zanchi, Chiara; Ronfani, Luca; Delise, Anna; Corbelli, Alessandra; Bortoluzzi, Rosamaria; Taddio, Andrea; Barbi, Egidio (Arch Dis Child, 2015)
OBJECTIVE: Recent evidence supports the use of normal saline flushes in place of heparin to maintain the patency of peripheral intravenous locks (IVLs); however, there are no data regarding the recommended flush frequency. STUDY DESIGN: This was an open, non-inferiority, randomised controlled trial. Children with IVLs, aged 1-17 years, were randomly assigned to receive saline flushing every 12 h (group A) or every 24 h (group B). The main outcome was the maintenance of catheter patency. RESULTS: Four hundred patients were randomised; 198 subjects were analysed in the 12 h group and 199 in the 24 h group (three patients were lost at follow-up). Occlusion occurred in 15 children (7.6%) in group A versus 9 (4.5%) in group B (p=0.21). The difference in catheter patency was +3.1% in favour of the 24 h group (95% CI -1.6% to 7.7%), showing the non-inferiority of the 24 h procedure (the non-inferiority margin was set at -4%). Catheter-related complications were not different between the two groups (12.1% in group A vs 9.5% in group B; p=0.42). CONCLUSIONS: A flushing procedure with one flush per day allows maintenance of catheter patency without an increase in catheter-related complications. We propose a simplification of the flushing procedure with only one flush per day, thereby reducing costs (materials use and nursing time), labour and unnecessary manipulation of the catheters which can cause distress in younger children and their parents. TRIAL REGISTRATION NUMBER: The study is registered in the international database ClinicalTrial.gov under registration number NCT02221024.
Keywords: Adolescent; Catheterization, Peripheral; Catheters, Indwelling; Child; Child, Preschool; Equipment Failure; Female; Humans; Infant; Male; Outcome Assessment (Health Care); Risk Assessment; Sodium Chloride; Therapeutic Irrigation

The novel dual PI3K/mTOR inhibitor NVP-BGT226 displays cytotoxic activity in both normoxic and hypoxic hepatocarcinoma cells. - Simioni, Carolina; Cani, Alice; Martelli, Alberto M; Zauli, Giorgio; Alameen, Ayman A M; Ultimo, Simona; Tabellini, Giovanna; McCubrey, James A; Capitani, Silvano; Neri, Luca M (Oncotarget, 2015)
Hepatocellular carcinoma (HCC) is one of the most common lethal human malignancies worldwide and its advanced status is frequently resistant to conventional chemotherapeutic agents and radiation. We evaluated the cytotoxic effect of the orally bioavailable dual PI3K/mTOR inhibitor, NVP-BGT226, on a panel of HCC cell lines, since hyperactivated PI3K/Akt/mTOR signaling pathway could represent a biomolecular target for Small Inhibitor Molecules in this neoplasia. We analyzed the drug activity in both normoxia and hypoxia conditions, the latter playing often a relevant role in the induction of chemoresistance and angiogenesis.In normoxia NVP-BGT226 caused cell cycle arrest in the G0/G1 phase of the cell cycle, induced apoptosis and autophagy at low concentrations. Interestingly the drug inactivated p-Akt and p-S6 at < 10 nM concentration.In hypoxia NVP-BGT226 maintained its cytotoxic efficacy at the same concentration as documented by MTT assays and Western blot analysis. Moreover, the drug showed in hypoxia inhibitory properties against angiogenesis by lowering the expression of the transcription factor HIF-1α and of VEGF.Our results indicate that NVP-BGT226 has a potent cytotoxic effect on HCC cell lines also in hypoxia condition, thus emerging as a potential candidate for cancer treatment in HCC targeted therapy.

Patients' Induced Pluripotent Stem Cells to Model Drug Induced Adverse Events: A Role in Predicting Thiopurine Induced Pancreatitis? - Stocco, Gabriele; Lanzi, Gaetana; Yue, Fengming; Giliani, Silvia; Sasaki, Katsunori; Tommasini, Alberto; Pelin, Marco; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana (Curr Drug Metab, 2015)
Induced pluripotent stem cells (iPSC) can be produced from adult cells by transfecting them with a definite set of pluripotency-associated genes. Under adequate growth conditions and stimulation iPSC can differentiate to almost every somatic lineage in the body. Patients' derived iPSC are an innovative model to study mechanisms of adverse drug reactions in individual patients and in cell types that cannot be easily obtained from human subjects. Proof-of concept studies with known toxicants have been performed for liver, cardiovascular and central nervous system cells: neurons obtained from iPSC have been used to elucidate the mechanism of chemotherapy-induced peripheral neuropathy by evaluating the effects of neurotoxic drugs such as vincristine. However, no study has been performed yet on pancreatic tissue and drug induced pancreatitis. Thiopurines (azathioprine and mercaptopurine) are immunosuppressive antimetabolite drugs, commonly used to treat Crohn's disease. About 5% of Crohn's disease patients treated with thiopurines develop pancreatitis, a severe idiosyncratic adverse event; these patients have to stop thiopurine administration and may require medical treatment, with significant personal and social costs. Molecular mechanism of thiopurine induced pancreatitis (TIP) is currently unknown and no fully validated biomarker is available to assist clinicians in preventing this adverse event. Hence, in this review we have reflected upon the probable research applications of exocrine pancreatic cells generated from patient specific iPS cells. Such pancreatic cells can provide excellent insights into the molecular mechanism of TIP. In particular three hypotheses on the mechanism of TIP could be explored: drug biotransformation, innate immunity and adaptative immunity.

Persistent viremia and urine shedding of tick-borne encephalitis virus in an infected immunosuppressed patient from a new epidemic cluster in North-Eastern Italy. - Caracciolo, Ilaria; Bassetti, Matteo; Paladini, Giorgio; Luzzati, Roberto; Santon, Daniela; Merelli, Maria; Sabbata, Giovanni De; Carletti, Tea; Marcello, Alessandro; D'Agaro, Pierlanfranco (J Clin Virol, 2015)
A persistent tick-borne encephalitis virus infection in an immune-suppressed patient is presented. Such an unusual clinical case offers the unique chance of detecting persistent viremia associated to the erythrocyte fraction and shedding of the virus in the urine for more than six weeks. The infection occurred in a new area of the Friuli Venezia-Giulia region (North Eastern Italy) where two additional cases are also being reported.

Polyclonal gammopathy after BKV infection in HSCT recipient: a novel trigger for plasma cells replication? - Maximova, Natalia; Pizzol, Antonio; Sonzogni, Aurelio; Gregori, Massimo; Granzotto, Marilena; Tamaro, Paolo (Virol J, 2015)
BACKGROUND: BK polyomavirus infects most of the general population. However, its clinical manifestations are almost exclusively seen in immunocompromised patients, particularly in kidney and hematopoietic stem cell transplantation recipients. CASE PRESENTATION: A 15-y-old female suffering from common B-cell acute lymphoblastic leukaemia underwent hematopoietic stem cell transplantation. The patient had reactivation of BKPyV infection and developed an haemorrhagic cystitis. Three months after transplant, BKPyV viremia and viruria increased and she developed a severe nephropathy associated to a polyclonal gammopathy with high levels of isolated IgM. CONCLUSION: This case report describes a rare and unexpected polyclonal gammopathy developed during a polyomavirus-associated nephropathy confirmed by immunohistochemical and laboratory analyses.

Polymorphisms in sweet taste genes (TAS1R2 and GLUT2), sweet liking, and dental caries prevalence in an adult Italian population. - Robino, Antonietta; Bevilacqua, Lorenzo; Pirastu, Nicola; Situlin, Roberta; Di Lenarda, Roberto; Gasparini, Paolo; Navarra, Chiara Ottavia (Genes Nutr, 2015)
The aim of the study was to assess the relationship between sweet taste genes and dental caries prevalence in a large sample of adults. In addition, the association between sweet liking and sugar intake with dental caries was investigated. Caries was measured by the decayed, missing, filled teeth (DMFT) index in 647 Caucasian subjects (285 males and 362 females, aged 18-65 years), coming from six villages in northeastern Italy. Sweet liking was assessed using a 9-point scale, and the mean of the liking given by each individual to specific sweet food and beverages was used to create a sweet liking score. Simple sugar consumption was estimated by a dietary history interview, considering both added sugars and sugar present naturally in foods. Our study confirmed that polymorphisms in TAS1R2 and GLUT2 genes are related to DMFT index. In particular, GG homozygous individuals for rs3935570 in TAS1R2 gene (p value = 0.0117) and GG homozygous individuals for rs1499821 in GLUT2 gene (p value = 0.0273) showed higher DMFT levels compared to both heterozygous and homozygous for the alternative allele. Furthermore, while the relationship sugar intake-DMFT did not achieve statistical significance (p value = 0.075), a significant association was identified between sweet liking and DMFT (p value = 0.004), independent of other variables. Our study showed that sweet taste genetic factors contribute to caries prevalence and highlighted the role of sweet liking as a predictor of caries risk. Therefore, these results may open new perspectives for individual risk identification and implementation of target preventive strategies, such as identifying high-risk patients before caries development.

Population genetic differentiation of height and body mass index across Europe. - Robinson, Matthew R; Hemani, Gibran; Medina-Gomez, Carolina; Mezzavilla, Massimo; Esko, Tõnu; Shakhbazov, Konstantin; Powell, Joseph E; Vinkhuyzen, Anna; Berndt, Sonja I; Gustafsson, Stefan; Justice, Anne E; Kahali, Bratati; et al. (Nat Genet, 2015)
Across-nation differences in the mean values for complex traits are common, but the reasons for these differences are unknown. Here we find that many independent loci contribute to population genetic differences in height and body mass index (BMI) in 9,416 individuals across 14 European countries. Using discovery data on over 250,000 individuals and unbiased effect size estimates from 17,500 sibling pairs, we estimate that 24% (95% credible interval (CI) = 9%, 41%) and 8% (95% CI = 4%, 16%) of the captured additive genetic variance for height and BMI, respectively, reflect population genetic differences. Population genetic divergence differed significantly from that in a null model (height, P < 3.94 × 10(-8); BMI, P < 5.95 × 10(-4)), and we find an among-population genetic correlation for tall and slender individuals (r = -0.80, 95% CI = -0.95, -0.60), consistent with correlated selection for both phenotypes. Observed differences in height among populations reflected the predicted genetic means (r = 0.51; P < 0.001), but environmental differences across Europe masked genetic differentiation for BMI (P < 0.58).

Positron emission tomography-laparoscopy based method in the prediction of complete cytoreduction in platinum-sensitive recurrent ovarian cancer. - Fanfani, Francesco; Monterossi, Giorgia; Fagotti, Anna; Gallotta, Valerio; Costantini, Barbara; Vizzielli, Giuseppe; Petrillo, Marco; Carbone, Maria Vittoria; Scambia, Giovanni (Ann Surg Oncol, 2015)
BACKGROUND: This study was designed to evaluate the positron emission tomography-laparoscopy-based method in the prediction of complete/optimal cytoreduction in platinum sensitive recurrent epithelial ovarian cancer patients. METHODS: We analysed 223 consecutive recurrent epithelial ovarian cancer patients. Inclusion criteria were absence of extra-abdominal disease and Eastern Cooperative Oncology Group Performance Status ≤2. Complete and optimal secondary cytoreduction are defined as macroscopic absence or less than 1 cm of residual tumor at the end of surgery. RESULTS: Laparoscopy was feasible in 210 of 223 patients (94.2 %). Laparoscopy stated 127 (60.5 %) possible cytoreductions and 83 (39.5 %) systemic chemotherapies. In the same population, AGO score evaluation avowed 150 possible cytoreduction (71.5 %) and 60 unresectable women (28.5 %). Overall, 115 of 210 patients (54.7 %) underwent successful secondary cytoreduction: complete and optimal cytoreduction was obtained in 103 (89.5 %) and 12 (10.5 %) patients, respectively. Laparoscopy obtained a positive predictive value of 91.3 %. Laparoscopy recovered to secondary cytoreduction 13 of 60 patients (21.7 %) deemed as not resectable according to AGO score. Forty-eight of 150 AGO score positive patients (32 %) were judged nonresectable by laparoscopy. CONCLUSIONS: This study confirmed that laparoscopy could be effective for the selection of platinum-sensitive recurrent epithelial ovarian cancer patients suitable for complete cytoreduction.
Keywords: Adult; Aged; Algorithms; Cytoreduction Surgical Procedures; Female; Humans; Laparoscopy; Middle Aged; Neoplasm Recurrence, Local; Neoplasm Staging; Neoplasms, Glandular and Epithelial; Ovarian Neoplasms; Positron-Emission Tomography; Tomography, X-Ray Computed

PSIP1/LEDGF: a new gene likely involved in sensorineural progressive hearing loss. - Girotto, Giorgia; Scheffer, Deborah I; Morgan, Anna; Vozzi, Diego; Rubinato, Elisa; Di Stazio, Mariateresa; Muzzi, Enrico; Pensiero, Stefano; Giersch, Anne B; Corey, David P; Gasparini, Paolo (Sci Rep, 2015)
Hereditary Hearing Loss (HHL) is an extremely heterogeneous disorder. Approximately 30 out of 80 known HHL genes are associated with autosomal dominant forms. Here, we identified PSIP1/LEDGF (isoform p75) as a novel strong candidate gene involved in dominant HHL. Using exome sequencing we found a frameshift deletion (c.1554_1555del leading to p.E518Dfs*2) in an Italian pedigree affected by sensorineural mild-to-moderate HHL but also showing a variable eye phenotype (i.e. uveitis, optic neuropathy). This deletion led to a premature stop codon (p.T519X) with truncation of the last 12 amino acids. PSIP1 was recently described as a transcriptional co-activator regulated by miR-135b in vestibular hair cells of the mouse inner ear as well as a possible protector against photoreceptor degeneration. Here, we demonstrate that it is ubiquitously expressed in the mouse inner ear. The PSIP1 mutation is associated with a peculiar audiometric slope toward the high frequencies. These findings indicate that PSIP1 likely plays an important role in HHL.

R705H mutation of MYH9 is associated with MYH9-related disease and not only with non-syndromic deafness DFNA17. - Verver, E; Pecci, A; De Rocco, D; Ryhänen, S; Barozzi, S; Kunst, H; Topsakal, V; Savoia, A (Clin Genet, 2015)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant disease caused by mutation of MYH9, the gene encoding for the heavy chain of non-muscle myosin IIA (NMMHC-IIA). MYH9-RD patients have macrothrombocytopenia and granulocyte inclusions (pathognomonic sign of the disease) containing wild-type and mutant NMMHC-IIA. During life they might develop sensorineural hearing loss, cataract, glomerulonephritis, and elevation of liver enzymes. One of the MYH9 mutations, p.R705H, was previously reported to be associated with DFNA17, an autosomal dominant non-syndromic sensorineural hearing loss without any other features associated. We identified the same mutation in two unrelated families, whose four affected individuals had not only hearing impairment but also thrombocytopenia, giant platelets, leukocyte inclusions, as well as mild to moderate elevation of some liver enzymes. Our data suggest that DFNA17 should not be a separate genetic entity but part of the wide phenotypic spectrum of MYH9-RD characterized by congenital hematological manifestations and variable penetrance and expressivity of the extra-hematological features.

A rapid screening of ancestry for genetic association studies in an admixed population from Pernambuco, Brazil. - Coelho, A V C; Moura, R R; Cavalcanti, C A J; Guimarães, R L; Sandrin-Garcia, P; Crovella, S; Brandão, L A C (Genet Mol Res, 2015)
Genetic association studies determine how genes influence traits. However, non-detected population substructure may bias the analysis, resulting in spurious results. One method to detect substructure is to genotype ancestry informative markers (AIMs) besides the candidate variants, quantifying how much ancestral populations contribute to the samples' genetic background. The present study aimed to use a minimum quantity of markers, while retaining full potential to estimate ancestries. We tested the feasibility of a subset of the 12 most informative markers from a previously established study to estimate influence from three ancestral populations: European, African and Amerindian. The results showed that in a sample with a diverse ethnicity (N = 822) derived from 1000 Genomes database, the 12 AIMs had the same capacity to estimate ancestries when compared to the original set of 128 AIMs, since estimates from the two panels were closely correlated. Thus, these 12 SNPs were used to estimate ancestry in a new sample (N = 192) from an admixed population in Recife, Northeast Brazil. The ancestry estimates from Recife subjects were in accordance with previous studies, showing that Northeastern Brazilian populations show great influence from European ancestry (59.7%), followed by African (23.0%) and Amerindian (17.3%) ancestries. Ethnicity self-classification according to skin-color was confirmed to be a poor indicator of population substructure in Brazilians, since ancestry estimates overlapped between classifications. Thus, our streamlined panel of 12 markers may substitute panels with more markers, while retaining the capacity to control for population substructure and admixture, thereby reducing sample processing time.

Rare coding variants and X-linked loci associated with age at menarche. - Lunetta, Kathryn L; Day, Felix R; Sulem, Patrick; Ruth, Katherine S; Tung, Joyce Y; Hinds, David A; Esko, Tõnu; Elks, Cathy E; Altmaier, Elisabeth; He, Chunyan; Huffman, Jennifer E; Mihailov, Evelin; et al. (Nat Commun, 2015)
More than 100 loci have been identified for age at menarche by genome-wide association studies; however, collectively these explain only ∼3% of the trait variance. Here we test two overlooked sources of variation in 192,974 European ancestry women: low-frequency protein-coding variants and X-chromosome variants. Five missense/nonsense variants (in ALMS1/LAMB2/TNRC6A/TACR3/PRKAG1) are associated with age at menarche (minor allele frequencies 0.08-4.6%; effect sizes 0.08-1.25 years per allele; P<5 × 10(-8)). In addition, we identify common X-chromosome loci at IGSF1 (rs762080, P=9.4 × 10(-13)) and FAAH2 (rs5914101, P=4.9 × 10(-10)). Highlighted genes implicate cellular energy homeostasis, post-transcriptional gene silencing and fatty-acid amide signalling. A frequently reported mutation in TACR3 for idiopathic hypogonatrophic hypogonadism (p.W275X) is associated with 1.25-year-later menarche (P=2.8 × 10(-11)), illustrating the utility of population studies to estimate the penetrance of reportedly pathogenic mutations. Collectively, these novel variants explain ∼0.5% variance, indicating that these overlooked sources of variation do not substantially explain the 'missing heritability' of this complex trait.

Recommendations for the use of long-term central venous catheter (CVC) in children with hemato-oncological disorders: management of CVC-related occlusion and CVC-related thrombosis. On behalf of the coagulation defects working group and the supportive the - Giordano, Paola; Saracco, Paola; Grassi, Massimo; Luciani, Matteo; Banov, Laura; Carraro, Francesca; Crocoli, Alessandro; Cesaro, Simone; Zanazzo, Giulio Andrea; Molinari, Angelo Claudio (Ann Hematol, 2015)
Central venous catheters (CVC), used for the management of children with hemato-oncological disorders, are burdened by a significant incidence of mechanical, infective, or thrombotic complications. These complications favor an increasing risk in prolongation of hospitalization, extra costs of care, and sometimes severe life-threatening events. No guidelines for the management of CVC-related occlusion and CVC-related thrombosis are available for children. To this aim, members of the coagulation defects working group and the supportive therapy working group of the Italian Association of Pediatric Hematology and Oncology (AIEOP) reviewed the pediatric and adult literature to propose the first recommendations for the management of CVC-related occlusion and CVC-related thrombosis in children with hemato-oncological disorders.
Keywords: Adult; Blood Coagulation Disorders; Catheter Obstruction; Catheterization, Central Venous; Central Venous Catheters; Child; Hematologic Neoplasms; Humans; Risk Factors; Thrombosis

Risk factors for mortality from acute lower respiratory infections (ALRI) in children under five years of age in low and middle-income countries: a systematic review and meta-analysis of observational studies. - Sonego, Michela; Pellegrin, Maria Chiara; Becker, Genevieve; Lazzerini, Marzia (PLoS One, 2015)
OBJECTIVE: To evaluate risk factors for death from acute lower respiratory infections (ALRI) in children in low- and middle-income countries. DESIGN: Systematic review and meta-analysis. STUDY SELECTION: Observational studies reporting on risk factors for death from ALRI in children below five years in low- and middle income countries. DATA SOURCES: Medline, Embase, Global Health Library, Lilacs, and Web of Science to January 2014. RISK OF BIAS ASSESSMENT: Quality In Prognosis Studies tool with minor adaptations to assess the risk of bias; funnel plots and Egger's test to evaluate publication bias. RESULTS: Out of 10,655 papers retrieved, 77 studies from 39 countries (198,359 children) met the inclusion criteria. Host and disease characteristics more strongly associated with ALRI mortality were: diagnosis of very severe pneumonia as per WHO definition (odds ratio 9.42, 95% confidence interval 6.37‒13.92); age below two months (5.22, 1.70‒16.03); diagnosis of Pneumocystis Carinii (4.79, 2.67‒8.61), chronic underlying diseases (4.76, 3.27‒6.93); HIV/AIDS (4.68, 3.72‒5.90); and severe malnutrition (OR 4.27, 3.47‒5.25). Socio-economic and environmental factors significantly associated with increased odds of death from ALRI were: young maternal age (1.84, 1.03‒3.31); low maternal education (1.43, 1.13‒1.82); low socio-economic status (1.62, 1.32‒2.00); second-hand smoke exposure (1.52, 1.20 to 1.93); indoor air pollution (3.02, 2.11‒4.31). Immunisation (0.46, 0.36‒0.58) and good antenatal practices (0.50, 0.31‒0.81) were associated with decreased odds of death. CONCLUSIONS: Host and disease characteristics as well as socio-economic and environmental determinants affect the risk of death from ALRI in children. Together with the prevention and treatment of chronic diseases, interventions to modify underlying risk factors such as poverty, lack of female education, and poor environmental conditions, should be considered among the strategies to reduce ALRI mortality in children in low- and middle-income countries.
Keywords: Child, Preschool; Developing Countries; Environmental Exposure; Humans; Infant; Infant, Newborn; Observational Studies as Topic; Poverty; Respiratory Tract Infections; Risk Factors; Survival Analysis

Role of oxidative stress mediated by glutathione-s-transferase in thiopurines' toxic effects. - Pelin, Marco; De Iudicibus, Sara; Fusco, Laura; Taboga, Eleonora; Pellizzari, Giulia; Lagatolla, Cristina; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana; Stocco, Gabriele (Chem Res Toxicol, 2015)
Azathioprine (AZA), 6-mercaptopurine (6-MP), and 6-thioguanine (6-TG) are antimetabolite drugs, widely used as immunosuppressants and anticancer agents. Despite their proven efficacy, a high incidence of toxic effects in patients during standard-dose therapy is recorded. The aim of this study is to explain, from a mechanistic point of view, the clinical evidence showing a significant role of glutathione-S-transferase (GST)-M1 genotype on AZA toxicity in inflammatory bowel disease patients. To this aim, the human nontumor IHH and HCEC cell lines were chosen as predictive models of the hepatic and intestinal tissues, respectively. AZA, but not 6-MP and 6-TG, induced a concentration-dependent superoxide anion production that seemed dependent on GSH depletion. N-Acetylcysteine reduced the AZA antiproliferative effect in both cell lines, and GST-M1 overexpression increased both superoxide anion production and cytotoxicity, especially in transfected HCEC cells. In this study, an in vitro model to study thiopurines' metabolism has been set up and helped us to demonstrate, for the first time, a clear role of GST-M1 in modulating AZA cytotoxicity, with a close dependency on superoxide anion production. These results provide the molecular basis to shed light on the clinical evidence suggesting a role of GST-M1 genotype in influencing the toxic effects of AZA treatment.

Role of Pharmacogenetics in Hematopoietic Stem Cell Transplantation Outcome in Children. - Franca, Raffaella; Stocco, Gabriele; Favretto, Diego; Giurici, Nagua; Decorti, Giuliana; Rabusin, Marco (Int J Mol Sci, 2015)
Hematopoietic stem cell transplantation (HSCT) is an established therapeutic procedure for several congenital and acquired disorders, both malignant and nonmalignant. Despite the great improvements in HSCT clinical practices over the last few decades, complications, such as graft vs. host disease (GVHD) and sinusoidal obstructive syndrome (SOS), are still largely unpredictable and remain the major causes of morbidity and mortality. Both donor and patient genetic background might influence the success of bone marrow transplantation and could at least partially explain the inter-individual variability in HSCT outcome. This review summarizes some of the recent studies on candidate gene polymorphisms in HSCT, with particular reference to pediatric cohorts. The interest is especially focused on pharmacogenetic variants affecting myeloablative and immunosuppressive drugs, although genetic traits involved in SOS susceptibility and transplant-related mortality are also reviewed.

Romiplostim for secondary thrombocytopenia following allogeneic stem cell transplantation in children. - Maximova, Natalia; Zanon, D; Rovere, F; Maestro, A; Schillani, G; Paparazzo, R (Int J Hematol, 2015)
The outcome of romiplostim for secondary failure of platelet recovery (SFPR) was investigated in children who had undergone hematopoietic stem cell transplantation (HSCT). Seven transfusion-dependent pediatric patients (median age 11 years), with platelet counts below 10 × 10(9)/L, received four weekly doses of subcutaneous romiplostim to treat SFPR developed after HSCT. All patients, except one (patient 4), became platelet transfusion-independent in the second week from the beginning of treatment and no patient needed to discontinue drug treatment because of adverse events. Romiplostim could represent a beneficial first-line treatment, but further studies are required.

A Sensitive Electrochemiluminescence Immunosensor for Celiac Disease Diagnosis Based on Nanoelectrode Ensembles. - Habtamu, Henok B; Sentic, Milica; Silvestrini, Morena; De Leo, Luigina; Not, Tarcisio; Arbault, Stephane; Manojlovic, Dragan; Sojic, Neso; Ugo, Paolo (Anal Chem, 2015)

Sensorineural hearing loss in very low birth weight infants with histological chorioamnionitis. - Vedovato, Stefania; Lo Iacono, Angela; Morando, Carla; Suppiej, Agnese; Orzan, Eva; Trevisanuto, Daniele; Visentin, Silvia; Cavallin, Francesco; Chiarelli, Silvia; Zanardo, Vincenzo (J Matern Fetal Neonatal Med, 2015)
OBJECTIVE: Histological chorioamnionitis (HCAM) has been associated with inflammatory diseases of preterm infants. Recently we have observed that it increased the risk of speech delay and hearing loss. So the aim of this study was to evaluate the relationship between sensorineural hearing loss (SNHL) of VLBW infants and HCAM. METHODS: We performed an observational study on VLBW infants admitted to the NICU of Padua. Each patient with HCAM was matched with one control without HCAM. All infants underwent hearing screening before discharge by means of automated transient-evoked otoacustic emissions and automated auditory brainstem responses, which were repeated at 3 and 6 months of age with tympanometry measurement. Incidence of SNHL at 6 months of age was compared in the 2 groups and risk factors for hearing loss were studied. RESULTS: Two of 77 (2.6%) newborns with HCAM e 6/73 (8.2%) without it presented SNHL at 6 months of corrected age (p = 0.16). Multivariable logistic regression analysis identified surgical ligation of patent ductus arteriosus (PDA) as independent predictors of SNHL (OR: 5.75, 95% CI 1.34-24.84, p = 0.02), whereas the effect of HCAM on SNHL was only near to statistical significance level. CONCLUSIONS: Surgical ligation of PDA is associated with an increased risk of SNHL in VLBW infants, regardless of HCAM.

Serum TRAIL levels increase shortly after insulin therapy and metabolic stabilization in children with type 1 diabetes mellitus. - Tornese, Gianluca; Tisato, Veronica; Monasta, Lorenzo; Vecchi Brumatti, Liza; Zauli, Giorgio; Secchiero, Paola (Acta Diabetol, 2015)

Short Communication FYB polymorphisms in Brazilian patients with type I diabetes mellitus and autoimmune polyglandular syndrome type III. - Addobbati, C J C; de Azevêdo Silva, J; Tavares, N A C; Araujo, J; Guimarães, R L; Brandão, L; Crovella, S; Sandrin-Garcia, P (Genet Mol Res, 2015)
The aim of this study was to perform an association study between seven Fyn-binding protein gene (FYB)-tag single nucleotide polymorphisms (SNPs) and type I diabetes mellitus (T1DM), as well as with disease age of onset. We also assessed the role of FYB SNPs in the insurgence of autoimmune polyglandular syndrome type III (APSIII), characterized by the simultaneous presence of autoimmune thyroid disease and celiac disease, in patients with T1DM from a Northeastern Brazilian population. One hundred and seventy-seven patients with T1DM and 190 healthy individuals were genotyped for seven tag SNPs, covering most of the FYB locus, using real-time polymerase chain reaction amplification. There was no significant difference in the distribution of allele and genotype frequencies among patients and healthy individuals. Moreover, none of the tag SNPs were associated either to T1DM age of onset or to the insurgence of APSIII. However, since the FYB protein is a key component in T cell response, its gene variants might play a role in protein function, which might be testable in a population with different genetic backgrounds or by using functional assays.

Targeted tumor imaging of anti-CD20-polymeric nanoparticles developed for the diagnosis of B-cell malignancies. - Capolla, Sara; Garrovo, Chiara; Zorzet, Sonia; Lorenzon, Andrea; Rampazzo, Enrico; Spretz, Ruben; Pozzato, Gabriele; Núñez, Luis; Tripodo, Claudio; Macor, Paolo; Biffi, Stefania (Int J Nanomedicine, 2015)
The expectations of nanoparticle (NP)-based targeted drug delivery systems in cancer, when compared with convectional therapeutic methods, are greater efficacy and reduced drug side effects due to specific cellular-level interactions. However, there are conflicting literature reports on enhanced tumor accumulation of targeted NPs, which is essential for translating their applications as improved drug-delivery systems and contrast agents in cancer imaging. In this study, we characterized biodegradable NPs conjugated with an anti-CD20 antibody for in vivo imaging and drug delivery onto tumor cells. NPs' binding specificity mediated by anti-CD20 antibody was evaluated on MEC1 cells and chronic lymphocytic leukemia patients' cells. The whole-body distribution of untargeted NPs and anti-CD20 NPs were compared by time-domain optical imaging in a localized human/mouse model of B-cell malignancy. These studies provided evidence that NPs' functionalization by an anti-CD20 antibody improves tumor pharmacokinetic profiles in vivo after systemic administration and increases in vivo imaging of tumor mass compared to non-targeted NPs. Together, drug delivery and imaging probe represents a promising theranostics tool for targeting B-cell malignancies.

Three cases of Bartonella quintana infection in children. - Magnolato, Andrea; Pederiva, Federica; Spagnut, Giulia; Maschio, Massimo; Ventura, Alessandro; Taddio, Andrea (Pediatr Infect Dis J, 2015)
We present 3 children affected by B. quintana infection treated at the IRCCS Burlo Garofolo of Trieste between March and April 2013. B. quintana infection is rare but it should be suspected in patients with fever and lymphadenopathy who do not respond to conventional antibiotic treatment. All patients had a complete recovery without sequelae or relapses.

TNF-related apoptosis inducing ligand in ocular cancers and ocular diabetic complications. - Perri, Paolo; Zauli, Giorgio; Gonelli, Arianna; Milani, Daniela; Celeghini, Claudio; Lamberti, Giuseppe; Secchiero, Paola (Biomed Res Int, 2015)
TNF-related apoptosis inducing ligand (TRAIL) is an intensively studied cytokine, in particular for its anticancer activity. The discovery that conjunctival sac fluid contains extremely high levels of soluble TRAIL as compared to other body fluids suggested important implications in the context of the immunological surveillance of the eye, in particular of the anterior surface. In this review, we discuss the potential physiopathologic and therapeutic role of the TRAIL/TRAIL receptor system in a variety of ocular cancers. Moreover, since an increasing amount of data has indicated the important biological activities of the TRAIL/TRAIL receptor systems also in a completely different pathologic context such as diabetes mellitus, in the second part of this review we summarize the currently available data on the involvement of TRAIL in the ocular complications of diabetes mellitus as modulator of the inflammatory and angiogenic response in the eye.
Keywords: Apoptosis; Diabetes Complications; Diabetes Mellitus; Eye Neoplasms; Humans; Receptors, TNF-Related Apoptosis-Inducing Ligand; TNF-Related Apoptosis-Inducing Ligand

Trace samples of human blood in mosquitoes as a forensic investigation tool. - Rabelo, K C N; Albuquerque, C M R; Tavares, V B; Santos, S M; Souza, C A; Oliveira, T C; Oliveira, N C L; Crovella, S (Genet Mol Res, 2015)
Investigations of any type of crime invariably starts at the crime scene by collecting evidence. Thus, the purpose of this research was to collect and analyze an entomological trace from an environment that is similar to those of indoor crime scenes. Hematophagous mosquitoes were collected from two residential units; saliva of volunteers that were residents in the units was also collected for genetic analysis as reference samples. We examined the allele frequencies of 15 short tandem repeat loci (D8S1179, D21S11, D7S820, CSF1PO, D3S1358, TH01, D13S317, D16S539, D2S1338, D19S433, vWA, TPOX, D18S51, D5S818, and FGA) and amelogenin. A total of 26 female hematophagous mosquitoes were identified as Aedes aegypti, Aedes albopictus, and Culex quinquefasciatus; we were able to obtain 11 forensically valid genetic profiles, with a minimum of 0.028203 ng/μL of human DNA. Thus, the results of this study showed that it was possible to correlate human genetic information from mosquitoes with the volunteer reference samples, which validates the use of this information as forensic evidence. Furthermore, we observed mixed genetic profiles from one mosquito. Therefore, it is clearly important to collect these insects indoors where crimes were committed, because it may be possible to find intact genetic profiles of suspects in the blood found in the digestive tract of hematophagous mosquitoes for later comparison to identify an offender and/or exclude suspects.

TRAIL modulates the immune system and protects against the development of diabetes. - Bossi, Fleur; Bernardi, Stella; Zauli, Giorgio; Secchiero, Paola; Fabris, Bruno (J Immunol Res, 2015)
TRAIL or tumor necrosis factor (TNF) related apoptosis-inducing ligand is a member of the TNF superfamily of proteins, whose best characterized function is the induction of apoptosis in tumor, infected, or transformed cells through activation of specific receptors. In nontransformed cells, however, the actions of TRAIL are less well characterized. Recent studies suggest that TRAIL may be implicated in the development and progression of diabetes. Here we review TRAIL biological actions, its effects on the immune system, and how and to what extent it has been shown to protect against diabetes.
Keywords: Animals; Diabetes Mellitus; Humans; Immune System; Receptors, TNF-Related Apoptosis-Inducing Ligand; Signal Transduction

Triple Akt inhibition as a new therapeutic strategy in T-cell acute lymphoblastic leukemia. - Cani, Alice; Simioni, Carolina; Martelli, Alberto M; Zauli, Giorgio; Tabellini, Giovanna; Ultimo, Simona; McCubrey, James A; Capitani, Silvano; Neri, Luca M (Oncotarget, 2015)
T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive neoplastic disorder in which chemotherapy resistance and refractory relapses occur, with a poorer prognostic outcome.Constitutively active PI3K/Akt/mTOR pathway is a common feature of T-ALL upregulating cell proliferation, survival and drug resistance. This pathway is currently under clinical trials with small molecules inhibitors (SMI).To verify whether a multi-inhibition treatment against Akt protein could enhance the efficacy of individual drug administration and overcome drug resistance as well as to obtain a decrease in single drug concentration, we tested on T-ALL cell lines the effects of combined treatments with three Akt inhibitors with different mode of action, GSK690693, MK-2206 and Perifosine.In cells with hyperactivated Akt, combined administration of the drugs displayed a significant synergistic and cytotoxic effect and affected PI3K/Akt/mTOR pathway at much lower concentration than single drug use. Highest synergistic effect for full inhibition of Akt was also related to the timing of every drug administration. Furthermore the triple treatment had greater efficacy in inducing cell cycle arrest in G0/G1 phase and both apoptosis and autophagy.Targeting Akt as a key protein of PI3K/Akt/mTOR pathway with multiple drugs might represent a new and promising pharmacological strategy for treatment of T-ALL patients.

Tumor necrosis factor-α and interleukin-6 gene polymorphism association with susceptibility to celiac disease in Italian patients. - de Albuquerque Maranhão, R M; Martins Esteves, F A; Crovella, S; Segat, L; Eleutério Souza, P R (Genet Mol Res, 2015)
The aim of this research was to study polymorphisms in the genes encoding cytokines interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) in patients with celiac disease (CD) antigens DQ2 (DQ2-positive) or DQ8 (DQ8-positive). We compared the results with healthy controls to determine whether any of the polymorphisms have a role in susceptibility to CD. A case-control of 192 patients with CD (96 DQ2-positive and 96 DQ8-positive) and 96 healthy controls from northeast Italy were included in the study. Analysis of single nucleotide polymorphisms (SNPs) was carried out using the polymerase chain reaction-restriction fragment length polymorphism method. Significant differences for the TNF-α(-308 G>A) polymorphism were observed when we compared the flowing groups: DQ2-positive with controls [odds ratio (OR) = 0.45, P = 0.0002]; DQ8-positive with controls (OR = 3.55, P < 0.0001); and DQ2-positive with DQ8-positive (OR = 0.12, P < 0.0001). We did not observe a statistically significant association between IL-6 (-174 G>C) polymorphism and CD (P > 0.05). Our results suggest that TNF-α(-308 G>A) polymorphism may play a role in susceptibility to CD in Italian patients.

Two-dimensional gel electrophoresis analysis of the leiomyoma interstitial fluid reveals altered protein expression with a possible involvement in pathogenesis. - Ura, Blendi; Scrimin, Federica; Zanconati, Fabrizio; Arrigoni, Giorgio; Monasta, Lorenzo; Romano, Andrea; Banco, Rubina; Zweyer, Marina; Milani, Daniela; Ricci, Giuseppe (Oncol Rep, 2015)
Uterine leiomyoma is the most common smooth benign neoplasm. In the present study, we analyzed the global interstitial fluid (IF) profile of leiomyoma vs. normal myometrium to identify protein dysregulation involved in leiomyoma pathogenesis. Two-dimensional gel electrophoresis and mass spectrometry were used to generate and compare the global interstitial fluid profiles of the leiomyoma and of the normal tissue. Two proteins were validated by immunohistochemistry. By comparing the interstitial fluid profile of the leiomyoma with that of the normal myometrium, the levels of seven proteins were found to be significantly different: four structural organization proteins (desmin, prelamin-A/C, transgelin and α-actinin-1), an inflammatory response (α1-antitrypsin), a response to oxidative stress (peroxiredoxin-2), and a folding protein (heat shock 70 kDa protein 1A/1B). Desmin, α1-antitrypsin and peroxiredoxin-2 were upregulated in the leiomyoma, whereas heat shock 70 kDa protein 1A/1B, α-actinin-1, prelamin-A/C and transgelin were downregulated. Desmin and α1-antitrypsin were further validated by immunohistochemistry. By identifying proteins with altered expression levels compared to the myometrium from several pathways of the leiomyoma pathogenesis, we found the leiomyoma interstitial fluid to have a characteristic proteomic profile. A better appreciation of the pathophysiology of the disease can be useful in the development of conservative treatments that serve as viable alternatives to hysterectomy.

Unusual onset of a case of chronic recurrent multifocal osteomyelitis. - Barrani, M; Massei, F; Scaglione, M; Paolicchi, A; Vitali, S; Ciancia, E M; Crovella, S; Caparello, M C; Consolini, R (Pediatr Rheumatol Online J, 2015)
BACKGROUND: Chronic recurrent multifocal osteomyelitis (CRMO) is a rare condition that commonly affects the clavicle and pelvis. CASE PRESENTATION: We report here a case a 12 years old girl with CRMO arising with recurrent episodes of left supraorbital headache, followed by the appearance of a periorbital dyschromia. Magnetic resonance imaging (MRI) of the skull and orbits revealed an important subacute inflammatory process. Few months after, the child presented a painful swelling of the left clavicle; the histological examination of the related biopsy allowed to establish the diagnosis of CRMO. CONCLUSION: CRMO presenting as acute headache involving neurocranium is rare; to our knowledge this is the first recognized case in the world literature. This pathological condition is frequently misdiagnosed as infection or neoplasm and needs a deep investigation for the differential diagnosis. The physical, laboratoristic and instrumental diagnostic investigations of the patient and the treatment employed are described in detail.

Vitamin D receptor polymorphisms and expression profile in rheumatoid arthritis brazilian patients. - Cavalcanti, Catarina Addobbati Jordão; De Azevêdo Silva, Jaqueline; de Barros Pita, Will; Veit, Tiago Degani; Monticielo, Odirlei Andre; Xavier, Ricardo Machado; Brenol, João Carlos Tavares; Brenol, Cleiton Viegas; Fragoso, Thiago Sotero; Barbosa, Alexandre Domingues; Duarte, Ângela Luiza Branco Pinto; Oliveira, Renê Donizeti Ribeiro; et al. (Mol Biol Rep, 2015)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation and important joint commitment, being the most common systemic autoimmune disease worldwide. RA displays important genetic background with a variety of genes contributing to the immune balance breakdown. Recent studies have demonstrated that vitamin D, through its receptor (VDR), is able to regulate the immune balance and suppress the autoimmunity process, being a potential target in autoimmune diseases. In the present genetic association study, we assessed 5 Tag single nucleotide polymorphisms (SNPs) (rs11168268, rs2248098, rs1540339, rs4760648 and rs3890733), which cover most of the VDR gene, in three different Brazilian populations (from Northeast, Southeast and South Brazil). We also evaluated the VDR expression profile in whole blood and monocytes from RA patients. For genotyping study, 428 RA patients and 616 healthy controls were genotyped with fluorogenic allele specific probes on an ABI7500 platform. For gene expression study, VDR mRNA levels of 15 RA patients and 26 healthy individuals were assessed by RT-PCR. Our results showed that SNPs rs4760648 and rs3890733 are associated to RA susceptibility (p value = 0.0026, OR 1.31 and p value = 0.0091, OR 1.28 with statistical power = 0.999 and 0.993, respectively). Regarding RA clinical features, the studied SNPs did not show significant associations. The gene expression assays showed that VDR mRNA levels were down regulated in both whole blood (-3.3 fold) and monocytes (-3.2 fold) of RA patients when compared to healthy controls. Our results, the first reported for distinct Brazilian populations, support a role of the VDR gene in the susceptibility to RA.

Analysis of 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. - Noris, Patrizia; Schlegel, Nicole; Klersy, Catherine; Heller, Paula G; Civaschi, Elisa; Pujol-Moix, Núria; Fabris, Fabrizio; Favier, Rémi; Gresele, Paolo; Latger-Cannard, Véronique; Cuker, Adam; Nurden, Paquita; et al. (Haematologica, 2014)
Pregnancy in women with inherited thrombocytopenias is a major matter of concern as both the mothers and the newborns are potentially at risk of bleeding. However, medical management of this condition cannot be based on evidence because of the lack of consistent information in the literature. To advance knowledge on this matter, we performed a multicentric, retrospective study evaluating 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. Neither the degree of thrombocytopenia nor the severity of bleeding tendency worsened during pregnancy and the course of pregnancy did not differ from that of healthy subjects in terms of miscarriages, fetal bleeding and pre-term births. The degree of thrombocytopenia in the babies was similar to that in the mother. Only 7 of 156 affected newborns had delivery-related bleeding, but 2 of them died of cerebral hemorrhage. The frequency of delivery-related maternal bleeding ranged from 6.8% to 14.2% depending on the definition of abnormal blood loss, suggesting that the risk of abnormal blood loss was increased with respect to the general population. However, no mother died or had to undergo hysterectomy to arrest bleeding. The search for parameters predicting delivery-related bleeding in the mother suggested that hemorrhages requiring blood transfusion were more frequent in women with history of severe bleedings before pregnancy and with platelet count at delivery below 50 × 10(9)/L.
Keywords: Adult; Female; Humans; Infant, Newborn; Pregnancy; Pregnancy Complications, Hematologic; Retrospective Studies; Thrombocytopenia; Young Adult

Assessment of coupling between trans-abdominally acquired fetal ECG and uterine activity by bivariate phase-rectified signal averaging analysis. - Casati, Daniela; Stampalija, Tamara; Rizas, Konstantinos; Ferrazzi, Enrico; Mastroianni, Cristina; Rosti, Eleonora; Quadrifoglio, Mariachiara; Bauer, Axel (PLoS One, 2014)
UNLABELLED: Couplings between uterine contractions (UC) and fetal heart rate (fHR) provide important information on fetal condition during labor. At present, couplings between UC and fHR are assessed by visual analysis and interpretation of cardiotocography. The application of computerized approaches is restricted due to the non-stationarity of the signal, missing data and noise, typical for fHR. Herein, we propose a novel approach to assess couplings between UC and fHR, based on a signal-processing algorithm termed bivariate phase-rectified signal averaging (BPRSA). METHODS: Electrohysterogram (EHG) and fetal electrocardiogram (fECG) were recorded non-invasively by a trans-abdominal device in 73 women at term with uneventful singleton pregnancy during the first stage of labor. Coupling between UC and fHR was analyzed by BPRSA and by conventional cross power spectral density analysis (CPSD). For both methods, degree of coupling was assessed by the maximum coefficient of coherence (CPRSA and CRAW, respectively) in the UC frequency domain. Coherence values greater than 0.50 were consider significant. CPRSA and CRAW were compared by Wilcoxon test. RESULTS: At visual inspection BPRSA analysis identified coupled periodicities in 86.3% (63/73) of the cases. 11/73 (15%) cases were excluded from further analysis because no 30 minutes of fECG recording without signal loss was available for spectral analysis. Significant coupling was found in 90.3% (56/62) of the cases analyzed by BPRSA, and in 24.2% (15/62) of the cases analyzed by CPSD, respectively. The difference between median value of CPRSA and CRAW was highly significant (0.79 [IQR 0.69-0.90] and 0.29 [IQR 0.17-0.47], respectively; p<0.0001). CONCLUSION: BPRSA is a novel computer-based approach that can be reliably applied to trans-abdominally acquired EHG-fECG. It allows the assessment of correlations between UC and fHR patterns in the majority of labors, overcoming the limitations of non-stationarity and artifacts. Compared to standard techniques of cross-correlations, such as CPSD, BPRSA is significantly superior.
Keywords: Electrocardiography; Female; Heart Rate, Fetal; Humans; Labor, Obstetric; Pregnancy; Uterine Contraction

Association analysis of bitter receptor genes in five isolated populations identifies a significant correlation between TAS2R43 variants and coffee liking. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; d'Adamo, Pio; Amin, Najaf; D'Eustacchio, Angela; Navarini, Luciano; Sala, Cinzia; Karssen, Lennart C; et al. (PLoS One, 2014)
Coffee, one of the most popular beverages in the world, contains many different physiologically active compounds with a potential impact on people's health. Despite the recent attention given to the genetic basis of its consumption, very little has been done in understanding genes influencing coffee preference among different individuals. Given its markedly bitter taste, we decided to verify if bitter receptor genes (TAS2Rs) variants affect coffee liking. In this light, 4066 people from different parts of Europe and Central Asia filled in a field questionnaire on coffee liking. They have been consequently recruited and included in the study. Eighty-eight SNPs covering the 25 TAS2R genes were selected from the available imputed ones and used to run association analysis for coffee liking. A significant association was detected with three SNP: one synonymous and two functional variants (W35S and H212R) on the TAS2R43 gene. Both variants have been shown to greatly reduce in vitro protein activity. Surprisingly the wild type allele, which corresponds to the functional form of the protein, is associated to higher liking of coffee. Since the hTAS2R43 receptor is sensible to caffeine, we verified if the detected variants produced differences in caffeine bitter perception on a subsample of people coming from the FVG cohort. We found a significant association between differences in caffeine perception and the H212R variant but not with the W35S, which suggests that the effect of the TAS2R43 gene on coffee liking is mediated by caffeine and in particular by the H212R variant. No other significant association was found with other TAS2R genes. In conclusion, the present study opens new perspectives in the understanding of coffee liking. Further studies are needed to clarify the role of the TAS2R43 gene in coffee hedonics and to identify which other genes and pathways are involved in its genetics.
Keywords: Coffee; Genetic Association Studies; Humans; Polymorphism, Single Nucleotide; Receptors, G-Protein-Coupled; Taste

Association of CD209 and CD209L polymorphisms with tuberculosis infection in a Northeastern Brazilian population. - da Silva, Ronaldo Celerino; Segat, Ludovica; da Cruz, Heidi Lacerda Alves; Schindler, Haiana Charifker; Montenegro, Lilian Maria Lapa; Crovella, Sergio; Guimarães, Rafael Lima (Mol Biol Rep, 2014)
Tuberculosis (TB) caused by Mycobacterium tuberculosis, is major cause of morbidity and mortality worldwide. So far, many candidate genes have been investigated for their possible association with TB. Dendritic cell-specific intercellular adhesion molecule 3 (ICAM-3) grabbing non-integrin (DC-SIGN) and Liver/lymph node-specific intercellular adhesion molecule-grabbing non-integrin (L-SIGN), encoded by CD209 and CD209L genes respectively, are known for binding to M. tuberculosis on human dendritic cells and macrophages. We screened 4 single nucleotide polymorphisms (SNPs) in the promoter region of CD209, namely -939G>A (rs735240), -871A>G (rs735239), -336A>G (rs4804803) and -139G>A (rs2287886) and tandem repeat polymorphisms in exon 4 of CD209 and CD209L genes looking for association with TB in a Northeastern Brazilian population (295 subjects, 131 TB patients and 164 healthy controls). The -139G>A and -939G>A SNPs were associated with susceptibility to TB, and in particular with pulmonary and extra-pulmonary forms respectively. The -871A>G and -336A>G SNPs were associated, the first with protection to both pulmonary and extra-pulmonary TB, the latter only with the pulmonary form. An association between GGAG haplotype and protection to TB infection was also found. Also tandem repeat polymorphism in CD209L exon 4 was associated with TB infection. This study provides evidence of an association between CD209 and CD209L polymorphisms and TB development in a Brazilian population, suggesting that variations in these genes may influence the protection and susceptibility to infection caused by M. tuberculosis.
Keywords: Adult; Alleles; Brazil; Case-Control Studies; Cell Adhesion Molecules; Dendritic Cells; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Lectins, C-Type; Male; Mycobacterium tuberculosis; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Receptors, Cell Surface; Tuberculosis; Young Adult

Association of serum tumor necrosis factor-related apoptosis inducing ligand with body fat distribution as assessed by dual X-rays absorptiometry. - Cervellati, Carlo; Secchiero, Paola; Bonaccorsi, Gloria; Celeghini, Claudio; Zauli, Giorgio (Mediators Inflamm, 2014)
A low chronic inflammation mediated by cytokine release is considered a major pathogenic mechanism accounting for the higher risk of cardiovascular disease in the overweight/obese population. In this context, although the existence of a possible interaction between soluble tumor necrosis factor- (TNF-) related apoptosis inducing ligand (TRAIL) and quantity and localization, of adiposity in the body has been hypothesized, no studies have yet investigated this link by radiologic techniques able to assess directly fat mass (FM) in different body regions. To address this issue, we assessed body fat distribution by dual X-rays absorptiometry (DXA) in a sample of 103 women and investigated the possible association between the derived adiposity measures and serum TRAIL concentration. The level of TRAIL showed a positive and independent correlation with arms FM (P < 0.05), trunk FM (P < 0.001) and trunk FM% (P < 0.05), total FM and total FM% (P < 0.001 for both), and an inverse association with legs FM% (P < 0.05). Only trunk FM retained a significant correlation (P < 0.05) with TRAIL after adjusting for all the other indices of regional adiposity. In conclusion, from our study it emerged a significant and independent association of serum TRAIL levels with overall, and, mainly, central adiposity. Further studies are needed to longitudinally investigate the cause-effect relationship between change in body fat distribution and TRAIL.
Keywords: Absorptiometry, Photon; Adipose Tissue; Adiposity; Adult; Anthropometry; Female; Gene Expression Regulation; Humans; Inflammation; Linear Models; Menopause; Middle Aged; Overweight; TNF-Related Apoptosis-Inducing Ligand

An asymptomatic multiple magnet ingestion with transmesenteric entero-enteric fistula. - Pederiva, Federica; Daniela, Codrich; Scarpa, Maria-Grazia; Guida, Edoardo; Dragovic, Danica; Martelossi, Stefano (APSP J Case Rep, 2014)
Ingestion of foreign bodies is a common presenting complaint in the pediatric emergency department. We present a case of a child in whom disc battery ingestion was suspected initially. The immobility of the foreign body on few days of conservative management raised the suspicion of two magnets. At operation, two magnets were found in the bowel causing a transmesenteric entero-enteric fistula.

Beta defensin-1 gene polymorphisms and susceptibility to atypical squamous cells of undetermined significance lesions in Italian gynecological patients. - Casalicchio, Giorgia; Freato, Nadia; Maestri, Iva; Comar, Manola; Crovella, Sergio; Segat, Ludovica (J Med Virol, 2014)
The role of the human beta-defensin 1 (hBD-1) in the susceptibility to the onset of the Atypical Squamous Cells of Undetermined Significance (ASCUS) lesion, in the presence or not of HPV infection, is still unknown. In the current study, the three functional single nucleotide polymorphisms (SNPs) -52G > A, -44C > G, and -20G > A at the 5' un-translated region (UTR) of DEFB1 gene, encoding hBD-1, were analyzed in ASCUS lesion gynecological patients and healthy women from the north-east of Italy (Trieste). Cervical samples from 249 European-Caucasian women were collected, screened for HPV and cytologically evaluated; DEFB1 genotyping has been performed by direct sequencing. No significant differences were found for -52G > A, -44C > G, and -20G > A SNPs allele and genotype frequencies between women with and without ASCUS lesions. DEFB1 minor haplotypes were significantly more frequent in ASCUS lesion positive than negative women, associating with an increased risk of this type of lesion. When women were stratified according to HPV infection status, significant differences in the distribution of -52G > A SNP genotype frequencies were found: the presence of the A allele in the homozygous genotype A/A associated with a lower risk of developing ASCUS lesions in HPV negative women. DEFB1 minor haplotypes were also associated with an increased risk of developing ASCUS lesions, being significantly more frequent in HPV negative women with lesions, than without lesions. Although these results highlight the possible involvement of DEFB1, further studies are needed to support the role of DEFB1 in the modulation of the susceptibility to ASCUS lesions.
Keywords: 5' Untranslated Regions; Adolescent; Adult; Atypical Squamous Cells of the Cervix; beta-Defensins; Female; Genotype; Humans; Italy; Papillomavirus Infections; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Uterine Cervical Neoplasms; Young Adult

Childhood high-risk acute lymphoblastic leukemia in first remission: results after chemotherapy or transplant from the AIEOP ALL 2000 study. - Conter, Valentino; Valsecchi, Maria Grazia; Parasole, Rosanna; Putti, Maria Caterina; Locatelli, Franco; Barisone, Elena; Lo Nigro, Luca; Santoro, Nicola; Aricò, Maurizio; Ziino, Ottavio; Pession, Andrea; Testi, Anna Maria; et al. (Blood, 2014)
The outcome of high-risk (HR) acute lymphoblastic leukemia patients enrolled in the AIEOP-BFM ALL 2000 study in Italy is described. HR criteria were minimal residual disease (MRD) levels ≥10(-3) at day 78 (MRD-HR), no complete remission (CR) at day 33, t(4;11) translocation, and prednisone poor response (PPR). Treatment (2 years) included protocol I, 3 polychemotherapy blocks, delayed intensification (protocol IIx2 or IIIx3), cranial radiotherapy, and maintenance. A total of 312 HR patients had a 5-year event-free survival (EFS) of 58.9% (standard error [SE] = 2.8) and an overall survival of 68.9% (SE = 2.6). In hierarchical order, EFS was 45.9% (4.4) in 132 MRD-HR patients, 41.2% (11.9) in 17 patients with no CR at day 33, 36.4% (14.5) in 11 patients with t(4;11), and 74.0% (3.6) in 152 HR patients only for PPR. No statistically significant difference was found for disease-free survival in patients with very HR features [MRD-HR, no CR at day 33, t(4;11) translocation], given hematopoietic stem cell transplantation (HSCT) (n = 66) or chemotherapy only (n = 88), after adjusting for waiting time to HSCT (5.7 months). Patients at HR only for PPR have a favorable outcome. MRD-HR is associated with poor outcome despite intensive treatment and/or HSCT and may qualify for innovative therapies. The study was registered at www.clinicaltrials.gov as #NCT00613457.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Child; Child, Preschool; Combined Modality Therapy; Female; Hematopoietic Stem Cell Transplantation; Humans; Infant; Male; Neoplasm, Residual; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Radiotherapy; Remission Induction; Treatment Outcome

Clinical features and follow-up in patients with 22q11.2 deletion syndrome. - Cancrini, Caterina; Puliafito, Pamela; Digilio, Maria Cristina; Soresina, Annarosa; Martino, Silvana; Rondelli, Roberto; Consolini, Rita; Ruga, Ezia Maria; Cardinale, Fabio; Finocchi, Andrea; Romiti, Maria Luisa; Martire, Baldassarre; et al. (J Pediatr, 2014)
OBJECTIVE: To investigate the clinical manifestations at diagnosis and during follow-up in patients with 22q11.2 deletion syndrome to better define the natural history of the disease. STUDY DESIGN: A retrospective and prospective multicenter study was conducted with 228 patients in the context of the Italian Network for Primary Immunodeficiencies. Clinical diagnosis was confirmed by cytogenetic or molecular analysis. RESULTS: The cohort consisted of 112 males and 116 females; median age at diagnosis was 4 months (range 0 to 36 years 10 months). The diagnosis was made before 2 years of age in 71% of patients, predominantly related to the presence of heart anomalies and neonatal hypocalcemia. In patients diagnosed after 2 years of age, clinical features such as speech and language impairment, developmental delay, minor cardiac defects, recurrent infections, and facial features were the main elements leading to diagnosis. During follow-up (available for 172 patients), the frequency of autoimmune manifestations (P = .015) and speech disorders (P = .002) increased. After a median follow-up of 43 months, the survival probability was 0.92 at 15 years from diagnosis. CONCLUSIONS: Our data show a delay in the diagnosis of 22q11.2 deletion syndrome with noncardiac symptoms. This study provides guidelines for pediatricians and specialists for early identification of cases that can be confirmed by genetic testing, which would permit the provision of appropriate clinical management.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Age Factors; Child; Child, Preschool; Chromosomes, Human, Pair 22; Delayed Diagnosis; Developmental Disabilities; DiGeorge Syndrome; Disease Progression; Early Diagnosis; Female; Follow-Up Studies; Genetic Testing; Humans; Infant; Infant, Newborn; Male; Monitoring, Physiologic; Prospective Studies; Retrospective Studies; Risk Assessment; Severity of Illness Index; Sex Factors; Time Factors; Young Adult

Common variants in UMOD associate with urinary uromodulin levels: a meta-analysis. - Olden, Matthias; Corre, Tanguy; Hayward, Caroline; Toniolo, Daniela; Ulivi, Sheila; Gasparini, Paolo; Pistis, Giorgio; Hwang, Shih-Jen; Bergmann, Sven; Campbell, Harry; Cocca, Massimiliano; Gandin, Ilaria; et al. (J Am Soc Nephrol, 2014)
Uromodulin is expressed exclusively in the thick ascending limb and is the most abundant protein excreted in normal urine. Variants in UMOD, which encodes uromodulin, are associated with renal function, and urinary uromodulin levels may be a biomarker for kidney disease. However, the genetic factors regulating uromodulin excretion are unknown. We conducted a meta-analysis of urinary uromodulin levels to identify associated common genetic variants in the general population. We included 10,884 individuals of European descent from three genetic isolates and three urban cohorts. Each study measured uromodulin indexed to creatinine and conducted linear regression analysis of approximately 2.5 million single nucleotide polymorphisms using an additive model. We also tested whether variants in genes expressed in the thick ascending limb associate with uromodulin levels. rs12917707, located near UMOD and previously associated with renal function and CKD, had the strongest association with urinary uromodulin levels (P<0.001). In all cohorts, carriers of a G allele of this variant had higher uromodulin levels than noncarriers did (geometric means 10.24, 14.05, and 17.67 μg/g creatinine for zero, one, or two copies of the G allele). rs12446492 in the adjacent gene PDILT (protein disulfide isomerase-like, testis expressed) also reached genome-wide significance (P<0.001). Regarding genes expressed in the thick ascending limb, variants in KCNJ1, SORL1, and CAB39 associated with urinary uromodulin levels. These data indicate that common variants in the UMOD promoter region may influence urinary uromodulin levels. They also provide insights into uromodulin biology and the association of UMOD variants with renal function.
Keywords: Creatinine; European Continental Ancestry Group; Genetic Variation; Humans; Polymorphism, Single Nucleotide; Uromodulin

DC-SIGN polymorphisms are associated to type 1 diabetes mellitus. - da Silva, Ronaldo Celerino; Cunha Tavares, Nathália de Alencar; Moura, Ronald; Coelho, Antônio; Guimarães, Rafael Lima; Araújo, Jacqueline; Crovella, Sergio; Brandão, Lucas André Cavalcanti; Silva, Jaqueline de Azevêdo (Immunobiology, 2014)
Type I diabetes mellitus (T1DM) is an autoimmune disorder featured by raised glucoses levels. It has been hypothesised that raised glucose levels in T1DM might be recognised as PAMPs, leading to immune response by overloading the cell receptors for pathogens recognition. DC-SIGN is a transmembrane protein, present in dendritic cells (DC) and macrophages: it has an important role in inflammatory response and T cells activation. Notably, DC-SIGN activation and triggering of the immune response depend on the type of ligand, which may lead to a pro or anti-inflammatory pathway. In our association study, we analysed the SNPs rs4804803 (-336 A>G) and rs735239 (-871 A>G), both at DC-SIGN promoter region, in 210 T1DM patients and 157 healthy controls, also looking for a correlation with the age of onset of the disease. We found that the allele G and genotypes G/G and A/G of SNP-871 (rs735239), as well as the alleles G-G (rs735239-rs4804803) and genotypes combined AA-GG (rs735239-rs4804803) were associated with protection of T1DM development. We did not find association between these variations with the age of onset of the disease and the presence of other autoimmune disorders. Our results suggest that SNPs in DC-SIGN promoter region can be associated to protection for T1DM in the Northeast Brazilian population.
Keywords: Adolescent; Alleles; Case-Control Studies; Cell Adhesion Molecules; Child; Child, Preschool; Diabetes Mellitus, Type 1; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Humans; Infant; Infant, Newborn; Lectins, C-Type; Male; Odds Ratio; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Receptors, Cell Surface

DEFB1 polymorphisms are involved in susceptibility to human papillomavirus infection in Brazilian gynaecological patients. - Segat, Ludovica; Zupin, Luisa; Moura, Ronald Rodrigues; Coelho, Antônio Victor Campos; Chagas, Bárbara Simas; de Freitas, Antonio Carlos; Crovella, Sergio (Mem Inst Oswaldo Cruz, 2014)
The human beta defensin 1 (hBD-1) antimicrobial peptide is a member of the innate immune system known to act in the first line of defence against microorganisms, including viruses such as human papillomavirus (HPV). In this study, five functional polymorphisms (namely g-52G>A, g-44C>G and g-20G>A in the 5'UTR and c.*5G>A and c.*87A>G in the 3'UTR) in the DEFB1 gene encoding for hBD-1 were analysed to investigate the possible involvement of these genetic variants in susceptibility to HPV infection and in the development of HPV-associated lesions in a population of Brazilian women. The DEFB1 g-52G>A and c.*5G>A single-nucleotide polymorphisms (SNPs) and the GCAAA haplotype showed associations with HPV-negative status; in particular, the c.*5G>A SNP was significantly associated after multiple test corrections. These findings suggest a possible role for the constitutively expressed beta defensin-1 peptide as a natural defence against HPV in the genital tract mucosa.
Keywords: Adolescent; Adult; Aged; beta-Defensins; Brazil; Case-Control Studies; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Middle Aged; Papillomavirus Infections; Polymorphism, Single Nucleotide; Reproductive Tract Infections; Young Adult

Development of an enzyme-linked immunosorbent assay for Bartonella henselae infection detection. - Ferrara, F; Di Niro, R; D'Angelo, S; Busetti, M; Marzari, R; Not, T; Sblattero, D (Lett Appl Microbiol, 2014)
UNLABELLED: Several serological diagnostics rely on enzyme-linked immunosorbent assay (ELISA) to detect bacterial infections. However, for some pathogens, including Bartonella henselae, diagnosis still depends on manually intensive, time-consuming assays including micro-immunofluorescence, Western blotting or indirect immunofluorescence. For such pathogens, there is obviously still a need to identify antigens to establish a reliable, fast and high-throughput assay (Dupon et al. ). We evaluated two B. henselae proteins to develop a novel serological ELISA: a well-known antigen, the 17-kDa protein, and GroEL, identified during this study by a proteomic approach. When serum IgG were tested, the specificity and sensitivity were 76 and 65·7% for 17-kDa, respectively, and 82 and 42·9% for GroEL, respectively. IgM were found to be more sensitive and specific for both proteins: 17-kDa protein, specificity 86·2% and sensitivity 75%; GroEL, specificity 97·7% and sensitivity 45·3%. IgM antibodies were also measured in lymphoma patients and patients with Mycobacterium tuberculosis infection to assess the usefulness of our ELISA to distinguish them from B. henselae infected patients. The resulting specificities were 89·1 and 93·5% for 17-kDa protein and GroEL, respectively. Combining the results from the two tests, we obtained a sensitivity of 82·8% and a specificity of 83·9%. Our work described and validated a proteomic approach suitable to identify immunogenic proteins useful for developing a serological test of B. henselae infection. SIGNIFICANCE AND IMPACT OF THE STUDY: A reliable serological assay for the diagnosis of Cat Scratch Disease (CSD) - a pathological condition caused by Bartonella henselae infection - has not yet been developed. Such an assay would be extremely useful to discriminate between CSD and other pathologies with similar symptoms but different aetiologies, for example lymphoma or tuberculosis. We investigate the use of two B. henselae proteins - GroEL and 17-kDa - to develop a serological-based ELISA, showing promising results with the potential for further development as an effective tool for the differential diagnosing of B. henselae infection.
Keywords: Adolescent; Adult; Amino Acid Sequence; Antibodies, Bacterial; Antigens, Bacterial; Bacterial Proteins; Bartonella henselae; Case-Control Studies; Cat-Scratch Disease; Chaperonin 60; Child; Child, Preschool; Diagnosis, Differential; Enzyme-Linked Immunosorbent Assay; Female; Humans; Immunoglobulin M; Lymphoma; Male; Molecular Sequence Data; ROC Curve; Tuberculosis, Pulmonary; Young Adult

DNA mismatch repair gene MSH6 implicated in determining age at natural menopause. - Perry, John R B; Hsu, Yi-Hsiang; Chasman, Daniel I; Johnson, Andrew D; Elks, Cathy; Albrecht, Eva; Andrulis, Irene L; Beesley, Jonathan; Berenson, Gerald S; Bergmann, Sven; Bojesen, Stig E; Bolla, Manjeet K; et al. (Hum Mol Genet, 2014)
The length of female reproductive lifespan is associated with multiple adverse outcomes, including breast cancer, cardiovascular disease and infertility. The biological processes that govern the timing of the beginning and end of reproductive life are not well understood. Genetic variants are known to contribute to ∼50% of the variation in both age at menarche and menopause, but to date the known genes explain <15% of the genetic component. We have used genome-wide association in a bivariate meta-analysis of both traits to identify genes involved in determining reproductive lifespan. We observed significant genetic correlation between the two traits using genome-wide complex trait analysis. However, we found no robust statistical evidence for individual variants with an effect on both traits. A novel association with age at menopause was detected for a variant rs1800932 in the mismatch repair gene MSH6 (P = 1.9 × 10(-9)), which was also associated with altered expression levels of MSH6 mRNA in multiple tissues. This study contributes to the growing evidence that DNA repair processes play a key role in ovarian ageing and could be an important therapeutic target for infertility.
Keywords: Age Factors; DNA-Binding Proteins; Female; Genome-Wide Association Study; Humans; Menopause; Polymorphism, Single Nucleotide

Expression and replication studies to identify new candidate genes involved in normal hearing function. - Girotto, Giorgia; Vuckovic, Dragana; Buniello, Annalisa; Lorente-Cánovas, Beatriz; Lewis, Morag; Gasparini, Paolo; Steel, Karen P (PLoS One, 2014)
Considerable progress has been made in identifying deafness genes, but still little is known about the genetic basis of normal variation in hearing function. We recently carried out a Genome Wide Association Study (GWAS) of quantitative hearing traits in southern European populations and found several SNPs with suggestive but none with significant association. In the current study, we followed up these SNPs to investigate which of them might show a genuine association with auditory function using alternative approaches. Firstly, we generated a shortlist of 19 genes from the published GWAS results. Secondly, we carried out immunocytochemistry to examine expression of these 19 genes in the mouse inner ear. Twelve of them showed distinctive cochlear expression patterns. Four showed expression restricted to sensory hair cells (Csmd1, Arsg, Slc16a6 and Gabrg3), one only in marginal cells of the stria vascularis (Dclk1) while the others (Ptprd, Grm8, GlyBP, Evi5, Rimbp2, Ank2, Cdh13) in multiple cochlear cell types. In the third step, we tested these 12 genes for replication of association in an independent set of samples from the Caucasus and Central Asia. Nine out of them showed nominally significant association (p<0.05). In particular, 4 were replicated at the same SNP and with the same effect direction while the remaining 5 showed a significant association in a gene-based test. Finally, to look for genotype-phenotype relationship, the audiometric profiles of the three genotypes of the most strongly associated gene variants were analyzed. Seven out of the 9 replicated genes (CDH13, GRM8, ANK2, SLC16A6, ARSG, RIMBP2 and DCLK1) showed an audiometric pattern with differences between different genotypes further supporting their role in hearing function. These data demonstrate the usefulness of this multistep approach in providing new insights into the molecular basis of hearing and may suggest new targets for treatment and prevention of hearing impairment.
Keywords: Adult; Animals; DNA Replication; Gene Expression Profiling; Genome-Wide Association Study; Genotype; Hair Cells, Auditory; Hearing; Humans; Mice; Phenotype; Polymorphism, Single Nucleotide; Stria Vascularis

F402L variant in NLRP12 in subjects with undiagnosed periodic fevers and in healthy controls. - De Pieri, Carlo; Vuch, Josef; Athanasakis, Emmanouil; Severini, Giovanni Maria; Crovella, Sergio; Bianco, Anna Monica; Tommasini, Alberto (Clin Exp Rheumatol, 2014)
Keywords: Cryopyrin-Associated Periodic Syndromes; Female; Humans; Intracellular Signaling Peptides and Proteins; Male; Mutation

From tube to breast: the bridging role of semi-demand breastfeeding. - Davanzo, Riccardo; Strajn, Tamara; Kennedy, Jacqueline; Crocetta, Anna; De Cunto, Angela (J Hum Lact, 2014)
Determination of the optimal timing of breastfeeding initiation for preterm infants is still a challenge for health professionals. Often unjustified delays and restrictions of breastfeeding occur due to non-evidence-based current opinions about preterm infants' feeding capacity. Semi-demand feeding has been proposed for preterm infants during the transition from scheduled to full demand feeding, to promote the establishment of self-regulated oral feeding. Although semi-demand feeding has been shown to be safe and effective in reducing time to reaching oral feeding, the implementation of this feeding pattern for preterm infants in the neonatal intensive care unit (NICU) is still limited. We developed a protocol for the application of semi-demand feeding in preterm infants based on the existing knowledge of preterm infant neurodevelopment and NICU organization and staff experience. The protocol's aim is to attain successful transition from tube feeding to breastfeeding. In this article, we describe the protocol used in the neonatal unit of the Maternal and Child Health Institute of Trieste, a third level care center in northeastern Italy.

A general approach for haplotype phasing across the full spectrum of relatedness. - O'Connell, Jared; Gurdasani, Deepti; Delaneau, Olivier; Pirastu, Nicola; Ulivi, Sheila; Cocca, Massimiliano; Traglia, Michela; Huang, Jie; Huffman, Jennifer E; Rudan, Igor; McQuillan, Ruth; Fraser, Ross M; et al. (PLoS Genet, 2014)
Many existing cohorts contain a range of relatedness between genotyped individuals, either by design or by chance. Haplotype estimation in such cohorts is a central step in many downstream analyses. Using genotypes from six cohorts from isolated populations and two cohorts from non-isolated populations, we have investigated the performance of different phasing methods designed for nominally 'unrelated' individuals. We find that SHAPEIT2 produces much lower switch error rates in all cohorts compared to other methods, including those designed specifically for isolated populations. In particular, when large amounts of IBD sharing is present, SHAPEIT2 infers close to perfect haplotypes. Based on these results we have developed a general strategy for phasing cohorts with any level of implicit or explicit relatedness between individuals. First SHAPEIT2 is run ignoring all explicit family information. We then apply a novel HMM method (duoHMM) to combine the SHAPEIT2 haplotypes with any family information to infer the inheritance pattern of each meiosis at all sites across each chromosome. This allows the correction of switch errors, detection of recombination events and genotyping errors. We show that the method detects numbers of recombination events that align very well with expectations based on genetic maps, and that it infers far fewer spurious recombination events than Merlin. The method can also detect genotyping errors and infer recombination events in otherwise uninformative families, such as trios and duos. The detected recombination events can be used in association scans for recombination phenotypes. The method provides a simple and unified approach to haplotype estimation, that will be of interest to researchers in the fields of human, animal and plant genetics.
Keywords: Chromosome Mapping; Cohort Effect; Family; Genotype; Haplotypes; Humans; Models, Genetic; Pedigree; Phenotype; Recombination, Genetic

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genome-wide association study of sexual maturation in males and females highlights a role for body mass and menarche loci in male puberty. - Cousminer, Diana L; Stergiakouli, Evangelia; Berry, Diane J; Ang, Wei; Groen-Blokhuis, Maria M; Körner, Antje; Siitonen, Niina; Ntalla, Ioanna; Marinelli, Marcella; Perry, John R B; Kettunen, Johannes; Jansen, Rick; et al. (Hum Mol Genet, 2014)
Little is known about genes regulating male puberty. Further, while many identified pubertal timing variants associate with age at menarche, a late manifestation of puberty, and body mass, little is known about these variants' relationship to pubertal initiation or tempo. To address these questions, we performed genome-wide association meta-analysis in over 11 000 European samples with data on early pubertal traits, male genital and female breast development, measured by the Tanner scale. We report the first genome-wide significant locus for male sexual development upstream of myocardin-like 2 (MKL2) (P = 8.9 × 10(-9)), a menarche locus tagging a developmental pathway linking earlier puberty with reduced pubertal growth (P = 4.6 × 10(-5)) and short adult stature (p = 7.5 × 10(-6)) in both males and females. Furthermore, our results indicate that a proportion of menarche loci are important for pubertal initiation in both sexes. Consistent with epidemiological correlations between increased prepubertal body mass and earlier pubertal timing in girls, body mass index (BMI)-increasing alleles correlated with earlier breast development. In boys, some BMI-increasing alleles associated with earlier, and others with delayed, sexual development; these genetic results mimic the controversy in epidemiological studies, some of which show opposing correlations between prepubertal BMI and male puberty. Our results contribute to our understanding of the pubertal initiation program in both sexes and indicate that although mechanisms regulating pubertal onset in males and females may largely be shared, the relationship between body mass and pubertal timing in boys may be complex and requires further genetic studies.

Global, regional, and national incidence and mortality for HIV, tuberculosis, and malaria during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Murray, Christopher J L; Ortblad, Katrina F; Guinovart, Caterina; Lim, Stephen S; Wolock, Timothy M; Roberts, D Allen; Dansereau, Emily A; Graetz, Nicholas; Barber, Ryan M; Brown, Jonathan C; Wang, Haidong; Duber, Herbert C; et al. (Lancet, 2014)
BACKGROUND: The Millennium Declaration in 2000 brought special global attention to HIV, tuberculosis, and malaria through the formulation of Millennium Development Goal (MDG) 6. The Global Burden of Disease 2013 study provides a consistent and comprehensive approach to disease estimation for between 1990 and 2013, and an opportunity to assess whether accelerated progress has occured since the Millennium Declaration. METHODS: To estimate incidence and mortality for HIV, we used the UNAIDS Spectrum model appropriately modified based on a systematic review of available studies of mortality with and without antiretroviral therapy (ART). For concentrated epidemics, we calibrated Spectrum models to fit vital registration data corrected for misclassification of HIV deaths. In generalised epidemics, we minimised a loss function to select epidemic curves most consistent with prevalence data and demographic data for all-cause mortality. We analysed counterfactual scenarios for HIV to assess years of life saved through prevention of mother-to-child transmission (PMTCT) and ART. For tuberculosis, we analysed vital registration and verbal autopsy data to estimate mortality using cause of death ensemble modelling. We analysed data for corrected case-notifications, expert opinions on the case-detection rate, prevalence surveys, and estimated cause-specific mortality using Bayesian meta-regression to generate consistent trends in all parameters. We analysed malaria mortality and incidence using an updated cause of death database, a systematic analysis of verbal autopsy validation studies for malaria, and recent studies (2010-13) of incidence, drug resistance, and coverage of insecticide-treated bednets. FINDINGS: Globally in 2013, there were 1·8 million new HIV infections (95% uncertainty interval 1·7 million to 2·1 million), 29·2 million prevalent HIV cases (28·1 to 31·7), and 1·3 million HIV deaths (1·3 to 1·5). At the peak of the epidemic in 2005, HIV caused 1·7 million deaths (1·6 million to 1·9 million). Concentrated epidemics in Latin America and eastern Europe are substantially smaller than previously estimated. Through interventions including PMTCT and ART, 19·1 million life-years (16·6 million to 21·5 million) have been saved, 70·3% (65·4 to 76·1) in developing countries. From 2000 to 2011, the ratio of development assistance for health for HIV to years of life saved through intervention was US$4498 in developing countries. Including in HIV-positive individuals, all-form tuberculosis incidence was 7·5 million (7·4 million to 7·7 million), prevalence was 11·9 million (11·6 million to 12·2 million), and number of deaths was 1·4 million (1·3 million to 1·5 million) in 2013. In the same year and in only individuals who were HIV-negative, all-form tuberculosis incidence was 7·1 million (6·9 million to 7·3 million), prevalence was 11·2 million (10·8 million to 11·6 million), and number of deaths was 1·3 million (1·2 million to 1·4 million). Annualised rates of change (ARC) for incidence, prevalence, and death became negative after 2000. Tuberculosis in HIV-negative individuals disproportionately occurs in men and boys (versus women and girls); 64·0% of cases (63·6 to 64·3) and 64·7% of deaths (60·8 to 70·3). Globally, malaria cases and deaths grew rapidly from 1990 reaching a peak of 232 million cases (143 million to 387 million) in 2003 and 1·2 million deaths (1·1 million to 1·4 million) in 2004. Since 2004, child deaths from malaria in sub-Saharan Africa have decreased by 31·5% (15·7 to 44·1). Outside of Africa, malaria mortality has been steadily decreasing since 1990. INTERPRETATION: Our estimates of the number of people living with HIV are 18·7% smaller than UNAIDS's estimates in 2012. The number of people living with malaria is larger than estimated by WHO. The number of people living with HIV, tuberculosis, or malaria have all decreased since 2000. At the global level, upward trends for malaria and HIV deaths have been reversed and declines in tuberculosis deaths have accelerated. 101 countries (74 of which are developing) still have increasing HIV incidence. Substantial progress since the Millennium Declaration is an encouraging sign of the effect of global action. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Epidemics; Female; Global Health; HIV Infections; Humans; Incidence; Malaria; Male; Mortality; Organizational Objectives; Sex Distribution; Tuberculosis

Global, regional, and national levels and causes of maternal mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Kassebaum, Nicholas J; Bertozzi-Villa, Amelia; Coggeshall, Megan S; Shackelford, Katya A; Steiner, Caitlyn; Heuton, Kyle R; Gonzalez-Medina, Diego; Barber, Ryan; Huynh, Chantal; Dicker, Daniel; Templin, Tara; Wolock, Timothy M; et al. (Lancet, 2014)
BACKGROUND: The fifth Millennium Development Goal (MDG 5) established the goal of a 75% reduction in the maternal mortality ratio (MMR; number of maternal deaths per 100,000 livebirths) between 1990 and 2015. We aimed to measure levels and track trends in maternal mortality, the key causes contributing to maternal death, and timing of maternal death with respect to delivery. METHODS: We used robust statistical methods including the Cause of Death Ensemble model (CODEm) to analyse a database of data for 7065 site-years and estimate the number of maternal deaths from all causes in 188 countries between 1990 and 2013. We estimated the number of pregnancy-related deaths caused by HIV on the basis of a systematic review of the relative risk of dying during pregnancy for HIV-positive women compared with HIV-negative women. We also estimated the fraction of these deaths aggravated by pregnancy on the basis of a systematic review. To estimate the numbers of maternal deaths due to nine different causes, we identified 61 sources from a systematic review and 943 site-years of vital registration data. We also did a systematic review of reports about the timing of maternal death, identifying 142 sources to use in our analysis. We developed estimates for each country for 1990-2013 using Bayesian meta-regression. We estimated 95% uncertainty intervals (UIs) for all values. FINDINGS: 292,982 (95% UI 261,017-327,792) maternal deaths occurred in 2013, compared with 376,034 (343,483-407,574) in 1990. The global annual rate of change in the MMR was -0·3% (-1·1 to 0·6) from 1990 to 2003, and -2·7% (-3·9 to -1·5) from 2003 to 2013, with evidence of continued acceleration. MMRs reduced consistently in south, east, and southeast Asia between 1990 and 2013, but maternal deaths increased in much of sub-Saharan Africa during the 1990s. 2070 (1290-2866) maternal deaths were related to HIV in 2013, 0·4% (0·2-0·6) of the global total. MMR was highest in the oldest age groups in both 1990 and 2013. In 2013, most deaths occurred intrapartum or postpartum. Causes varied by region and between 1990 and 2013. We recorded substantial variation in the MMR by country in 2013, from 956·8 (685·1-1262·8) in South Sudan to 2·4 (1·6-3·6) in Iceland. INTERPRETATION: Global rates of change suggest that only 16 countries will achieve the MDG 5 target by 2015. Accelerated reductions since the Millennium Declaration in 2000 coincide with increased development assistance for maternal, newborn, and child health. Setting of targets and associated interventions for after 2015 will need careful consideration of regions that are making slow progress, such as west and central Africa. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Cause of Death; Female; Global Health; HIV Infections; Humans; Maternal Mortality; Models, Statistical; Organizational Objectives; Pregnancy; Pregnancy Complications, Infectious; Risk Factors; Socioeconomic Factors; Time Factors

Global, regional, and national levels of neonatal, infant, and under-5 mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Wang, Haidong; Liddell, Chelsea A; Coates, Matthew M; Mooney, Meghan D; Levitz, Carly E; Schumacher, Austin E; Apfel, Henry; Iannarone, Marissa; Phillips, Bryan; Lofgren, Katherine T; Sandar, Logan; Dorrington, Rob E; et al. (Lancet, 2014)
BACKGROUND: Remarkable financial and political efforts have been focused on the reduction of child mortality during the past few decades. Timely measurements of levels and trends in under-5 mortality are important to assess progress towards the Millennium Development Goal 4 (MDG 4) target of reduction of child mortality by two thirds from 1990 to 2015, and to identify models of success. METHODS: We generated updated estimates of child mortality in early neonatal (age 0-6 days), late neonatal (7-28 days), postneonatal (29-364 days), childhood (1-4 years), and under-5 (0-4 years) age groups for 188 countries from 1970 to 2013, with more than 29,000 survey, census, vital registration, and sample registration datapoints. We used Gaussian process regression with adjustments for bias and non-sampling error to synthesise the data for under-5 mortality for each country, and a separate model to estimate mortality for more detailed age groups. We used explanatory mixed effects regression models to assess the association between under-5 mortality and income per person, maternal education, HIV child death rates, secular shifts, and other factors. To quantify the contribution of these different factors and birth numbers to the change in numbers of deaths in under-5 age groups from 1990 to 2013, we used Shapley decomposition. We used estimated rates of change between 2000 and 2013 to construct under-5 mortality rate scenarios out to 2030. FINDINGS: We estimated that 6·3 million (95% UI 6·0-6·6) children under-5 died in 2013, a 64% reduction from 17·6 million (17·1-18·1) in 1970. In 2013, child mortality rates ranged from 152·5 per 1000 livebirths (130·6-177·4) in Guinea-Bissau to 2·3 (1·8-2·9) per 1000 in Singapore. The annualised rates of change from 1990 to 2013 ranged from -6·8% to 0·1%. 99 of 188 countries, including 43 of 48 countries in sub-Saharan Africa, had faster decreases in child mortality during 2000-13 than during 1990-2000. In 2013, neonatal deaths accounted for 41·6% of under-5 deaths compared with 37·4% in 1990. Compared with 1990, in 2013, rising numbers of births, especially in sub-Saharan Africa, led to 1·4 million more child deaths, and rising income per person and maternal education led to 0·9 million and 2·2 million fewer deaths, respectively. Changes in secular trends led to 4·2 million fewer deaths. Unexplained factors accounted for only -1% of the change in child deaths. In 30 developing countries, decreases since 2000 have been faster than predicted attributable to income, education, and secular shift alone. INTERPRETATION: Only 27 developing countries are expected to achieve MDG 4. Decreases since 2000 in under-5 mortality rates are accelerating in many developing countries, especially in sub-Saharan Africa. The Millennium Declaration and increased development assistance for health might have been a factor in faster decreases in some developing countries. Without further accelerated progress, many countries in west and central Africa will still have high levels of under-5 mortality in 2030. FUNDING: Bill & Melinda Gates Foundation, US Agency for International Development.
Keywords: Child Mortality; Child, Preschool; Global Health; Humans; Infant; Infant Mortality; Infant, Newborn; Organizational Objectives; Risk Factors; Socioeconomic Factors

HLA-G 14 bp deletion/insertion polymorphism and mother-to-child transmission of HIV. - Segat, L; Zupin, L; Kim, H-Y; Catamo, E; Thea, D M; Kankasa, C; Aldrovandi, G M; Kuhn, L; Crovella, S (Tissue Antigens, 2014)
The human leukocyte antigen HLA-G, highly expressed at the maternal-fetal interface, has a pivotal role in mediating immune tolerance. In this study we investigated the influence of HLA-G 14 bp insertion polymorphism in human immunodeficiency virus (HIV)-1 mother-to-child HIV-1 transmission. The 14 bp insertion polymorphism was analyzed among 99 HIV-1 positive mothers and 329 infants born to HIV-positive mothers in Zambia, among whom vertical transmission status and timing had been determined. HLA-G 14 bp insertion polymorphism was detected using a custom TaqMan single nucleotide polymorphisms (SNPs) genotyping assay. Logistic regression was conducted to examine the associations between HLA-G alleles and the risk of HIV transmission. The 14 bp insertion allele was more frequent in HIV exposed-uninfected (EU) infants than in infected infants, and was associated with reduced risk of both in utero (IU) and intrapartum (IP) HIV transmission, after adjusting for maternal cluster of differentiation 4 (CD4) cell count and plasma viral load. Maternal HLA-G 14 bp insertion genotype and HLA-G concordance between mother and child were not associated with the risk of perinatal HIV transmission. The presence of the 14 bp insertion associates with protection toward IU and IP HIV infection in children from Zambia, suggesting that HLA-G could be involved in the vertical transmission of HIV.
Keywords: Adult; Alleles; Base Pairing; Child; Genotype; HIV Infections; HLA-G Antigens; Humans; INDEL Mutation; Infant; Infectious Disease Transmission, Vertical; Mothers; Polymorphism, Genetic; Young Adult

HLA-G gene polymorphisms associated with susceptibility to rheumatoid arthritis disease and its severity in Brazilian patients. - Catamo, E; Addobbati, C; Segat, L; Sotero Fragoso, T; Domingues Barbosa, A; Tavares Dantas, A; de Ataíde Mariz, H; F da Rocha, L; Branco Pinto Duarte, A L; Monasta, L; Sandrin-Garcia, P; Crovella, S (Tissue Antigens, 2014)
We analyzed the possible association between human leukocyte antigen-G (HLA-G) genetic variants, supposed to regulate HLA-G expression, and the susceptibility to develop rheumatoid arthritis (RA) as well as its clinical manifestations. The 5'upstream regulatory region (5'URR) and 3'untranslated region (3'UTR) regions of the HLA-G gene were screened in 127 RA patients and 128 controls: 10 5'URR and 3 3'UTR HLA-G polymorphisms as well as two haplotypes were associated with risk for RA development, while a polymorphism in the 5'URR showed an association with the degree of disease activity. These findings, although the number of cases analyzed is limited and the P-values are modest, indicate a possible association between HLA-G gene polymorphisms and susceptibility to develop RA disease and its severity.
Keywords: 3' Untranslated Regions; 5' Flanking Region; Aged; Arthritis, Rheumatoid; Brazil; Disease Progression; DNA Mutational Analysis; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Haplotypes; HLA-G Antigens; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk

HPV and Chlamydia trachomatis co-detection in young asymptomatic women from high incidence area for cervical cancer. - Bellaminutti, Serena; Seraceni, Silva; De Seta, Francesco; Gheit, Tarik; Tommasino, Massimo; Comar, Manola (J Med Virol, 2014)
Chlamydia trachomatis causing chronic inflammatory diseases has investigated as possible human papillomavirus (HPV) cofactor in cervical cancer. The aim of this study is to evaluate the prevalence of Chlamydia trachomatis and HPV co-infection in different cohorts of asymptomatic women from a Northern Italy area at high incidence for cervical cancer. Cervical samples from 441 females were collected from Cervical Cancer Screening Program, Sexually Transmitted Infectious and Assisted Reproductive Technology centres. HPV and Chlamydia trachomatis were detected simultaneously and genotyped using a highly sensitive bead based assay. The overall prevalence of Chlamydia trachomatis was estimated 9.7%, in contrast with the reported national data of 2.3%, and co-infection with HPV was diagnosed in the 17% of the samples. In females ≤ 25 years of age, the infection reached a peak of 22% and co-infection with HPV of 45.8% (P < 0.001). Of note, in young females diagnosed with low grade cervical lesions, no significant difference between Chlamydia trachomatis and HPV distribution was observed, while differently, HPV co-infection was found significantly associated to the presence of intraepithelial lesions when compared to older females (20% vs. 1%; P < 0.001). In this study, the use of a high sensitive molecular technique exhibited higher analytical sensitivity than the referred assays for the diagnosis of Chlamydia trachomatis and HPV co-infection in asymptomatic females, leading to reduction of the potential to identify incorrectly the infection status. An active screening for timely treatment of Chlamydia trachomatis infection is suggested in young females to evaluate a possible decrease in incidence of pre-cancer intraepithelial lesions.
Keywords: Adolescent; Adult; Age Factors; Cervix Uteri; Chlamydia Infections; Chlamydia trachomatis; Coinfection; Female; Genotype; Humans; Incidence; Italy; Middle Aged; Papillomaviridae; Papillomavirus Infections; Prevalence; Young Adult

Human recombinant lysozyme downregulates advanced glycation endproduct-induced interleukin-6 production and release in an in-vitro model of human proximal tubular epithelial cells. - Gallo, Davide; Cocchietto, Moreno; Masat, Elisa; Agostinis, Chiara; Harei, Elisa; Veronesi, Paolo; Sava, Gianni (Exp Biol Med (Maywood), 2014)
Diabetic nephropathy is the leading cause of chronic renal disease and one of the major causes of cardiovascular mortality. Evidence suggests that its progression is due to the chronic hyperglycemia consequent to the production and accumulation of advanced glycation endproducts (AGEs). Lysozyme was shown to posses AGE-sequestering properties and the capacity to reduce the severity of the early stage manifestations of the diabetic nephropathy. This study was aimed to contribute to the understanding the molecular mechanisms of lysozyme effectiveness in the diabetic nephropathy, using an in-vitro cellular model, represented by the HK-2 cells, human proximal tubular epithelial cells. Lysozyme significantly reduced the AGE-induced IL-6 mRNA and an ELISA assay showed also a decreased release of the functional protein with a dose-dependent trend. In addition, lysozyme prevented macrophage recruitment, suggesting its capacity to elicit an anti-inflammatory action. We may conclude that the protective action of lysozyme on the nephrotoxic effects of AGE may depend, at least in part, on its ability to prevent the production and release of inflammatory mediators, such as IL-6 and to reduce macrophage recruitment in the inflammatory sites.
Keywords: Cell Line; Cell Movement; Cell Survival; Chemokine CX3CL1; Diabetic Nephropathies; Down-Regulation; Epithelial Cells; Glycosylation End Products, Advanced; Humans; Inflammation Mediators; Interleukin-18; Interleukin-6; Kidney Tubules, Proximal; Macrophage Activation; Macrophages; Muramidase; Recombinant Proteins; RNA, Messenger; Tumor Necrosis Factor-alpha; U937 Cells

The implications of diagnosis of small for gestational age fetuses using European and South Asian growth charts: an outcome-based comparative study. - Maso, Gianpaolo; Jayawardane, Mathota A M M; Alberico, Salvatore; Piccoli, Monica; Senanayake, Hemantha M (ScientificWorldJournal, 2014)
The antenatal condition of small for gestational age (SGA) is significantly associated with perinatal morbidity and mortality and it is known that there are significant differences in birth weight and fetal size among different populations. The aim of our study was to assess the impact on outcomes of the diagnosis of SGA according to Bangladeshi and European antenatal growth charts in Sri Lankan population. The estimated fetal weight before delivery was retrospectively reviewed according to Bangladeshi and European growth references. Three groups were identified: Group 1-SGA according to Bangladeshi growth chart; Group 2-SGA according to European growth chart but not having SGA according to Bangladeshi growth chart; Group 3-No SGA according to both charts. There was a difference in prevalence of SGA between Bangladeshi and European growth charts: 12.7% and 51.7%, respectively. There were statistically significant higher rates in emergency cesarean section, fetal distress in labour, and intrauterine death (P < 0.001) in Group 1 compared with Group, 2 and 3. No differences of outcomes occurred between Groups 2 and 3. Our study demonstrated that only cases diagnosed as SGA according to population-based growth charts are at risk of adverse outcome. The use of inappropriate prenatal growth charts might lead to misdiagnosis and potential unnecessary interventions.
Keywords: Asian Continental Ancestry Group; Bangladesh; Birth Weight; Europe; European Continental Ancestry Group; Female; Fetal Growth Retardation; Growth Charts; Humans; Infant, Newborn; Infant, Small for Gestational Age; Pregnancy; Prognosis; Sri Lanka

In vitro endothelial cell proliferation assay reveals distinct levels of proangiogenic cytokines characterizing sera of healthy subjects and of patients with heart failure. - Voltan, Rebecca; Zauli, Giorgio; Rizzo, Paola; Fucili, Alessandro; Pannella, Micaela; Marci, Roberto; Tisato, Veronica; Ferrari, Roberto; Secchiero, Paola (Mediators Inflamm, 2014)
Although myocardial angiogenesis is thought to play an important role in heart failure (HF), the involvement of circulating proinflammatory and proangiogenic cytokines in the pathogenesis and/or prognosis of HF has not been deeply investigated. By using a highly standardized proliferation assay with human endothelial cells, we first demonstrated that sera from older (mean age 52 ± 7.6 years; n = 46) healthy donors promoted endothelial cell proliferation to a significantly higher extent compared to sera obtained from younger healthy donors (mean age 29 ± 8.6 years; n = 20). The promotion of endothelial cell proliferation was accompanied by high serum levels of several proangiogenic cytokines. When we assessed endothelial cell proliferation in response to HF patients' sera, we observed that a subset of sera (n = 11) promoted cell proliferation to a significantly lesser extent compared to the majority of sera (n = 18). Also, in this case, the difference between the patient groups in the ability to induce endothelial cell proliferation correlated to significant (P < 0.05) differences in serum proangiogenic cytokine levels. Unexpectedly, HF patients associated to the highest endothelial proliferation index showed the worst prognosis as evaluated in terms of subsequent cardiovascular events in the follow-up, suggesting that high levels of circulating proangiogenic cytokines might be related to a worse prognosis.
Keywords: Adult; Cell Proliferation; Cells, Cultured; Chemokines; Cytokines; Heart Failure; Human Umbilical Vein Endothelial Cells; Humans; Middle Aged; Neovascularization, Pathologic; Prognosis

Influence of HLA-G polymorphisms in human immunodeficiency virus infection and hepatitis C virus co-infection in Brazilian and Italian individuals. - da Silva, G K; Vianna, Priscila; Veit, Tiago Degani; Crovella, Sergio; Catamo, Eulalia; Cordero, Elvira Alicia Aparicio; Mattevi, Vanessa Suñé; Lazzaretti, Rosmeri Kuhmmer; Sprinz, Eduardo; Kuhmmer, Regina; Chies, José Artur Bogo (Infect Genet Evol, 2014)
OBJECTIVE: This study aimed to investigate the role of Human Leukocyte Antigen (HLA)-G in the susceptibility to HIV-1 infection through the analysis of the HLA-G 3' untranslated region (UTR) polymorphisms 14 bp insertion/deletion (rs66554220) and +3142C>G (rs1063320). DESIGN: We analyzed 582 HIV-1 infected patients and 626 uninfected individuals from Brazil and Italy in a case-control study. METHODS: HLA-G polymorphisms were genotyped using PCR, PCR-RFLP assays or direct sequencing. All analyses were stratified by ethnicity. Genotypic, allelic and diplotypic frequencies were compared between HIV-1 infected subjects and controls using Chi-square or Fischer exact tests. Also, haplotypic frequencies were estimated using MLocus software. RESULTS: African-derived HIV-infected individuals presented a higher frequency of the 14 bp insertion allele as compared to non-infected individuals (0.468 versus 0.373, respectively; p(Bonf) = 0.010). A higher frequency of the 14 bp insertion +3142G (insG) haplotype (0.456 versus 0.346, p<0.001) and the insG/insG diplotype (OR=1.88, 95%CI = 1.08-3.23, p=0.021) was observed among African-derived patients as compared to uninfected controls. Also, we observed a higher frequency of the ins/ins genotype among African-derived HIV patients co-infected with HCV (OR=2.78, 95%CI = 1.20-6.49, p = 0.008). CONCLUSIONS: Our data point out to an increased frequency of alleles and genotypes associated with low HLA-G expression among African-derived patients, suggesting a potential role for HLA-G in the susceptibility to HIV-1 infection and HCV co-infection in those individuals.
Keywords: 3' Untranslated Regions; Adolescent; Adult; African Continental Ancestry Group; Aged; Brazil; Coinfection; Gene Frequency; Genetic Variation; Haplotypes; Hepatitis C; HIV Infections; HLA-G Antigens; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

Influence of urine volume on the assessment of intestinal permeability in affected children by multiple sugar probes. - Addobbati, Riccardo; Pascolo, Lorella; Di Toro, Nicola; Sebastiani, Giulia B; Martellossi, Stefano; Not, Tarcisio (Clin Chem Lab Med, 2014)
BACKGROUND: In this study we have looked at the reliability of a multi-sugar test in a pediatric patient population and its accuracy at small urine volumes to evaluate intestinal permeability. METHODS: Out of 117 subjects enrolled, 31 were healthy and 86 were sick. A solution containing lactulose, rhamnose, sucrose, and sucralose was administered to subjects who were on fasting; the urine excreted during 5 h was collected and measured. Samples were analyzed by gas chromatography-tandem mass spectrometry and results were expressed as percentage of sugar recoveries and lactulose/rhamnose (L/R) ratio. RESULTS: The analyses showed a clear effect of low urinary volumes (≤240 mL) particularly affecting rhamnose excretion in healthy subjects and sucrose and sucralose recovery in diseased children. Despite the low rhamnose recovery, as lactulose is not similarly affected, the diagnostic reliability of L/R ratio is well preserved at low diuresis conditions. However, this ratio can be useful to discriminate acute conditions vs. clinical remissions only at high urine volumes. Data also suggest potential diagnostic applicability of sucrose and sucralose in children at high urine volumes. CONCLUSIONS: In conclusion, the multi-sugar test has a good predictivity in pediatric subjects but results must be carefully interpreted in the face of reduced diuresis.
Keywords: Carbohydrates; Child, Preschool; Diuresis; Female; Gas Chromatography-Mass Spectrometry; Gastrointestinal Diseases; Humans; Infant; Intestines; Lactulose; Male; Permeability; Rhamnose; Sucrose

Informed consent, and an ethico-legal framework for paediatric observational research and biobanking: the experience of an Italian birth cohort study. - Toccaceli, Virgilia; Serino, Laura; Stazi, Maria Antonietta (Cell Tissue Bank, 2014)
Birth cohort studies are important tools for life-course epidemiology, given the spectrum of the environmental, behavioural, and genetic factors that should be considered when making judgements on human health. Biobanks are valuable components of studies designed to investigate the genetic variability of diseases and improve phenotypic characterisation. In studies involving vulnerable populations and biobanks, it is essential to provide ethical reasoning and analyse the legal requirements. We describe the processes and the tools used in the iterative design of an appropriate informed consent model and the ethico-legal framework of the Piccolipiù study. The Piccolipiù study is a prospective population-based study funded by the Italian Ministry of Health that intends to enrol 3,000 newborns and their mothers in five Italian cities, and to store biological samples for future use. To realise these objectives, we performed a thorough evaluation of the literature, of national and international guidelines, and of the impact of the Italian legal requirements for research biobanking. Discussions among stakeholders facilitated the design of the informed consent and the ethico-legal framework. Several topics are addressed, including the suitability of a broad informed consent for paediatric biobanks, infant vulnerability, access to and sharing of data, and the disclosure of individual's genetic results. Discussion of the ethical and legal procedures adopted in epidemiological biobanking might be a fruitful ground for comparison both at the national level, where standardization and homogeneity are lacking, and at the international level, where different regulatory issues are often in the background and might hamper research biobanks networking.
Keywords: Cohort Studies; Confidentiality; Databases, Genetic; Genetic Privacy; Genetic Research; Genotype; Humans; Infant, Newborn; Information Dissemination; Informed Consent; Internationality; Italy; Parents; Phenotype

Insight into genetic determinants of resting heart rate. - Mezzavilla, Massimo; Iorio, Annamaria; Bobbo, Marco; D'Eustacchio, Angela; Merlo, Marco; Gasparini, Paolo; Ulivi, Sheila; Sinagra, Gianfranco (Gene, 2014)
BACKGROUND: Recent studies suggested that resting heart rate (RHR) might be an independent predictor of cardiovascular mortality and morbidity. Nonetheless, the interrelation between RHR and cardiovascular diseases is not clear. In order to resolve this puzzle, the importance of genetic determinants of RHR has been recently suggested, but it needs to be further investigated. OBJECTIVE: The aim of this study was to estimate the contribution of common genetic variations on RHR using Genome Wide Association Study. METHODS: We performed a Genome Wide Association Study in an isolated population cohort of 1737 individuals, the Italian Network on Genetic Isolates - Friuli Venezia Giulia (INGI-FVG). Moreover, a haplotype analysis was performed. A regression tree analysis was run to highlight the effect of each haplotype combination on the phenotype. RESULTS: A significant level of association (p<5 × 10(-8)) was detected for Single Nucleotide Polymorphisms (SNPs) in two genes expressed in the heart: MAML1 and CANX. Founding that the three different variants of the haplotype, which encompass both genes, yielded a phenotypic correlation. Indeed, a haplotype in homozygosity is significantly associated with the lower quartile of RHR (RHR ≤ 58 bpm). Moreover no significant association was found between cardiovascular risk factors and the different haplotype combinations. CONCLUSION: Mastermind-like 1 and Calnexin were found to be associated with RHR. We demonstrated a relation between a haplotype and the lower quartile of RHR in our populations. Our findings highlight that genetic determinants of RHR may be implicated in determining cardiovascular diseases and could allow a better risk stratification.
Keywords: Calnexin; Cardiovascular Diseases; DNA-Binding Proteins; Female; Genome-Wide Association Study; Haplotypes; Heart Rate; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Transcription Factors

Interleukin-10 gene promoter polymorphisms in celiac patients from north-eastern Italy. - Zupin, Luisa; Polesello, Vania; Catamo, Eulalia; Crovella, Sergio; Segat, Ludovica (Hum Immunol, 2014)
Celiac disease is a complex chronic intestinal disorder driven by an immune response against the gliadin fraction of gluten: many factors are involved in the pathogenesis of the disease, and among these Interleukin-10 could play an important role. In the present study, the -1082A>G, -819T>C and -592A>C IL10 functional polymorphisms were analyzed in 565 celiac patients and 576 healthy controls from north-eastern Italy, stratified for HLA class II celiac disease risk haplotypes. No significant differences were observed for the three IL10 polymorphisms distribution between celiac patients and controls with the exception of a slightly increased risk for the -1082A allele in HLA-DQ8 male individuals. Although our findings suggest that the IL10 genetic variants analyzed do not have a major role in the susceptibility to the development of celiac disease in north-eastern Italian patients, we think that the possible involvement of IL10 gene in CD should deserve further investigation and that large-scale studies are recommended to confirm our findings.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alleles; Case-Control Studies; Celiac Disease; Child; Child, Preschool; European Continental Ancestry Group; Female; Gene Frequency; HLA-DQ Antigens; Humans; Interleukin-10; Italy; Male; Middle Aged; Models, Genetic; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Risk Factors; Sex Factors

Inverse correlation between circulating levels of TNF-related apoptosis-inducing ligand and 17β-estradiol. - Zauli, Giorgio; Tisato, Veronica; Melloni, Elisabetta; Volpato, Stefano; Cervellati, Carlo; Bonaccorsi, Gloria; Radillo, Oriano; Marci, Roberto; Secchiero, Paola (J Clin Endocrinol Metab, 2014)
CONTEXT: The regulation of the circulating levels of TNF-related apoptosis-inducing ligand (TRAIL), a cytokine of the TNF family, playing a key role in the immune surveillance against cancer, is incompletely understood. OBJECTIVE: The objective of the study was to investigate the potential link between TRAIL and 17β-estradiol. DESIGN, SETTING, AND PARTICIPANTS: Circulating TRAIL levels were measured by an ELISA in plasma samples (n = 246) of healthy, age-matched (range 30-70 y) men and women and in the sera (n = 180) of females belonging to different physiopathological conditions (childhood, pregnancy, under gonadotropin treatment, menopause) characterized by different levels of circulating 17β-estradiol. RESULTS: TRAIL plasma levels in women with aged younger than 50 years were significantly lower compared with age-matched men, whereas in woman 50 years old or older, TRAIL levels were significantly higher compared with the age-matched men and with the younger women. Moreover, an analysis of women with different conditions revealed a significant inverse correlation between the serum levels of TRAIL and 17β-estradiol, with the lowest levels of TRAIL being observed during pregnancy and the highest in childhood and in postmenopausal women. Moreover, gonadotropin treatment in women undergoing assisted reproduction was accompanied by an acute decrease of serum TRAIL levels. Finally, in vitro treatment with 17β-estradiol decreased the TRAIL expression levels in peripheral blood mononuclear cells. CONCLUSIONS: Our data suggest that 17β-estradiol plays a role in regulating TRAIL circulating levels. The demonstration that postmenopausal women exhibit the highest TRAIL levels is of particular interest in light of a previous large study population showing that TRAIL is positively correlated to the overall survival.
Keywords: Adult; Aged; Case-Control Studies; Child; Child, Preschool; Estradiol; Female; Humans; Infant; Male; Middle Aged; Pregnancy; Sex Factors; TNF-Related Apoptosis-Inducing Ligand; Young Adult

Lactobacillus plantarum P17630 for preventing Candida vaginitis recurrence: a retrospective comparative study. - De Seta, F; Parazzini, F; De Leo, R; Banco, R; Maso, G P; De Santo, D; Sartore, A; Stabile, G; Inglese, S; Tonon, M; Restaino, S (Eur J Obstet Gynecol Reprod Biol, 2014)
BACKGROUND: Recurrence is a frequent complaint of patients with vulvovaginal candidiasis (VVC). Although the pathogenesis of VVC remains a controversial issue, disruption of the balance between the vaginal microbiota may facilitate overgrowth by Candida. Some probiotic bacterial strains can suppress Candida albicans; Lactobacillus plantarum P17630 is able to attach to vaginal epithelial cells and significantly reduce the adhesion of C. albicans. OBJECTIVE: To evaluate the effect of the application of Lactobacillus plantarum P17630 in restoring the vaginal microbiota and prevention of relapses among women with acute VVC undergoing conventional (azole) local and main therapy. METHODS: Retrospective comparative study. We recruited 89 women with a diagnosis of VVC, who were placed into two groups on the basis of reported treatment. The control group was treated with a daily dose of 2% clotrimazole vaginal cream at bedtime for 3 days, followed by vaginal application of a capsule containing lubricant once a day for 6 days and then once a week for another 4 weeks. The probiotic group was treated with the same azole-based protocol but followed by vaginal application of a capsule containing Lactobacillus plantarum P17630 (>10₈ CFU) once a day for 6 days and then once a week for another 4 weeks beginning the day following clotrimazole discontinuation. Clinical and diagnostic patterns were monitored for three months of follow-up. RESULTS: At the end of study the probiotic-treated women showed a statistically significant increase in Lactobacillus values "+++" (80% versus 40%, p<0.001) and a better subjective resolution of symptoms such as vaginal discomfort described as burning or itching (90% versus 67.5%, p<0.03). Among controls there was a non-significant increase at 3 months of recurrence of infection, but a significant increase of women with value of pH=5 or >5. CONCLUSION: Although the results of different studies are controversial, most have suggested use of probiotics in the prevention or treatment of VVC, and no adverse effects have been reported. Our data with L. plantarum P17630 (Gyno-Canesflor - Bayer) confirm the role of this specific strain as a potential empirical preventive agent for reducing vaginal discomfort after conventional treatment of acute VVC and shifting the vaginal milieu toward a predominance of lactobacilli with an improvement of the vaginal pH value.
Keywords: Administration, Intravaginal; Adolescent; Adult; Antifungal Agents; Candidiasis, Vulvovaginal; Clotrimazole; Female; Humans; Lactobacillus plantarum; Microbiota; Middle Aged; Probiotics; Recurrence; Retrospective Studies; Secondary Prevention; Vagina; Vaginal Creams, Foams, and Jellies; Young Adult

Levels of circulating TNF-related apoptosis-inducing ligand in celiac disease. - Celeghini, Claudio; Not, Tarcisio; Norcio, Alessia; Monasta, Lorenzo; Secchiero, Paola (Exp Ther Med, 2014)
It has previously been demonstrated that the circulating levels of TNF-related apoptosis-inducing ligand (TRAIL) are significantly lower in patients with type 1 diabetes (T1D) than in normal age- and gender-matched controls. Since celiac disease (CD) is often associated with T1D, a retrospective study was performed to analyze the sera of a cohort of pediatric subjects: i) patients with CD at onset (n=100); ii) patients with potential CD (n=45); iii) patients with CD associated with other auto-immune diseases (n=17); and iv) patients with eosinophilic esophagitis (n=15). Among the patients with CD, 49 were also analyzed after six months on a gluten-free diet, while data were also available for 13 patients after one year on a gluten-free diet. No significant differences were found in the circulating levels of TRAIL between the patients with CD and the patients with either eosinophilic esophagitis or potential CD. Patients with CD associated with other auto-immune diseases showed significantly lower levels of TRAIL when compared with patients with CD alone. The gluten-free diet did not significantly modify the levels of circulating TRAIL at 6 or 12 months. Thus, although T1D and CD share common immunological features, the circulating levels of TRAIL show a significant difference between the two pathologies, and do not appear to be modulated in CD.

LIG4 and RAD52 DNA repair genes polymorphisms and systemic lupus erythematosus. - De Azevêdo Silva, Jaqueline; Pancotto, João Alexandre Trés; Donadi, Eduardo Antônio; Crovella, Sergio; Sandrin-Garcia, Paula (Mol Biol Rep, 2014)
Systemic lupus erythematosus (SLE) is a complex autoimmune disorder with a strong genetic background. Nevertheless, SLE might also be triggered due to environmental factors, such as UV light exposure. DNA double strand breaks (DSBs) may be induced secondarily by UV radiation, increasing DNA immunogenicity and in SLE patients DNA repair is diminished, allowing the accumulation of DSBs and genomic instability. LIG4 and RAD52 genes play important roles in DNA repair mechanisms and a recent microarray analysis showed their differential expression in active SLE patients. In this study we investigated a potential association between LIG4 and RAD52 single nucleotide polymorphisms (SNPs) and SLE predisposition in a Southeast Brazilian population. We assessed four Tag SNPs in LIG4 and three in RAD52 gene region, encompassing most of the gene sequence, in 158 SLE patients and 212 healthy controls. We also performed SNPs analysis considering clinical manifestation, gender and ethnicity in SLE patients. Our data did not show association between LIG4 and RAD52 SNPs and SLE, its clinical manifestations or ethnicity in the tested population. The analysis regarding ethnicity and SLE clinical manifestations indicated Caucasian-derived patients as more susceptible to cutaneous and hematological alterations than the African-derived. To our knowledge, this is the first association study involving LIG4 and RAD52 genes and SLE predisposition.
Keywords: Adult; Alleles; Brazil; Case-Control Studies; DNA Ligases; DNA Repair; Ethnic Groups; Female; Genetic Linkage; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Lupus Erythematosus, Systemic; Male; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide; Rad52 DNA Repair and Recombination Protein

Long-term follow-up in children with benign convulsions associated with gastroenteritis. - Verrotti, Alberto; Moavero, Romina; Vigevano, Federico; Cantonetti, Laura; Guerra, Azzurra; Spezia, Elisabetta; Tricarico, Antonella; Nanni, Giuliana; Agostinelli, Sergio; Chiarelli, Francesco; Parisi, Pasquale; Capovilla, Giuseppe; et al. (Eur J Paediatr Neurol, 2014)
BACKGROUND: The outcome of benign convulsions associated with gastroenteritis (CwG) has generally been reported as being excellent. However, these data need to be confirmed in studies with longer follow-up evaluations. AIM: To assess the long-term neurological outcome of a large sample of children presenting with CwG. METHODS: We reviewed clinical features of 81 subjects presenting with CwG (1994-2010) from three different Italian centers with a follow-up period of at least 3 years. RESULTS: Follow-up period ranged from 39 months to 15 years (mean 9.8 years). Neurological examination and cognitive level at the last evaluation were normal in all the patients. A mild attention deficit was detected in three cases (3.7%). Fourteen children (17.3%) received chronic anti-epileptic therapy. Interictal EEG abnormalities detected at onset in 20 patients (24.7%) reverted to normal. Transient EEG epileptiform abnormalities were detected in other three cases (3.7%), and a transient photosensitivity in one (1.2%). No recurrence of CwG was observed. Three patients (3.7%) presented with a febrile seizure and two (2.5%) with an unprovoked seizure, but none developed epilepsy. CONCLUSIONS: The long-term evaluation of children with CwG confirms the excellent prognosis of this condition, with normal psychomotor development and low risk of relapse and of subsequent epilepsy.
Keywords: Adolescent; Anticonvulsants; Attention Deficit Disorder with Hyperactivity; Child; Child, Preschool; Electroencephalography; Epilepsy; Female; Gastroenteritis; Humans; Longitudinal Studies; Male; Neurologic Examination; Retrospective Studies

Management of central venous catheters in pediatric onco-hematology using 0.9% sodium chloride and positive-pressure-valve needleless connector. - Buchini, Sara; Scarsini, Sara; Montico, Marcella; Buzzetti, Roberto; Ronfani, Luca; Decorti, Cinzia (Eur J Oncol Nurs, 2014)
PURPOSE: To describe, in a sample of pediatric onco-hematological patients, the rate of occlusions in unused central venous catheters (CVC) flushed once a week with a 0.9% sodium chloride solution through a positive-pressure-valve needleless connector. METHOD: Retrospective cohort study. Subjects aged 0-17 years were identified through a manual search in medical and nursing records and were observed for two years or until the occurrence of one of the following events: start or resume of continuous infusion; CVC removal; death. The primary study outcome was the frequency of CVC occlusion (partial or complete). RESULTS: Fifty-one patients were identified (median age 6 years). The median duration of follow-up was 169 days (IQR 111-305). During the follow up period, 14 patients (27%) had one CVC occlusion, in 2 cases (4%) the occlusion was complete, in 12 (23%) partial. All the occlusions were solved without the need for catheter removal. The lumen diameter ≤ 4.2 vs > 4.2 French showed a statistically significant association with occlusion at multivariate analysis (OR 4.0; 95% CI 1.1-14.7). CONCLUSIONS: Our findings are reassuring with respect to the management of the CVC using the adopted protocol. The study provides useful information for patient care, by verifying the performance of the adopted CVC management protocol and by identifying critical areas for nursing care.
Keywords: Adolescent; Catheter Obstruction; Catheterization, Central Venous; Central Venous Catheters; Child; Child, Preschool; Cohort Studies; Equipment Design; Female; Hematology; Humans; Infant; Infant, Newborn; Italy; Male; Oncology Nursing; Pediatric Nursing; Practice Guidelines as Topic; Retrospective Studies; Sodium Chloride

Modulation of circulating cytokine-chemokine profile in patients affected by chronic venous insufficiency undergoing surgical hemodynamic correction. - Tisato, Veronica; Zauli, Giorgio; Gianesini, Sergio; Menegatti, Erica; Brunelli, Laura; Manfredini, Roberto; Zamboni, Paolo; Secchiero, Paola (J Immunol Res, 2014)
The expression of proinflammatory cytokines/chemokines has been reported in in vitro/ex vivo settings of chronic venous insufficiency (CVI), but the identification of circulating mediators that might be associated with altered hemodynamic forces or might represent innovative biomarkers is still missing. In this study, the circulating levels of 31 cytokines/chemokines involved in inflammatory/angiogenic processes were analysed in (i) CVI patients at baseline before surgical hemody namic correction, (ii) healthy subjects, and (iii) CVI patients after surgery. In a subgroup of CVI patients, in whom the baseline levels of cytokines/chemokines were analyzed in paired blood samples obtained from varicose vein and forearm vein, EGF, PDGF, and RANTES were increased at the varicose vein site as compared to the general circulation. Moreover, while at baseline, CVI patients showed increased levels of 14 cytokines/chemokines as compared to healthy subjects, 6 months after surgery, 11 cytokines/chemokines levels were significantly reduced in the treated CVI patients as compared to the CVI patients before surgery. Of note, a patient who exhibited recurrence of the disease 6 months after surgery, showed higher levels of EGF, PDGF, and RANTES compared to nonrecurrent patients, highlighting the potential role of the EGF/PDGF/RANTES triad as sensitive biomarkers in the context of CVI.
Keywords: Adult; Aged; Chemokines; Chronic Disease; Cytokines; Female; Hemodynamics; Humans; Male; Middle Aged; Saphenous Vein; Varicose Veins; Venous Insufficiency

Molecular analysis of Fanconi anemia: the experience of the Bone Marrow Failure Study Group of the Italian Association of Pediatric Onco-Hematology. - De Rocco, Daniela; Bottega, Roberta; Cappelli, Enrico; Cavani, Simona; Criscuolo, Maria; Nicchia, Elena; Corsolini, Fabio; Greco, Chiara; Borriello, Adriana; Svahn, Johanna; Pillon, Marta; Mecucci, Cristina; et al. (Haematologica, 2014)
Fanconi anemia is an inherited disease characterized by congenital malformations, pancytopenia, cancer predisposition, and sensitivity to cross-linking agents. The molecular diagnosis of Fanconi anemia is relatively complex for several aspects including genetic heterogeneity with mutations in at least 16 different genes. In this paper, we report the mutations identified in 100 unrelated probands enrolled into the National Network of the Italian Association of Pediatric Hematoly and Oncology. In approximately half of these cases, mutational screening was carried out after retroviral complementation analyses or protein analysis. In the other half, the analysis was performed on the most frequently mutated genes or using a next generation sequencing approach. We identified 108 distinct variants of the FANCA, FANCG, FANCC, FANCD2, and FANCB genes in 85, 9, 3, 2, and 1 families, respectively. Despite the relatively high number of private mutations, 45 of which are novel Fanconi anemia alleles, 26% of the FANCA alleles are due to 5 distinct mutations. Most of the mutations are large genomic deletions and nonsense or frameshift mutations, although we identified a series of missense mutations, whose pathogenetic role was not always certain. The molecular diagnosis of Fanconi anemia is still a tiered procedure that requires identifying candidate genes to avoid useless sequencing. Introduction of next generation sequencing strategies will greatly improve the diagnostic process, allowing a rapid analysis of all the genes.
Keywords: Amino Acid Substitution; Cell Line; Cohort Studies; Computational Biology; Databases, Nucleic Acid; Fanconi Anemia; Fanconi Anemia Complementation Group Proteins; Founder Effect; Genotype; Humans; Italy; Mosaicism; Mutation; Polymorphism, Single Nucleotide

Mutations of cytochrome c identified in patients with thrombocytopenia THC4 affect both apoptosis and cellular bioenergetics. - De Rocco, Daniela; Cerqua, Cristina; Goffrini, Paola; Russo, Giovanna; Pastore, Annalisa; Meloni, Francesca; Nicchia, Elena; Moraes, Carlos T; Pecci, Alessandro; Salviati, Leonardo; Savoia, Anna (Biochim Biophys Acta, 2014)
Inherited thrombocytopenias are heterogeneous diseases caused by at least 20 genes playing different role in the processes of megakaryopoiesis and platelet production. Some forms, such as thrombocytopenia 4 (THC4), are very rare and not well characterized. THC4 is an autosomal dominant mild thrombocytopenia described in only one large family from New Zealand and due to a mutation (G41S) of the somatic isoform of the cytochrome c (CYCS) gene. We report a novel CYCS mutation (Y48H) in patients from an Italian family. Similar to individuals carrying G41S, they have platelets of normal size and morphology, which are only partially reduced in number, but no prolonged bleeding episodes. In order to determine the pathogenetic consequences of Y48H, we studied the effects of the two CYCS mutations in yeast and mouse cellular models. In both cases, we found reduction of respiratory level and increased apoptotic rate, supporting the pathogenetic role of CYCS in thrombocytopenia.
Keywords: Amino Acid Sequence; Animals; Apoptosis; Base Sequence; Cells, Cultured; Child, Preschool; Cytochromes c; DNA Mutational Analysis; Embryo, Mammalian; Energy Metabolism; Family Health; Female; Fibroblasts; Humans; Lung; Male; Mice; Molecular Sequence Data; Mutation, Missense; Oxygen Consumption; Pedigree; Saccharomyces cerevisiae; Sequence Homology, Amino Acid; Thrombocytopenia

MYH9-related disease: a novel prognostic model to predict the clinical evolution of the disease based on genotype-phenotype correlations. - Pecci, Alessandro; Klersy, Catherine; Gresele, Paolo; Lee, Kieran J D; De Rocco, Daniela; Bozzi, Valeria; Russo, Giovanna; Heller, Paula G; Loffredo, Giuseppe; Ballmaier, Matthias; Fabris, Fabrizio; Beggiato, Eloise; et al. (Hum Mutat, 2014)
MYH9-related disease (MYH9-RD) is a rare autosomal-dominant disorder caused by mutations in the gene for nonmuscle myosin heavy chain IIA (NMMHC-IIA). MYH9-RD is characterized by a considerable variability in clinical evolution: patients present at birth with only thrombocytopenia, but some of them subsequently develop sensorineural deafness, cataract, and/or nephropathy often leading to end-stage renal disease (ESRD). We searched for genotype-phenotype correlations in the largest series of consecutive MYH9-RD patients collected so far (255 cases from 121 families). Association of genotypes with noncongenital features was assessed by a generalized linear regression model. The analysis defined disease evolution associated to seven different MYH9 genotypes that are responsible for 85% of MYH9-RD cases. Mutations hitting residue R702 demonstrated a complete penetrance for early-onset ESRD and deafness. The p.D1424H substitution associated with high risk of developing all the noncongenital manifestations of disease. Mutations hitting a distinct hydrophobic seam in the NMMHC-IIA head domain or substitutions at R1165 associated with high risk of deafness but low risk of nephropathy or cataract. Patients with p.E1841K, p.D1424N, and C-terminal deletions had low risk of noncongenital defects. These findings are essential to patients' clinical management and genetic counseling and are discussed in view of molecular pathogenesis of MYH9-RD.
Keywords: Adult; Age of Onset; Amino Acid Substitution; Cataract; Female; Genetic Association Studies; Genotype; Hearing Loss, Sensorineural; Humans; Italy; Linear Models; Male; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Phenotype; Risk Factors; Thrombocytopenia

Non-classical MHC-I human leukocyte antigen (HLA-G) in hepatotropic viral infections and in hepatocellular carcinoma. - Catamo, Eulalia; Zupin, Luisa; Crovella, Sergio; Celsi, Fulvio; Segat, Ludovica (Hum Immunol, 2014)
The human leukocyte antigen (HLA)-G is a "nonclassical" major histocompatibility complex (MHC) class Ib gene, located at chromosome 6, in the 6p21.3 region. The HLA-G presents immunomodulatory functions essential in pregnancy for the tolerance of the semi-allogenic fetus, but an abnormal expression of HLA-G has been observed in numerous pathological conditions, such as tumors, autoimmune diseases and viral infections. In recent years, numerous studies have assessed the clinical relevance of HLA-G expression in different types of cancer: in general, a higher HLA-G expression correlates with a lower survival rate or a shorter disease-free survival. Altered expression of HLA-G has been found in both HCV and HBV infection, and some genetic polymorphisms have been associated with altered susceptibility/disease development for these infections, however, whether the biologic role of HLA-G in HCV and HBV infection is beneficial or hazardous, it is not completely clear. In the context of hepatocellular carcinoma, HLA-G has shown a potential diagnostic role, moreover a prognostic value in HCC patients has been also attributed to HLA-G molecules. We revise here the role of HLA-G in hepatotropic HBV/HCV infections and in hepatocellular carcinoma (HCC).
Keywords: Carcinoma, Hepatocellular; Female; Genetic Predisposition to Disease; Hepatitis B; Hepatitis C; HLA-G Antigens; Humans; Immune Tolerance; Liver Neoplasms; Polymorphism, Genetic; Pregnancy

A non-complement-fixing antibody to β2 glycoprotein I as a novel therapy for antiphospholipid syndrome. - Agostinis, Chiara; Durigutto, Paolo; Sblattero, Daniele; Borghi, Maria O; Grossi, Claudia; Guida, Filomena; Bulla, Roberta; Macor, Paolo; Pregnolato, Francesca; Meroni, Pier Luigi; Tedesco, Francesco (Blood, 2014)
A single-chain fragment variable (scFv) recognizing β2-glycoprotein 1 (β2GPI) from humans and other species was isolated from a human phage display library and engineered to contain an IgG1 hinge-CH2-CH3 domain. The scFv-Fc directed against β2GPI domain I-induced thrombosis and fetal loss, thus mimicking the effect of antibodies from patients with antiphospholipid syndrome (APS). Complement is involved in the biological effect of anti-β2GPI scFv-Fc, as demonstrated by its ability to promote in vitro and in vivo complement deposition and the failure to induce vascular thrombosis in C6-deficient rats and fetal loss in C5-depleted mice. A critical role for complement was also supported by the inability of the CH2-deleted scFv-Fc to cause vessel occlusion and pregnancy failure. This antibody prevented the pathological effects of anti-β2GPI antibodies from APS patients and displaced β2GPI-bound patient antibodies. The CH2-deleted antibody represents an innovative approach potentially useful to treat APS patients refractory to standard therapy.
Keywords: Abortion, Spontaneous; Animals; Antibodies, Monoclonal; Antiphospholipid Syndrome; Autoantigens; beta 2-Glycoprotein I; Complement Activation; Complement System Proteins; Human Umbilical Vein Endothelial Cells; Humans; Immunoglobulin G; Male; Mice; Protein Binding; Rats; Recombinant Proteins; Single-Chain Antibodies; Thrombosis; Trophoblasts

Osteoprotegerin increases in metabolic syndrome and promotes adipose tissue proinflammatory changes. - Bernardi, Stella; Fabris, Bruno; Thomas, Merlin; Toffoli, Barbara; Tikellis, Christos; Candido, Riccardo; Catena, Cristiana; Mulatero, Paolo; Barbone, Fabio; Radillo, Oriano; Zauli, Giorgio; Secchiero, Paola (Mol Cell Endocrinol, 2014)
BACKGROUND: Inflammation is believed to link obesity to insulin resistance, as in the setting of metabolic syndrome (MetS). Osteoprotegerin (OPG) is a soluble protein that seems to exert proatherogenic and prodiabetogenic effects. This study aims at determining OPG levels in MetS and whether OPG might contribute to MetS development and progression. METHODOLOGY/PRINCIPAL FINDINGS: Circulating OPG was measured in 46 patients with MetS and 63 controls, and was found significantly elevated in those with MetS. In addition, circulating and tissue OPG was significantly increased in high-fat diet (HFD) fed C57BL6 mice, which is one of the animal models for the study of MetS. To evaluate the consequences of OPG elevation, we delivered this protein to C57BL6 mice, finding that it promoted systemic and adipose tissue proinflammatory changes in association with metabolic abnormalities. CONCLUSIONS/SIGNIFICANCE: These data suggest that OPG may trigger adipose tissue proinflammatory changes in MetS/HFD-induced obesity.
Keywords: Adipose Tissue; Adult; Animals; Blood Glucose; Body Mass Index; C-Reactive Protein; Case-Control Studies; Cholesterol, HDL; Cholesterol, LDL; Diet, High-Fat; Female; Humans; Inflammation; Insulin; Insulin Resistance; Male; Metabolic Syndrome X; Mice; Mice, Inbred C57BL; Middle Aged; Obesity; Osteoprotegerin; Triglycerides

The p53 transcriptional pathway is preserved in ATMmutated and NOTCH1mutated chronic lymphocytic leukemias. - Athanasakis, Emmanouil; Melloni, Elisabetta; Rigolin, Gian Matteo; Agnoletto, Chiara; Voltan, Rebecca; Vozzi, Diego; Piscianz, Elisa; Segat, Ludovica; dal Monego, Simeone; Cuneo, Antonio; Secchiero, Paola; Zauli, Giorgio (Oncotarget, 2014)
By using next generation sequencing, we have analyzed 108 B chronic lymphocytic leukemia (B-CLL) patients. Among genes involved in the TP53 pathway, we found frequent mutations in ATM (n=18), TP53 (n=10) and NOTCH1 (n=10) genes, rare mutations of NOTCH2 (n=2) and CDKN1A/p21 (n=1) and no mutations in BAX, MDM2, TNFRSF10A and TNFRSF10B genes. The in vitro treatment of primary B-CLL cells with the activator of p53 Nutlin-3 induced the transcription of p53 target genes, without significant differences between the B-CLL without mutations and those harboring either ATM or NOTCH1mutations. On the other hand, the subgroup of TP53mutated B-CLL exhibited a significantly lower induction of the p53 target genes in response to Nutlin-3 as compared to the other B-CLL samples. However, among the TP53mutated B-CLL, those showing mutations in the high hot spot region of the DNA binding domain [273-280 aa] maintained a significantly higher p53-dependent transcriptional activity as compared to the other TP53mutated B-CLL samples. Since the ability to elicit a p53-dependent transcriptional activity in vitro has a positive prognostic significance, our data suggest that ATMmutated, NOTCH1mutated and surprisingly, also a subset of TP53mutated B-CLL patients might benefit from therapeutic combinations including small molecule activator of the p53 pathway.
Keywords: Aged; Aged, 80 and over; Ataxia Telangiectasia Mutated Proteins; Base Sequence; Female; Genes, p53; Humans; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Models, Molecular; Molecular Sequence Data; Mutation; Receptor, Notch1; Signal Transduction; Tumor Suppressor Protein p53

Parent-of-origin-specific allelic associations among 106 genomic loci for age at menarche. - Perry, John R B; Day, Felix; Elks, Cathy E; Sulem, Patrick; Thompson, Deborah J; Ferreira, Teresa; He, Chunyan; Chasman, Daniel I; Esko, Tõnu; Thorleifsson, Gudmar; Albrecht, Eva; Ang, Wei Q; et al. (Nature, 2014)
Age at menarche is a marker of timing of puberty in females. It varies widely between individuals, is a heritable trait and is associated with risks for obesity, type 2 diabetes, cardiovascular disease, breast cancer and all-cause mortality. Studies of rare human disorders of puberty and animal models point to a complex hypothalamic-pituitary-hormonal regulation, but the mechanisms that determine pubertal timing and underlie its links to disease risk remain unclear. Here, using genome-wide and custom-genotyping arrays in up to 182,416 women of European descent from 57 studies, we found robust evidence (P < 5 × 10(-8)) for 123 signals at 106 genomic loci associated with age at menarche. Many loci were associated with other pubertal traits in both sexes, and there was substantial overlap with genes implicated in body mass index and various diseases, including rare disorders of puberty. Menarche signals were enriched in imprinted regions, with three loci (DLK1-WDR25, MKRN3-MAGEL2 and KCNK9) demonstrating parent-of-origin-specific associations concordant with known parental expression patterns. Pathway analyses implicated nuclear hormone receptors, particularly retinoic acid and γ-aminobutyric acid-B2 receptor signalling, among novel mechanisms that regulate pubertal timing in humans. Our findings suggest a genetic architecture involving at least hundreds of common variants in the coordinated timing of the pubertal transition.
Keywords: Adolescent; Age Factors; Alleles; Body Mass Index; Breast Neoplasms; Cardiovascular Diseases; Child; Diabetes Mellitus, Type 2; Europe; Female; Genetic Loci; Genome-Wide Association Study; Genomic Imprinting; Humans; Hypothalamo-Hypophyseal System; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Obesity; Ovary; Parents; Polymorphism, Single Nucleotide; Potassium Channels, Tandem Pore Domain; Proteins; Quantitative Trait Loci; Receptors, GABA-B; Receptors, Retinoic Acid; Ribonucleoproteins

Pharmacogenetics of azathioprine in inflammatory bowel disease: a role for glutathione-S-transferase? - Stocco, Gabriele; Pelin, Marco; Franca, Raffaella; De Iudicibus, Sara; Cuzzoni, Eva; Favretto, Diego; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana (World J Gastroenterol, 2014)
Azathioprine is a purine antimetabolite drug commonly used to treat inflammatory bowel disease (IBD). In vivo it is active after reaction with reduced glutathione (GSH) and conversion to mercaptopurine. Although this reaction may occur spontaneously, the presence of isoforms M and A of the enzyme glutathione-S-transferase (GST) may increase its speed. Indeed, in pediatric patients with IBD, deletion of GST-M1, which determines reduced enzymatic activity, was recently associated with reduced sensitivity to azathioprine and reduced production of azathioprine active metabolites. In addition to increase the activation of azathioprine to mercaptopurine, GSTs may contribute to azathioprine effects even by modulating GSH consumption, oxidative stress and apoptosis. Therefore, genetic polymorphisms in genes for GSTs may be useful to predict response to azathioprine even if more in vitro and clinical validation studies are needed.
Keywords: 6-Mercaptopurine; Animals; Apoptosis; Azathioprine; Glutathione; Glutathione Transferase; Humans; Immunosuppressive Agents; Inflammatory Bowel Diseases; Oxidative Stress; Pharmacogenetics; Polymorphism, Genetic

Piccolipiù, a multicenter birth cohort in Italy: protocol of the study. - Farchi, Sara; Forastiere, Francesco; Vecchi Brumatti, Liza; Alviti, Sabrina; Arnofi, Antonio; Bernardini, Tommaso; Bin, Maura; Brescianini, Sonia; Colelli, Valentina; Cotichini, Rodolfo; Culasso, Martina; De Bartolo, Paolo; et al. (BMC Pediatr, 2014)
BACKGROUND: The fetal and infant life are periods of rapid development, characterized by high susceptibility to exposures. Birth cohorts provide unique opportunities to study early-life exposures in association with child development and health, as well as, with longer follow-up, the early life origin of adult diseases. Piccolipiù is an Italian birth cohort recently set up to investigate the effects of environmental exposures, parental conditions and social factors acting during pre-natal and early post-natal life on infant and child health and development. We describe here its main characteristics. METHODS/DESIGN: Piccolipiù is a prospective cohort of expected 3000 newborns, who will be recruiting in six maternity units of five Italian cities (Florence, Rome, Trieste, Turin and Viareggio) since October 2011. Mothers are contacted during pregnancy or at delivery and are offered to participate in the study. Upon acceptance, their newborns are recruited at birth and followed up until at least 18 years of age. At recruitment, the mothers donate a blood sample and complete a baseline questionnaire. Umbilical cord blood, pieces of umbilical cord and heel blood spots are also collected. Postnatal follow-up currently occurs at 6, 12, and 24 months of age using on-line or postal self administered questionnaire; further questionnaires and medical examinations are envisaged. Questionnaires collect information on several factors, including mother's and/or child's environmental exposures, anthropometric measures, reproductive factors, diet, supplements, medical history, cognitive development, mental health and socioeconomic factors. Health promotion materials are also offered to parents. DISCUSSION: Piccolipiù will broaden our understanding of the contribution of early-life factors to infant and child health and development. Several hypotheses on the developmental origins of health can be tested or piloted using the data collected from the Piccolipiù cohort. By pooling these data with those collected by other existing birth cohorts it will be possible to validate previous findings and to study rare exposures and outcomes.
Keywords: Adolescent; Child; Child Development; Child Welfare; Child, Preschool; Cohort Studies; Environmental Exposure; Humans; Infant; Infant, Newborn; Italy; Prospective Studies; Socioeconomic Factors

Platelet diameters in inherited thrombocytopenias: analysis of 376 patients with all known disorders. - Noris, Patrizia; Biino, Ginevra; Pecci, Alessandro; Civaschi, Elisa; Savoia, Anna; Seri, Marco; Melazzini, Federica; Loffredo, Giuseppe; Russo, Giovanna; Bozzi, Valeria; Notarangelo, Lucia Dora; Gresele, Paolo; et al. (Blood, 2014)
Abnormalities of platelet size are one of the distinguishing features of inherited thrombocytopenias (ITs), and evaluation of blood films is recommended as an essential step for differential diagnosis of these disorders. Nevertheless, what we presently know about this subject is derived mainly from anecdotal evidence. To improve knowledge in this field, we evaluated platelet size on blood films obtained from 376 patients with all 19 forms of IT identified so far and found that these conditions differ not only in mean platelet diameter, but also in platelet diameter distribution width and the percentage of platelets with increased or reduced diameters. On the basis of these findings, we propose a new classification of ITs according to platelet size. It distinguishes forms with giant platelets, with large platelets, with normal or slightly increased platelet size, and with normal or slightly decreased platelet size. We also measured platelet diameters in 87 patients with immune thrombocytopenia and identified cutoff values for mean platelet diameter and the percentage of platelets with increased or reduced size that have good diagnostic accuracy in differentiating ITs with giant platelets and with normal or slightly decreased platelet size from immune thrombocytopenia and all other forms of IT.
Keywords: Adolescent; Adult; Blood Platelets; Case-Control Studies; Cell Size; Child; Child, Preschool; Diagnosis, Differential; Female; Hearing Loss, Sensorineural; Humans; Infant; Male; Middle Aged; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Purpura, Thrombocytopenic, Idiopathic; Thrombocytopenia; Young Adult

Polyubiquitinated proteins, proteasome, and glycogen characterize the particle-rich cytoplasmic structure (PaCS) of neoplastic and fetal cells. - Necchi, Vittorio; Sommi, Patrizia; Vitali, Agostina; Vanoli, Alessandro; Savoia, Anna; Ricci, Vittorio; Solcia, Enrico (Histochem Cell Biol, 2014)
A particle-rich cytoplasmic structure (PaCS) concentrating ubiquitin-proteasome system (UPS) components and barrel-like particles in clear, cytoskeleton- and organelle-free areas has recently been described in some neoplasms and in genetic or infectious diseases at risk of neoplasia. Ultrastructurally similar particulate cytoplasmic structures, interpreted as glycogen deposits, have previously been reported in clear-cell neoplasms and some fetal tissues. It remains to be investigated whether the two structures are the same, colocalize UPS components and polysaccharides, and have a role in highly proliferative cells such as fetal and neoplastic cells. We used immunogold electron microscopy and confocal immunofluorescence microscopy to examine human and mouse fetal tissues and human neoplasms. Fetal and neoplastic cells both showed colocalization of polyubiquitinated proteins, 19S and 20S proteasomes, and polysaccharides, both glycogen and chondroitin sulfate, inside cytoplasmic structures showing all distinctive features of PaCSs. Poorly demarcated and/or hybrid (ribosomes admixed) UPS- and glycogen-enriched areas, likely stages in PaCS development, were also seen in some fetal cells, with special reference to those, like primary alveolar pulmonary cells or pancreatic centroacinar cells, having a crucial role in organogenesis. UPS- and glycogen-rich PaCSs developed extensively in clear-cell neoplasms of the kidney, ovary, pancreas, and other organs, as well as, in infantile, development-related tumors replicating fetal patterns, such as choroid plexus papilloma. UPS-mediated, ATP-dependent proteolysis and its potential energy source, glycogen metabolism, may have a crucial, synergic role in embryo-/organogenesis and carcinogenesis.
Keywords: Cytoplasm; Fetus; Glycogen; Humans; Immunohistochemistry; Microscopy, Confocal; Microscopy, Electron, Transmission; Neoplasms; Proteasome Endopeptidase Complex; Ubiquitinated Proteins

Pregnancy and postpartum following a prenatal diagnosis of fetal thoracoabdominal malformation: the parental perspective. - Giuliani, Rosella; Tripani, Antonella; Pellizzoni, Sandra; Clarici, Andrea; Lonciari, Isabella; D'Ottavio, Giuseppina; Schleef, Jurgen (J Pediatr Surg, 2014)
PURPOSE: The study's aim was to evaluate how information related to a prenatal diagnosis of fetal malformation could modify parenthood experience descriptions during pregnancy and after the child's birth. METHODS: A longitudinal case-control clinical study was conducted. Data on parenthood experience descriptions collected using a validated semantic differential technique during pregnancy and after the child's birth were compared between seven couples of parents receiving a prenatal diagnosis of fetal malformation and seven couples without any fetal diagnosis. RESULTS: Our results show that during pregnancy parents in the clinical group describe themselves as more fragile, passive, and timid [p=0.007] than those in the control group. On the other hand, after the child's birth, there are no significant differences between groups. CONCLUSIONS: Data are discussed with reference to better knowledge of the psychological dynamics involved in becoming a parent and to rational planning of support for parents receiving a diagnosis of fetal malformation.
Keywords: Adult; Case-Control Studies; Counseling; Cystic Adenomatoid Malformation of Lung, Congenital; Female; Hernia, Diaphragmatic; Hernias, Diaphragmatic, Congenital; Humans; Hydronephrosis; Kidney Diseases; Longitudinal Studies; Male; Musculoskeletal Abnormalities; Parents; Pregnancy; Psychological Tests; Stress, Psychological; Ultrasonography, Prenatal; Urogenital Abnormalities

Radiological contrast media in the breastfeeding woman: a position paper of the Italian Society of Radiology (SIRM), the Italian Society of Paediatrics (SIP), the Italian Society of Neonatology (SIN) and the Task Force on Breastfeeding, Ministry of Health - Cova, Maria Assunta; Stacul, Fulvio; Quaranta, Roberto; Guastalla, Pierpaolo; Salvatori, Guglielmo; Banderali, Giuseppe; Fonda, Claudio; David, Vincenzo; Gregori, Massimo; Zuppa, Antonio Alberto; Davanzo, Riccardo (Eur Radiol, 2014)
OBJECTIVES: Breastfeeding is a well-recognised investment in the health of the mother-infant dyad. Nevertheless, many professionals still advise breastfeeding mothers to temporarily discontinue breastfeeding after contrast media imaging. Therefore, we performed this review to provide health professionals with basic knowledge and skills for appropriate use of contrast media. METHODS: A joint working group of the Italian Society of Radiology (SIRM), Italian Society of Paediatrics (SIP), Italian Society of Neonatology (SIN) and Task Force on Breastfeeding, Ministry of Health, Italy prepared a review of the relevant medical literature on the safety profile of contrast media for the nursing infant/child. RESULTS: Breastfeeding is safe for the nursing infant of any post-conceptional age after administration of the majority of radiological contrast media to the mother; only gadolinium-based agents considered at high risk of nephrogenic systemic fibrosis (gadopentetate dimeglumine, gadodiamide, gadoversetamide) should be avoided in the breastfeeding woman as a precaution; there is no need to temporarily discontinue breastfeeding or to express and discard breast milk following the administration of contrast media assessed as compatible with breastfeeding. CONCLUSIONS: Breastfeeding women should receive unambiguous professional advice and clear encouragement to continue breastfeeding after imaging with the compatible contrast media. KEY POINTS: • Breastfeeding is a well-known investment in the health of the mother-infant dyad. • Breastfeeding is safe after administration of contrast media to the mother. • There is no need to temporarily discontinue breastfeeding following administration of contrast media.
Keywords: Adult; Breast Feeding; Contrast Media; Female; Humans; Infant; Italy; Neonatology; Practice Guidelines as Topic; Radiology; Societies, Medical

A randomized trial of hyperimmune globulin to prevent congenital cytomegalovirus. - Revello, Maria Grazia; Lazzarotto, Tiziana; Guerra, Brunella; Spinillo, Arsenio; Ferrazzi, Enrico; Kustermann, Alessandra; Guaschino, Secondo; Vergani, Patrizia; Todros, Tullia; Frusca, Tiziana; Arossa, Alessia; Furione, Milena; et al. (N Engl J Med, 2014)
BACKGROUND: Congenital infection with human cytomegalovirus (CMV) is a major cause of morbidity and mortality. In an uncontrolled study published in 2005, administration of CMV-specific hyperimmune globulin to pregnant women with primary CMV infection significantly reduced the rate of intrauterine transmission, from 40% to 16%. METHODS: We evaluated the efficacy of hyperimmune globulin in a phase 2, randomized, placebo-controlled, double-blind study. A total of 124 pregnant women with primary CMV infection at 5 to 26 weeks of gestation were randomly assigned within 6 weeks after the presumed onset of infection to receive hyperimmune globulin or placebo every 4 weeks until 36 weeks of gestation or until detection of CMV in amniotic fluid. The primary end point was congenital infection diagnosed at birth or by means of amniocentesis. RESULTS: A total of 123 women could be evaluated in the efficacy analysis (1 woman in the placebo group withdrew). The rate of congenital infection was 30% (18 fetuses or infants of 61 women) in the hyperimmune globulin group and 44% (27 fetuses or infants of 62 women) in the placebo group (a difference of 14 percentage points; 95% confidence interval, -3 to 31; P=0.13). There was no significant difference between the two groups or, within each group, between the women who transmitted the virus and those who did not, with respect to levels of virus-specific antibodies, T-cell-mediated immune response, or viral DNA in the blood. The clinical outcome of congenital infection at birth was similar in the two groups. The number of obstetrical adverse events was higher in the hyperimmune globulin group than in the placebo group (13% vs. 2%). CONCLUSIONS: In this study involving 123 women who could be evaluated, treatment with hyperimmune globulin did not significantly modify the course of primary CMV infection during pregnancy. (Funded by Agenzia Italiana del Farmaco; CHIP ClinicalTrials.gov number, NCT00881517; EudraCT no. 2008-006560-11.).
Keywords: Adult; Amniocentesis; Cytomegalovirus; Cytomegalovirus Infections; Female; Fetal Diseases; Humans; Immunoglobulins; Infectious Disease Transmission, Vertical; Pregnancy; Pregnancy Complications, Infectious

Recommendations for self-monitoring in pediatric diabetes: a consensus statement by the ISPED. - Scaramuzza, Andrea; Cherubini, Valentino; Tumini, Stefano; Bonfanti, Riccardo; Buono, Pietro; Cardella, Francesca; d'Annunzio, Giuseppe; Frongia, Anna Paola; Lombardo, Fortunato; Monciotti, Anna Carla Maria; Rabbone, Ivana; Schiaffini, Riccardo; et al. (Acta Diabetol, 2014)
A panel of experts of the Italian Society of Pediatric Endocrinology and Diabetology comprehensively discussed and approved the Italian recommendations regarding self-monitoring of blood glucose, continuous glucose monitoring and other measures of glycemic control in children and adolescents with type 1 diabetes. After an extensive review of the literature, we took these issues into account: self-monitoring blood glucose, continuous glucose monitoring, glycemic variability, glycosuria, ketonuria, ketonemia, glycated hemoglobin, fructosamine and glycated albumin, logbook, data downloading, lancing devices, carbohydrate counting, and glycemic measurements at school. We concluded that clinical guidelines on self-management should be developed in every country with faithful adaptation to local languages and taking into account specific contexts and local peculiarities, without any substantial modifications to the international recommendations. We believe that the National Health Service should provide all necessary resources to ensure self-monitoring of blood glucose and possibly continuous glucose monitoring of all children and adolescents with type 1 diabetes, according to the standards of care provided by these recommendations and internationally.

Rhythm perception and production predict reading abilities in developmental dyslexia. - Flaugnacco, Elena; Lopez, Luisa; Terribili, Chiara; Zoia, Stefania; Buda, Sonia; Tilli, Sara; Monasta, Lorenzo; Montico, Marcella; Sila, Alessandra; Ronfani, Luca; Schön, Daniele (Front Hum Neurosci, 2014)
Rhythm organizes events in time and plays a major role in music, but also in the phonology and prosody of a language. Interestingly, children with developmental dyslexia-a learning disability that affects reading acquisition despite normal intelligence and adequate education-have a poor rhythmic perception. It has been suggested that an accurate perception of rhythmical/metrical structure, that requires accurate perception of rise time, may be critical for phonological development and subsequent literacy. This hypothesis is mostly based on results showing a high degree of correlation between phonological awareness and metrical skills, using a very specific metrical task. We present new findings from the analysis of a sample of 48 children with a diagnosis of dyslexia, without comorbidities. These children were assessed with neuropsychological tests, as well as specifically-devised psychoacoustic and musical tasks mostly testing temporal abilities. Associations were tested by multivariate analyses including data mining strategies, correlations and most importantly logistic regressions to understand to what extent the different auditory and musical skills can be a robust predictor of reading and phonological skills. Results show a strong link between several temporal skills and phonological and reading abilities. These findings are discussed in the framework of the neuroscience literature comparing music and language processing, with a particular interest in the links between rhythm processing in music and language.

Risk of Essure microinsert abdominal migration: case report and review of literature. - Ricci, Giuseppe; Restaino, Stefano; Di Lorenzo, Giovanni; Fanfani, Francesco; Scrimin, Federica; Mangino, Francesco P (Ther Clin Risk Manag, 2014)
PURPOSE: To report a case of Essure microinsert abdominal migration and literature review. METHODS: A 41-year-old woman was counseled to undergo Essure sterilization. The procedure was hampered by the presence of endometrial cavity adhesions, obscuring left tubal ostium. By using microscissors the adhesions were progressively lysed. Since the procedure had become very painful, the patient required general anesthesia. Once adhesion lysis was completed, the tubal ostium was well visible. Both devices were then easily introduced into the fallopian tubes. At the end of the procedure, five coils were visible on the right side and five coils on the left side, as recommended. RESULTS: The 3-month hysterosalpingogram follow-up suspected abdominal migration of the left device. Laparoscopy confirmed the device displacement in the left lower abdominal quadrant. Both fallopian tubes and the uterus appeared normal. No signs of perforation were detected. The device was embedded into the omentum, but it was easily removed. Bilateral tubal sterilization was performed by bipolar coagulation. CONCLUSION: There are only 13 cases, including the present, of Essure abdominal migration in the literature. In most cases, abdominal displacement of the microinsert is asymptomatic and does not induce tissue damage. However, in some cases, it may cause a severe adverse event, requiring major surgery. Therefore, removal of the migrated device should be performed as soon as possible. Moreover, during presterilization counseling, the patient should also be correctly informed about the risk of this rare but relevant complication, as well as about the surgical interventions that could be required to solve it.

The role of gestational diabetes, pre-pregnancy body mass index and gestational weight gain on the risk of newborn macrosomia: results from a prospective multicentre study. - Alberico, Salvatore; Montico, Marcella; Barresi, Valentina; Monasta, Lorenzo; Businelli, Caterina; Soini, Valentina; Erenbourg, Anna; Ronfani, Luca; Maso, Gianpaolo (BMC Pregnancy Childbirth, 2014)
BACKGROUND: It is crucial to identify in large population samples the most important determinants of excessive fetal growth. The aim of the study was to evaluate the independent role of pre-pregnancy body mass index (BMI), gestational weight gain and gestational diabetes on the risk of macrosomia. METHODS: A prospective study collected data on mode of delivery and maternal/neonatal outcomes in eleven Hospitals in Italy. Multiple pregnancies and preterm deliveries were excluded. The sample included 14109 women with complete records. Associations between exposure variables and newborn macrosomia were analyzed using Pearson's chi squared test. Multiple logistic regression models were built to assess the independent association between potential predictors and macrosomia. RESULTS: Maternal obesity (adjusted OR 1.7, 95% CI 1.4-2.2), excessive gestational weight gain (adjusted OR 1.9, 95% CI 1.6-2.2) and diabetes (adjusted OR 2.1, 95% CI 1.5-3.0 for gestational; adjusted OR 3.0, 95% CI 1.2-7.6 for pre-gestational) resulted to be independent predictors of macrosomia, when adjusted for other recognized risk factors. Since no significant interaction was found between pre-gestational BMI and gestational weight gain, excessive weight gain should be considered an independent risk factor for macrosomia. In the sub-group of women affected by gestational or pre-gestational diabetes, pre-gestational BMI was not significantly associated to macrosomia, while excessive pregnancy weight gain, maternal height and gestational age at delivery were significantly associated. In this sub-population, pregnancy weight gain less than recommended was not significantly associated to a reduction in macrosomia. CONCLUSIONS: Our findings indicate that maternal obesity, gestational weight gain excess and diabetes should be considered as independent risk factors for newborn macrosomia. To adequately evaluate the clinical evolution of pregnancy all three variables need to be carefully assessed and monitored.
Keywords: Adolescent; Adult; Birth Weight; Body Height; Body Mass Index; Diabetes, Gestational; Female; Fetal Macrosomia; Gestational Age; Humans; Infant, Newborn; Italy; Middle Aged; Obesity; Pregnancy; Pregnancy in Diabetics; Prospective Studies; Risk Factors; Weight Gain; Young Adult

Salt-inducible kinase 3, SIK3, is a new gene associated with hearing. - Wolber, Lisa E; Girotto, Giorgia; Buniello, Annalisa; Vuckovic, Dragana; Pirastu, Nicola; Lorente-Cánovas, Beatriz; Rudan, Igor; Hayward, Caroline; Polasek, Ozren; Ciullo, Marina; Mangino, Massimo; Steves, Claire; et al. (Hum Mol Genet, 2014)
Hearing function is known to be heritable, but few significant and reproducible associations of genetic variants have been identified to date in the adult population. In this study, genome-wide association results of hearing function from the G-EAR consortium and TwinsUK were used for meta-analysis. Hearing ability in eight population samples of Northern and Southern European ancestry (n = 4591) and the Silk Road (n = 348) was measured using pure-tone audiometry and summarized using principal component (PC) analysis. Genome-wide association analyses for PC1-3 were conducted separately in each sample assuming an additive model adjusted for age, sex and relatedness of subjects. Meta-analysis was performed using 2.3 million single-nucleotide polymorphisms (SNPs) tested against each of the three PCs of hearing ability in 4939 individuals. A single SNP lying in intron 6 of the salt-inducible kinase 3 (SIK3) gene was found to be associated with hearing PC2 (P = 3.7×10(-8)) and further supported by whole-genome sequence in a subset. To determine the relevance of this gene in the ear, expression of the Sik3 protein was studied in mouse cochlea of different ages. Sik3 was expressed in murine hair cells during early development and in cells of the spiral ganglion during early development and adulthood. Our results suggest a developmental role of Sik3 in hearing and may be required for the maintenance of adult auditory function.
Keywords: Age Factors; Animals; Cochlea; European Continental Ancestry Group; Genome-Wide Association Study; Hearing; Humans; Mice, Inbred C57BL; Polymorphism, Single Nucleotide; Protein Kinases

Single-day trimethoprim/sulfamethoxazole prophylaxis for Pneumocystis pneumonia in children with cancer. - Caselli, Désirée; Petris, Maria Grazia; Rondelli, Roberto; Carraro, Francesca; Colombini, Antonella; Muggeo, Paola; Ziino, Ottavio; Melchionda, Fraia; Russo, Giovanna; Pierani, Paolo; Soncini, Elena; DeSantis, Raffaella; et al. (J Pediatr, 2014)
OBJECTIVE: To determine whether a simplified, 1-day/week regimen of trimethoprim/sulfamethoxazole is sufficient to prevent Pneumocystis (jirovecii [carinii]) pneumonia (PCP). Current recommended regimens for prophylaxis against PCP range from daily administration to 3 consecutive days per week dosing. STUDY DESIGN: A prospective survey of the regimens adopted for the PCP prophylaxis in all patients treated for childhood cancer at pediatric hematology-oncology centers of the Associazione Italiana Ematologia Oncologia Pediatrica. RESULTS: The 20 centers participating in the study reported a total of 2466 patients, including 1093 with solid tumor and 1373 with leukemia/lymphoma (or primary immunodeficiency; n = 2). Of these patients, 1371 (55.6%) received the 3-day/week prophylaxis regimen, 406 (16.5%) received the 2-day/week regimen, and 689 (27.9%), including 439 with leukemia/lymphoma, received the 1-day/week regimen. Overall, only 2 cases of PCP (0.08%) were reported, both in the 2-day/week group. By intention to treat, the cumulative incidence of PCP at 3 years was 0.09% overall (95% CI, 0.00-0.40%) and 0.51% for the 2-day/week group (95% CI, 0.10%-2.00%). Remarkably, both patients who failed had withdrawn from prophylaxis. CONCLUSION: A single-day course of prophylaxis with trimethoprim/sulfamethoxazole may be sufficient to prevent PCP in children with cancer undergoing intensive chemotherapy regimens. This simplified strategy might have implications for the emerging need for PCP prophylaxis in other patients subjected to the increased use of biological and nonbiological agents that induce higher levels of immune suppression, such as those with rheumatic diseases.
Keywords: Anti-Infective Agents; Child; Dose-Response Relationship, Drug; Drug Administration Schedule; Follow-Up Studies; Hematologic Neoplasms; Humans; Incidence; Italy; Pneumocystis carinii; Pneumonia, Pneumocystis; Prospective Studies; Treatment Outcome; Trimethoprim, Sulfamethoxazole Drug Combination

Sodium dichloroacetate exhibits anti-leukemic activity in B-chronic lymphocytic leukemia (B-CLL) and synergizes with the p53 activator Nutlin-3. - Agnoletto, Chiara; Melloni, Elisabetta; Casciano, Fabio; Rigolin, Gian Matteo; Rimondi, Erika; Celeghini, Claudio; Brunelli, Laura; Cuneo, Antonio; Secchiero, Paola; Zauli, Giorgio (Oncotarget, 2014)
The anti-leukemic activity of the mitochondria-targeting small molecule sodium dichloroacetate (DCA), used alone and in association with the small molecule inhibitor of the p53/MDM2 interaction Nutlin-3, was analyzed in primary B-chronic lymphocytic leukemia (B-CLL) samples (n=22), normal peripheral blood cells (n=10) and in p53wild-type EHEB, JVM-2, JVM-3 B lymphoblastoid cell lines. DCA exhibited a dose-dependent anti-leukemic activity in both primary B-CLL and B leukemic cell lines with a functional p53 status and showed a synergistic cytotoxic activity when used in combination with Nutlin-3. At the molecular level, DCA positively regulated p53 activity, as documented by post-transcriptional modifications of p53 protein and synergized with Nutlin-3 in increasing the expression of the p53-target genes MDM2, PUMA, TIGAR and in particular p21. The potential role of p21 in mediating the DCA+Nutlin-3 anti-leukemic activity was underscored in knocking-down experiments. Indeed, transfection of leukemic cells with p21 siRNAs significantly decreased the DCA+Nutlin-3-induced cytotoxicity. Taken together, our data emphasize that DCA is a molecule that merits to be further evaluated as a chemotherapeutic agent for B-CLL, likely in combination with other therapeutic compounds.
Keywords: Aged; Aged, 80 and over; Dichloroacetic Acid; Drug Synergism; Female; Humans; Imidazoles; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Middle Aged; Piperazines; Tumor Suppressor Protein p53

Soluble TRAIL is present at high concentrations in seminal plasma and promotes spermatozoa survival. - Zauli, Giorgio; Celeghini, Claudio; Monasta, Lorenzo; Martinelli, Monica; Luppi, Stefania; Gonelli, Arianna; Grill, Vittorio; Ricci, Giuseppe; Secchiero, Paola (Reproduction, 2014)
The expression of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL(TNFSF10)) and of its receptors (TRAILR1, TRAILR2, TRAILR3, and TRAILR4) have been documented in testis, but the presence of soluble TRAIL in seminal fluid, as well as the potential physiopathological role of the TRAIL/TRAILR system in spermatozoa, has not been previously investigated. Male donors (n=123) among couples presenting for infertility evaluation were consecutively enrolled in this study. The presence of soluble TRAIL was analyzed in seminal samples by ELISA, while the surface expression of TRAIL receptors was investigated by flow cytometry. High levels of soluble TRAIL were detected in seminal plasma (median, 11 621 pg/ml and mean±s.d., 13 371±8367 pg/ml) and flow cytometric analysis revealed a variable expression of TRAIL receptors in the sperm cellular fraction among different subjects. In addition, the effect of physiologically relevant concentrations of recombinant TRAIL was investigated on survival and motility of spermatozoa. Of interest, the in vitro exposure of capacitated spermatozoa to recombinant TRAIL (10 ng/ml) significantly preserved their overall survival. Therefore, the present study demonstrates for the first time the presence of elevated levels of the anti-inflammatory cytokine TRAIL in seminal fluids. Moreover, the demonstration that recombinant TRAIL promotes spermatozoa survival after capacitation suggests potential therapeutic implications.
Keywords: Adult; Apoptosis; Enzyme-Linked Immunosorbent Assay; Flow Cytometry; Humans; Infertility, Male; Male; Receptors, TNF-Related Apoptosis-Inducing Ligand; Semen; Sperm Capacitation; Sperm Motility; Spermatozoa; TNF-Related Apoptosis-Inducing Ligand

Spectrum of the mutations in Bernard-Soulier syndrome. - Savoia, Anna; Kunishima, Shinji; De Rocco, Daniela; Zieger, Barbara; Rand, Margaret L; Pujol-Moix, Núria; Caliskan, Umran; Tokgoz, Huseyin; Pecci, Alessandro; Noris, Patrizia; Srivastava, Alok; Ward, Christopher; et al. (Hum Mutat, 2014)
Bernard-Soulier syndrome (BSS) is a rare autosomal recessive bleeding disorder characterized by defects of the GPIb-IX-V complex, a platelet receptor for von Willebrand factor (VWF). Most of the mutations identified in the genes encoding for the GP1BA (GPIbα), GP1BB (GPIbβ), and GP9 (GPIX) subunits prevent expression of the complex at the platelet membrane or more rarely its interaction with VWF. As a consequence, platelets are unable to adhere to the vascular subendothelium and agglutinate in response to ristocetin. In order to collect information on BSS patients, we established an International Consortium for the study of BSS, allowing us to enrol and genotype 132 families (56 previously unreported). With 79 additional families for which molecular data were gleaned from the literature, the 211 families characterized so far have mutations in the GP1BA (28%), GP1BB (28%), or GP9 (44%) genes. There is a wide spectrum of mutations with 112 different variants, including 22 novel alterations. Consistent with the rarity of the disease, 85% of the probands carry homozygous mutations with evidence of founder effects in some geographical areas. This overview provides the first global picture of the molecular basis of BSS and will lead to improve patient diagnosis and management.
Keywords: Alleles; Bernard-Soulier Syndrome; Databases, Nucleic Acid; Founder Effect; Genetic Variation; Humans; Mutation; Platelet Glycoprotein GPIb-IX Complex; Polymorphism, Single Nucleotide; von Willebrand Diseases; Web Browser

Systemic Lupus Erythematosus: Old and New Susceptibility Genes versus Clinical Manifestations. - J, De Azevêdo Silva; C, Addobbati; P, Sandrin-Garcia; S, Crovella (Curr Genomics, 2014)
Systemic Lupus Erythematosus (SLE) is one of the most relevant world-wide autoimmune disorders. The formation of autoantibodies and the deposition of antibody-containing immune complexes in blood vessels throughout the body is the main pathogenic mechanism of SLE leading to heterogeneous clinical manifestations and target tissue damage. The complexity of etiology and pathogenesis in SLE, enclosing genetic and environmental factors, apparently is one of the greatest challenges for both researchers and clinicians. Strong indications for a genetic background in SLE come from studies in families as well as in monozygotic and dizygotic twins, discovering several SLE-associated loci and genes (e.g. IRF5, PTPN22, CTLA4, STAT4 and BANK1). As SLE has a complex genetic background, none of these genes is likely to be entirely responsible for triggering autoimmune response in SLE even if they disclosure a potentially novel molecular mechanisms in the pathogenesis' disease. The clinical manifestations and disease severity varies greatly among patients, thus several studies try to associate clinical heterogeneity and prognosis with specific genetic polymorphisms in SLE associated genes. The continue effort to describe new predisposing or modulating genes in SLE is justified by the limited knowledge about the pathogenesis, assorted clinical manifestation and the possible prevention strategies. In this review we describe newly discovered, as well as the most studied genes associated to SLE susceptibility, and relate them to clinical manifestations of the disease.

Trans-ethnic meta-analysis of white blood cell phenotypes. - Keller, Margaux F; Reiner, Alexander P; Okada, Yukinori; van Rooij, Frank J A; Johnson, Andrew D; Chen, Ming-Huei; Smith, Albert V; Morris, Andrew P; Tanaka, Toshiko; Ferrucci, Luigi; Zonderman, Alan B; Lettre, Guillaume; et al. (Hum Mol Genet, 2014)
White blood cell (WBC) count is a common clinical measure used as a predictor of certain aspects of human health, including immunity and infection status. WBC count is also a complex trait that varies among individuals and ancestry groups. Differences in linkage disequilibrium structure and heterogeneity in allelic effects are expected to play a role in the associations observed between populations. Prior genome-wide association study (GWAS) meta-analyses have identified genomic loci associated with WBC and its subtypes, but much of the heritability of these phenotypes remains unexplained. Using GWAS summary statistics for over 50 000 individuals from three diverse populations (Japanese, African-American and European ancestry), a Bayesian model methodology was employed to account for heterogeneity between ancestry groups. This approach was used to perform a trans-ethnic meta-analysis of total WBC, neutrophil and monocyte counts. Ten previously known associations were replicated and six new loci were identified, including several regions harboring genes related to inflammation and immune cell function. Ninety-five percent credible interval regions were calculated to narrow the association signals and fine-map the putatively causal variants within loci. Finally, a conditional analysis was performed on the most significant SNPs identified by the trans-ethnic meta-analysis (MA), and nine secondary signals within loci previously associated with WBC or its subtypes were identified. This work illustrates the potential of trans-ethnic analysis and ascribes a critical role to multi-ethnic cohorts and consortia in exploring complex phenotypes with respect to variants that lie outside the European-biased GWAS pool.
Keywords: African Americans; Asian Continental Ancestry Group; Bayes Theorem; European Continental Ancestry Group; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Leukocyte Count; Leukocytes; Linkage Disequilibrium; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

An unusual long-term complication of transobturator polypropylene mesh. - Sartore, Andrea; Zennaro, Floriana; Banco, Rubina (Arch Gynecol Obstet, 2014)
Serious complications associated with surgical mesh for transvaginal repair of POP, as infections, vaginal mesh exposure, painful mesh shrinkage and dyspareunia, are not rare. A 48-year-old woman underwent the Perigee procedure because of a stage 3 anterior wall prolapse. Eleven months after surgery, the patient became suddenly unable to walk because of a strong pain to the left thigh root after running. The MRI revealed an external obturator left muscle hyperintensity consistent with muscular oedema; the patient was treated with oral corticosteroids with a complete resolution of the pain. We could hypothesize that the posterior arm of the mesh caused a laceration of the muscles of the obturator space with consequent oedema and pain. The use of the meshes in prolapse surgery can cause unexpected long-term complications.
Keywords: Cystocele; Dyspareunia; Female; Glucocorticoids; Humans; Middle Aged; Pelvic Organ Prolapse; Polypropylenes; Postoperative Complications; Prednisone; Surgical Mesh; Treatment Outcome; Vagina

Unusual splice site mutations disrupt FANCA exon 8 definition. - Mattioli, Chiara; Pianigiani, Giulia; De Rocco, Daniela; Bianco, Anna Monica Rosaria; Cappelli, Enrico; Savoia, Anna; Pagani, Franco (Biochim Biophys Acta, 2014)
The pathological role of mutations that affect not conserved splicing regulatory sequences can be difficult to determine. In a patient with Fanconi anemia, we identified two unpredictable splicing mutations that act on either sides of FANCA exon 8. In patients-derived cells and in minigene splicing assay, we showed that both an apparently benign intronic c.710-5T>C transition and the nonsense c.790C>T substitution induce almost complete exon 8 skipping. Site-directed mutagenesis experiments indicated that the c.710-5T>C transition affects a polypyrimidine tract where most of the thymidines cannot be compensated by cytidines. The c.790C>T mutation located in position -3 relative to the donor site induce exon 8 skipping in an NMD-independent manner and complementation experiments with modified U1 snRNAs showed that U1 snRNP is only partially involved in the splicing defect. Our results highlight the importance of performing splicing functional assay for correct identification of disease-causing mechanism of genomic variants and provide mechanistic insights on how these two FANCA mutations affect exon 8 definition.
Keywords: Base Sequence; Cell Line, Tumor; Codon, Nonsense; Exons; Fanconi Anemia Complementation Group A Protein; HeLa Cells; Humans; Introns; Molecular Sequence Data; Mutagenesis, Site-Directed; Ribonucleoproteins, Small Nuclear; RNA Splice Sites; RNA Splicing

Validation of point-of-care testing for coeliac disease in children in a tertiary hospital in north India. - Singh, Prashant; Wadhwa, Nitya; Chaturvedi, Mona K; Bhatia, Vidyut; Saini, Savita; Tandon, Nikhil; Makharia, Govind K; Maki, Markku; Not, Tarcisio; Phillips, Alan; Bhatnagar, Shinjini (Arch Dis Child, 2014)
OBJECTIVE: Some of the conventional serological tests for coeliac disease (CD) are expensive, time-consuming and not readily available in developing countries, leading to a delay in diagnosis. Recently, point-of-care tests (POCT) have been manufactured and tested in Europe but have not been validated in our setting. We therefore aimed to study the diagnostic accuracy of the POCT 'Biocard' test in diagnosing CD in Indian children. DESIGN: Cross-sectional study. SETTING: Tertiary care centre in north India. PATIENTS: Children, aged 2-18 years, with chronic diarrhoea, short stature or refractory anaemia underwent serological testing for CD with antiendomysial antibodies (AEA), antitissue transglutaminase (tTG) antibodies and Biocard test followed by duodenal biopsy irrespective of serological results. CD was diagnosed with positive AEA and duodenal biopsy showing >grade 2 changes using modified Marsh criteria. Those who were both AEA negative and had normal histology were considered CD negative. RESULTS: Of 319 children who underwent the serological testing, 170 agreed for biopsy. Of these, 110 were diagnosed with CD and 30 were found to be CD negative. Remaining 30 had discordant AEA and histology results and were not included in analysis. Biocard test agreed with 92/110 positive and 27/30 negative diagnoses based on reference tests (83.6% sensitivity and 90% specificity). tTG was found to be 93.8% sensitive and 96.4% specific. CONCLUSIONS: We successfully validated the POCT for CD in our setting. It could be used to increase case detection rates in developing countries with a large undiagnosed CD burden.
Keywords: Adolescent; Celiac Disease; Child; Child, Preschool; Cross-Sectional Studies; Female; Humans; India; Male; Point-of-Care Systems; Sensitivity and Specificity; Serologic Tests; Tertiary Care Centers

Does EMLA cream application interfere with the success of venipuncture or venous cannulation? A prospective multicenter observational study. - Schreiber, S; Ronfani, L; Chiaffoni, G P; Matarazzo, L; Minute, M; Panontin, E; Poropat, F; Germani, C; Barbi, E (Eur J Pediatr, 2013)
UNLABELLED: Venipuncture and intravenous cannulation are the most common painful procedures performed on children. The most widely used topical anesthetic is eutectic mixture of local anesthetics (EMLA). EMLA use is associated with a transient cutaneous vasoconstriction which can make it difficult to identify veins. We assessed with a prospective, multicenter, observational study whether EMLA interferes with venipuncture and intravenous cannulation. The primary study outcome was a success at first attempt in the course of venipuncture or venous cannulation. The study enrolled 388 children; 255 of them received EMLA and 133 did not. Eighty-six percent of procedures were successful at the first attempt in the EMLA group and 76.7 % in the no EMLA group. CONCLUSION: In this study, EMLA use did not interfere with the success of venipuncture or venous cannulation in children.
Keywords: Anesthetics, Local; Catheterization, Peripheral; Child; Child, Preschool; Female; Humans; Lidocaine; Logistic Models; Male; Ointments; Phlebotomy; Prilocaine; Prospective Studies; Vasoconstriction

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

Human colostrum and breast milk contain high levels of TNF-related apoptosis-inducing ligand (TRAIL). - Davanzo, Riccardo; Zauli, Giorgio; Monasta, Lorenzo; Vecchi Brumatti, Liza; Abate, Maria Valentina; Ventura, Giovanna; Rimondi, Erika; Secchiero, Paola; Demarini, Sergio (J Hum Lact, 2013)
BACKGROUND: TNF-related apoptosis inducing ligand (TRAIL) is a pleiotropic cytokine, which plays a key role in the immune system as well as in controlling the balance of apoptosis and proliferation in various organs and tissues. OBJECTIVE: To investigate the presence and levels of soluble TRAIL in human colostrum and milk. METHODS: The levels of soluble human TRAIL were measured in human colostrum (day 2 after delivery) and breast milk (day 5 after delivery). The presence of TRAIL was also measured in infant formula. RESULTS: Levels of soluble TRAIL in the colostrum and mature human milk were, respectively, at least 400 and 100 fold higher than those detected in human serum. No TRAIL was detected in formula. CONCLUSION: Human soluble TRAIL is present at extremely high levels in human colostrum and human milk and might have a significant role in mediating the anti-cancer activity of human milk.
Keywords: Adult; Apgar Score; Colostrum; Female; Gestational Age; Humans; Infant Formula; Infant, Newborn; Milk, Human; TNF-Related Apoptosis-Inducing Ligand

MYH9-related disease: five novel mutations expanding the spectrum of causative mutations and confirming genotype/phenotype correlations. - De Rocco, Daniela; Zieger, Barbara; Platokouki, Helen; Heller, Paula G; Pastore, Annalisa; Bottega, Roberta; Noris, Patrizia; Barozzi, Serena; Glembotsky, Ana C; Pergantou, Helen; Balduini, Carlo L; Savoia, Anna; et al. (Eur J Med Genet, 2013)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant syndromic disorder caused by mutations in MYH9, the gene encoding for the heavy chain of non-muscle myosin IIA (myosin-9). MYH9-RD is characterized by congenital macrothrombocytopenia and typical inclusion bodies in neutrophils associated with a variable risk of developing sensorineural deafness, presenile cataract, and/or progressive nephropathy. The spectrum of mutations responsible for MYH9-RD is limited. We report five families, each with a novel MYH9 mutation. Two mutations, p.Val34Gly and p.Arg702Ser, affect the motor domain of myosin-9, whereas the other three, p.Met847_Glu853dup, p.Lys1048_Glu1054del, and p.Asp1447Tyr, hit the coiled-coil tail domain of the protein. The motor domain mutations were associated with more severe clinical phenotypes than those in the tail domain.
Keywords: Adolescent; Adult; Amino Acid Sequence; Amino Acid Substitution; Base Sequence; Child; Child, Preschool; Exons; Female; Genes, Dominant; Genetic Association Studies; Humans; Male; Middle Aged; Models, Molecular; Molecular Motor Proteins; Molecular Sequence Data; Mutation; Myosin Heavy Chains; Pedigree; Protein Conformation; Sequence Alignment; Syndrome; Thrombocytopenia; Young Adult

Organizing national responses for rare blood disorders: the Italian experience with sickle cell disease in childhood. - Colombatti, Raffaella; Perrotta, Silverio; Samperi, Piera; Casale, Maddalena; Masera, Nicoletta; Palazzi, Giovanni; Sainati, Laura; Russo, Giovanna (Orphanet J Rare Dis, 2013)
BACKGROUND: Sickle cell disease (SCD) is the most frequent hemoglobinopathy worldwide but remains a rare blood disorder in most western countries. Recommendations for standard of care have been produced in the United States, the United Kingdom and France, where this disease is relatively frequent because of earlier immigration from Africa. These recommendations have changed the clinical course of SCD but can be difficult to apply in other contexts. The Italian Association of Pediatric Hematology Oncology (AIEOP) decided to develop a common national response to the rising number of SCD patients in Italy with the following objectives: 1) to create a national working group focused on pediatric SCD, and 2) to develop tailored guidelines for the management of SCD that could be accessed and practiced by those involved in the care of children with SCD in Italy. METHODS: Guidelines, adapted to the Italian social context and health system, were developed by 22 pediatric hematologists representing 54 AIEOP centers across Italy. The group met five times for a total of 128 hours in 22 months; documents and opinions were circulated via web. RESULTS: Recommendations regarding the prevention and treatment of the most relevant complications of SCD in childhood adapted to the Italian context and health system were produced. CONCLUSIONS: Creating a network of physicians involved in the day-to-day care of children with SCD is feasible in a country where it remains rare. Providing hematologists, primary and secondary care physicians, and caregivers across the country with web-based guidelines for the management of SCD tailored to the Italian context is the first step in building a sustainable response to a rare but emerging childhood blood disorder and in implementing the World Health Organization's suggestion "to design (and) implement … comprehensive national integrated programs for the prevention and management of SCD".
Keywords: Adolescent; Anemia, Sickle Cell; Child; Child, Preschool; Disease Management; Female; Hematologic Diseases; Humans; Infant; Infant, Newborn; Italy; Male; Neonatal Screening; Rare Diseases

Patients affected by metabolic syndrome show decreased levels of circulating platelet derived growth factor (PDGF)-BB. - Tisato, Veronica; Toffoli, Barbara; Monasta, Lorenzo; Bernardi, Stella; Candido, Riccardo; Zauli, Giorgio; Secchiero, Paola (Clin Nutr, 2013)
BACKGROUND & AIMS: The development and/or progression of metabolic syndrome (MetS) in overweight and obese individuals have been associated to low-grade inflammation, but few studies have simultaneously analyzed the circulating levels of several cytokines. METHODS: In this pilot study, a group of 27 cytokines and growth factors was analyzed in the serum of obese patients (n=40) diagnosed for MetS in comparison with sex- and age-matched control subjects without MetS (n=53) by using a multiplex immunoassay. Release of cytokines was measured in culture supernatants of human primary endothelial cells, THP-1 macrophagic cells and HuH-7 hepatoma cells upon exposure to a high fat mixture. RESULTS: While the majority of cytokines did not show significant differences between the investigated groups, the circulating levels of CXCL10/IP-10 and IL-6 were higher in the MetS group versus overweight control group. In contrast, PDGF-BB serum levels were significantly decreased in MetS patients. The in vitro addition of a high fat mixture increased the release of IL-6 and/or CXCL10/IP-10 in the culture supernatant of human primary endothelial cells and THP-1 macrophagic cells, while the same mixture significantly decreased the release of PDGF-BB by human THP-1 macrophagic and HuH-7 hepatoma cells. CONCLUSIONS: The current demonstration that MetS is associated with decrease of the pro-fibrotic PDGF cytokine is a completely novel finding, which adds complexity to the interplay between inflammation and fibrosis in patients affected by MetS.
Keywords: Adolescent; Adult; Aged; Case-Control Studies; Cell Line, Tumor; Chemokine CXCL10; Endothelial Cells; Female; Humans; Interleukin-6; Linear Models; Male; Metabolic Syndrome X; Middle Aged; Obesity; Pilot Projects; Proto-Oncogene Proteins c-sis; RNA, Messenger; Young Adult

Safety and efficacy of infliximab and adalimumab for refractory uveitis in juvenile idiopathic arthritis: 1-year followup data from the Italian Registry. - Zannin, Maria E; Birolo, Carolina; Gerloni, Valeria M; Miserocchi, Elisabetta; Pontikaki, Irene; Paroli, Maria P; Bracaglia, Claudia; Shardlow, Alison; Parentin, Fulvio; Cimaz, Rolando; Simonini, Gabriele; Falcini, Fernanda; et al. (J Rheumatol, 2013)
OBJECTIVE: To evaluate safety and efficacy of adalimumab (ADA) and infliximab (IFX) for the treatment of juvenile idiopathic arthritis-related anterior uveitis (JIA-AU). METHODS: Starting January 2007, patients with JIA-AU treated with IFX and ADA were managed by a standard protocol and data were entered into the National Italian Registry (NIR). At baseline, all patients were refractory to standard immunosuppressive treatment and/or were corticosteroid-dependent. Data recorded every 3 months included uveitis course, number/type of ocular complications, drug-related adverse events (AE), treatment change or withdrawal, and laboratory measures. Data of patients treated for at least 1 year were retrieved from the NIR and analyzed using descriptive statistics. Treatment efficacy was based on change in uveitis course and in number of ocular complications. RESULTS: Up to December 2009, data for 108 patients with JIA-AU treated with anti-tumor necrosis factor-α agents were recorded in the NIR and data from 91, with at least 12 months' followup, were included in the study. Forty-eight patients were treated with IFX, 43 with ADA. Forty-seven patients (55.3%) achieved remission of AU, 28 (32.9%) had recurrent AU, and 10 (11.8%) maintained a chronic course. A higher remission rate was observed with ADA (67.4% vs 42.8% with IFX; p = 0.025). Ocular complications decreased from 0.47 to 0.32 per subject. Five patients experienced resolution of structural complications. No patient reported serious AE; 8 (8.8%) experienced 11 minor AE (9 with IFX, 2 with ADA). CONCLUSION: IFX and ADA appear to be effective and safe for treatment of refractory JIA-related uveitis, with a better performance of ADA in the medium-term period.
Keywords: Adolescent; Antibodies, Monoclonal; Antibodies, Monoclonal, Humanized; Antirheumatic Agents; Arthritis, Juvenile; Child; Child, Preschool; Female; Follow-Up Studies; Humans; Infant; Italy; Male; Registries; Treatment Outcome; Tumor Necrosis Factor-alpha; Uveitis

Accuracy of diagnostic antibody tests for coeliac disease in children: summary of an evidence report. - Giersiepen, Klaus; Lelgemann, Monika; Stuhldreher, Nina; Ronfani, Luca; Husby, Steffen; Koletzko, Sibylle; Korponay-Szabó, Ilma R (J Pediatr Gastroenterol Nutr, 2012)
OBJECTIVE: The aim of this study was to summarise the evidence from 2004 to September 2009 on the performance of laboratory-based serological and point of care (POC) tests for diagnosing coeliac disease (CD) in children using histology as reference standard. PATIENTS AND METHODS: We searched MEDLINE and EMBASE for studies reporting on children for tests based on IgA and IgG anti-gliadin (AGA), endomysial (EmA), anti-transglutaminase-2 (TG2), and anti-deamidated gliadin peptides (DGP) antibodies or POC tests. For inclusion, histological analysis of duodenal biopsies and sensitivity and specificity for index tests had to be reported. Data were pooled and summary measures calculated for sensitivity, specificity, positive and negative likelihood ratios ("LR+", "LR-"), and diagnostic odds ratios (DOR). In case of elevated statistical heterogeneity, studies reaching 90% sensitivity or specificity were reported. RESULTS: A total of 2510 articles were reviewed; 16 entered meta-analysis, reporting on 3110 patients (1876 with CD, 1234 without CD). For IgA-EmA, sensitivity was ≥90% in 7/11 studies and pooled specificity 98.2%. For IgA-anti-TG2, 11/15 studies yielded sensitivities ≥90% and 13/15 specificities ≥90%. For IgA-DGP, sensitivity ranged between 80.7% and 95.1% (specificity 86.3%-93.1%); for IgG-DGP between 80.1% and 98.6% (specificity 86.0-96.9%). IgA-EmA had the highest pooled DOR (554) and LR+ (31.8) for a laboratory test, followed by IgA-anti-TG2, IgG-DGP, IgA-DGP and IgA-AGA. POC tests showed a pooled sensitivity of 96.4% for IgA-TG2 (specificity 97.7%). CONCLUSIONS: IgA-EmA and IgA-anti-TG2 tests appear highly accurate to diagnose CD. IgG-anti-DGP tests may help in excluding CD. IgA-AGA and IgA-DGP tests show inferior accuracy. POC tests may achieve high accuracy in the hands of experienced readers, but IgA-anti-TG2/EmA were superior.
Keywords: Autoantibodies; Biological Markers; Celiac Disease; Child; Gliadin; GTP-Binding Proteins; Humans; Immunoglobulin A; Immunoglobulin G; Point-of-Care Systems; Sensitivity and Specificity; Transglutaminases

Activation of the p53 pathway induces α-smooth muscle actin expression in both myeloid leukemic cells and normal macrophages. - Secchiero, Paola; Rimondi, Erika; di Iasio, Maria Grazia; Voltan, Rebecca; Gonelli, Arianna; Zauli, Giorgio (J Cell Physiol, 2012)
A range of cell types of mesenchymal origin express α-smooth muscle actin (α-SMA), a protein that plays a key role in controlling cell motility and differentiation along the fibrocyte and myofibroblast lineages. Although α-SMA is often expressed in stromal cells associated to a variety of cancers including hematological malignancies, up to now the role of anti-cancer drugs on α-SMA has not been deeply investigated. In this study, we demonstrated that Nutlin-3, the small molecule inhibitor of the MDM2/p53 interactions, significantly up-regulated the mRNA and protein levels of α-SMA in normal macrophages as well as in p53(wild-type) but not in p53(mutated/null) myeloid leukemic cells. The p53-dependence of α-SMA up-regulation induced by Nutlin-3 was demonstrated in experiments performed with siRNA for p53. Of note, Nutlin-3 mediated up-regulation of α-SMA in OCI leukemic cells was accompanied by cell adhesion to plastic substrate and by reduced cell migratory response in transwell assays. Notably, the role of α-SMA induction in the modulation of myeloid cell migration was clearly documented in α-SMA gene knockdown experiments. In addition, Nutlin-3 significantly up-regulated α-SMA expression in primary endothelial cells, but not in fibroblasts and mesenchymal stem cells (MSC). Conversely, transforming growth factor-β1 up-regulated α-SMA in fibroblasts and MSC, but not in macrophages and endothelial cells. Taken together, these data indicate that Nutlin-3 is a potent inducer of α-SMA in both normal and leukemic myeloid cells as well as in endothelial cells.
Keywords: Actins; Cell Movement; Cells, Cultured; Endothelial Cells; Fibroblasts; Humans; Imidazoles; Leukemia, Myeloid; Macrophages; Mesenchymal Stromal Cells; Piperazines; Proto-Oncogene Proteins c-mdm2; RNA, Small Interfering; Signal Transduction; Transforming Growth Factor beta1; Tumor Suppressor Protein p53

Adverse effects during specific oral tolerance induction: in home phase. - Barbi, E; Longo, G; Berti, I; Matarazzo, L; Rubert, L; Saccari, A; Lenisa, I; Ronfani, L; Radillo, O; Ventura, A (Allergol Immunopathol (Madr), 2012)
BACKGROUND: Specific oral tolerance induction (SOTI) is a promising approach for severe food allergies. There are little data in the literature regarding the home-phase of SOTI, not only with regard to type and frequency of adverse reactions but also regarding the most suitable treatment and protocol. AIMS: To define the incidence and severity of adverse reactions, possible risk factors, and the safety and effectiveness of the home-phase of an original SOTI protocol in a large group of children with severe cow's milk (CM) allergy, after the hospital "rush" phase. METHODS: The study was conducted by recording in-home phase adverse events, success and failure as reported by parents, and calling families. Adverse reactions were treated following the International Guidelines, arbitrarily modified by introducing nebulised epinephrine for respiratory reactions, oral beclomethasone for acute gastric pain and oral cromolyn for recurrent gastric pain. RESULTS: Out of 140 patients, 132 were contacted; eight were inaccessible (follow-up 2-84 months). The number of adverse reactions was 1 in every 100 doses. The reactions were treated with nebulised epinephrine (221 reactions), IM epinephrine (6 reactions), and other drugs. Patients with high specific IgE levels (greater than 100 kU(A)/L) and lower CM dose (less than 5 ml) at the end of in-hospital phase showed a higher risk both for number of reactions and use of nebulised epinephrine. CONCLUSIONS: The home phase of SOTI was characterised by a significant number of adverse reactions, mostly managed with an acceptable rate of side effects. Nebulised epinephrine played a pivotal role in respiratory reactions.
Keywords: Adolescent; Adult; Age Factors; Allergens; Child; Child, Preschool; Desensitization, Immunologic; Epinephrine; Female; Food Hypersensitivity; Humans; Immune Tolerance; Immunoglobulin E; Male; Milk Hypersensitivity; Nebulizers and Vaporizers

Adverse effects during specific oral tolerance induction: in-hospital "rush" phase. - Barbi, E; Longo, G; Berti, I; Neri, E; Saccari, A; Rubert, L; Matarazzo, L; Montico, M; Ventura, A (Eur Ann Allergy Clin Immunol, 2012)
BACKGROUND: Specific oral tolerance induction (SOTI) is a promising approach in the treatment of severe food allergies. Different protocols have demonstrated its efficacy. Nevertheless, SOTI is still considered an experimental method and should be limited to highly controlled settings. AIMS: To define the incidence and severity of adverse reactions, possible risk factors, and the safety and effectiveness of nebulized epinephrine as a first-line treatment of respiratory reactions during in-hospital SOTI for cow's milk allergy. MATERIALS AND METHODS: A retrospective study was conducted by reviewing the medical records of patients admitted for SOTI beginning in 2001. Reactions were classified as mild, moderate and severe on a partially modified Clark scale. Adverse reactions were treated following the International Guidelines with the introduction of nebulized epinephrine for level four reactions. RESULTS: Of 209 patients, 17 were excluded due to the absence of objective reactions. The remaining 192 were classified as follows: Mild Reactions (Clark Scale 1 to 3): 100 patients received either no treatment, oral antihistamines or nebulized steroids; Moderate Reactions (Clark Scale 4): 87 patients treated with nebulized epinephrine and, depending on their symptoms, oral antihistamines, corticosteroids (nebulized, oral or IV) or nebulized beta 2 agonists; Severe Reactions (Clark Scale 5): 5 children, 4 of whom initially underwent one nebulization of epinephrine and eventually required an IM dose. The fifth patient was immediately treated with IM epinephrine due to hypotension. DISCUSSION: adverse reactions during this in-hospital SOTI protocol were frequent but easily manageable. Nebulized epinephrine can play a relevant role in the treatment of respiratory reactions.
Keywords: Administration, Inhalation; Anaphylaxis; Animals; Bronchodilator Agents; Child; Desensitization, Immunologic; Epinephrine; Humans; Milk; Milk Hypersensitivity; Retrospective Studies

Alteration of liver enzymes is a feature of the MYH9-related disease syndrome. - Pecci, Alessandro; Biino, Ginevra; Fierro, Tiziana; Bozzi, Valeria; Mezzasoma, Annamaria; Noris, Patrizia; Ramenghi, Ugo; Loffredo, Giuseppe; Fabris, Fabrizio; Momi, Stefania; Magrini, Umberto; Pirastu, Mario; et al. (PLoS One, 2012)
BACKGROUND: MYH9-related disease (MYH9-RD) is a rare autosomal dominant genetic syndrome characterized by congenital thrombocytopenia associated with the risk of developing progressive nephropathy, sensorineural deafness, and presenile cataract. During the collection of a large case-series of patients with MYH9-RD we noticed several cases with unexplained elevation of liver enzymes. Our aim was to evaluate if the alteration of liver tests is a feature of the MYH9-RD and to define its clinical significance. METHODS AND FINDINGS: Data concerning liver tests, prospectively recorded in the Italian Registry for MYH9-RD, were collected and compared with those of three control populations: patients with autoimmune thrombocytopenia, patients with inherited thrombocytopenias other than MYH9-RD, and the participants to a large epidemiologic survey in an Italian geographic isolate. Thirty-eight of 75 evaluable MYH9-RD patients (50.7%) showed an elevation of ALT and/or AST, and 17 of 63 (27.0%) an increase of GGT. The increases ranged from 1.9 ± 0.7 to 2.7 ± 1.6 fold the upper normal limit. The prevalence of liver test alterations was significantly higher in MYH9-RD patients than in each of the control populations, with odds ratios ranging from 8.2 (95% CIs 2.2-44.8) to 24.7 (14.8-40.8). Clinical follow-up and more detailed liver studies of a subset of patients, including ultrasound liver scan, liver elastography and liver biopsy in one case, did not show any significant structural damage or evolution towards liver insufficiency. CONCLUSIONS: Elevation of liver enzymes is a frequent and previously unrecognized feature of the MYH9-RD syndrome; however, this defect does not appear to have poor prognostic value.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Aged; Aged, 80 and over; Biopsy; Case-Control Studies; Child; Child, Preschool; Demography; Female; Follow-Up Studies; Humans; Immunohistochemistry; Infant; Liver; Liver Function Tests; Male; Middle Aged; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Odds Ratio; Syndrome; Young Adult

Anti-leukemic activity of dasatinib in both p53(wild-type) and p53(mutated) B malignant cells. - Bosco, Raffaella; Rabusin, Marco; Voltan, Rebecca; Celeghini, Claudio; Corallini, Federica; Capitani, Silvano; Secchiero, Paola (Invest New Drugs, 2012)
The multi-kinase inhibitor dasatinib induced a variable but significant decrease of viability in both p53(wild-type) (EHEB, JVM-2, JVM-3) and p53(mutated) (MEC-1, MEC-2, BJAB) prolymphocytic B leukemic cells, due to a combination of cell cycle block in G1 and apoptosis. Antibody phospho-kinase array analysis revealed that dasatinib inhibited the phosphorylation of various kinases, including ERK1/2 and p38/MAPK as well as of STAT3 transcription factors, in both p53(wild-type) and p53(mutated) cells. Therefore, dasatinib might offer a novel therapeutic strategy not only for p53(wild-type), but also for p53(mutated) B malignancies that have the worst prognosis and urgently need innovative therapeutic approaches.
Keywords: Antineoplastic Agents; Apoptosis; B-Lymphocytes; Cell Line, Tumor; Cell Survival; G1 Phase Cell Cycle Checkpoints; Granulocyte Precursor Cells; Humans; Leukemia, Prolymphocytic, B-Cell; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 3; Mutation; p38 Mitogen-Activated Protein Kinases; Phosphorylation; Protein Kinase Inhibitors; Pyrimidines; STAT3 Transcription Factor; Thiazoles; Time Factors; Tumor Suppressor Protein p53

Association of MBL2 gene exon 1 variants with autoimmune thyroid disease in Brazilian patients. - Filho, C B; Rodrigues, F F; Segat, L; Fonseca, A M; Araujo, J; Arahata, C; Pontes, L; Vilar, L; de Lima Filho, J L; Crovella, S (Int J Immunogenet, 2012)
We investigated the association between MBL2 gene exon 1 functional polymorphisms and autoimmune thyroid disease (AITD) in 163 Brazilian patients (87 with Hashimoto thyroiditis, HT; 76 with Graves' disease) and 214 healthy controls. Individuals carrying MBL2 O allele are at higher risk of developing AITD (OR = 1.58, 95% CI: 1.11-2.26; P-value = 0.009) and HT (OR = 1.67, 95% CI: 1.09-2.55; P-value = 0.013) as suggesting a possible role for mannose-binding lectin in influencing disease susceptibility.
Keywords: Adolescent; Adult; Brazil; Case-Control Studies; Child; Child, Preschool; Exons; Female; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Testing; Graves Disease; Hashimoto Disease; Humans; Infant; Male; Mannose-Binding Lectin; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

CD14 polymorphisms correlate with an augmented risk for celiac disease in Italian patients. - Catamo, E; Segat, L; Lenarduzzi, S; Petix, V; Morgutti, M; Crovella, S (Genes Immun, 2012)
Celiac disease (CD) is a T-cell-mediated chronic inflammatory disease characterized by autoimmune, immunological and environmental components, where genetic factors in addition to the main known risk factors (gliadin and human leukocyte antigen (HLA)-DQ haplotypes) are supposed to be involved. CD14 is a multifunctional receptor involved in the bacterial lipopolysaccharides-dependent signal transduction. The CD14 gene maps on the long arm of chromosome 5 (5q22-q32), a 'hotbed' region for CD; promoter polymorphisms are known to influence its expression. In this study we analyzed three CD14 promoter polymorphisms (c.-1359G>T, c.-1145A>G and c.-159C>T, ) in 938 CD Italian patients and 533 healthy controls, with known HLA-DQ haplotypes, with the aim of evaluating their possible association with the disease. The c.-1145A>G G and c.-159C>T T alleles (as well as the combination of the two alleles in the GT haplotype), were identified as susceptibility factors for CD development, being significantly more frequent in CD patients than in healthy controls. This association was also confirmed when the analysis was restricted to only those subjects characterized by HLA-DQ risk haplotypes. Our results indicate the involvement of CD14 gene polymorphisms in the susceptibility to CD.
Keywords: Adolescent; Adult; Aged; Antigens, CD14; Case-Control Studies; Celiac Disease; Child; Child, Preschool; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Haplotypes; HLA Antigens; Humans; Infant; Italy; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Young Adult

Chemerin regulates NK cell accumulation and endothelial cell morphogenesis in the decidua during early pregnancy. - Carlino, Claudia; Trotta, Eleonora; Stabile, Helena; Morrone, Stefania; Bulla, Roberta; Soriani, Alessandra; Iannitto, Maria Luisa; Agostinis, Chiara; Mocci, Carlo; Minozzi, Massimo; Aragona, Cesare; Perniola, Giorgia; et al. (J Clin Endocrinol Metab, 2012)
CONTEXT: Although decidual natural killer (NK) cell accumulation and vascular remodeling are critical steps to ensure successful pregnancy, the molecular mechanisms controlling these events are poorly defined. OBJECTIVE: Herein we analyzed whether chemerin, a recently identified chemoattractant involved in many pathophysiological processes, could be expressed in the uterine compartment and could regulate events relevant for the good outcome of pregnancy. DESIGN: Chemerin expression in human primary culture of stromal (ST) cells, extravillous trophoblast cells, and decidual endothelial cells (DEC) was analyzed by RT-PCR, ELISA, and Western blot. Migration through ST or DEC of peripheral blood and decidual (d) NK cells from pregnant women was performed using a transwell assay. A DEC capillary-like tube formation assay was used to evaluate endothelial morphogenesis. RESULTS: Chemerin is differentially expressed by decidual cells during early pregnancy being present at high levels in ST and extravillous trophoblast cells but not in DEC. Notably, ST cells from pregnant women exhibit and release higher levels of chemerin as compared with ST cells from menopausal or fertile nonpregnant women. Chemerin can support peripheral blood NK cell migration through both DEC and ST cells. Although dNK cells exhibit lower chemerin receptor (CMKLR1) expression than their blood counterpart, CMKLR1 engagement on dNK cells resulted in both ERK activation and migration through decidual ST cells. Interestingly, DEC also express CMKLR1 and undergo ERK activation and capillary-like tube structure formation upon exposure to chemerin. CONCLUSIONS: Our data indicate that chemerin is up-regulated during decidualization and might contribute to NK cell accumulation and vascular remodeling during early pregnancy.
Keywords: Capillaries; Cell Movement; Chemokines; Decidua; Endothelial Cells; Female; Humans; Killer Cells, Natural; MAP Kinase Signaling System; Neovascularization, Physiologic; Pregnancy; Pregnancy Trimester, First; Receptors, Chemokine; RNA, Messenger; Stromal Cells; Trophoblasts

Clinical and laboratory features of 103 patients from 42 Italian families with inherited thrombocytopenia derived from the monoallelic Ala156Val mutation of GPIbα (Bolzano mutation). - Noris, Patrizia; Perrotta, Silverio; Bottega, Roberta; Pecci, Alessandro; Melazzini, Federica; Civaschi, Elisa; Russo, Sabina; Magrin, Silvana; Loffredo, Giuseppe; Di Salvo, Veronica; Russo, Giovanna; Casale, Maddalena; et al. (Haematologica, 2012)
BACKGROUND: Bernard-Soulier syndrome is a very rare form of inherited thrombocytopenia that derives from mutations in GPIbα, GPIbβ, or GPIX and is typically inherited as a recessive disease. However, some years ago it was shown that the monoallelic c.515C>T transition in the GPIBA gene (Bolzano mutation) was responsible for macrothrombocytopenia in a few Italian patients. DESIGN AND METHODS: Over the past 10 years, we have searched for the Bolzano mutation in all subjects referred to our institutions because of an autosomal, dominant form of thrombocytopenia of unknown origin. RESULTS: We identified 42 new Italian families (103 cases) with a thrombocytopenia induced by monoallelic Bolzano mutation. Analyses of the geographic origin of affected pedigrees and haplotypes indicated that this mutation originated in southern Italy. Although the clinical expression was variable, patients with this mutation typically had a mild form of Bernard-Soulier syndrome with mild thrombocytopenia and bleeding tendency. The most indicative laboratory findings were enlarged platelets and reduced GPIb/IX/V platelet expression; in vitro platelet aggregation was normal in nearly all of the cases. CONCLUSIONS: Our study indicates that monoallelic Bolzano mutation is the most frequent cause of inherited thrombocytopenia in Italy, affecting 20% of patients recruited at our institutions during the last 10 years. Because many people from southern Italy have emigrated during the last century, this mutation may have spread to other countries.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Bernard-Soulier Syndrome; Child; Child, Preschool; Family Health; Female; Heterozygote; Humans; Infant; Italy; Male; Membrane Glycoproteins; Middle Aged; Mutation, Missense; Platelet Aggregation; Platelet Count; Platelet Glycoprotein GPIb-IX Complex; Polymorphism, Genetic; Thrombocytopenia; Thrombopoietin; Tubulin; Young Adult

The clinical interpretation and significance of electronic fetal heart rate patterns 2 h before delivery: an institutional observational study. - Maso, Gianpaolo; Businelli, Caterina; Piccoli, Monica; Montico, Marcella; De Seta, Francesco; Sartore, Andrea; Alberico, Salvatore (Arch Gynecol Obstet, 2012)
PURPOSE: To evaluate the clinical significance of intrapartum fetal heart rate (FHR) monitoring in low-risk pregnancies according to guidelines and specific patterns. METHODS: An obstetrician, blinded to neonatal outcome, retrospectively reviewed 198 low-risk cases that underwent continuous electronic fetal monitoring (EFM) during the last 2 h before delivery. The tracings were interpreted as normal, suspicious or pathological, according to specific guidelines of EFM and by grouping the different FHR patterns considering baseline, variability, presence of decelerations and bradycardia. The EFM groups and the different FHR-subgroups were associated with neonatal acid base status at birth, as well as the short-term neonatal composite outcome. Comparisons between groups were performed with Kruskal-Wallis test. Differences among categorical variables were evaluated using Fisher's exact test. Significance was set at p < 0.05 level. RESULTS: Significant differences were found for mean pH values in the three EFM groups, with a significant trend from "normal" [pH 7.25, 95 % confidence interval (CI) 7.28-7.32] to "pathological" tracings (pH 7.20, 95 % CI 7.17-7.13). Also the rates of adverse composite neonatal outcome were statistically different between the two groups (p < 0.005). Among the different FHR patterns, tracings with atypical variable decelerations and severe bradycardia were more frequently associated with adverse neonatal composite outcome (11.1 and 26.7 %, respectively). However, statistically significant differences were only observed between the subgroups with normal tracings and bradycardia. CONCLUSIONS: In low-risk pregnancies, there is a significant association between neonatal outcome and EFM classification. However, within abnormal tracings, neonatal outcome might differ according to specific FHR pattern.
Keywords: Acidosis; Bradycardia; Female; Fetal Blood; Fetal Monitoring; Heart Rate, Fetal; Humans; Hydrogen-Ion Concentration; Infant, Newborn; Labor, Obstetric; Predictive Value of Tests; Pregnancy; Pregnancy Outcome; Retrospective Studies; Single-Blind Method; Statistics, Nonparametric; Time Factors

Coeliac disease diagnosis: ESPGHAN 1990 criteria or need for a change? Results of a questionnaire. - Ribes-Koninckx, C; Mearin, M L; Korponay-Szabó, I R; Shamir, R; Husby, S; Ventura, A; Branski, D; Catassi, C; Koletzko, S; Mäki, M; Troncone, R; Zimmer, K P (J Pediatr Gastroenterol Nutr, 2012)
BACKGROUND AND OBJECTIVES: A revision of criteria for diagnosing coeliac disease (CD) is being conducted by The European Society for Pediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN). In parallel, we have performed a survey aimed to evaluate present practices for CD among paediatric gastroenterologists and to learn their views on the need for modification of present criteria for CD diagnosis. PATIENTS AND METHODS: Questionnaires were distributed to experienced paediatric gastroenterologists (ESPGHAN members) via the Internet. RESULTS: Overall, 95 valid questionnaires were available for analysis, pertaining to 28 different countries, with the majority of responders treating patients with CD for >15 years. Only about 12% of the responders comply with present criteria, noncompliance being related mainly to the challenge policy. Approximately 90% request a revision and modification of the present criteria. Forty-four percent want to omit the small bowel biopsy in symptomatic children with positive anti-tissue transglutaminase immunoglobulin (Ig) A or endomysial IgA antibodies, especially if they are DQ2/DQ8 positive. For silent cases detected by screening with convincingly positive anti-tissue transglutaminase IgA or EMA IgA, about 30% consider that no small bowel biopsy should be required in selected cases. Adding human leukocyte antigen typing in the diagnostic workup was asked for by 42% of the responders. As for gluten challenge, a new policy is advocated restricting its obligation to cases whenever the diagnosis is doubtful or unclear. CONCLUSIONS: Based on these opinions, revision of the ESPGHAN criteria for diagnosing CD is urgently needed.
Keywords: Adolescent; Adult; Biopsy; Celiac Disease; Child; Child, Preschool; Glutens; Guideline Adherence; Guidelines as Topic; Health Care Surveys; Humans; Immunoglobulin A; Intestine, Small; Physician's Practice Patterns; Questionnaires; Societies, Medical; Transglutaminases; Young Adult

Contribution of SNP arrays in diagnosis of deletion 2p11.2-p12. - Rocca, Maria Santa; Fabretto, Antonella; Faletra, Flavio; Carlet, Ombretta; Skabar, Aldo; Gasparini, Paolo; Pecile, Vanna (Gene, 2012)
Deletions of the short arm of chromosome 2 are exceedingly rare, having been reported in few patients. Furthermore most cases with deletion in 2p11.2-p12 have been studied using standard karyotype and so it is not possible to delineate the precise size of deletions. Here, we describe a 9-year-old girl with a 9.4 Mb de novo interstitial deletion of region 2p11.2-p12 identified by SNP array analysis. The deleted region encompasses over 40 known genes, including LRRTM1, CTNNA2 and REEP1, haploinsufficiency of which could explain some clinical features of this patient such as mental retardation, speech delay and gait abnormalities. A comparison of our case with previously reported patients who present deletions in 2p11.2-p12 was carried out. Our case adds new information to the deletion of 2p11.2-p12, improving the knowledge on this rearrangement.
Keywords: Abnormalities, Multiple; Child; Chromosomes, Human, Pair 2; Female; Humans; Intellectual Disability; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Sequence Deletion

De novo 6.9 Mb interstitial deletion on chromosome 4q31.1-q32.1 in a girl with severe speech delay and dysmorphic features. - Fabretto, Antonella; Santa Rocca, Maria; Perrone, Maria Dolores; Skabar, Aldo; Pecile, Vanna; Gasparini, Paolo (Am J Med Genet A, 2012)
Deletion of the terminal part of long arm of chromosome 4 is a condition characterized by facial dysmorphisms, cardiac and limb defects, and developmental delay. Deletions usually involve the terminal part of the chromosome and most frequently are interstitial. Here, we report a de novo interstitial deletion resulting in a microdeletion of 6.9 Mb involving 4q31.3-q32.1 segment, detected by SNPs-Array technique in a 4-year-old female showing severe speech delay, mild facial dysmorphisms, and joint laxity. Phenotype-genotype relationships looking at the genes involved in this part of the chromosome were also carried out and data compared with those previously described.
Keywords: Abnormalities, Multiple; Child, Preschool; Chromosome Deletion; Chromosomes, Human, Pair 4; Developmental Disabilities; Female; Genotype; Humans; Language Development Disorders; Phenotype; Sequence Deletion

DEFB1 gene 5' untranslated region (UTR) polymorphisms in inflammatory bowel diseases. - Zanin, Valentina; Segat, Ludovica; Bianco, Anna Monica; Padovan, Lara; Tavares, Nathalia de Alencar Cunha; Crovella, Sergio (Clinics (Sao Paulo), 2012)
Keywords: 5' Untranslated Regions; Adult; Antimicrobial Cationic Peptides; beta-Defensins; Case-Control Studies; Colitis, Ulcerative; Crohn Disease; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Inflammatory Bowel Diseases; Male; Polymorphism, Genetic; Polymorphism, Single Nucleotide

Effects of hormonal contraception on vaginal flora. - De Seta, Francesco; Restaino, Stefano; De Santo, Davide; Stabile, Guglielmo; Banco, Rubina; Busetti, Marina; Barbati, Giulia; Guaschino, Secondo (Contraception, 2012)
BACKGROUND: The sector of the market that deals with contraception offers a long list of different contraceptive methods. Within the estroprogestinic choice, the routes of administration are oral, transdermic and vaginal one. Even though efficacy is comparable with these methods, secondary and adverse effects are directly involved in the acceptability of the method. STUDY DESIGN: This was a prospective comparative study. During 1 year, we enrolled 60 asymptomatic women who voluntarily requested combined oral contraception (COC) or combined contraceptive vaginal ring (CCVR group). After a baseline study of vaginal milieu prior to starting hormonal contraception, we performed a follow-up. For each woman, we examined vaginal pH; quantification of leukocytes, lactobacilli, Candida and cocci on saline microscopy fluid; Gram stain with Nugent score and the presence of vaginal infection [culture for Trichomonas vaginalis, albicans and nonalbicans Candida, Group B Streptococcus (GBS)]. RESULTS: At the end of follow-up, there was a little change of vaginal milieu in both groups. We noted an increase of lactobacilli in the CCVR users and an increase of GBS in COC users. CONCLUSION: CCVR compared to COC users showed an increase of the number of lactobacilli in vaginal flora. It means that an increase of leukorrhea in that group could be protective in terms of prevention of vaginal imbalance/infection.
Keywords: Administration, Intravaginal; Adolescent; Adult; Bacterial Load; Candida; Candida albicans; Contraceptive Devices, Female; Contraceptives, Oral, Combined; Female; Humans; Hydrogen-Ion Concentration; Lactobacillus; Leukocyte Count; Middle Aged; Prospective Studies; Streptococcus agalactiae; Trichomonas vaginalis; Vagina

The effects of uterine fundal pressure (Kristeller maneuver) on pelvic floor function after vaginal delivery. - Sartore, Andrea; De Seta, Francesco; Maso, Gianpaolo; Ricci, Giuseppe; Alberico, Salvatore; Borelli, Massimo; Guaschino, Secondo (Arch Gynecol Obstet, 2012)
PURPOSE: To evaluate the role of uterine fundal pressure during the second stage of labor (Kristeller maneuver) on pelvic floor dysfunction (urinary and anal incontinence, genital prolapse, pelvic floor strength). METHODS: 522 primiparous women, enrolled 3 months after vaginal delivery, were divided in two groups: group A (297 women) identifies the women who received Kristeller maneuvers with different indications (e.g. fetal distress, failure to progress, mother exhaustion), group B (225 women) the women without maneuver. Participants were questioned about urogynecological symptoms and examined by Q-tip test, digital test, vaginal perineometry and uroflowmetric stop test score. RESULTS: Mediolateral episiotomies, dyspareunia and perineal pain were significantly higher in Kristeller group, whereas urinary and anal incontinence, genital prolapse and pelvic floor strength were not significantly different between the groups. CONCLUSIONS: Kristeller maneuver does not modify puerperal pelvic floor function but increases the rate of episiotomies.
Keywords: Delivery, Obstetric; Dyspareunia; Dystocia; Episiotomy; Fatigue; Fecal Incontinence; Female; Fetal Distress; Humans; Labor Stage, Second; Pain, Postoperative; Pelvic Floor; Pelvic Organ Prolapse; Perineum; Pregnancy; Pressure; Puerperal Disorders; Urinary Incontinence; Uterus

Endothelial cells obtained from patients affected by chronic venous disease exhibit a pro-inflammatory phenotype. - Tisato, Veronica; Zauli, Giorgio; Voltan, Rebecca; Gianesini, Sergio; di Iasio, Maria Grazia; Volpi, Ilaria; Fiorentini, Guido; Zamboni, Paolo; Secchiero, Paola (PLoS One, 2012)
BACKGROUND: The inflammatory properties of vein endothelium in relation to chronic venous disease (CVD) have been poorly investigated. Therefore, new insights on the characteristics of large vein endothelium would increase our knowledge of large vessel physiopathology. METHODOLOGY/PRINCIPAL FINDINGS: Surgical specimens of veins were obtained from the tertiary venous network (R3) and/or saphenous vein (SF) of patients affected by CVD and from control individuals. Highly purified venous endothelial cell (VEC) cultures obtained from CVD patients were characterized for morphological, phenotypic and functional properties compared to control VEC. An increase of CD31/PECAM-1, CD146 and ICAM-1 surface levels was documented at flow cytometry in pathological VEC with respect to normal controls. Of note, the strongest expression of these pro-inflammatory markers was observed in VEC obtained from patients with more advanced disease. Similarly, spontaneous cell proliferation and resistance to starvation was higher in pathological than in normal VEC, while the migratory response of VEC showed an opposite trend, being significantly lower in VEC obtained from pathological specimens. In addition, in keeping with a higher baseline transcriptional activity of NF-kB, the release of the pro-inflammatory cytokines osteoprotegerin (OPG) and vascular endothelial growth factor (VEGF) was higher in pathological VEC cultures with respect to control VEC. Interestingly, there was a systemic correlation to these in vitro data, as demonstrated by higher serum OPG and VEGF levels in CVD patients with respect to normal healthy controls. CONCLUSION/SIGNIFICANCE: Taken together, these data indicate that large vein endothelial cells obtained from CVD patients exhibit a pro-inflammatory phenotype, which might significantly contribute to systemic inflammation in CVD patients.
Keywords: Adult; Antigens, CD146; Antigens, CD31; Body Mass Index; Cell Culture Techniques; Endothelial Cells; Female; Flow Cytometry; Humans; Inflammation; Intercellular Adhesion Molecule-1; Kinetics; Male; Microscopy, Electron, Scanning; Middle Aged; Phenotype; Saphenous Vein; Vascular Diseases

The energy balance positively regulates the levels of circulating TNF-related apoptosis inducing ligand in humans. - Biolo, Gianni; Secchiero, Paola; De Giorgi, Sara; Tisato, Veronica; Zauli, Giorgio (Clin Nutr, 2012)
BACKGROUND & AIMS: Although decreased levels of circulating TRAIL have been associated to cardiovascular risk and overall mortality, the mechanisms controlling TRAIL levels in physiopathological conditions are currently unknown. The aim of the present study was to investigate whether changes in the energy intake and insulin sensitivity may influence circulating TRAIL, and to analyze potential relationships between circulating TRAIL and changes in fat mass in healthy subjects receiving hypocaloric or hypercaloric diets. METHODS: Three distinct groups of participants were studied, at the end of a 14-day (n = 9), 35-day (n = 30) or 60-day (n = 16) period of experimental bed rest to induce insulin resistance and during controlled ambulation, after receiving eucaloric, hypocaloric or hypercaloric diets. RESULTS: After bed rest conditions, energy restriction significantly decreased circulating TRAIL, while overfeeding significantly increased TRAIL levels with respect to eucaloric control subjects. Moreover, a positive correlation was found between levels of circulating TRAIL and energy intake as well as between circulating TRAIL and energy balance, as determined by changes in fat mass in these subjects. CONCLUSIONS: Circulating levels of TRAIL exhibit a clear-cut positive correlation with the energy intake and balance in healthy subjects during experimental physical inactivity.
Keywords: Adult; Apoptosis; Bed Rest; Cross-Over Studies; Diet; Energy Intake; Energy Metabolism; Female; Humans; Insulin Resistance; Male; Motor Activity; Risk Factors; TNF-Related Apoptosis-Inducing Ligand; Young Adult

European Society for Pediatric Gastroenterology, Hepatology, and Nutrition guidelines for the diagnosis of coeliac disease. - Husby, S; Koletzko, S; Korponay-Szabó, I R; Mearin, M L; Phillips, A; Shamir, R; Troncone, R; Giersiepen, K; Branski, D; Catassi, C; Lelgeman, M; Mäki, M; et al. (J Pediatr Gastroenterol Nutr, 2012)
OBJECTIVE: Diagnostic criteria for coeliac disease (CD) from the European Society for Paediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) were published in 1990. Since then, the autoantigen in CD, tissue transglutaminase, has been identified; the perception of CD has changed from that of a rather uncommon enteropathy to a common multiorgan disease strongly dependent on the haplotypes human leukocyte antigen (HLA)-DQ2 and HLA-DQ8; and CD-specific antibody tests have improved. METHODS: A panel of 17 experts defined CD and developed new diagnostic criteria based on the Delphi process. Two groups of patients were defined with different diagnostic approaches to diagnose CD: children with symptoms suggestive of CD (group 1) and asymptomatic children at increased risk for CD (group 2). The 2004 National Institutes of Health/Agency for Healthcare Research and Quality report and a systematic literature search on antibody tests for CD in paediatric patients covering the years 2004 to 2009 was the basis for the evidence-based recommendations on CD-specific antibody testing. RESULTS: In group 1, the diagnosis of CD is based on symptoms, positive serology, and histology that is consistent with CD. If immunoglobulin A anti-tissue transglutaminase type 2 antibody titers are high (>10 times the upper limit of normal), then the option is to diagnose CD without duodenal biopsies by applying a strict protocol with further laboratory tests. In group 2, the diagnosis of CD is based on positive serology and histology. HLA-DQ2 and HLA-DQ8 testing is valuable because CD is unlikely if both haplotypes are negative. CONCLUSIONS: The aim of the new guidelines was to achieve a high diagnostic accuracy and to reduce the burden for patients and their families. The performance of these guidelines in clinical practice should be evaluated prospectively.
Keywords: Adolescent; Celiac Disease; Child; Duodenum; HLA-DQ Antigens; Humans; Immunoglobulin A; Transglutaminases

Evidence of inbreeding depression on human height. - McQuillan, Ruth; Eklund, Niina; Pirastu, Nicola; Kuningas, Maris; McEvoy, Brian P; Esko, Tõnu; Corre, Tanguy; Davies, Gail; Kaakinen, Marika; Lyytikäinen, Leo-Pekka; Kristiansson, Kati; Havulinna, Aki S; et al. (PLoS Genet, 2012)
Stature is a classical and highly heritable complex trait, with 80%-90% of variation explained by genetic factors. In recent years, genome-wide association studies (GWAS) have successfully identified many common additive variants influencing human height; however, little attention has been given to the potential role of recessive genetic effects. Here, we investigated genome-wide recessive effects by an analysis of inbreeding depression on adult height in over 35,000 people from 21 different population samples. We found a highly significant inverse association between height and genome-wide homozygosity, equivalent to a height reduction of up to 3 cm in the offspring of first cousins compared with the offspring of unrelated individuals, an effect which remained after controlling for the effects of socio-economic status, an important confounder (χ(2) = 83.89, df = 1; p = 5.2 × 10(-20)). There was, however, a high degree of heterogeneity among populations: whereas the direction of the effect was consistent across most population samples, the effect size differed significantly among populations. It is likely that this reflects true biological heterogeneity: whether or not an effect can be observed will depend on both the variance in homozygosity in the population and the chance inheritance of individual recessive genotypes. These results predict that multiple, rare, recessive variants influence human height. Although this exploratory work focuses on height alone, the methodology developed is generally applicable to heritable quantitative traits (QT), paving the way for an investigation into inbreeding effects, and therefore genetic architecture, on a range of QT of biomedical importance.
Keywords: Adult; Aged; Body Height; Consanguinity; Databases, Genetic; Family; Female; Genes, Recessive; Genetic Heterogeneity; Genome-Wide Association Study; Homozygote; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Febrile urinary tract infections in young children: recommendations for the diagnosis, treatment and follow-up. - Ammenti, Anita; Cataldi, Luigi; Chimenz, Roberto; Fanos, Vassilios; La Manna, Angela; Marra, Giuseppina; Materassi, Marco; Pecile, Paolo; Pennesi, Marco; Pisanello, Lorena; Sica, Felice; Toffolo, Antonella; et al. (Acta Paediatr, 2012)
UNLABELLED: We report the recommendations for the diagnosis, treatment, imaging evaluation and use of antibiotic prophylaxis in children with the first febrile urinary tract infection, aged 2 months to 3 years. They were prepared by a working group of the Italian Society of Pediatric Nephrology after careful review of the available literature and a consensus decision, when clear evidence was not available. CONCLUSION: These recommendations are endorsed by the Italian Society of Pediatric Nephrology. They can also be a tool of comparison with other existing guidelines in issues in which much controversy still exists.
Keywords: Anti-Bacterial Agents; Child, Preschool; Female; Fever; Follow-Up Studies; Humans; Infant; Male; Urinary Tract Infections

Frequency of human papillomavirus types 16, 18, 31, and 33 and sites of cervical lesions in gynecological patients from Recife, Brazil. - Baldez da Silva, M F P T; Guimarães, V; Silva, M A R; Medeiros do Amaral, C M; Beçak, W; Stocco, R C; Freitas, A C; Crovella, S (Genet Mol Res, 2012)
Human papilloma virus (HPV) is a well-established cause of cervical cancer. While many studies have been performed so far on HPV viral biology, mode of infection and prevention measures, scanty information is available on lesion sites of infected women and the incidence of viral types at specific locations. We looked for a possible relationship between the most common viral types (HPVs 16, 18, 31, 33) found in Recife, PE, Brazil, and lesion sites. We examined 396 HPV-positive women at the Gynecological Unit of the IMIP at Recife; 288 women were positive for HPV 16, 18, 31, or 33, present as a single-virus type or as co-infection. HPV 16 was the most frequent virus type found in the vulva, vagina, uterine cervix-vagina, and uterine cervix. HPV 31 was the second prevalent virus type in vulva, vagina, uterine cervix-vagina, uterine cervix, and mole. HPVs 18 and 33 were present with similar frequencies in the mole-vulva region. Among the co-infections, HPV 16/18 and HPV16/31 were the most frequent in our study group, followed by HPV 16/33.
Keywords: Adolescent; Adult; Brazil; Cervix Uteri; DNA, Viral; Female; Human papillomavirus 16; Human papillomavirus 18; Human papillomavirus 31; Humans; Papillomavirus Infections; Uterine Cervical Diseases; Young Adult

Functional single-nucleotide polymorphisms in the DEFB1 gene are associated with systemic lupus erythematosus in Southern Brazilians. - Sandrin-Garcia, P; Brandão, L A C; Guimarães, R L; Pancoto, J A T; Donadi, E A; Lima-Filho, J L de; Segat, L; Crovella, S (Lupus, 2012)
Systemic lupus erythematosus (SLE) is an autoimmune disease that results in inflammation and tissue damage. The etiology of SLE remains unknown, but recent studies have shown that the innate immune system may have a role in SLE pathogenesis through the secretion of small cationic peptides named defensins. The aim of the study was to determine the possible involvement in SLE of three functional single nucleotide polymorphisms (SNPs) (c.-52G>A, c.-44C>G and c.-20G>A) in the 5'UTR region of DEFB1 gene, by analyzing them in a population of 139 SLE patients and 288 healthy controls. The c.-52G>A SNP showed significant differences in allele and genotype frequency distribution between SLE patients and controls (p = 0.01 and p = 0.02 respectively) indicating protection against SLE (A allele, OR = 0.68, AA genotype OR = 0.51). Significant differences were also observed for c.-44C>G SNP, the C/G genotype being associated with susceptibility to SLE (OR = 1.60, p = 0.04). Moreover, statistically significant differences between patients and controls were found for two DEFB1 haplotypes (GCA and GGG, p = 0.01 and p = 0.02 respectively). When considering DEFB1 SNPs and SLE clinical and laboratory manifestations, significant association was found with neuropsychiatric disorders, immunological alterations and anti-DNA antibodies. In conclusion, our results evidence a possible role for the c.-52G>A and c.-44C>G DEFB1 polymorphisms in SLE pathogenesis, that can be considered as possible risk factors for development of disease and disease-related clinical manifestations. Additional studies are needed, to corroborate these results as well as functional studies to understand the biological role of these SNPs in the pathogenesis of SLE.
Keywords: Adolescent; Adult; Aged; beta-Defensins; Brazil; Case-Control Studies; Female; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Lupus Erythematosus, Systemic; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Young Adult

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Genomic profiling by whole-genome single nucleotide polymorphism arrays in Wilms tumor and association with relapse. - Perotti, Daniela; Spreafico, Filippo; Torri, Federica; Gamba, Beatrice; d'Adamo, Pio; Pizzamiglio, Sara; Terenziani, Monica; Catania, Serena; Collini, Paola; Nantron, Marilina; Pession, Andrea; Bianchi, Maurizio; et al. (Genes Chromosomes Cancer, 2012)
Despite the excellent survival rate of Wilms tumor (WT) patients, only approximately one-half of children who suffer tumor recurrence reach second durable remission. This underlines the need for novel markers to optimize initial treatment. We investigated 77 tumors using Illumina 370CNV-QUAD genotyping BeadChip arrays and compared their genomic profiles to detect copy number (CN) abnormalities and allelic ratio anomalies associated with the following clinicopathological variables: relapse (yes vs. no), age at diagnosis (≤ 24 months vs. >24 months), and disease stage (low stage, I and II, vs. high stage, III and IV). We found that CN gains at chromosome region 1q21.1-q31.3 were significantly associated with relapse. Additional genetic events, including allelic imbalances at chromosome arms 1p, 1q, 3p, 3q, and 14q were also found to occur at higher frequency in relapsing tumors. Interestingly, allelic imbalances at 1p and 14q also showed a borderline association with higher tumor stages. No genetic events were found to be associated with age at diagnosis. This is the first genome wide analysis with single nucleotide polymorphism (SNP) arrays specifically investigating the role of genetic anomalies in predicting WT relapse on cases prospectively enrolled in the same clinical trial. Our study, besides confirming the role of 1q gains, identified a number of additional candidate genetic markers, warranting further molecular investigations.
Keywords: Adolescent; Allelic Imbalance; Child; Child, Preschool; Chromosome Aberrations; DNA Copy Number Variations; Female; Genetic Markers; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Infant; Kaplan-Meier Estimate; Male; Polymorphism, Single Nucleotide; Prospective Studies; Recurrence; Wilms Tumor

Gluten-dependent intestinal autoimmune response. - Korponay-Szabó, Ilma Rita; Simon-Vecsei, Zsafia; De Leo, Luigina; Not, Tarcisio (Curr Pharm Des, 2012)
Celiac disease is a multi-systemic autoimmune disease of the small bowel induced by gluten in genetically predisposed subjects. Highly specific and gluten-dependent production of auto-antibodies targeting self-proteins of the transglutaminase family occurs in the intestinal mucosa. These anti-transglutaminase antibodies are found deposited in intestinal and extra-intestinal tissue where they might exert biological effects, together with the intestinal mucosal gliadin-specific T lymphocytes. We conducted a brief review on antitransglutaminase antibodies effects, discussing their roles in the pathogenesis of several clinical manifestations of celiac disease.
Keywords: Animals; Autoantibodies; Celiac Disease; Genetic Predisposition to Disease; Gliadin; Glutens; Humans; Intestinal Mucosa; T-Lymphocytes; Transglutaminases

Haematopoietic SCT in severe autoimmune diseases: updated guidelines of the European Group for Blood and Marrow Transplantation. - Snowden, J A; Saccardi, R; Allez, M; Ardizzone, S; Arnold, R; Cervera, R; Denton, C; Hawkey, C; Labopin, M; Mancardi, G; Martin, R; Moore, J J; et al. (Bone Marrow Transplant, 2012)
In 1997, the first consensus guidelines for haematopoietic SCT (HSCT) in autoimmune diseases (ADs) were published, while an international coordinated clinical programme was launched. These guidelines provided broad principles for the field over the following decade and were accompanied by comprehensive data collection in the European Group for Blood and Marrow Transplantation (EBMT) AD Registry. Subsequently, retrospective analyses and prospective phase I/II studies generated evidence to support the feasibility, safety and efficacy of HSCT in several types of severe, treatment-resistant ADs, which became the basis for larger-scale phase II and III studies. In parallel, there has also been an era of immense progress in biological therapy in ADs. The aim of this document is to provide revised and updated guidelines for both the current application and future development of HSCT in ADs in relation to the benefits, risks and health economic considerations of other modern treatments. Patient safety considerations are central to guidance on patient selection and HSCT procedural aspects within appropriately experienced and Joint Accreditation Committee of International Society for Cellular Therapy and EBMT accredited centres. A need for prospective interventional and non-interventional studies, where feasible, along with systematic data reporting, in accordance with EBMT policies and procedures, is emphasized.
Keywords: Autoimmune Diseases; Clinical Trials, Phase I as Topic; Clinical Trials, Phase II as Topic; European Union; Female; Hematopoietic Stem Cell Transplantation; Humans; Male; Risk Factors; Safety; Severity of Illness Index

HIV-1 induces NALP3-inflammasome expression and interleukin-1β secretion in dendritic cells from healthy individuals but not from HIV-positive patients. - Pontillo, Alessandra; Silva, Lais T; Oshiro, Telma M; Finazzo, Claudia; Crovella, Sergio; Duarte, Alberto J S (AIDS, 2012)
OBJECTIVE: NALP3-inflammasome is an innate mechanism, alternative to type-1 interferon, which is able to recognize nucleic acids and viruses in the cytoplasm and to induce pro-inflammatory response. Here, we hypothesized the involvement of inflammasome in the early defense against HIV-1 and in the full maturation of dendritic cells: for this, we evaluated the response of dendritic cells pulsed with HIV-1 in terms of inflammasome activation in healthy donors. Moreover, inflammasome response to HIV was evaluated in HIV-infected individuals. DESIGN AND METHODS: Monocyte-derived dendritic cells isolated from 20 healthy individuals (HC-DC) and 20 HIV-1-infected patients (HIV-DC) were pulsed with alditrithiol-2-inactivated HIV-1. We then analyzed inflammasome genes expression and interleukin-1β (IL-1β) secretion. RESULTS: In HC-DC, HIV-1 induced higher NLRP3/NALP3 mRNA expression compared with other inflammasome genes such as NALP1/NLRP1 or IPAF/NLRC4 (P < 0.001). This augmented expression was accompanied by CASP1-increased and IL1B-increased mRNA levels and by a significant increment of IL-1β secretion (P < 0.05). Otherwise, HIV-1 failed to activate inflammasome and cytokine production in HIV-DC. HIV-DC showed an increased NLRP3/NALP3 basal expression, suggesting a chronic inflammatory profile of patients' immune cells. CONCLUSION: HIV-1 was able to induce a NALP3-inflammasome response in healthy individuals, indicating that this inflammasome could play a role in the first steps of HIV-1 infection; the consequent inflammatory process may be important for directing host immune response against the virus and/or disease progression. HIV-DC seemed to be chronically activated, but unresponsive against pathogens. Our findings could be of interest considering the ongoing research about dendritic cell manipulation and therapeutic strategies for AIDS involving dendritic cell-based immune-vaccines.
Keywords: Acquired Immunodeficiency Syndrome; Adult; Brazil; Carrier Proteins; Caspase 1; Cells, Cultured; Dendritic Cells; DNA, Viral; Female; HIV-1; Humans; Immunity, Innate; Inflammasomes; Interleukin-1beta; Male; Tumor Necrosis Factor-alpha

HLA-G 14bp del/ins genetic variation: association with susceptibility to human immunodeficiency virus-1 vertical transmission but not with human immunodeficiency virus-1 infection through horizontal transmission. - Segat, L; Crovella, S (Tissue Antigens, 2012)
Keywords: Ethnic Groups; Genetic Association Studies; Genetic Predisposition to Disease; HIV Infections; HIV-1; HLA-G Antigens; Humans; INDEL Mutation; Infectious Disease Transmission, Vertical; Polymorphism, Genetic

Hydrogen sulfide down-regulates the expression and release of osteoprotegerin (OPG) by vascular endothelial cells. - Rimondi, Erika; di Iasio, Maria Grazia; Gonelli, Arianna; Celeghini, Claudio; Secchiero, Paola; Zauli, Giorgio (Invest New Drugs, 2012)
Keywords: Cell Death; Cytostatic Agents; Down-Regulation; Human Umbilical Vein Endothelial Cells; Humans; Hydrogen Sulfide; Osteoprotegerin; Tumor Necrosis Factor-alpha

In vivo anti-lymphoma activity of an agonistic human recombinant anti-TRAIL-R2 minibody. - Zauli, Giorgio; Corallini, Federica; Zorzet, Sonia; Grill, Vittorio; Marzari, Roberto; Secchiero, Paola (Invest New Drugs, 2012)
A new single-chain fragment variable (scFv) to TRAIL-R2 receptor produced as minibody (MB2.23) was characterized for anti-lymphoma activity in vivo. For this purpose, a disseminated lymphoma model was generated by intraperitoneal inoculation of BJAB cells in severe combined immunodeficiency mice. Two weekly injections with MB2.23 (10 mg/kg) were able to significantly increase the median survival time of lymphoma-bearing animals with respect to the vehicle-treated control mice, providing a rationale for further investigating the use of MB2.23 in anticancer therapy.
Keywords: Animals; Humans; Immunotherapy; Injections, Intraperitoneal; Lymphoma, B-Cell; Mice; Mice, SCID; Receptors, TNF-Related Apoptosis-Inducing Ligand; Single-Chain Antibodies; Time Factors; Xenograft Model Antitumor Assays

Influence of age, sex and ethnicity on platelet count in five Italian geographic isolates: mild thrombocytopenia may be physiological. - Biino, Ginevra; Gasparini, Paolo; d'Adamo, Pio; Ciullo, Marina; Nutile, Teresa; Toniolo, Daniela; Sala, Cinzia; Minelli, Cosetta; Gögele, Martin; Balduini, Carlo L (Br J Haematol, 2012)
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Child; Child, Preschool; Female; Humans; Infant; Italy; Male; Middle Aged; Platelet Count; Reference Values; Sex Distribution; Thrombocytopenia; Young Adult

Integration of genome-wide association studies with biological knowledge identifies six novel genes related to kidney function. - Chasman, Daniel I; Fuchsberger, Christian; Pattaro, Cristian; Teumer, Alexander; Böger, Carsten A; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (Hum Mol Genet, 2012)
In conducting genome-wide association studies (GWAS), analytical approaches leveraging biological information may further understanding of the pathophysiology of clinical traits. To discover novel associations with estimated glomerular filtration rate (eGFR), a measure of kidney function, we developed a strategy for integrating prior biological knowledge into the existing GWAS data for eGFR from the CKDGen Consortium. Our strategy focuses on single nucleotide polymorphism (SNPs) in genes that are connected by functional evidence, determined by literature mining and gene ontology (GO) hierarchies, to genes near previously validated eGFR associations. It then requires association thresholds consistent with multiple testing, and finally evaluates novel candidates by independent replication. Among the samples of European ancestry, we identified a genome-wide significant SNP in FBXL20 (P = 5.6 × 10(-9)) in meta-analysis of all available data, and additional SNPs at the INHBC, LRP2, PLEKHA1, SLC3A2 and SLC7A6 genes meeting multiple-testing corrected significance for replication and overall P-values of 4.5 × 10(-4)-2.2 × 10(-7). Neither the novel PLEKHA1 nor FBXL20 associations, both further supported by association with eGFR among African Americans and with transcript abundance, would have been implicated by eGFR candidate gene approaches. LRP2, encoding the megalin receptor, was identified through connection with the previously known eGFR gene DAB2 and extends understanding of the megalin system in kidney function. These findings highlight integration of existing genome-wide association data with independent biological knowledge to uncover novel candidate eGFR associations, including candidates lacking known connections to kidney-specific pathways. The strategy may also be applicable to other clinical phenotypes, although more testing will be needed to assess its potential for discovery in general.
Keywords: Amino Acid Transport Systems, Basic; Antigens, CD98 Heavy Chain; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inhibin-beta Subunits; Intracellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-2; Membrane Proteins; Polymorphism, Single Nucleotide

International collaboration as a tool for diagnosis of patients with inherited thrombocytopenia in the setting of a developing country. - Glembotsky, A C; Marta, R F; Pecci, A; De Rocco, D; Gnan, C; Espasandin, Y R; Goette, N P; Negro, F; Noris, P; Savoia, A; Balduini, C L; Molinas, F C; et al. (J Thromb Haemost, 2012)
BACKGROUND: Inherited thrombocytopenias (ITs) are heterogeneous genetic disorders that frequently represent a diagnostic challenge. The requirement of highly specialized tests for diagnosis represents a particular problem in resource-limited settings. To overcome this difficulty, we applied a diagnostic algorithm and developed a collaboration program with a specialized international center in order to increase the diagnostic yield in a cohort of patients in Argentina. METHODS: Based on the algorithm, initial evaluation included collection of clinical data, platelet size, blood smear examination and platelet aggregation tests. Confirmatory tests were performed according to diagnostic suspicion, which included platelet glycoprotein expression, immunofluorescence for myosin-9 in granulocytes and platelet thrombospondin-1 and molecular screening of candidate genes. RESULTS: Thirty-one patients from 14 pedigrees were included; their median age was 32 (4-72) years and platelet count 72 (4-147)×10(9) L(-1). Autosomal dominant inheritance was found in nine (64%) pedigrees; 10 (71%) had large platelets and nine (29%) patients presented with syndromic forms. A definitive diagnosis was made in 10 of 14 pedigrees and comprised MYH9-related disease in four, while classic and monoallelic Bernard-Soulier syndrome, gray platelet syndrome, X-linked thrombocytopenia, thrombocytopenia 2 (ANKRD26 mutation) and familial platelet disorder with predisposition to acute myelogenous leukemia were diagnosed in one pedigree each. CONCLUSIONS: Adoption of an established diagnostic algorithm and collaboration with an expert referral center proved useful for diagnosis of IT patients in the setting of a developing country. This initiative may serve as a model to develop international networks with the goal of improving diagnosis and care of patients with these rare diseases.
Keywords: Adolescent; Adult; Aged; Algorithms; Argentina; Biological Markers; Child; Child, Preschool; Cooperative Behavior; Developing Countries; DNA Mutational Analysis; Feasibility Studies; Female; Flow Cytometry; Fluorescent Antibody Technique; Genetic Predisposition to Disease; Genetic Testing; Health Services Accessibility; Hematologic Tests; Heredity; Humans; International Cooperation; Italy; Male; Middle Aged; Molecular Motor Proteins; Myosin Heavy Chains; Pedigree; Phenotype; Platelet Count; Platelet Function Tests; Predictive Value of Tests; Prognosis; Referral and Consultation; Thrombocytopenia; Thrombospondin 1; Young Adult

JCV+ Patients with Inflammatory bowel disease show elevated plasma levels of MIG and SCF. - Comar, Manola; Secchiero, Paola; De Lorenzo, Elisa; Martelossi, Stefano; Tommasini, Alberto; Zauli, Giorgio (Inflamm Bowel Dis, 2012)
Keywords: Adolescent; Adult; Chemokine CXCL9; Child; DNA, Viral; Female; Humans; Inflammatory Bowel Diseases; JC Virus; Leukoencephalopathy, Progressive Multifocal; Male; Stem Cell Factor; Young Adult

Letter: TPMT activity and age in IBD patients. - Stocco, G; De Iudicibus, S; Cuzzoni, E; Decorti, G; Martelossi, S; Ventura, A (Aliment Pharmacol Ther, 2012)
Keywords: Azathioprine; Humans; Immunosuppressive Agents; Inflammatory Bowel Diseases; Thioguanine

Mannose-binding lectin and MBL-associated serine protease-2 gene polymorphisms in a Brazilian population from Rio de Janeiro. - Ferraroni, N R; Segat, L; Guimarães, R L; Brandão, L A C; Crovella, S; Constantino-Silva, R N; Loja, C; da Silva Duarte, A J; Grumach, A S (Int J Immunogenet, 2012)
Mannose-binding lectin (MBL) is a protein able to bind to carbohydrate patterns on pathogen membranes; upon MBL binding, its' associated serine protease MBL-associated serine protease type 2 (MASP2) is autoactivated, promoting the activation of complement via the lectin pathway. For both MBL2 and MASP2 genes, the frequencies of polymorphisms are extremely variable between different ethnicities, and this aspect has to be carefully considered when performing genetic studies. While polymorphisms in the MBL-encoding gene (MBL2) have been associated, depending upon ethnicity, with several diseases in different populations, little is known about the distribution of MASP2 gene polymorphisms in human populations. The aim of our study was thus to determine the frequencies of MBL2 (exon 1 and promoter) and MASP2 (p.D371Y) polymorphisms in a Brazilian population from Rio de Janeiro. A total of 294 blood donor samples were genotyped for 27 polymorphisms in the MBL2 gene by direct sequencing of a region spanning from the promoter polymorphism H/L rs11003125 to the rs1800451 polymorphism (at codon 57 in the first exon of the gene). Genotyping for MASP2 p.D371Y was carried out using fluorogenic probes. To our knowledge, this is the first study reporting the prevalence of the MASP2 p.D371Y polymorphism in a Brazilian population. The C allele frequency 39% is something intermediate between the reported 14% in Europeans and 90% in Sub-Saharan Africans. MBL2 polymorphisms frequencies were quite comparable to those previously reported for admixed Brazilians. Both MBL2 and MASP2 polymorphisms frequencies reported in our study for the admixed Brazilian population are somehow intermediate between those reported in Europeans and Africans, reflecting the ethnic composition of the southern Brazilian population, estimated to derive from an admixture of Caucasian (31%), African (34%) and Native American (33%) populations. In conclusion, our population genetic study describes the frequencies of MBL2 and MASP2 functional SNPs in a population from Rio de Janeiro, with the aim of adding new information concerning the distribution of these SNPs in a previously unanalysed Brazilian population, thus providing a new genetic tool for the evaluation of the association of MBL2 and MASP2 functional SNPs with diseases in Brazil, with particular emphasis on the state of Rio de Janeiro.
Keywords: Adolescent; Adult; Brazil; Ethnic Groups; Exons; Female; Fluorescent Dyes; Gene Frequency; Genetics, Population; Genome, Human; HapMap Project; Humans; Male; Mannose-Binding Lectin; Mannose-Binding Protein-Associated Serine Proteases; Middle Aged; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Sequence Analysis, DNA; Young Adult

MCL1 down-regulation plays a critical role in mediating the higher anti-leukaemic activity of the multi-kinase inhibitor Sorafenib with respect to Dasatinib. - Secchiero, Paola; Melloni, Elisabetta; Voltan, Rebecca; Norcio, Alessia; Celeghini, Claudio; Zauli, Giorgio (Br J Haematol, 2012)
Keywords: Antineoplastic Agents; Benzenesulfonates; Cell Line, Tumor; Down-Regulation; Humans; Leukemia, Myeloid, Acute; Myeloid Cell Leukemia Sequence 1 Protein; Niacinamide; Phenylurea Compounds; Protein Kinase Inhibitors; Proto-Oncogene Proteins c-bcl-2; Pyridines; Pyrimidines; Thiazoles

Merkel-cell polyomavirus (MCPyV) is rarely associated to B-chronic lymphocytic leukemia (1 out of 50) samples and occurs late in the natural history of the disease. - Comar, Manola; Cuneo, Antonio; Maestri, Iva; Melloni, Elisabetta; Pozzato, Gabriele; Soffritti, Olga; Secchiero, Paola; Zauli, Giorgio (J Clin Virol, 2012)
BACKGROUND: Previous studies have reported conflicting results on the frequency and potential pathogenetic role of Merkel-cell polyomavirus (MCPyV) in B-chronic lymphocytic leukemia (B-CLL). OBJECTIVES: To evaluate the association of MCPyV to B-CLL and to investigate the occurrence of MCPyV infection in relationship to the natural history of B-CLL. STUDY DESIGN: Samples of primary B-CLL peripheral blood mononuclear cells were obtained from two distinct University Hospitals of Italy from January 2010. For one B-CLL patient, it was possible to retrospectively examine the blood sample at diagnosis of B-CLL (March 2004) and several pathological tissues of cutaneous tumors occurring during the course of the disease. RESULTS: Only one out of 50 B-CLL blood samples examined was positive for MCPyV DNA. Retrospective analysis revealed that MCPyV DNA was absent in peripheral blood sample at diagnosis, becoming present only in advanced disease stages also in tonsil tissue as well as in a biopsy of differentiated squamous cell carcinoma. CONCLUSIONS: The association with MCPyV seems to represent a rare and late event during the natural history of B-CLL.
Keywords: Aged; Aged, 80 and over; Blood; Female; Humans; Italy; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Merkel cell polyomavirus; Middle Aged; Palatine Tonsil; Polyomavirus Infections; Prevalence; Skin; Tumor Virus Infections

Mesenchymal stem cells display hepato-protective activity in lymphoma bearing xenografts. - Secchiero, Paola; Corallini, Federica; Zavan, Barbara; Tripodo, Claudio; Vindigni, Vincenzo; Zauli, Giorgio (Invest New Drugs, 2012)
A disseminated model of non-Hodgkin's lymphoma with prevalent liver metastasis was generated by intraperitoneal (i.p.) injection of EBV(+) B lymphoblastoid SKW6.4 in nude-SCID mice. The survival of SKW6.4 xenografts (median survival = 27 days) was significantly improved when hyaluronan scaffolds embedded with mesenchimal stem cells (MSC) were implanted in the abdominal area 4 days after SKW6.4 injection (median survival = 39.5 days). Mice implanted with MSC showed a significant improvement of hepatic functionality in lymphoma xenografts, as demonstrated by measurement of serum ALT/AST levels. Co-culture of MSC with lymphoma cells enhanced the release of hepatocyte growth factor (HGF) by MSC. These data suggest that hyaluronan-embedded MSC exert anti-lymphoma activity by ameliorating hepatic functionality.
Keywords: Alanine Transaminase; Animals; Aspartate Aminotransferases; Biological Markers; Cell Communication; Cell Line, Tumor; Cell Survival; Coculture Techniques; Hepatocyte Growth Factor; Humans; Hyaluronic Acid; Liver; Liver Neoplasms; Lymphoma, Non-Hodgkin; Mesenchymal Stem Cell Transplantation; Mesenchymal Stromal Cells; Mice; Mice, Nude; Mice, SCID; Time Factors; Tissue Scaffolds; Xenograft Model Antitumor Assays

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

Meta-analysis identifies multiple loci associated with kidney function-related traits in east Asian populations. - Okada, Yukinori; Sim, Xueling; Go, Min Jin; Wu, Jer-Yuarn; Gu, Dongfeng; Takeuchi, Fumihiko; Takahashi, Atsushi; Maeda, Shiro; Tsunoda, Tatsuhiko; Chen, Peng; Lim, Su-Chi; Wong, Tien-Yin; et al. (Nat Genet, 2012)
Chronic kidney disease (CKD), impairment of kidney function, is a serious public health problem, and the assessment of genetic factors influencing kidney function has substantial clinical relevance. Here, we report a meta-analysis of genome-wide association studies for kidney function-related traits, including 71,149 east Asian individuals from 18 studies in 11 population-, hospital- or family-based cohorts, conducted as part of the Asian Genetic Epidemiology Network (AGEN). Our meta-analysis identified 17 loci newly associated with kidney function-related traits, including the concentrations of blood urea nitrogen, uric acid and serum creatinine and estimated glomerular filtration rate based on serum creatinine levels (eGFRcrea) (P < 5.0 × 10(-8)). We further examined these loci with in silico replication in individuals of European ancestry from the KidneyGen, CKDGen and GUGC consortia, including a combined total of ∼110,347 individuals. We identify pleiotropic associations among these loci with kidney function-related traits and risk of CKD. These findings provide new insights into the genetics of kidney function.
Keywords: Asian Continental Ancestry Group; Blood Urea Nitrogen; Cohort Studies; Creatinine; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic; Uric Acid

miR-EdiTar: a database of predicted A-to-I edited miRNA target sites. - Laganà, Alessandro; Paone, Alessio; Veneziano, Dario; Cascione, Luciano; Gasparini, Pierluigi; Carasi, Stefania; Russo, Francesco; Nigita, Giovanni; Macca, Valentina; Giugno, Rosalba; Pulvirenti, Alfredo; Shasha, Dennis; et al. (Bioinformatics, 2012)
MOTIVATION: A-to-I RNA editing is an important mechanism that consists of the conversion of specific adenosines into inosines in RNA molecules. Its dysregulation has been associated to several human diseases including cancer. Recent work has demonstrated a role for A-to-I editing in microRNA (miRNA)-mediated gene expression regulation. In fact, edited forms of mature miRNAs can target sets of genes that differ from the targets of their unedited forms. The specific deamination of mRNAs can generate novel binding sites in addition to potentially altering existing ones. RESULTS: This work presents miR-EdiTar, a database of predicted A-to-I edited miRNA binding sites. The database contains predicted miRNA binding sites that could be affected by A-to-I editing and sites that could become miRNA binding sites as a result of A-to-I editing. AVAILABILITY: miR-EdiTar is freely available online at http://microrna.osumc.edu/mireditar. CONTACT: alessandro.lagana@osumc.edu or carlo.croce@osumc.edu SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Adenosine; Binding Sites; Databases, Genetic; Gene Expression Regulation; Humans; Inosine; Internet; MicroRNAs; Nucleic Acid Conformation; RNA Editing

Molecular analysis of HEXA gene in Argentinean patients affected with Tay-Sachs disease: possible common origin of the prevalent c.459+5A>G mutation. - Zampieri, Stefania; Montalvo, Annalisa; Blanco, Mariana; Zanin, Irene; Amartino, Hernan; Vlahovicek, Kristian; Szlago, Marina; Schenone, Andrea; Pittis, Gabriela; Bembi, Bruno; Dardis, Andrea (Gene, 2012)
Tay-Sachs disease (TSD) is a recessively inherited disorder caused by the deficient activity of hexosaminidase A due to mutations in the HEXA gene. Up to date there is no information regarding the molecular genetics of TSD in Argentinean patients. In the present study we have studied 17 Argentinean families affected by TSD, including 20 patients with the acute infantile form and 3 with the sub-acute form. Overall, we identified 14 different mutations accounting for 100% of the studied alleles. Eight mutations were novel: 5 were single base changes leading to drastic residue changes or truncated proteins, 2 were small deletions and one was an intronic mutation that may cause a splicing defect. Although the spectrum of mutations was highly heterogeneous, a high frequency of the c.459+5G>A mutation, previously described in different populations was found among the studied cohort. Haplotype analysis suggested that in these families the c.459+5G>A mutation might have arisen by a single mutational event.
Keywords: Child; Cohort Studies; Female; Hexosaminidase A; Humans; Infant; Male; Mutation; Tay-Sachs Disease

Molecular diagnosis of Usher syndrome: application of two different next generation sequencing-based procedures. - Licastro, Danilo; Mutarelli, Margherita; Peluso, Ivana; Neveling, Kornelia; Wieskamp, Nienke; Rispoli, Rossella; Vozzi, Diego; Athanasakis, Emmanouil; D'Eustacchio, Angela; Pizzo, Mariateresa; D'Amico, Francesca; Ziviello, Carmela; et al. (PLoS One, 2012)
Usher syndrome (USH) is a clinically and genetically heterogeneous disorder characterized by visual and hearing impairments. Clinically, it is subdivided into three subclasses with nine genes identified so far. In the present study, we investigated whether the currently available Next Generation Sequencing (NGS) technologies are already suitable for molecular diagnostics of USH. We analyzed a total of 12 patients, most of which were negative for previously described mutations in known USH genes upon primer extension-based microarray genotyping. We enriched the NGS template either by whole exome capture or by Long-PCR of the known USH genes. The main NGS sequencing platforms were used: SOLiD for whole exome sequencing, Illumina (Genome Analyzer II) and Roche 454 (GS FLX) for the Long-PCR sequencing. Long-PCR targeting was more efficient with up to 94% of USH gene regions displaying an overall coverage higher than 25×, whereas whole exome sequencing yielded a similar coverage for only 50% of those regions. Overall this integrated analysis led to the identification of 11 novel sequence variations in USH genes (2 homozygous and 9 heterozygous) out of 18 detected. However, at least two cases were not genetically solved. Our result highlights the current limitations in the diagnostic use of NGS for USH patients. The limit for whole exome sequencing is linked to the need of a strong coverage and to the correct interpretation of sequence variations with a non obvious, pathogenic role, whereas the targeted approach suffers from the high genetic heterogeneity of USH that may be also caused by the presence of additional causative genes yet to be identified.
Keywords: Child, Preschool; Exome; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Molecular Diagnostic Techniques; Pilot Projects; Sequence Analysis, DNA; Usher Syndromes

MYH9-related disorders: report on a patient of Greek origin presenting with macroscopic hematuria and presenile cataract, caused by an R1165C mutation. - Economou, Marina; Batzios, Spyros P; Pecci, Alessandro; Printza, Nikoletta; Savoia, Anna; Barozzi, Serena; Theodoridou, Stamatia; Teli, Aikaterini; Psillas, Georgios; Zafeiriou, Dimitrios I (J Pediatr Hematol Oncol, 2012)
Myosin heavy chain-9 (MYH9)-related disorders represent a heterogenous group of hereditary diseases caused by mutations in the gene encoding the heavy chain of nonmuscle myosin IIA. May-Hegglin anomaly and Fechtner, Sebastian, and Epstein syndromes are the four phenotypes of the disease, characterized by congenital macrothrombocytopenia and distinguished by different combinations of clinical signs that may include glomerulonephritis, sensorineural hearing loss, and presenile cataract. The spectrum of mutations responsible for the disease is wide and the existence of genotype-phenotype correlation remains a critical issue. We report the first case of an MYH9-RD in a patient of Greek origin presenting with macroscopic hematuria and presenile cataract caused by a p.R1165C mutation. The same mutation was present in the patient's father, who exhibited no extrahematological features of the disease. The p.R1165C mutation is one of the MYH9 alterations whose prognostic significance is still poorly defined. Thus, the patients described add to the limited existing data on the MYH9 mutations and their resultant phenotypes.
Keywords: Adolescent; Cataract; Diagnosis, Differential; DNA Mutational Analysis; Greece; Hematuria; Humans; Male; Molecular Motor Proteins; Myosin Heavy Chains; Point Mutation

The negative prognostic value of TRAIL overexpression in oral squamous cell carcinomas does not preclude the potential therapeutic use of recombinant TRAIL. - Carinci, Francesco; Monasta, Lorenzo; Rubini, Corrado; Stramazzotti, Daniela; Palmieri, Annalisa; Melloni, Elisabetta; Knowles, Alex; Ronfani, Luca; Zauli, Giorgio; Secchiero, Paola (Invest New Drugs, 2012)
Keywords: Adult; Aged; Aged, 80 and over; Antineoplastic Agents; Apoptosis; Carcinoma, Squamous Cell; Female; Flow Cytometry; HL-60 Cells; Humans; Immunohistochemistry; Male; Middle Aged; Mouth Neoplasms; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Recombinant Proteins; Risk Assessment; Risk Factors; Survival Analysis; TNF-Related Apoptosis-Inducing Ligand; Tumor Markers, Biological; Up-Regulation; Young Adult

New insights in the sugarcane transcriptome responding to drought stress as revealed by superSAGE. - Kido, Éderson Akio; Ferreira Neto, José Ribamar Costa; Silva, Roberta Lane de Oliveira; Pandolfi, Valesca; Guimarães, Ana Carolina Ribeiro; Veiga, Daniela Truffi; Chabregas, Sabrina Moutinho; Crovella, Sergio; Benko-Iseppon, Ana Maria (ScientificWorldJournal, 2012)
In the scope of the present work, four SuperSAGE libraries have been generated, using bulked root tissues from four drought-tolerant accessions as compared with four bulked sensitive genotypes, aiming to generate a panel of differentially expressed stress-responsive genes. Both groups were submitted to 24 hours of water deficit stress. The SuperSAGE libraries produced 8,787,315 tags (26 bp) that, after exclusion of singlets, allowed the identification of 205,975 unitags. Most relevant BlastN matches comprised 567,420 tags, regarding 75,404 unitags with 164,860 different ESTs. To optimize the annotation efficiency, the Gene Ontology (GO) categorization was carried out for 186,191 ESTs (BlastN against Uniprot-SwissProt), permitting the categorization of 118,208 ESTs (63.5%). In an attempt to elect a group of the best tags to be validated by RTqPCR, the GO categorization of the tag-related ESTs allowed the in silico identification of 213 upregulated unitags responding basically to abiotic stresses, from which 145 presented no hits after BlastN analysis, probably concerning new genes still uncovered in previous studies. The present report analyzes the sugarcane transcriptome under drought stress, using a combination of high-throughput transcriptome profiling by SuperSAGE with the Solexa sequencing technology, allowing the identification of potential target genes during the stress response.
Keywords: Droughts; Gene Expression Profiling; Heat-Shock Response; Plant Proteins; Saccharum; Transcriptome

Pegylated TRAIL retains anti-leukemic cytotoxicity and exhibits improved signal transduction activity with respect to TRAIL. - Gonelli, Arianna; Radillo, Oriano; Drioli, Sara; Rimondi, Erika; Secchiero, Paola; Maria Bonora, Gian (Invest New Drugs, 2012)
To improve the pharmacokinetic profile of tumor necrosis factor-related apoptosis inducing ligand (TRAIL) an N-terminal specific pegylation was performed to generate pegylated TRAIL (PEG-TRAIL). In in vitro experiments, we found that although PEG-TRAIL was slightly less efficient than recombinant TRAIL in promoting leukemic cell apoptosis, it showed an improved ability to promote migration of bone-marrow mesenchymal stem cells and to elicit the ERK1/2 intracellular signal transduction pathway. Overall, these data suggest that TRAIL pegylation retains, or even enhances, the biological activities of TRAIL relevant for its therapeutic applications.
Keywords: Antineoplastic Agents; Apoptosis; Caspase 3; Cell Movement; Dose-Response Relationship, Drug; HL-60 Cells; Humans; Leukemia; Mesenchymal Stromal Cells; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 3; Phosphorylation; Polyethylene Glycols; Recombinant Fusion Proteins; Signal Transduction; Time Factors; TNF-Related Apoptosis-Inducing Ligand

Pelvic inflammatory disease (PID) from Chlamydia trachomatis versus PID from Neisseria gonorrhea: from clinical suspicion to therapy. - De Seta, F; Banco, R; Turrisi, A; Airoud, M; De Leo, R; Stabile, G; Ceccarello, M; Restaino, S; De Santo, D (G Ital Dermatol Venereol, 2012)
Pelvic inflammatory disease (PID) is the most significant complication of sexually transmitted infections in childbearing-age women and it represents an important public health problem because of its long-term sequelae (chronic pelvic pain, tubal infertility, ectopic pregnancy). Prior to the mid 1970s PID was considered a monoetiologic infection, due primarily to Neisseria gonorrhea. Now it is well documented as a polymicrobial process, with a great number of microrganisms involved. In addition to Neisseria gonorrhea and Chlamydia trachomatis, other vaginal microrganisms (anaerobes, Gardnerella vaginalis, Haemophilus influenzae, enteric Gram negative rods, Streptococco agalactie, Mycoplasma genitalium) also have been associated with PID. There is a wide variation in PID clinical features; the type and severity of symptoms vary by microbiologic etiology. Women who have chlamydial PID seem more likely than women who have gonococcal PID to be asymptomatic. Since clinical diagnosis is imprecise, the suspicion of PID should be confirmed by genital assessment for signs of inflammation or infection, blood test and imaging evaluation. Laparoscopic approach is considered the gold standard. According to the polymicrobial etiology of PID, antibiotic treatment must provide broad spectrum coverage of likely pathogens. Early administration of antibiotics is necessary to reduce the risk of long-term sequelae.
Keywords: Chlamydia Infections; Chlamydia trachomatis; Female; Gonorrhea; Humans; Neisseria gonorrhoeae; Pelvic Inflammatory Disease

Personalized therapies in pediatric inflammatory and autoimmune diseases. - Stocco, Gabriele; De Iudicibus, Sara; Franca, Raffaella; Addobbati, Riccardo; Decorti, Giuliana (Curr Pharm Des, 2012)
Pediatric inflammatory and autoimmune diseases are a wide array of systemic or organ-specific conditions, characterized by an exaggerated immune reactivity, which generally occurs in immunogenetically predisposed children. Among the most important ones, in terms of their diffusion and morbidity in the population worldwide, pediatric inflammatory bowel disease (IBD) and juvenile rheumatoid arthritis (JRA) have to be considered. The aim of personalized therapy is to give to each patient the most appropriate drug and dose regimen, in order to maximize treatment response and reduce the risk of adverse events. In general, several therapeutic options exist for pediatric inflammatory and autoimmune conditions, therefore the perspective of pharmacological tools that allow identification of patients with increased risk of treatment issues related to a particular medication, in terms of lack of efficacy or increased probability of adverse events, is particularly desirable and promising. The present review will be focused on the personalized therapy approaches already available or in development for pediatric patients with IBD or JRA, comprising pharmacokinetic, pharmacodynamic and pharmacogenetic assays.
Keywords: Arthritis, Rheumatoid; Autoimmune Diseases; Child; Genetic Predisposition to Disease; Humans; Immunogenetic Phenomena; Individualized Medicine; Inflammation; Inflammatory Bowel Diseases; Pharmacogenetics

Polimorphisms in inflammasome genes are involved in the predisposition to systemic lupus erythematosus. - Pontillo, Alessandra; Girardelli, Martina; Kamada, Anselmo J; Pancotto, Joao A T; Donadi, Eduardo A; Crovella, Sergio; Sandrin-Garcia, Paula (Autoimmunity, 2012)
Recent findings provide evidence of inflammasome critical role in the predisposition to autoimmune disorders. The involvement of inflammasome in the pathogenesis of systemic lupus erythematosus (SLE) has been hypothesized even if no significant association within inflammasome genes mutations or polymorphisms and lupus has been reported yet. We analyzed 14 single nucleotide polymorphisms (SNPs) within 7 inflammasome genes (NLRP1, NLRP3, NLRC4, AIM2, CARD8, CASP1, IL1B) in 144 patients affected by systemic lupus erythematosus and in 158 healthy controls from Southern Brazilian (state of São Paulo) with the aim of disclosing the possible role of inflammasome genes in the susceptibility of SLE. Our results demonstrated that NLRP1 rs2670660 SNP and the NLRP1 rs12150220-rs2670660 A-G haplotype were associated with SLE in our study population, and in particular with the development of nephritis, rash and arthritis. These findings are concordant with previously reported association of NLRP1 with vitiligo and type-1 diabetes underlining once more the involvement of NALP1 inflammasome in the pathogenesis of autoimmune disorders.
Keywords: Adaptor Proteins, Signal Transducing; Adult; Alleles; Apoptosis Regulatory Proteins; Brazil; Female; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Inflammasomes; Lupus Erythematosus, Systemic; Male; Middle Aged; Polymorphism, Single Nucleotide

Polymorphisms in DC-SIGN and L-SIGN genes are associated with HIV-1 vertical transmission in a Northeastern Brazilian population. - da Silva, Ronaldo Celerino; Segat, Ludovica; Zanin, Valentina; Arraes, Luiz Claudio; Crovella, Sergio (Hum Immunol, 2012)
DC-SIGN and L-SIGN are receptors expressed on specialized macrophages in decidua, (Hofbauer and placental capillary endothelial cells), known to interact with several pathogens, including HIV-1. To disclose the possible involvement of these molecules in the susceptibility to HIV vertical transmission, we analyzed DC-SIGN and L-SIGN gene single nucleotide polymorphisms (SNPs) in 192 HIV-1 positive children and 58 HIV-1 negative children all born to HIV-1 positive mothers, as well as 96 healthy uninfected children not exposed to HIV-1, all from Northeast Brazil. The frequency of three SNPs in the DC-SIGN promoter (-139G>A, -201G>T and -336A>G) were significantly different when comparing HIV positive children with HIV-1 exposed uninfected children, indicating an association with susceptibility to HIV-1 vertical transmission. This genetic association suggests that DC-SIGN molecule may play a role in susceptibility to HIV-1 infection through vertical transmission.
Keywords: Alleles; Brazil; Cell Adhesion Molecules; Child; Child, Preschool; Exons; Female; Gene Frequency; Genotype; HIV Infections; HIV-1; Humans; Infectious Disease Transmission, Vertical; Lectins, C-Type; Male; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Receptors, Cell Surface; Tandem Repeat Sequences

Potential role of TRAIL in the management of autoimmune diabetes mellitus. - Bernardi, Stella; Norcio, Alessia; Toffoli, Barbara; Zauli, Giorgio; Secchiero, Paola (Curr Pharm Des, 2012)
Type 1 diabetes mellitus (T1DM) is an autoimmune disease, due to the immune-mediated destruction of pancreatic β-cells, whose incidence has been steadily increasing during the last decades. Insulin replacement therapy can treat T1DM, which, however, is still associated with substantial morbidity and mortality. For this reason, great effort is being put into developing strategies that could eventually prevent and/or cure this disease. These strategies are mainly focused on blocking the immune system from attacking β-cells together with functional islet restoration either by regeneration or transplantation. Recent experimental evidences suggest that TNFrelated apoptosis-inducing ligand (TRAIL), which is an immune system modulator protein, could represent an interesting candidate for the cure for T1DM and/or its complications. Here we review the evidences on the potential role of TRAIL in the management of T1DM.
Keywords: Animals; Autoimmunity; Diabetes Mellitus, Type 1; Humans; Hypoglycemic Agents; Insulin; Insulin-Secreting Cells; Islets of Langerhans; TNF-Related Apoptosis-Inducing Ligand

A real-time polymerase chain reaction-based protocol for low/medium-throughput Y-chromosome microdeletions analysis. - Segat, Ludovica; Padovan, Lara; Doc, Darja; Petix, Vincenzo; Morgutti, Marcello; Crovella, Sergio; Ricci, Giuseppe (Genet Test Mol Biomarkers, 2012)
PURPOSE: We describe a real-time polymerase chain reaction (PCR) protocol based on the fluorescent molecule SYBR Green chemistry, for a low- to medium-throughput analysis of Y-chromosome microdeletions, optimized according to the European guidelines and aimed at making the protocol faster, avoiding post-PCR processing, and simplifying the results interpretation. METHODS: We screened 156 men from the Assisted Reproduction Unit, Department of Obstetrics and Gynecology, Institute for Maternal and Child Health IRCCS Burlo Garofolo (Trieste, Italy), 150 not presenting Y-chromosome microdeletion, and 6 with microdeletions in different azoospermic factor (AZF) regions. For each sample, the Zinc finger Y-chromosomal protein (ZFY), sex-determining region Y (SRY), sY84, sY86, sY127, sY134, sY254, and sY255 loci were analyzed by performing one reaction for each locus. RESULTS: AZF microdeletions were successfully detected in six individuals, confirming the results obtained with commercial kits. CONCLUSION: Our real-time PCR protocol proved to be a rapid, safe, and relatively cheap method that was suitable for a low- to medium-throughput diagnosis of Y-chromosome microdeletion, which allows an analysis of approximately 10 samples (with the addition of positive and negative controls) in a 96-well plate format, or approximately 46 samples in a 384-well plate for all markers simultaneously, in less than 2 h without the need of post-PCR manipulation.
Keywords: Azoospermia; Chromosome Deletion; Chromosomes, Human, Y; Female; Humans; Kruppel-Like Transcription Factors; Male; Real-Time Polymerase Chain Reaction; Sex Chromosome Aberrations; Sex Chromosome Disorders of Sex Development

Role of high molecular weight hyaluronic acid in postmenopausal vaginal discomfort. - Grimaldi, E F; Restaino, S; Inglese, S; Foltran, L; Sorz, A; Di Lorenzo, G; Guaschino, S (Minerva Ginecol, 2012)
AIM: Aim of the present study was to quantify the intensity of vulvovaginal symptoms before and after treatment with high molecular weight hyaluronic acid (HA), to test the tolerability and safety of the product, to evaluate the effect on the quality of life and the compliance to the treatment. METHODS: This was a double-blind randomized placebo-controlled study. In seven months we enrolled 36 post-menopausal women, equally distributed in placebo and active group. The evaluation was based on at least three atrophy-related signs and on the patient reported symptoms. After the written informed consent, the participants were instructed to apply the gel (drug or placebo) daily. Three days after the end of the treatment the patients received a final examination to evaluate the progress of symptoms, the presence of any adverse events and their correlation with the treatment. RESULTS: Self-evaluation scales and investigator evaluation showed that the vaginal dryness was significantly reduced both in placebo and in the active group; however, high molecular weight HA was the only active treatment in reducing significantly itching and burning (P<0.02 and <0.04 respectively). Both treatments significantly reduced vaginal atrophy (P<0.001), erythema (P<0.01 placebo and P<0.001 HA) and vaginal dryness (P<0.001), but HA treatment was significantly more effective on the first two symptoms. Both treatments were very well tolerated and compliance of the treatment was very high. CONCLUSION: High molecular weight HA could be effective in subjective and objective improvement of postmenopausal vaginal atrophy providing a good compliance. No adverse events occurred during the entire period of the study.
Keywords: Atrophy; Double-Blind Method; Female; Humans; Hyaluronic Acid; Middle Aged; Molecular Weight; Postmenopause; Vagina; Vaginal Diseases

Sedation with intranasal midazolam of Angolan children undergoing invasive procedures. - Kawanda, Lumana; Capobianco, Ivan; Starc, Meta; Felipe, Daniel; Zanon, Davide; Barbi, Egidio; Munkela, Nadine; Rodrigues, Verónica; Malundo, Lúis; Not, Tarcisio (Acta Paediatr, 2012)
AIM: Ambulatory surgery is a daily requirement in poor countries, and limited means and insufficient trained staff lead to the lack of attention to the patient's pain. Midazolam is a rapid-onset, short-acting benzodiazepine which is used safely to reduce pain in children. We evaluated the practicability of intranasal midazolam sedation in a suburban hospital in Luanda (Angola), during the surgical procedures. METHODS: Intranasal midazolam solution was administered at a dose of 0.5 mg/kg. Using the Ramsay's reactivity score, we gave a score to four different types of children's behaviour: moaning, shouting, crying and struggling, and the surgeon evaluated the ease of completing the surgical procedure using scores from 0 (very easy) to 3 (managing with difficulty). RESULTS: Eighty children (median age, 3 years) were recruited, and 140 surgical procedures were performed. Fifty-two children were treated with midazolam during 85 procedures, and 28 children were not treated during 55 procedures. We found a significant difference between the two groups on the shouting, crying and struggling parameters (p < 0.001). The mean score of the ease of completing the procedures was significantly different among the two groups (p < 0.0001). CONCLUSION: These results provide a model of procedural sedation in ambulatory surgical procedures in poor countries, thus abolishing pain and making the surgeon's job easier.
Keywords: Administration, Intranasal; Adolescent; Ambulatory Surgical Procedures; Angola; Child; Child Behavior; Child, Preschool; Conscious Sedation; Crying; Female; Humans; Hypnotics and Sedatives; Infant; Male; Midazolam; Prospective Studies

Simultaneous determination of multiple cytokines reveals a pro-inflammatory and pro-angiogenic signature after major cardiothoracic surgery: potential role of C-reactive protein. - Tisato, Veronica; Monasta, Lorenzo; Biolo, Gianni; Donatelli, Francesco; Secchiero, Paola; Zauli, Giorgio (Cytokine, 2012)
Keywords: C-Reactive Protein; Coronary Artery Bypass; Cytokines; Humans; Inflammation; Macrophages; Neovascularization, Physiologic; Risk Factors

Soluble TRAIL is elevated in recurrent miscarriage and inhibits the in vitro adhesion and migration of HTR8 trophoblastic cells. - Agostinis, Chiara; Bulla, Roberta; Tisato, Veronica; De Seta, Francesco; Alberico, Salvatore; Secchiero, Paola; Zauli, Giorgio (Hum Reprod, 2012)
STUDY QUESTION: What is the potential physiopathological role of tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) in recurrent miscarriage (RM), characterized by at least three consecutive pregnancy losses. SUMMARY ANSWER: The levels of serum TRAIL immediately after miscarriage in RM patients are significantly elevated with respect to that in first-trimester normal pregnant women, and recombinant TRAIL inhibits the adhesion and migration of HTR8 trophoblastic cells in vitro. WHAT IS KNOWN ALREADY: Both TRAIL and its trans-membrane receptors (TRAIL-R1, TRAIL-R2, TRAIL-R3 and TRAIL-R4) have been documented in the placenta, but their physiopathological role is incompletely understood. STUDY DESIGN, SIZE, DURATION: The study populations consisted of RM patients (n = 80) and first-trimester normal pregnant women (n = 80). Blood samples were obtained within 24 h after abortion (RM) or at gestational 12-week (normal pregnant women). As additional controls, third-trimester normal pregnant women (n = 28) were examined before (within 72 h) and after (within 24 h) partum. PARTICIPANTS/MATERIALS, SETTING, METHODS: The concentrations of TRAIL were analysed in serum samples by ELISA. In parallel, the effect of soluble recombinant TRAIL (0.1-1000 ng/ml) was analysed on the survival of primary extravillus trophoblasts (EVTs) and on the survival, proliferation, adhesion and migration of trophoblastic HTR8 cells. MAIN RESULTS AND THE ROLE OF CHANCE: The circulating levels of TRAIL in RM women (median: 52.5 pg/ml; mean and SD: 55.5 ± 24.4 pg/ml) were significantly higher with respect to first-trimester normal pregnant women (median: 44.9 pg/ml; mean and SD: 47 ± 15.1 pg/ml) and third-trimester normal pregnant women, as assessed before (median: 45.1 pg/ml; mean and SD: 46 ± 12.4 pg/ml) and after partum (median: 35.4 pg/ml; mean and SD: 38 + 17.5 pg/ml). Both primary EVT and HTR8 cells expressed detectable levels of TRAIL death receptors, but exposure to soluble recombinant TRAIL did not induce cell death of trophoblastic cells. On the other hand, TRAIL dose-dependently inhibited the adhesion of HTR8 cells to decidual endothelial cells (DEC) as well as the migration of HTR8 in transwell assays using either fibronectin or DEC. LIMITATIONS, REASONS FOR CAUTION: Although this study suggests that TRAIL might have a pathogenic role in RM by inhibiting both the adhesion and migration capabilities of first trimester trophoblastic cells, there is a possibility that the elevated serum levels of TRAIL in RM are not cause but rather the result of RM. WIDER IMPLICATIONS OF THE FINDINGS: Our current findings together with data of other authors suggest that circulating TRAIL should be further analysed as a potential important biomarker in different physiopathological settings. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by FIRB projects (RBAP11Z4Z9_002 to Giorgio Zauli and RBAP10447J_002 to Paola Secchiero). The authors have no competing interests to declare.
Keywords: Abortion, Habitual; Apoptosis; Cell Adhesion; Cell Line; Cell Movement; Cells, Cultured; Enzyme-Linked Immunosorbent Assay; Female; Humans; Pregnancy; Receptors, TNF-Related Apoptosis-Inducing Ligand; TNF-Related Apoptosis-Inducing Ligand; Trophoblasts

The sorafenib plus nutlin-3 combination promotes synergistic cytotoxicity in acute myeloid leukemic cells irrespectively of FLT3 and p53 status. - Zauli, Giorgio; Celeghini, Claudio; Melloni, Elisabetta; Voltan, Rebecca; Ongari, Manuele; Tiribelli, Mario; di Iasio, Maria Grazia; Lanza, Francesco; Secchiero, Paola (Haematologica, 2012)
BACKGROUND: Both the multi-kinase inhibitor sorafenib and the small molecule inhibitor of the MDM2/p53 interaction, nutlin-3, used alone, have shown promising anti-leukemic activity in acute myeloid leukemia cells. Thus, in this study we investigated the effect of the combination of sorafenib plus nutlin-3 in acute myeloid leukemia. DESIGN AND METHODS: Primary acute myeloid leukemia blasts (n=13) and FLT3(wild-type)/p53(wild-type) (OCI-AML3), FLT3(mutated)/p53(wild-type) (MOLM), FLT3(mutated)/p53(mutated) (MV4-11), FLT3(wild-type)/p53(deleted) (HL60) or FLT3(wild-type)/p53(mutated) (NB4) acute myeloid cell lines were exposed to sorafenib, used alone or in association with nutlin-3 at a 1:1 ratio, in a range of clinically achievable concentrations (1-10 μM). Induction of apoptosis and autophagy was evaluated by transmission electron microscopy and by specific flow cytometry analyses. The levels of Mcl-1, p53 and Bak proteins were analyzed by western blotting. Knock-down of Bax and Bak gene expression was performed in transfection experiments with specific short interfering RNA. RESULTS: The sorafenib+nutlin-3 drug combination exhibits synergistic cytotoxicity in primary acute myeloid leukemia blasts and in acute myeloid leukemia cell lines with maximal cytotoxicity in FLT3(mutated) MV4-11 and MOLM, followed by the FLT3(wild-type) OCI-AML3, HL60 and NB4 cell lines. The cytotoxic activity of sorafenib+nutlin-3 was characterized by an increase of both apoptosis and autophagy. Moreover, Bax and Bak showed prominent roles in mediating the decrease of cell viability in response to the drug combination in p53(wild-type) OCI-AML3 and p53(deleted) HL-60 cells, respectively, as demonstrated in transfection experiments performed with specific short interfering RNA. CONCLUSIONS: Our data demonstrate that acute myeloid leukemia cells show a variable but overall good susceptibility to the innovative therapeutic combination of sorafenib+nutlin-3, which differentially involves the pro-apoptotic Bcl-2 family members Bax and Bak in p53(wild-type) and p53(deleted) cells.
Keywords: Antineoplastic Agents; Drug Synergism; Female; fms-Like Tyrosine Kinase 3; HL-60 Cells; Humans; Imidazoles; Leukemia, Myeloid, Acute; Male; Niacinamide; Phenylurea Compounds; Piperazines; Tumor Suppressor Protein p53

State of art and recent developments of anti-cancer strategies based on TRAIL. - Bernardi, Stella; Secchiero, Paola; Zauli, Giorgio (Recent Pat Anticancer Drug Discov, 2012)
Multicellular organisms require apoptosis whereby the human body eliminates unnecessary and/or damaged cells. Apoptosis, or programmed cell death, can indeed be considered as a constitutive anti-cancer mechanism that seems to be defective in more than 50% of cancers. Molecular insights on the biology of the apoptotic process have led to the development of new anti-cancer strategies aiming at recovering and stimulating this process. Preclinical and clinical studies of our and other groups have demonstrated that targeting the extrinsic apoptotic pathway by various death receptors agonists is a safe and effective anti-cancer strategy, which thus may become a new cornerstone of cancer therapy. Here, we review the most recent acquisitions and patents on TRAIL or TRAIL mimetics, as well as the combination therapies that could be used with them.
Keywords: Animals; Antineoplastic Agents; Antineoplastic Combined Chemotherapy Protocols; Apoptosis; Clinical Trials as Topic; Humans; Mice; Neoplasms; Receptors, Death Domain; TNF-Related Apoptosis-Inducing Ligand

State of the art of the therapeutic perspective of sorafenib against hematological malignancies. - Zauli, G; Voltan, R; Tisato, V; Secchiero, P (Curr Med Chem, 2012)
The bi-aryl urea multi-kinase inhibitor Sorafenib (BAY 43-9006, Nexavar) was initially approved for the treatment of unresectable hepatocellular carcinoma and advanced renal cell carcinoma. Eleven years after its first description in PubMed, the therapeutic potential of Sorafenib has been evaluated in an increasing number of studies, mainly focused on solid tumors. More recently, the potential usefullness of Sorafenib has started to emerge also against hematological malignancies. At the molecular level, besides the RAF kinase pathway, which represents the first therapeutic target of Sorafenib, additional kinases, in particular the vascular endothelial growth factor receptor, have been identified as important targets of Sorafenib. A great interest for the potential use of Sorafenib against acute myeloid leukemia (AML) arose when it was demonstrated that a specific mutation of a kinase gene, called FMS-like tyrosin-kinase-3- internal tandem duplication (FLT-3-ITD) and occurring in more than 30% of AML, represents a molecular target of Sorafenib. However, recent phase I and II clinical studies showed that, in spite of its ability to suppress the activity of this mutated kinase, resistence to Sorafenib rapidly occurs in AML, suggesting that Sorafenib will be more effective in combined therapy than used as single drug. Another critical molecular target of Sorafenib is the anti-apoptotic protein Mcl-1. The ability of Sorafenib to rapidly shut-off Mcl-1 in virtually all the hematological malignancies investigated, including the B-chronic lymphocytic leukemia, represents a key element for its antileukemic activity as well as for therapeutic combinations based on Sorafenib. In this respect, it is of particular interest that many chemotherapeutic drugs or innovative anti-neoplastic compounds, such as recombinant TRAIL or inibitors of MDM2 protein, are either unable to down-regulate Mcl-1 or in some instances promote a paradoxical induction of Mcl-1. In this review, the growing evidences for the role of Mcl-1 in mediating the anti-leukemic activity of Sorafenib will be discussed in relationship with promising therapeutic perspectives.
Keywords: Apoptosis; Clinical Trials as Topic; fms-Like Tyrosine Kinase 3; Hematologic Neoplasms; Humans; Leukemia, Myeloid, Acute; Myeloid Cell Leukemia Sequence 1 Protein; Niacinamide; Phenylurea Compounds; Proto-Oncogene Proteins c-bcl-2; Proto-Oncogene Proteins c-mdm2; Receptors, Vascular Endothelial Growth Factor; TNF-Related Apoptosis-Inducing Ligand

Stem cell ageing and apoptosis. - Fulle, Stefania; Centurione, Lucia; Mancinelli, Rosa; Sancilio, Silvia; Manzoli, Francesco Antonio; Di Pietro, Roberta (Curr Pharm Des, 2012)
Ageing has been defined as the process of deterioration of many body functions over the lifespan of an individual. In spite of the number of different theories about ageing, there is a general consensus in identifying ageing effects in a reduced capacity to regenerate injured tissues or organs and an increased propensity to infections and cancer. In recent years the stem cell theory of ageing has gained much attention. Adult stem cells residing in mammalian tissues are essential for tissue homeostasis and repair throughout adult life. With advancing age, the highly regulated molecular signalling necessary to ensure proper cellular, tissue, and organ homeostasis loses coordination and leads, as a consequence, to a compromised potential of regeneration and repair of damaged cells and tissues. Although a complete comprehension of the molecular mechanisms involved in stem cell ageing and apoptosis is far to be reached, recent studies are beginning to unravel the processes involved in stem cell ageing, particularly in adult skeletal muscle stem cells, namely satellite cells. Thus, the focus of this review is to analyse the relationship between stem cell ageing and apoptosis with a peculiar attention to human satellite cells as compared to haematopoietic stem cells. Undoubtedly, the knowledge of age-related changes of stem cells will help in understanding the ageing process itself and will provide novel therapeutic challenges for improved tissue regeneration.
Keywords: Adult; Apoptosis; Cell Aging; Humans; Stem Cells

Thoracoscopic removal of a bulky cystic mediastinal mature teratoma in a 4-year-old child: report of one case and few surgical tricks. - Codrich, Daniela; Lembo, Maria Antonietta; Schleef, Jurgen (Eur J Pediatr Surg, 2012)
Keywords: Child, Preschool; Female; Humans; Mediastinal Neoplasms; Teratoma; Thoracoscopy; Tomography, X-Ray Computed

TNF-related apoptosis-inducing ligand significantly attenuates metabolic abnormalities in high-fat-fed mice reducing adiposity and systemic inflammation. - Bernardi, Stella; Zauli, Giorgio; Tikellis, Christos; Candido, Riccardo; Fabris, Bruno; Secchiero, Paola; Cooper, Mark E; Thomas, Merlin C (Clin Sci (Lond), 2012)
TRAIL [TNF (tumour necrosis factor)-related apoptosis-inducing ligand] has recently been shown to ameliorate the natural history of DM (diabetes mellitus). It has not been determined yet whether systemic TRAIL delivery would prevent the metabolic abnormalities due to an HFD [HF (high-fat) diet]. For this purpose, 27 male C57bl6 mice aged 8 weeks were randomly fed on a standard diet, HFD or HFD+TRAIL for 12 weeks. TRAIL was delivered weekly by intraperitoneal injection. Body composition was evaluated; indirect calorimetry studies, GTT (glucose tolerance test) and ITT (insulin tolerance test) were performed. Pro-inflammatory cytokines, together with adipose tissue gene expression and apoptosis, were measured. TRAIL treatment reduced significantly the increased adiposity associated with an HFD. Moreover, it reduced significantly hyperglycaemia and hyperinsulinaemia during a GTT and it improved significantly the peripheral response to insulin. TRAIL reversed the changes in substrate utilization induced by the HFD and ameliorated skeletal muscle non-esterified fatty acids oxidation rate. This was associated with a significant reduction of pro-inflammatory cytokines together with a modulation of adipose tissue gene expression and apoptosis. These findings shed light on the possible anti-adipogenic and anti-inflammatory effects of TRAIL and open new therapeutic possibilities against obesity, systemic inflammation and T2DM (Type 2 DM).
Keywords: Adiposity; Animals; Apoptosis; Calorimetry; Cytokines; Dietary Fats; Energy Intake; Glucose Tolerance Test; Hyperglycemia; Hyperinsulinism; Inflammation; Inflammation Mediators; Male; Mice; Mice, Inbred C57BL; Oxidation-Reduction; Palmitic Acid; Real-Time Polymerase Chain Reaction; TNF-Related Apoptosis-Inducing Ligand

TRAIL, a new weapon against neointimal hyperplasia. - Secchiero, Paola; Zauli, Giorgio (Cardiology, 2012)
Keywords: Coronary Restenosis; Drug-Eluting Stents; Female; Humans; Male; Neointima; TNF-Related Apoptosis-Inducing Ligand

TRAIL administration down-modulated the acute systemic inflammatory response induced in a mouse model by muramyldipeptide or lipopolysaccharide. - Marcuzzi, Annalisa; Secchiero, Paola; Crovella, Sergio; Zauli, Giorgio (Cytokine, 2012)
The potent inducer of apoptosis TRAIL/Apo2 ligand is now under considerations in clinical trials for the treatment of different types of cancer. Since the natural history of cancer is often characterized by microbial infections, we have investigated the effect of recombinant human TRAIL in a mouse model of systemic acute inflammation of microbial origin represented by BALB/c mice treated with either bacterial muramyldipeptide (MDP) or lipopolysaccharide (LPS). When administered intraperitoneally (i.p.), these inflammatory bacterial compounds triggered a severe systemic inflammatory response within 2h, represented by body temperature elevation, increase of circulating serum amyloid-A (SAA) and of the number of leukocytes in the peritoneal cavity. Moreover, both MDP and LPS induced a significant elevation of the circulating levels of several inflammatory cytokines and chemokines. Noteworthy, pre-treatment with recombinant human TRAIL 48 and 72 h before administration of either MDP or LPS, significantly counteracted all acute inflammatory responses, including the elevation of key pro-inflammatory cytokines/chemokines such as IL-1α, IL-6, G-CSF, MCP-1. These data demonstrate for the first time that TRAIL has a potent anti-inflammatory activity, which might be beneficial for the anti-tumoral activity of TRAIL.
Keywords: Acetylmuramyl-Alanyl-Isoglutamine; Acute Disease; Animals; Chemokine CCL2; Cytokines; Disease Models, Animal; Down-Regulation; Granulocyte Colony-Stimulating Factor; Humans; Immunoassay; Inflammation; Inflammation Mediators; Interleukin-1alpha; Interleukin-6; Lipopolysaccharides; Male; Mice; Mice, Inbred BALB C; Recombinant Proteins; Serum Amyloid A Protein; TNF-Related Apoptosis-Inducing Ligand

TRAIL as biomarker and potential therapeutic tool for cardiovascular diseases. - Bernardi, Stella; Milani, Daniela; Fabris, Bruno; Secchiero, Paola; Zauli, Giorgio (Curr Drug Targets, 2012)
This review focuses on TNF-related apoptosis-inducing ligand (TRAIL), also called Apo2 ligand, a protein belonging to the TNF superfamily. TRAIL can be found either in its transmembrane or circulating form, and its mostly studied peripheral effect is the induction of cellular apoptosis. Here, we discuss the evidences supporting the use of TRAIL as biomarker of cardiovascular diseases as well as the evidences showing the potential beneficial therapeutic effects of TRAIL on cardiovascular diseases and diabetes.
Keywords: Biological Markers; Cardiovascular Diseases; Humans; Prognosis; TNF-Related Apoptosis-Inducing Ligand

TRAIL shows potential cardioprotective activity. - Toffoli, Barbara; Bernardi, Stella; Candido, Riccardo; Zacchigna, Serena; Fabris, Bruno; Secchiero, Paola (Invest New Drugs, 2012)
Recent clinical trials carried out in patients with advanced cancer have shown that recombinant TRAIL administration is usually safe and well tolerated when used either alone or in association with chemotherapeutic drugs. Notably, anticancer chemotherapy can be associated to cardiomiopathy. We have here demonstrated that TRAIL (administrated as either recombinant soluble TRAIL or as AAV-TRAIL expression viral vector) reduced the development of cardiomyopathy in the ApoE(-/-) diabetic mouse model. These data suggest, for the first time, that therapeutically administration of TRAIL might have a cardioprotective effect.
Keywords: Animals; Apolipoproteins E; Apoptosis; Cardiotonic Agents; Diabetes Mellitus, Experimental; Diabetes Mellitus, Type 1; Diabetic Cardiomyopathies; Fibrosis; Male; Mice; Mice, Knockout; Recombinant Proteins; TNF-Related Apoptosis-Inducing Ligand

Β-hexosaminidase over-expression affects lysosomal glycohydrolases expression and glycosphingolipid metabolism in mammalian cells. - Tancini, Brunella; Magini, Alessandro; Bortot, Barbara; Polchi, Alice; Urbanelli, Lorena; Sonnino, Sandro; Severini, Giovanni Maria; Emiliani, Carla (Mol Cell Biochem, 2012)
Lysosomes are not only degrading organelles but also involved in other critical cellular processes. In addition, active lysosomal glycohydrolases have been detected in an extra-lysosomal compartment: the presence of glycohydrolases on the plasma membrane (PM) has been widely demonstrated, and a possible role on the modification of the cell surface glycosphingolipids (GSL) participating in the modulation of cell functions such as cell-to-cell interactions and signal transduction pathways has been proposed. On this basis, the coordinated expression of lysosomal glycohydrolases and their translocation to the PM appear to be crucial for many cellular events. In this paper, we report evidence for the existence of a coordinated mechanism regulating the expression/activity of both lysosomal and PM-associated glycohydrolases. We show that the over-expression of the acidic glycohydrolase β-hexosaminidase α-subunit in mouse NIH/3T3 fibroblasts induces the increased expression of the Hex β-subunit necessary to form the active isoenzyme dimers as well as of other glycohydrolases participating in the GSL catabolism, such as β-galactosidase and β-glucocerebrosidase. More interestingly, this regulatory effect was also extended to the PM-associated hydrolases. In addition, transfected cells displayed a rearrangement of the GSL expression pattern that cannot be simply explained by the increased activity of a single enzyme. These observations clearly indicate that the expression level of metabolically related glycohydrolases is regulated in a coordinated manner and this regulation mechanism also involves the PM-associated isoforms.
Keywords: Animals; beta-Hexosaminidase alpha Chain; Cell Membrane; Exocytosis; Fibroblasts; Glycoside Hydrolases; Glycosphingolipids; Humans; Lysosomes; Mice; NIH 3T3 Cells; Transfection

Anti-α-enolase Antibodies in Serum from Pediatric Patients Affected by Inflammatory Diseases: Diagnostic and Pathogenetic Insights. - Pontillo, Alessandra; Di Toro, Nicola; Edomi, Paolo; Shadlow, A; Ammadeo, A; Gattorno, M; Not, T; Lepore, L; Crovella, S (Int J Rheumatol, 2011)
Human glycolytic enzyme α-enolase was associated with human diseases and with inflammation. An ELISA test was developed to measure anti-α-enolase AAE IgG and AAE IgA in the serum from patients affected by inflammatory diseases with the purpose to evaluate it as a novel diagnostic marker. 80 healthy blood donors and 194 paediatric patients affected by Juvenile idiopathic arthritis (JIA), celiac disease (CD), Crohn's Disease (CrD), hereditary periodic fever (HPF), and PFAPA syndrome were included in the study. HPF patients showed high levels of AAE antibodies, whereas JIA, CD, and CrD presented only partial results. Benign fevers such as PFAPA were almost negative for AAE Abs. These findings suggested that the genetic dysfunction of inflammasome associated with HPF could lead to the formation of AAE Abs that could be used for an early and easy diagnosis.

Association of a variant in the CHRNA5-A3-B4 gene cluster region to heavy smoking in the Italian population. - Sorice, Rossella; Bione, Silvia; Sansanelli, Serena; Ulivi, Sheila; Athanasakis, Emmanouil; Lanzara, Carmela; Nutile, Teresa; Sala, Cinzia; Camaschella, Clara; d'Adamo, Pio; Gasparini, Paolo; Ciullo, Marina; et al. (Eur J Hum Genet, 2011)
Large-scale population studies have established that genetic factors contribute to individual differences in smoking behavior. Linkage and genome-wide association studies have shown many chromosomal regions and genes associated with different smoking behaviors. One study was the association of single-nucleotide polymorphisms (SNPs) in the CHRNA5-A3-B4 gene cluster to nicotine addiction. Here, we report a replication of this association in the Italian population represented by three genetically isolated populations. One, the Val Borbera, is a genetic isolate from North-Western Italy; the Cilento population, is located in South-Western Italy; and the Carlantino village is located in South-Eastern Italy. Owing to their position and their isolation, the three populations have a different environment, different history and genetic structure. The variant A of the rs1051730 SNP was significantly associated with smoking quantity in two populations, Val Borbera and Cilento, no association was found in Carlantino population probably because difference in LD pattern in the variant region.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Italy; Multigene Family; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Receptors, Nicotinic; Smoking; Tobacco Use Disorder

Association of tumor necrosis factor-related apoptosis-inducing ligand with total and cardiovascular mortality in older adults. - Volpato, Stefano; Ferrucci, Luigi; Secchiero, Paola; Corallini, Federica; Zuliani, Giovanni; Fellin, Renato; Guralnik, Jack M; Bandinelli, Stefania; Zauli, Giorgio (Atherosclerosis, 2011)
OBJECTIVE: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) exhibits biological activity on vascular cells in vitro. Rapid variation of circulating TRAIL levels occurs during acute coronary ischemia, suggesting that biological pathways involving TRAIL may be activated during ischemic heart disease. However, whether differential levels of soluble TRAIL in normal individuals are associated with adverse health outcomes has not been investigated. We tested the hypothesis that TRAIL levels predict mortality in a population based sample of community dwelling men and women. METHODS: Plasma TRAIL level was measured by ELISA at baseline in 1282 adults (mean age 68 years) enrolled in the InCHIANTI study. Vital status was ascertained over the six-year follow-up. RESULTS: In multivariable Cox regression analysis adjusted for potential confounders including prevalent cardiovascular diseases (CVD), ankle-brachial index, electrocardiogram abnormalities, and inflammatory markers, baseline TRAIL levels were inversely related to all-cause mortality (p=0.008). In stratified analyses, the prognostic effect of TRAIL level was strong and highly significant in participants with prevalent CVD (N=321), (lowest versus highest quartile: HR 3.1; 95% CI 1.5-6.5) while it was negligible in those free of CVD (p value for the interaction term between CVD status and TRAIL levels=0.038). Similar findings were obtained when CVD mortality was considered as the outcome of interest. CONCLUSIONS: In older patients with CVD, low levels of TRAIL were associated with increased risk of death over a period of 6 years. Lower concentration of circulating TRAIL may be related to the clinical evolution of older adults with CVD.
Keywords: Adult; Aged; Ankle Brachial Index; Cardiovascular Diseases; Female; Follow-Up Studies; Humans; Italy; Male; Middle Aged; TNF-Related Apoptosis-Inducing Ligand

Childhood chronic anterior uveitis associated with vernal keratoconjunctivitis (VKC): successful treatment with topical tacrolimus. Case series. - Taddio, Andrea; Cimaz, Rolando; Caputo, Roberto; de Libero, Cinzia; Di Grande, Laura; Simonini, Gabriele; Mori, Francesca; Novembre, Elio; Pucci, Neri (Pediatr Rheumatol Online J, 2011)
Uveitis treatment involves topical corticosteroids along with cycloplegic-mydriatics. Particularly severe cases may require systemic corticosteroids and immunosuppressive drugs. Vernal keratoconjunctivitis (VKC) treatment consists of a brief period of topical corticosteroids and/or cyclosporine. In patients refractory to traditional treatment, the use of 0.1% topical ophtalmic FK- 506 (tacrolimus) ointment has been occasionally reported.This is the first report of the coexistence of uveitis and VKC. The documented response to topical tacrolimus eyedrop of uveitis and VKC is also of interest, in particular since to our knowledge there are no published reports on its clinical use in uveitis.

Circulating TRAIL shows a significant post-partum decline associated to stressful conditions. - Zauli, Giorgio; Monasta, Lorenzo; Rimondi, Erika; Vecchi Brumatti, Liza; Radillo, Oriano; Ronfani, Luca; Montico, Marcella; D'Ottavio, Giuseppina; Alberico, Salvatore; Secchiero, Paola (PLoS One, 2011)
BACKGROUND: Since circulating levels of TNF-related apoptosis inducing ligand (TRAIL) may be important in the physiopathology of pregnancy, we tested the hypothesis that TRAIL levels change at delivery in response to stressful conditions. METHODS/PRINCIPAL FINDINGS: We conducted a longitudinal study in a cohort of 73 women examined at week 12, week 16, delivery and in the corresponding cord blood (CB). Serum TRAIL was assessed in relationship with maternal characteristics and to biochemical parameters. TRAIL did not vary between 12 (67.6±27.6 pg/ml, means±SD) and 16 (64.0±16.2 pg/ml) weeks' gestation, while displaying a significant decline after partum (49.3±26.4 pg/ml). Using a cut-off decline >20 pg/ml between week 12 and delivery, the subset of women with the higher decline of circulating TRAIL (41.7%) showed the following characteristics: i) nullipara, ii) higher age, iii) operational vaginal delivery or urgent CS, iv) did not receive analgesia during labor, v) induced labor. CB TRAIL was significantly higher (131.6±52 pg/ml) with respect to the corresponding maternal TRAIL, and the variables significantly associated with the first quartile of CB TRAIL (<90 pg/ml) were higher pre-pregnancy BMI, induction of labor and fetal distress. With respect to the biochemical parameters, maternal TRAIL at delivery showed an inverse correlation with C-reactive protein (CRP), total cortisol, glycemia and insulin at bivariate analysis, but only with CRP at multivariate analysis. CONCLUSIONS: Stressful partum conditions and elevated CRP levels are associated with a decrease of circulating TRAIL.
Keywords: Adult; Biological Markers; C-Reactive Protein; Female; Fetal Blood; Fetal Distress; Humans; Labor, Obstetric; Logistic Models; Multivariate Analysis; Postpartum Period; Pregnancy; Pregnancy Outcome; Statistics, Nonparametric; Stress, Physiological; TNF-Related Apoptosis-Inducing Ligand

Clinical and genetic aspects of Bernard-Soulier syndrome: searching for genotype/phenotype correlations. - Savoia, Anna; Pastore, Annalisa; De Rocco, Daniela; Civaschi, Elisa; Di Stazio, Mariateresa; Bottega, Roberta; Melazzini, Federica; Bozzi, Valeria; Pecci, Alessandro; Magrin, Silvana; Balduini, Carlo L; Noris, Patrizia (Haematologica, 2011)
BACKGROUND: Bernard-Soulier syndrome is a severe bleeding disease due to a defect of GPIb/IX/V, a platelet complex that binds the von Willebrand factor. Due to the rarity of the disease, there are reports only on a few cases compromising any attempt to establish correlations between genotype and phenotype. In order to identify any associations, we describe the largest case series ever reported, which was evaluated systematically at the same center. DESIGN AND METHODS: Thirteen patients with the disease and seven obligate carriers were enrolled. We collected clinical aspects and determined platelet features, including number and size, expression of membrane glycoproteins, and ristocetin induced platelet aggregation. Mutations were identified by direct sequencing of the GP1BA, GP1BB, and GP9 genes and their effect was shown by molecular modeling analyses. RESULTS: Patients all had a moderate thrombocytopenia with giant platelets and a bleeding tendency whose severity varied among individuals. Consistent with expression levels of GPIbα always lower than 10% of control values, platelet aggregation was absent or severely reduced. Homozygous mutations were identified in the GP1BA, GP1BB and GP9 genes; six were novel alterations expected to destabilize the conformation of the respective protein. Except for obligate carriers of a GP9 mutation with a reduced GPIb/IX/V expression and defective aggregation, all the other carriers had no obvious anomalies. CONCLUSIONS: Regardless of mutations identified, the patients' bleeding diathesis did not correlate with thrombocytopenia, which was always moderate, and platelet GPIbα expression, which was always severely impaired. Obligate carriers had features similar to controls though their GPIb/IX/V expression showed discrepancies. Aware of the limitations of our cohort, we cannot define any correlations. However, further investigations should be encouraged to better understand the causes of this rare and underestimated disease.
Keywords: Adolescent; Adult; Amino Acid Sequence; Bernard-Soulier Syndrome; Blood Platelets; Cell Shape; Child; Child, Preschool; Female; Genetic Association Studies; Genetic Markers; Hemorrhage; Homozygote; Humans; Italy; Male; Membrane Glycoproteins; Middle Aged; Molecular Sequence Data; Platelet Aggregation; Platelet Count; Platelet Glycoprotein GPIb-IX Complex; Point Mutation; Polymerase Chain Reaction; Ristocetin; Thrombocytopenia; von Willebrand Factor; Young Adult

Clinical heterogeneity and diagnostic delay of autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy syndrome. - Mazza, Cinzia; Buzi, Fabio; Ortolani, Federica; Vitali, Alberto; Notarangelo, Lucia D; Weber, Giovanna; Bacchetta, Rosa; Soresina, Annarosa; Lougaris, Vassilios; Greggio, Nella A; Taddio, Andrea; Pasic, Srdjan; et al. (Clin Immunol, 2011)
Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) is a rare autosomal recessive organ-specific autoimmune disorder that is characterized by a variable combination of (i) chronic mucocutaneous candidiasis, (ii) polyendocrinopathy and/or hepatitis and (iii) dystrophy of the dental enamel and nails. We analyzed the AIRE (autoimmune regulator) gene in subjects who presented any symptom that has been associated with APECED, including candidiasis and autoimmune endocrinopathy. We observed that 83.3% of patients presented at least two of the three typical manifestations of APECED, while the remaining 16.7% of patients showed other signs of the disease. Analysis of the genetic diagnosis of these subjects revealed that a considerable delay occurs in the majority of patients between the appearance of symptoms and the diagnosis. Overall, the mean diagnostic delay in our patients was 10.2 years. These results suggest that molecular analysis of AIRE should be performed in patients with relapsing mucocutaneous candidiasis for early identification of APECED.
Keywords: Adolescent; Adult; Child; Child, Preschool; Heterozygote; Homozygote; Humans; Middle Aged; Mutation; Polyendocrinopathies, Autoimmune; Time Factors; Young Adult

Cryptic genetic gluten intolerance revealed by intestinal antitransglutaminase antibodies and response to gluten-free diet. - Not, Tarcisio; Ziberna, Fabiana; Vatta, Serena; Quaglia, Sara; Martelossi, Stefano; Villanacci, Vincenzo; Marzari, Roberto; Florian, Fiorella; Vecchiet, Monica; Sulic, Ana-Marija; Ferrara, Fortunato; Bradbury, Andrew; et al. (Gut, 2011)
BACKGROUND AND OBJECTIVE: Antitransglutaminase (anti-TG2) antibodies are synthesised in the intestine and their presence seems predictive of future coeliac disease (CD). This study investigates whether mucosal antibodies represent an early stage of gluten intolerance even in the absence of intestinal damage and serum anti-TG2 antibodies. METHODS: This study investigated 22 relatives of patients with CD genetically predisposed to gluten intolerance but negative for both serum anti-TG2 antibodies and intestinal abnormalities. Fifteen subjects were symptomatic and seven were asymptomatic. The presence of immunoglobulin A anti-TG2 antibodies in the intestine was studied by creating phage-antibody libraries against TG-2. The presence of intestinal anti-TG2 antibodies was compared with the serum concentration of the intestinal fatty acid-binding protein (I-FABP), a marker for early intestinal mucosal damage. The effects of a 12-month gluten-free diet on anti-TG2 antibody production and the subjects' clinical condition was monitored. Twelve subjects entered the study as controls. RESULTS: The intestinal mucosa appeared normal in 18/22; 4 had a slight increase in intraepithelial lymphocytes. Mucosal anti-TG2 antibodies were isolated in 15/22 subjects (68%); in particular symptomatic subjects were positive in 13/15 cases and asymptomatic subjects in 2/7 cases (p=0.01). No mucosal antibodies were selected from the controls' biopsies. There was significant correlation between the presence of intestinal anti-TG2 antibodies and positive concentrations of I-FABP (p=0.0008). After a gluten-free diet, 19/22 subjects underwent a second intestinal biopsy, which showed that anti-TG2 antibodies had disappeared in 12/15 (p=0.002), while I-FABP decreased significantly (p<0.0001). The diet resolved both extraintestinal and intestinal symptoms. CONCLUSIONS: A new form of genetic-dependent gluten intolerance has been described in which none of the usual diagnostic markers is present. Symptoms and intestinal anti-TG2 antibodies respond to a gluten free-diet. The detection of intestinal anti-TG2 antibodies by the phage-antibody libraries has an important diagnostic and therapeutic impact for the subjects with gluten-dependent intestinal or extraintestinal symptoms. Clinical trial number NCT00677495.
Keywords: Adolescent; Adult; Antibodies, Anti-Idiotypic; Asymptomatic Diseases; Celiac Disease; Child; Child, Preschool; Diet, Gluten-Free; Fatty Acid-Binding Proteins; Female; Genetic Predisposition to Disease; GTP-Binding Proteins; Health Status; Humans; Intestinal Mucosa; Male; Middle Aged; Peptide Library; Transglutaminases; Young Adult

Daily practice of mechanical ventilation in Italian pediatric intensive care units: a prospective survey. - Wolfler, Andrea; Calderoni, Edoardo; Ottonello, Giancarlo; Conti, Giorgio; Baroncini, Simonetta; Santuz, Pierantonio; Vitale, Pasquale; Salvo, Ida (Pediatr Crit Care Med, 2011)
OBJECTIVES: To assess how children requiring endotracheal intubation are mechanically ventilated in Italian pediatric intensive care units (PICUs). DESIGN: A prospective, national, observational, multicenter, 6-month study. SETTING: Eighteen medical-surgical PICUs. PATIENTS: A total of 1943 consecutive children, aged 0-16 yrs, admitted between November 1, 2006 and April 30, 2007. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Data on cause of respiratory failure, length of mechanical ventilation (MV), mode of ventilation, use of specific interventions were recorded for all children requiring endotracheal intubation for >24 hrs. Children were stratified for age, type of patient, and cause of respiratory failure. A total of 956 (49.2%) patients required MV via an endotracheal tube; 673 (34.6%) were ventilated for >24 hrs. The median length of MV was 4.5 days for all patients. If postoperative patients were excluded, the median time was 5 days. Bronchiolitis (6.7%), pneumonia (6.7%), and upper airway obstruction (5.3%) were the most frequent causes of acute respiratory failure, and altered mental status (9.2%) was the most frequent reason for MV. The overall mortality was 6.7% with highest rates for heart disease (nonoperative), sepsis, and acute respiratory distress syndrome (26.1%, 22.2%, and 16.7% respectively). Length of stay, associated chronic disease, severity score on admission, and PICU mortality were significantly higher in children who received MV (p < .05) than in children who did not. Controlled MV and pressure support ventilation + synchronized intermittent mandatory ventilation were the most frequently used modes of ventilatory assistance during PICU stay. CONCLUSIONS: Mechanical ventilation is frequently used in Italian PICUs with almost one child of two requiring endotracheal intubation. Children treated with MV represent a more severe category of patients than children who are breathing spontaneously. Describing the standard care and how MV is performed in children can be useful for future clinical studies.
Keywords: Adolescent; Child; Child, Preschool; Clinical Protocols; Female; Humans; Infant; Infant, Newborn; Intensive Care Units, Pediatric; Intubation, Intratracheal; Italy; Male; Prospective Studies; Respiration, Artificial; Respiratory Insufficiency

Dasatinib plus Nutlin-3 shows synergistic antileukemic activity in both p53 wild-type and p53 mutated B chronic lymphocytic leukemias by inhibiting the Akt pathway. - Zauli, Giorgio; Voltan, Rebecca; Bosco, Raffaella; Melloni, Elisabetta; Marmiroli, Sandra; Rigolin, Gian Matteo; Cuneo, Antonio; Secchiero, Paola (Clin Cancer Res, 2011)
PURPOSE: To analyze the effect of the combination of Dasatinib, a multikinase inhibitor, plus Nutlin-3, a nongenotoxic activator of the p53 pathway, in primary B chronic lymphocytic leukemia (B-CLL) patient samples and B leukemic cell line models. EXPERIMENTAL DESIGN: The induction of cytotoxicity was evaluated in both primary B-CLL cell samples (n = 20) and in p53(wild-type) (EHEB, JVM-2) and p53(deleted/mutated) (MEC-2, BJAB) B leukemic cell lines. The role of Akt in modulating leukemic cell survival/apoptosis in response to Dasatinib or Dasatinib + Nutlin-3 was documented by functional experiments carried out using specific pharmacological inhibitors and by overexpression of membrane-targeted constitutively active form of Akt. RESULTS: The combination of Dasatinib + Nutlin-3 exhibited a synergistic cytotoxicity in the majority (19 out of 20) of B-CLL samples, including patients carrying 17p- (n = 4), and in both p53(wild-type) and p53(deleted/mutated) B leukemic cell lines. At the molecular level, Dasatinib significantly counteracted the Nutlin-3-mediated induction of the p53 transcriptional targets MDM2 and p21 observed in p53(wild-type) leukemic cells. Conversely, Nutlin-3 did not interfere with the ability of Dasatinib to decrease the phosphorylation levels of ERK1/2, p38/MAPK, and Akt in both p53(wild-type) and p53(deleted/mutated) B leukemic cell lines. A critical role of Akt downregulation in mediating the antileukemic activity of Dasatinib and Dasatinib + Nutlin-3 was demonstrated in experiments carried out by specifically modulating the Akt pathway. CONCLUSIONS: These findings suggest that Dasatinib + Nutlin-3 might represent an innovative therapeutic combination for both p53(wild-type) and p53(deleted/mutated) B-CLL.
Keywords: Antineoplastic Agents; Apoptosis; Cell Line, Tumor; Cell Survival; Down-Regulation; Drug Synergism; Humans; Imidazoles; Leukemia, Lymphocytic, Chronic, B-Cell; Mutation; Piperazines; Protein Kinase Inhibitors; Protein Kinases; Proto-Oncogene Proteins c-akt; Pyrimidines; Thiazoles; Transcription, Genetic; Tumor Suppressor Protein p53

Decreased levels of soluble TNF-related apoptosis-inducing ligand (TRAIL) in the conjunctival sac fluid of patients with diabetes affected by proliferative retinopathy. - Secchiero, P; Perri, P; Melloni, E; Martini, A; Lamberti, G; Sebastiani, A; Zauli, G (Diabet Med, 2011)
Keywords: Apoptosis Regulatory Proteins; Body Fluids; Conjunctiva; Diabetic Retinopathy; Female; Humans; Male; Middle Aged; Receptors, TNF-Related Apoptosis-Inducing Ligand; TNF-Related Apoptosis-Inducing Ligand

Epidemiological and molecular assessment of a measles outbreak in a highly vaccinated population of northeast Italy. - D'Agaro, P; Molin, G Dal; Gallo, T; Rossi, T; Santon, D; Busetti, M; Comar, M; Campello, C (Epidemiol Infect, 2011)
Two distinct measles outbreaks, unrelated from the epidemiological point of view but caused by genetically related strains, occurred in the Friuli Venezia Giulia region of northeastern Italy. Forty-two cases were reported during the period April-May 2008. In the first outbreak the index case was a teacher who introduced the virus into the Pordenone area, involving eight adolescents and young adults. The other concomitant outbreak occurred in the city of Trieste with 33 cases. The containment of the epidemics can be explained by the high MMR vaccine coverage in an area where the first dose was delivered to 93·4% and the second dose to 88·3% of the target children. Phylogenetic analysis of 14 measles virus strains showed that they belonged to a unique D4 genotype indistinguishable from the MVs/Enfield.GBR/14.07 strain, probably introduced from areas (i.e. Piedmont and Germany) where this genotype was present or had recently caused a large epidemic.
Keywords: Adolescent; Adult; Chi-Square Distribution; Child; Child, Preschool; Community-Acquired Infections; Disease Outbreaks; Female; Humans; Immunization Schedule; Infant; Italy; Male; Measles; Measles Vaccine; Measles virus; Middle Aged; Molecular Epidemiology; Phylogeny

Frequency of HLA B*5701 allele carriers in abacavir treated-HIV infected patients and controls from northeastern Brazil. - Crovella, Sergio; Biller, Lara; Santos, Sergio; Salustiano, Ana; Brandão, Lucas; Guimarães, Rafael; Segat, Ludovica; Lima Filho, Jose Luiz de; Arraes, Luiz Claudio (Clinics (Sao Paulo), 2011)
Keywords: Adolescent; Adult; Anti-HIV Agents; Brazil; Case-Control Studies; Dideoxynucleosides; Drug Hypersensitivity; Female; Gene Frequency; Genotype; HIV Infections; HLA-B Antigens; Humans; Male; Middle Aged; Real-Time Polymerase Chain Reaction; Young Adult

Functional type 1 regulatory T cells develop regardless of FOXP3 mutations in patients with IPEX syndrome. - Passerini, Laura; Di Nunzio, Sara; Gregori, Silvia; Gambineri, Eleonora; Cecconi, Massimiliano; Seidel, Markus G; Cazzola, Giantonio; Perroni, Lucia; Tommasini, Alberto; Vignola, Silvia; Guidi, Luisa; Roncarolo, Maria G; et al. (Eur J Immunol, 2011)
Mutations of forkhead box p3 (FOXP3), the master gene for naturally occurring regulatory T cells (nTregs), are responsible for the impaired function of nTregs, resulting in an autoimmune disease known as the immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome. The relevance of other peripheral tolerance mechanisms, such as the presence and function of type 1 regulatory T (Tr1) cells, the major adaptive IL-10-producing Treg subset, in patients with IPEX syndrome remains to be clarified. FOXP3(mutated) Tr1-polarized cells, differentiated in vitro from CD4(+) T cells of four IPEX patients, were enriched in IL-10(+) IL-4(-) IFN-γ(+) T cells, a cytokine production profile specific for Tr1 cells, and expressed low levels of FOXP3 and high levels of Granzyme-B. IPEX Tr1 cells were hypoproliferative and suppressive, thus indicating that FOXP3 mutations did not impair their function. Furthermore, we isolated Tr1 cell clones from the peripheral blood of one FOXP3(null) patient, demonstrating that Tr1 cells are present in vivo and they can be expanded in vitro in the absence of WT FOXP3. Overall, our results (i) show that functional Tr1 cells differentiate independently of FOXP3, (ii) confirm that human Tr1 and nTregs are distinct T-cell lineages, and (iii) suggest that under favorable conditions Tr1 cells could exert regulatory functions in IPEX patients.
Keywords: Cell Differentiation; Cell Lineage; Cells, Cultured; Enteritis; Forkhead Transcription Factors; Genetic Diseases, X-Linked; Humans; Immunity, Innate; Interleukin-2 Receptor alpha Subunit; Mutation; Polyendocrinopathies, Autoimmune; Syndrome; T-Lymphocytes, Regulatory

Genetic predictors of glucocorticoid response in pediatric patients with inflammatory bowel diseases. - De Iudicibus, Sara; Stocco, Gabriele; Martelossi, Stefano; Londero, Margherita; Ebner, Egle; Pontillo, Alessandra; Lionetti, Paolo; Barabino, Arrigo; Bartoli, Fiora; Ventura, Alessandro; Decorti, Giuliana (J Clin Gastroenterol, 2011)
BACKGROUND: Glucocorticoids (GCs) are used in moderate-to-severe inflammatory bowel diseases (IBD) but their effect is often unpredictable. AIM: To determine the influence of 4 polymorphisms in the GC receptor [nuclear receptor subfamily 3, group C, member 1 (NR3C1)], interleukin-1β (IL-1β), and NACHT leucine-rich-repeat protein 1 (NALP1) genes, on the clinical response to steroids in pediatric patients with IBD. METHODS: One hundred fifty-four young IBD patients treated with GCs for at least 30 days and with a minimum follow-up of 1 year were genotyped. The polymorphisms considered are the BclI in the NR3C1 gene, C-511T in IL-1β gene, and Leu155His and rs2670660/C in NALP1 gene. Patients were grouped as responder, dependant, and resistant to GCs. The relation between GC response and the genetic polymorphisms considered was examined using univariate, multivariate, and Classification and Regression Tree (CART) analysis. RESULTS: Univariate analysis showed that BclI polymorphism was more frequent in responders compared with dependant patients (P=0.03) and with the combined dependant and resistant groups (P=0.02). Moreover, the NALP1 Leu155His polymorphism was less frequent in the GC responsive group compared with resistant (P=0.0059) and nonresponder (P=0.02) groups. Multivariate analysis comparing responders and nonresponders confirmed an association between BclI mutated genotype and steroid response (P=0.030), and between NALP1 Leu155His mutant variant and nonresponders (P=0.033). An association between steroid response and male sex was also observed (P=0.034). In addition, Leu155His mutated genotype was associated with steroid resistance (P=0.034). Two CART analyses supported these findings by showing that BclI and Leu155His polymorphisms had the greatest effect on steroid response (permutation P value=0.046). The second CART analysis also identified age of disease onset and male sex as important variables affecting response. CONCLUSIONS: These results confirm that genetic and demographic factors may affect the response to GCs in young patients with IBD and strengthen the importance of studying high-order interactions for predicting response.
Keywords: Adolescent; Child; Drug Resistance; Female; Follow-Up Studies; Genotype; Glucocorticoids; Humans; Inflammatory Bowel Diseases; Male; Multivariate Analysis; Polymorphism, Genetic; Receptors, Glucocorticoid; Regression Analysis; Retrospective Studies; Sex Factors; Treatment Outcome

A genome-wide approach identifies that the aspartate metabolism pathway contributes to asparaginase sensitivity. - Chen, S-H; Yang, W; Fan, Y; Stocco, G; Crews, K R; Yang, J J; Paugh, S W; Pui, C-H; Evans, W E; Relling, M V (Leukemia, 2011)
Asparaginase is an important component for treatment of childhood acute lymphoblastic leukemia (ALL). The basis for interindividual differences in asparaginase sensitivity remains unclear. To comprehensively identify genetic variants important in the cytotoxicity of asparaginase, we used a genome-wide association approach using the HapMap lymphoblastoid cell lines (87 CEU trio members) and 54 primary ALL leukemic blast samples at diagnosis. Asparaginase sensitivity was assessed as the drug concentration necessary to inhibit 50% of growth (inhibitory concentration (IC)(50)). In CEU lines, we tested 2,390,203 single-nucleotide polymorphism (SNP) genotypes at the individual SNP (P<0.001) and gene level (P<0.05), and identified 329 SNPs representing 94 genes that were associated with asparaginase IC(50). The aspartate metabolism pathway was the most overrepresented among 199 pathways evaluated (P=8.1 × 10(-3)), with primary involvement of adenylosuccinate lyase and aspartyl-tRNA synthetase genes. We validated that SNPs in the aspartate metabolism pathway were also associated with asparaginase sensitivity in primary ALL leukemic blast samples (P=5.5 × 10(-5)). Our genome-wide interrogation of CEU cell lines and primary ALL blasts revealed that inherited genomic interindividual variation in a plausible candidate pathway can contribute to asparaginase sensitivity.
Keywords: Antineoplastic Agents; Asparaginase; Aspartic Acid; Cell Line; Genome-Wide Association Study; Humans; Multivariate Analysis; Polymorphism, Single Nucleotide; Precursor Cell Lymphoblastic Leukemia-Lymphoma

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

Hearing function and thresholds: a genome-wide association study in European isolated populations identifies new loci and pathways. - Girotto, Giorgia; Pirastu, Nicola; Sorice, Rossella; Biino, Ginevra; Campbell, Harry; d'Adamo, Adamo P; Hastie, Nicholas D; Nutile, Teresa; Polasek, Ozren; Portas, Laura; Rudan, Igor; Ulivi, Sheila; et al. (J Med Genet, 2011)
BACKGROUND: Hearing is a complex trait, but until now only a few genes are known to contribute to variability of this process. In order to discover genes and pathways that underlie auditory function, a genome-wide association study was carried out within the International Consortium G-EAR. METHODS: Meta-analysis of genome-wide association study's data from six isolated populations of European ancestry for an overall number of 3417 individuals. RESULTS: Eight suggestive significant loci (p<10(-7)) were detected with a series of genes expressed within the inner ear such as: DCLK1, PTPRD, GRM8, CMIP. Additional biological candidates marked by a single nucleotide polymorphism (SNP) with a suggestive association (p<10(-6)) were identified, as well as loci encompassing 'gene desert regions'-genes of unknown function or genes whose function has not be linked to hearing so far. Some of these new loci map to already known hereditary hearing loss loci whose genes still need to be identified. Data have also been used to construct a highly significant 'in silico' pathway for hearing function characterised by a network of 49 genes, 34 of which are certainly expressed in the ear. CONCLUSION: These results provide new insights into the molecular basis of hearing function and may suggest new targets for hearing impairment treatment and prevention.
Keywords: Adaptor Proteins, Signal Transducing; Animals; Auditory Threshold; Carrier Proteins; Databases, Genetic; Europe; European Continental Ancestry Group; Female; Founder Effect; Genetic Linkage; Genome-Wide Association Study; Hearing; Hearing Loss; Humans; Intracellular Signaling Peptides and Proteins; Male; Mice; Phenotype; Polymorphism, Single Nucleotide; Protein-Serine-Threonine Kinases; Receptor-Like Protein Tyrosine Phosphatases, Class 2; Receptors, Metabotropic Glutamate

High incidence of NLRP3 somatic mosaicism in patients with chronic infantile neurologic, cutaneous, articular syndrome: results of an International Multicenter Collaborative Study. - Tanaka, Naoko; Izawa, Kazushi; Saito, Megumu K; Sakuma, Mio; Oshima, Koichi; Ohara, Osamu; Nishikomori, Ryuta; Morimoto, Takeshi; Kambe, Naotomo; Goldbach-Mansky, Raphaela; Aksentijevich, Ivona; de Saint Basile, Geneviève; et al. (Arthritis Rheum, 2011)
OBJECTIVE: Chronic infantile neurologic, cutaneous, articular (CINCA) syndrome, also known as neonatal-onset multisystem inflammatory disease (NOMID), is a dominantly inherited systemic autoinflammatory disease. Although heterozygous germline gain-of-function NLRP3 mutations are a known cause of this disease, conventional genetic analyses fail to detect disease-causing mutations in ∼40% of patients. Since somatic NLRP3 mosaicism has been detected in several mutation-negative NOMID/CINCA syndrome patients, we undertook this study to determine the precise contribution of somatic NLRP3 mosaicism to the etiology of NOMID/CINCA syndrome. METHODS: An international case-control study was performed to detect somatic NLRP3 mosaicism in NOMID/CINCA syndrome patients who had shown no mutation during conventional sequencing. Subcloning and sequencing of NLRP3 was performed in these mutation-negative NOMID/CINCA syndrome patients and their healthy relatives. Clinical features were analyzed to identify potential genotype-phenotype associations. RESULTS: Somatic NLRP3 mosaicism was identified in 18 of the 26 patients (69.2%). Estimates of the level of mosaicism ranged from 4.2% to 35.8% (mean ± SD 12.1 ± 7.9%). Mosaicism was not detected in any of the 19 healthy relatives (18 of 26 patients versus 0 of 19 relatives; P < 0.0001). In vitro functional assays indicated that the detected somatic NLRP3 mutations had disease-causing functional effects. No differences in NLRP3 mosaicism were detected between different cell lineages. Among nondescript clinical features, a lower incidence of mental retardation was noted in patients with somatic mosaicism. Genotype-matched comparison confirmed that patients with somatic NLRP3 mosaicism presented with milder neurologic symptoms. CONCLUSION: Somatic NLRP3 mutations were identified in 69.2% of patients with mutation-negative NOMID/CINCA syndrome. This indicates that somatic NLRP3 mosaicism is a major cause of NOMID/CINCA syndrome.
Keywords: Adolescent; Adult; Carrier Proteins; Case-Control Studies; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Female; Genetic Association Studies; Humans; Infant; Male; Mosaicism

High-throughput genotyping robot-assisted method for mutation detection in patients with hypertrophic cardiomyopathy. - Bortot, Barbara; Athanasakis, Emmanouil; Brun, Francesca; Rizzotti, Diego; Mestroni, Luisa; Sinagra, Gianfranco; Severini, Giovanni Maria (Diagn Mol Pathol, 2011)
Hypertrophic cardiomyopathy (HCM) is the most frequent autosomal dominant genetic heart muscle disease and the most common cause of sudden cardiac death in young people (under 30 y of age), who are often unaware of their underlying condition. Genetic screening is now considered a fundamental tool for clinical management of HCM families. However, the high genetic heterogeneity of HCM makes genetic screening very expensive. Here, we propose a new high-throughput genotyping method based on a HCM 96-well sequencing plate for the analysis of 8 of the most frequent HCM-causing sarcomeric genes by automating several processes required for direct sequencing, using a commercially available robotic systems and routinely used instruments. To assess the efficiency of the robot-assisted method, we have analyzed the entire coding sequence and flanking intronic sequences of the 8 sarcomeric genes in samples from 18 patients affected by HCM and their relatives, which revealed 9 different mutations, 3 of which were novel. The automated, robot-assisted assembling of polymerase chain reaction, purification of polymerase chain reaction products, and assembly of sequencing reactions resulted in a substantial saving of time, reagent costs, and reduction of human errors, and can therefore be proposed as a primary strategy for mutation identification in HCM genetic screening in many medical genetic laboratories.
Keywords: Cardiomyopathy, Hypertrophic; DNA Mutational Analysis; Genetic Predisposition to Disease; Genetic Testing; Genotyping Techniques; High-Throughput Nucleotide Sequencing; Humans; Muscle Proteins; Mutation; Robotics

HLA-G 14 bp deletion/insertion polymorphism in celiac disease. - Fabris, Annalisa; Segat, Ludovica; Catamo, Eulalia; Morgutti, Marcello; Vendramin, Anna; Crovella, Sergio (Am J Gastroenterol, 2011)
OBJECTIVES: Nonclassical major histocompatibility class I HLA-G antigen is a tolerogenic molecule that inhibits lytic activity of natural killer (NK) cells and cytotoxic T lymphocytes. Because of its immunomodulatory and tolerogenic properties, HLA-G molecules may have a role in celiac disease (CD). We analyzed the HLA-G 14 bp deletion/insertion polymorphism, known to have a functional effect on mRNA stability, in a group of 522 CD patients, stratified for the presence of HLA-DQ2 genotype, and 400 healthy individuals to evaluate the possible effect of the polymorphism on the risk to develop the disease. METHODS: HLA-G 14 bp deletion/insertion polymorphism (rs1704) was detected by polymerase chain reaction and double-checked by direct sequencing. RESULTS: The 14 bp inserted (I) allele and the homozygous I/I genotype were significantly more frequent in CD patients than in healthy controls. The presence of I allele was associated with an increased risk of CD (OR 1.35) and the effect of I allele was consistent with a recessive genetic model (P<0.001). CONCLUSIONS: Our results also indicate that the effect of the HLA-G D/I polymorphism is restricted for HLA-DQ2, and not simply due to the presence of linkage disequilibrium with the major known risk factor; moreover we found that the presence of the I allele confers an increased risk of CD in addition to the risk conferred by HLA-DQ2 alone and that subjects that carry both DQ2 and HLA-G I alleles have an increased risk of CD than subjects that carry DQ2 but not the I allele.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alleles; Case-Control Studies; Celiac Disease; Child; Child, Preschool; Confidence Intervals; Female; Genetic Predisposition to Disease; Genotype; Histocompatibility Antigens Class I; HLA Antigens; HLA-DQ Antigens; HLA-G Antigens; Humans; Male; Middle Aged; Mutagenesis, Insertional; Odds Ratio; Polymerase Chain Reaction; Polymorphism, Genetic; Reference Values; RNA Stability; Sequence Deletion; Young Adult

Long-term clinical profile of children with the low-penetrance R92Q mutation of the TNFRSF1A gene. - Pelagatti, M A; Meini, A; Caorsi, R; Cattalini, M; Federici, S; Zulian, F; Calcagno, G; Tommasini, A; Bossi, G; Sormani, M P; Caroli, F; Plebani, A; et al. (Arthritis Rheum, 2011)
OBJECTIVE: To analyze the long-term impact of the R92Q mutation of TNFRSF1A in children with periodic fever, in comparison with children with tumor necrosis factor receptor-associated periodic syndrome (TRAPS) with TNFRSF1A structural mutations and children with periodic fever of unknown origin fulfilling the criteria for periodic fever, aphthosis, pharyngitis, and adenitis syndrome (PFAPA). METHODS: The extracellular region of TNFRSF1A was analyzed in 720 consecutive children with periodic fever, using denaturing high-performance liquid chromatography and DNA sequencing. Followup data on 11 pediatric patients with TNFRSF1A structural mutations (cysteine or T50M), 23 pediatric patients with an R92Q substitution, and 64 pediatric patients with PFAPA were collected during routine clinic visits. The 50-item Child Health Questionnaire was used to assess health-related quality of life (HRQOL). RESULTS: The frequency of typical TRAPS-related clinical manifestations was significantly lower and the impact of the disease on HRQOL was significantly reduced in patients with the R92Q mutation compared with TRAPS patients carrying structural mutations of TNFRSF1A. Followup data on 11 TRAPS patients with TNFRSF1A structural mutations (mean followup 7.9 years), 16 patients with theR92Q substitution (mean followup 7.3 years), and 64 patients with PFAPA (mean followup 5.2 years) were available. Patients with R92Q mutations and patients with PFAPA displayed a higher rate of self-resolution or amelioration of the fever episodes than did TRAPS patients with structural mutations. CONCLUSION: Although some cases may progress to a more chronic disease course, the majority of children with an R92Q mutation of the TNFRSFA1 gene show a milder disease course than that in children with TNFRSFA1 structural mutations and have a high rate of spontaneous resolution and amelioration of the recurrent fever episodes.
Keywords: Adolescent; Antirheumatic Agents; Biological Therapy; Child; Child, Preschool; Familial Mediterranean Fever; Female; Fever; Follow-Up Studies; Genotype; Health Surveys; Humans; Infant; Interleukin 1 Receptor Antagonist Protein; Longitudinal Studies; Lymphadenitis; Male; Mutation; Pharyngitis; Quality of Life; Receptors, Tumor Necrosis Factor; Receptors, Tumor Necrosis Factor, Type I; Recurrence; Retrospective Studies; Steroids; Syndrome

Mannose binding lectin gene (MBL2) functional polymorphisms are associated with systemic lupus erythematosus in southern Brazilians. - Sandrin-Garcia, Paula; Brandão, Lucas André Cavalcanti; Coelho, Antônio Victor Campos; Guimarães, Rafael Lima; Pancoto, João Alexandre Trés; Segat, Ludovica; Donadi, Eduardo Antônio; de Lima-Filho, José Luiz; Crovella, Sergio (Hum Immunol, 2011)
Susceptibility to systemic lupus erythematosus (SLE) has been associated with immunologic, environmental, and genetic factors. To uncover a possible association between MBL2 gene polymorphisms and SLE, we analyzed functional polymorphisms in the promoter and first exon of the MBL2 gene in 134 Brazilian SLE patients and 101 healthy controls. Genotype and allele frequencies of MBL2 A/O polymorphism were significantly different between patients and controls, and the O allele was associated with an increased risk of SLE. An association between low mannose binding lectin (MBL) producer combined genotypes and increased risk for SLE was also reported. Furthermore, when stratifying SLE patients according to clinical and laboratory data, an association between the A/O genotype and nephritic disorders and between the X/Y genotype and antiphospholipid syndrome was evident. Combined genotypes responsible for low MBL production were more frequently observed in SLE patients with nephritis. Our results indicate MBL2 polymorphisms as possible risk factors for SLE development and disease-related clinical manifestations.
Keywords: Adolescent; Adult; Aged; Brazil; DNA Mutational Analysis; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Humans; Lupus Erythematosus, Systemic; Male; Mannose-Binding Lectin; Middle Aged; Polymorphism, Genetic; Population Groups; Promoter Regions, Genetic

Marriage and parenthood among childhood cancer survivors: a report from the Italian AIEOP Off-Therapy Registry. - Pivetta, Emanuele; Maule, Milena M; Pisani, Paola; Zugna, Daniela; Haupt, Riccardo; Jankovic, Momcilo; Aricò, Maurizio; Casale, Fiorina; Clerico, Anna; Cordero di Montezemolo, Luca; Kiren, Valentina; Locatelli, Franco; et al. (Haematologica, 2011)
BACKGROUND: The aim of this study was to describe the patterns of marriage and parenthood in a cohort of childhood cancer survivors included in the Off-Therapy Registry maintained by the Italian Association of Pediatric Hematology and Oncology. DESIGN AND METHODS: We analyzed a cohort of 6,044 patients diagnosed with cancer between 1960 and 1998, while aged 0 to 14 years and who were 18 years old or older by December 2003. They were followed up through the regional vital statistics registers until death or the end of follow up (October 30, 2006), whichever occurred first, and their marital status and date of birth of their children were recorded. The cumulative probabilities of being married and having a first child were computed by gender and compared by tumor type within the cohort. Marriage and fertility rates (the latter defined as the number of live births per woman-year) were compared with those of the Italian population of the same age, gender, area of residence and calendar period by means of the observed to expected (O/E) ratios. RESULTS: During the follow-up period, 4,633 (77%) subjects had not married. The marriage O/E ratios were 0.56 (95% CI: 0.51-0.61) and 0.70 (95% CI: 0.65-0.76) among men and women, respectively. Overall, 263 men had 367 liveborn children, and 473 women had 697 liveborn children. The female fertility O/E ratio was 0.57 (95% CI: 0.53-0.62) overall, and 1.08 (95% CI: 0.99-1.17) when analyses were restricted to married/cohabiting women CONCLUSIONS: Childhood cancer survivors are less likely to marry and to have children than the general population, confirming the life-long impact of their previous disease on their social behavior and choices. The inclusion of counseling in the strategies of management and long-term surveillance of childhood cancer patients could be beneficial to survivors as they approach adulthood.
Keywords: Adult; Child; Child, Preschool; Cohort Studies; Female; Follow-Up Studies; Hematologic Neoplasms; Humans; Infant; Infant, Newborn; Italy; Male; Marriage; Middle Aged; Parents; Registries; Survivors

MBL1 gene in nonhuman primates. - Segat, Ludovica; Crovella, Sergio (Hum Immunol, 2011)
With the aim of investigating the evolution of MBL1P1 (MBL1) gene, we analyzed the MBL1 coding region sequences in several specimens of two species of great apes, two species of Hylobatidae, four species of Cercopithecidae, and one Platyrrhine species, and in human beings. An indication for a progressive silencing of the molecule has been found. We found a ∼300 bp insertion in the first intron of MBL1 in the Cercopithecidae that could explain the different splicing between primates species and possibly why Macaca mulatta is able to produce a complete protein, whereas in human beings the protein product is truncated. Based on our genetic findings, we could speculate that all the Cercopithecidae (presenting the 300-bp insertion) may express MBL1 mature protein like the M mulatta, whereas the lesser and great apes, which lack this insertion as do human beings, may have only the truncated pseudogene.
Keywords: Animals; Base Sequence; Evolution, Molecular; Gene Silencing; Genome; Humans; Mannose-Binding Lectin; Molecular Sequence Data; Multigene Family; Phylogeny; Polymorphism, Genetic; Primates; Pseudogenes; Sequence Alignment; Sequence Analysis, DNA; Sequence Deletion; Species Specificity

MBL2 polymorphisms and the choice of controls for association studies: just another story? - Segat, L; Crovella, S (Int J Immunogenet, 2011)
Keywords: Antibodies; Brazil; Control Groups; Gene Frequency; Genetic Association Studies; Genetic Heterogeneity; Genetic Predisposition to Disease; Hepatitis C; Humans; Mannose-Binding Lectin; Polymorphism, Genetic; Thyroid Gland

miR-34a induces the downregulation of both E2F1 and B-Myb oncogenes in leukemic cells. - Zauli, Giorgio; Voltan, Rebecca; di Iasio, Maria Grazia; Bosco, Raffaella; Melloni, Elisabetta; Sana, Maria Elena; Secchiero, Paola (Clin Cancer Res, 2011)
PURPOSE: To elucidate new molecular mechanisms able to downregulate the mRNA levels of key oncogenes, such as B-Myb and E2F1, in a therapeutic perspective. EXPERIMENTAL DESIGN: B-Myb and E2F1 mRNA levels were evaluated in primary B chronic lymphocytic leukemia (B-CLL, n = 10) and acute myeloid leukemia (AML, n = 5) patient cells, in a variety of p53(wild-type) and p53(mutated/deleted) leukemic cell lines, as well as in primary endothelial cells and fibroblasts. Knockdown experiments with siRNA for p53 and E2F1 and overexpression experiments with miR34a were conducted to elucidate the role of these pathways in promoting B-Myb downregulation. RESULTS: In vitro exposure to Nutlin-3, a nongenotoxic activator of p53, variably downregulated the expression of B-Myb in primary leukemic cells and in p53(wild-type) myeloid (OCI, MOLM) and lymphoblastoid (SKW6.4, EHEB) but not in p53(mutated) (NB4, BJAB, MAVER) or p53(deleted) (HL-60) leukemic cell lines. The transcriptional repression of B-Myb was also observed in primary normal endothelial cells and fibroblasts. B-Myb downregulation played a critical role in the cell-cycle block in G(1) phase induced by Nutlin-3, as shown by transfection experiments with specific siRNA. Moreover, we have provided experimental evidence suggesting that miR-34a is a central mediator in the repression of B-Myb both directly and through E2F1. CONCLUSIONS: Owing to the role of B-Myb and E2F1 transcription factors in controlling cell-cycle progression of leukemic cells, the downregulation of these oncogenes by miR-34a suggests the usefulness of therapeutic approaches aimed to modulate the levels of miR-34a.
Keywords: Base Sequence; Cell Cycle Proteins; Cell Line, Tumor; Cells, Cultured; Down-Regulation; E2F1 Transcription Factor; Gene Expression Regulation, Leukemic; HCT116 Cells; HL-60 Cells; Humans; Imidazoles; Leukemia; MicroRNAs; Models, Biological; Oncogenes; Piperazines; Sequence Homology, Nucleic Acid; Trans-Activators; Transfection

Molecular targets for selective killing of TRAIL-resistant leukemic cells. - Zauli, Giorgio; Bosco, Raffaella; Secchiero, Paola (Expert Opin Ther Targets, 2011)
INTRODUCTION: TNF-related apoptosis-inducing ligand (TRAIL) is a member of the TNF family of cytokines, and shows promising therapeutic activity against solid tumors and lymphomas, in a variety of Phase I and II clinical trials. In contrast, primary leukemias have shown poor susceptibility to TRAIL-mediated cytotoxicity, suggesting the need for sensitizing TRAIL-resistant leukemic cells, by combining soluble recombinant TRAIL either with chemotherapeutic drugs, or with targeted small molecules. AREAS COVERED: This review discusses potential therapeutic applications of combinations able to restore the sensitivity of leukemic cells to either recombinant TRAIL or anti-TRAIL-receptor agonistic antibodies for the treatment of hematological malignancies. EXPERT OPINION: Up-to-date knowledge of the most innovative anti-leukemic therapies including functional screening of specific-sensitizers, enhancing TRAIL-mediated cytotoxicity. Strategies aimed to enhance TRAIL-mediated apoptosis, include the combination of novel sensitizers, functionally identified from libraries of pharmaceutically active, synthetic or naturally derived compounds. Other approaches aim to employ the administration of stem cells engineered to express TRAIL, in the leukemic stem cell niche, and promise to be a successful treatment with reduced specific toxicity.
Keywords: Humans; Leukemia; TNF-Related Apoptosis-Inducing Ligand

Multiple loci are associated with white blood cell phenotypes. - Nalls, Michael A; Couper, David J; Tanaka, Toshiko; van Rooij, Frank J A; Chen, Ming-Huei; Smith, Albert V; Toniolo, Daniela; Zakai, Neil A; Yang, Qiong; Greinacher, Andreas; Wood, Andrew R; Garcia, Melissa; et al. (PLoS Genet, 2011)
White blood cell (WBC) count is a common clinical measure from complete blood count assays, and it varies widely among healthy individuals. Total WBC count and its constituent subtypes have been shown to be moderately heritable, with the heritability estimates varying across cell types. We studied 19,509 subjects from seven cohorts in a discovery analysis, and 11,823 subjects from ten cohorts for replication analyses, to determine genetic factors influencing variability within the normal hematological range for total WBC count and five WBC subtype measures. Cohort specific data was supplied by the CHARGE, HeamGen, and INGI consortia, as well as independent collaborative studies. We identified and replicated ten associations with total WBC count and five WBC subtypes at seven different genomic loci (total WBC count-6p21 in the HLA region, 17q21 near ORMDL3, and CSF3; neutrophil count-17q21; basophil count- 3p21 near RPN1 and C3orf27; lymphocyte count-6p21, 19p13 at EPS15L1; monocyte count-2q31 at ITGA4, 3q21, 8q24 an intergenic region, 9q31 near EDG2), including three previously reported associations and seven novel associations. To investigate functional relationships among variants contributing to variability in the six WBC traits, we utilized gene expression- and pathways-based analyses. We implemented gene-clustering algorithms to evaluate functional connectivity among implicated loci and showed functional relationships across cell types. Gene expression data from whole blood was utilized to show that significant biological consequences can be extracted from our genome-wide analyses, with effect estimates for significant loci from the meta-analyses being highly corellated with the proximal gene expression. In addition, collaborative efforts between the groups contributing to this study and related studies conducted by the COGENT and RIKEN groups allowed for the examination of effect homogeneity for genome-wide significant associations across populations of diverse ancestral backgrounds.
Keywords: Genetic Loci; Genome-Wide Association Study; Humans; Leukocyte Count; Leukocytes; Molecular Epidemiology; Multigene Family; Phenotype; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Mutations in ANKRD26 are responsible for a frequent form of inherited thrombocytopenia: analysis of 78 patients from 21 families. - Noris, Patrizia; Perrotta, Silverio; Seri, Marco; Pecci, Alessandro; Gnan, Chiara; Loffredo, Giuseppe; Pujol-Moix, Núria; Zecca, Marco; Scognamiglio, Francesca; De Rocco, Daniela; Punzo, Francesca; Melazzini, Federica; et al. (Blood, 2011)
Until recently, thrombocytopenia 2 (THC2) was considered an exceedingly rare form of autosomal dominant thrombocytopenia and only 2 families were known. However, we recently identified mutations in the 5'-untranslated region of the ANKRD26 gene in 9 THC2 families. Here we report on 12 additional pedigrees with ANKRD26 mutations, 6 of which are new. Because THC2 affected 21 of the 210 families in our database, it has to be considered one of the less rare forms of inherited thrombocytopenia. Analysis of all 21 families with ANKRD26 mutations identified to date revealed that thrombocytopenia and bleeding tendency were usually mild. Nearly all patients had no platelet macrocytosis, and this characteristic distinguishes THC2 from most other forms of inherited thrombocytopenia. In the majority of cases, platelets were deficient in glycoprotein Ia and α-granules, whereas in vitro platelet aggregation was normal. Bone marrow examination and serum thrombopoietin levels suggested that thrombocytopenia was derived from dysmegakaryopoiesis. Unexplained high values of hemoglobin and leukocytes were observed in a few cases. An unexpected finding that warrants further investigation was a high incidence of acute leukemia. Given the scarcity of distinctive characteristics, the ANKRD26-related thrombocytopenia has to be taken into consideration in the differential diagnosis of isolated thrombocytopenias.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Ankyrin Repeat; Child; Cohort Studies; Family; Female; Gene Frequency; Humans; Inheritance Patterns; Male; Middle Aged; Mutation; Pedigree; Thrombocytopenia; Transcription Factors; Young Adult

Mutations in the 5' UTR of ANKRD26, the ankirin repeat domain 26 gene, cause an autosomal-dominant form of inherited thrombocytopenia, THC2. - Pippucci, Tommaso; Savoia, Anna; Perrotta, Silverio; Pujol-Moix, Núria; Noris, Patrizia; Castegnaro, Giovanni; Pecci, Alessandro; Gnan, Chiara; Punzo, Francesca; Marconi, Caterina; Gherardi, Samuele; Loffredo, Giuseppe; et al. (Am J Hum Genet, 2011)
THC2, an autosomal-dominant thrombocytopenia described so far in only two families, has been ascribed to mutations in MASTL or ACBD5. Here, we show that ANKRD26, another gene within the THC2 locus, and neither MASTL nor ACBD5, is mutated in eight unrelated families. ANKRD26 was also found to be mutated in the family previously reported to have an ACBD5 mutation. We identified six different ANKRD26 mutations, which were clustered in a highly conserved 19 bp sequence located in the 5' untranslated region. Mutations were not detected in 500 controls and are absent from the 1000 Genomes database. Available data from an animal model and Dr. Watson's genome give evidence against haploinsufficiency as the pathogenetic mechanism for ANKRD26-mediated thrombocytopenia. The luciferase reporter assay suggests that these 5' UTR mutations might enhance ANKRD26 expression. ANKRD26 is the ancestor of a family of primate-specific genes termed POTE, which have been recently identified as a family of proapoptotic proteins. Dysregulation of apoptosis might therefore be the pathogenetic mechanism, as demonstrated for another thrombocytopenia, THC4. Further investigation is needed to provide evidence supporting this hypothesis.
Keywords: Ankyrin Repeat; Base Sequence; Chromosome Breakage; Chromosome Disorders; Conserved Sequence; Female; Genes, Dominant; Genetic Loci; Haploinsufficiency; Humans; Male; Molecular Sequence Data; Mutation; Pedigree; Thrombocytopenia

Mutations in TTC19 cause mitochondrial complex III deficiency and neurological impairment in humans and flies. - Ghezzi, Daniele; Arzuffi, Paola; Zordan, Mauro; Da Re, Caterina; Lamperti, Costanza; Benna, Clara; d'Adamo, Pio; Diodato, Daria; Costa, Rodolfo; Mariotti, Caterina; Uziel, Graziella; Smiderle, Cristina; et al. (Nat Genet, 2011)
Although mutations in CYTB (cytochrome b) or BCS1L have been reported in isolated defects of mitochondrial respiratory chain complex III (cIII), most cIII-defective individuals remain genetically undefined. We identified a homozygous nonsense mutation in the gene encoding tetratricopeptide 19 (TTC19) in individuals from two families affected by progressive encephalopathy associated with profound cIII deficiency and accumulation of cIII-specific assembly intermediates. We later found a second homozygous nonsense mutation in a fourth affected individual. We demonstrated that TTC19 is embedded in the inner mitochondrial membrane as part of two high-molecular-weight complexes, one of which coincides with cIII. We then showed a physical interaction between TTC19 and cIII by coimmunoprecipitation. We also investigated a Drosophila melanogaster knockout model for TTC19 that showed low fertility, adult-onset locomotor impairment and bang sensitivity, associated with cIII deficiency. TTC19 is a putative cIII assembly factor whose disruption is associated with severe neurological abnormalities in humans and flies.
Keywords: Adult; Animals; Brain; Codon, Nonsense; Drosophila melanogaster; Electron Transport Complex III; Female; Gene Knockdown Techniques; Humans; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Nervous System Diseases

Neonatal necrotizing tracheobronchitis. - Bua, Jenny; Trappan, Antonella; Demarini, Sergio; Grasso, Domenico; Schleef, Jurgen; Zennaro, Floriana (J Pediatr, 2011)
Keywords: Bronchitis; Bronchoscopy; High-Frequency Ventilation; Humans; Infant, Newborn; Male; Necrosis; Respiratory Insufficiency; Respiratory Mucosa; Tracheitis

Neuromotor deficits in developmental coordination disorder: evidence from a reach-to-grasp task. - Biancotto, Marina; Skabar, Aldo; Bulgheroni, Maria; Carrozzi, Marco; Zoia, Stefania (Res Dev Disabil, 2011)
Developmental coordination disorder (DCD) has been classified as a specific learning disability, nonetheless the underlying cognitive mechanisms are still a matter of discussion. After a summary of the main hypotheses on the principal neuromotor causes of DCD, this study applies a causal model framework to describe the possible coexistence of more than one deficit in this disorder. For this purpose, kinematic analysis was applied to an ecological task, the reach-to-grasp action, introducing the manipulation of three variables: vision, distance and object size. After a thorough neurological and neuropsychological evaluation, 9 children with DCD (7-9 years old) were selected and compared to 27 age-matched control children. The results suggest that children with DCD have a normal neurological characterization of the reaching and grasping movements, in terms of proximal to distal action, but their grasping aperture (MGA) was always wider with respect to controls, particularly when vision was not allowed. In addition, the performance of children with DCD was always slower, more dependent on vision and more variable than that of controls. The MGA of children with DCD could be explained by a deficit in the internal construction of movement for a forward model, while slowness could be related to a control problem in the neuronal firing of the muscles. The idea of a possible coexistence of these two deficits is discussed in accordance to a causal model framework and also addressed considering recent neurophysiologic evidences.
Keywords: Analysis of Variance; Biomechanical Phenomena; Child; Female; Humans; Male; Motor Skills Disorders; Psychometrics; Psychomotor Performance; Reaction Time; Space Perception

Osteoprotegerin induces morphological and functional alterations in mouse pancreatic islets. - Toffoli, Barbara; Bernardi, Stella; Candido, Riccardo; Sabato, Nicoletta; Carretta, Renzo; Corallini, Federica; Secchiero, Paola; Zauli, Giorgio; Fabris, Bruno (Mol Cell Endocrinol, 2011)
Although serum osteoprotegerin (OPG) is significantly increased in diabetic subjects, its potential role in beta cell dysfunction has not been investigated. This study aimed to assess the effect of full-length OPG administered in vivo in mice on pancreatic islet structure and function and its interaction with the renin-angiotensin system (RAS). OPG-treated mice showed increased islet monocyte/macrophage infiltration, fibrosis and apoptosis with reduction of islet function. The remodeling of islet architecture was associated with increased pancreatic expression of components of the RAS, growth factor genes (transforming growth factor β and connective tissue growth factor) and inflammatory molecules (monocyte chemotactic protein-1 and vascular adhesion molecule type 1). Prevention of these changes with improvement of insulin secretion was observed in ramipril treated animals. Our data suggest that OPG might play an important role in promoting beta cell dysfunction and that the upregulation of the local RAS represents one possible mechanism responsible for the OPG-induced beta cell dysfunction.
Keywords: Animals; Apoptosis; Blood Glucose; Blood Pressure; Body Weight; Cell Lineage; Cell Movement; Chemokine CCL2; Connective Tissue Growth Factor; Fibrosis; Gene Expression Regulation; Humans; Insulin; Islets of Langerhans; Macrophages; Mice; Monocytes; Organ Size; Osteoprotegerin; Peptidyl-Dipeptidase A; Receptor, Angiotensin, Type 1; Systole; Transforming Growth Factor beta; Vascular Cell Adhesion Molecule-1

Osteoprotegerin promotes vascular fibrosis via a TGF-β1 autocrine loop. - Toffoli, Barbara; Pickering, Raelene J; Tsorotes, Despina; Wang, Bo; Bernardi, Stella; Kantharidis, Phillip; Fabris, Bruno; Zauli, Giorgio; Secchiero, Paola; Thomas, Merlin C (Atherosclerosis, 2011)
BACKGROUND: This study was designed to evaluate the potential role of osteoprotegerin (OPG) in arterial fibrosis. METHODS: Aortic samples were analyzed after in vivo treatment of ApoE(-/-) mice with recombinant human OPG. Mouse vascular smooth muscle cells (VSMC) were exposed in vitro to recombinant OPG and analyzed for markers of inflammation and fibrosis, such as fibronectin, collagen I, III, IV and transforming growth factor-β1 (TGF-β1). Conversely, the potential modulation of endogenous OPG expression and release by VSMC was analyzed in response to different pro-atherosclerotic cytokines, TGF-β1, platelet derived growth factor (PDGF) and angiogensin II (Ang II). RESULTS: In vivo treatment with human OPG induced signs of fibrosis and up-regulated the arterial expression of TGF-β1. Consistently, in vitro treatment of VSMC with human OPG induced the expression of fibronectin, collagen type I, III, IV, metalloprotein-2 (MMP-2) and MMP-9, as well as of TGF-β1. On the other hand, exposure to recombinant TGF-β1 promoted the expression/release of endogenous OPG and mediated the increase of OPG release induced by PDGF and Ang II in VSMC. CONCLUSIONS: Taken together, these data support a pathogenic role for OPG in the development and progression of atherosclerotic lesions and suggest the existence of a vicious circle between TGF-β1 and OPG.
Keywords: Animals; Apolipoproteins E; Cell Proliferation; Collagen; Fibronectins; Fibrosis; Gene Expression Regulation; Humans; Mice; Mice, Inbred C57BL; Mice, Transgenic; Muscle, Smooth, Vascular; Myocytes, Smooth Muscle; Osteoprotegerin; Platelet-Derived Growth Factor; Transforming Growth Factor beta1

Periodontal infection and preterm birth: successful periodontal therapy reduces the risk of preterm birth. - Di Mario, S; Spettoli, D; Alessandrini, C; Erenbourg, A; Ronfani, L; Basevi, V (BJOG, 2011)
Keywords: Female; Humans; Periodontal Diseases; Pregnancy; Pregnancy Complications, Infectious; Premature Birth; Randomized Controlled Trials as Topic; Risk Factors

A polymorphism in PRF1 gene is associated with HIV-1 vertical transmission in Brazilian children. - Padovan, Lara; Segat, Ludovica; Crovella, Sergio (AIDS, 2011)
We investigated the possible association between PRF1 gene polymorphisms and HIV-1 vertical transmission in Brazilian children by analyzing PRF1 gene coding and untranslated regions in 173 perinatally infected children (HIV+), 51 exposed uninfected (HIV-), and 171 HIV-unexposed uninfected children. Seven single nucleotide polymorphisms were identified in our samples. The rs885822 C allele and CC genotype were significantly more frequent in HIV-negative than in HIV-positive patients and associated with a protective effect toward HIV vertical transmission.
Keywords: Brazil; Female; HIV Infections; HIV-1; Humans; Infant, Newborn; Infectious Disease Transmission, Vertical; Male; Polymorphism, Genetic; Pore Forming Cytotoxic Proteins; Pregnancy

A polymorphism in the 5' UTR of the DEFB1 gene is associated with the lung phenotype in F508del homozygous Italian cystic fibrosis patients. - Crovella, Sergio; Segat, Ludovica; Amato, Annalisa; Athanasakis, Emmanouil; Bezzerri, Valentino; Braggion, Cesare; Casciaro, Rosaria; Castaldo, Giuseppe; Colombo, Carla; Covone, Angela Elvira; De Rose, Virginia; Gagliardini, Rolando; et al. (Clin Chem Lab Med, 2011)
BACKGROUND: The identification of cystic fibrosis (CF) patients who are at greater risk of lung damage could be clinically valuable. Thus, we attempted to replicate previous findings and verify the possible association between three single nucleotide polymorphisms (SNPs c.-52G>A, c.-44C>G and c.-20G>A) in the 5' untranslated region (5' UTR) of the β defensin 1 (DEFB1) gene and the CF pulmonary phenotype. METHODS: Genomic DNA from 92 Italian CF patients enrolled in different regional CF centres was extracted from peripheral blood and genotyped for DEFB1 SNPs using TaqMan(®) allele specific probes. In order to avoid genetic confounding causes that can account for CF phenotype variability, all patients were homozygous for the F508del CFTR mutation, and were then classified on the basis of clinical and functional data as mild lung phenotype (Mp, n=50) or severe lung phenotype patients (Sp, n=42). RESULTS: For the c.-20G>A SNP, the frequency of the A allele, as well as the AA genotype, were significantly more frequent in Mp than in Sp patients, and thus this was associated with a protective effect against severe pulmonary disease (OR=0.48 and 0.28, respectively). The effect of the c.-20G>A A allele is consistent with a recessive model, and the protective effect against Sp is exerted only when it is present in homozygosis. For the other two SNPs, no differences were observed as allelic and genotypic frequency in the two subgroups of CF patients. CONCLUSIONS: Our results, although necessary to be confirmed in larger and multiethnic populations, reinforce DEFB1 as a candidate modifier gene of the CF pulmonary phenotype.
Keywords: 5' Untranslated Regions; Adult; beta-Defensins; Cystic Fibrosis; Cystic Fibrosis Transmembrane Conductance Regulator; Female; Genotype; Homozygote; Humans; Italy; Male; Mutation; Phenotype; Polymorphism, Genetic; Young Adult

Procalcitonin in detecting neonatal nosocomial sepsis. - Auriti, Cinzia; Fiscarelli, Ersilia; Ronchetti, Maria Paola; Argentieri, Marta; Marrocco, Gabriella; Quondamcarlo, Anna; Seganti, Giulio; Bagnoli, Francesco; Buonocore, Giuseppe; Serra, Giovanni; Bacolla, Gianfranco; Mastropasqua, Savino; et al. (Arch Dis Child Fetal Neonatal Ed, 2011)
OBJECTIVE: To investigate the accuracy of procalcitonin (PCT) as a diagnostic marker of nosocomial sepsis (NS) and define the most accurate cut-off to distinguish infected from uninfected neonates. SETTING: Six neonatal intensive care units (NICUs). PATIENTS: 762 neonates admitted to six NICUs during a 28-month observational study for whom at least one serum sample was taken on admission. MAIN OUTCOME MEASURES: Positive and negative predictive values at different PCT cut-off levels. RESULTS: The overall probability of an NS was doubled or more if PCT was >0.5 ng/ml. In very-low-birth-weight (VLBW) infants, a cut-off of >2.4 ng/ml gave a positive predictive value of NS near to 50% with a probability of a false-positive diagnosis of NS in about 10% of the patients. CONCLUSIONS: In VLBW neonates, a serum PCT value >2.4 ng/ml prompts early empirical antibiotic therapy, while in normal-birth-weight infants, a PCT value ≤2.4 ng/ml carries a low risk of missing an NS.

Quality of maternal and neonatal care in Albania, Turkmenistan and Kazakhstan: a systematic, standard-based, participatory assessment. - Tamburlini, Giorgio; Siupsinskas, Gelmius; Bacci, Alberta (PLoS One, 2011)
BACKGROUND: Progress in maternal and neonatal mortality has been slow in many countries despite increasing access to institutional births, suggesting deficiencies in the quality of care. We carried out a systematic assessment of the quality of maternal and newborn care in three CEE/CIS countries, using an innovative approach to identify priority issues and promote action. METHODS: A standard-based tool, covering over 400 items grouped in 13 main areas ranging from support services to case management, was used to assess a sample of ten maternity hospitals in Albania, Kazakhstan and Turkmenistan. Sources of information were visit to services, medical records, observation of cases, and interviews with staff and mothers. A score (range 0 to 3) was attributed to each item and area of care. The assessment was carried out by a multidisciplinary team of international and national professionals. Local managers and staff provided the necessary information and were involved in discussing the findings and the priority actions. RESULTS: Quality of care was found to be substandard in all 13 areas. The lowest scores (between one and two) were obtained by: management of normal labour, delivery, obstetric complications and sick babies; infection prevention; use of guidelines and audits; monitoring and follow-up. Neonatal care as a whole scored better than obstetric care. Interviewed mothers identified lack of information, insufficient support during labour and lack of companionship as main issues. Actions to improve quality of care were identified at facility as well as at central level and framed according to main health system functions. CONCLUSIONS: Quality of care is a key issue to improve maternal and neonatal outcomes, particularly in countries such as CEE/CIS where access to institutional births is nearly universal. Approaches that involve health professionals and managers in comprehensive, action-oriented assessments of quality of care are promising and should be further supported.
Keywords: Albania; Child Health Services; Female; Humans; Infant, Newborn; Kazakhstan; Maternal Health Services; Pregnancy; Quality of Health Care; Turkmenistan

Quantification of heteroplasmic mitochondrial DNA mutations for DNA samples in the low picogram range by nested real-time ARMS-qPCR. - Biffi, Stefania; Bortot, Barbara; Carrozzi, Marco; Severini, Giovanni Maria (Diagn Mol Pathol, 2011)
In many mitochondrial diseases, different clinical manifestations are related to tissue-specific distribution of mutated mitochondrial DNA (mtDNA). In this study, we describe an assay for the determination of mutated mtDNA copy number in small clinical samples, using standard polymerase chain reaction (PCR) followed by SYBR Green real-time allelic-specific PCR [amplification refractory mutation system-quantitative PCR (ARMS-qPCR)]. To assess the degree of heteroplasmy in a patient harboring 2 cosegregating mtDNA mutations (4415A>G and 9922A>C) starting from picogram amounts of DNA, we first amplified the mutated target sequence by standard PCR, and then analyzed it by real-time ARMS-qPCR. To validate this method, we analyzed by real-time ARMS-qPCR the PCR amplification products derived from different mixtures containing known proportions of mutant and wild-type cloned mtDNA fragments. The correlation coefficient of 0.994 between expected and observed values for the percentage of mutant A4415G confirms that the relative proportion of mutated and wild-type mtDNA was maintained after the first PCR amplification. This method allows the precise quantification of heteroplasmic mutations in DNA samples extracted from hairs, urine, small stomach biopsies, and, more importantly, single-muscle fiber, with a limit of detection close to 0.5%. This nested real-time ARMS-PCR represents a rapid, efficient, and less expensive method for the detection and quantification of heteroplasmic mutant mtDNA, even in very small clinical samples.
Keywords: Child; DNA, Mitochondrial; Humans; Mitochondrial Diseases; Mutation; Polymerase Chain Reaction; Sensitivity and Specificity

Recent advances in the therapeutic perspectives of Nutlin-3. - Secchiero, Paola; Bosco, Raffaella; Celeghini, Claudio; Zauli, Giorgio (Curr Pharm Des, 2011)
Nutlin-3 is a small molecule inhibitor of the MDM2/p53 interaction, which leads to the non-genotoxic p53 stabilization, activation of cell cycle arrest and apoptosis pathways. A series of recent studies have strengthened the concept that selective, non-genotoxic p53 activation by Nutlin-3 might represent an alternative to the current cytotoxic chemotherapy, in particular for pediatric tumors and for hematological malignancies, which retain a high percentage of p53(wild-type) status at diagnosis. Like most other drugs employed in cancer therapy, it will be unlikely that Nutlin-3 will be used as a monotherapy. In this respect, Nutlin-3 shows a synergistic cytotoxic effect when used in combination with innovative drugs, such as TRAIL or bortozemib. Although Nutlin-3 is currently in phase I clinical trial for the treatment of retinoblastoma, its effects on normal tissues and cell types remain largely to be determined and will require further investigation in the future years.
Keywords: Antineoplastic Agents; Antineoplastic Combined Chemotherapy Protocols; Drug Synergism; Genes, p53; Humans; Imidazoles; Neoplasms; Piperazines; Proto-Oncogene Proteins c-mdm2; Tumor Suppressor Protein p53

Recent advances in the understanding and management of MYH9-related inherited thrombocytopenias. - Balduini, Carlo L; Pecci, Alessandro; Savoia, Anna (Br J Haematol, 2011)
MYH9-related disease (MYH9-RD) is one of the most frequent forms of inherited thrombocytopenia. It is transmitted in an autosomal dominant fashion and derives from mutations of MYH9, the gene for the heavy chain of non-muscle myosin IIA. Patients present with congenital macrothrombocytopenia with mild bleeding tendency and may develop kidney dysfunction, deafness and cataracts later in life. The term MYH9-RD encompasses four autosomal-dominant thrombocytopenias that were previously described as distinct disorders, namely May-Hegglin Anomaly, Sebastian, Fechtner and Epstein syndromes. Thrombocytopenia is usually mild and derives from complex defects of megakaryocyte maturation and platelet formation. It is easily diagnosed, in that the presence of giant platelets in peripheral blood raises the suspicion of MYH9-RD and a simple immunofluorescence test on blood films confirms the diagnostic hypothesis. However, genotype/phenotype correlations have been recognized and mutation screening is therefore required to define the risk of acquiring extra-haematological defects. Results of a small clinical study suggested that a non-peptide thrombopoietin mimetic might greatly benefit both thrombocytopenia and bleeding tendency of MYH9-RD patients.
Keywords: Animals; Disease Models, Animal; Genetic Predisposition to Disease; Genotype; Humans; Mice; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Myosin Type II; Phenotype; Thrombocytopenia

Role of DC-SIGN and L-SIGN receptors in HIV-1 vertical transmission. - da Silva, Ronaldo Celerino; Segat, Ludovica; Crovella, Sergio (Hum Immunol, 2011)
The innate immune system acts in the first line of host defense against pathogens. One of the mechanisms used involves the early recognition and uptake of microbes by host professional phagocytes, through pattern recognition receptors (PRRs). These PRRs bind to conserved microbial ligands expressed by pathogens and initiate both innate and adaptative immune responses. Some PRRs located on the surface of dendritic cells (DCs) and other cells seem to play an important role in human immunodeficiency virus type 1 (HIV-1) transmission. Dendritic cell-specific intercellular adhesion molecule-3 grabbing non-integrin, CD209 (DC-SIGN) and its homolog, DC-SIGN-related (DC-SIGNR or L-SIGN) receptors are PPRs able to bind the HIV-1 gp120 envelope protein and, because alterations in their expression patterns also occur, they might play a role in both horizontal and vertical transmission as well as in disseminating the virus within the host. This review aims to explore the involvement of the DC-SIGN and L-SIGN receptors in HIV-1 transmission from mother to child.
Keywords: Cell Adhesion Molecules; HIV Infections; HIV-1; Humans; Immunity, Innate; Infectious Disease Transmission, Vertical; Lectins, C-Type; Polymorphism, Genetic; Receptors, Cell Surface

The role of mannose-binding lectin gene polymorphisms in susceptibility to HIV-1 infection in Southern Brazilian patients. - da Silva, Gabriela Kniphoff; Guimarães, Rafael; Mattevi, Vanessa Suñé; Lazzaretti, Rosmeri Kuhmmer; Sprinz, Eduardo; Kuhmmer, Regina; Brandão, Lucas; Crovella, Sergio; Chies, José Artur Bogo (AIDS, 2011)
OBJECTIVE: This study investigates the role of mannose-binding lectin (MBL) in the susceptibility to HIV-1 infection analyzing polymorphisms located at the MBL2 promoter and exon 1 regions. MATERIALS AND METHODS: The prevalence of MBL2 variant alleles was investigated in 410 HIV-1-infected patients from the South Brazilian HIV cohort and in 345 unexposed uninfected healthy individuals. The promoter variants were genotyped using polymerase chain reaction with sequence-specific primers (PCR-SSP) and exon 1 variants were analyzed by real-time PCR using a melting temperature assay and were confirmed by PCR-restriction fragment length polymorphism (RFLP). MBL2 genotypic and allelic frequencies were compared between HIV-1-infected patients and controls using the chi-squared tests. RESULTS: The analyses were performed subdividing the individuals according to their ethnic origin. Among Euro-derived individuals a higher frequency of the LX/LX genotype was observed in patients when compared to controls (P < 0.001). The haplotypic analysis also showed a higher frequency of the haplotypes associated with lower MBL levels among HIV-1-infected patients (P = 0.0001). Among Afro-derived individuals the frequencies of LY/LY and HY/HY genotypes were higher in patients when compared to controls (P = 0.009 and P = 0.02). CONCLUSIONS: An increased frequency of MBL2 genotypes associated with low MBL levels was observed in Euro-derived patients, suggesting a potential role for MBL in the susceptibility to HIV-1 infection in Euro-derived individuals.
Keywords: Adult; Aged; Brazil; Female; Genetic Predisposition to Disease; HIV Infections; HIV-1; Humans; Lectins, C-Type; Male; Mannose-Binding Lectin; Mannose-Binding Lectins; Middle Aged; Polymorphism, Genetic; Promoter Regions, Genetic; Receptors, Cell Surface; Young Adult

Rubella susceptibility profile in pregnant women with HIV. - Floridia, Marco; Pinnetti, Carmela; Ravizza, Marina; Tibaldi, Cecilia; Sansone, Matilde; Fiscon, Marta; Guaraldi, Giovanni; Guerra, Brunella; Alberico, Salvatore; Spinillo, Arsenio; Castelli, Paula; Dalzero, Serena; et al. (Clin Infect Dis, 2011)
Keywords: Female; HIV Infections; Humans; Pregnancy; Pregnancy Complications, Infectious; Rubella

Setting research priorities to reduce global mortality from childhood pneumonia by 2015. - Rudan, Igor; El Arifeen, Shams; Bhutta, Zulfiqar A; Black, Robert E; Brooks, Abdullah; Chan, Kit Yee; Chopra, Mickey; Duke, Trevor; Marsh, David; Pio, Antonio; Simoes, Eric A F; Tamburlini, Giorgio; et al. (PLoS Med, 2011)
Keywords: Biomedical Research; Child, Preschool; Humans; Infant; Infant, Newborn; Pneumonia

Shwachman-Diamond syndrome and type 1 diabetes mellitus: more than a chance association? - Gana, S; Sainati, L; Frau, M R; Monciotti, C; Poli, F; Cannioto, Z; Comelli, M; Danesino, C; Minelli, A (Exp Clin Endocrinol Diabetes, 2011)
Shwachman-Diamond syndrome is a rare clinical condition consisting of exocrine pancreatic dysfunction, various degree of pancytopenia, and metaphyseal dysplasia. The majority of Shwachman-Diamond syndrome cases result from mutations in the Shwachman-Bodian-Diamond Syndrome gene. To date, type 1 diabetes mellitus has only been reported in 4 independent cases presenting with Shwachman-Diamond syndrome, 3 of them with molecular confirmation of the diagnosis. We describe 2 unrelated patients with clinical and molecular features typical of Shwachman-Diamond syndrome and type 1 diabetes mellitus. In addition, we report the occurrence rate of type 1 diabetes mellitus in the Italian registry for Shwachman-Diamond syndrome, which is low (3.23%) but increased at least 30-fold over the type 1 diabetes mellitus occurrence rate in the general population. No evidence of a direct correlation between Shwachman-Diamond syndrome and type 1 diabetes mellitus have been reported, therefore the presence of both diseases in the same patient might be a chance association, however we suggest that the defects in immune regulation of Shwachman-Diamond syndrome might play a role in the development of type 1 diabetes mellitus.
Keywords: Bone Marrow Diseases; CD4-CD8 Ratio; Diabetes Mellitus, Type 1; Exocrine Pancreatic Insufficiency; Female; Heterozygote; Humans; Immune System; Infant; Italy; Lipomatosis; Male; Mutation; Prevalence; Proteins; Registries

The significance of mannose-binding lectin gene polymorphisms on the risk of BK virus coinfection in women with human papillomavirus-positive cervical lesions. - Comar, Manola; Segat, Ludovica; Crovella, Sergio; Bovenzi, Massimo; Cortini, Enzo; Tognon, Mauro (Hum Immunol, 2011)
The simultaneous detection of oncogenic human papillomavirus (HPV) and BK virus (BKV) has been recently reported in cervical cancers, suggesting that these viruses may act together in the process of cell transformation; host genetic polymorphisms may also influence virus persistence/reactivation. To disclose a possible role of the gene encoding for the mannose-binding lectin, MBL2, in susceptibility to BKV infection, we analyzed functional polymorphisms in the first exon of MBL2 in women stratified for the presence/absence of BKV and affected by different grades of HPV-induced cervical precancerous lesions. All BKV-positive samples were also HPV positive (HPV 16), and all presented with high-grade squamous intraepithelial lesions. The MBL2 A allele was significantly more frequent in BKV-negative patients than in BKV-positive patients. These data indicate a possible role for the A allele in conferring protection to BKV infection in high-risk HPV-positive women (odds ratio 0.40, 95% confidence interval 0.20-0.85, p = 0.01).
Keywords: Adult; Aged; Alleles; BK Virus; Cervical Intraepithelial Neoplasia; Cervix Uteri; DNA Fingerprinting; DNA, Viral; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Human papillomavirus 16; Humans; Italy; Mannose-Binding Lectin; Odds Ratio; Papillomavirus Infections; Polymorphism, Genetic; Polyomavirus Infections; Risk; Viral Load

Somatic mosaic IDH1 and IDH2 mutations are associated with enchondroma and spindle cell hemangioma in Ollier disease and Maffucci syndrome. - Pansuriya, Twinkal C; van Eijk, Ronald; d'Adamo, Pio; van Ruler, Maayke A J H; Kuijjer, Marieke L; Oosting, Jan; Cleton-Jansen, Anne-Marie; van Oosterwijk, Jolieke G; Verbeke, Sofie L J; Meijer, Daniëlle; van Wezel, Tom; Nord, Karolin H; et al. (Nat Genet, 2011)
Ollier disease and Maffucci syndrome are non-hereditary skeletal disorders characterized by multiple enchondromas (Ollier disease) combined with spindle cell hemangiomas (Maffucci syndrome). We report somatic heterozygous mutations in IDH1 (c.394C>T encoding an R132C substitution and c.395G>A encoding an R132H substitution) or IDH2 (c.516G>C encoding R172S) in 87% of enchondromas (benign cartilage tumors) and in 70% of spindle cell hemangiomas (benign vascular lesions). In total, 35 of 43 (81%) subjects with Ollier disease and 10 of 13 (77%) with Maffucci syndrome carried IDH1 (98%) or IDH2 (2%) mutations in their tumors. Fourteen of 16 subjects had identical mutations in separate lesions. Immunohistochemistry to detect mutant IDH1 R132H protein suggested intraneoplastic and somatic mosaicism. IDH1 mutations in cartilage tumors were associated with hypermethylation and downregulated expression of several genes. Mutations were also found in 40% of solitary central cartilaginous tumors and in four chondrosarcoma cell lines, which will enable functional studies to assess the role of IDH1 and IDH2 mutations in tumor formation.
Keywords: Adult; Case-Control Studies; Cell Line, Tumor; DNA Methylation; Enchondromatosis; Female; Gene Expression Profiling; Gene Expression Regulation; Genome-Wide Association Study; Humans; Isocitrate Dehydrogenase; Male; Middle Aged; Mosaicism; Mutation, Missense; Sequence Analysis, DNA; Transcription, Genetic; Young Adult

Tag-single nucleotide polymorphism-based human leukocyte antigen genotyping in celiac disease patients from northeastern Italy. - Vatta, Serena; Fabris, Annalisa; Segat, Ludovica; Not, Tarcisio; Crovella, Sergio (Hum Immunol, 2011)
We genotyped celiac disease (CD)-associated haplotypes DQ2.5, DQ8, DQ2.2, and DQ7 in 1005 CD patients from North Eastern Italy using a Tag-single nucleotide polymorphism (SNPs) approach and real time PCR platform, checking the accuracy and reliability of the method and comparing it to traditional PCR-SSP. Only 14 of 2010 chromosomes analyzed (0.7%) showed discrepancies between the Tag-SNPs real-time polymerase chain reaction (PCR) method and the PCR-single-strand polymorphism (SSP) technique, indicating a high sensitivity and specificity (ranging from 0.987 to 1 and from 0.998 to 0.999, respectively) for tagging with respect to corresponding human leukocyte antigen (HLA) alleles identified by PCR-SSP. Moreover, the overall cost of the Tag-SNPs HLA typing method was low (3 to 4 €/sample instead of 35 to 70 €/sample with commercial kits), making it suitable for mass screenings. Hence, we believe that the Tag-SNPs HLA typing could be used to complement or replace classic HLA typing in at high-risk groups, for research purposes and eventually in population screening programs.
Keywords: Adolescent; Adult; Aged; Celiac Disease; Child; Child, Preschool; Female; Humans; Infant; Italy; Male; Mass Screening; Middle Aged; Polymerase Chain Reaction; Polymorphism, Single Nucleotide; Reproducibility of Results; Reverse Transcriptase Polymerase Chain Reaction; Sensitivity and Specificity

Trail down-regulates the release of osteoprotegerin (OPG) by primary stromal cells. - Corallini, Federica; Celeghini, Claudio; Rimondi, Erika; di Iasio, Maria Grazia; Gonelli, Arianna; Secchiero, Paola; Zauli, Giorgio (J Cell Physiol, 2011)
The soluble member of the TNF-R superfamily osteoprotegerin (OPG) is abundantly released under basal conditions by both mesenchymal stem cells (MSC) and fibroblasts and by endothelial cells upon stimulation with inflammatory cytokines. Since MSC, fibroblasts and endothelial cells represent key elements of the normal and tumor microenvironment and express detectable levels of surface TRAIL receptors, we investigated the effect of TRAIL on OPG release. Unexpectedly, recombinant TRAIL decreased the spontaneous OPG release in all cell types examined. Moreover, TRAIL decreased OPG release also in stromal cells co-cultured with lymphoma cells and counteracted the OPG induction by TN-alpha in HUVEC and MSC. Such down-regulation was not due to a masking effect in the ELISA quantification of the OPG released in the culture supernatants due to binding of OPG to its ligands (TRAIL and RANKL), as demonstrated by competition experiments with recombinant TRAIL and by the lack of RANKL release/induction. In addition, OPG down-regulation was not due to induction of cytotoxic effects by TRAIL, since the degree of apoptosis in response to TRAIL was negligible in all primary cell types. With regards to the possible molecular mechanism accounting for the down-regulation of OPG release by TRAIL, we found that treatment of MSC with TRAIL significantly decreased the phosphorylation levels of p38/MAPK. There is a suggestion that this pathway is involved in the stabilization of OPG mRNA. In this respect, the ability of TRAIL to decrease the release of OPG, in the absence of cell cytotoxicity, was mimicked by the p38/MAPK inhibitor SB203580.
Keywords: Bone Marrow Cells; Cell Death; Cells, Cultured; Coculture Techniques; Down-Regulation; Endothelial Cells; Enzyme Activation; Enzyme-Linked Immunosorbent Assay; Fibroblasts; Humans; MAP Kinase Signaling System; Mesenchymal Stromal Cells; Osteoprotegerin; p38 Mitogen-Activated Protein Kinases; Protein Binding; Recombinant Proteins; Stromal Cells; TNF-Related Apoptosis-Inducing Ligand; Tumor Necrosis Factor-alpha

TRAIL promotes a pro-survival signal in erythropoietin-deprived human erythroblasts through the activation of an NF-kB/IkBalpha pathway. - Sancilio, S; Di Giacomo, V; Quaglietta, A M; Iacone, A; Angelucci, D; Tatasciore, U; Rana, R A; Cataldi, A; Zauli, G; Di Pietro, R (J Biol Regul Homeost Agents, 2011)
The biological activity of TNF-related apoptosis inducing ligand (TRAIL) was analyzed in primary human erythroblasts derived from mononuclear cells of blood donors, kept in culture in the presence of 20 percent foetal calf serum, growth factors (EPO, SCF, IL-3) and glucocorticoids (10-6 M dexamethasone, 10-6 M oestradiol) or under growth factor and serum starvation. In the presence of growth factors and serum, primary erythroblasts showed a differential expression of TRAIL-Receptors (Rs) at various degrees of maturation and responded to TRAIL treatment with a mild cytotoxicity. On the other hand, in the absence of serum and growth factors, TRAIL treatment unexpectedly up-regulated TRAIL-R4 decoy receptor and promoted erythroblast survival. The concomitant activation of NF-kB/IkB survival pathway was detected with Western blotting and immunofluorescence procedures and confirmed by experiments performed with SN50, a pharmacological inhibitor of the NF-kB/IkB pathway. Our study indicates that TRAIL has a twofold activity on erythroid lineages: it induces a mild erythroid cell cytotoxicity in the presence of serum and growth factors, while it promotes erythroid cell survival through the activation of the NF-kB/IkB pathway under starvation conditions.
Keywords: Cell Survival; Erythroblasts; Erythropoietin; Gene Expression Regulation; Humans; I-kappa B Kinase; Jurkat Cells; NF-kappa B; Peptides; TNF-Related Apoptosis-Inducing Ligand; Tumor Necrosis Factor Decoy Receptors

Usefulness of wireless capsule endoscopy for detecting inflammatory bowel disease in children presenting with arthropathy. - Taddio, Andrea; Simonini, Gabriele; Lionetti, Paolo; Lepore, Loredana; Martelossi, Stefano; Ventura, Alessandro; Cimaz, Rolando (Eur J Pediatr, 2011)
Inflammatory bowel disease (IBD) is a cause of chronic intestinal inflammation in children. In a subset of patients affected by IBD, arthropathy may be the leading presenting sign. In the past years, remarkable advances in gastrointestinal endoscopy techniques have been achieved; recently, the development of capsule endoscopy (CE) provided a non-invasive method for the complete endoscopic evaluation, including small bowel assessment. We report three children suffering from IBD but presenting with articular complaints in whom CE was a useful tool for detecting gut inflammation. Patients were investigated with the wireless CE: PillCam SB2 (Given Imaging, Yoqneam, Israel) capsule, the second-generation capsule, was used in our paediatric patients. Three patients were initially evaluated for arthropathy. Enteropathic arthritis was suspected for gastrointestinal symptoms and/or persistence of inflammatory markers elevation. In one of these children, conventional endoscopy was refused by parents, while in the other two children, CE was proposed as first-line diagnostic tool. In all patients, CE revealed to be safe and provided information that led to diagnosis. Paediatric rheumatologists should consider CE as a valid, non-invasive tool, eventually first level diagnostic approach in order to evaluate the presence of IBD in children presenting with chronic articular complaints.
Keywords: Adolescent; Arthritis, Juvenile; Capsule Endoscopy; Child; Colitis, Ulcerative; Colon; Crohn Disease; Diagnosis, Differential; Follow-Up Studies; Humans; Inflammatory Bowel Diseases; Intestine, Small; Male; Predictive Value of Tests; Sensitivity and Specificity; Severity of Illness Index; Treatment Outcome

X-ray fluorescence elemental mapping and microscopy to follow hepatic disposition of a Gd-based magnetic resonance imaging contrast agent. - Delfino, Riccarda; Altissimo, Matteo; Menk, Ralf Hendrik; Alberti, Roberto; Klatka, Tomasz; Frizzi, Tommaso; Longoni, Antonio; Salomè, Murielle; Tromba, Giuliana; Arfelli, Fulvia; Clai, Milan; Vaccari, Lisa; et al. (Clin Exp Pharmacol Physiol, 2011)
1. Spatially resolved X-ray fluorescence (XRF) spectroscopy with synchrotron radiation is a technique that allows imaging and quantification of chemical elements in biological specimens with high sensitivity. In the present study, we applied XRF techniques at a macro and micro level to carry out drug distribution studies on ex vivo models to confirm the hepatobiliary disposition of the Gd-based magnetic resonance imaging contrast agent B22956/1. 2. Gd presence was selectively quantified allowing the determination of the time dependent disappearance of the drug from blood and its hepatic accumulation in mice after administration. Elemental mapping highlighted the drug distribution differences between healthy and diseased livers. XRF microanalyses showed that in CCl(4) -induced hepatitis, B22956/1 has greatly reduced hepatic accumulation, shown as a 20-fold reduction of Gd presence. Furthermore, a significant increase of Fe presence was found in steatotic compared with healthy livers, in line with the disease features. 3. The present results show that XRF might be useful in preclinical pharmacological studies with drugs containing exogenous elements. Furthermore, quantitative and high-sensitivity elemental mapping allows simultaneous detection of chemical variation, showing pathological conditions. This approach was useful in suggesting reduced B22956/1 accumulation in steatotic livers, thus opening possible new diagnostic perspectives for this drug.
Keywords: Animals; Contrast Media; Fatty Liver; Female; Gadolinium; Hepatitis; Iron; Liver; Magnetic Resonance Imaging; Mice; Mice, Inbred CBA; Organometallic Compounds; Spectrometry, X-Ray Emission

A 3'UTR SNP in NLRP3 gene is associated with susceptibility to HIV-1 infection. - Pontillo, Alessandra; Brandão, Lucas A; Guimarães, Rafael L; Segat, Ludovica; Athanasakis, Emmanouil; Crovella, Sergio (J Acquir Immune Defic Syndr, 2010)
OBJECTIVES: Innate immunity genes polymorphisms are known to be involved in the multifactorial susceptibility to HIV-1 infection. Recently it has been hypothesized that inflammasomes could play an important role in the host response to viruses. The aim of our study is to verify if single-nucleotide polymorphisms (SNPs) in genes encoding for NALPs-innate immune receptors that form molecular complexes leading to the production of IL-1beta and the activation of immune response-could influence the individual susceptibility to HIV-1. DESIGN: We performed an association study analyzing 2 NLRP1 and NLRP3 SNPs in HIV-1 vertically infected Brazilian children (n = 135), HIV-1-infected Brazilain adults (n = 192) and HIV-1-positive Italian seropositive subjects (n = 192). RESULTS: The 3'UTR NLRP3 rs10754558 SNP was associated with HIV-1 infection in all the studied groups. The frequency of rs10754558 G allele was differently distributed within seropositive subjects (HIV+) and controls, and in particular the GG genotype was less frequent in HIV+. CONCLUSIONS: susceptibility to HIV-1 infection is associated with a 3'UTR NLRP3 polymorphism. This is the first report linking SNPs in the NALPs with HIV-1 infection, and further epidemiologic and functional studies are needed to deeper investigate the role of inflammasome in the susceptibility to HIV-1 infection.
Keywords: Adult; Brazil; Carrier Proteins; Case-Control Studies; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Genotype; HIV Infections; HIV-1; Humans; Infant; Infectious Disease Transmission, Vertical; Male; Middle Aged; Polymorphism, Single Nucleotide; Pregnancy; Young Adult

Abatacept improves health-related quality of life, pain, sleep quality, and daily participation in subjects with juvenile idiopathic arthritis. - Ruperto, Nicolino; Lovell, Daniel J; Li, Tracy; Sztajnbok, Flavio; Goldenstein-Schainberg, Claudia; Scheinberg, Morton; Penades, Inmaculada Calvo; Fischbach, Michael; Alcala, Javier Orozco; Hashkes, Philip J; Hom, Christine; Jung, Lawrence; et al. (Arthritis Care Res (Hoboken), 2010)
OBJECTIVE: To assess health-related quality of life (HRQOL) in abatacept-treated children/adolescents with juvenile idiopathic arthritis (JIA). METHODS: In this phase III, double-blind, placebo-controlled trial, subjects with active polyarticular course JIA and an inadequate response/intolerance to ≥1 disease-modifying antirheumatic drug (including biologics) received abatacept 10 mg/kg plus methotrexate (MTX) during the 4-month open-label period (period A). Subjects achieving the American College of Rheumatology Pediatric 30 criteria for improvement (defined "responders") were randomized to abatacept or placebo (plus MTX) in the 6-month double-blind withdrawal period (period B). HRQOL assessments included 15 Child Health Questionnaire (CHQ) health concepts plus the physical (PhS) and psychosocial summary scores (PsS), pain (100-mm visual analog scale), the Children's Sleep Habits Questionnaire, and a daily activity participation questionnaire. RESULTS: A total of 190 subjects from period A and 122 from period B were eligible for analysis. In period A, there were substantial improvements across all of the CHQ domains (greatest improvement was in pain/discomfort) and the PhS (8.3 units) and PsS (4.3 units) with abatacept. At the end of period B, abatacept-treated subjects had greater improvements versus placebo in all domains (except behavior) and both summary scores. Similar improvement patterns were seen with pain and sleep. For participation in daily activities, an additional 2.6 school days/month and 2.3 parents' usual activity days/month were gained in period A responders with abatacept, and further gains were made in period B (1.9 versus 0.9 [P = 0.033] and 0.2 versus -1.3 [P = 0.109] school days/month and parents' usual activity days/month, respectively, in abatacept- versus placebo-treated subjects). CONCLUSION: Improvements in HRQOL were observed with abatacept, providing real-life tangible benefits to children with JIA and their parents/caregivers.
Keywords: Adolescent; Arthritis, Juvenile; Child; Double-Blind Method; Female; Health Status; Humans; Immunoconjugates; Male; Pain; Quality of Life; Questionnaires; Sleep Stages

Acute respiratory failure in a child after talc inhalation. - Patarino, Federica; Norbedo, Stefania; Barbi, Egidio; Poli, Furio; Furlan, Stefano; Savron, Fabio (Respiration, 2010)
Keywords: Female; Humans; Infant; Inhalation Exposure; Respiratory Insufficiency; Talc

An alternative role of C1q in cell migration and tissue remodeling: contribution to trophoblast invasion and placental development. - Agostinis, Chiara; Bulla, Roberta; Tripodo, Claudio; Gismondi, Angela; Stabile, Helena; Bossi, Fleur; Guarnotta, Carla; Garlanda, Cecilia; De Seta, Francesco; Spessotto, Paola; Santoni, Angela; Ghebrehiwet, Berhane; et al. (J Immunol, 2010)
Fetal trophoblast cells invading the decidua in the early phase of pregnancy establish complex interaction with the maternal extracellular matrix. We discovered that C1q was widely distributed in human decidual stroma in the absence of C4 and C3 and was actively synthesized by migrating extravillous trophoblasts. The cells expressed the messages for the three chains of C1q and secreted this complement component that interacted with the proteins of the decidual extracellular matrix. Solid phase-bound C1q promoted trophoblast adhesion and migration, and cell binding to C1q resulted in activation of ERK1/2 MAPKs. Ab inhibition experiments showed that the receptors for the globular head of C1q/p33 and α(4)β(1) integrin were both involved in this process and were colocalized on the cell surface following binding of C1q to trophoblasts. We also found that C1q(-/-) mice manifested increased frequency of fetal resorption, reduced fetal weight, and smaller litter sizes compared with wild-type mice. C1q deficiency was associated with impaired labyrinth development and decidual vessel remodeling. Collectively, these data suggest that C1q plays an important role in promoting trophoblast invasion of decidua and that defective local production of C1q may be involved in pregnancy disorders, such as pre-eclampsia, characterized by poor trophoblast invasion.
Keywords: Animals; Cell Adhesion; Chemotaxis, Leukocyte; Complement C1q; Female; Humans; Immunoblotting; Immunohistochemistry; Immunoprecipitation; Mice; Mice, Inbred C57BL; Microscopy, Confocal; Placentation; Pre-Eclampsia; Pregnancy; Reverse Transcriptase Polymerase Chain Reaction; Trophoblasts

Analysis of DEFB1 regulatory SNPs in cystic fibrosis patients from North-Eastern Italy. - Segat, L; Morgutti, M; Athanasakis, E; Trevisiol, C; Amaddeo, A; Poli, F; Crovella, S (Int J Immunogenet, 2010)
Cystic fibrosis (CF) transmembrane regulator protein (CFTR) gene is undoubtedly the main genetic factor involved in the modulation of CF phenotype. However, other factors such as human defensins and the genes encoding for these antimicrobial peptides have been hypothesized as possible modifiers influencing airways infection in CF patients, but their role in the pathogenesis of lung disease is still debated. Since DEFB1 gene encoding for human beta-defensin 1 displays features such as antimicrobial or chemotactic activity playing a role in inflammation, it has been considered as a possible candidate CF modifier gene. We analysed three single nucleotide polymorphisms (SNPs) in the 5'-untranslated region of the DEFB1 gene (namely g-52G>A, g-44C>G and g-20G>A) in a group of 62 CF patients from North Eastern Italy, and in 130 healthy controls, with the aim of verifying the possible association of these functional SNPs with the pulmonary phenotype of CF patients. DEFB1 SNPs have been genotyped by using Taqman allele-specific fluorescent probes and a real-time PCR platform. No significant differences were found for allele, genotype and haplotype frequencies of DEFB1 g-52G>A, g-44C>G and g-20G>A SNPs in CF patients stratified for Pseudomonas aeruginosa infection, as well as in patients with a severe and mild clinical phenotype or in patients stratified for CFTR genotypes. DEFB1 allele, genotype and haplotype frequencies of CF patients globally considered were similar to those of healthy controls. Our findings are discordant with respect to another recent study performed on CF patients coming from Southern Italy, probably due to different ethnicity of the patients.
Keywords: 5' Untranslated Regions; Adolescent; Alleles; beta-Defensins; Case-Control Studies; Child; Child, Preschool; Chronic Disease; Cystic Fibrosis; Cystic Fibrosis Transmembrane Conductance Regulator; Female; Gene Frequency; Genotype; Haplotypes; Humans; Immunity, Innate; Infant; Infant, Newborn; Italy; Male; Polymorphism, Single Nucleotide; Pseudomonas Infections

Anti transglutaminase antibodies cause ataxia in mice. - Boscolo, Sabrina; Lorenzon, Andrea; Sblattero, Daniele; Florian, Fiorella; Stebel, Marco; Marzari, Roberto; Not, Tarcisio; Aeschlimann, Daniel; Ventura, Alessandro; Hadjivassiliou, Marios; Tongiorgi, Enrico (PLoS One, 2010)
BACKGROUND: Celiac disease (CD) is an autoimmune gastrointestinal disorder characterized by the presence of anti-transglutaminase 2 (TG2) and anti-gliadin antibodies. Amongst the neurological dysfunctions associated with CD, ataxia represents the most common one. METHODS: We analyzed by immunohistochemistry, the anti-neural reactivity of the serum from 20 CD patients. To determine the role of anti-TG2 antibodies in ataxia, two anti-TG2 single chain variable fragments (scFv), isolated from a phage-display IgA antibody library, were characterized by immunohistochemistry and ELISA, and injected in mice to study their effects on motor coordination. We found that 75% of the CD patient population without evidence of neurological involvement, has circulating anti-neural IgA and/or IgG antibodies. Two anti-TG2 scFvs, cloned from one CD patient, stained blood vessels but only one reacted with neurons. This anti-TG2 antibody showed cross reactivity with the transglutaminase isozymes TG3 and TG6. Intraventricular injection of the anti-TG2 or the anti-TG2/3/6 cross-reactive scFv provoked transient, equally intensive ataxia in mice. CONCLUSION: The serum from CD patients contains anti-TG2, TG3 and TG6 antibodies that may potentially cause ataxia.
Keywords: Adult; Animals; Antibodies; Ataxia; Autoimmune Diseases; Brain; Celiac Disease; Female; Gliadin; Humans; Isoenzymes; Male; Mice; Mice, Inbred C57BL; Middle Aged; Motor Skills; Rats; Rats, Sprague-Dawley; Transglutaminases

Beta defensin-1 gene (DEFB1) polymorphisms are not associated with atopic dermatitis in children and adolescents from northeast Brazil (Recife, Pernambuco). - Segat, Ludovica; Guimarães, Rafael L; Brandão, Lucas A C; Rocha, Cintia R C; Zanin, Valentina; Trevisiol, Chiara; de Lima Filho, José Luiz; Crovella, Sergio (Int J Dermatol, 2010)
BACKGROUND: Atopic dermatitis (AD) is a common inflammatory skin disease resulting from the interplay between environmental, immunological and genetic factors. In our study, we investigated the role of three single nucleotide polymorphisms (SNPs) at 5'-UTR of DEFB1 gene, encoding for the human beta defensin-1, on the susceptibility to develop AD in a group of Brazilian children and adolescents. METHODS: Three SNPs, -20 G/A (rs11362), -44 C/G (rs1800972), and -52 G/A (rs1799946) at 5'-UTR of DEFB1 gene were genotyped in two groups of children and adolescents, one affected by AD (96 subjects), the other healthy (191 individuals), from northeast Brazil. RESULTS: -44 C/G frequencies were comparable between the two groups. The -20 GG genotype was more frequent in AD subjects than in healthy controls; the -52 GG, conversely, was more frequent in healthy controls than in AD. However, both these differences did not reach statistical significance. Also, association between SNPs and AD severity has been shown. The analysis of DEFB1 haplotypes did not highlight any association of the three SNPs with AD development or disease severity. CONCLUSIONS: Our results seem to exclude a role for the -44 C/G DEFB1 SNPs on the pathogenesis and severity of AD, while for the -20 C/G and -52 G/A, even if not statistically significant, we evidenced a slight trend for susceptibility (-20 GG) and protection (-52 GG) for the development of AD. However, as controversial findings have been reported in the literature, the role of DEFB1 in the development of AD and in the severity of the phenotype deserves further investigation.
Keywords: Adolescent; beta-Defensins; Brazil; Child; Child, Preschool; Dermatitis, Atopic; Female; Gene Frequency; Genetic Predisposition to Disease; Haplotypes; Humans; Infant; Male; Polymorphism, Single Nucleotide; Risk Factors

A case of lymphedema-distichiasis syndrome carrying a new de novo frameshift FOXC2 mutation. - Fabretto, Antonella; Shardlow, Alison; Faletra, Flavio; Lepore, Loredana; Hladnik, Uros; Gasparini, Paolo (Ophthalmic Genet, 2010)
PURPOSE: Lymphedema-Distichiasis (LD, OMIM 153400) is an autosomal dominant disorder with variable expression. The mutated gene implicated is FOXC2, which encodes for a forkhead transcription factor involved in the development of the lymphatic and vascular system. LD is characterized by late childhood or pubertal onset lymphedema of the limbs and distichiasis. Other associations have been reported, including congenital heart disease, ptosis, scoliosis. CONCLUSIONS: Here we describe a case of LD carrying a de novo frameshift mutation of FOXC2 who presented a prepubertal onset of lower limbs lymphedema and mild distichiasis associated with other anomalies such as webbing neck and ptosis.
Keywords: Abnormalities, Multiple; Adolescent; Eye Abnormalities; Eyelashes; Face; Forkhead Transcription Factors; Frameshift Mutation; Humans; Lymphedema; Male; Syndrome

Circulating levels of frizzled-related protein (FRZB) are increased in patients with early rheumatoid arthritis and decrease in response to disease-modifying antirheumatic drugs. - Corallini, Federica; Secchiero, Paola; Castellino, Gabriella; Montecucco, Maurizio; Trotta, Francesco; Zauli, Giorgio (Ann Rheum Dis, 2010)
Keywords: Antirheumatic Agents; Arthritis, Rheumatoid; Biological Markers; Glycoproteins; Humans

Defective FOXP3 expression in patients with acute Kawasaki disease and restoration by intravenous immunoglobulin therapy. - Olivito, Biagio; Taddio, Andrea; Simonini, Gabriele; Massai, Cristina; Ciullini, Sara; Gambineri, Eleonora; de Martino, Maurizio; Azzari, Chiara; Cimaz, Rolando (Clin Exp Rheumatol, 2010)
OBJECTIVES: The aims of this study were: 1) to investigate forkhead box P3 (FOXP3) expression in patients with Kawasaki disease (KD), exploring possible differences during the acute phase and after defervescence; 2) to evaluate a possible association of the FOXP3 single nucleotide polymorphism (SNP) 543 (SNP ID: rs2232367) with KD. METHODS: FOXP3 expression was evaluated on 8 children with KD and 15 healthy children by flow cytometry and Real-Time polymerase chain reaction (RT-PCR). FOXP3 SNP 543 was genotyped by denaturing high-performance liquid chromatography (DHPLC) and sequencing on DNA samples from 58 additional children with KD and 114 healthy donors. RESULTS: The frequencies of CD4+CD25 +FOXP3+ regulatory T cells were significantly (p=0.0002) lower during the acute phase of KD than in sex- and age-matched healthy donors (median % + SD: 4.8+/-1.3 vs. 7.7+/-1.7) and a similar tendency was revealed for FOXP3 mRNA transcripts (p<0.0001). FOXP3 expression increased significantly, at both protein and mRNA levels, after intravenous immunoglobulin (IVIG) therapy treatment and achieving complete remission of disease (at least 48 hrs; median 9.5 days, range 2-30). Of the 58 patients screened, only one female subject (1.7%) carried the presence of 543 SNP in heterozygosis (C>T; for a total of 1 allele out of 88), with no difference between KD patients and controls (0.0%, 0/203 alleles). CONCLUSIONS: Our data reinforce the notion of an impaired immunoregulation in KD, suggesting also a role of IVIG treatment in modifying the Treg compartment. FOXP3 SNP 543 does not seem to be involved in susceptibility to KD in Italian children.
Keywords: Acute Disease; Child; Child, Preschool; Female; Flow Cytometry; Forkhead Transcription Factors; Genotype; Humans; Immunoglobulins, Intravenous; Infant; Italy; Male; Mucocutaneous Lymph Node Syndrome; Polymorphism, Single Nucleotide; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; T-Lymphocytes, Regulatory

Determinants of nosocomial infection in 6 neonatal intensive care units: an Italian multicenter prospective cohort study. - Auriti, Cinzia; Ronchetti, Maria Paola; Pezzotti, Patrizio; Marrocco, Gabriella; Quondamcarlo, Anna; Seganti, Giulio; Bagnoli, Francesco; De Felice, Claudio; Buonocore, Giuseppe; Arioni, Cesare; Serra, Giovanni; Bacolla, Gianfranco; et al. (Infect Control Hosp Epidemiol, 2010)
BACKGROUND: Nosocomial infections are still a major cause of morbidity and mortality among neonates admitted to neonatal intensive care units (NICUs). OBJECTIVE: To describe the epidemiology of nosocomial infections in NICUs and to assess the risk of nosocomial infection related to the therapeutic procedures performed and to the clinical characteristics of the neonates at birth and at admission to the NICU, taking into account the time between the exposure and the onset of infection. DESIGN: A multicenter, prospective cohort study. PATIENTS AND SETTING: A total of 1,692 neonates admitted to 6 NICUs in Italy were observed and monitored for the development of nosocomial infection during their hospital stay. METHODS: Data were collected on the clinical characteristics of the neonates admitted to the NICUs, their therapeutic interventions and treatments, their infections, and their mortality rate. The cumulative probability of having at least 1 infection and the cumulative probability of having at least 1 infection or dying were estimated. The hazard ratio (HR) for the first infection and the HR for the first infection or death were also estimated. RESULTS: A total of 255 episodes of nosocomial infection were diagnosed in 217 neonates, yielding an incidence density of 6.9 episodes per 1,000 patient-days. The risk factors related to nosocomial infection in very-low-birth-weight neonates were receipt of continuous positive airway pressure (HR, 3.8 [95% confidence interval CI, 1.7-8.1]), a Clinical Risk Index for Babies score of 4 or greater (HR, 2.2 [95% CI, 1.4-3.4]), and a gestational age of less than 28 weeks (HR, 2.1 [95% CI, 1.2-3.8]). Among heavier neonates, the risk factors for nosocomial infection were receipt of parenteral nutrition (HR, 8.1 [95% CI, 3.2-20.5]) and presence of malformations (HR, 2.3 [95% CI, 1.5-3.5]). CONCLUSIONS: Patterns of risk factors for nosocomial infection differ between very-low-birth-weight neonates and heavier neonates. Therapeutic procedures appear to be strong determinants of nosocomial infection in both groups of neonates, after controlling for clinical characteristics.
Keywords: Bacteremia; Birth Weight; Cross Infection; Gestational Age; Hospitals, University; Humans; Incidence; Infant, Newborn; Infant, Very Low Birth Weight; Intensive Care Units, Neonatal; Italy; Length of Stay; Proportional Hazards Models; Prospective Studies; Risk Factors; Sepsis; Time Factors

Development of paediatric quality of inpatient care indicators for low-income countries - A Delphi study. - Ntoburi, Stephen; Hutchings, Andrew; Sanderson, Colin; Carpenter, James; Weber, Martin; English, Mike (BMC Pediatr, 2010)
BACKGROUND: Indicators of quality of care for children in hospitals in low-income countries have been proposed, but information on their perceived validity and acceptability is lacking. METHODS: Potential indicators representing structural and process aspects of care for six common conditions were selected from existing, largely qualitative WHO assessment tools and guidelines. We employed the Delphi technique, which combines expert opinion and existing scientific information, to assess their perceived validity and acceptability. Panels of experts, one representing an international panel and one a national (Kenyan) panel, were asked to rate the indicators over 3 rounds and 2 rounds respectively according to a variety of attributes. RESULTS: Based on a pre-specified consensus criteria most of the indicators presented to the experts were accepted: 112/137(82%) and 94/133(71%) for the international and local panels respectively. For the other indicators there was no consensus; none were rejected. Most indicators were rated highly on link to outcomes, reliability, relevance, actionability and priority but rated more poorly on feasibility of data collection under routine conditions. There was moderate to substantial agreement between the two panels of experts. CONCLUSIONS: This Delphi study provided evidence for the perceived usefulness of most of a set of measures of quality of hospital care for children proposed for use in low-income countries. However, both international and local experts expressed concerns that data for many process-based indicators may not currently be available. The feasibility of widespread quality assessment and responsiveness of indicators to intervention should be examined as part of continued efforts to improve approaches to informative hospital quality assessment.
Keywords: Child; Child, Hospitalized; Delphi Technique; Developing Countries; Expert Testimony; Female; Humans; Inpatients; Male; Pediatrics; Quality Indicators, Health Care; World Health Organization

Eltrombopag for the treatment of the inherited thrombocytopenia deriving from MYH9 mutations. - Pecci, Alessandro; Gresele, Paolo; Klersy, Catherine; Savoia, Anna; Noris, Patrizia; Fierro, Tiziana; Bozzi, Valeria; Mezzasoma, Anna Maria; Melazzini, Federica; Balduini, Carlo L (Blood, 2010)
Platelet transfusion is currently the primary medical treatment for reducing thrombocytopenia in patients with inherited thrombocytopenias. To evaluate whether stimulating megakaryopoiesis could increase platelet count in these conditions, we treated patients with a severe thrombocytopenia induced by MYH9 mutations (MYH9-related disease) with a nonpeptide thrombopoietin receptor agonist, eltrombopag. Twelve adult patients with MYH9-RD and platelet counts of less than 50 × 10(9)/L received 50 mg of eltrombopag orally per day for 3 weeks. Patients who achieved a platelet count higher than 150 × 10(9)/L stopped therapy, those with 100 to 150 platelets × 10(9)/L continued treatment at the same eltrombopag dose for 3 additional weeks, while those with less than 100 platelets × 10(9)/L increased the eltrombopag dose to 75 mg for 3 weeks. Major responses (platelet count of at least 100 × 10(9)/L or 3 times the baseline value) were obtained in 8 patients, minor responses (platelet counts at least twice the baseline value) in 3. One patient did not respond. Bleeding tendency disappeared in 8 of 10 patients with bleeding symptoms at baseline. Mild adverse events were reported in 2 patients. The availability of thrombopoietin mimetics opened new prospects in the treatment of inherited thrombocytopenias. This study is registered at www.clinicaltrials.gov as NCT01133860 (European Union Drug Regulating Authorities Clinical Trials number 2008-001903-42).
Keywords: Administration, Oral; Adolescent; Adult; Benzoates; Dose-Response Relationship, Drug; Female; Genetic Predisposition to Disease; Humans; Hydrazines; Male; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Platelet Aggregation; Platelet Count; Pyrazoles; Receptors, Thrombopoietin; Survival Rate; Thrombocytopenia; Treatment Outcome; Young Adult

Epidemiological and molecular assessment of a rubella outbreak in North-Eastern Italy. - D'Agaro, Pierlanfranco; Dal Molin, Gianna; Zamparo, Emanuela; Rossi, Tatiana; Micuzzo, Michele; Busetti, Marina; Santon, Daniela; Campello, Cesare (J Med Virol, 2010)
From January to June 2008, a rubella outbreak involving 111 laboratory confirmed cases occurred in the Friuli Venezia Giulia (FVG) region of North-Eastern Italy. The outbreak occurred initially in two residential homes for young adults disabled mentally and physically. Subsequently, the epidemic spread to the general population. Young adult cohorts were mostly affected and the mean age of the patients was 26.8 years; the majority of cases were male (73.8%), with a mean age of 26.6 years in males and 27.4 in females. Three pregnant women had a primary infection and two had their pregnancies terminated. Genotyping of 16 isolates showed the circulation of RUBV 2B, a genotype originating from Asia and South Africa and now present in Europe. In addition, molecular analysis revealed a well defined space-temporal spread of two viruses showing distinct sequences. A seroepidemiological survey carried out in a city within the same geographical area showed that the proportion of women of childbearing age still susceptible to rubella virus was 5.5%, fairly close to the figure (<5%) expected by 2010.
Keywords: Adolescent; Adult; Antibodies, Viral; Disease Outbreaks; Epidemics; Female; Genotype; Humans; Immunoglobulin G; Italy; Male; Pregnancy; Pregnancy Complications, Infectious; Rubella; Rubella virus; Young Adult

EULAR/PRINTO/PRES criteria for Henoch-Schönlein purpura, childhood polyarteritis nodosa, childhood Wegener granulomatosis and childhood Takayasu arteritis: Ankara 2008. Part I: Overall methodology and clinical characterisation. - Ruperto, Nicolino; Ozen, Seza; Pistorio, Angela; Dolezalova, Pavla; Brogan, Paul; Cabral, David A; Cuttica, Ruben; Khubchandani, Raju; Lovell, Daniel J; O'Neil, Kathleen M; Quartier, Pierre; Ravelli, Angelo; et al. (Ann Rheum Dis, 2010)
OBJECTIVES: To report methodology and overall clinical, laboratory and radiographic characteristics for Henoch-Schönlein purpura (HSP), childhood polyarteritis nodosa (c-PAN), c-Wegener granulomatosis (c-WG) and c-Takayasu arteritis (c-TA) classification criteria. METHODS: The preliminary Vienna 2005 consensus conference, which proposed preliminary criteria for paediatric vasculitides, was followed by a EULAR/PRINTO/PRES - supported validation project divided into three main steps. Step 1: retrospective/prospective web-data collection for HSP, c-PAN, c-WG and c-TA, with age at diagnosis <or=18 years. Step 2: blinded classification by consensus panel of a subgroup of 280 cases (128 difficult cases, 152 randomly selected) enabling expert diagnostic verification. Step 3: Ankara 2008 Consensus Conference and statistical evaluation (sensitivity, specificity, area under the curve, kappa-agreement) using as 'gold standard' the final consensus classification or original treating physician diagnosis. RESULTS: A total of 1183/1398 (85%) samples collected were available for analysis: 827 HSP, 150 c-PAN, 60 c-WG, 87 c-TA and 59 c-other. Prevalence, signs/symptoms, laboratory, biopsy and imaging reports were consistent with the clinical picture of the four c-vasculitides. A representative subgroup of 280 patients was blinded to the treating physician diagnosis and classified by a consensus panel, with a kappa-agreement of 0.96 for HSP (95% CI 0.84 to 1), 0.88 for c-WG (95% CI 0.76 to 0.99), 0.84 for c-TA (95% CI 0.73 to 0.96) and 0.73 for c-PAN (95% CI 0.62 to 0.84), with an overall kappa of 0.79 (95% CI 0.73 to 0.84). CONCLUSION: EULAR/PRINTO/PRES propose validated classification criteria for HSP, c-PAN, c-WG and c-TA, with substantial/almost perfect agreement with the final consensus classification or original treating physician diagnosis.
Keywords: Adolescent; Biopsy; Child; Delphi Technique; Granulomatosis with Polyangiitis; Humans; International Cooperation; Internet; Polyarteritis Nodosa; Purpura, Schoenlein-Henoch; Reproducibility of Results; Takayasu Arteritis

Expression and association data strongly support JARID2 involvement in nonsyndromic cleft lip with or without cleft palate. - Scapoli, Luca; Martinelli, Marcella; Pezzetti, Furio; Palmieri, Annalisa; Girardi, Ambra; Savoia, Anna; Bianco, Anna Monica; Carinci, Francesco (Hum Mutat, 2010)
Nonsyndromic cleft lip with or without cleft palate (CL/P) affects approximately 1 in 1,000 births. Genetic studies have provided evidence for the role of several genes and candidate loci in clefting; however, conflicting results have frequently been obtained and much have to be done to unravel the complex genetics of CL/P. In the present investigation we have focused on the candidate region in 6p23, a region that have been found linked to CL/P in several investigations, in the attempt to find out the susceptibility gene provisionally named OFC1. Gene expression experiments in mice embryo of positional candidate genes revealed that JARID2 was highly and specifically expressed in epithelial cells in merging palatal shelves. A family-based linkage disequilibrium study confirmed the pivotal role of JARID2 in orofacial development and strongly supports a role for this gene in CL/P etiology (multiallelic haplotype test P=6 x 10(-5)). Understanding the molecular role of JARID2 within facial development may offer additional information to further unravel the complex genetics of CL/P.
Keywords: Animals; Cleft Lip; Cleft Palate; DNA Mutational Analysis; Family Health; Female; Gene Expression; Gene Expression Regulation, Developmental; Genetic Predisposition to Disease; Haplotypes; Humans; In Situ Hybridization; Linkage Disequilibrium; Male; Mice; Mice, Inbred C57BL; Mutation; Nerve Tissue Proteins; Palate; Polycomb Repressive Complex 2; Polymorphism, Single Nucleotide; Pregnancy; Reverse Transcriptase Polymerase Chain Reaction

First case in Italy of acquired resistance to oseltamivir in an immunocompromised patient with influenza A/H1N1v infection. - Campanini, Giulia; Piralla, Antonio; Rovida, Francesca; Puzelli, Simona; Facchini, Marzia; Locatelli, Franco; Minoli, Lorenzo; Percivalle, Elena; Donatelli, Isabella; Baldanti, Fausto (J Clin Virol, 2010)
A pandemic influenza A/H1N1v strain with the neuraminidase H274Y mutation was detected in nasal secretions of a 2-year-old leukemic patient with influenza-like illness after 18 days of treatment with oseltamivir. At baseline, no drug-resistant virus was found, while 4 days after treatment initiation a mixture of wild-type and mutated virus was detected. After treatment interruption, the wild type influenza virus re-emerged and became prevalent in nasal secretions after a few days, suggesting the lower fitness of the mutated virus strain. The patient slowly improved concurrently with a decrease in virus load, which resulted negative 42 days after diagnosis. No other drug-resistant influenza A/H1N1v virus strains have been detected in Italy (up to the end of November 2009) since the first case of the novel A/H1N1v virus was identified in the country (May 2009).
Keywords: Amino Acid Substitution; Antiviral Agents; Bodily Secretions; Child, Preschool; Drug Resistance, Viral; Female; Humans; Immunocompromised Host; Influenza A Virus, H1N1 Subtype; Influenza, Human; Italy; Molecular Sequence Data; Mutation, Missense; Neuraminidase; Nose; Oseltamivir; RNA, Viral; Sequence Analysis, DNA; Treatment Outcome; Viral Load; Viral Proteins; Withholding Treatment

A G to C transversion at the last nucleotide of exon 25 of the MYH9 gene results in a missense mutation rather than in a splicing defect. - Vettore, Silvia; De Rocco, Daniela; Gerber, Bernhard; Scandellari, Raffaella; Bianco, Anna Monica; Balduini, Carlo L; Pecci, Alessandro; Fabris, Fabrizio; Savoia, Anna (Eur J Med Genet, 2010)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant disorder caused by mutations in MYH9, the gene encoding the heavy chain of non-muscle myosin IIA. Patients present with congenital macrothrombocytopenia and inclusion bodies in neutrophils and might develop sensorineural deafness, presenile cataract, and/or progressive nephropathy leading to end-stage renal failure. In two families with macrothrombocytopenia we identified a novel c.3485G > C mutation in the last nucleotide of exon 25. Bioinformatic tools for splice site prediction and minigene functional test predicted splicing anomalies of exon 25. However, analysis of RNA purified from patient's peripheral blood did not allowed us to detect any anomalies, suggesting that RNA processing is correct at least in this tissue. Therefore, we concluded that c.3485G > C leads to a novel missense mutation (p.Arg1162Thr) of myosin-9, which resulted to be slightly degraded in patient platelets. A precise definition of the effect of mutations is fundamental to improve our knowledge into the pathogenetic mechanisms responsible for the disease.
Keywords: Adolescent; Adult; Blood Platelets; Computational Biology; Exons; Female; Humans; Inclusion Bodies; Kidney Failure, Chronic; Molecular Motor Proteins; Mutation, Missense; Myosin Heavy Chains; Neutrophils; Nonmuscle Myosin Type IIA; Nucleotides; RNA Splicing; Thrombocytopenia

Genetic polymorphism of inosine-triphosphate-pyrophosphatase influences mercaptopurine metabolism and toxicity during treatment of acute lymphoblastic leukemia individualized for thiopurine-S-methyl-transferase status. - Stocco, Gabriele; Crews, Kristine R; Evans, William E (Expert Opin Drug Saf, 2010)
IMPORTANCE OF THE FIELD: Although genetic polymorphisms in the gene encoding human thiopurine methyltransferase (TPMT) are known to have a marked effect on mercaptopurine metabolism and toxicity, there are many patients with wild-type TPMT who develop toxicity. Furthermore, when mercaptopurine dosages are adjusted in patients who are heterozygous at the TPMT locus, there are still some patients who develop toxicity for reasons that are not fully understood. Therefore, we recently studied the effects of a common polymorphism in another gene encoding an enzyme involved in mercaptopurine metabolism (SNP rs1127354 in inosine-triphospate-pyrophosphatase, ITPA), showing that genetic polymorphism of ITPA is a significant determinant of mercaptopurine metabolism and of febrile neutropenia following combination chemotherapy of acute lymphoblastic leukemia (ALL) in which mercaptopurine doses are individualized based on TPMT genotype. AREA COVERED IN THIS REVIEW: In this review, we summarize the knowledge available about the effect and clinical relevance of TPMT and ITPA on mercaptopurine pharmacogenomics, with a particular focus on the use of this medication in pediatric patients with ALL. WHAT THE READER WILL GAIN: Reader will gain insights into: i) the effects of pharmacogenomic traits on mercaptopurine toxicity and efficacy for the treatment of ALL and ii) individualization strategies that can be used to mitigate toxicity without compromising efficacy in pediatric patients with ALL. TAKE HOME MESSAGE: Mercaptopurine dose can be adjusted on the basis of TPMT genotype to mitigate toxicity in pediatric patients with ALL. As treatment is individualized in this way for the most relevant genetic determinant of drug response (i.e., for mercaptopurine, TPMT), the importance of other genetic polymorphisms emerges (e.g., ITPA).
Keywords: 6-Mercaptopurine; Antineoplastic Combined Chemotherapy Protocols; Child; Humans; Individualized Medicine; Methyltransferases; Models, Biological; Neutropenia; Nucleotide Transport Proteins; Polymorphism, Genetic; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Pyrophosphatases

High polymorphism of the MBL2 gene in patients with atopic dermatitis. - Carréra, Matilde Campos; Moura, Patrícia; Crovella, Sergio; de Souza, Paulo Roberto Eleutério; de Alencar, Luiz Cláudio Arraes; Sarinho, Emanuel (Ann Allergy Asthma Immunol, 2010)
BACKGROUND: Low serum levels of mannose-binding lectin (MBL) are determined mainly by variant alleles of the MBL2 gene and it has been suggested that MBL may play a role in the susceptibility to atopic dermatitis (AD). OBJECTIVE: The aim was to investigate the difference of the frequency of MBL2 variant alleles in AD patients and in a group of individuals without AD, and associate the MBL2 alleles with AD severity. METHODS: MBL2 variant allele's frequency was investigated in 131 children with AD and 165 healthy children/adolescents matched by convenience. The severity of disease was graded according to the SCORing Atopic Dermatitis (SCORAD) index. The first exon variants were called "O" and the wild type "A". The variants in the promoter were H/L at -550 and X/Y at -221, determined by Real Time PCR. RESULTS: Children with AD had higher frequency of allele O and the genotypes related to low or deficient levels of MBL, when compared to the healthy group (p = 0.0012 and p < 0.001, respectively), but not with AD severity. CONCLUSION: Low or deficient MBL serum levels determined genetically may contribute to the predisposition for AD, but not for disease severity.
Keywords: Adolescent; Alleles; Child; Child, Preschool; Dermatitis, Atopic; Disease Progression; Female; Genetic Predisposition to Disease; Genotype; Humans; Infant; Male; Mannose-Binding Lectin; Polymorphism, Genetic; Promoter Regions, Genetic

Histatins in non-human primates: gene variations and functional effects. - Padovan, Lara; Segat, Ludovica; Pontillo, Alessandra; Antcheva, Nikolinka; Tossi, Alessandro; Crovella, Sergio (Protein Pept Lett, 2010)
Human histatins are histidine-rich, low molecular weight salivary proteins that contribute to the immune system of the oral cavity. In this work, nucleotide sequences of the HIS1 (coding for histatin 1) and HIS2 (coding for histatin 3) genes, homologous to the human ones, have been sequenced and analysed in five primates species including Great Ape, Hylobatidae and Cercopithecidae. In HIS1, the region corresponding to the putative mature peptide shows a premature stop codon in Macaca and Cercopithecus, while HIS2 a six codon insertion in the Cercopithecidae. Histatin 5, a 24-residue peptide derived from histatin 3, is the most antimicrobially active among human histatins, thus macaque and nomascus orthologues of histatin 5 were selected for chemical synthesis and functional characterization, in comparison to the human peptide. All synthesized histatins are predicted to be poorly amphipathic, depending on the charged state of His residues and assume partially a-helical conformations only in lipophilic conditions. Antimicrobial assays against Candida and Criptococcus spp. indicate somewhat different spectra of in vitro activity against the tested fungi. We have described HIS1 and HIS2 gene variations in primates and have analysed their functional effects on selected Hst5 orthologues. The human antimicrobial peptide has been proposed to represent an important lead for new generation of antimicrobial compounds for the treatment of oral mycoses, thus the information from the non-human primates histatins studied may aid strategies for drugs design.
Keywords: Amino Acid Sequence; Animals; Anti-Infective Agents; Base Sequence; Candida; Catarrhini; Cell Proliferation; Computational Biology; Cryptococcus; Genetic Variation; Histatins; Humans; Molecular Sequence Data; Phylogeny; Sequence Alignment; Sequence Analysis, DNA

HLA-G*0105N allele is associated with augmented risk for HIV infection in white female patients. - Segat, Ludovica; Catamo, Eulalia; Fabris, Annalisa; Morgutti, Marcello; D'Agaro, Pierlanfranco; Campello, Cesare; Crovella, Sergio (AIDS, 2010)
We analyzed HLA-G 3777G > C, HLA-G 14 bp deletion/insertion and HLA-G*0105N polymorphisms in HIV-positive white adult participants, infected through horizontal heterosexual transmission, and unexposed uninfected individuals, all from north eastern Italy. We report a new association between the HLA-G*0105N allele and HIV infection in adult white female participants, being HLA-G*0105N null allele correlated with an augmented risk (odds ratio = 4.35, 95% confidence interval = 1.38-18.07, P = 0.005) for HIV infection.
Keywords: Adolescent; Adult; Aged; Female; Genetic Predisposition to Disease; Histocompatibility Antigens Class I; HIV Infections; HIV-1; Humans; Middle Aged; Polymorphism, Genetic; Young Adult

Methotrexate withdrawal at 6 vs 12 months in juvenile idiopathic arthritis in remission: a randomized clinical trial. - Foell, Dirk; Wulffraat, Nico; Wedderburn, Lucy R; Wittkowski, Helmut; Frosch, Michael; Gerss, Joachim; Stanevicha, Valda; Mihaylova, Dimitrina; Ferriani, Virginia; Tsakalidou, Florence Kanakoudi; Foeldvari, Ivan; Cuttica, Ruben; et al. (JAMA, 2010)
CONTEXT: Novel therapies have improved the remission rate in chronic inflammatory disorders including juvenile idiopathic arthritis (JIA). Therefore, strategies of tapering therapy and reliable parameters for detecting subclinical inflammation have now become challenging questions. OBJECTIVES: To analyze whether longer methotrexate treatment during remission of JIA prevents flares after withdrawal of medication and whether specific biomarkers identify patients at risk for flares. DESIGN, SETTING, AND PATIENTS: Prospective, open, multicenter, medication-withdrawal randomized clinical trial including 364 patients (median age, 11.0 years) with JIA recruited in 61 centers from 29 countries between February 2005 and June 2006. Patients were included at first confirmation of clinical remission while continuing medication. At the time of therapy withdrawal, levels of the phagocyte activation marker myeloid-related proteins 8 and 14 heterocomplex (MRP8/14) were determined. INTERVENTION: Patients were randomly assigned to continue with methotrexate therapy for either 6 months (group 1 [n = 183]) or 12 months (group 2 [n = 181]) after induction of disease remission. MAIN OUTCOME MEASURES: Primary outcome was relapse rate in the 2 treatment groups; secondary outcome was time to relapse. In a prespecified cohort analysis, the prognostic accuracy of MRP8/14 concentrations for the risk of flares was assessed. RESULTS: Intention-to-treat analysis of the primary outcome revealed relapse within 24 months after the inclusion into the study in 98 of 183 patients (relapse rate, 56.7%) in group 1 and 94 of 181 (55.6%) in group 2. The odds ratio for group 1 vs group 2 was 1.02 (95% CI, 0.82-1.27; P = .86). The median relapse-free interval after inclusion was 21.0 months in group 1 and 23.0 months in group 2. The hazard ratio for group 1 vs group 2 was 1.07 (95% CI, 0.82-1.41; P = .61). Median follow-up duration after inclusion was 34.2 and 34.3 months in groups 1 and 2, respectively. Levels of MRP8/14 during remission were significantly higher in patients who subsequently developed flares (median, 715 [IQR, 320-1 110] ng/mL) compared with patients maintaining stable remission (400 [IQR, 220-800] ng/mL; P = .003). Low MRP8/14 levels indicated a low risk of flares within the next 3 months following the biomarker test (area under the receiver operating characteristic curve, 0.76; 95% CI, 0.62-0.90). CONCLUSIONS: In patients with JIA in remission, a 12-month vs 6-month withdrawal of methotrexate did not reduce the relapse rate. Higher MRP8/14 concentrations were associated with risk of relapse after discontinuing methotrexate. TRIAL REGISTRATION: isrctn.org Identifier: ISRCTN18186313.
Keywords: Adolescent; Antirheumatic Agents; Arthritis, Juvenile; ATP-Binding Cassette Transporters; Calgranulin B; Child; Child, Preschool; Female; Humans; Infant; Male; Methotrexate; Predictive Value of Tests; Prospective Studies; Recurrence; Remission Induction

Molecular surveillance of pandemic influenza A(H1N1) viruses circulating in Italy from May 2009 to February 2010: association between haemagglutinin mutations and clinical outcome. - Puzelli, S; Facchini, M; De Marco, M A; Palmieri, A; Spagnolo, D; Boros, S; Corcioli, F; Trotta, D; Bagnarelli, P; Azzi, A; Cassone, A; Rezza, G; et al. (Euro Surveill, 2010)
Haemagglutinin sequences of pandemic influenza A(H1N1) viruses circulating in Italy were examined, focusing on amino acid changes at position 222 because of its suggested pathogenic relevance. Among 169 patients, the D222G substitution was detected in three of 52 (5.8%) severe cases and in one of 117 (0.9%) mild cases, whereas the D222E mutation was more frequent and evenly distributed in mild (31.6%) and severe cases (38.4%). A cluster of D222E viruses among school children confirms reported human-to-human transmission of viruses mutated at amino acid position 222.
Keywords: Adolescent; Adult; Age Distribution; Aged; Amino Acid Substitution; Child; Child, Preschool; Female; Hemagglutinins; Humans; Infant; Influenza A Virus, H1N1 Subtype; Influenza, Human; Italy; Male; Middle Aged; Mutation; Pandemics; Population Surveillance; Reverse Transcriptase Polymerase Chain Reaction; Severity of Illness Index; Sex Distribution; Young Adult

MYH9-related disease: Report on five German families and description of a novel mutation. - Savoia, Anna; Germeshausen, Manuela; De Rocco, Daniela; Henschel, Bettina; Kratz, Christian P; Kuhlen, Michaela; Rath, Bettina; Steuhl, Klaus-Peter; Wermes, Cornelia; Ballmaier, Matthias (Ann Hematol, 2010)
Keywords: Adult; Aged; Child; Chromosome Disorders; DNA Mutational Analysis; Germany; Humans; Infant; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Young Adult

Pharmacogenomics in pediatric leukemia. - Paugh, Steven W; Stocco, Gabriele; Evans, William E (Curr Opin Pediatr, 2010)
PURPOSE OF REVIEW: The therapeutic index of many medications, especially in children, is very narrow with substantial risk for toxicity at doses required for therapeutic effects. This is particularly relevant to cancer chemotherapy, when the risk of toxicity must be balanced against potential suboptimal (low) systemic exposure that can be less effective in patients with higher rates of drug clearance. The purpose of this review is to discuss genetic factors that lead to interpatient differences in the pharmacokinetics and pharmacodynamics of these medications. RECENT FINDINGS: Genome-wide agonistic studies of pediatric patient populations are revealing genome variations that may affect susceptibility to specific diseases and that influence the pharmacokinetic and pharmacodynamic characteristics of medications. Several genetic factors with relatively small effect may be combined in the determination of a pharmacogenomic phenotype and considering these polygenic models may be mandatory in order to predict the related drug response phenotypes. These findings have potential to yield new insights into disease pathogenesis, and lead to molecular diagnostics that can be used to optimize the treatment of childhood cancers. SUMMARY: Advances in genome technology, and their comprehensive and systematic deployment to elucidate the genomic basis of interpatient differences in drug response and disease risk, hold great promise to ultimately enhance the efficacy and reduce the toxicity of drug therapy in children.
Keywords: Antineoplastic Agents; Child; Genetic Predisposition to Disease; Genetic Testing; Humans; Individualized Medicine; Pharmacogenetics; Phenotype; Precursor Cell Lymphoblastic Leukemia-Lymphoma

Predictors of poor response to methotrexate in polyarticular-course juvenile idiopathic arthritis: analysis of the PRINTO methotrexate trial. - Vilca, Iris; Munitis, Pablo Garcia; Pistorio, Angela; Ravelli, Angelo; Buoncompagni, Antonella; Bica, Blanca; Campos, Lucia; Häfner, Renate; Hofer, Michael; Ozen, Seza; Huemer, Christian; Bae, Sang Cheol; et al. (Ann Rheum Dis, 2010)
OBJECTIVES: To determine whether baseline demographic, clinical, articular and laboratory variables predict methotrexate (MTX) poor response in polyarticular-course juvenile idiopathic arthritis. METHODS: Patients newly treated for 6 months with MTX enrolled in the Paediatric Rheumatology International Trials Organization (PRINTO) MTX trial. Bivariate and logistic regression analyses were used to identify baseline predictors of poor response according to the American College of Rheumatology pediatric (ACR-ped) 30 and 70 criteria. RESULTS: In all, 405/563 (71.9%) of patients were women; median age at onset and disease duration were 4.3 and 1.4 years, respectively, with anti-nuclear antibody (ANA) detected in 259/537 (48.2%) patients. With multivariate logistic regression analysis, the most important determinants of ACR-ped 70 non-responders were: disease duration > 1.3 years (OR 1.93), ANA negativity (OR 1.77), Childhood Health Assessment Questionnaire (CHAQ) disability index > 1.125 (OR 1.65) and the presence of right and left wrist activity (OR 1.55). Predictors of ACR-ped 30 non-responders were: ANA negativity (OR 1.92), CHAQ disability index > 1.14 (OR 2.18) and a parent's evaluation of child's overall well-being < or = 4.69 (OR 2.2). CONCLUSION: The subgroup of patients with longer disease duration, ANA negativity, higher disability and presence of wrist activity were significantly associated with a poorer response to a 6-month MTX course.
Keywords: Adolescent; Antibodies, Antinuclear; Antirheumatic Agents; Arthritis, Juvenile; Child; Child, Preschool; Disability Evaluation; Female; Follow-Up Studies; Humans; Immunosuppressive Agents; Male; Methotrexate; Prognosis; Treatment Outcome

Severe X-linked mitochondrial encephalomyopathy associated with a mutation in apoptosis-inducing factor. - Ghezzi, Daniele; Sevrioukova, Irina; Invernizzi, Federica; Lamperti, Costanza; Mora, Marina; d'Adamo, Pio; Novara, Francesca; Zuffardi, Orsetta; Uziel, Graziella; Zeviani, Massimo (Am J Hum Genet, 2010)
We investigated two male infant patients who were given a diagnosis of progressive mitochondrial encephalomyopathy on the basis of clinical, biochemical, and morphological features. These patients were born from monozygotic twin sisters and unrelated fathers, suggesting an X-linked trait. Fibroblasts from both showed reduction of respiratory chain (RC) cIII and cIV, but not of cI activities. We found a disease-segregating mutation in the X-linked AIFM1 gene, encoding the Apoptosis-Inducing Factor (AIF) mitochondrion-associated 1 precursor that deletes arginine 201 (R201 del). Under normal conditions, mature AIF is a FAD-dependent NADH oxidase of unknown function and is targeted to the mitochondrial intermembrane space (this form is called AIF(mit)). Upon apoptogenic stimuli, a soluble form (AIF(sol)) is released by proteolytic cleavage and migrates to the nucleus, where it induces "parthanatos," i.e., caspase-independent fragmentation of chromosomal DNA. In vitro, the AIF(R201 del) mutation decreases stability of both AIF(mit) and AIF(sol) and increases the AIF(sol) DNA binding affinity, a prerequisite for nuclear apoptosis. In AIF(R201 del) fibroblasts, staurosporine-induced parthanatos was markedly increased, whereas re-expression of AIF(wt) induced recovery of RC activities. Numerous TUNEL-positive, caspase 3-negative nuclei were visualized in patient #1's muscle, again indicating markedly increased parthanatos in the AIF(R201 del) critical tissues. We conclude that AIF(R201 del) is an unstable mutant variant associated with increased parthanatos-linked cell death. Our data suggest a role for AIF in RC integrity and mtDNA maintenance, at least in some tissues. Interestingly, riboflavin supplementation was associated with prolonged improvement of patient #1's neurological conditions, as well as correction of RC defects in mutant fibroblasts, suggesting that stabilization of the FAD binding in AIF(mit) is beneficial.
Keywords: Apoptosis; Apoptosis Inducing Factor; Caspase 3; Computer Simulation; Dietary Supplements; DNA Primers; DNA, Mitochondrial; Electron Transport; Female; Fibroblasts; Flavin-Adenine Dinucleotide; Genes, X-Linked; Humans; In Situ Nick-End Labeling; Infant, Newborn; Magnetic Resonance Imaging; Male; Mitochondrial Encephalomyopathies; Muscle, Skeletal; Mutation; Nervous System Diseases; Pedigree; Poly(ADP-ribose) Polymerases; Protein Conformation; Riboflavin; Staurosporine; Twins, Monozygotic

Splenomegaly as presentation of a wandering spleen. - Maschio, Massimo; Cozzi, Giorgio; Sanabor, Daniela; Zennaro, Floriana; Gloria, Pelizzo; Barbi, Egidio (J Pediatr, 2010)
Keywords: Child; Female; Humans; Splenomegaly; Wandering Spleen

State of the art and recommendations. Kangaroo mother care: application in a high-tech environment. - Nyqvist, K H; Anderson, G C; Bergman, N; Cattaneo, A; Charpak, N; Davanzo, R; Ewald, U; Ludington-Hoe, S; Mendoza, S; Pallás-Allonso, C; Peláez, J G; Sizun, J; et al. (Breastfeed Rev, 2010)
UNLABELLED: Since Kangaroo Mother Care (KMC) was developed in Colombia in the 1970s, two trends in clinical application emerged. In low-income settings, the original KMC modelis implemented. This consists of continuous (24 h/day; 7 days/week) and prolonged mother/parent-infant skin-to-skin contact; early discharge with the infant in the kangaroo position; (ideally) exclusive breastfeeding and, adequate follow up. In affluent settings, intermittent KMC with sessions of one or a few hours skin-to-skin contact for a limited period is common. As a result of the increasing evidence of the benefits of KMC for both infants and families in all intensive care settings, KMC in a high-tech environment was chosen as the topic for the first European Conference on KMC, and the clinical implementation of the KMC modelin all types of settings was discussed at the 7th International Workshop on KMC Kangaroo Mother Care protocols in high-tech Neonatal Intensive Care Units (NICU) should specify criteria for initiation, kangaroo position, transfer to/from KMC, transport in kangaroo position, kangaroo nutrition, parents'role, modification of the NICU environment, performance of care in KMC, and KMCin case of infant instability. CONCLUSION: Implementation of the original KMC method, with continuous skin-to-skin contact whenever possible, is recommended for application in high-tech environments, although scientific evaluation should continue.

State of the art and recommendations. Kangaroo mother care: application in a high-tech environment. - Nyqvist, K H; Anderson, G C; Bergman, N; Cattaneo, A; Charpak, N; Davanzo, R; Ewald, U; Ludington-Hoe, S; Mendoza, S; Pallás-Allonso, C; Peláez, J G; Sizun, J; et al. (Acta Paediatr, 2010)
UNLABELLED: Since Kangaroo Mother Care (KMC) was developed in Colombia in the 1970s, two trends in clinical application emerged. In low income settings, the original KMC model is implemented. This consists of continuous (24 h/day, 7 days/week) and prolonged mother/parent-infant skin-to-skin contact; early discharge with the infant in the kangaroo position; (ideally) exclusive breastfeeding; and, adequate follow-up. In affluent settings, intermittent KMC with sessions of one or a few hours skin-to-skin contact for a limited period is common. As a result of the increasing evidence of the benefits of KMC for both infants and families in all intensive care settings, KMC in a high-tech environment was chosen as the topic for the first European Conference on KMC, and the clinical implementation of the KMC model in all types of settings was discussed at the 7th International Workshop on KMC. Kangaroo Mother Care protocols in high-tech Neonatal Intensive Care Units (NICU) should specify criteria for initiation, kangaroo position, transfer to/from KMC, transport in kangaroo position, kangaroo nutrition, parents' role, modification of the NICU environment, performance of care in KMC, and KMC in case of infant instability. CONCLUSION: Implementation of the original KMC method, with continuous skin-to-skin contact whenever possible, is recommended for application in high-tech environments, although scientific evaluation should continue.
Keywords: Attitude of Health Personnel; Female; Humans; Infant Care; Infant, Newborn; Intensive Care Units, Neonatal; Male; Parent-Child Relations; Practice Guidelines as Topic; Professional-Patient Relations; Role; Skin; Visitors to Patients

[Strategies for cardiovascular prevention in children]. - Spinelli, Angela; Nardone, Paola; Lamberti, Anna; Baglio, Giovanni (G Ital Cardiol (Rome), 2010)
Keywords: Body Mass Index; Cardiovascular Diseases; Child; Diet, Mediterranean; Food Habits; Humans; Life Style; Motor Activity; Obesity; Overweight; Patient Education as Topic; Population Surveillance; Questionnaires; Risk Factors

Structural aspects of plant antimicrobial peptides. - Padovan, Lara; Scocchi, Marco; Tossi, Alessandro (Curr Protein Pept Sci, 2010)
Antimicrobial peptides exert an important role in plant defence and their structure/activity relationship against pathogens is widely described. Although the most striking feature of these antimicrobial peptides is their molecular diversity, they share some common features, such as a relatively low molecular weight, and the presence of a variable number of cysteines residues that contribute to stabilize conserved scaffolds through disulphide bond formation, and can be assigned to different structural classes. Peptides from different classes in some cases act synergistically against pathogens when produced by the same tissue, and contribute to extending defence to a wider range of microbes. In this review we briefly describe the structure of some of the main plant antimicrobial peptide classes: thionins, defensins, lipid transfer proteins, cyclotides and snakins, and how they are reported to contribute to the plant protection. In many cases these antimicrobial peptides show a wider activity spectrum than that suggested by their name, exerting an action also against predatory insects and revealing useful antiviral activities. This extends their interest from defense of important food crops also to the design of novel anti-infective compounds for both pharmaceutical and agricultural applications.
Keywords: Amino Acid Sequence; Antimicrobial Cationic Peptides; Molecular Sequence Data; Plant Proteins; Plants; Sequence Alignment

Therapeutic strategy in p47-phox deficient chronic granulomatous disease presenting as inflammatory bowel disease. - Freudenberg, Folke; Wintergerst, Uwe; Roesen-Wolff, Angela; Albert, Michael H; Prell, Christine; Strahm, Brigitte; Koletzko, Sibylle; Ehl, Stephan; Roos, Dirk; Tommasini, Alberto; Ventura, Alessandro; Belohradsky, Bernd H; et al. (J Allergy Clin Immunol, 2010)
Keywords: Age of Onset; Anti-Bacterial Agents; Antibodies, Monoclonal; Child; Drug Therapy, Combination; Gene Deletion; Granulomatous Disease, Chronic; Humans; Inflammatory Bowel Diseases; Male; NADPH Oxidase; Steroids; Treatment Outcome; Vidarabine

Thirty new loci for age at menarche identified by a meta-analysis of genome-wide association studies. - Elks, Cathy E; Perry, John R B; Sulem, Patrick; Chasman, Daniel I; Franceschini, Nora; He, Chunyan; Lunetta, Kathryn L; Visser, Jenny A; Byrne, Enda M; Cousminer, Diana L; Gudbjartsson, Daniel F; Esko, Tõnu; et al. (Nat Genet, 2010)
To identify loci for age at menarche, we performed a meta-analysis of 32 genome-wide association studies in 87,802 women of European descent, with replication in up to 14,731 women. In addition to the known loci at LIN28B (P = 5.4 × 10⁻⁶⁰) and 9q31.2 (P = 2.2 × 10⁻³³), we identified 30 new menarche loci (all P < 5 × 10⁻⁸) and found suggestive evidence for a further 10 loci (P < 1.9 × 10⁻⁶). The new loci included four previously associated with body mass index (in or near FTO, SEC16B, TRA2B and TMEM18), three in or near other genes implicated in energy homeostasis (BSX, CRTC1 and MCHR2) and three in or near genes implicated in hormonal regulation (INHBA, PCSK2 and RXRG). Ingenuity and gene-set enrichment pathway analyses identified coenzyme A and fatty acid biosynthesis as biological processes related to menarche timing.
Keywords: Adolescent; Aging; Body Height; Body Size; Child; DNA Copy Number Variations; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Inheritance Patterns; Menarche; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Time Factors

Toward a consensus on guiding principles for health systems strengthening. - Swanson, Robert C; Bongiovanni, Annette; Bradley, Elizabeth; Murugan, Varnee; Sundewall, Jesper; Betigeri, Arvind; Nyonator, Frank; Cattaneo, Adriano; Harless, Brandi; Ostrovsky, Andrey; Labonté, Ronald (PLoS Med, 2010)
Keywords: Global Health; Humans; Public Health

Towards universal Kangaroo Mother Care: recommendations and report from the First European conference and Seventh International Workshop on Kangaroo Mother Care. - Nyqvist, K H; Anderson, G C; Bergman, N; Cattaneo, A; Charpak, N; Davanzo, R; Ewald, U; Ibe, O; Ludington-Hoe, S; Mendoza, S; Pallás-Allonso, C; Ruiz Peláez, J G; et al. (Acta Paediatr, 2010)
UNLABELLED: The hallmark of Kangaroo Mother Care (KMC) is the kangaroo position: the infant is cared for skin-to-skin vertically between the mother's breasts and below her clothes, 24 h/day, with father/substitute(s) participating as KMC providers. Intermittent KMC (for short periods once or a few times per day, for a variable number of days) is commonly employed in high-tech neonatal intensive care units. These two modalities should be regarded as a progressive adaptation of the mother-infant dyad, ideally towards continuous KMC, starting gradually and progressively with intermittent KMC. The other components in KMC are exclusive breastfeeding (ideally) and early discharge in kangaroo position with strict follow-up. Current evidence allows the following general statements about KMC in affluent and low-income settings: KMC enhances bonding and attachment; reduces maternal postpartum depression symptoms; enhances infant physiologic stability and reduces pain, increases parental sensitivity to infant cues; contributes to the establishment and longer duration of breastfeeding and has positive effects on infant development and infant/parent interaction. Therefore, intrapartum and postnatal care in all types of settings should adhere to a paradigm of nonseparation of infants and their mothers/families. Preterm/low-birth-weight infants should be regarded as extero-gestational foetuses needing skin-to-skin contact to promote maturation. CONCLUSION: Kangaroo Mother Care should begin as soon as possible after birth, be applied as continuous skin-to-skin contact to the extent that this is possible and appropriate and continue for as long as appropriate.
Keywords: Congresses as Topic; Female; Global Health; Humans; Infant Care; Infant, Newborn; Male; Parent-Child Relations; Practice Guidelines as Topic; Randomized Controlled Trials as Topic; Skin

Transmission of hemagglutinin D222G mutant strain of pandemic (H1N1) 2009 virus. - Puzelli, Simona; Facchini, Marzia; Spagnolo, Domenico; De Marco, Maria A; Calzoletti, Laura; Zanetti, Alessandro; Fumagalli, Roberto; Tanzi, Maria L; Cassone, Antonio; Rezza, Giovanni; Donatelli, Isabella (Emerg Infect Dis, 2010)
A pandemic (H1N1) 2009 virus strain carrying the D222G mutation was identified in a severely ill man and was transmitted to a household contact. Only mild illness developed in the contact, despite his obesity and diabetes. The isolated virus reacted fully with an antiserum against the pandemic vaccine strain.
Keywords: Adult; Amino Acid Substitution; Disease Outbreaks; Hemagglutinin Glycoproteins, Influenza Virus; Humans; Influenza A Virus, H1N1 Subtype; Influenza, Human; Male; Middle Aged; Mutation, Missense; Phylogeny; Retrospective Studies; RNA, Viral; Sequence Analysis, RNA; Severity of Illness Index

Treatment with recombinant tumor necrosis factor-related apoptosis-inducing ligand alleviates the severity of streptozotocin-induced diabetes. - Zauli, Giorgio; Toffoli, Barbara; di Iasio, Maria Grazia; Celeghini, Claudio; Fabris, Bruno; Secchiero, Paola (Diabetes, 2010)
OBJECTIVE: To evaluate the potential therapeutic effect of recombinant human tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) treatment in a model of type 1 diabetes. RESEARCH DESIGN AND METHODS: Recombinant TRAIL was added in vitro to primary human and mouse peripheral blood mononuclear cells (PBMCs) and isolated human islets to evaluate the expression of the immunoregulatory gene SOCS1. Diabetes was induced by five consecutive daily injections of low-concentration (50 mg/kg) streptozotocin (STZ) in C57 black mice (n = 24). A group of these mice (n = 12) was co-injected with recombinant TRAIL (20 microg/day) for 5 days, and the diabetic status (glycemia and body weight) was followed over time. After 6 weeks, circulating levels of insulin, TNF-alpha, and osteoprotegerin (OPG) were measured, and animals were killed to perform the histological analysis of the pancreas. RESULTS: The in vitro exposure of both PBMCs and human islets to recombinant TRAIL significantly upregulated the expression of SOCS1. With respect to STZ-treated animals, mice co-injected with STZ+TRAIL were characterized by 1) lower levels of hyperglycemia, 2) higher levels of body weight and insulinemia, 3) a partial preservation of pancreatic islets with normal morphology, and 4) a lower expression of both systemic (TNF-alpha and OPG) and pancreatic (vascular cell adhesion molecule [VCAM]-1) inflammatory markers. CONCLUSIONS: Overall, these data demonstrate that the administration of recombinant TRAIL ameliorates the severity of STZ-induced type 1 diabetes, and this effect was accompanied by the upregulation of SOCS1 expression.
Keywords: Animals; Cells, Cultured; Diabetes Mellitus, Experimental; Gene Expression; Humans; Islets of Langerhans; Leukocytes, Mononuclear; Mice; Recombinant Proteins; Suppressor of Cytokine Signaling Proteins; TNF-Related Apoptosis-Inducing Ligand

Usefulness of the measurement of azathioprine metabolites in the assessment of non-adherence. - Stocco, Gabriele; Londero, Margherita; Campanozzi, Angelo; Martelossi, Stefano; Marino, Sara; Malusà, Noelia; Bartoli, Fiora; Decorti, Giuliana; Ventura, Alessandro (J Crohns Colitis, 2010)
Azathioprine is a thiopurine immunosuppressive antimetabolite used to chronically treat inflammatory bowel disease and autoimmune hepatitis. Azathioprine treatment is a long-term therapy and therefore it is at risk for non-adherence, which is considered an important determinant of treatment inefficacy. Measurement of 6-thioguanine and 6-methylmercaptopurine nucleotides has been recently suggested as a screener for non-adherence detection. We describe four young patients in which non-adherence to azathioprine therapy was detected only through the measurement of drug metabolite concentrations, and the criterion for non-adherence was undetectable metabolite levels. After the identification of non-adherence, patients and their families were approached and the importance of a correct drug administration was thoroughly enlightened and discussed; this allowed obtaining a full remission in all subjects. Our observations support the use of undetectable metabolite levels as indicators of non-adherence to therapy in azathioprine treated patients. The additional level of medical supervision given by this assay allows getting a better adherence to medical treatment, which results in an improvement in the response to therapy; these benefits may justify the costs associated with the assay.
Keywords: 6-Mercaptopurine; Adolescent; Azathioprine; Child; Child, Preschool; Female; Guanine Nucleotides; Hepatitis, Autoimmune; Humans; Immunosuppressive Agents; Inflammatory Bowel Diseases; Male; Medication Adherence; Thionucleotides; Young Adult

Wired to be social: the ontogeny of human interaction. - Castiello, Umberto; Becchio, Cristina; Zoia, Stefania; Nelini, Cristian; Sartori, Luisa; Blason, Laura; D'Ottavio, Giuseppina; Bulgheroni, Maria; Gallese, Vittorio (PLoS One, 2010)
BACKGROUND: Newborns come into the world wired to socially interact. Is a propensity to socially oriented action already present before birth? Twin pregnancies provide a unique opportunity to investigate the social pre-wiring hypothesis. Although various types of inter-twins contact have been demonstrated starting from the 11(th) week of gestation, no study has so far investigated the critical question whether intra-pair contact is the result of motor planning rather then the accidental outcome of spatial proximity. METHODOLOGY/PRINCIPAL FINDINGS: Kinematic profiles of movements in five pairs of twin foetuses were studied by using four-dimensional ultrasonography during two separate recording sessions carried out at the 14(th) and 18(th) week of gestation. We demonstrate that by the 14th week of gestation twin foetuses do not only display movements directed towards the uterine wall and self-directed movements, but also movements specifically aimed at the co-twin, the proportion of which increases between the 14(th) and 18(th) gestational week. Kinematic analysis revealed that movement duration was longer and deceleration time was prolonged for other-directed movements compared to movements directed towards the uterine wall. Similar kinematic profiles were observed for movements directed towards the co-twin and self-directed movements aimed at the eye-region, i.e. the most delicate region of the body. CONCLUSIONS/SIGNIFICANCE: We conclude that performance of movements towards the co-twin is not accidental: already starting from the 14th week of gestation twin foetuses execute movements specifically aimed at the co-twin.
Keywords: Female; Fetus; Humans; Pregnancy; Social Behavior; Ultrasonography, Prenatal

Comparison between procaine and isocarboxazid metabolism in vitro by a liver microsomal amidase-esterase. - Moroi, K; Sato, T (Biochem Pharmacol, 1975)
Keywords: Amidohydrolases; Animals; Esterases; Hydrogen-Ion Concentration; In Vitro Techniques; Isocarboxazid; Kinetics; Male; Metals; Microsomes, Liver; Phospholipids; Procaine; Proteins; Rats; Subcellular Fractions; Temperature

Delineation of the intimate details of the backbone conformation of pyridine nucleotide coenzymes in aqueous solution. - Bose, K S; Sarma, R H (Biochem Biophys Res Commun, 1975)
Keywords: Fourier Analysis; Magnetic Resonance Spectroscopy; Models, Molecular; Molecular Conformation; NAD; NADP; Structure-Activity Relationship; Temperature

Maturation of the adrenal medulla--IV. Effects of morphine. - Anderson, T R; Slotkin, T A (Biochem Pharmacol, 1975)
Keywords: Adrenal Medulla; Aging; Animals; Animals, Newborn; Body Weight; Catecholamines; Dopamine beta-Hydroxylase; Epinephrine; Female; Humans; In Vitro Techniques; Maternal-Fetal Exchange; Metaraminol; Morphine; Morphine Dependence; Pregnancy; Rats; Tyrosine 3-Monooxygenase

Metal substitutions incarbonic anhydrase: a halide ion probe study. - Smith, R J; Bryant, R G (Biochem Biophys Res Commun, 1975)
Keywords: Animals; Binding Sites; Cadmium; Carbonic Anhydrases; Cattle; Humans; Hydrogen-Ion Concentration; Magnetic Resonance Spectroscopy; Mercury; Protein Binding; Protein Conformation; Zinc